Association analysis of mitochondrial DNA heteroplasmic variants: methods and application. - Sun, Xianbang; Bulekova, Katia; Yang, Jian; Lai, Meng; Pitsillides, Achilleas N; Liu, Xue; Zhang, Yuankai; Guo, Xiuqing; Yong, Qian; Raffield, Laura M; Rotter, Jerome I; Rich, Stephen S; et al. (medRxiv, 2024)
We rigorously assessed a comprehensive association testing framework for heteroplasmy, employing both simulated and real-world data. This framework employed a variant allele fraction (VAF) threshold and harnessed multiple gene-based tests for robust identification and association testing of heteroplasmy. Our simulation studies demonstrated that gene-based tests maintained an appropriate type I error rate at α=0.001. Notably, when 5% or more heteroplasmic variants within a target region were linked to an outcome, burden-extension tests (including the adaptive burden test, variable threshold burden test, and z-score weighting burden test) outperformed the sequence kernel association test (SKAT) and the original burden test. Applying this framework, we conducted association analyses on whole-blood derived heteroplasmy in 17,507 individuals of African and European ancestries (31% of African Ancestry, mean age of 62, with 58% women) with whole genome sequencing data. We performed both cohort- and ancestry-specific association analyses, followed by meta-analysis on both pooled samples and within each ancestry group. Our results suggest that mtDNA-encoded genes/regions are likely to exhibit varying rates in somatic aging, with the notably strong associations observed between heteroplasmy in the and genes (<0.001) and advance aging by the Original Burden test. In contrast, SKAT identified significant associations (<0.001) between diabetes and the aggregated effects of heteroplasmy in several protein-coding genes. Further research is warranted to validate these findings. In summary, our proposed statistical framework represents a valuable tool for facilitating association testing of heteroplasmy with disease traits in large human populations.

Genetic sex validation for sample tracking in next-generation sequencing clinical testing. - Jianhong Hu; Korchina, Viktoriya; Zouk, Hana; Harden, Maegan V; Murdock, David; Macbeth, Alyssa; Harrison, Steven M; Lennon, Niall; Kovar, Christie; Balasubramanian, Adithya; Zhang, Lan; Chandanavelli, Gauthami; et al. (BMC Res Notes, 2024)
OBJECTIVE: Data from DNA genotyping via a 96-SNP panel in a study of 25,015 clinical samples were utilized for quality control and tracking of sample identity in a clinical sequencing network. The study aimed to demonstrate the value of both the precise SNP tracking and the utility of the panel for predicting the sex-by-genotype of the participants, to identify possible sample mix-ups. RESULTS: Precise SNP tracking showed no sample swap errors within the clinical testing laboratories. In contrast, when comparing predicted sex-by-genotype to the provided sex on the test requisition, we identified 110 inconsistencies from 25,015 clinical samples (0.44%), that had occurred during sample collection or accessioning. The genetic sex predictions were confirmed using additional SNP sites in the sequencing data or high-density genotyping arrays. It was determined that discrepancies resulted from clerical errors (49.09%), samples from transgender participants (3.64%) and stem cell or bone marrow transplant patients (7.27%) along with undetermined sample mix-ups (40%) for which sample swaps occurred prior to arrival at genome centers, however the exact cause of the events at the sampling sites resulting in the mix-ups were not able to be determined.
Keywords: Bone Marrow Transplantation; Clinical Laboratory Services; Genotype; High-Throughput Nucleotide Sequencing; Humans; Laboratories

Genome-wide analysis in over 1 million individuals of European ancestry yields improved polygenic risk scores for blood pressure traits. - Keaton, Jacob M; Kamali, Zoha; Xie, Tian; Vaez, Ahmad; Williams, Ariel; Goleva, Slavina B; Ani, Alireza; Evangelou, Evangelos; Hellwege, Jacklyn N; Yengo, Loic; Young, William J; Traylor, Matthew; et al. (Nat Genet, 2024)
Hypertension affects more than one billion people worldwide. Here we identify 113 novel loci, reporting a total of 2,103 independent genetic signals (P < 5 × 10) from the largest single-stage blood pressure (BP) genome-wide association study to date (n = 1,028,980 European individuals). These associations explain more than 60% of single nucleotide polymorphism-based BP heritability. Comparing top versus bottom deciles of polygenic risk scores (PRSs) reveals clinically meaningful differences in BP (16.9 mmHg systolic BP, 95% CI, 15.5-18.2 mmHg, P = 2.22 × 10) and more than a sevenfold higher odds of hypertension risk (odds ratio, 7.33; 95% CI, 5.54-9.70; P = 4.13 × 10) in an independent dataset. Adding PRS into hypertension-prediction models increased the area under the receiver operating characteristic curve (AUROC) from 0.791 (95% CI, 0.781-0.801) to 0.826 (95% CI, 0.817-0.836, ∆AUROC, 0.035, P = 1.98 × 10). We compare the 2,103 loci results in non-European ancestries and show significant PRS associations in a large African-American sample. Secondary analyses implicate 500 genes previously unreported for BP. Our study highlights the role of increasingly large genomic studies for precision health research.

Gut Microbiota and Blood Metabolites Related to Fiber Intake and Type 2 Diabetes. - Wang, Zheng; Peters, Brandilyn A; Yu, Bing; Grove, Megan L; Wang, Tao; Xue, Xiaonan; Thyagarajan, Bharat; Daviglus, Martha L; Eric Boerwinkle; Hu, Gang; Mossavar-Rahmani, Yasmin; Isasi, Carmen R; et al. (Circ Res, 2024)
BACKGROUND: Consistent evidence suggests diabetes-protective effects of dietary fiber intake. However, the underlying mechanisms, particularly the role of gut microbiota and host circulating metabolites, are not fully understood. We aimed to investigate gut microbiota and circulating metabolites associated with dietary fiber intake and their relationships with type 2 diabetes (T2D). METHODS: This study included up to 11 394 participants from the HCHS/SOL (Hispanic Community Health Study/Study of Latinos). Diet was assessed with two 24-hour dietary recalls at baseline. We examined associations of dietary fiber intake with gut microbiome measured by shotgun metagenomics (350 species/85 genera and 1958 enzymes; n=2992 at visit 2), serum metabolome measured by untargeted metabolomics (624 metabolites; n=6198 at baseline), and associations between fiber-related gut bacteria and metabolites (n=804 at visit 2). We examined prospective associations of serum microbial-associated metabolites (n=3579 at baseline) with incident T2D over 6 years. RESULTS: We identified multiple bacterial genera, species, and related enzymes associated with fiber intake. Several bacteria (eg, , ) and enzymes involved in fiber degradation (eg, xylanase EC3.2.1.156) were positively associated with fiber intake, inversely associated with prevalent T2D, and favorably associated with T2D-related metabolic traits. We identified 159 metabolites associated with fiber intake, 47 of which were associated with incident T2D. We identified 18 of these 47 metabolites associated with the identified fiber-related bacteria, including several microbial metabolites (eg, indolepropionate and 3-phenylpropionate) inversely associated with the risk of T2D. Both and were associated with these favorable metabolites. The associations of fiber-related bacteria, especially and , with T2D were attenuated after further adjustment for these microbial metabolites. CONCLUSIONS: Among United States Hispanics/Latinos, dietary fiber intake was associated with favorable profiles of gut microbiota and circulating metabolites for T2D. These findings advance our understanding of the role of gut microbiota and microbial metabolites in the relationship between diet and T2D.
Keywords: Bacteria; Diabetes Mellitus, Type 2; Diet; Dietary Fiber; Gastrointestinal Microbiome; Humans

Multi-omics and pathway analyses of genome-wide associations implicate regulation and immunity in verbal declarative memory performance. - Mei, Hao; Simino, Jeannette; Li, Lianna; Jiang, Fan; Bis, Joshua C; Davies, Gail; Hill, W David; Xia, Charley; Gudnason, Vilmundur; Yang, Qiong; Lahti, Jari; Smith, Jennifer A; et al. (Alzheimers Res Ther, 2024)
BACKGROUND: Uncovering the functional relevance underlying verbal declarative memory (VDM) genome-wide association study (GWAS) results may facilitate the development of interventions to reduce age-related memory decline and dementia. METHODS: We performed multi-omics and pathway enrichment analyses of paragraph (PAR-dr) and word list (WL-dr) delayed recall GWAS from 29,076 older non-demented individuals of European descent. We assessed the relationship between single-variant associations and expression quantitative trait loci (eQTLs) in 44 tissues and methylation quantitative trait loci (meQTLs) in the hippocampus. We determined the relationship between gene associations and transcript levels in 53 tissues, annotation as immune genes, and regulation by transcription factors (TFs) and microRNAs. To identify significant pathways, gene set enrichment was tested in each cohort and meta-analyzed across cohorts. Analyses of differential expression in brain tissues were conducted for pathway component genes. RESULTS: The single-variant associations of VDM showed significant linkage disequilibrium (LD) with eQTLs across all tissues and meQTLs within the hippocampus. Stronger WL-dr gene associations correlated with reduced expression in four brain tissues, including the hippocampus. More robust PAR-dr and/or WL-dr gene associations were intricately linked with immunity and were influenced by 31 TFs and 2 microRNAs. Six pathways, including type I diabetes, exhibited significant associations with both PAR-dr and WL-dr. These pathways included fifteen MHC genes intricately linked to VDM performance, showing diverse expression patterns based on cognitive status in brain tissues. CONCLUSIONS: VDM genetic associations influence expression regulation via eQTLs and meQTLs. The involvement of TFs, microRNAs, MHC genes, and immune-related pathways contributes to VDM performance in older individuals.
Keywords: Aged; Cognition; Genome-Wide Association Study; Humans; Memory; MicroRNAs; Multiomics; Polymorphism, Single Nucleotide

NODAL variants are associated with a continuum of laterality defects from simple D-transposition of the great arteries to heterotaxy. - Dardas, Zain; Fatih, Jawid M; Jolly, Angad; Dawood, Moez; Du, Haowei; Grochowski, Christopher M; Jones, Edward G; Jhangiani, Shalini N; Wehrens, Xander H T; Liu, Pengfei; Bi, Weimin; Eric Boerwinkle; et al. (Genome Med, 2024)
BACKGROUND: NODAL signaling plays a critical role in embryonic patterning and heart development in vertebrates. Genetic variants resulting in perturbations of the TGF-β/NODAL signaling pathway have reproducibly been shown to cause laterality defects in humans. To further explore this association and improve genetic diagnosis, the study aims to identify and characterize a broader range of NODAL variants in a large number of individuals with laterality defects. METHODS: We re-analyzed a cohort of 321 proband-only exomes of individuals with clinically diagnosed laterality congenital heart disease (CHD) using family-based, rare variant genomic analyses. To this cohort we added 12 affected subjects with known NODAL variants and CHD from institutional research and clinical cohorts to investigate an allelic series. For those with candidate contributory variants, variant allele confirmation and segregation analysis were studied by Sanger sequencing in available family members. Array comparative genomic hybridization and droplet digital PCR were utilized for copy number variants (CNV) validation and characterization. We performed Human Phenotype Ontology (HPO)-based quantitative phenotypic analyses to dissect allele-specific phenotypic differences. RESULTS: Missense, nonsense, splice site, indels, and/or structural variants of NODAL were identified as potential causes of heterotaxy and other laterality defects in 33 CHD cases. We describe a recurrent complex indel variant for which the nucleic acid secondary structure predictions implicate secondary structure mutagenesis as a possible mechanism for formation. We identified two CNV deletion alleles spanning NODAL in two unrelated CHD cases. Furthermore, 17 CHD individuals were found (16/17 with known Hispanic ancestry) to have the c.778G > A:p.G260R NODAL missense variant which we propose reclassification from variant of uncertain significance (VUS) to likely pathogenic. Quantitative HPO-based analyses of the observed clinical phenotype for all cases with p.G260R variation, including heterozygous, homozygous, and compound heterozygous cases, reveal clustering of individuals with biallelic variation. This finding provides evidence for a genotypic-phenotypic correlation and an allele-specific gene dosage model. CONCLUSION: Our data further support a role for rare deleterious variants in NODAL as a cause for sporadic human laterality defects, expand the repertoire of observed anatomical complexity of potential cardiovascular anomalies, and implicate an allele specific gene dosage model.
Keywords: Animals; Arteries; Comparative Genomic Hybridization; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Phenotype; Transposition of Great Vessels

A polygenic risk score of atrial fibrillation improves prediction of lifetime risk for heart failure. - Alkis, Taryn; Luo, Xi; Wall, Katherine; Brody, Jennifer; Bartz, Traci; Chang, Patricia P; Norby, Faye L; Hoogeveen, Ron C; Morrison, Alanna C; Ballantyne, Christie M; Coresh, Josef; Eric Boerwinkle; et al. (ESC Heart Fail, 2024)
AIMS: Heart failure (HF) has shared genetic architecture with its risk factors: atrial fibrillation (AF), body mass index (BMI), coronary heart disease (CHD), systolic blood pressure (SBP), and type 2 diabetes (T2D). We aim to assess the association and risk prediction performance of risk-factor polygenic risk scores (PRSs) for incident HF and its subtypes in bi-racial populations. METHODS AND RESULTS: Five PRSs were constructed for AF, BMI, CHD, SBP, and T2D in White participants of the Atherosclerosis Risk in Communities (ARIC) study. The associations between PRSs and incident HF and its subtypes were assessed using Cox models, and the risk prediction performance of PRSs was assessed using C statistics. Replication was performed in the ARIC study Black and Cardiovascular Health Study (CHS) White participants. In 8624 ARIC study Whites, 1922 (31% cumulative incidence) HF cases developed over 30 years of follow-up. PRSs of AF, BMI, and CHD were associated with incident HF (P < 0.001), where PRS showed the strongest association [hazard ratio (HR): 1.47, 95% confidence interval (CI): 1.41-1.53]. Only the addition of PRS to the ARIC study HF risk equation improved C statistics for 10 year risk prediction from 0.812 to 0.829 (∆C: 0.017, 95% CI: 0.009-0.026). The PRS was associated with both incident HF with reduced ejection fraction (HR: 1.43, 95% CI: 1.27-1.60) and incident HF with preserved ejection fraction (HR: 1.46, 95% CI: 1.33-1.62). The associations between PRS and incident HF and its subtypes, as well as the improved risk prediction, were replicated in the ARIC study Blacks and the CHS Whites (P < 0.050). Protein analyses revealed that N-terminal pro-brain natriuretic peptide and other 98 proteins were associated with PRS. CONCLUSIONS: The PRS was associated with incident HF and its subtypes and had significant incremental value over an established HF risk prediction equation.
Keywords: Atherosclerosis; Atrial Fibrillation; Coronary Disease; Diabetes Mellitus, Type 2; Genetic Risk Score; Heart Failure; Humans; Risk Factors

X-linked genetic associations in sporadic thoracic aortic dissection. - Musfee, Fadi I; Jun, Goo; Mitchell, Laura E; Chen, Han; Guo, Dongchuan; Prakash, Siddharth K; Adkar, Shaunak Sanjay; Grove, Megan L; Choi, Ryan Bohyun; Klarin, Derek; Eric Boerwinkle; Milewicz, Dianna M (Am J Med Genet A, 2024)
The male predominance in sporadic thoracic aortic aneurysm and dissection (TAD) suggests that the X chromosome contributes to TAD, but this has not been tested. We investigated whether X-linked variation-common (minor allele frequency [MAF] ≥0.01) and rare (MAF <0.01)-was associated with sporadic TAD in three cohorts of European descent (Discovery: 364 cases, 874 controls; Replication: 516 cases, 440,131 controls, and ARIC [Atherosclerosis Risk in Communities study]: 753 cases, 2247 controls). For analysis of common variants, we applied a sex-stratified logistic regression model followed by a meta-analysis of sex-specific odds ratios. Furthermore, we conducted a meta-analysis of overlapping common variants between the Discovery and Replication cohorts. For analysis of rare variants, we used a sex-stratified optimized sequence kernel association test model. Common variants results showed no statistically significant findings in the Discovery cohort. An intergenic common variant near SPANXN1 was statistically significant in the Replication cohort (p = 1.81 × 10). The highest signal from the meta-analysis of the Discovery and Replication cohorts was a ZNF182 intronic common variant (p = 3.5 × 10). In rare variants results, RTL9 reached statistical significance (p = 5.15 × 10). Although most of our results were statistically insignificant, our analysis is the most comprehensive X-chromosome association analysis of sporadic TAD to date.

Aberrant activation of TCL1A promotes stem cell expansion in clonal haematopoiesis. - Weinstock, Joshua S; Gopakumar, Jayakrishnan; Burugula, Bala Bharathi; Uddin, Md Mesbah; Jahn, Nikolaus; Belk, Julia A; Bouzid, Hind; Daniel, Bence; Miao, Zhuang; Ly, Nghi; Mack, Taralynn M; Luna, Sofia E; et al. (Nature, 2023)
Mutations in a diverse set of driver genes increase the fitness of haematopoietic stem cells (HSCs), leading to clonal haematopoiesis. These lesions are precursors for blood cancers, but the basis of their fitness advantage remains largely unknown, partly owing to a paucity of large cohorts in which the clonal expansion rate has been assessed by longitudinal sampling. Here, to circumvent this limitation, we developed a method to infer the expansion rate from data from a single time point. We applied this method to 5,071 people with clonal haematopoiesis. A genome-wide association study revealed that a common inherited polymorphism in the TCL1A promoter was associated with a slower expansion rate in clonal haematopoiesis overall, but the effect varied by driver gene. Those carrying this protective allele exhibited markedly reduced growth rates or prevalence of clones with driver mutations in TET2, ASXL1, SF3B1 and SRSF2, but this effect was not seen in clones with driver mutations in DNMT3A. TCL1A was not expressed in normal or DNMT3A-mutated HSCs, but the introduction of mutations in TET2 or ASXL1 led to the expression of TCL1A protein and the expansion of HSCs in vitro. The protective allele restricted TCL1A expression and expansion of mutant HSCs, as did experimental knockdown of TCL1A expression. Forced expression of TCL1A promoted the expansion of human HSCs in vitro and mouse HSCs in vivo. Our results indicate that the fitness advantage of several commonly mutated driver genes in clonal haematopoiesis may be mediated by TCL1A activation.
Keywords: Alleles; Animals; Clonal Hematopoiesis; Genome-Wide Association Study; Hematopoiesis; Hematopoietic Stem Cells; Humans; Mice; Mutation; Promoter Regions, Genetic

Association Between Whole Blood-Derived Mitochondrial DNA Copy Number, Low-Density Lipoprotein Cholesterol, and Cardiovascular Disease Risk. - Liu, Xue; Sun, Xianbang; Zhang, Yuankai; Jiang, Wenqing; Lai, Meng; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Haessler, Jeffrey; Zheng, Yinan; et al. (J Am Heart Assoc, 2023)
Background The relationship between mitochondrial DNA copy number (mtDNA CN) and cardiovascular disease remains elusive. Methods and Results We performed cross-sectional and prospective association analyses of blood-derived mtDNA CN and cardiovascular disease outcomes in 27 316 participants in 8 cohorts of multiple racial and ethnic groups with whole-genome sequencing. We also performed Mendelian randomization to explore causal relationships of mtDNA CN with coronary heart disease (CHD) and cardiometabolic risk factors (obesity, diabetes, hypertension, and hyperlipidemia). <0.01 was used for significance. We validated most of the previously reported associations between mtDNA CN and cardiovascular disease outcomes. For example, 1-SD unit lower level of mtDNA CN was associated with 1.08 (95% CI, 1.04-1.12; <0.001) times the hazard for developing incident CHD, adjusting for covariates. Mendelian randomization analyses showed no causal effect from a lower level of mtDNA CN to a higher CHD risk (β=0.091; =0.11) or in the reverse direction (β=-0.012; =0.076). Additional bidirectional Mendelian randomization analyses revealed that low-density lipoprotein cholesterol had a causal effect on mtDNA CN (β=-0.084; <0.001), but the reverse direction was not significant (=0.059). No causal associations were observed between mtDNA CN and obesity, diabetes, and hypertension, in either direction. Multivariable Mendelian randomization analyses showed no causal effect of CHD on mtDNA CN, controlling for low-density lipoprotein cholesterol level (=0.52), whereas there was a strong direct causal effect of higher low-density lipoprotein cholesterol on lower mtDNA CN, adjusting for CHD status (β=-0.092; <0.001). Conclusions Our findings indicate that high low-density lipoprotein cholesterol may underlie the complex relationships between mtDNA CN and vascular atherosclerosis.
Keywords: Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Coronary Disease; Cross-Sectional Studies; Diabetes Mellitus; DNA Copy Number Variations; DNA, Mitochondrial; Humans; Hypertension; Obesity; Risk Factors

Association of Common and Rare Variants with Alzheimer's Disease in over 13,000 Diverse Individuals with Whole-Genome Sequencing from the Alzheimer's Disease Sequencing Project. - Lee, Wan-Ping; Choi, Seung Hoan; Shea, Margaret G; Cheng, Po-Liang; Dombroski, Beth A; Pitsillides, Achilleas N; Heard-Costa, Nancy L; Wang, Hui; Bulekova, Katia; Kuzma, Amanda B; Leung, Yuk Yee; Farrell, John J; et al. (medRxiv, 2023)
Alzheimer's Disease (AD) is a common disorder of the elderly that is both highly heritable and genetically heterogeneous. Here, we investigated the association between AD and both common variants and aggregates of rare coding and noncoding variants in 13,371 individuals of diverse ancestry with whole genome sequence (WGS) data. Pooled-population analyses identified genetic variants in or near , , and significantly associated with AD (p < 5×10). Population-specific analyses identified a haplotype on chromosome 14 including associated with AD in Hispanics, further supported by aggregate testing of rare coding and noncoding variants in this region. Finally, we observed suggestive associations (p < 5×10) of aggregates of rare coding rare variants in ABCA7 among non-Hispanic Whites (p=5.4×10), and rare noncoding variants in the promoter of distinct of in pooled-population analyses (p=7.2×10). Complementary pooled-population and population-specific analyses offered unique insights into the genetic architecture of AD.

Association of Mitochondrial DNA Copy Number With Brain MRI Markers and Cognitive Function: A Meta-analysis of Community-Based Cohorts. - Zhang, Yuankai; Liu, Xue; Wiggins, Kerri L; Kurniansyah, Nuzulul; Guo, Xiuqing; Rodrigue, Amanda L; Zhao, Wei; Yanek, Lisa R; Ratliff, Scott M; Pitsillides, Achilleas; Aguirre Patiño, Juan Sebastian; Sofer, Tamar; et al. (Neurology, 2023)
BACKGROUND AND OBJECTIVES: Previous studies suggest that lower mitochondrial DNA (mtDNA) copy number (CN) is associated with neurodegenerative diseases. However, whether mtDNA CN in whole blood is related to endophenotypes of Alzheimer disease (AD) and AD-related dementia (AD/ADRD) needs further investigation. We assessed the association of mtDNA CN with cognitive function and MRI measures in community-based samples of middle-aged to older adults. METHODS: We included dementia-free participants from 9 diverse community-based cohorts with whole-genome sequencing in the Trans-Omics for Precision Medicine (TOPMed) program. Circulating mtDNA CN was estimated as twice the ratio of the average coverage of mtDNA to nuclear DNA. Brain MRI markers included total brain, hippocampal, and white matter hyperintensity volumes. General cognitive function was derived from distinct cognitive domains. We performed cohort-specific association analyses of mtDNA CN with AD/ADRD endophenotypes assessed within ±5 years (i.e., cross-sectional analyses) or 5-20 years after blood draw (i.e., prospective analyses) adjusting for potential confounders. We further explored associations stratified by sex and age (<60 vs ≥60 years). Fixed-effects or sample size-weighted meta-analyses were performed to combine results. Finally, we performed mendelian randomization (MR) analyses to assess causality. RESULTS: We included up to 19,152 participants (mean age 59 years, 57% women). Higher mtDNA CN was cross-sectionally associated with better general cognitive function (β = 0.04; 95% CI 0.02-0.06) independent of age, sex, batch effects, race/ethnicity, time between blood draw and cognitive evaluation, cohort-specific variables, and education. Additional adjustment for blood cell counts or cardiometabolic traits led to slightly attenuated results. We observed similar significant associations with cognition in prospective analyses, although of reduced magnitude. We found no significant associations between mtDNA CN and brain MRI measures in meta-analyses. MR analyses did not reveal a causal relation between mtDNA CN in blood and cognition. DISCUSSION: Higher mtDNA CN in blood is associated with better current and future general cognitive function in large and diverse communities across the United States. Although MR analyses did not support a causal role, additional research is needed to assess causality. Circulating mtDNA CN could serve nevertheless as a biomarker of current and future cognitive function in the community.
Keywords: Aged; Alzheimer Disease; Brain; Cognition; Cross-Sectional Studies; DNA Copy Number Variations; DNA, Mitochondrial; Female; Humans; Magnetic Resonance Imaging; Male; Middle Aged; Prospective Studies

Association of Rare Protein-Truncating DNA Variants in APOB or PCSK9 With Low-density Lipoprotein Cholesterol Level and Risk of Coronary Heart Disease. - Dron, Jacqueline S; Patel, Aniruddh P; Zhang, Yiyi; Jurgens, Sean J; Maamari, Dimitri J; Wang, Minxian; Eric Boerwinkle; Morrison, Alanna C; de Vries, Paul S; Fornage, Myriam; Hou, Lifang; Lloyd-Jones, Donald M; et al. (JAMA Cardiol, 2023)
IMPORTANCE: Protein-truncating variants (PTVs) in apolipoprotein B (APOB) and proprotein convertase subtilisin/kexin type 9 (PCSK9) are associated with significantly lower low-density lipoprotein (LDL) cholesterol concentrations. The association of these PTVs with coronary heart disease (CHD) warrants further characterization in large, multiracial prospective cohort studies. OBJECTIVE: To evaluate the association of PTVs in APOB and PCSK9 with LDL cholesterol concentrations and CHD risk. DESIGN, SETTING, AND PARTICIPANTS: This studied included participants from 5 National Heart, Lung, and Blood Institute (NHLBI) studies and the UK Biobank. NHLBI study participants aged 5 to 84 years were recruited between 1971 and 2002 across the US and underwent whole-genome sequencing. UK Biobank participants aged 40 to 69 years were recruited between 2006 and 2010 in the UK and underwent whole-exome sequencing. Data were analyzed from June 2021 to October 2022. EXPOSURES: PTVs in APOB and PCSK9. MAIN OUTCOMES AND MEASURES: Estimated untreated LDL cholesterol levels and CHD. RESULTS: Among 19 073 NHLBI participants (10 598 [55.6%] female; mean [SD] age, 52 [17] years), 139 (0.7%) carried an APOB or PCSK9 PTV, which was associated with 49 mg/dL (95% CI, 43-56) lower estimated untreated LDL cholesterol level. Over a median (IQR) follow-up of 21.5 (13.9-29.4) years, incident CHD was observed in 12 of 139 carriers (8.6%) vs 3029 of 18 934 noncarriers (16.0%), corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.28-0.89; P = .02). Among 190 464 UK Biobank participants (104 831 [55.0%] female; mean [SD] age, 57 [8] years), 662 (0.4%) carried a PTV, which was associated with 45 mg/dL (95% CI, 42-47) lower estimated untreated LDL cholesterol level. Estimated CHD risk by age 75 years was 3.7% (95% CI, 2.0-5.3) in carriers vs 7.0% (95% CI, 6.9-7.2) in noncarriers, corresponding to an adjusted hazard ratio of 0.51 (95% CI, 0.32-0.81; P = .004). CONCLUSIONS AND RELEVANCE: Among 209 537 individuals in this study, 0.4% carried an APOB or PCSK9 PTV that was associated with less exposure to LDL cholesterol and a 49% lower risk of CHD.
Keywords: Adult; Aged; Apolipoproteins B; Cholesterol, LDL; Coronary Disease; DNA; Female; Humans; Male; Middle Aged; Proprotein Convertase 9; Prospective Studies

Author Correction: Clonal haematopoiesis and risk of chronic liver disease. - Wong, Waihay J; Emdin, Connor; Bick, Alexander G; Zekavat, Seyedeh M; Niroula, Abhishek; Pirruccello, James P; Dichtel, Laura; Griffin, Gabriel; Uddin, Md Mesbah; Gibson, Christopher J; Kovalcik, Veronica; Lin, Amy E; et al. (Nature, 2023)

Author Correction: Common variants in Alzheimer's disease and risk stratification by polygenic risk scores. - de Rojas, Itziar; Moreno-Grau, Sonia; Tesi, Niccolo; Grenier-Boley, Benjamin; Andrade, Victor; Jansen, Iris E; Pedersen, Nancy L; Stringa, Najada; Zettergren, Anna; Hernández, Isabel; Montrreal, Laura; Antúnez, Carmen; et al. (Nat Commun, 2023)

Clonal haematopoiesis and risk of chronic liver disease. - Wong, Waihay J; Emdin, Connor; Bick, Alexander G; Zekavat, Seyedeh M; Niroula, Abhishek; Pirruccello, James P; Dichtel, Laura; Griffin, Gabriel; Uddin, Md Mesbah; Gibson, Christopher J; Kovalcik, Veronica; Lin, Amy E; et al. (Nature, 2023)
Chronic liver disease is a major public health burden worldwide. Although different aetiologies and mechanisms of liver injury exist, progression of chronic liver disease follows a common pathway of liver inflammation, injury and fibrosis. Here we examined the association between clonal haematopoiesis of indeterminate potential (CHIP) and chronic liver disease in 214,563 individuals from 4 independent cohorts with whole-exome sequencing data (Framingham Heart Study, Atherosclerosis Risk in Communities Study, UK Biobank and Mass General Brigham Biobank). CHIP was associated with an increased risk of prevalent and incident chronic liver disease (odds ratio = 2.01, 95% confidence interval (95% CI) [1.46, 2.79]; P < 0.001). Individuals with CHIP were more likely to demonstrate liver inflammation and fibrosis detectable by magnetic resonance imaging compared to those without CHIP (odds ratio = 1.74, 95% CI [1.16, 2.60]; P = 0.007). To assess potential causality, Mendelian randomization analyses showed that genetic predisposition to CHIP was associated with a greater risk of chronic liver disease (odds ratio = 2.37, 95% CI [1.57, 3.6]; P < 0.001). In a dietary model of non-alcoholic steatohepatitis, mice transplanted with Tet2-deficient haematopoietic cells demonstrated more severe liver inflammation and fibrosis. These effects were mediated by the NLRP3 inflammasome and increased levels of expression of downstream inflammatory cytokines in Tet2-deficient macrophages. In summary, clonal haematopoiesis is associated with an elevated risk of liver inflammation and chronic liver disease progression through an aberrant inflammatory response.
Keywords: Animals; Clonal Hematopoiesis; Disease Progression; Disease Susceptibility; Hepatitis; Inflammation; Liver Cirrhosis; Mice; Non-alcoholic Fatty Liver Disease; Odds Ratio

Epigenetic and integrative cross-omics analyses of cerebral white matter hyperintensities on MRI. - Yang, Yunju; Knol, Maria J; Wang, Ruiqi; Mishra, Aniket; Liu, Dan; Luciano, Michelle; Teumer, Alexander; Armstrong, Nicola; Bis, Joshua C; Jhun, Min A; Li, Shuo; Adams, Hieab H H; et al. (Brain, 2023)
Cerebral white matter hyperintensities on MRI are markers of cerebral small vessel disease, a major risk factor for dementia and stroke. Despite the successful identification of multiple genetic variants associated with this highly heritable condition, its genetic architecture remains incompletely understood. More specifically, the role of DNA methylation has received little attention. We investigated the association between white matter hyperintensity burden and DNA methylation in blood at ∼450 000 cytosine-phosphate-guanine (CpG) sites in 9732 middle-aged to older adults from 14 community-based studies. Single CpG and region-based association analyses were carried out. Functional annotation and integrative cross-omics analyses were performed to identify novel genes underlying the relationship between DNA methylation and white matter hyperintensities. We identified 12 single CpG and 46 region-based DNA methylation associations with white matter hyperintensity burden. Our top discovery single CpG, cg24202936 (P = 7.6 × 10-8), was associated with F2 expression in blood (P = 6.4 × 10-5) and co-localized with FOLH1 expression in brain (posterior probability = 0.75). Our top differentially methylated regions were in PRMT1 and in CCDC144NL-AS1, which were also represented in single CpG associations (cg17417856 and cg06809326, respectively). Through Mendelian randomization analyses cg06809326 was putatively associated with white matter hyperintensity burden (P = 0.03) and expression of CCDC144NL-AS1 possibly mediated this association. Differentially methylated region analysis, joint epigenetic association analysis and multi-omics co-localization analysis consistently identified a role of DNA methylation near SH3PXD2A, a locus previously identified in genome-wide association studies of white matter hyperintensities. Gene set enrichment analyses revealed functions of the identified DNA methylation loci in the blood-brain barrier and in the immune response. Integrative cross-omics analysis identified 19 key regulatory genes in two networks related to extracellular matrix organization, and lipid and lipoprotein metabolism. A drug-repositioning analysis indicated antihyperlipidaemic agents, more specifically peroxisome proliferator-activated receptor-alpha, as possible target drugs for white matter hyperintensities. Our epigenome-wide association study and integrative cross-omics analyses implicate novel genes influencing white matter hyperintensity burden, which converged on pathways related to the immune response and to a compromised blood-brain barrier possibly due to disrupted cell-cell and cell-extracellular matrix interactions. The results also suggest that antihyperlipidaemic therapy may contribute to lowering risk for white matter hyperintensities possibly through protection against blood-brain barrier disruption.
Keywords: Aged; Brain; DNA Methylation; Epigenesis, Genetic; Genome-Wide Association Study; Humans; Magnetic Resonance Imaging; Middle Aged; Protein-Arginine N-Methyltransferases; Repressor Proteins; White Matter

Epigenome-wide association study using peripheral blood leukocytes identifies genomic regions associated with periodontal disease and edentulism in the Atherosclerosis Risk in Communities study. - Zhao, Naisi; Teles, Flavia; Lu, Jiayun; Koestler, Devin C; Beck, James; Eric Boerwinkle; Bressler, Jan; Kelsey, Karl T; Platz, Elizabeth A; Michaud, Dominique S (J Clin Periodontol, 2023)
AIM: To investigate individual susceptibility to periodontitis by conducting an epigenome-wide association study using peripheral blood. MATERIALS AND METHODS: We included 1077 African American and 457 European American participants of the Atherosclerosis Risk in Communities (ARIC) study who had completed a dental examination or reported being edentulous at Visit 4 and had available data on DNA methylation from Visit 2 or 3. DNA methylation levels were compared by periodontal disease severity and edentulism through discovery analyses and subsequent testing of individual CpGs. RESULTS: Our discovery analysis replicated findings from a previous study reporting a region in gene ZFP57 (6p22.1) that was significantly hypomethylated in severe periodontal disease compared with no/mild periodontal disease in European American participants. Higher methylation levels in a separate region in an unknown gene (located in Chr10: 743,992-744,958) was associated with significantly higher odds of edentulism compared with no/mild periodontal disease in African American participants. In subsequent CpG testing, four CpGs in a region previously associated with periodontitis located within HOXA4 were significantly hypermethylated in severe periodontal disease compared with no/mild periodontal disease in African American participants (odds ratio per 1 SD increase in methylation level: cg11015251: 1.28 (1.02, 1.61); cg14359292: 1.24 (1.01, 1.54); cg07317062: 1.30 (1.05, 1.61); cg08657492: 1.25 (1.01, 1.55)). CONCLUSIONS: Our study highlights epigenetic variations in ZPF57 and HOXA4 that are significantly and reproducibly associated with periodontitis. Future studies should evaluate gene regulatory mechanisms in the candidate regions of these loci.
Keywords: Atherosclerosis; Epigenome; Genome-Wide Association Study; Genomics; Humans; Leukocytes; Periodontal Diseases; Periodontitis

Gene-educational attainment interactions in a multi-population genome-wide meta-analysis identify novel lipid loci. - de Las Fuentes, Lisa; Schwander, Karen L; Brown, Michael R; Bentley, Amy R; Winkler, Thomas W; Sung, Yun Ju; Munroe, Patricia B; Miller, Clint L; Aschard, Hugo; Aslibekyan, Stella; Bartz, Traci M; Bielak, Lawrence F; et al. (Front Genet, 2023)
Educational attainment, widely used in epidemiologic studies as a surrogate for socioeconomic status, is a predictor of cardiovascular health outcomes. A two-stage genome-wide meta-analysis of low-density lipoprotein cholesterol (LDL), high-density lipoprotein cholesterol (HDL), and triglyceride (TG) levels was performed while accounting for gene-educational attainment interactions in up to 226,315 individuals from five population groups. We considered two educational attainment variables: "Some College" (yes/no, for any education beyond high school) and "Graduated College" (yes/no, for completing a 4-year college degree). Genome-wide significant ( < 5 × 10) and suggestive ( < 1 × 10) variants were identified in Stage 1 (in up to 108,784 individuals) through genome-wide analysis, and those variants were followed up in Stage 2 studies (in up to 117,531 individuals). In combined analysis of Stages 1 and 2, we identified 18 novel lipid loci (nine for LDL, seven for HDL, and two for TG) by two degree-of-freedom (2 DF) joint tests of main and interaction effects. Four loci showed significant interaction with educational attainment. Two loci were significant only in cross-population analyses. Several loci include genes with known or suggested roles in adipose (), brain (), and liver () biology, highlighting the potential importance of brain-adipose-liver communication in the regulation of lipid metabolism. An investigation of the potential druggability of genes in identified loci resulted in five gene targets shown to interact with drugs approved by the Food and Drug Administration, including genes with roles in adipose and brain tissue. Genome-wide interaction analysis of educational attainment identified novel lipid loci not previously detected by analyses limited to main genetic effects.

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Eric Boerwinkle; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; Hersh, Craig P; et al. (Genetics, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-sequencing data in GTEx V8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased whole genome sequencing data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.
Keywords: Alternative Splicing; Exons; Genotype; Penetrance; RNA Splice Sites; RNA Splicing; RNA, Messenger

Genetic control of mRNA splicing as a potential mechanism for incomplete penetrance of rare coding variants. - Einson, Jonah; Glinos, Dafni; Eric Boerwinkle; Castaldi, Peter; Darbar, Dawood; de Andrade, Mariza; Ellinor, Patrick; Fornage, Myriam; Gabriel, Stacey; Germer, Soren; Richard A Gibbs; Hersh, Craig P; et al. (bioRxiv, 2023)
Exonic variants present some of the strongest links between genotype and phenotype. However, these variants can have significant inter-individual pathogenicity differences, known as variable penetrance. In this study, we propose a model where genetically controlled mRNA splicing modulates the pathogenicity of exonic variants. By first cataloging exonic inclusion from RNA-seq data in GTEx v8, we find that pathogenic alleles are depleted on highly included exons. Using a large-scale phased WGS data from the TOPMed consortium, we observe that this effect may be driven by common splice-regulatory genetic variants, and that natural selection acts on haplotype configurations that reduce the transcript inclusion of putatively pathogenic variants, especially when limiting to haploinsufficient genes. Finally, we test if this effect may be relevant for autism risk using families from the Simons Simplex Collection, but find that splicing of pathogenic alleles has a penetrance reducing effect here as well. Overall, our results indicate that common splice-regulatory variants may play a role in reducing the damaging effects of rare exonic variants.

The genetic determinants of recurrent somatic mutations in 43,693 blood genomes. - Weinstock, Joshua S; Laurie, Cecelia A; Broome, Jai G; Taylor, Kent D; Guo, Xiuqing; Shuldiner, Alan R; O'Connell, Jeffrey R; Lewis, Joshua P; Eric Boerwinkle; Barnes, Kathleen C; Chami, Nathalie; Kenny, Eimear E; et al. (Sci Adv, 2023)
Nononcogenic somatic mutations are thought to be uncommon and inconsequential. To test this, we analyzed 43,693 National Heart, Lung and Blood Institute Trans-Omics for Precision Medicine blood whole genomes from 37 cohorts and identified 7131 non-missense somatic mutations that are recurrently mutated in at least 50 individuals. These recurrent non-missense somatic mutations (RNMSMs) are not clearly explained by other clonal phenomena such as clonal hematopoiesis. RNMSM prevalence increased with age, with an average 50-year-old having 27 RNMSMs. Inherited germline variation associated with RNMSM acquisition. These variants were found in genes involved in adaptive immune function, proinflammatory cytokine production, and lymphoid lineage commitment. In addition, the presence of eight specific RNMSMs associated with blood cell traits at effect sizes comparable to Mendelian genetic mutations. Overall, we found that somatic mutations in blood are an unexpectedly common phenomenon with ancestry-specific determinants and human health consequences.
Keywords: Germ-Line Mutation; Hematopoiesis; Humans; Middle Aged; Mutation; Mutation, Missense; Phenotype

Genetic loci of beta-aminoisobutyric acid are associated with aging-related mild cognitive impairment. - Granot-Hershkovitz, Einat; Spitzer, Brian; Yang, Yunju; Tarraf, Wassim; Yu, Bing; Eric Boerwinkle; Fornage, Myriam; Mosley, Thomas H; DeCarli, Charles; Kristal, Bruce S; Gonzalez, Hector M; Sofer, Tamar (Transl Psychiatry, 2023)
We studied the genetic associations of a previously developed Metabolomic Risk Score (MRS) for Mild Cognitive Impairment (MCI) and beta-aminoisobutyric acid metabolite (BAIBA)-the metabolite highlighted by results from a genome-wide association study (GWAS) of the MCI-MRS, and assessed their association with MCI in datasets of diverse race/ethnicities. We first performed a GWAS for the MCI-MRS and BAIBA, in Hispanic/Latino adults (n = 3890) from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). We identified ten independent genome-wide significant (p value <5 × 10) variants associated with MCI-MRS or BAIBA. Variants associated with the MCI-MRS are located in the Alanine-Glyoxylate Aminotransferase 2 (AGXT2 gene), which is known to be associated with BAIBA metabolism. Variants associated with BAIBA are located in the AGXT2 gene and in the SLC6A13 gene. Next, we tested the variants' association with MCI in independent datasets of n = 3178 HCHS/SOL older individuals, n = 3775 European Americans, and n = 1032 African Americans from the Atherosclerosis Risk In Communities (ARIC) study. Variants were considered associated with MCI if their p value <0.05 in the meta-analysis of the three datasets and their direction of association was consistent with expectation. Rs16899972 and rs37369 from the AGXT2 region were associated with MCI. Mediation analysis supported the mediation effect of BAIBA between the two genetic variants and MCI (p value = 0.004 for causal mediated effect). In summary, genetic variants in the AGXT2 region are associated with MCI in Hispanic/Latino, African, and European American populations in the USA, and their effect is likely mediated by changes in BAIBA levels.
Keywords: Aging; Genetic Loci; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide

Genetic Sex Validation for Sample Tracking in Clinical Testing. - Jianhong Hu; Korchina, Viktoriya; Zouk, Hana; Harden, Maegan V; Murdock, David; Macbeth, Alyssa; Harrison, Steven M; Lennon, Niall; Kovar, Christie; Balasubramanian, Adithya; Zhang, Lan; Chandanavelli, Gauthami; et al. (Res Sq, 2023)
OBJECTIVE: Data from DNA genotyping via a 96-SNP panel in a study of 25,015 clinical samples were utilized for quality control and tracking of sample identity in a clinical sequencing network. The study aimed to demonstrate the value of both the precise SNP tracking and the utility of the panel for predicting the sex-by-genotype of the participants, to identify possible sample mix-ups. RESULTS: Precise SNP tracking showed no sample swap errors within the clinical testing laboratories. In contrast, when comparing predicted sex-by-genotype to the provided sex on the test requisition, we identified 110 inconsistencies from 25,015 clinical samples (0.44%), that had occurred during sample collection or accessioning. The genetic sex predictions were confirmed using additional SNP sites in the sequencing data or high-density genotyping arrays. It was determined that discrepancies resulted from clerical errors, samples from transgender participants and stem cell or bone marrow transplant patients along with undetermined sample mix-ups.

Genetic studies of paired metabolomes reveal enzymatic and transport processes at the interface of plasma and urine. - Schlosser, Pascal; Scherer, Nora; Grundner-Culemann, Franziska; Monteiro-Martins, Sara; Haug, Stefan; Steinbrenner, Inga; Uluvar, Burulça; Wuttke, Matthias; Cheng, Yurong; Ekici, Arif B; Gyimesi, Gergely; Karoly, Edward D; et al. (Nat Genet, 2023)
The kidneys operate at the interface of plasma and urine by clearing molecular waste products while retaining valuable solutes. Genetic studies of paired plasma and urine metabolomes may identify underlying processes. We conducted genome-wide studies of 1,916 plasma and urine metabolites and detected 1,299 significant associations. Associations with 40% of implicated metabolites would have been missed by studying plasma alone. We detected urine-specific findings that provide information about metabolite reabsorption in the kidney, such as aquaporin (AQP)-7-mediated glycerol transport, and different metabolomic footprints of kidney-expressed proteins in plasma and urine that are consistent with their localization and function, including the transporters NaDC3 (SLC13A3) and ASBT (SLC10A2). Shared genetic determinants of 7,073 metabolite-disease combinations represent a resource to better understand metabolic diseases and revealed connections of dipeptidase 1 with circulating digestive enzymes and with hypertension. Extending genetic studies of the metabolome beyond plasma yields unique insights into processes at the interface of body compartments.
Keywords: Kidney; Metabolome; Metabolomics

The genomic landscape of familial glioma. - Choi, Dong-Joo; Armstrong, Georgina; Lozzi, Brittney; Vijayaraghavan, Prashanth; Plon, Sharon E; Wong, Terence C; Eric Boerwinkle; Donna M Muzny; Chen, Hsiao-Chi; Richard A Gibbs; Ostrom, Quinn T; Melin, Beatrice; et al. (Sci Adv, 2023)
Glioma is a rare brain tumor with a poor prognosis. Familial glioma is a subset of glioma with a strong genetic predisposition that accounts for approximately 5% of glioma cases. We performed whole-genome sequencing on an exploratory cohort of 203 individuals from 189 families with a history of familial glioma and an additional validation cohort of 122 individuals from 115 families. We found significant enrichment of rare deleterious variants of seven genes in both cohorts, and the most significantly enriched gene was ( = 0.0006). Furthermore, we identified rare noncoding variants in both cohorts that were predicted to affect transcription factor binding sites or cause cryptic splicing. Last, we selected a subset of discovered genes for validation by CRISPR knockdown screening and found that , have profound impacts on proliferation. This study performs comprehensive surveillance of the genomic landscape of familial glioma.
Keywords: Brain Neoplasms; Calcium-Binding Proteins; DNA-Binding Proteins; Genetic Predisposition to Disease; Genomics; Glioma; Humans; Tumor Suppressor Proteins; Whole Genome Sequencing

Identification of allele-specific KIV-2 repeats and impact on Lp(a) measurements for cardiovascular disease risk. - Behera, S; Belyeu, J R; Chen, X; Paulin, L F; Nguyen, N Q H; Newman, E; Mahmoud, M; Menon, V K; Qi, Q; Joshi, P; Marcovina, S; Rossi, M; et al. (bioRxiv, 2023)
The abundance of Lp(a) protein holds significant implications for the risk of cardiovascular disease (CVD), which is directly impacted by the copy number (CN) of KIV-2, a 5.5 kbp sub-region. KIV-2 is highly polymorphic in the population and accurate analysis is challenging. In this study, we present the DRAGEN KIV-2 CN caller, which utilizes short reads. Data across 166 WGS show that the caller has high accuracy, compared to optical mapping and can further phase ~50% of the samples. We compared KIV-2 CN numbers to 24 previously postulated KIV-2 relevant SNVs, revealing that many are ineffective predictors of KIV-2 copy number. Population studies, including USA-based cohorts, showed distinct KIV-2 CN, distributions for European-, African-, and Hispanic-American populations and further underscored the limitations of SNV predictors. We demonstrate that the CN estimates correlate significantly with the available Lp(a) protein levels and that phasing is highly important.

Identification of Dietary Supplements Associated with Blood Metabolites in the Hispanic Community Health Study/Study of Latinos Cohort Study. - Kaplan, Robert C; Williams-Nguyen, Jessica S; Huang, Yuhan; Mossavar-Rahmani, Yasmin; Yu, Bing; Eric Boerwinkle; Gellman, Marc D; Daviglus, Martha; Chilcoat, Aisha; Van Horn, Linda; Faurot, Kim; Qi, Qibin; et al. (J Nutr, 2023)
BACKGROUND: Metabolomics approaches have been widely used to define the consumption of foods but have less often been used to study exposure to dietary supplements. OBJECTIVES: This study aimed to identify dietary supplements associated with metabolite levels and to examine whether these metabolites predicted incident diabetes risk. METHODS: We studied 3972 participants from a prospective cohort study of 18-74-y-old Hispanic/Latino adults. At a baseline examination, we ascertained use of dietary supplements using recall methods and concurrently, a serum metabolomic panel. After adjustment for potential confounders, we identified dietary supplements associated with metabolites. We then examined the association of these metabolites with incident diabetes at the 6-y study examination. RESULTS: We observed a total of 110 dietary supplement-metabolite associations that met the criteria for statistical significance adjusted for age, sex, field center, Hispanic/Latino background, body mass index, diet, smoking, physical activity, and number of medications (adjusted P < 0.05). This included 13 metabolites uniquely associated with only one dietary supplement ingredient. Vitamin C had the most associated metabolites (n = 15), including positive associations with oxalate, tartronate, threonate, and isocitrate, which were each in turn protective for the risk of incident diabetes. Vitamin C was also associated with higher N-acetylvaline level, which was an unfavorable diabetes risk factor. Other findings related to branched chain amino acid related compounds including α-hydroxyisovalerate and 2-hydroxy-3-methylvalerate, which were inversely associated with thiamine or riboflavin intake and also predicted higher diabetes risk. Vitamin B12 had an inverse association with γ-glutamylvaline, levels of which were positively associated with the risk of diabetes. CONCLUSIONS: Our data point to potential metabolite changes associated with vitamin C and B vitamins, which may have favorable metabolic effects. Knowledge of blood metabolites that can be modified by dietary supplement intake may aid understanding the health effects of dietary supplements and identify potential biological mediators.
Keywords: Ascorbic Acid; Cohort Studies; Dietary Supplements; Hispanic or Latino; Humans; Prospective Studies; Public Health; Vitamin B Complex

Investigating Gene-Diet Interactions Impacting the Association Between Macronutrient Intake and Glycemic Traits. - Westerman, Kenneth E; Walker, Maura E; Gaynor, Sheila M; Wessel, Jennifer; DiCorpo, Daniel; Ma, Jiantao; Alonso, Alvaro; Aslibekyan, Stella; Baldridge, Abigail S; Bertoni, Alain G; Biggs, Mary L; Brody, Jennifer A; et al. (Diabetes, 2023)
UNLABELLED: Few studies have demonstrated reproducible gene-diet interactions (GDIs) impacting metabolic disease risk factors, likely due in part to measurement error in dietary intake estimation and insufficient capture of rare genetic variation. We aimed to identify GDIs across the genetic frequency spectrum impacting the macronutrient-glycemia relationship in genetically and culturally diverse cohorts. We analyzed 33,187 participants free of diabetes from 10 National Heart, Lung, and Blood Institute Trans-Omics for Precision Medicine program cohorts with whole-genome sequencing, self-reported diet, and glycemic trait data. We fit cohort-specific, multivariable-adjusted linear mixed models for the effect of diet, modeled as an isocaloric substitution of carbohydrate for fat, and its interactions with common and rare variants genome-wide. In main effect meta-analyses, participants consuming more carbohydrate had modestly lower glycemic trait values (e.g., for glycated hemoglobin [HbA1c], -0.013% HbA1c/250 kcal substitution). In GDI meta-analyses, a common African ancestry-enriched variant (rs79762542) reached study-wide significance and replicated in the UK Biobank cohort, indicating a negative carbohydrate-HbA1c association among major allele homozygotes only. Simulations revealed that >150,000 samples may be necessary to identify similar macronutrient GDIs under realistic assumptions about effect size and measurement error. These results generate hypotheses for further exploration of modifiable metabolic disease risk in additional cohorts with African ancestry. ARTICLE HIGHLIGHTS: We aimed to identify genetic modifiers of the dietary macronutrient-glycemia relationship using whole-genome sequence data from 10 Trans-Omics for Precision Medicine program cohorts. Substitution models indicated a modest reduction in glycemia associated with an increase in dietary carbohydrate at the expense of fat. Genome-wide interaction analysis identified one African ancestry-enriched variant near the FRAS1 gene that may interact with macronutrient intake to influence hemoglobin A1c. Simulation-based power calculations accounting for measurement error suggested that substantially larger sample sizes may be necessary to discover further gene-macronutrient interactions.
Keywords: Diabetes Mellitus; Diet; Eating; Genome-Wide Association Study; Glycated Hemoglobin; Guanine Nucleotide Dissociation Inhibitors; Humans

Metabolomics of Dietary Intake of Total, Animal, and Plant Protein: Results from the Atherosclerosis Risk in Communities (ARIC) Study. - Bernard, Lauren; Chen, Jingsha; Kim, Hyunju; Wong, Kari E; Steffen, Lyn M; Yu, Bing; Eric Boerwinkle; Rebholz, Casey M (Curr Dev Nutr, 2023)
BACKGROUND: Dietary consumption has traditionally been studied through food intake questionnaires. Metabolomics can be used to identify blood markers of dietary protein that may complement existing dietary assessment tools. OBJECTIVES: We aimed to identify associations between 3 dietary protein sources (total protein, animal protein, and plant protein) and serum metabolites using data from the Atherosclerosis Risk in Communities Study. METHODS: Participants' dietary protein intake was derived from a food frequency questionnaire administered by an interviewer, and fasting serum samples were collected at study visit 1 (1987-1989). Untargeted metabolomic profiling was performed in 2 subgroups (subgroup 1: = 1842; subgroup 2: = 2072). Multivariable linear regression models were used to assess associations between 3 dietary protein sources and 360 metabolites, adjusting for demographic factors and other participant characteristics. Analyses were performed separately within each subgroup and meta-analyzed with fixed-effects models. RESULTS: In this study of 3914 middle-aged adults, the mean (SD) age was 54 (6) y, 60% were women, and 61% were Black. We identified 41 metabolites significantly associated with dietary protein intake. Twenty-six metabolite associations overlapped between total protein and animal protein, such as pyroglutamine, creatine, 3-methylhistidine, and 3-carboxy-4-methyl-5-propyl-2-furanpropanoic acid. Plant protein was uniquely associated with 11 metabolites, such as tryptophan betaine, 4-vinylphenol sulfate, -δ-acetylornithine, and pipecolate. CONCLUSIONS: The results of 17 of the 41 metabolites (41%) were consistent with those of previous nutritional metabolomic studies and specific protein-rich food items. We discovered 24 metabolites that had not been previously associated with dietary protein intake. These results enhance the validity of candidate markers of dietary protein intake and introduce novel metabolomic markers of dietary protein intake.

Powerful, scalable and resource-efficient meta-analysis of rare variant associations in large whole genome sequencing studies. - Li, Xihao; Quick, Corbin; Zhou, Hufeng; Gaynor, Sheila M; Liu, Yaowu; Chen, Han; Selvaraj, Margaret Sunitha; Sun, Ryan; Dey, Rounak; Arnett, Donna K; Bielak, Lawrence F; Bis, Joshua C; et al. (Nat Genet, 2023)
Meta-analysis of whole genome sequencing/whole exome sequencing (WGS/WES) studies provides an attractive solution to the problem of collecting large sample sizes for discovering rare variants associated with complex phenotypes. Existing rare variant meta-analysis approaches are not scalable to biobank-scale WGS data. Here we present MetaSTAAR, a powerful and resource-efficient rare variant meta-analysis framework for large-scale WGS/WES studies. MetaSTAAR accounts for relatedness and population structure, can analyze both quantitative and dichotomous traits and boosts the power of rare variant tests by incorporating multiple variant functional annotations. Through meta-analysis of four lipid traits in 30,138 ancestrally diverse samples from 14 studies of the Trans Omics for Precision Medicine (TOPMed) Program, we show that MetaSTAAR performs rare variant meta-analysis at scale and produces results comparable to using pooled data. Additionally, we identified several conditionally significant rare variant associations with lipid traits. We further demonstrate that MetaSTAAR is scalable to biobank-scale cohorts through meta-analysis of TOPMed WGS data and UK Biobank WES data of ~200,000 samples.
Keywords: Exome Sequencing; Genome-Wide Association Study; Lipids; Phenotype; Whole Genome Sequencing

Proteomic Analysis Identifies Circulating Proteins Associated With Plasma Amyloid-β and Incident Dementia. - Tin, Adrienne; Sullivan, Kevin J; Walker, Keenan A; Bressler, Jan; Talluri, Rajesh; Yu, Bing; Simino, Jeanette; Gudmundsdottir, Valborg; Emilsson, Valur; Jennings, Lori L; Launer, Lenore; Mei, Hao; et al. (Biol Psychiatry Glob Open Sci, 2023)
BACKGROUND: Plasma amyloid-β (Aβ) (Aβ, Aβ, and Aβ/Aβ), biomarkers of the Alzheimer's form of dementia, are under consideration for clinical use. The associations of these peptides with circulating proteins may identify novel plasma biomarkers of dementia and inform peripheral factors influencing the levels of these peptides. METHODS: We analyzed the association of these 3 plasma Aβ measures with 4638 circulating proteins among a subset of the participants of the Atherosclerosis Risk in Communities (ARIC) study (midlife:  = 1955; late life:  = 2082), related the Aβ-associated proteins with incident dementia in the overall ARIC cohort (midlife:  = 11,069, late life:  = 4110) with external replication in the Age, Gene/Environment Susceptibility (AGES)-Reykjavik Study ( = 4973), estimated the proportion of Aβ variance explained, and conducted enrichment analyses to characterize the proteins associated with the plasma Aβ peptides. RESULTS: At midlife, of the 296 Aβ-associated proteins, 8 were associated with incident dementia from midlife and late life in the ARIC study, and NPPB, IBSP, and THBS2 were replicated in the AGES-Reykjavik Study. At late life, of the 34 Aβ-associated proteins, none were associated with incident dementia at midlife, and kidney function explained 10%, 12%, and 0.2% of the variance of Aβ, Aβ, and Aβ/Aβ, respectively. Aβ42-associated proteins at midlife were found to be enriched in the liver, and those at late life were found to be enriched in the spleen. CONCLUSIONS: This study identifies circulating proteins associated with plasma Aβ levels and incident dementia and informs peripheral factors associated with plasma Aβ levels.

Proteomics analysis of plasma from middle-aged adults identifies protein markers of dementia risk in later life. - Walker, Keenan A; Chen, Jingsha; Shi, Liu; Yang, Yunju; Fornage, Myriam; Zhou, Linda; Schlosser, Pascal; Surapaneni, Aditya; Grams, Morgan E; Duggan, Michael R; Peng, Zhongsheng; Gomez, Gabriela T; et al. (Sci Transl Med, 2023)
A diverse set of biological processes have been implicated in the pathophysiology of Alzheimer's disease (AD) and related dementias. However, there is limited understanding of the peripheral biological mechanisms relevant in the earliest phases of the disease. Here, we used a large-scale proteomics platform to examine the association of 4877 plasma proteins with 25-year dementia risk in 10,981 middle-aged adults. We found 32 dementia-associated plasma proteins that were involved in proteostasis, immunity, synaptic function, and extracellular matrix organization. We then replicated the association between 15 of these proteins and clinically relevant neurocognitive outcomes in two independent cohorts. We demonstrated that 12 of these 32 dementia-associated proteins were associated with cerebrospinal fluid (CSF) biomarkers of AD, neurodegeneration, or neuroinflammation. We found that eight of these candidate protein markers were abnormally expressed in human postmortem brain tissue from patients with AD, although some of the proteins that were most strongly associated with dementia risk, such as GDF15, were not detected in these brain tissue samples. Using network analyses, we found a protein signature for dementia risk that was characterized by dysregulation of specific immune and proteostasis/autophagy pathways in adults in midlife ~20 years before dementia onset, as well as abnormal coagulation and complement signaling ~10 years before dementia onset. Bidirectional two-sample Mendelian randomization genetically validated nine of our candidate proteins as markers of AD in midlife and inferred causality of SERPINA3 in AD pathogenesis. Last, we prioritized a set of candidate markers for AD and dementia risk prediction in midlife.
Keywords: Adult; Alzheimer Disease; Amyloid beta-Peptides; Biomarkers; Brain; Humans; Middle Aged; Proteomics; tau Proteins

Rare Genetic Variants Associated With Sudden Cardiac Arrest in the Young: A Prospective, Population-Based Study. - Holmstrom, Lauri; Chaudhary, Ninad S; Nakamura, Kotoka; Chugh, Harpriya; Uy-Evanado, Audrey; Norby, Faye; Ginger A Metcalf; Menon, Vipin K; Yu, Bing; Eric Boerwinkle; Chugh, Sumeet S; Akdemir, Zeynep; et al. (Circ Genom Precis Med, 2023)
Keywords: Death, Sudden, Cardiac; Heart Arrest; Humans; Prospective Studies

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed whole-genome sequencing study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Eric Boerwinkle; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (Am J Hum Genet, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions in lipid metabolism. Large-scale whole-genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess more associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with measurement of blood lipids and lipoproteins (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare-variant aggregate association tests using the STAAR (variant-set test for association using annotation information) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare-coding variants in nearby protein-coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500-kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variation and rare protein-coding variation at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNAs.
Keywords: Genome-Wide Association Study; Humans; Lipids; Polymorphism, Single Nucleotide; Precision Medicine; RNA, Long Noncoding; Whole Genome Sequencing

Rare variants in long non-coding RNAs are associated with blood lipid levels in the TOPMed Whole Genome Sequencing Study. - Wang, Yuxuan; Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Holdcraft, Jacob A; Arnett, Donna K; Bis, Joshua C; Blangero, John; Eric Boerwinkle; Bowden, Donald W; Cade, Brian E; Carlson, Jenna C; et al. (medRxiv, 2023)
Long non-coding RNAs (lncRNAs) are known to perform important regulatory functions. Large-scale whole genome sequencing (WGS) studies and new statistical methods for variant set tests now provide an opportunity to assess the associations between rare variants in lncRNA genes and complex traits across the genome. In this study, we used high-coverage WGS from 66,329 participants of diverse ancestries with blood lipid levels (LDL-C, HDL-C, TC, and TG) in the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) program to investigate the role of lncRNAs in lipid variability. We aggregated rare variants for 165,375 lncRNA genes based on their genomic locations and conducted rare variant aggregate association tests using the STAAR (variant-Set Test for Association using Annotation infoRmation) framework. We performed STAAR conditional analysis adjusting for common variants in known lipid GWAS loci and rare coding variants in nearby protein coding genes. Our analyses revealed 83 rare lncRNA variant sets significantly associated with blood lipid levels, all of which were located in known lipid GWAS loci (in a ±500 kb window of a Global Lipids Genetics Consortium index variant). Notably, 61 out of 83 signals (73%) were conditionally independent of common regulatory variations and rare protein coding variations at the same loci. We replicated 34 out of 61 (56%) conditionally independent associations using the independent UK Biobank WGS data. Our results expand the genetic architecture of blood lipids to rare variants in lncRNA, implicating new therapeutic opportunities.

A statistical framework for powerful multi-trait rare variant analysis in large-scale whole-genome sequencing studies. - Li, Xihao; Chen, Han; Selvaraj, Margaret Sunitha; Van Buren, Eric; Zhou, Hufeng; Wang, Yuxuan; Sun, Ryan; McCaw, Zachary R; Yu, Zhi; Arnett, Donna K; Bis, Joshua C; Blangero, John; et al. (bioRxiv, 2023)
Large-scale whole-genome sequencing (WGS) studies have improved our understanding of the contributions of coding and noncoding rare variants to complex human traits. Leveraging association effect sizes across multiple traits in WGS rare variant association analysis can improve statistical power over single-trait analysis, and also detect pleiotropic genes and regions. Existing multi-trait methods have limited ability to perform rare variant analysis of large-scale WGS data. We propose MultiSTAAR, a statistical framework and computationally-scalable analytical pipeline for functionally-informed multi-trait rare variant analysis in large-scale WGS studies. MultiSTAAR accounts for relatedness, population structure and correlation among phenotypes by jointly analyzing multiple traits, and further empowers rare variant association analysis by incorporating multiple functional annotations. We applied MultiSTAAR to jointly analyze three lipid traits (low-density lipoprotein cholesterol, high-density lipoprotein cholesterol and triglycerides) in 61,861 multi-ethnic samples from the Trans-Omics for Precision Medicine (TOPMed) Program. We discovered new associations with lipid traits missed by single-trait analysis, including rare variants within an enhancer of and an intergenic region on chromosome 1.

StocSum: stochastic summary statistics for whole genome sequencing studies. - Wang, Nannan; Yu, Bing; Jun, Goo; Qi, Qibin; Durazo-Arvizu, Ramon A; Lindström, Sara; Morrison, Alanna C; Kaplan, Robert C; Eric Boerwinkle; Chen, Han (bioRxiv, 2023)
Genomic summary statistics, usually defined as single-variant test results from genome-wide association studies, have been widely used to advance the genetics field in a wide range of applications. Applications that involve multiple genetic variants also require their correlations or linkage disequilibrium (LD) information, often obtained from an external reference panel. In practice, it is usually difficult to find suitable external reference panels that represent the LD structure for underrepresented and admixed populations, or rare genetic variants from whole genome sequencing (WGS) studies, limiting the scope of applications for genomic summary statistics. Here we introduce StocSum, a novel reference-panel-free statistical framework for generating, managing, and analyzing stochastic summary statistics using random vectors. We develop various downstream applications using StocSum including single-variant tests, conditional association tests, gene-environment interaction tests, variant set tests, as well as meta-analysis and LD score regression tools. We demonstrate the accuracy and computational efficiency of StocSum using two cohorts from the Trans-Omics for Precision Medicine Program. StocSum will facilitate sharing and utilization of genomic summary statistics from WGS studies, especially for underrepresented and admixed populations.

Transcriptome- and proteome-wide association studies nominate determinants of kidney function and damage. - Schlosser, Pascal; Zhang, Jingning; Liu, Hongbo; Surapaneni, Aditya L; Rhee, Eugene P; Arking, Dan E; Yu, Bing; Eric Boerwinkle; Welling, Paul A; Chatterjee, Nilanjan; Susztak, Katalin; Coresh, Josef; et al. (Genome Biol, 2023)
BACKGROUND: The pathophysiological causes of kidney disease are not fully understood. Here we show that the integration of genome-wide genetic, transcriptomic, and proteomic association studies can nominate causal determinants of kidney function and damage. RESULTS: Through transcriptome-wide association studies (TWAS) in kidney cortex, kidney tubule, liver, and whole blood and proteome-wide association studies (PWAS) in plasma, we assess for effects of 12,893 genes and 1342 proteins on kidney filtration (glomerular filtration rate (GFR) estimated by creatinine; GFR estimated by cystatin C; and blood urea nitrogen) and kidney damage (albuminuria). We find 1561 associations distributed among 260 genomic regions that are supported as putatively causal. We then prioritize 153 of these genomic regions using additional colocalization analyses. Our genome-wide findings are supported by existing knowledge (animal models for MANBA, DACH1, SH3YL1, INHBB), exceed the underlying GWAS signals (28 region-trait combinations without significant GWAS hit), identify independent gene/protein-trait associations within the same genomic region (INHBC, SPRYD4), nominate tissues underlying the associations (tubule expression of NRBP1), and distinguish markers of kidney filtration from those with a role in creatinine and cystatin C metabolism. Furthermore, we follow up on members of the TGF-beta superfamily of proteins and find a prognostic value of INHBC for kidney disease progression even after adjustment for measured glomerular filtration rate (GFR). CONCLUSION: In summary, this study combines multimodal, genome-wide association studies to generate a catalog of putatively causal target genes and proteins relevant to kidney function and damage which can guide follow-up studies in physiology, basic science, and clinical medicine.
Keywords: Animals; Creatinine; Cystatin C; Genome-Wide Association Study; Kidney; Proteome; Proteomics; Renal Insufficiency, Chronic; Transcriptome

Whole Genome Analysis of Venous Thromboembolism: the Trans-Omics for Precision Medicine Program. - Seyerle, Amanda A; Laurie, Cecelia A; Coombes, Brandon J; Jain, Deepti; Conomos, Matthew P; Brody, Jennifer; Chen, Ming-Huei; Gogarten, Stephanie M; Beutel, Kathleen M; Gupta, Namrata; Heckbert, Susan R; Jackson, Rebecca D; et al. (Circ Genom Precis Med, 2023)
BACKGROUND: Risk for venous thromboembolism has a strong genetic component. Whole genome sequencing from the TOPMed program (Trans-Omics for Precision Medicine) allowed us to look for new associations, particularly rare variants missed by standard genome-wide association studies. METHODS: The 3793 cases and 7834 controls (11.6% of cases were individuals of African, Hispanic/Latino, or Asian ancestry) were analyzed using a single variant approach and an aggregate gene-based approach using our primary filter (included only loss-of-function and missense variants predicted to be deleterious) and our secondary filter (included all missense variants). RESULTS: Single variant analyses identified associations at 5 known loci. Aggregate gene-based analyses identified only (odds ratio, 6.2 for carriers of rare variants; =7.4×10) when using our primary filter. Employing our secondary variant filter led to a smaller effect size at (odds ratio, 3.8; =1.6×10), while excluding variants found only in rare isoforms led to a larger one (odds ratio, 7.5). Different filtering strategies improved the signal for 2 other known genes: became significant (minimum =1.8×10 with the secondary filter), while did not (minimum =4.4×10 with minor allele frequency <0.0005). Results were largely the same when restricting the analyses to include only unprovoked cases; however, one novel gene, , became significant (=4.4×10 using all missense variants with minor allele frequency <0.0005). CONCLUSIONS: Here, we have demonstrated the importance of using multiple variant filtering strategies, as we detected additional genes when filtering variants based on their predicted deleteriousness, frequency, and presence on the most expressed isoforms. Our primary analyses did not identify new candidate loci; thus larger follow-up studies are needed to replicate the novel locus and to identify additional rare variation associated with venous thromboembolism.
Keywords: Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Precision Medicine; Venous Thromboembolism

Whole-exome sequencing study identifies four novel gene loci associated with diabetic kidney disease. - Pan, Yang; Sun, Xiao; Mi, Xuenan; Huang, Zhijie; Hsu, Yenchih; Hixson, James E; Munzy, Donna; Ginger A Metcalf; Franceschini, Nora; Tin, Adrienne; Köttgen, Anna; Francis, Michael; et al. (Hum Mol Genet, 2023)
Diabetic kidney disease (DKD) is recognized as an important public health challenge. However, its genomic mechanisms are poorly understood. To identify rare variants for DKD, we conducted a whole-exome sequencing (WES) study leveraging large cohorts well-phenotyped for chronic kidney disease and diabetes. Our two-stage WES study included 4372 European and African ancestry participants from the Chronic Renal Insufficiency Cohort and Atherosclerosis Risk in Communities studies (stage 1) and 11 487 multi-ancestry Trans-Omics for Precision Medicine participants (stage 2). Generalized linear mixed models, which accounted for genetic relatedness and adjusted for age, sex and ancestry, were used to test associations between single variants and DKD. Gene-based aggregate rare variant analyses were conducted using an optimized sequence kernel association test implemented within our mixed model framework. We identified four novel exome-wide significant DKD-related loci through initiating diabetes. In single-variant analyses, participants carrying a rare, in-frame insertion in the DIS3L2 gene (rs141560952) exhibited a 193-fold increased odds [95% confidence interval (CI): 33.6, 1105] of DKD compared with noncarriers (P = 3.59 × 10-9). Likewise, each copy of a low-frequency KRT6B splice-site variant (rs425827) conferred a 5.31-fold higher odds (95% CI: 3.06, 9.21) of DKD (P = 2.72 × 10-9). Aggregate gene-based analyses further identified ERAP2 (P = 4.03 × 10-8) and NPEPPS (P = 1.51 × 10-7), which are both expressed in the kidney and implicated in renin-angiotensin-aldosterone system modulated immune response. In the largest WES study of DKD, we identified novel rare variant loci attaining exome-wide significance. These findings provide new insights into the molecular mechanisms underlying DKD.
Keywords: Aminopeptidases; Diabetes Mellitus; Diabetic Nephropathies; Exome Sequencing; Humans; Kidney; Renal Insufficiency, Chronic

American Heart Association's Life's Simple 7: Lifestyle Recommendations, Polygenic Risk, and Lifetime Risk of Coronary Heart Disease. - Hasbani, Natalie R; Ligthart, Symen; Brown, Michael R; Heath, Adam S; Bebo, Allison; Ashley, Kellan E; Eric Boerwinkle; Morrison, Alanna C; Folsom, Aaron R; Aguilar, David; de Vries, Paul S (Circulation, 2022)
BACKGROUND: Understanding the effect of lifestyle and genetic risk on the lifetime risk of coronary heart disease (CHD) is important to improving public health initiatives. Our objective was to quantify remaining lifetime risk and years free of CHD according to polygenic risk and the American Heart Association's Life's Simple 7 (LS7) guidelines in a population-based cohort study. METHODS: Our analysis included data from participants of the ARIC (Atherosclerosis Risk in Communities) study: 8372 White and 2314 Black participants; 45 years of age and older; and free of CHD at baseline examination. A polygenic risk score (PRS) comprised more than 6 million genetic variants was categorized into low (<20th percentile), intermediate, and high (>80th percentile). An overall LS7 score was calculated at baseline and categorized into "poor," "intermediate," and "ideal" cardiovascular health. Lifetime risk and CHD-free years were computed according to polygenic risk and LS7 categories. RESULTS: The overall remaining lifetime risk was 27%, ranging from 16.6% in individuals with an ideal LS7 score to 43.1% for individuals with a poor LS7 score. The association of PRS with lifetime risk differed according to ancestry. In White participants, remaining lifetime risk ranged from 19.8% to 39.3% according to increasing PRS categories. Individuals with a high PRS and poor LS7 had a remaining lifetime risk of 67.1% and 15.9 fewer CHD-free years than did those with intermediate polygenic risk and LS7 scores. In the high-PRS group, ideal LS7 was associated with 20.2 more CHD-free years compared with poor LS7. In Black participants, remaining lifetime risk ranged from 19.1% to 28.6% according to increasing PRS category. Similar lifetime risk estimates were observed for individuals of poor LS7 regardless of PRS category. In the high-PRS group, an ideal LS7 score was associated with only 4.5 more CHD-free years compared with a poor LS7 score. CONCLUSIONS: Ideal adherence to LS7 recommendations was associated with lower lifetime risk of CHD for all individuals, especially in those with high genetic susceptibility. In Black participants, adherence to LS7 guidelines contributed to lifetime risk of CHD more so than current PRSs. Improved PRSs are needed to properly evaluate genetic susceptibility for CHD in diverse populations.
Keywords: American Heart Association; Cardiovascular Diseases; Cohort Studies; Coronary Disease; Genetic Predisposition to Disease; Humans; Life Style; Risk Factors; United States

Apolipoprotein E Polymorphism, Cardiac Remodeling, and Heart Failure in the ARIC Study. - Selvaraj, Senthil; Claggett, Brian; Johansen, Michelle C; Cunningham, Jonathan W; Gottesman, Rebecca F; Yu, Bing; Eric Boerwinkle; Mosley, Thomas H; Shah, Amil M; Solomon, Scott D (J Card Fail, 2022)
BACKGROUND: β-Amyloid has recently been discovered in the myocardium of patients with Alzheimer's disease (AD). Whether genetic variation in apolipoprotein E (APOE) ɛ4, a common variant associated with Alzheimer's disease, is associated with incident heart failure (HF), N-terminal pro-B-type natriuretic peptide (NT-proBNP), and cardiac structure and function is unknown. METHODS AND RESULTS: We studied 15,064 White and Black participants in the Atherosclerosis Risk in Communities, relating genotype status at visit 1 (1987-1989) to incident HF hospitalization using Cox regression. At visits 2, 4, and 5, we assessed NT-proBNP levels by genotype. At visits 3 and 5, we related Aβ peptides to incident HF. At visit 5 (2011-2013, n = 6251), we assessed the relationship of genotype with prevalent HF and echocardiographic parameters. The mean participant age was 54.7 ± 5.8 years, 45% were men, and 73% were White. At visit 5, there was no difference in prevalent HF by genotype. The APOE ε4 carriers did not have increased risk for HF hospitalization. The APOE ε4 genotype was not associated with cardiac structure and function or NT-proBNP levels. The Aβ peptides were not associated with incident HF after multivariable adjustment. CONCLUSIONS: A genetic predisposition to Alzheimer's disease through APOE ε4 is not associated with an increased prevalence of HF, HF hospitalization, myocardial remodeling, or biochemical evidence of HF.
Keywords: Alzheimer Disease; Apolipoprotein E4; Apolipoproteins E; Biomarkers; Female; Heart Failure; Humans; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Ventricular Remodeling

Assessing the contribution of rare genetic variants to phenotypes of chronic obstructive pulmonary disease using whole-genome sequence data. - Kim, Wonji; Hecker, Julian; Barr, R Graham; Eric Boerwinkle; Cade, Brian; Correa, Adolfo; Dupuis, Josée; Gharib, Sina A; Lange, Leslie; London, Stephanie J; Morrison, Alanna C; O'Connor, George T; et al. (Hum Mol Genet, 2022)
RATIONALE: Genetic variation has a substantial contribution to chronic obstructive pulmonary disease (COPD) and lung function measurements. Heritability estimates using genome-wide genotyping data can be biased if analyses do not appropriately account for the nonuniform distribution of genetic effects across the allele frequency and linkage disequilibrium (LD) spectrum. In addition, the contribution of rare variants has been unclear. OBJECTIVES: We sought to assess the heritability of COPD and lung function using whole-genome sequence data from the Trans-Omics for Precision Medicine program. METHODS: Using the genome-based restricted maximum likelihood method, we partitioned the genome into bins based on minor allele frequency and LD scores and estimated heritability of COPD, FEV1% predicted and FEV1/FVC ratio in 11 051 European ancestry and 5853 African-American participants. MEASUREMENTS AND MAIN RESULTS: In European ancestry participants, the estimated heritability of COPD, FEV1% predicted and FEV1/FVC ratio were 35.5%, 55.6% and 32.5%, of which 18.8%, 19.7%, 17.8% were from common variants, and 16.6%, 35.8%, and 14.6% were from rare variants. These estimates had wide confidence intervals, with common variants and some sets of rare variants showing a statistically significant contribution (P-value < 0.05). In African-Americans, common variant heritability was similar to European ancestry participants, but lower sample size precluded calculation of rare variant heritability. CONCLUSIONS: Our study provides updated and unbiased estimates of heritability for COPD and lung function, and suggests an important contribution of rare variants. Larger studies of more diverse ancestry will improve accuracy of these estimates.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Phenotype; Polymorphism, Single Nucleotide; Pulmonary Disease, Chronic Obstructive

Blood metabolites predicting mild cognitive impairment in the study of Latinos-investigation of neurocognitive aging (HCHS/SOL). - He, Shan; Granot-Hershkovitz, Einat; Zhang, Ying; Bressler, Jan; Tarraf, Wassim; Yu, Bing; Huang, Tianyi; Zeng, Donglin; Wassertheil-Smoller, Sylvia; Lamar, Melissa; Daviglus, Martha; Marquine, Maria J; et al. (Alzheimers Dement (Amst), 2022)
INTRODUCTION: Blood metabolomics-based biomarkers may be useful to predict measures of neurocognitive aging. METHODS: We tested the association between 707 blood metabolites measured in 1451 participants from the Hispanic Community Health Study/Study of Latinos (HCHS/SOL), with mild cognitive impairment (MCI) and global cognitive change assessed 7 years later. We further used Lasso penalized regression to construct a metabolomics risk score (MRS) that predicts MCI, potentially identifying a different set of metabolites than those discovered in individual-metabolite analysis. RESULTS: We identified 20 metabolites predicting prevalent MCI and/or global cognitive change. Six of them were novel and 14 were previously reported as associated with neurocognitive aging outcomes. The MCI MRS comprised 61 metabolites and improved prediction accuracy from 84% (minimally adjusted model) to 89% in the entire dataset and from 75% to 87% among apolipoprotein E ε4 carriers. DISCUSSION: Blood metabolites may serve as biomarkers identifying individuals at risk for MCI among US Hispanics/Latinos.

Clonal hematopoiesis of indeterminate potential, DNA methylation, and risk for coronary artery disease. - Uddin, M D Mesbah; Nguyen, Ngoc Quynh H; Yu, Bing; Brody, Jennifer A; Pampana, Akhil; Nakao, Tetsushi; Fornage, Myriam; Bressler, Jan; Sotoodehnia, Nona; Weinstock, Joshua S; Honigberg, Michael C; Nachun, Daniel; et al. (Nat Commun, 2022)
Age-related changes to the genome-wide DNA methylation (DNAm) pattern observed in blood are well-documented. Clonal hematopoiesis of indeterminate potential (CHIP), characterized by the age-related acquisition and expansion of leukemogenic mutations in hematopoietic stem cells (HSCs), is associated with blood cancer and coronary artery disease (CAD). Epigenetic regulators DNMT3A and TET2 are the two most frequently mutated CHIP genes. Here, we present results from an epigenome-wide association study for CHIP in 582 Cardiovascular Health Study (CHS) participants, with replication in 2655 Atherosclerosis Risk in Communities (ARIC) Study participants. We show that DNMT3A and TET2 CHIP have distinct and directionally opposing genome-wide DNAm association patterns consistent with their regulatory roles, albeit both promoting self-renewal of HSCs. Mendelian randomization analyses indicate that a subset of DNAm alterations associated with these two leading CHIP genes may promote the risk for CAD.
Keywords: Clonal Hematopoiesis; Coronary Artery Disease; DNA Methylation; Hematopoiesis; Hematopoietic Stem Cells; Humans

Correction: Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2022)

Discovery and systematic characterization of risk variants and genes for coronary artery disease in over a million participants. - Aragam, Krishna G; Jiang, Tao; Goel, Anuj; Kanoni, Stavroula; Wolford, Brooke N; Atri, Deepak S; Weeks, Elle M; Wang, Minxian; Hindy, George; Zhou, Wei; Grace, Christopher; Roselli, Carolina; et al. (Nat Genet, 2022)
The discovery of genetic loci associated with complex diseases has outpaced the elucidation of mechanisms of disease pathogenesis. Here we conducted a genome-wide association study (GWAS) for coronary artery disease (CAD) comprising 181,522 cases among 1,165,690 participants of predominantly European ancestry. We detected 241 associations, including 30 new loci. Cross-ancestry meta-analysis with a Japanese GWAS yielded 38 additional new loci. We prioritized likely causal variants using functionally informed fine-mapping, yielding 42 associations with less than five variants in the 95% credible set. Similarity-based clustering suggested roles for early developmental processes, cell cycle signaling and vascular cell migration and proliferation in the pathogenesis of CAD. We prioritized 220 candidate causal genes, combining eight complementary approaches, including 123 supported by three or more approaches. Using CRISPR-Cas9, we experimentally validated the effect of an enhancer in MYO9B, which appears to mediate CAD risk by regulating vascular cell motility. Our analysis identifies and systematically characterizes >250 risk loci for CAD to inform experimental interrogation of putative causal mechanisms for CAD.
Keywords: Coronary Artery Disease; Genome-Wide Association Study; Humans

DNA methylation signature of chronic low-grade inflammation and its role in cardio-respiratory diseases. - Wielscher, Matthias; Mandaviya, Pooja R; Kuehnel, Brigitte; Joehanes, Roby; Mustafa, Rima; Robinson, Oliver; Zhang, Yan; Bodinier, Barbara; Walton, Esther; Mishra, Pashupati P; Schlosser, Pascal; Wilson, Rory; et al. (Nat Commun, 2022)
We performed a multi-ethnic Epigenome Wide Association study on 22,774 individuals to describe the DNA methylation signature of chronic low-grade inflammation as measured by C-Reactive protein (CRP). We find 1,511 independent differentially methylated loci associated with CRP. These CpG sites show correlation structures across chromosomes, and are primarily situated in euchromatin, depleted in CpG islands. These genomic loci are predominantly situated in transcription factor binding sites and genomic enhancer regions. Mendelian randomization analysis suggests altered CpG methylation is a consequence of increased blood CRP levels. Mediation analysis reveals obesity and smoking as important underlying driving factors for changed CpG methylation. Finally, we find that an activated CpG signature significantly increases the risk for cardiometabolic diseases and COPD.
Keywords: C-Reactive Protein; CpG Islands; DNA Methylation; Humans; Inflammation; Nucleotide Motifs

A framework for detecting noncoding rare-variant associations of large-scale whole-genome sequencing studies. - Li, Zilin; Li, Xihao; Zhou, Hufeng; Gaynor, Sheila M; Selvaraj, Margaret Sunitha; Arapoglou, Theodore; Quick, Corbin; Liu, Yaowu; Chen, Han; Sun, Ryan; Dey, Rounak; Arnett, Donna K; et al. (Nat Methods, 2022)
Large-scale whole-genome sequencing studies have enabled analysis of noncoding rare-variant (RV) associations with complex human diseases and traits. Variant-set analysis is a powerful approach to study RV association. However, existing methods have limited ability in analyzing the noncoding genome. We propose a computationally efficient and robust noncoding RV association detection framework, STAARpipeline, to automatically annotate a whole-genome sequencing study and perform flexible noncoding RV association analysis, including gene-centric analysis and fixed window-based and dynamic window-based non-gene-centric analysis by incorporating variant functional annotations. In gene-centric analysis, STAARpipeline uses STAAR to group noncoding variants based on functional categories of genes and incorporate multiple functional annotations. In non-gene-centric analysis, STAARpipeline uses SCANG-STAAR to incorporate dynamic window sizes and multiple functional annotations. We apply STAARpipeline to identify noncoding RV sets associated with four lipid traits in 21,015 discovery samples from the Trans-Omics for Precision Medicine (TOPMed) program and replicate several of them in an additional 9,123 TOPMed samples. We also analyze five non-lipid TOPMed traits.
Keywords: Genetic Variation; Genome; Genome-Wide Association Study; Humans; Phenotype; Whole Genome Sequencing

Genetic analyses of the electrocardiographic QT interval and its components identify additional loci and pathways. - Young, William J; Lahrouchi, Najim; Isaacs, Aaron; Duong, ThuyVy; Foco, Luisa; Ahmed, Farah; Brody, Jennifer A; Salman, Reem; Noordam, Raymond; Benjamins, Jan-Walter; Haessler, Jeffrey; Lyytikäinen, Leo-Pekka; et al. (Nat Commun, 2022)
The QT interval is an electrocardiographic measure representing the sum of ventricular depolarization and repolarization, estimated by QRS duration and JT interval, respectively. QT interval abnormalities are associated with potentially fatal ventricular arrhythmia. Using genome-wide multi-ancestry analyses (>250,000 individuals) we identify 177, 156 and 121 independent loci for QT, JT and QRS, respectively, including a male-specific X-chromosome locus. Using gene-based rare-variant methods, we identify associations with Mendelian disease genes. Enrichments are observed in established pathways for QT and JT, and previously unreported genes indicated in insulin-receptor signalling and cardiac energy metabolism. In contrast for QRS, connective tissue components and processes for cell growth and extracellular matrix interactions are significantly enriched. We demonstrate polygenic risk score associations with atrial fibrillation, conduction disease and sudden cardiac death. Prioritization of druggable genes highlight potential therapeutic targets for arrhythmia. Together, these results substantially advance our understanding of the genetic architecture of ventricular depolarization and repolarization.
Keywords: Arrhythmias, Cardiac; Death, Sudden, Cardiac; Electrocardiography; Genetic Testing; Humans; Male

Genome-wide analysis of mitochondrial DNA copy number reveals loci implicated in nucleotide metabolism, platelet activation, and megakaryocyte proliferation. - Longchamps, R J; Yang, S Y; Castellani, C A; Shi, W; Lane, J; Grove, M L; Bartz, T M; Sarnowski, C; Liu, C; Burrows, K; Guyatt, A L; Gaunt, T R; et al. (Hum Genet, 2022)
Mitochondrial DNA copy number (mtDNA-CN) measured from blood specimens is a minimally invasive marker of mitochondrial function that exhibits both inter-individual and intercellular variation. To identify genes involved in regulating mitochondrial function, we performed a genome-wide association study (GWAS) in 465,809 White individuals from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (UKB). We identified 133 SNPs with statistically significant, independent effects associated with mtDNA-CN across 100 loci. A combination of fine-mapping, variant annotation, and co-localization analyses was used to prioritize genes within each of the 133 independent sites. Putative causal genes were enriched for known mitochondrial DNA depletion syndromes (p = 3.09 × 10) and the gene ontology (GO) terms for mtDNA metabolism (p = 1.43 × 10) and mtDNA replication (p = 1.2 × 10). A clustering approach leveraged pleiotropy between mtDNA-CN associated SNPs and 41 mtDNA-CN associated phenotypes to identify functional domains, revealing three distinct groups, including platelet activation, megakaryocyte proliferation, and mtDNA metabolism. Finally, using mitochondrial SNPs, we establish causal relationships between mitochondrial function and a variety of blood cell-related traits, kidney function, liver function and overall (p = 0.044) and non-cancer mortality (p = 6.56 × 10).
Keywords: Aged; Cell Proliferation; DNA Copy Number Variations; DNA, Mitochondrial; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Megakaryocytes; Middle Aged; Mitochondria; Nucleotides; Phenotype; Platelet Activation; Polymorphism, Single Nucleotide

Genome-wide meta-analyses reveal novel loci for verbal short-term memory and learning. - Lahti, Jari; Tuominen, Samuli; Yang, Qiong; Pergola, Giulio; Ahmad, Shahzad; Amin, Najaf; Armstrong, Nicola J; Beiser, Alexa; Bey, Katharina; Bis, Joshua C; Eric Boerwinkle; Bressler, Jan; et al. (Mol Psychiatry, 2022)
Understanding the genomic basis of memory processes may help in combating neurodegenerative disorders. Hence, we examined the associations of common genetic variants with verbal short-term memory and verbal learning in adults without dementia or stroke (N = 53,637). We identified novel loci in the intronic region of CDH18, and at 13q21 and 3p21.1, as well as an expected signal in the APOE/APOC1/TOMM40 region. These results replicated in an independent sample. Functional and bioinformatic analyses supported many of these loci and further implicated POC1. We showed that polygenic score for verbal learning associated with brain activation in right parieto-occipital region during working memory task. Finally, we showed genetic correlations of these memory traits with several neurocognitive and health outcomes. Our findings suggest a role of several genomic loci in verbal memory processes.
Keywords: Brain; Learning; Memory, Short-Term; Multifactorial Inheritance; Verbal Learning

Genome-wide studies reveal factors associated with circulating uromodulin and its relationships to complex diseases. - Li, Yong; Cheng, Yurong; Consolato, Francesco; Schiano, Guglielmo; Chong, Michael R; Pietzner, Maik; Nguyen, Ngoc Quynh H; Scherer, Nora; Biggs, Mary L; Kleber, Marcus E; Haug, Stefan; Göçmen, Burulça; et al. (JCI Insight, 2022)
Uromodulin (UMOD) is a major risk gene for monogenic and complex forms of kidney disease. The encoded kidney-specific protein uromodulin is highly abundant in urine and related to chronic kidney disease, hypertension, and pathogen defense. To gain insights into potential systemic roles, we performed genome-wide screens of circulating uromodulin using complementary antibody-based and aptamer-based assays. We detected 3 and 10 distinct significant loci, respectively. Integration of antibody-based results at the UMOD locus with functional genomics data (RNA-Seq, ATAC-Seq, Hi-C) of primary human kidney tissue highlighted an upstream variant with differential accessibility and transcription in uromodulin-synthesizing kidney cells as underlying the observed cis effect. Shared association patterns with complex traits, including chronic kidney disease and blood pressure, placed the PRKAG2 locus in the same pathway as UMOD. Experimental validation of the third antibody-based locus, B4GALNT2, showed that the p.Cys466Arg variant of the encoded N-acetylgalactosaminyltransferase had a loss-of-function effect leading to higher serum uromodulin levels. Aptamer-based results pointed to enzymes writing glycan marks present on uromodulin and to their receptors in the circulation, suggesting that this assay permits investigating uromodulin's complex glycosylation rather than its quantitative levels. Overall, our study provides insights into circulating uromodulin and its emerging functions.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Hypertension; Renal Insufficiency, Chronic; Uromodulin

Implementation of preemptive DNA sequence-based pharmacogenomics testing across a large academic medical center: The Mayo-Baylor RIGHT 10K Study. - Wang, Liewei; Steven E Scherer; Bielinski, Suzette J; Donna M Muzny; Jones, Leila A; Black, John Logan; Moyer, Ann M; Giri, Jyothsna; Sharp, Richard R; Matey, Eric T; Wright, Jessica A; Oyen, Lance J; et al. (Genet Med, 2022)
PURPOSE: The Mayo-Baylor RIGHT 10K Study enabled preemptive, sequence-based pharmacogenomics (PGx)-driven drug prescribing practices in routine clinical care within a large cohort. We also generated the tools and resources necessary for clinical PGx implementation and identified challenges that need to be overcome. Furthermore, we measured the frequency of both common genetic variation for which clinical guidelines already exist and rare variation that could be detected by DNA sequencing, rather than genotyping. METHODS: Targeted oligonucleotide-capture sequencing of 77 pharmacogenes was performed using DNA from 10,077 consented Mayo Clinic Biobank volunteers. The resulting predicted drug response-related phenotypes for 13 genes, including CYP2D6 and HLA, affecting 21 drug-gene pairs, were deposited preemptively in the Mayo electronic health record. RESULTS: For the 13 pharmacogenes of interest, the genomes of 79% of participants carried clinically actionable variants in 3 or more genes, and DNA sequencing identified an average of 3.3 additional conservatively predicted deleterious variants that would not have been evident using genotyping. CONCLUSION: Implementation of preemptive rather than reactive and sequence-based rather than genotype-based PGx prescribing revealed nearly universal patient applicability and required integrated institution-wide resources to fully realize individualized drug therapy and to show more efficient use of health care resources.
Keywords: Academic Medical Centers; Base Sequence; Cytochrome P-450 CYP2D6; Genotype; Humans; Pharmacogenetics

Insights From a Large-Scale Whole-Genome Sequencing Study of Systolic Blood Pressure, Diastolic Blood Pressure, and Hypertension. - Kelly, Tanika N; Sun, Xiao; He, Karen Y; Brown, Michael R; Taliun, Sarah A Gagliano; Hellwege, Jacklyn N; Irvin, Marguerite R; Mi, Xuenan; Brody, Jennifer A; Franceschini, Nora; Guo, Xiuqing; Hwang, Shih-Jen; et al. (Hypertension, 2022)
BACKGROUND: The availability of whole-genome sequencing data in large studies has enabled the assessment of coding and noncoding variants across the allele frequency spectrum for their associations with blood pressure. METHODS: We conducted a multiancestry whole-genome sequencing analysis of blood pressure among 51 456 Trans-Omics for Precision Medicine and Centers for Common Disease Genomics program participants (stage-1). Stage-2 analyses leveraged array data from UK Biobank (N=383 145), Million Veteran Program (N=318 891), and Reasons for Geographic and Racial Differences in Stroke (N=10 643) participants, along with whole-exome sequencing data from UK Biobank (N=199 631) participants. RESULTS: Two blood pressure signals achieved genome-wide significance in meta-analyses of stage-1 and stage-2 single variant findings (<5×10). Among them, a rare intergenic variant at novel locus, , was associated with lower systolic blood pressure in stage-1 (beta [SE]=-32.6 [6.0]; =4.99×10) but not stage-2 analysis (=0.11). Furthermore, a novel common variant at the known locus was suggestively associated with diastolic blood pressure in stage-1 (beta [SE]=-0.36 [0.07]; =4.18×10) and attained genome-wide significance in stage-2 (beta [SE]=-0.29 [0.03]; =7.28×10). Nineteen additional signals suggestively associated with blood pressure in meta-analysis of single and aggregate rare variant findings (<1×10 and <1×10, respectively). DISCUSSION: We report one promising but unconfirmed rare variant for blood pressure and, more importantly, contribute insights for future blood pressure sequencing studies. Our findings suggest promise of aggregate analyses to complement single variant analysis strategies and the need for larger, diverse samples, and family studies to enable robust rare variant identification.
Keywords: Blood Pressure; Genome-Wide Association Study; Genomics; Humans; Hypertension; Polymorphism, Single Nucleotide; Precision Medicine

Kidney Risk Variants and Proteomics. - Chen, Teresa K; Surapaneni, Aditya L; Arking, Dan E; Ballantyne, Christie M; Eric Boerwinkle; Chen, Jingsha; Coresh, Josef; Köttgen, Anna; Susztak, Katalin; Tin, Adrienne; Yu, Bing; Grams, Morgan E (Clin J Am Soc Nephrol, 2022)
BACKGROUND AND OBJECTIVES: The risk variants (G1 and G2) are associated with kidney disease among Black adults, but the clinical presentation is heterogeneous. In mouse models and cell systems, increased gene expression of G1 and G2 confers cytotoxicity. How risk variants relate to the circulating proteome warrants further investigation. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: Among 461 African American Study of Kidney Disease and Hypertension (AASK) participants (mean age: 54 years; 41% women; mean GFR: 46 ml/min per 1.73 m), we evaluated associations of risk variants with 6790 serum proteins (measured SOMAscan) using linear regression models. Covariates included age, sex, percentage of European ancestry, and protein principal components 1-5. Associated proteins were then evaluated as mediators of -associated risk for kidney failure. Findings were replicated among 875 Atherosclerosis Risk in Communities (ARIC) study Black participants (mean age: 75 years; 66% women; mean eGFR: 67 ml/min per 1.73 m). RESULTS: In the AASK study, having two (versus zero or one) risk alleles was associated with lower serum levels of APOL1 (=3.11E-13; =3.12E-06 [two aptamers]), APOL2 (1.45E-10), CLSTN2 (=2.66E-06), MMP-2 (=2.96E-06), SPOCK2 (=2.57E-05), and TIMP-2 (=2.98E-05) proteins. In the ARIC study, risk alleles were associated with APOL1 (=1.28E-11); MMP-2 (=0.004) and TIMP-2 (=0.007) were associated only in an additive model, and APOL2 was not available. high-risk status was associated with a 1.6-fold greater risk of kidney failure in the AASK study; none of the identified proteins mediated this association. APOL1 protein levels were not associated with kidney failure in either cohort. CONCLUSIONS: risk variants were strongly associated with lower circulating levels of APOL1 and other proteins, but none mediated the -associated risk for kidney failure. APOL1 protein level was also not associated with kidney failure.
Keywords: Animals; Apolipoprotein L1; Creatinine; Female; Genetic Predisposition to Disease; Genotype; Humans; Kidney; Male; Matrix Metalloproteinase 2; Mice; Proteoglycans; Proteomics; Renal Insufficiency, Chronic; Risk Factors; Tissue Inhibitor of Metalloproteinase-2

New insights into the genetic etiology of Alzheimer's disease and related dementias. - Bellenguez, Céline; Küçükali, Fahri; Jansen, Iris E; Kleineidam, Luca; Moreno-Grau, Sonia; Amin, Najaf; Naj, Adam C; Campos-Martin, Rafael; Grenier-Boley, Benjamin; Andrade, Victor; Holmans, Peter A; Boland, Anne; et al. (Nat Genet, 2022)
Characterization of the genetic landscape of Alzheimer's disease (AD) and related dementias (ADD) provides a unique opportunity for a better understanding of the associated pathophysiological processes. We performed a two-stage genome-wide association study totaling 111,326 clinically diagnosed/'proxy' AD cases and 677,663 controls. We found 75 risk loci, of which 42 were new at the time of analysis. Pathway enrichment analyses confirmed the involvement of amyloid/tau pathways and highlighted microglia implication. Gene prioritization in the new loci identified 31 genes that were suggestive of new genetically associated processes, including the tumor necrosis factor alpha pathway through the linear ubiquitin chain assembly complex. We also built a new genetic risk score associated with the risk of future AD/dementia or progression from mild cognitive impairment to AD/dementia. The improvement in prediction led to a 1.6- to 1.9-fold increase in AD risk from the lowest to the highest decile, in addition to effects of age and the APOE ε4 allele.
Keywords: Alzheimer Disease; Cognitive Dysfunction; Genome-Wide Association Study; Humans; tau Proteins

Patient and Clinician Perceptions of Precision Cardiology Care: Findings From the HeartCare Study. - Smith, Hadley Stevens; Sanchez, Clarissa E; Maag, Ronald; Buentello, Alexandria; David R Murdock; Ginger A Metcalf; Hadley, Trevor D; Riconda, Daniel L; Eric Boerwinkle; Wehrens, Xander H T; Ballantyne, Christie M; Richard A Gibbs; et al. (Circ Genom Precis Med, 2022)
BACKGROUND: Routine genome-wide screening for cardiovascular disease risk may inform clinical decision-making. However, little is known about whether clinicians and patients would find such testing useful or acceptable within the context of a genomics-enabled learning health system. METHODS: We conducted surveys with patients and their clinicians who were participating in the HeartCare Study, a precision cardiology care project that returned results from a next-generation sequencing panel of 158 genes associated with cardiovascular disease risk. Six weeks after return of results, we assessed patients' and clinicians' perceived utility and disutility of HeartCare, the effect of the test on clinical recommendations, and patients' attitudes toward integration of research and clinical care. RESULTS: Among 666 HeartCare patients with a result returned during the survey study period, 42.0% completed a full or partial survey. Patient-participants who completed a full survey (n=224) generally had positive perceptions of HeartCare independent of whether they received a positive or negative result. Most patient-participants considered genetic testing for cardiovascular disease risk to have more benefit than risk (88.3%) and agreed that it provided information that they wanted to know (81.2%), while most disagreed that the test caused them to feel confused (77.7%) or overwhelmed (78.0%). For 122 of their patients with positive results, clinicians (n=13) reported making changes in clinical care for 66.4% of patients, recommending changes in health behaviors for 36.9% of patients, and recommending to 33.6% of patients that their family members have clinical testing. CONCLUSIONS: Both patients and clinicians thought the HeartCare panel screen for cardiovascular disease risk provided information that was useful in terms of personal or health benefits to the patient and that informed clinical care without causing patients to be confused or overwhelmed. Further research is needed to assess perceptions of genome-wide screening among the US cardiology clinic population.
Keywords: Cardiology; Cardiovascular Diseases; Clinical Decision-Making; Family; Humans; Surveys and Questionnaires

Plasma proteome analyses in individuals of European and African ancestry identify cis-pQTLs and models for proteome-wide association studies. - Zhang, Jingning; Dutta, Diptavo; Köttgen, Anna; Tin, Adrienne; Schlosser, Pascal; Grams, Morgan E; Harvey, Benjamin; Yu, Bing; Eric Boerwinkle; Coresh, Josef; Chatterjee, Nilanjan (Nat Genet, 2022)
Improved understanding of genetic regulation of the proteome can facilitate identification of the causal mechanisms for complex traits. We analyzed data on 4,657 plasma proteins from 7,213 European American (EA) and 1,871 African American (AA) individuals from the Atherosclerosis Risk in Communities study, and further replicated findings on 467 AA individuals from the African American Study of Kidney Disease and Hypertension study. Here, we identified 2,004 proteins in EA and 1,618 in AA, with most overlapping, which showed associations with common variants in cis-regions. Availability of AA samples led to smaller credible sets and notable number of population-specific cis-protein quantitative trait loci. Elastic Net produced powerful models for protein prediction in both populations. An application of proteome-wide association studies to serum urate and gout implicated several proteins, including IL1RN, revealing the promise of the drug anakinra to treat acute gout flares. Our study demonstrates the value of large and diverse ancestry study to investigate the genetic mechanisms of molecular phenotypes and their relationship with complex traits.
Keywords: Genetic Predisposition to Disease; Genome-Wide Association Study; Gout; Humans; Polymorphism, Single Nucleotide; Proteome

Rare coding variants in 35 genes associate with circulating lipid levels-A multi-ancestry analysis of 170,000 exomes. - Hindy, George; Dornbos, Peter; Chaffin, Mark D; Liu, Dajiang J; Wang, Minxian; Selvaraj, Margaret Sunitha; Zhang, David; Park, Joseph; Aguilar-Salinas, Carlos A; Antonacci-Fulton, Lucinda; Ardissino, Diego; Arnett, Donna K; et al. (Am J Hum Genet, 2022)
Large-scale gene sequencing studies for complex traits have the potential to identify causal genes with therapeutic implications. We performed gene-based association testing of blood lipid levels with rare (minor allele frequency < 1%) predicted damaging coding variation by using sequence data from >170,000 individuals from multiple ancestries: 97,493 European, 30,025 South Asian, 16,507 African, 16,440 Hispanic/Latino, 10,420 East Asian, and 1,182 Samoan. We identified 35 genes associated with circulating lipid levels; some of these genes have not been previously associated with lipid levels when using rare coding variation from population-based samples. We prioritize 32 genes in array-based genome-wide association study (GWAS) loci based on aggregations of rare coding variants; three (EVI5, SH2B3, and PLIN1) had no prior association of rare coding variants with lipid levels. Most of our associated genes showed evidence of association among multiple ancestries. Finally, we observed an enrichment of gene-based associations for low-density lipoprotein cholesterol drug target genes and for genes closest to GWAS index single-nucleotide polymorphisms (SNPs). Our results demonstrate that gene-based associations can be beneficial for drug target development and provide evidence that the gene closest to the array-based GWAS index SNP is often the functional gene for blood lipid levels.
Keywords: Alleles; Blood Glucose; Case-Control Studies; Computational Biology; Databases, Genetic; Diabetes Mellitus, Type 2; Exome; Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome-Wide Association Study; Humans; Lipid Metabolism; Lipids; Liver; Molecular Sequence Annotation; Multifactorial Inheritance; Open Reading Frames; Phenotype; Polymorphism, Single Nucleotide

Rare coding variants in RCN3 are associated with blood pressure. - He, Karen Y; Kelly, Tanika N; Wang, Heming; Liang, Jingjing; Zhu, Luke; Cade, Brian E; Assimes, Themistocles L; Becker, Lewis C; Beitelshees, Amber L; Bielak, Lawrence F; Bress, Adam P; Brody, Jennifer A; et al. (BMC Genomics, 2022)
BACKGROUND: While large genome-wide association studies have identified nearly one thousand loci associated with variation in blood pressure, rare variant identification is still a challenge. In family-based cohorts, genome-wide linkage scans have been successful in identifying rare genetic variants for blood pressure. This study aims to identify low frequency and rare genetic variants within previously reported linkage regions on chromosomes 1 and 19 in African American families from the Trans-Omics for Precision Medicine (TOPMed) program. Genetic association analyses weighted by linkage evidence were completed with whole genome sequencing data within and across TOPMed ancestral groups consisting of 60,388 individuals of European, African, East Asian, Hispanic, and Samoan ancestries. RESULTS: Associations of low frequency and rare variants in RCN3 and multiple other genes were observed for blood pressure traits in TOPMed samples. The association of low frequency and rare coding variants in RCN3 was further replicated in UK Biobank samples (N = 403,522), and reached genome-wide significance for diastolic blood pressure (p = 2.01 × 10). CONCLUSIONS: Low frequency and rare variants in RCN3 contributes blood pressure variation. This study demonstrates that focusing association analyses in linkage regions greatly reduces multiple-testing burden and improves power to identify novel rare variants associated with blood pressure traits.
Keywords: Blood Pressure; Genetic Linkage; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Precision Medicine; Whole Genome Sequencing

Rare Variants in Genes Encoding Subunits of the Epithelial Na Channel Are Associated With Blood Pressure and Kidney Function. - Blobner, Brandon M; Kirabo, Annet; Kashlan, Ossama B; Sheng, Shaohu; Arnett, Donna K; Becker, Lewis C; Eric Boerwinkle; Carlson, Jenna C; Gao, Yan; Richard A Gibbs; He, Jiang; Irvin, Marguerite R; et al. (Hypertension, 2022)
BACKGROUND: The epithelial Na channel (ENaC) is intrinsically linked to fluid volume homeostasis and blood pressure. Specific rare mutations in , , and , genes encoding the α, β, and γ subunits of ENaC, respectively, are associated with extreme blood pressure phenotypes. No associations between blood pressure and , which encodes the δ subunit of ENaC, have been reported. A small number of sequence variants in ENaC subunits have been reported to affect functional transport in vitro or blood pressure. The effects of the vast majority of rare and low-frequency ENaC variants on blood pressure are not known. METHODS: We explored the association of low frequency and rare variants in the genes encoding ENaC subunits, with systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure. Using whole-genome sequencing data from 14 studies participating in the Trans-Omics in Precision Medicine Whole-Genome Sequencing Program, and sequence kernel association tests. RESULTS: We found that variants in and were associated with diastolic blood pressure and mean arterial pressure (<0.00625). Although is poorly expressed in human kidney tissue, variants were associated with systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure (<0.00625). ENaC variants in 2 of the 4 subunits ( and ) were also associated with estimated glomerular filtration rate (<0.00625), but not with stroke. CONCLUSIONS: Our results suggest that variants in extrarenal ENaCs, in addition to ENaCs expressed in kidneys, influence blood pressure and kidney function.
Keywords: Blood Pressure; Epithelial Sodium Channels; Humans; Kidney; Phenotype; Sodium

Serum Metabolites and Kidney Outcomes: The Atherosclerosis Risk in Communities Study. - Bernard, Lauren; Zhou, Linda; Surapaneni, Aditya; Chen, Jingsha; Rebholz, Casey M; Coresh, Josef; Yu, Bing; Eric Boerwinkle; Schlosser, Pascal; Grams, Morgan E (Kidney Med, 2022)
RATIONALE & OBJECTIVE: Novel metabolite biomarkers of kidney failure with replacement therapy (KFRT) may help identify people at high risk for adverse kidney outcomes and implicated pathways may aid in developing targeted therapeutics. STUDY DESIGN: Prospective cohort. SETTING & PARTICIPANTS: The cohort included 3,799 Atherosclerosis Risk in Communities study participants with serum samples available for measurement at visit 1 (1987-1989). EXPOSURE: Baseline serum levels of 318 metabolites. OUTCOMES: Incident KFRT, kidney failure (KFRT, estimated glomerular filtration rate <15 mL/min/1.73 m, or death from kidney disease). ANALYTICAL APPROACH: Because metabolites are often intercorrelated and represent shared pathways, we used a high dimension reduction technique called Netboost to cluster metabolites. Longitudinal associations between clusters of metabolites and KFRT and kidney failure were estimated using a Cox proportional hazards model. RESULTS: Mean age of study participants was 53 years, 61% were African American, and 13% had diabetes. There were 160 KFRT cases and 357 kidney failure cases over a mean of 23 years. The 314 metabolites were grouped in 43 clusters. Four clusters were significantly associated with risk of KFRT and 6 were associated with kidney failure (including 3 shared clusters). The 3 shared clusters suggested potential pathways perturbed early in kidney disease: cluster 5 (15 metabolites involved in alanine, aspartate, and glutamate metabolism as well as 5-oxoproline and several gamma-glutamyl amino acids), cluster 26 (6 metabolites involved in sugar and inositol phosphate metabolism), and cluster 34 (21 metabolites involved in glycerophospholipid metabolism). Several individual metabolites were also significantly associated with both KFRT and kidney failure, including glucose and mannose, which were associated with higher risk of both outcomes, and 5-oxoproline, gamma-glutamyl amino acids, linoleoylglycerophosphocholine, 1,5-anhydroglucitol, which were associated with lower risk of both outcomes. LIMITATIONS: Inability to determine if the metabolites cause or are a consequence of changes in kidney function. CONCLUSIONS: We identified several clusters of metabolites reproducibly associated with development of KFRT. Future experimental studies are needed to validate our findings as well as continue unraveling metabolic pathways involved in kidney function decline.

Targeted Genome Sequencing Identifies Multiple Rare Variants in Caveolin-1 Associated with Obstructive Sleep Apnea. - Liang, Jingjing; Wang, Heming; Cade, Brian E; Kurniansyah, Nuzulul; He, Karen Y; Lee, Jiwon; Sands, Scott A; A Brody, Jennifer; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Respir Crit Care Med, 2022)
Obstructive sleep apnea (OSA) is a common disorder associated with increased risk for cardiovascular disease, diabetes, and premature mortality. There is strong clinical and epidemiologic evidence supporting the importance of genetic factors influencing OSA but limited data implicating specific genes. To search for rare variants contributing to OSA severity. Leveraging high-depth genomic sequencing data from the NHLBI Trans-Omics for Precision Medicine (TOPMed) program and imputed genotype data from multiple population-based studies, we performed linkage analysis in the CFS (Cleveland Family Study), followed by multistage gene-based association analyses in independent cohorts for apnea-hypopnea index (AHI) in a total of 7,708 individuals of European ancestry. Linkage analysis in the CFS identified a suggestive linkage peak on chromosome 7q31 (LOD = 2.31). Gene-based analysis identified 21 noncoding rare variants in (Caveolin-1) associated with lower AHI after accounting for multiple comparisons ( = 7.4 × 10). These noncoding variants together significantly contributed to the linkage evidence ( < 10). Follow-up analysis revealed significant associations between these variants and increased expression, and increased expression in peripheral monocytes was associated with lower AHI ( = 0.024) and higher minimum overnight oxygen saturation ( = 0.007). Rare variants in , a membrane-scaffolding protein essential in multiple cellular and metabolic functions, are associated with higher gene expression and lower OSA severity, suggesting a novel target for modulating OSA severity.
Keywords: Caveolin 1; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Sleep Apnea, Obstructive

TOP-LD: A tool to explore linkage disequilibrium with TOPMed whole-genome sequence data. - Huang, Le; Rosen, Jonathan D; Sun, Quan; Chen, Jiawen; Wheeler, Marsha M; Zhou, Ying; Min, Yuan-I; Kooperberg, Charles; Conomos, Matthew P; Stilp, Adrienne M; Rich, Stephen S; Rotter, Jerome I; et al. (Am J Hum Genet, 2022)
Current publicly available tools that allow rapid exploration of linkage disequilibrium (LD) between markers (e.g., HaploReg and LDlink) are based on whole-genome sequence (WGS) data from 2,504 individuals in the 1000 Genomes Project. Here, we present TOP-LD, an online tool to explore LD inferred with high-coverage (∼30×) WGS data from 15,578 individuals in the NHLBI Trans-Omics for Precision Medicine (TOPMed) program. TOP-LD provides a significant upgrade compared to current LD tools, as the TOPMed WGS data provide a more comprehensive representation of genetic variation than the 1000 Genomes data, particularly for rare variants and in the specific populations that we analyzed. For example, TOP-LD encompasses LD information for 150.3, 62.2, and 36.7 million variants for European, African, and East Asian ancestral samples, respectively, offering 2.6- to 9.1-fold increase in variant coverage compared to HaploReg 4.0 or LDlink. In addition, TOP-LD includes tens of thousands of structural variants (SVs). We demonstrate the value of TOP-LD in fine-mapping at the GGT1 locus associated with gamma glutamyltransferase in the African ancestry participants in UK Biobank. Beyond fine-mapping, TOP-LD can facilitate a wide range of applications that are based on summary statistics and estimates of LD. TOP-LD is freely available online.
Keywords: Asian People; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Polymorphism, Single Nucleotide; Precision Medicine; Whole Genome Sequencing

Type 2 Diabetes Partitioned Polygenic Scores Associate With Disease Outcomes in 454,193 Individuals Across 13 Cohorts. - DiCorpo, Daniel; LeClair, Jessica; Cole, Joanne B; Sarnowski, Chloe; Ahmadizar, Fariba; Bielak, Lawrence F; Blokstra, Anneke; Bottinger, Erwin P; Chaker, Layal; Chen, Yii-Der I; Chen, Ye; de Vries, Paul S; et al. (Diabetes Care, 2022)
OBJECTIVE: Type 2 diabetes (T2D) has heterogeneous patient clinical characteristics and outcomes. In previous work, we investigated the genetic basis of this heterogeneity by clustering 94 T2D genetic loci using their associations with 47 diabetes-related traits and identified five clusters, termed β-cell, proinsulin, obesity, lipodystrophy, and liver/lipid. The relationship between these clusters and individual-level metabolic disease outcomes has not been assessed. RESEARCH DESIGN AND METHODS: Here we constructed individual-level partitioned polygenic scores (pPS) for these five clusters in 12 studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and the UK Biobank (n = 454,193) and tested for cross-sectional association with T2D-related outcomes, including blood pressure, renal function, insulin use, age at T2D diagnosis, and coronary artery disease (CAD). RESULTS: Despite all clusters containing T2D risk-increasing alleles, they had differential associations with metabolic outcomes. Increased obesity and lipodystrophy cluster pPS, which had opposite directions of association with measures of adiposity, were both significantly associated with increased blood pressure and hypertension. The lipodystrophy and liver/lipid cluster pPS were each associated with CAD, with increasing and decreasing effects, respectively. An increased liver/lipid cluster pPS was also significantly associated with reduced renal function. The liver/lipid cluster includes known loci linked to liver lipid metabolism (e.g., GCKR, PNPLA3, and TM6SF2), and these findings suggest that cardiovascular disease risk and renal function may be impacted by these loci through their shared disease pathway. CONCLUSIONS: Our findings support that genetically driven pathways leading to T2D also predispose differentially to clinical outcomes.
Keywords: Alleles; Cross-Sectional Studies; Diabetes Mellitus, Type 2; Genetic Loci; Humans; Obesity; Pharmaceutical Preparations

The Value of Rare Genetic Variation in the Prediction of Common Obesity in European Ancestry Populations. - Wang, Zhe; Choi, Shing Wan; Chami, Nathalie; Eric Boerwinkle; Fornage, Myriam; Redline, Susan; Bis, Joshua C; Brody, Jennifer A; Psaty, Bruce M; Kim, Wonji; McDonald, Merry-Lynn N; Regan, Elizabeth A; et al. (Front Endocrinol (Lausanne), 2022)
Polygenic risk scores (PRSs) aggregate the effects of genetic variants across the genome and are used to predict risk of complex diseases, such as obesity. Current PRSs only include common variants (minor allele frequency (MAF) ≥1%), whereas the contribution of rare variants in PRSs to predict disease remains unknown. Here, we examine whether augmenting the standard common variant PRS (PRS) with a rare variant PRS (PRS) improves prediction of obesity. We used genome-wide genotyped and imputed data on 451,145 European-ancestry participants of the UK Biobank, as well as whole exome sequencing (WES) data on 184,385 participants. We performed single variant analyses (for both common and rare variants) and gene-based analyses (for rare variants) for association with BMI (kg/m), obesity (BMI ≥ 30 kg/m), and extreme obesity (BMI ≥ 40 kg/m). We built PRSs and PRSs using a range of methods (Clumping+Thresholding [C+T], PRS-CS, lassosum, gene-burden test). We selected the best-performing PRSs and assessed their performance in 36,757 European-ancestry unrelated participants with whole genome sequencing (WGS) data from the Trans-Omics for Precision Medicine (TOPMed) program. The best-performing PRS explained 10.1% of variation in BMI, and 18.3% and 22.5% of the susceptibility to obesity and extreme obesity, respectively, whereas the best-performing PRS explained 1.49%, and 2.97% and 3.68%, respectively. The PRS was associated with an increased risk of obesity and extreme obesity (OR = 1.37 per SD, = 1.7x10; OR = 1.55 per SD, = 3.8x10), which was attenuated, after adjusting for PRS (OR = 1.08 per SD, = 9.8x10; OR= 1.09 per SD, = 0.02). When PRS and PRS are combined, the increase in explained variance attributed to PRS was small (incremental Nagelkerke R = 0.24% for obesity and 0.51% for extreme obesity). Consistently, combining PRS to PRS provided little improvement to the prediction of obesity (PRS AUC = 0.591; PRS AUC = 0.708; PRS AUC = 0.710). In summary, while rare variants show convincing association with BMI, obesity and extreme obesity, the PRS provides limited improvement over PRS in the prediction of obesity risk, based on these large populations.
Keywords: Gene Frequency; Genetic Variation; Genome-Wide Association Study; Humans; Obesity; Whole Genome Sequencing

Whole genome sequence analysis of blood lipid levels in >66,000 individuals. - Selvaraj, Margaret Sunitha; Li, Xihao; Li, Zilin; Pampana, Akhil; Zhang, David Y; Park, Joseph; Aslibekyan, Stella; Bis, Joshua C; Brody, Jennifer A; Cade, Brian E; Chuang, Lee-Ming; Chung, Ren-Hua; et al. (Nat Commun, 2022)
Blood lipids are heritable modifiable causal factors for coronary artery disease. Despite well-described monogenic and polygenic bases of dyslipidemia, limitations remain in discovery of lipid-associated alleles using whole genome sequencing (WGS), partly due to limited sample sizes, ancestral diversity, and interpretation of clinical significance. Among 66,329 ancestrally diverse (56% non-European) participants, we associate 428M variants from deep-coverage WGS with lipid levels; ~400M variants were not assessed in prior lipids genetic analyses. We find multiple lipid-related genes strongly associated with blood lipids through analysis of common and rare coding variants. We discover several associated rare non-coding variants, largely at Mendelian lipid genes. Notably, we observe rare LDLR intronic variants associated with markedly increased LDL-C, similar to rare LDLR exonic variants. In conclusion, we conducted a systematic whole genome scan for blood lipids expanding the alleles linked to lipids for multiple ancestries and characterize a clinically-relevant rare non-coding variant model for lipids.
Keywords: Alleles; Cholesterol, LDL; Genome-Wide Association Study; Humans; Lipids; Whole Genome Sequencing

Whole genome sequencing identifies structural variants contributing to hematologic traits in the NHLBI TOPMed program. - Wheeler, Marsha M; Stilp, Adrienne M; Rao, Shuquan; Halldórsson, Bjarni V; Beyter, Doruk; Wen, Jia; Mihkaylova, Anna V; McHugh, Caitlin P; Lane, John; Jiang, Min-Zhi; Raffield, Laura M; Jun, Goo; et al. (Nat Commun, 2022)
Genome-wide association studies have identified thousands of single nucleotide variants and small indels that contribute to variation in hematologic traits. While structural variants are known to cause rare blood or hematopoietic disorders, the genome-wide contribution of structural variants to quantitative blood cell trait variation is unknown. Here we utilized whole genome sequencing data in ancestrally diverse participants of the NHLBI Trans Omics for Precision Medicine program (N = 50,675) to detect structural variants associated with hematologic traits. Using single variant tests, we assessed the association of common and rare structural variants with red cell-, white cell-, and platelet-related quantitative traits and observed 21 independent signals (12 common and 9 rare) reaching genome-wide significance. The majority of these associations (N = 18) replicated in independent datasets. In genome-editing experiments, we provide evidence that a deletion associated with lower monocyte counts leads to disruption of an S1PR3 monocyte enhancer and decreased S1PR3 expression.
Keywords: Blood Cells; Genome-Wide Association Study; Humans; Whole Genome Sequencing

Whole-exome sequencing of 14 389 individuals from the ESP and CHARGE consortia identifies novel rare variation associated with hemostatic factors. - Pankratz, Nathan; Wei, Peng; Brody, Jennifer A; Chen, Ming-Huei; de Vries, Paul S; Huffman, Jennifer E; Stimson, Mary Rachel; Auer, Paul L; Eric Boerwinkle; Cushman, Mary; de Maat, Moniek P M; Folsom, Aaron R; et al. (Hum Mol Genet, 2022)
Plasma levels of fibrinogen, coagulation factors VII and VIII and von Willebrand factor (vWF) are four intermediate phenotypes that are heritable and have been associated with the risk of clinical thrombotic events. To identify rare and low-frequency variants associated with these hemostatic factors, we conducted whole-exome sequencing in 10 860 individuals of European ancestry (EA) and 3529 African Americans (AAs) from the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and the National Heart, Lung and Blood Institute's Exome Sequencing Project. Gene-based tests demonstrated significant associations with rare variation (minor allele frequency < 5%) in fibrinogen gamma chain (FGG) (with fibrinogen, P = 9.1 × 10-13), coagulation factor VII (F7) (with factor VII, P = 1.3 × 10-72; seven novel variants) and VWF (with factor VIII and vWF; P = 3.2 × 10-14; one novel variant). These eight novel rare variant associations were independent of the known common variants at these loci and tended to have much larger effect sizes. In addition, one of the rare novel variants in F7 was significantly associated with an increased risk of venous thromboembolism in AAs (Ile200Ser; rs141219108; P = 4.2 × 10-5). After restricting gene-based analyses to only loss-of-function variants, a novel significant association was detected and replicated between factor VIII levels and a stop-gain mutation exclusive to AAs (rs3211938) in CD36 molecule (CD36). This variant has previously been linked to dyslipidemia but not with the levels of a hemostatic factor. These efforts represent the largest integration of whole-exome sequence data from two national projects to identify genetic variation associated with plasma hemostatic factors.
Keywords: Exome Sequencing; Factor VII; Factor VIII; Fibrinogen; Hemostatics; Humans; Polymorphism, Single Nucleotide; von Willebrand Factor

xAtlas: scalable small variant calling across heterogeneous next-generation sequencing experiments. - Farek, Jesse; Hughes, Daniel; Salerno, William; Zhu, Yiming; Pisupati, Aishwarya; Mansfield, Adam; Krasheninina, Olga; English, Adam C; Ginger A Metcalf; Eric Boerwinkle; Donna M Muzny; Richard A Gibbs; et al. (Gigascience, 2022)
BACKGROUND: The growing volume and heterogeneity of next-generation sequencing (NGS) data complicate the further optimization of identifying DNA variation, especially considering that curated high-confidence variant call sets frequently used to validate these methods are generally developed from the analysis of comparatively small and homogeneous sample sets. FINDINGS: We have developed xAtlas, a single-sample variant caller for single-nucleotide variants (SNVs) and small insertions and deletions (indels) in NGS data. xAtlas features rapid runtimes, support for CRAM and gVCF file formats, and retraining capabilities. xAtlas reports SNVs with 99.11% recall and 98.43% precision across a reference HG002 sample at 60× whole-genome coverage in less than 2 CPU hours. Applying xAtlas to 3,202 samples at 30× whole-genome coverage from the 1000 Genomes Project achieves an average runtime of 1.7 hours per sample and a clear separation of the individual populations in principal component analysis across called SNVs. CONCLUSIONS: xAtlas is a fast, lightweight, and accurate SNV and small indel calling method. Source code for xAtlas is available under a BSD 3-clause license at https://github.com/jfarek/xatlas.
Keywords: Algorithms; Genome; High-Throughput Nucleotide Sequencing; INDEL Mutation; Polymorphism, Single Nucleotide; Software

Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. - Dyment, David A; O'Donnell-Luria, Anne; Agrawal, Pankaj B; Coban Akdemir, Zeynep; Aleck, Kyrieckos A; Antaki, Danny; Al Sharhan, Hind; Au, Ping-Yee B; Aydin, Hatip; Beggs, Alan H; Bilguvar, Kaya; Eric Boerwinkle; et al. (Am J Med Genet A, 2021)
Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz-like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome-wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy-number variation at1p36.11(ARID1A), 8q22.2(VPS13B), Xp22, and Xq13(HDAC8). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family (N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next-generation sequencing. Overall, the DubS-like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.
Keywords: Adolescent; Child; Child, Preschool; DNA Copy Number Variations; Eczema; Exome; Exome Sequencing; Facies; Female; Genetic Predisposition to Disease; Genome, Human; Genomics; Growth Disorders; Histone Deacetylases; Humans; Infant; Intellectual Disability; Male; Microcephaly; Phenotype; Repressor Proteins

Association Between Midlife Obesity and Kidney Function Trajectories: The Atherosclerosis Risk in Communities (ARIC) Study. - Yu, Zhi; Grams, Morgan E; Ndumele, Chiadi E; Wagenknecht, Lynne; Eric Boerwinkle; North, Kari E; Rebholz, Casey M; Giovannucci, Edward L; Coresh, Josef (Am J Kidney Dis, 2021)
RATIONALE & OBJECTIVE: Obesity has been related to risk for chronic kidney disease. However, the associations of different measures of midlife obesity with long-term kidney function trajectories and whether they differ by sex and race are unknown. STUDY DESIGN: Observational study. SETTING & PARTICIPANTS: 13,496 participants from the Atherosclerosis Risk in Communities (ARIC) Study. PREDICTORS: Midlife obesity status as measured by body mass index (BMI), waist-to-hip ratio, and predicted percent fat at baseline. OUTCOMES: Estimated glomerular filtration rate (eGFR) calculated using serum creatinine level measured at 5 study visits, and incident kidney failure with replacement therapy (KFRT). ANALYTICAL APPROACH: Mixed models with random intercepts and random slopes for eGFR. Cox proportional hazards models for KFRT. RESULTS: Baseline mean age was 54 years, median eGFR was 103mL/min/1.73m, and median BMI was 27kg/m. Over 30 years of follow-up, midlife obesity measures were associated with eGFR decline in White and Black women but not consistently in men. Adjusted for age, center, smoking, and coronary heart disease, the differences in eGFR slope per 1-SD higher BMI, waist-to-hip ratio, and predicted percent fat were 0.09 (95% CI, -0.18 to 0.36), -0.25 (95% CI, -0.50 to 0.01), and-0.14 (95% CI, -0.41 to 0.13) mL/min/1.73m per decade for White men; -0.91 (95% CI, -1.15 to-0.67), -0.82 (95% CI, -1.06 to-0.58), and-1.02 (95% CI, -1.26 to-0.78) mL/min/1.73m per decade for White women; -0.70 (95% CI, -1.54 to 0.14), -1.60 (95% CI, -2.42 to-0.78), and-1.24 (95% CI, -2.08 to-0.40) mL/min/1.73m per decade for Black men; and-1.24 (95% CI, -2.08 to-0.40), -1.50 (95% CI, -2.05 to-0.95), and-1.43 (95% CI, -2.00 to-0.86) mL/min/1.73m per decade for Black women. Obesity indicators were independently associated with risk for KFRT for all sex-race groups except White men. LIMITATIONS: Loss to follow-up during 3 decades of follow-up with 5 eGFR assessments. CONCLUSIONS: Obesity status is a risk factor for future decline in kidney function and development of KFRT in Black and White women, with less consistent associations among men.
Keywords: Black or African American; Body Mass Index; Creatinine; Female; Glomerular Filtration Rate; Humans; Kidney Failure, Chronic; Longitudinal Studies; Male; Middle Aged; Obesity; Proportional Hazards Models; Renal Replacement Therapy; Sex Factors; Waist-Hip Ratio; White People

Association of low-frequency and rare coding variants with information processing speed. - Bressler, Jan; Davies, Gail; Smith, Albert V; Saba, Yasaman; Bis, Joshua C; Jian, Xueqiu; Hayward, Caroline; Yanek, Lisa; Smith, Jennifer A; Mirza, Saira S; Wang, Ruiqi; Adams, Hieab H H; et al. (Transl Psychiatry, 2021)
Measures of information processing speed vary between individuals and decline with age. Studies of aging twins suggest heritability may be as high as 67%. The Illumina HumanExome Bead Chip genotyping array was used to examine the association of rare coding variants with performance on the Digit-Symbol Substitution Test (DSST) in community-dwelling adults participating in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. DSST scores were available for 30,576 individuals of European ancestry from nine cohorts and for 5758 individuals of African ancestry from four cohorts who were older than 45 years and free of dementia and clinical stroke. Linear regression models adjusted for age and gender were used for analysis of single genetic variants, and the T5, T1, and T01 burden tests that aggregate the number of rare alleles by gene were also applied. Secondary analyses included further adjustment for education. Meta-analyses to combine cohort-specific results were carried out separately for each ancestry group. Variants in RNF19A reached the threshold for statistical significance (p = 2.01 × 10) using the T01 test in individuals of European descent. RNF19A belongs to the class of E3 ubiquitin ligases that confer substrate specificity when proteins are ubiquitinated and targeted for degradation through the 26S proteasome. Variants in SLC22A7 and OR51A7 were suggestively associated with DSST scores after adjustment for education for African-American participants and in the European cohorts, respectively. Further functional characterization of its substrates will be required to confirm the role of RNF19A in cognitive function.
Keywords: Adult; Aging; Cognition; Genome-Wide Association Study; Geroscience; Humans; Polymorphism, Single Nucleotide; Ubiquitin-Protein Ligases

Association of mitochondrial DNA copy number with cardiometabolic diseases. - Liu, Xue; Longchamps, Ryan J; Wiggins, Kerri L; Raffield, Laura M; Bielak, Lawrence F; Zhao, Wei; Pitsillides, Achilleas; Blackwell, Thomas W; Yao, Jie; Guo, Xiuqing; Kurniansyah, Nuzulul; Thyagarajan, Bharat; et al. (Cell Genom, 2021)
Mitochondrial DNA (mtDNA) is present in multiple copies in human cells. We evaluated cross-sectional associations of whole blood mtDNA copy number (CN) with several cardiometabolic disease traits in 408,361 participants of multiple ancestries in TOPMed and UK Biobank. Age showed a threshold association with mtDNA CN: among younger participants (<65 years of age), each additional 10 years of age was associated with 0.03 standard deviation (s.d.) higher level of mtDNA CN ( = 0.0014) versus a 0.14 s.d. lower level of mtDNA CN ( = 1.82 × 10) among older participants (≥65 years). At lower mtDNA CN levels, we found age-independent associations with increased odds of obesity ( = 5.6 × 10), hypertension ( = 2.8 × 10), diabetes ( = 3.6 × 10), and hyperlipidemia ( = 6.3 × 10). The observed decline in mtDNA CN after 65 years of age may be a key to understanding age-related diseases.

Author Correction: Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2021)

BinomiRare: A robust test for association of a rare genetic variant with a binary outcome for mixed models and any case-control proportion. - Sofer, Tamar; Lee, Jiwon; Kurniansyah, Nuzulul; Jain, Deepti; Laurie, Cecelia A; Gogarten, Stephanie M; Conomos, Matthew P; Heavner, Ben; Hu, Yao; Kooperberg, Charles; Haessler, Jeffrey; Vasan, Ramachandran S; et al. (HGG Adv, 2021)
Whole-genome sequencing (WGS) and whole-exome sequencing studies have become increasingly available and are being used to identify rare genetic variants associated with health and disease outcomes. Investigators routinely use mixed models to account for genetic relatedness or other clustering variables (e.g., family or household) when testing genetic associations. However, no existing tests of the association of a rare variant with a binary outcome in the presence of correlated data control the type 1 error where there are (1) few individuals harboring the rare allele, (2) a small proportion of cases relative to controls, and (3) covariates to adjust for. Here, we address all three issues in developing a framework for testing rare variant association with a binary trait in individuals harboring at least one risk allele. In this framework, we estimate outcome probabilities under the null hypothesis and then use them, within the individuals with at least one risk allele, to test variant associations. We extend the BinomiRare test, which was previously proposed for independent observations, and develop the Conway-Maxwell-Poisson (CMP) test and study their properties in simulations. We show that the BinomiRare test always controls the type 1 error, while the CMP test sometimes does not. We then use the BinomiRare test to test the association of rare genetic variants in target genes with small-vessel disease (SVD) stroke, short sleep, and venous thromboembolism (VTE), in whole-genome sequence data from the Trans-Omics for Precision Medicine (TOPMed) program.

Chromosome Xq23 is associated with lower atherogenic lipid concentrations and favorable cardiometabolic indices. - Natarajan, Pradeep; Pampana, Akhil; Graham, Sarah E; Ruotsalainen, Sanni E; Perry, James A; de Vries, Paul S; Broome, Jai G; Pirruccello, James P; Honigberg, Michael C; Aragam, Krishna; Wolford, Brooke; Brody, Jennifer A; et al. (Nat Commun, 2021)
Autosomal genetic analyses of blood lipids have yielded key insights for coronary heart disease (CHD). However, X chromosome genetic variation is understudied for blood lipids in large sample sizes. We now analyze genetic and blood lipid data in a high-coverage whole X chromosome sequencing study of 65,322 multi-ancestry participants and perform replication among 456,893 European participants. Common alleles on chromosome Xq23 are strongly associated with reduced total cholesterol, LDL cholesterol, and triglycerides (min P = 8.5 × 10), with similar effects for males and females. Chromosome Xq23 lipid-lowering alleles are associated with reduced odds for CHD among 42,545 cases and 591,247 controls (P = 1.7 × 10), and reduced odds for diabetes mellitus type 2 among 54,095 cases and 573,885 controls (P = 1.4 × 10). Although we observe an association with increased BMI, waist-to-hip ratio adjusted for BMI is reduced, bioimpedance analyses indicate increased gluteofemoral fat, and abdominal MRI analyses indicate reduced visceral adiposity. Co-localization analyses strongly correlate increased CHRDL1 gene expression, particularly in adipose tissue, with reduced concentrations of blood lipids.
Keywords: Cardiometabolic Risk Factors; Chromosomes, Human, X; Eye Proteins; Female; Gene Expression Regulation; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genotype; Humans; Lipids; Male; Middle Aged; Nerve Tissue Proteins; Phenomics; Polymorphism, Single Nucleotide; Subcutaneous Tissue; Whole Genome Sequencing

Common variants in Alzheimer's disease and risk stratification by polygenic risk scores. - de Rojas, Itziar; Moreno-Grau, Sonia; Tesi, Niccolo; Grenier-Boley, Benjamin; Andrade, Victor; Jansen, Iris E; Pedersen, Nancy L; Stringa, Najada; Zettergren, Anna; Hernández, Isabel; Montrreal, Laura; Antúnez, Carmen; et al. (Nat Commun, 2021)
Genetic discoveries of Alzheimer's disease are the drivers of our understanding, and together with polygenetic risk stratification can contribute towards planning of feasible and efficient preventive and curative clinical trials. We first perform a large genetic association study by merging all available case-control datasets and by-proxy study results (discovery n = 409,435 and validation size n = 58,190). Here, we add six variants associated with Alzheimer's disease risk (near APP, CHRNE, PRKD3/NDUFAF7, PLCG2 and two exonic variants in the SHARPIN gene). Assessment of the polygenic risk score and stratifying by APOE reveal a 4 to 5.5 years difference in median age at onset of Alzheimer's disease patients in APOE ɛ4 carriers. Because of this study, the underlying mechanisms of APP can be studied to refine the amyloid cascade and the polygenic risk score provides a tool to select individuals at high risk of Alzheimer's disease.
Keywords: Age of Onset; Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Protein Precursor; Apolipoproteins E; Case-Control Studies; Cohort Studies; Datasets as Topic; Female; Follow-Up Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Heterozygote; Humans; Male; Middle Aged; Multifactorial Inheritance; Polymorphism, Single Nucleotide; Risk Assessment; Risk Factors

Determinants of penetrance and variable expressivity in monogenic metabolic conditions across 77,184 exomes. - Goodrich, Julia K; Singer-Berk, Moriel; Son, Rachel; Sveden, Abigail; Wood, Jordan; England, Eleina; Cole, Joanne B; Weisburd, Ben; Watts, Nick; Caulkins, Lizz; Dornbos, Peter; Koesterer, Ryan; et al. (Nat Commun, 2021)
Hundreds of thousands of genetic variants have been reported to cause severe monogenic diseases, but the probability that a variant carrier develops the disease (termed penetrance) is unknown for virtually all of them. Additionally, the clinical utility of common polygenetic variation remains uncertain. Using exome sequencing from 77,184 adult individuals (38,618 multi-ancestral individuals from a type 2 diabetes case-control study and 38,566 participants from the UK Biobank, for whom genotype array data were also available), we apply clinical standard-of-care gene variant curation for eight monogenic metabolic conditions. Rare variants causing monogenic diabetes and dyslipidemias display effect sizes significantly larger than the top 1% of the corresponding polygenic scores. Nevertheless, penetrance estimates for monogenic variant carriers average 60% or lower for most conditions. We assess epidemiologic and genetic factors contributing to risk prediction in monogenic variant carriers, demonstrating that inclusion of polygenic variation significantly improves biomarker estimation for two monogenic dyslipidemias.
Keywords: Adult; Biological Variation, Population; Biomarkers; Diabetes Mellitus, Type 2; Dyslipidemias; Exome; Genetic Predisposition to Disease; Genotype; Humans; Multifactorial Inheritance; Penetrance; Risk Assessment

Epigenome-wide association study of mitochondrial genome copy number. - Wang, Penglong; Castellani, Christina A; Yao, Jie; Huan, Tianxiao; Bielak, Lawrence F; Zhao, Wei; Haessler, Jeffrey; Joehanes, Roby; Sun, Xianbang; Guo, Xiuqing; Longchamps, Ryan J; Manson, JoAnn E; et al. (Hum Mol Genet, 2021)
We conducted cohort- and race-specific epigenome-wide association analyses of mitochondrial deoxyribonucleic acid (mtDNA) copy number (mtDNA CN) measured in whole blood from participants of African and European origins in five cohorts (n = 6182, mean age = 57-67 years, 65% women). In the meta-analysis of all the participants, we discovered 21 mtDNA CN-associated DNA methylation sites (CpG) (P < 1 × 10-7), with a 0.7-3.0 standard deviation increase (3 CpGs) or decrease (18 CpGs) in mtDNA CN corresponding to a 1% increase in DNA methylation. Several significant CpGs have been reported to be associated with at least two risk factors (e.g. chronological age or smoking) for cardiovascular disease (CVD). Five genes [PR/SET domain 16, nuclear receptor subfamily 1 group H member 3 (NR1H3), DNA repair protein, DNA polymerase kappa and decaprenyl-diphosphate synthase subunit 2], which harbor nine significant CpGs, are known to be involved in mitochondrial biosynthesis and functions. For example, NR1H3 encodes a transcription factor that is differentially expressed during an adipose tissue transition. The methylation level of cg09548275 in NR1H3 was negatively associated with mtDNA CN (effect size = -1.71, P = 4 × 10-8) and was positively associated with the NR1H3 expression level (effect size = 0.43, P = 0.0003), which indicates that the methylation level in NR1H3 may underlie the relationship between mtDNA CN, the NR1H3 transcription factor and energy expenditure. In summary, the study results suggest that mtDNA CN variation in whole blood is associated with DNA methylation levels in genes that are involved in a wide range of mitochondrial activities. These findings will help reveal molecular mechanisms between mtDNA CN and CVD.
Keywords: Aged; DNA Copy Number Variations; DNA Methylation; DNA, Mitochondrial; Epigenome; Female; Genome, Mitochondrial; Humans; Male; Middle Aged

Exome sequence association study of levels and longitudinal change of cardiovascular risk factor phenotypes in European Americans and African Americans from the Atherosclerosis Risk in Communities Study. - Feofanova, Elena V; Lim, Elise; Chen, Han; Lee, MinJae; Liu, Ching-Ti; Cupples, L Adrienne; Eric Boerwinkle (Genet Epidemiol, 2021)
Cardiovascular disease (CVD) is responsible for 31% of all deaths worldwide. Among CVD risk factors are age, race, increased systolic blood pressure (BP), and dyslipidemia. Both BP and blood lipids levels change with age, with a dose-dependent relationship between the cumulative exposure to hyperlipidemia and the risk of CVD. We performed an exome sequence association study using longitudinal data with up to 7805 European Americans (EAs) and 3171 African Americans (AAs) from the Atherosclerosis Risk in Communities (ARIC) study. We assessed associations of common (minor allele frequency > 5%) nonsynonymous and splice-site variants and gene-based sets of rare variants with levels and with longitudinal change of seven CVD risk factor phenotypes (BP traits: systolic BP, diastolic BP, pulse pressure; lipids traits: triglycerides, total cholesterol, high-density lipoprotein cholesterol [HDL-C], low-density lipoprotein cholesterol [LDL-C]). Furthermore, we investigated the relationship of the identified variants and genes with select CVD endpoints. We identified two novel genes: DCLK3 associated with the change of HDL-C levels in AAs and RAB7L1 associated with the change of LDL-C levels in EAs. RAB7L1 is further associated with an increased risk of heart failure in ARIC EAs. Investigation of the contribution of genetic factors to the longitudinal change of CVD risk factor phenotypes promotes our understanding of the etiology of CVD outcomes, stressing the importance of incorporating the longitudinal structure of the cohort data in future analyses.
Keywords: Atherosclerosis; Black or African American; Cardiovascular Diseases; Exome; Heart Disease Risk Factors; Humans; Phenotype; Risk Factors

Gene-educational attainment interactions in a multi-ancestry genome-wide meta-analysis identify novel blood pressure loci. - de Las Fuentes, Lisa; Sung, Yun Ju; Noordam, Raymond; Winkler, Thomas; Feitosa, Mary F; Schwander, Karen; Bentley, Amy R; Brown, Michael R; Guo, Xiuqing; Manning, Alisa; Chasman, Daniel I; Aschard, Hugues; et al. (Mol Psychiatry, 2021)
Educational attainment is widely used as a surrogate for socioeconomic status (SES). Low SES is a risk factor for hypertension and high blood pressure (BP). To identify novel BP loci, we performed multi-ancestry meta-analyses accounting for gene-educational attainment interactions using two variables, "Some College" (yes/no) and "Graduated College" (yes/no). Interactions were evaluated using both a 1 degree of freedom (DF) interaction term and a 2DF joint test of genetic and interaction effects. Analyses were performed for systolic BP, diastolic BP, mean arterial pressure, and pulse pressure. We pursued genome-wide interrogation in Stage 1 studies (N = 117 438) and follow-up on promising variants in Stage 2 studies (N = 293 787) in five ancestry groups. Through combined meta-analyses of Stages 1 and 2, we identified 84 known and 18 novel BP loci at genome-wide significance level (P < 5 × 10). Two novel loci were identified based on the 1DF test of interaction with educational attainment, while the remaining 16 loci were identified through the 2DF joint test of genetic and interaction effects. Ten novel loci were identified in individuals of African ancestry. Several novel loci show strong biological plausibility since they involve physiologic systems implicated in BP regulation. They include genes involved in the central nervous system-adrenal signaling axis (ZDHHC17, CADPS, PIK3C2G), vascular structure and function (GNB3, CDON), and renal function (HAS2 and HAS2-AS1, SLIT3). Collectively, these findings suggest a role of educational attainment or SES in further dissection of the genetic architecture of BP.
Keywords: Blood Pressure; Epistasis, Genetic; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Polymorphism, Single Nucleotide

Genetic susceptibility, obesity and lifetime risk of type 2 diabetes: The ARIC study and Rotterdam Study. - Ligthart, Symen; Hasbani, Natalie R; Ahmadizar, Fariba; van Herpt, Thijs T W; Leening, Maarten J G; Uitterlinden, André G; Sijbrands, Eric J G; Morrison, Alanna C; Eric Boerwinkle; Pankow, James S; Selvin, Elizabeth; Ikram, M Arfan; et al. (Diabet Med, 2021)
AIMS: Both lifestyle factors and genetic background contribute to the development of type 2 diabetes. Estimation of the lifetime risk of diabetes based on genetic information has not been presented, and the extent to which a normal body weight can offset a high lifetime genetic risk is unknown. METHODS: We used data from 15,671 diabetes-free participants of European ancestry aged 45 years and older from the prospective population-based ARIC study and Rotterdam Study (RS). We quantified the remaining lifetime risk of diabetes stratified by genetic risk and quantified the effect of normal weight in terms of relative and lifetime risks in low, intermediate and high genetic risk. RESULTS: At age 45 years, the lifetime risk of type 2 diabetes in ARIC in the low, intermediate and high genetic risk category was 33.2%, 41.3% and 47.2%, and in RS 22.8%, 30.6% and 35.5% respectively. The absolute lifetime risk for individuals with normal weight compared to individuals with obesity was 24% lower in ARIC and 8.6% lower in RS in the low genetic risk group, 36.3% lower in ARIC and 31.3% lower in RS in the intermediate genetic risk group, and 25.0% lower in ARIC and 29.4% lower in RS in the high genetic risk group. CONCLUSIONS: Genetic variants for type 2 diabetes have value in estimating the lifetime risk of type 2 diabetes. Normal weight mitigates partly the deleterious effect of high genetic risk.
Keywords: Aged; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Life Style; Male; Middle Aged; Multifactorial Inheritance; Obesity; Risk; White People

Genetic testing in ambulatory cardiology clinics reveals high rate of findings with clinical management implications. - David R Murdock; Eric Venner; Donna M Muzny; Ginger A Metcalf; Mullai Murugan; Hadley, Trevor D; Chander, Varuna; de Vries, Paul S; Jia, Xiaoming; Hussain, Aliza; Agha, Ali M; Aniko Sabo; et al. (Genet Med, 2021)
PURPOSE: Cardiovascular disease (CVD) is the leading cause of death in adults in the United States, yet the benefits of genetic testing are not universally accepted. METHODS: We developed the "HeartCare" panel of genes associated with CVD, evaluating high-penetrance Mendelian conditions, coronary artery disease (CAD) polygenic risk, LPA gene polymorphisms, and specific pharmacogenetic (PGx) variants. We enrolled 709 individuals from cardiology clinics at Baylor College of Medicine, and samples were analyzed in a CAP/CLIA-certified laboratory. Results were returned to the ordering physician and uploaded to the electronic medical record. RESULTS: Notably, 32% of patients had a genetic finding with clinical management implications, even after excluding PGx results, including 9% who were molecularly diagnosed with a Mendelian condition. Among surveyed physicians, 84% reported medical management changes based on these results, including specialist referrals, cardiac tests, and medication changes. LPA polymorphisms and high polygenic risk of CAD were found in 20% and 9% of patients, respectively, leading to diet, lifestyle, and other changes. Warfarin and simvastatin pharmacogenetic variants were present in roughly half of the cohort. CONCLUSION: Our results support the use of genetic information in routine cardiovascular health management and provide a roadmap for accompanying research.
Keywords: Adult; Cardiology; Cardiovascular Diseases; Genetic Testing; Humans; Pharmacogenetics; Pharmacogenomic Testing; United States

Genetically determined NLRP3 inflammasome activation associates with systemic inflammation and cardiovascular mortality. - Schunk, Stefan J; Kleber, Marcus E; Marz, Winfried; Pang, Shichao; Zewinger, Stephen; Triem, Sarah; Ege, Philipp; Reichert, Matthias C; Krawczyk, Marcin; Weber, Susanne N; Jaumann, Isabella; Schmit, David; et al. (Eur Heart J, 2021)
AIMS: Inflammation plays an important role in cardiovascular disease (CVD) development. The NOD-like receptor protein-3 (NLRP3) inflammasome contributes to the development of atherosclerosis in animal models. Components of the NLRP3 inflammasome pathway such as interleukin-1β can therapeutically be targeted. Associations of genetically determined inflammasome-mediated systemic inflammation with CVD and mortality in humans are unknown. METHODS AND RESULTS: We explored the association of genetic NLRP3 variants with prevalent CVD and cardiovascular mortality in 538 167 subjects on the individual participant level in an explorative gene-centric approach without performing multiple testing. Functional relevance of single-nucleotide polymorphisms on NLRP3 inflammasome activation has been evaluated in monocyte-enriched peripheral blood mononuclear cells (PBMCs). Genetic analyses identified the highly prevalent (minor allele frequency 39.9%) intronic NLRP3 variant rs10754555 to affect NLRP3 gene expression. rs10754555 carriers showed significantly higher C-reactive protein and serum amyloid A plasma levels. Carriers of the G allele showed higher NLRP3 inflammasome activation in isolated human PBMCs. In carriers of the rs10754555 variant, the prevalence of coronary artery disease was significantly higher as compared to non-carriers with a significant interaction between rs10754555 and age. Importantly, rs10754555 carriers had significantly higher risk for cardiovascular mortality during follow-up. Inflammasome inducers (e.g. urate, triglycerides, apolipoprotein C3) modulated the association between rs10754555 and mortality. CONCLUSION: The NLRP3 intronic variant rs10754555 is associated with increased systemic inflammation, inflammasome activation, prevalent coronary artery disease, and mortality. This study provides evidence for a substantial role of genetically driven systemic inflammation in CVD and highlights the NLRP3 inflammasome as a therapeutic target.
Keywords: Cardiovascular Diseases; Humans; Inflammasomes; Inflammation; Leukocytes, Mononuclear; NLR Family, Pyrin Domain-Containing 3 Protein

Genome-wide association study of circulating interleukin 6 levels identifies novel loci. - Ahluwalia, Tarunveer S; Prins, Bram P; Abdollahi, Mohammadreza; Armstrong, Nicola J; Aslibekyan, Stella; Bain, Lisa; Jefferis, Barbara; Baumert, Jens; Beekman, Marian; Ben-Shlomo, Yoav; Bis, Joshua C; Mitchell, Braxton D; et al. (Hum Mol Genet, 2021)
Interleukin 6 (IL-6) is a multifunctional cytokine with both pro- and anti-inflammatory properties with a heritability estimate of up to 61%. The circulating levels of IL-6 in blood have been associated with an increased risk of complex disease pathogenesis. We conducted a two-staged, discovery and replication meta genome-wide association study (GWAS) of circulating serum IL-6 levels comprising up to 67 428 (ndiscovery = 52 654 and nreplication = 14 774) individuals of European ancestry. The inverse variance fixed effects based discovery meta-analysis, followed by replication led to the identification of two independent loci, IL1F10/IL1RN rs6734238 on chromosome (Chr) 2q14, (Pcombined = 1.8 × 10-11), HLA-DRB1/DRB5 rs660895 on Chr6p21 (Pcombined = 1.5 × 10-10) in the combined meta-analyses of all samples. We also replicated the IL6R rs4537545 locus on Chr1q21 (Pcombined = 1.2 × 10-122). Our study identifies novel loci for circulating IL-6 levels uncovering new immunological and inflammatory pathways that may influence IL-6 pathobiology.
Keywords: Cohort Studies; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; HLA-DRB1 Chains; Humans; Interleukin 1 Receptor Antagonist Protein; Interleukin-1; Interleukin-6; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; White People

Genome-wide meta-analysis of muscle weakness identifies 15 susceptibility loci in older men and women. - Jones, Garan; Trajanoska, Katerina; Santanasto, Adam J; Stringa, Najada; Kuo, Chia-Ling; Atkins, Janice L; Lewis, Joshua R; Duong, ThuyVy; Hong, Shengjun; Biggs, Mary L; Luan, Jian'an; Sarnowski, Chloe; et al. (Nat Commun, 2021)
Low muscle strength is an important heritable indicator of poor health linked to morbidity and mortality in older people. In a genome-wide association study meta-analysis of 256,523 Europeans aged 60 years and over from 22 cohorts we identify 15 loci associated with muscle weakness (European Working Group on Sarcopenia in Older People definition: n = 48,596 cases, 18.9% of total), including 12 loci not implicated in previous analyses of continuous measures of grip strength. Loci include genes reportedly involved in autoimmune disease (HLA-DQA1 p = 4 × 10), arthritis (GDF5 p = 4 × 10), cell cycle control and cancer protection, regulation of transcription, and others involved in the development and maintenance of the musculoskeletal system. Using Mendelian randomization we report possible overlapping causal pathways, including diabetes susceptibility, haematological parameters, and the immune system. We conclude that muscle weakness in older adults has distinct mechanisms from continuous strength, including several pathways considered to be hallmarks of ageing.
Keywords: Aged; Aged, 80 and over; Aging; Cohort Studies; Europe; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Growth Differentiation Factor 5; HLA-DQ alpha-Chains; Humans; Male; Middle Aged; Muscle Strength; Muscle Weakness; Polymorphism, Single Nucleotide; Sarcopenia

Germline Cancer Predisposition Variants in Pediatric Rhabdomyosarcoma: A Report From the Children's Oncology Group. - Li, He; Sisoudiya, Saumya D; Martin-Giacalone, Bailey A; Khayat, Michael M; Dugan-Perez, Shannon; Marquez-Do, Deborah A; Scheurer, Michael E; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Chi, Yueh-Yun; Barkauskas, Donald A; et al. (J Natl Cancer Inst, 2021)
BACKGROUND: Several cancer-susceptibility syndromes are reported to underlie pediatric rhabdomyosarcoma (RMS); however, to our knowledge there have been no systematic efforts to characterize the heterogeneous genetic etiologies of this often-fatal malignancy. METHODS: We performed exome-sequencing on germline DNA from 615 patients with newly diagnosed RMS consented through the Children's Oncology Group. We compared the prevalence of cancer predisposition variants in 63 autosomal-dominant cancer predisposition genes in these patients with population controls (n = 9963). All statistical tests were 2-sided. RESULTS: We identified germline cancer predisposition variants in 45 RMS patients (7.3%; all FOXO1 fusion negative) across 15 autosomal dominant genes, which was statistically significantly enriched compared with controls (1.4%, P = 1.3 × 10-22). Specifically, 73.3% of the predisposition variants were found in predisposition syndrome genes previously associated with pediatric RMS risk, such as Li-Fraumeni syndrome (TP53) and neurofibromatosis type I (NF1). Notably, 5 patients had well-described oncogenic missense variants in HRAS (p.G12V and p.G12S) associated with Costello syndrome. Also, genetic etiology differed with histology, as germline variants were more frequent in embryonal vs alveolar RMS patients (10.0% vs 3.0%, P = .02). Although patients with a cancer predisposition variant tended to be younger at diagnosis (P = 9.9 × 10-4), 40.0% of germline variants were identified in those older than 3 years of age, which is in contrast to current genetic testing recommendations based on early age at diagnosis. CONCLUSIONS: These findings demonstrate that genetic risk of RMS results from germline predisposition variants associated with a wide spectrum of cancer susceptibility syndromes. Germline genetic testing for children with RMS should be informed by RMS subtypes and not be limited to only young patients.
Keywords: Child; Genetic Predisposition to Disease; Germ Cells; Germ-Line Mutation; Humans; Li-Fraumeni Syndrome; Rhabdomyosarcoma

The Implementation Science for Genomic Health Translation (INSIGHT) Study in Epilepsy: Protocol for a Learning Health Care System. - Feofanova, Elena Valeryevna; Zhang, Guo-Qiang; Lhatoo, Samden; Ginger A Metcalf; Eric Boerwinkle; Eric Venner (JMIR Res Protoc, 2021)
BACKGROUND: Genomic medicine is poised to improve care for common complex diseases such as epilepsy, but additional clinical informatics and implementation science research is needed for it to become a part of the standard of care. Epilepsy is an exemplary complex neurological disorder for which DNA diagnostics have shown to be advantageous for patient care. OBJECTIVE: We designed the Implementation Science for Genomic Health Translation (INSIGHT) study to leverage the fact that both the clinic and testing laboratory control the development and customization of their respective electronic health records and clinical reporting platforms. Through INSIGHT, we can rapidly prototype and benchmark novel approaches to incorporating clinical genomics into patient care. Of particular interest are clinical decision support tools that take advantage of domain knowledge from clinical genomics and can be rapidly adjusted based on feedback from clinicians. METHODS: Building on previously developed evidence and infrastructure components, our model includes the following: establishment of an intervention-ready genomic knowledge base for patient care, creation of a health informatics platform and linking it to a clinical genomics reporting system, and scaling and evaluation of INSIGHT following established implementation science principles. RESULTS: INSIGHT was approved by the Institutional Review Board at the University of Texas Health Science Center at Houston on May 15, 2020, and is designed as a 2-year proof-of-concept study beginning in December 2021. By design, 120 patients from the Texas Comprehensive Epilepsy Program are to be enrolled to test the INSIGHT workflow. Initial results are expected in the first half of 2023. CONCLUSIONS: INSIGHT's domain-specific, practical but generalizable approach may help catalyze a pathway to accelerate translation of genomic knowledge into impactful interventions in patient care. INTERNATIONAL REGISTERED REPORT IDENTIFIER (IRRID): PRR1-10.2196/25576.

Large-scale plasma proteomic analysis identifies proteins and pathways associated with dementia risk. - Walker, Keenan A; Chen, Jingsha; Zhang, Jingning; Fornage, Myriam; Yang, Yunju; Zhou, Linda; Grams, Morgan E; Tin, Adrienne; Daya, Natalie; Hoogeveen, Ron C; Wu, Aozhou; Sullivan, Kevin J; et al. (Nat Aging, 2021)
The plasma proteomic changes that precede the onset of dementia could yield insights into disease biology and highlight new biomarkers and avenues for intervention. We quantified 4,877 plasma proteins in nondemented older adults in the Atherosclerosis Risk in Communities cohort and performed a proteome-wide association study of dementia risk over five years (n = 4,110; 428 incident cases). Thirty-eight proteins were associated with incident dementia after Bonferroni correction. Of these, 16 were also associated with late-life dementia risk when measured in plasma collected nearly 20 years earlier, during mid-life. Two-sample Mendelian randomization causally implicated two dementia-associated proteins (SVEP1 and angiostatin) in Alzheimer's disease. SVEP1, an immunologically relevant cellular adhesion protein, was found to be part of larger dementia-associated protein networks, and circulating levels were associated with atrophy in brain regions vulnerable to Alzheimer's pathology. Pathway analyses for the broader set of dementia-associated proteins implicated immune, lipid, metabolic signaling and hemostasis pathways in dementia pathogenesis.
Keywords: Aged; Alzheimer Disease; Brain; Humans; Proteome; Proteomics

Large-scale sequencing studies expand the known genetic architecture of Alzheimer's disease. - Xue, Diane; Bush, William S; Renton, Alan E; Marcora, Edoardo A; Bis, Joshua C; Kunkle, Brian W; Eric Boerwinkle; DeStefano, Anita L; Farrer, Lindsay; Goate, Alison; Mayeux, Richard; Pericak-Vance, Margaret; et al. (Alzheimers Dement (Amst), 2021)
INTRODUCTION: Genes implicated by genome-wide association studies and family-based studies of Alzheimer's disease (AD) are largely discordant. We hypothesized that genes identified by sequencing studies like the Alzheimer's Disease Sequencing Project (ADSP) may bridge this gap and highlight shared biological mechanisms. METHODS: We performed structured literature review of genes prioritized by ADSP studies, genes underlying familial dementias, and genes nominated by genome-wide association studies. Gene set enrichment analyses of each list identified enriched pathways. RESULTS: The genes prioritized by the ADSP, familial dementia studies, and genome-wide association studies minimally overlapped. Each gene set identified dozens of enriched pathways, several of which were shared (e.g., regulation of amyloid beta clearance). DISCUSSION: Alternative study designs provide unique insights into AD genetics. Shared pathways enriched by different genes highlight their relevance to AD pathogenesis, while the patterns of pathway enrichment unique to each gene set provide additional targets for functional studies.

Lifestyle Risk Score: handling missingness of individual lifestyle components in meta-analysis of gene-by-lifestyle interactions. - Xu, Hanfei; Schwander, Karen; Brown, Michael R; Wang, Wenyi; Waken, R J; Eric Boerwinkle; Cupples, L Adrienne; de Las Fuentes, Lisa; van Heemst, Diana; Osazuwa-Peters, Oyomoare; de Vries, Paul S; van Dijk, Ko Willems; et al. (Eur J Hum Genet, 2021)
Recent studies consider lifestyle risk score (LRS), an aggregation of multiple lifestyle exposures, in identifying association of gene-lifestyle interaction with disease traits. However, not all cohorts have data on all lifestyle factors, leading to increased heterogeneity in the environmental exposure in collaborative meta-analyses. We compared and evaluated four approaches (Naïve, Safe, Complete and Moderator Approaches) to handle the missingness in LRS-stratified meta-analyses under various scenarios. Compared to "benchmark" results with all lifestyle factors available for all cohorts, the Complete Approach, which included only cohorts with all lifestyle components, was underpowered due to lower sample size, and the Naïve Approach, which utilized all available data and ignored the missingness, was slightly inflated. The Safe Approach, which used all data in LRS-exposed group and only included cohorts with all lifestyle factors available in the LRS-unexposed group, and the Moderator Approach, which handled missingness via moderator meta-regression, were both slightly conservative and yielded almost identical p values. We also evaluated the performance of the Safe Approach under different scenarios. We observed that the larger the proportion of cohorts without missingness included, the more accurate the results compared to "benchmark" results. In conclusion, we generally recommend the Safe Approach, a straightforward and non-inflated approach, to handle heterogeneity among cohorts in the LRS based genome-wide interaction meta-analyses.
Keywords: Cardiometabolic Risk Factors; Gene-Environment Interaction; Genome-Wide Association Study; Healthy Lifestyle; Humans; Hypertension; Obesity

muCNV: Genotyping Structural Variants for Population-level Sequencing. - Jun, Goo; Fritz J Sedlazeck; Zhu, Qihui; English, Adam; Ginger A Metcalf; Kang, Hyun Min; Lee, Charles; Richard A Gibbs; Eric Boerwinkle (Bioinformatics, 2021)
MOTIVATION: There are high demands for joint genotyping of structural variations with short-read sequencing, but efficient and accurate genotyping in population scale is a challenging task. RESULTS: We developed muCNV that aggregates per-sample summary pileups for joint genotyping of > 100,000 samples. Pilot results show very low Mendelian inconsistencies. Applications to large-scale projects in cloud show the computational efficiencies of muCNV genotyping pipeline. AVAILABILITY: muCNV is publicly available for download at: https://github.com/gjun/muCNV. SUPPLEMENTARY INFORMATION: Supplementary data are available at Bioinformatics online.

Multi-Ancestry Genome-wide Association Study Accounting for Gene-Psychosocial Factor Interactions Identifies Novel Loci for Blood Pressure Traits. - Sun, Daokun; Richard, Melissa; Musani, Solomon K; Sung, Yun Ju; Winkler, Thomas W; Schwander, Karen; Chai, Jin Fang; Guo, Xiuqing; Kilpeläinen, Tuomas O; Vojinovic, Dina; Aschard, Hugues; Bartz, Traci M; et al. (HGG Adv, 2021)
Psychological and social factors are known to influence blood pressure (BP) and risk of hypertension and associated cardiovascular diseases. To identify novel BP loci, we carried out genome-wide association meta-analyses of systolic, diastolic, pulse, and mean arterial BP taking into account the interaction effects of genetic variants with three psychosocial factors: depressive symptoms, anxiety symptoms, and social support. Analyses were performed using a two-stage design in a sample of up to 128,894 adults from 5 ancestry groups. In the combined meta-analyses of Stages 1 and 2, we identified 59 loci (p value <5e-8), including nine novel BP loci. The novel associations were observed mostly with pulse pressure, with fewer observed with mean arterial pressure. Five novel loci were identified in African ancestry, and all but one showed patterns of interaction with at least one psychosocial factor. Functional annotation of the novel loci supports a major role for genes implicated in the immune response (), synaptic function and neurotransmission (), as well as genes previously implicated in neuropsychiatric or stress-related disorders (). These findings underscore the importance of considering psychological and social factors in gene discovery for BP, especially in non-European populations.

Multi-ancestry genome-wide gene-sleep interactions identify novel loci for blood pressure. - Wang, Heming; Noordam, Raymond; Cade, Brian E; Schwander, Karen; Winkler, Thomas W; Lee, Jiwon; Sung, Yun Ju; Bentley, Amy R; Manning, Alisa K; Aschard, Hugues; Kilpeläinen, Tuomas O; Ilkov, Marjan; et al. (Mol Psychiatry, 2021)
Long and short sleep duration are associated with elevated blood pressure (BP), possibly through effects on molecular pathways that influence neuroendocrine and vascular systems. To gain new insights into the genetic basis of sleep-related BP variation, we performed genome-wide gene by short or long sleep duration interaction analyses on four BP traits (systolic BP, diastolic BP, mean arterial pressure, and pulse pressure) across five ancestry groups in two stages using 2 degree of freedom (df) joint test followed by 1df test of interaction effects. Primary multi-ancestry analysis in 62,969 individuals in stage 1 identified three novel gene by sleep interactions that were replicated in an additional 59,296 individuals in stage 2 (stage 1 + 2 P < 5 × 10), including rs7955964 (FIGNL2/ANKRD33) that increases BP among long sleepers, and rs73493041 (SNORA26/C9orf170) and rs10406644 (KCTD15/LSM14A) that increase BP among short sleepers (P < 5 × 10). Secondary ancestry-specific analysis identified another novel gene by long sleep interaction at rs111887471 (TRPC3/KIAA1109) in individuals of African ancestry (P = 2 × 10). Combined stage 1 and 2 analyses additionally identified significant gene by long sleep interactions at 10 loci including MKLN1 and RGL3/ELAVL3 previously associated with BP, and significant gene by short sleep interactions at 10 loci including C2orf43 previously associated with BP (P < 10). 2df test also identified novel loci for BP after modeling sleep that has known functions in sleep-wake regulation, nervous and cardiometabolic systems. This study indicates that sleep and primary mechanisms regulating BP may interact to elevate BP level, suggesting novel insights into sleep-related BP regulation.
Keywords: Blood Pressure; Genetic Loci; Genome-Wide Association Study; Humans; Hypertension; Polymorphism, Single Nucleotide; Sleep

Physical Activity-Related Metabolites Are Associated with Mortality: Findings from the Atherosclerosis Risk in Communities (ARIC) Study. - Xu, Jun; Liu, Guning; Hegde, Sheila M; Palta, Priya; Eric Boerwinkle; Gabriel, Kelley P; Yu, Bing (Metabolites, 2021)
Habitual physical activity can diminish the risk of premature death. Identifying a pattern of metabolites related to physical activity may advance our understanding of disease etiology. We quantified 245 serum metabolites in 3802 participants from the Atherosclerosis Risk in Communities (ARIC) study using chromatography-mass spectrometry. We regressed self-reported moderate-to-vigorous intensity leisure-time physical activity (LTPA) against each metabolite, adjusting for traditional risk factors. A standardized metabolite risk score (MRS) was constructed to examine its association with all-cause mortality using the Cox proportional hazard model. We identified 10 metabolites associated with LTPA ( < 2.04 × 10) and established that an increase of one unit of the metabolic equivalent of task-hours per week (MET·hr·wk) in LTPA was associated with a 0.012 SD increase in MRS. During a median of 27.5 years of follow-up, we observed 1928 deaths. One SD increase of MRS was associated with a 10% lower risk of death (HR = 0.90, 95% CI: 0.85-0.95). The highest vs. the lowest MRS quintile rank was associated with a 22% reduced risk of death (HR = 0.78, 95% CI: 0.62-0.94). The effects were consistent across race and sex groups. In summary, we identified a set of metabolites associated with LTPA and an MRS associated with a lower risk of death. Our study provides novel insights into the potential mechanisms underlying the health impacts of physical activity.

Plasma amyloid β levels are driven by genetic variants near APOE, BACE1, APP, PSEN2: A genome-wide association study in over 12,000 non-demented participants. - Damotte, Vincent; van der Lee, Sven J; Chouraki, Vincent; Grenier-Boley, Benjamin; Simino, Jeannette; Adams, Hieab; Tosto, Giuseppe; White, Charles; Terzikhan, Natalie; Cruchaga, Carlos; Knol, Maria J; Li, Shuo; et al. (Alzheimers Dement, 2021)
INTRODUCTION: There is increasing interest in plasma amyloid beta (Aβ) as an endophenotype of Alzheimer's disease (AD). Identifying the genetic determinants of plasma Aβ levels may elucidate important biological processes that determine plasma Aβ measures. METHODS: We included 12,369 non-demented participants from eight population-based studies. Imputed genetic data and measured plasma Aβ1-40, Aβ1-42 levels and Aβ1-42/Aβ1-40 ratio were used to perform genome-wide association studies, and gene-based and pathway analyses. Significant variants and genes were followed up for their association with brain positron emission tomography Aβ deposition and AD risk. RESULTS: Single-variant analysis identified associations with apolipoprotein E (APOE) for Aβ1-42 and Aβ1-42/Aβ1-40 ratio, and BACE1 for Aβ1-40. Gene-based analysis of Aβ1-40 additionally identified associations for APP, PSEN2, CCK, and ZNF397. There was suggestive evidence for interaction between a BACE1 variant and APOE ε4 on brain Aβ deposition. DISCUSSION: Identification of variants near/in known major Aβ-processing genes strengthens the relevance of plasma-Aβ levels as an endophenotype of AD.
Keywords: Alzheimer Disease; Amyloid; Amyloid beta-Protein Precursor; Amyloid Precursor Protein Secretases; Apolipoproteins E; Aspartic Acid Endopeptidases; Brain; Genome-Wide Association Study; Healthy Volunteers; Humans; Positron-Emission Tomography; Presenilin-2

Population sequencing data reveal a compendium of mutational processes in the human germ line. - Seplyarskiy, Vladimir B; Soldatov, Ruslan A; Koch, Evan; McGinty, Ryan J; Goldmann, Jakob M; Hernandez, Ryan D; Barnes, Kathleen; Correa, Adolfo; Burchard, Esteban G; Ellinor, Patrick T; McGarvey, Stephen T; Mitchell, Braxton D; et al. (Science, 2021)
Biological mechanisms underlying human germline mutations remain largely unknown. We statistically decompose variation in the rate and spectra of mutations along the genome using volume-regularized nonnegative matrix factorization. The analysis of a sequencing dataset (TOPMed) reveals nine processes that explain the variation in mutation properties between loci. We provide a biological interpretation for seven of these processes. We associate one process with bulky DNA lesions that are resolved asymmetrically with respect to transcription and replication. Two processes track direction of replication fork and replication timing, respectively. We identify a mutagenic effect of active demethylation primarily acting in regulatory regions and a mutagenic effect of long interspersed nuclear elements. We localize a mutagenic process specific to oocytes from population sequencing data. This process appears transcriptionally asymmetric.
Keywords: Algorithms; CpG Islands; DNA Damage; DNA Demethylation; DNA Mutational Analysis; DNA Replication; Genetic Variation; Genome, Human; Germ Cells; Germ-Line Mutation; Humans; Long Interspersed Nucleotide Elements; Mutagenesis; Oocytes; Transcription, Genetic

Proteins Associated with Risk of Kidney Function Decline in the General Population. - Grams, Morgan E; Surapaneni, Aditya; Chen, Jingsha; Zhou, Linda; Yu, Zhi; Dutta, Diptavo; Welling, Paul A; Chatterjee, Nilanjan; Zhang, Jingning; Arking, Dan E; Chen, Teresa K; Rebholz, Casey M; et al. (J Am Soc Nephrol, 2021)
BACKGROUND: Proteomic profiling may allow identification of plasma proteins that associate with subsequent changesin kidney function, elucidating biologic processes underlying the development and progression of CKD. METHODS: We quantified the association between 4877 plasma proteins and a composite outcome of ESKD or decline in eGFR by ≥50% among 9406 participants in the Atherosclerosis Risk in Communities (ARIC) Study (visit 3; mean age, 60 years) who were followed for a median of 14.4 years. We performed separate analyses for these proteins in a subset of 4378 participants (visit 5), who were followed at a later time point, for a median of 4.4 years. For validation, we evaluated proteins with significant associations (false discovery rate <5%) in both time periods in 3249 participants in the Chronic Renal Insufficiency Cohort (CRIC) and 703 participants in the African American Study of Kidney Disease and Hypertension (AASK). We also compared the genetic determinants of protein levels with those from a meta-analysis genome-wide association study of eGFR. RESULTS: In models adjusted for multiple covariates, including baseline eGFR and albuminuria, we identified 13 distinct proteins that were significantly associated with the composite end point in both time periods, including TNF receptor superfamily members 1A and 1B, trefoil factor 3, and -trace protein. Of these proteins, 12 were also significantly associated in CRIC, and nine were significantly associated in AASK. Higher levels of each protein associated with higher risk of 50% eGFR decline or ESKD. We found genetic evidence for a causal role for one protein, lectin mannose-binding 2 protein (LMAN2). CONCLUSIONS: Large-scale proteomic analysis identified both known and novel proteomic risk factors for eGFR decline.
Keywords: Age Factors; Aged; Cohort Studies; Female; Glomerular Filtration Rate; Humans; Male; Middle Aged; Proteomics; Renal Insufficiency, Chronic; Risk Factors

Publisher Correction: Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals. - Surendran, Praveen; Feofanova, Elena V; Lahrouchi, Najim; Ntalla, Ioanna; Karthikeyan, Savita; Cook, James; Chen, Lingyan; Mifsud, Borbala; Yao, Chen; Kraja, Aldi T; Cartwright, James H; Hellwege, Jacklyn N; et al. (Nat Genet, 2021)

Robust, flexible, and scalable tests for Hardy-Weinberg equilibrium across diverse ancestries. - Kwong, Alan M; Blackwell, Thomas W; LeFaive, Jonathon; de Andrade, Mariza; Barnard, John; Barnes, Kathleen C; Blangero, John; Eric Boerwinkle; Burchard, Esteban G; Cade, Brian E; Chasman, Daniel I; Chen, Han; et al. (Genetics, 2021)
Traditional Hardy-Weinberg equilibrium (HWE) tests (the χ2 test and the exact test) have long been used as a metric for evaluating genotype quality, as technical artifacts leading to incorrect genotype calls often can be identified as deviations from HWE. However, in data sets composed of individuals from diverse ancestries, HWE can be violated even without genotyping error, complicating the use of HWE testing to assess genotype data quality. In this manuscript, we present the Robust Unified Test for HWE (RUTH) to test for HWE while accounting for population structure and genotype uncertainty, and to evaluate the impact of population heterogeneity and genotype uncertainty on the standard HWE tests and alternative methods using simulated and real sequence data sets. Our results demonstrate that ignoring population structure or genotype uncertainty in HWE tests can inflate false-positive rates by many orders of magnitude. Our evaluations demonstrate different tradeoffs between false positives and statistical power across the methods, with RUTH consistently among the best across all evaluations. RUTH is implemented as a practical and scalable software tool to rapidly perform HWE tests across millions of markers and hundreds of thousands of individuals while supporting standard VCF/BCF formats. RUTH is publicly available at https://www.github.com/statgen/ruth.
Keywords: Alleles; Gene Frequency; Genetics, Population; Genotype; Humans; Linkage Disequilibrium; Models, Genetic; Models, Statistical; Phenotype; Software

Sequencing of 53,831 diverse genomes from the NHLBI TOPMed Program. - Taliun, Daniel; Harris, Daniel N; Kessler, Michael D; Carlson, Jedidiah; Szpiech, Zachary A; Torres, Raul; Taliun, Sarah A Gagliano; Corvelo, André; Gogarten, Stephanie M; Kang, Hyun Min; Pitsillides, Achilleas N; LeFaive, Jonathon; et al. (Nature, 2021)
The Trans-Omics for Precision Medicine (TOPMed) programme seeks to elucidate the genetic architecture and biology of heart, lung, blood and sleep disorders, with the ultimate goal of improving diagnosis, treatment and prevention of these diseases. The initial phases of the programme focused on whole-genome sequencing of individuals with rich phenotypic data and diverse backgrounds. Here we describe the TOPMed goals and design as well as the available resources and early insights obtained from the sequence data. The resources include a variant browser, a genotype imputation server, and genomic and phenotypic data that are available through dbGaP (Database of Genotypes and Phenotypes). In the first 53,831 TOPMed samples, we detected more than 400 million single-nucleotide and insertion or deletion variants after alignment with the reference genome. Additional previously undescribed variants were detected through assembly of unmapped reads and customized analysis in highly variable loci. Among the more than 400 million detected variants, 97% have frequencies of less than 1% and 46% are singletons that are present in only one individual (53% among unrelated individuals). These rare variants provide insights into mutational processes and recent human evolutionary history. The extensive catalogue of genetic variation in TOPMed studies provides unique opportunities for exploring the contributions of rare and noncoding sequence variants to phenotypic variation. Furthermore, combining TOPMed haplotypes with modern imputation methods improves the power and reach of genome-wide association studies to include variants down to a frequency of approximately 0.01%.
Keywords: Cytochrome P-450 CYP2D6; Genetic Variation; Genome, Human; Genomics; Haplotypes; Heterozygote; Humans; INDEL Mutation; Loss of Function Mutation; Mutagenesis; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Polymorphism, Single Nucleotide; Population Density; Precision Medicine; Quality Control; Sample Size; United States; Whole Genome Sequencing

The trans-ancestral genomic architecture of glycemic traits. - Chen, Ji; Spracklen, Cassandra N; Marenne, Gaëlle; Varshney, Arushi; Corbin, Laura J; Luan, Jian'an; Willems, Sara M; Wu, Ying; Zhang, Xiaoshuai; Horikoshi, Momoko; Boutin, Thibaud S; Mägi, Reedik; et al. (Nat Genet, 2021)
Glycemic traits are used to diagnose and monitor type 2 diabetes and cardiometabolic health. To date, most genetic studies of glycemic traits have focused on individuals of European ancestry. Here we aggregated genome-wide association studies comprising up to 281,416 individuals without diabetes (30% non-European ancestry) for whom fasting glucose, 2-h glucose after an oral glucose challenge, glycated hemoglobin and fasting insulin data were available. Trans-ancestry and single-ancestry meta-analyses identified 242 loci (99 novel; P < 5 × 10), 80% of which had no significant evidence of between-ancestry heterogeneity. Analyses restricted to individuals of European ancestry with equivalent sample size would have led to 24 fewer new loci. Compared with single-ancestry analyses, equivalent-sized trans-ancestry fine-mapping reduced the number of estimated variants in 99% credible sets by a median of 37.5%. Genomic-feature, gene-expression and gene-set analyses revealed distinct biological signatures for each trait, highlighting different underlying biological pathways. Our results increase our understanding of diabetes pathophysiology by using trans-ancestry studies for improved power and resolution.
Keywords: Alleles; Blood Glucose; Epigenesis, Genetic; Gene Expression Profiling; Genome, Human; Genome-Wide Association Study; Glycated Hemoglobin; Humans; Multifactorial Inheritance; Physical Chromosome Mapping; Quantitative Trait Loci; Quantitative Trait, Heritable; White People

Whole genome sequence analyses of eGFR in 23,732 people representing multiple ancestries in the NHLBI trans-omics for precision medicine (TOPMed) consortium. - Lin, Bridget M; Grinde, Kelsey E; Brody, Jennifer A; Breeze, Charles E; Raffield, Laura M; Mychaleckyj, Josyf C; Thornton, Timothy A; Perry, James A; Baier, Leslie J; de Las Fuentes, Lisa; Guo, Xiuqing; Heavner, Benjamin D; et al. (EBioMedicine, 2021)
BACKGROUND: Genetic factors that influence kidney traits have been understudied for low frequency and ancestry-specific variants. METHODS: We combined whole genome sequencing (WGS) data from 23,732 participants from 10 NHLBI Trans-Omics for Precision Medicine (TOPMed) Program multi-ethnic studies to identify novel loci for estimated glomerular filtration rate (eGFR). Participants included European, African, East Asian, and Hispanic ancestries. We applied linear mixed models using a genetic relationship matrix estimated from the WGS data and adjusted for age, sex, study, and ethnicity. FINDINGS: When testing single variants, we identified three novel loci driven by low frequency variants more commonly observed in non-European ancestry (PRKAA2, rs180996919, minor allele frequency [MAF] 0.04%, P = 6.1 × 10; METTL8, rs116951054, MAF 0.09%, P = 4.5 × 10; and MATK, rs539182790, MAF 0.05%, P = 3.4 × 10). We also replicated two known loci for common variants (rs2461702, MAF=0.49, P = 1.2 × 10, nearest gene GATM, and rs71147340, MAF=0.34, P = 3.3 × 10, CDK12). Testing aggregated variants within a gene identified the MAF gene. A statistical approach based on local ancestry helped to identify replication samples for ancestry-specific variants. INTERPRETATION: This study highlights challenges in studying variants influencing kidney traits that are low frequency in populations and more common in non-European ancestry.
Keywords: Alleles; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Glomerular Filtration Rate; Humans; Male; National Heart, Lung, and Blood Institute (U.S.); Polymorphism, Single Nucleotide; Precision Medicine; Public Health Surveillance; Quantitative Trait, Heritable; United States; Whole Genome Sequencing

Whole-genome association analyses of sleep-disordered breathing phenotypes in the NHLBI TOPMed program. - Cade, Brian E; Lee, Jiwon; Sofer, Tamar; Wang, Heming; Zhang, Man; Chen, Han; Gharib, Sina A; Gottlieb, Daniel J; Guo, Xiuqing; Lane, Jacqueline M; Liang, Jingjing; Lin, Xihong; et al. (Genome Med, 2021)
BACKGROUND: Sleep-disordered breathing is a common disorder associated with significant morbidity. The genetic architecture of sleep-disordered breathing remains poorly understood. Through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program, we performed the first whole-genome sequence analysis of sleep-disordered breathing. METHODS: The study sample was comprised of 7988 individuals of diverse ancestry. Common-variant and pathway analyses included an additional 13,257 individuals. We examined five complementary traits describing different aspects of sleep-disordered breathing: the apnea-hypopnea index, average oxyhemoglobin desaturation per event, average and minimum oxyhemoglobin saturation across the sleep episode, and the percentage of sleep with oxyhemoglobin saturation < 90%. We adjusted for age, sex, BMI, study, and family structure using MMSKAT and EMMAX mixed linear model approaches. Additional bioinformatics analyses were performed with MetaXcan, GIGSEA, and ReMap. RESULTS: We identified a multi-ethnic set-based rare-variant association (p = 3.48 × 10) on chromosome X with ARMCX3. Additional rare-variant associations include ARMCX3-AS1, MRPS33, and C16orf90. Novel common-variant loci were identified in the NRG1 and SLC45A2 regions, and previously associated loci in the IL18RAP and ATP2B4 regions were associated with novel phenotypes. Transcription factor binding site enrichment identified associations with genes implicated with respiratory and craniofacial traits. Additional analyses identified significantly associated pathways. CONCLUSIONS: We have identified the first gene-based rare-variant associations with objectively measured sleep-disordered breathing traits. Our results increase the understanding of the genetic architecture of sleep-disordered breathing and highlight associations in genes that modulate lung development, inflammation, respiratory rhythmogenesis, and HIF1A-mediated hypoxic response.
Keywords: Alleles; Chromatin Immunoprecipitation Sequencing; Female; Gene Expression Regulation; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Male; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Research; Signal Transduction; Sleep Apnea Syndromes; United States; Whole Genome Sequencing

Biallelic GRM7 variants cause epilepsy, microcephaly, and cerebral atrophy. - Marafi, Dana; Mitani, Tadahiro; Isikay, Sedat; Hertecant, Jozef; Almannai, Mohammed; Manickam, Kandamurugu; Abou Jamra, Rami; El-Hattab, Ayman W; Rajah, Jaishen; Fatih, Jawid M; Du, Haowei; Karaca, Ender; et al. (Ann Clin Transl Neurol, 2020)
OBJECTIVE: Defects in ion channels and neurotransmitter receptors are implicated in developmental and epileptic encephalopathy (DEE). Metabotropic glutamate receptor 7 (mGluR7), encoded by GRM7, is a presynaptic G-protein-coupled glutamate receptor critical for synaptic transmission. We previously proposed GRM7 as a candidate disease gene in two families with neurodevelopmental disorders (NDDs). One additional family has been published since. Here, we describe three additional families with GRM7 biallelic variants and deeply characterize the associated clinical neurological and electrophysiological phenotype and molecular data in 11 affected individuals from six unrelated families. METHODS: Exome sequencing and family-based rare variant analyses on a cohort of 220 consanguineous families with NDDs revealed three families with GRM7 biallelic variants; three additional families were identified through literature search and collaboration with a clinical molecular laboratory. RESULTS: We compared the observed clinical features and variants of 11 affected individuals from the six unrelated families. Identified novel deleterious variants included two homozygous missense variants (c.2671G>A:p.Glu891Lys and c.1973G>A:p.Arg685Gln) and one homozygous stop-gain variant (c.1975C>T:p.Arg659Ter). Developmental delay, neonatal- or infantile-onset epilepsy, and microcephaly were universal. Three individuals had hypothalamic-pituitary-axis dysfunction without pituitary structural abnormality. Neuroimaging showed cerebral atrophy and hypomyelination in a majority of cases. Two siblings demonstrated progressive loss of myelination by 2 years in both and an acquired microcephaly pattern in one. Five individuals died in early or late childhood. CONCLUSION: Detailed clinical characterization of 11 individuals from six unrelated families demonstrates that rare biallelic GRM7 pathogenic variants can cause DEEs, microcephaly, hypomyelination, and cerebral atrophy.
Keywords: Adolescent; Alleles; Atrophy; Child; Child, Preschool; Cohort Studies; Consanguinity; Epilepsy; Exome Sequencing; Female; Humans; Infant; Male; Microcephaly; Neurodevelopmental Disorders; Pedigree; Phenotype; Receptors, Metabotropic Glutamate

A bidirectional Mendelian randomization study supports causal effects of kidney function on blood pressure. - Yu, Zhi; Coresh, Josef; Qi, Guanghao; Grams, Morgan; Eric Boerwinkle; Snieder, Harold; Teumer, Alexander; Pattaro, Cristian; Köttgen, Anna; Chatterjee, Nilanjan; Tin, Adrienne (Kidney Int, 2020)
Blood pressure and kidney function have a bidirectional relation. Hypertension has long been considered as a risk factor for kidney function decline. However, whether intensive blood pressure control could promote kidney health has been uncertain. The kidney is known to have a major role in affecting blood pressure through sodium extraction and regulating electrolyte balance. This bidirectional relation makes causal inference between these two traits difficult. Therefore, to examine the causal relations between these two traits, we performed two-sample Mendelian randomization analyses using summary statistics of large-scale genome-wide association studies. We selected genetic instruments more likely to be specific for kidney function using meta-analyses of complementary kidney function biomarkers (glomerular filtration rate estimated from serum creatinine [eGFRcr], and blood urea nitrogen from the CKDGen Consortium). Systolic and diastolic blood pressure summary statistics were from the International Consortium for Blood Pressure and UK Biobank. Significant evidence supported the causal effects of higher kidney function on lower blood pressure. Based on the mode-based Mendelian randomization method, the effect estimates for one standard deviation (SD) higher in log-transformed eGFRcr was -0.17 SD unit (95 % confidence interval: -0.09 to -0.24) in systolic blood pressure and -0.15 SD unit (95% confidence interval: -0.07 to -0.22) in diastolic blood pressure. In contrast, the causal effects of blood pressure on kidney function were not statistically significant. Thus, our results support causal effects of higher kidney function on lower blood pressure and suggest preventing kidney function decline can reduce the public health burden of hypertension.
Keywords: Blood Pressure; Genome-Wide Association Study; Humans; Hypertension; Kidney; Mendelian Randomization Analysis

Cohort Profile: The Right Drug, Right Dose, Right Time: Using Genomic Data to Individualize Treatment Protocol (RIGHT Protocol). - Bielinski, Suzette J; St Sauver, Jennifer L; Olson, Janet E; Larson, Nicholas B; Black, John L; Steven E Scherer; Bernard, Matthew E; Eric Boerwinkle; Borah, Bijan J; Caraballo, Pedro J; Curry, Timothy B; Harshavardhan Doddapaneni; et al. (Int J Epidemiol, 2020)
Keywords: Clinical Protocols; Cohort Studies; Female; Genomics; Humans; Male; Pharmacogenetics; Precision Medicine

Correction: Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
A correction to this paper has been published and can be accessed via a link at the top of the paper.

Corrigendum to 'Association of sickle cell trait with measures of cognitive function and dementia in African Americans' Vol. 16 (2019), 100,201. - Chen, Nemin; Caruso, Christina; Alonso, Alvaro; Derebail, Vimal K; Kshirsagar, Abhijit V; Sharrett, A Richey; Key, Nigel S; Gottesman, Rebecca F; Grove, Megan L; Bressler, Jan; Eric Boerwinkle; Windham, B Gwen; et al. (eNeurologicalSci, 2020)
[This corrects the article DOI: 10.1016/j.ensci.2019.100201.].

A diagnostic ceiling for exome sequencing in cerebellar ataxia and related neurological disorders. - Ngo, Kathie J; Rexach, Jessica E; Lee, Hane; Petty, Lauren E; Perlman, Susan; Valera, Juliana M; Deignan, Joshua L; Mao, Yuanming; Aker, Mamdouh; Posey, Jennifer E; Jhangiani, Shalini N; Coban-Akdemir, Zeynep H; et al. (Hum Mutat, 2020)
Genetic ataxias are associated with mutations in hundreds of genes with high phenotypic overlap complicating the clinical diagnosis. Whole-exome sequencing (WES) has increased the overall diagnostic rate considerably. However, the upper limit of this method remains ill-defined, hindering efforts to address the remaining diagnostic gap. To further assess the role of rare coding variation in ataxic disorders, we reanalyzed our previously published exome cohort of 76 predominantly adult and sporadic-onset patients, expanded the total number of cases to 260, and introduced analyses for copy number variation and repeat expansion in a representative subset. For new cases (n = 184), our resulting clinically relevant detection rate remained stable at 47% with 24% classified as pathogenic. Reanalysis of the previously sequenced 76 patients modestly improved the pathogenic rate by 7%. For the combined cohort (n = 260), the total observed clinical detection rate was 52% with 25% classified as pathogenic. Published studies of similar neurological phenotypes report comparable rates. This consistency across multiple cohorts suggests that, despite continued technical and analytical advancements, an approximately 50% diagnostic rate marks a relative ceiling for current WES-based methods and a more comprehensive genome-wide assessment is needed to identify the missing causative genetic etiologies for cerebellar ataxia and related neurodegenerative diseases.
Keywords: Cerebellar Ataxia; DNA Copy Number Variations; Exome; Exome Sequencing; Genetic Association Studies; Genetic Linkage; Genetic Predisposition to Disease; Humans; Microsatellite Repeats; Nervous System Diseases

Discovery of rare variants associated with blood pressure regulation through meta-analysis of 1.3 million individuals. - Surendran, Praveen; Feofanova, Elena V; Lahrouchi, Najim; Ntalla, Ioanna; Karthikeyan, Savita; Cook, James; Chen, Lingyan; Mifsud, Borbala; Yao, Chen; Kraja, Aldi T; Cartwright, James H; Hellwege, Jacklyn N; et al. (Nat Genet, 2020)
Genetic studies of blood pressure (BP) to date have mainly analyzed common variants (minor allele frequency > 0.05). In a meta-analysis of up to ~1.3 million participants, we discovered 106 new BP-associated genomic regions and 87 rare (minor allele frequency ≤ 0.01) variant BP associations (P < 5 × 10), of which 32 were in new BP-associated loci and 55 were independent BP-associated single-nucleotide variants within known BP-associated regions. Average effects of rare variants (44% coding) were ~8 times larger than common variant effects and indicate potential candidate causal genes at new and known loci (for example, GATA5 and PLCB3). BP-associated variants (including rare and common) were enriched in regions of active chromatin in fetal tissues, potentially linking fetal development with BP regulation in later life. Multivariable Mendelian randomization suggested possible inverse effects of elevated systolic and diastolic BP on large artery stroke. Our study demonstrates the utility of rare-variant analyses for identifying candidate genes and the results highlight potential therapeutic targets.
Keywords: Blood Pressure; GATA5 Transcription Factor; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Hypertension; Mutation; Phospholipase C beta; Polymorphism, Single Nucleotide

Dynamic incorporation of multiple in silico functional annotations empowers rare variant association analysis of large whole-genome sequencing studies at scale. - Li, Xihao; Li, Zilin; Zhou, Hufeng; Gaynor, Sheila M; Liu, Yaowu; Chen, Han; Sun, Ryan; Dey, Rounak; Arnett, Donna K; Aslibekyan, Stella; Ballantyne, Christie M; Bielak, Lawrence F; et al. (Nat Genet, 2020)
Large-scale whole-genome sequencing studies have enabled the analysis of rare variants (RVs) associated with complex phenotypes. Commonly used RV association tests have limited scope to leverage variant functions. We propose STAAR (variant-set test for association using annotation information), a scalable and powerful RV association test method that effectively incorporates both variant categories and multiple complementary annotations using a dynamic weighting scheme. For the latter, we introduce 'annotation principal components', multidimensional summaries of in silico variant annotations. STAAR accounts for population structure and relatedness and is scalable for analyzing very large cohort and biobank whole-genome sequencing studies of continuous and dichotomous traits. We applied STAAR to identify RVs associated with four lipid traits in 12,316 discovery and 17,822 replication samples from the Trans-Omics for Precision Medicine Program. We discovered and replicated new RV associations, including disruptive missense RVs of NPC1L1 and an intergenic region near APOC1P1 associated with low-density lipoprotein cholesterol.
Keywords: Cholesterol, LDL; Computer Simulation; Genetic Predisposition to Disease; Genetic Variation; Genome; Genome-Wide Association Study; Humans; Models, Genetic; Molecular Sequence Annotation; Phenotype; Whole Genome Sequencing

Efficient gene-environment interaction tests for large biobank-scale sequencing studies. - Wang, Xinyu; Lim, Elise; Liu, Ching-Ti; Sung, Yun Ju; Rao, Dabeeru C; Morrison, Alanna C; Eric Boerwinkle; Manning, Alisa K; Chen, Han (Genet Epidemiol, 2020)
Complex human diseases are affected by genetic and environmental risk factors and their interactions. Gene-environment interaction (GEI) tests for aggregate genetic variant sets have been developed in recent years. However, existing statistical methods become rate limiting for large biobank-scale sequencing studies with correlated samples. We propose efficient Mixed-model Association tests for GEne-Environment interactions (MAGEE), for testing GEI between an aggregate variant set and environmental exposures on quantitative and binary traits in large-scale sequencing studies with related individuals. Joint tests for the aggregate genetic main effects and GEI effects are also developed. A null generalized linear mixed model adjusting for covariates but without any genetic effects is fit only once in a whole genome GEI analysis, thereby vastly reducing the overall computational burden. Score tests for variant sets are performed as a combination of genetic burden and variance component tests by accounting for the genetic main effects using matrix projections. The computational complexity is dramatically reduced in a whole genome GEI analysis, which makes MAGEE scalable to hundreds of thousands of individuals. We applied MAGEE to the exome sequencing data of 41,144 related individuals from the UK Biobank, and the analysis of 18,970 protein coding genes finished within 10.4 CPU hours.
Keywords: Biological Specimen Banks; Body Mass Index; Computer Simulation; Exome; Exome Sequencing; Female; Gene-Environment Interaction; Humans; Linear Models; Male; Models, Genetic; Obesity; Phenotype; Quantitative Trait, Heritable; Time Factors

Epigenetic Age Acceleration and Cognitive Function in African American Adults in Midlife: The Atherosclerosis Risk in Communities Study. - Bressler, Jan; Marioni, Riccardo E; Walker, Rosie M; Xia, Rui; Gottesman, Rebecca F; Windham, B Gwen; Grove, Megan L; Guan, Weihua; Pankow, James S; Evans, Kathryn L; McIntosh, Andrew M; Deary, Ian J; et al. (J Gerontol A Biol Sci Med Sci, 2020)
Methylation levels measured at defined sites across the genome have recently been shown to be correlated with an individual's chronological age. Age acceleration, or the difference between age estimated from DNA methylation status and chronological age, has been proposed as a novel biomarker of aging. In this study, the cross-sectional association between two different measures of age acceleration and cognitive function was investigated using whole blood samples from 2,157 African American participants 47-70 years of age in the population-based Atherosclerosis Risk in Communities (ARIC) Study. Cognition was evaluated using three domain-specific tests. A significant inverse association between a 1-year increase in age acceleration calculated using a blood-based age predictor and scores on the Word Fluency Test was found using a general linear model adjusted for chronological age, gender, and years of education (β = -0.140 words; p = .001) and after adding other potential confounding variables (β = -0.104 words, p = .023). The results were replicated in 1,670 European participants in the Generation Scotland: Scottish Family Health Study (fully adjusted model: β = -0.199 words; p = .034). A significant association was also identified in a trans-ethnic meta-analysis across cohorts that included an additional 708 European American ARIC study participants (fully adjusted model: β = -0.110 words, p = .003). There were no associations found using an estimate of age acceleration derived from multiple tissues. These findings provide evidence that age acceleration is a correlate of performance on a test of verbal fluency in middle-aged adults.
Keywords: Aged; Aging; Atherosclerosis; Black or African American; Cognition; Cross-Sectional Studies; Epigenesis, Genetic; Female; Humans; Male; Middle Aged; Risk Assessment; Time Factors

Evaluation of mitochondrial DNA copy number estimation techniques. - Longchamps, Ryan J; Castellani, Christina A; Yang, Stephanie Y; Newcomb, Charles E; Sumpter, Jason A; Lane, John; Grove, Megan L; Guallar, Eliseo; Pankratz, Nathan; Taylor, Kent D; Rotter, Jerome I; Eric Boerwinkle; et al. (PLoS One, 2020)
Mitochondrial DNA copy number (mtDNA-CN), a measure of the number of mitochondrial genomes per cell, is a minimally invasive proxy measure for mitochondrial function and has been associated with several aging-related diseases. Although quantitative real-time PCR (qPCR) is the current gold standard method for measuring mtDNA-CN, mtDNA-CN can also be measured from genotyping microarray probe intensities and DNA sequencing read counts. To conduct a comprehensive examination on the performance of these methods, we use known mtDNA-CN correlates (age, sex, white blood cell count, Duffy locus genotype, incident cardiovascular disease) to evaluate mtDNA-CN calculated from qPCR, two microarray platforms, as well as whole genome (WGS) and whole exome sequence (WES) data across 1,085 participants from the Atherosclerosis Risk in Communities (ARIC) study and 3,489 participants from the Multi-Ethnic Study of Atherosclerosis (MESA). We observe mtDNA-CN derived from WGS data is significantly more associated with known correlates compared to all other methods (p < 0.001). Additionally, mtDNA-CN measured from WGS is on average more significantly associated with traits by 5.6 orders of magnitude and has effect size estimates 5.8 times more extreme than the current gold standard of qPCR. We further investigated the role of DNA extraction method on mtDNA-CN estimate reproducibility and found mtDNA-CN estimated from cell lysate is significantly less variable than traditional phenol-chloroform-isoamyl alcohol (p = 5.44x10-4) and silica-based column selection (p = 2.82x10-7). In conclusion, we recommend the field moves towards more accurate methods for mtDNA-CN, as well as re-analyze trait associations as more WGS data becomes available from larger initiatives such as TOPMed.
Keywords: Aged; DNA, Mitochondrial; Female; Gene Dosage; Genomics; Humans; Male; Middle Aged

Genetic Burden Contributing to Extremely Low or High Bone Mineral Density in a Senior Male Population From the Osteoporotic Fractures in Men Study (MrOS). - Chen, Shan; Jain, Mahim; Jhangiani, Shalini; Akdemir, Zeynep C; Campeau, Philippe M; Klein, Robert F; Nielson, Carrie; Dai, Hongzheng; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Orwoll, Eric S; et al. (JBMR Plus, 2020)
Worldwide, one in five men aged over 50 years will experience osteoporosis or a clinical bone fracture, with a greater fracture-related mortality rate than women. However, the genetic etiology of osteoporosis in men is still poorly understood. We aimed to identify the genetic variants and candidate genes associated with extremely low or high BMD for a better understanding of the biology underlying low bone density that may point to potential therapeutic targets for increasing bone mass. Subjects from the Osteoporotic Fractures in Men Study (MrOS) cohort were evaluated by age and BMI-adjusted total hip BMD. Those with BMD values 3 SDs away from the mean were selected and the remaining individuals whose adjusted BMD ranked at the highest or lowest 100 were included. Men with the lowest adjusted BMD ( = 98) and highest adjusted BMD ( = 110) were chosen for exome sequencing. Controls ( = 82) were men of Northern and Western European descent from the US Utah population of the 1000 Genomes Project. Fisher's exact test was performed to compare low- or high-BMD subjects with controls for single-gene associations. Additionally, sets of candidate genes causative of heritable disorders of connective tissue, including osteogenesis imperfecta (OI) and Ehlers-Danlos syndrome (EDS), were grouped for multigene and mutation burden analyses. No single-gene associations with rare variants were found for either the low BMD group (33 genes) or high BMD group (18 genes). In the group of OI genes, we detected a significant threefold increased accumulation of rare variants in low-BMD subjects compared with controls ( = 0.009). Additionally, genes associated with EDS had a twofold increased frequency in low-BMD subjects compared with controls ( = 0.03). These findings reveal a rare variant burden in OI and EDS disease genes at low BMD, which suggests a potential gene-panel approach to screen for multivariant associations in larger cohorts. © 2019 The Authors. published by Wiley Periodicals, Inc. on behalf of American Society for Bone and Mineral Research.

Genetic loci associated with prevalent and incident myocardial infarction and coronary heart disease in the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. - Hahn, Julie; Fu, Yi-Ping; Brown, Michael R; Bis, Joshua C; de Vries, Paul S; Feitosa, Mary F; Yanek, Lisa R; Weiss, Stefan; Giulianini, Franco; Smith, Albert Vernon; Guo, Xiuqing; Bartz, Traci M; et al. (PLoS One, 2020)
BACKGROUND: Genome-wide association studies have identified multiple genomic loci associated with coronary artery disease, but most are common variants in non-coding regions that provide limited information on causal genes and etiology of the disease. To overcome the limited scope that common variants provide, we focused our investigation on low-frequency and rare sequence variations primarily residing in coding regions of the genome. METHODS AND RESULTS: Using samples of individuals of European ancestry from ten cohorts within the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium, both cross-sectional and prospective analyses were conducted to examine associations between genetic variants and myocardial infarction (MI), coronary heart disease (CHD), and all-cause mortality following these events. For prevalent events, a total of 27,349 participants of European ancestry, including 1831 prevalent MI cases and 2518 prevalent CHD cases were used. For incident cases, a total of 55,736 participants of European ancestry were included (3,031 incident MI cases and 5,425 incident CHD cases). There were 1,860 all-cause deaths among the 3,751 MI and CHD cases from six cohorts that contributed to the analysis of all-cause mortality. Single variant and gene-based analyses were performed separately in each cohort and then meta-analyzed for each outcome. A low-frequency intronic variant (rs988583) in PLCL1 was significantly associated with prevalent MI (OR = 1.80, 95% confidence interval: 1.43, 2.27; P = 7.12 × 10-7). We conducted gene-based burden tests for genes with a cumulative minor allele count (cMAC) ≥ 5 and variants with minor allele frequency (MAF) < 5%. TMPRSS5 and LDLRAD1 were significantly associated with prevalent MI and CHD, respectively, and RC3H2 and ANGPTL4 were significantly associated with incident MI and CHD, respectively. No loci were significantly associated with all-cause mortality following a MI or CHD event. CONCLUSION: This study identified one known locus (ANGPTL4) and four new loci (PLCL1, RC3H2, TMPRSS5, and LDLRAD1) associated with cardiovascular disease risk that warrant further investigation.
Keywords: Aging; Coronary Artery Disease; Cross-Sectional Studies; Europe; Genetic Loci; Genome-Wide Association Study; Humans; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; White People

Inherited causes of clonal haematopoiesis in 97,691 whole genomes. - Bick, Alexander G; Weinstock, Joshua S; Nandakumar, Satish K; Fulco, Charles P; Bao, Erik L; Zekavat, Seyedeh M; Szeto, Mindy D; Liao, Xiaotian; Leventhal, Matthew J; Nasser, Joseph; Chang, Kyle; Laurie, Cecelia; et al. (Nature, 2020)
Age is the dominant risk factor for most chronic human diseases, but the mechanisms through which ageing confers this risk are largely unknown. The age-related acquisition of somatic mutations that lead to clonal expansion in regenerating haematopoietic stem cell populations has recently been associated with both haematological cancer and coronary heart disease-this phenomenon is termed clonal haematopoiesis of indeterminate potential (CHIP). Simultaneous analyses of germline and somatic whole-genome sequences provide the opportunity to identify root causes of CHIP. Here we analyse high-coverage whole-genome sequences from 97,691 participants of diverse ancestries in the National Heart, Lung, and Blood Institute Trans-omics for Precision Medicine (TOPMed) programme, and identify 4,229 individuals with CHIP. We identify associations with blood cell, lipid and inflammatory traits that are specific to different CHIP driver genes. Association of a genome-wide set of germline genetic variants enabled the identification of three genetic loci associated with CHIP status, including one locus at TET2 that was specific to individuals of African ancestry. In silico-informed in vitro evaluation of the TET2 germline locus enabled the identification of a causal variant that disrupts a TET2 distal enhancer, resulting in increased self-renewal of haematopoietic stem cells. Overall, we observe that germline genetic variation shapes haematopoietic stem cell function, leading to CHIP through mechanisms that are specific to clonal haematopoiesis as well as shared mechanisms that lead to somatic mutations across tissues.
Keywords: Adult; Africa; Aged; Aged, 80 and over; alpha Karyopherins; Black People; Cell Self Renewal; Clonal Hematopoiesis; Dioxygenases; DNA-Binding Proteins; Female; Genetic Predisposition to Disease; Genome, Human; Germ-Line Mutation; Hematopoietic Stem Cells; Humans; Intracellular Signaling Peptides and Proteins; Male; Middle Aged; National Heart, Lung, and Blood Institute (U.S.); Phenotype; Precision Medicine; Proto-Oncogene Proteins; Tripartite Motif Proteins; United States; Whole Genome Sequencing

A Mendelian randomization of γ' and total fibrinogen levels in relation to venous thromboembolism and ischemic stroke. - Maners, Jillian; Gill, Dipender; Pankratz, Nathan; Laffan, Michael A; Wolberg, Alisa S; de Maat, Moniek P M; Ligthart, Symen; Tang, Weihong; Ward-Caviness, Cavin K; Fornage, Myriam; Debette, Stephanie; Dichgans, Martin; et al. (Blood, 2020)
Fibrinogen is a key component of the coagulation cascade, and variation in its circulating levels may contribute to thrombotic diseases, such as venous thromboembolism (VTE) and ischemic stroke. Gamma prime (γ') fibrinogen is an isoform of fibrinogen that has anticoagulant properties. We applied 2-sample Mendelian randomization (MR) to estimate the causal effect of total circulating fibrinogen and its isoform, γ' fibrinogen, on risk of VTE and ischemic stroke subtypes using summary statistics from genome-wide association studies. Genetic instruments for γ' fibrinogen and total fibrinogen were selected, and the inverse-variance weighted MR approach was used to estimate causal effects in the main analysis, complemented by sensitivity analyses that are more robust to the inclusion of pleiotropic variants, including MR-Egger, weighted median MR, and weighted mode MR. The main inverse-variance weighted MR estimates based on a combination of 16 genetic instruments for γ' fibrinogen and 75 genetic instruments for total fibrinogen indicated a protective effect of higher γ' fibrinogen and higher total fibrinogen on VTE risk. There was also a protective effect of higher γ' fibrinogen levels on cardioembolic and large artery stroke risk. Effect estimates were consistent across sensitivity analyses. Our results provide evidence to support effects of genetically determined γ' fibrinogen on VTE and ischemic stroke risk. Further research is needed to explore mechanisms underlying these effects and their clinical applications.
Keywords: Female; Fibrinogen; Genetic Variation; Genome-Wide Association Study; Humans; Ischemic Stroke; Male; Mendelian Randomization Analysis; Risk Factors; Venous Thromboembolism

Methylome-wide association study of central adiposity implicates genes involved in immune and endocrine systems. - Justice, Anne E; Chittoor, Geetha; Gondalia, Rahul; Melton, Phillip E; Lim, Elise; Grove, Megan L; Whitsel, Eric A; Liu, Ching-Ti; Cupples, L Adrienne; Fernandez-Rhodes, Lindsay; Guan, Weihua; Bressler, Jan; et al. (Epigenomics, 2020)
We conducted a methylome-wide association study to examine associations between DNA methylation in whole blood and central adiposity and body fat distribution, measured as waist circumference, waist-to-hip ratio and waist-to-height ratio adjusted for body mass index, in 2684 African-American adults in the Atherosclerosis Risk in Communities study. We validated significantly associated cytosine-phosphate-guanine methylation sites (CpGs) among adults using the Women's Health Initiative and Framingham Heart Study participants (combined n = 5743) and generalized associations in adolescents from The Raine Study (n = 820). We identified 11 CpGs that were robustly associated with one or more central adiposity trait in adults and two in adolescents, including CpG site associations near , ,  and that had not previously been associated with obesity-related traits.
Keywords: Adiposity; Cohort Studies; CpG Islands; Disease Susceptibility; DNA Methylation; Endocrine System; Epigenesis, Genetic; Epigenomics; Genome-Wide Association Study; Humans; Immune System; Obesity

Parliament2: Accurate structural variant calling at scale. - Zarate, Samantha; Carroll, Andrew; Mahmoud, Medhat; Krasheninina, Olga; Jun, Goo; Salerno, William J; Schatz, Michael C; Eric Boerwinkle; Richard A Gibbs; Fritz J Sedlazeck (Gigascience, 2020)
BACKGROUND: Structural variants (SVs) are critical contributors to genetic diversity and genomic disease. To predict the phenotypic impact of SVs, there is a need for better estimates of both the occurrence and frequency of SVs, preferably from large, ethnically diverse cohorts. Thus, the current standard approach requires the use of short paired-end reads, which remain challenging to detect, especially at the scale of hundreds to thousands of samples. FINDINGS: We present Parliament2, a consensus SV framework that leverages multiple best-in-class methods to identify high-quality SVs from short-read DNA sequence data at scale. Parliament2 incorporates pre-installed SV callers that are optimized for efficient execution in parallel to reduce the overall runtime and costs. We demonstrate the accuracy of Parliament2 when applied to data from NovaSeq and HiSeq X platforms with the Genome in a Bottle (GIAB) SV call set across all size classes. The reported quality score per SV is calibrated across different SV types and size classes. Parliament2 has the highest F1 score (74.27%) measured across the independent gold standard from GIAB. We illustrate the compute performance by processing all 1000 Genomes samples (2,691 samples) in <1 day on GRCH38. Parliament2 improves the runtime performance of individual methods and is open source (https://github.com/slzarate/parliament2), and a Docker image, as well as a WDL implementation, is available. CONCLUSION: Parliament2 provides both a highly accurate single-sample SV call set from short-read DNA sequence data and enables cost-efficient application over cloud or cluster environments, processing thousands of samples.
Keywords: Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis; Software

Role of Rare and Low-Frequency Variants in Gene-Alcohol Interactions on Plasma Lipid Levels. - Wang, Zhe; Chen, Han; Bartz, Traci M; Bielak, Lawrence F; Chasman, Daniel I; Feitosa, Mary F; Franceschini, Nora; Guo, Xiuqing; Lim, Elise; Noordam, Raymond; Richard, Melissa A; Wang, Heming; et al. (Circ Genom Precis Med, 2020)
BACKGROUND: Alcohol intake influences plasma lipid levels, and such effects may be moderated by genetic variants. We aimed to characterize the role of aggregated rare and low-frequency protein-coding variants in gene by alcohol consumption interactions associated with fasting plasma lipid levels. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology consortium, fasting plasma triglycerides and high- and low-density lipoprotein cholesterol were measured in 34 153 individuals with European ancestry from 5 discovery studies and 32 277 individuals from 6 replication studies. Rare and low-frequency functional protein-coding variants (minor allele frequency, ≤5%) measured by an exome array were aggregated by genes and evaluated by a gene-environment interaction test and a joint test of genetic main and gene-environment interaction effects. Two dichotomous self-reported alcohol consumption variables, current drinker, defined as any recurrent drinking behavior, and regular drinker, defined as the subset of current drinkers who consume at least 2 drinks per week, were considered. RESULTS: We discovered and replicated 21 gene-lipid associations at 13 known lipid loci through the joint test. Eight loci (, , , , , , , and ) remained significant after conditioning on the common index single-nucleotide polymorphism identified by previous genome-wide association studies, suggesting an independent role for rare and low-frequency variants at these loci. One significant gene-alcohol interaction on triglycerides in a novel locus was significantly discovered (=6.65×10 for the interaction test) and replicated at nominal significance level (=0.013) in . CONCLUSIONS: In conclusion, this study applied new gene-based statistical approaches and suggested that rare and low-frequency genetic variants interacted with alcohol consumption on lipid levels.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Apolipoproteins E; Cholesterol, HDL; Female; Gene Frequency; Genetic Loci; Genome-Wide Association Study; Humans; Lipids; Male; Middle Aged; Polymorphism, Single Nucleotide; Proprotein Convertase 9; Triglycerides; White People; Young Adult

Serum sphingolipids and incident diabetes in a US population with high diabetes burden: the Hispanic Community Health Study/Study of Latinos (HCHS/SOL). - Chen, Guo-Chong; Chai, Jin Choul; Yu, Bing; Michelotti, Gregory A; Grove, Megan L; Fretts, Amanda M; Daviglus, Martha L; Garcia-Bedoya, Olga L; Thyagarajan, Bharat; Schneiderman, Neil; Cai, Jianwen; Kaplan, Robert C; et al. (Am J Clin Nutr, 2020)
BACKGROUND: Genetic or pharmacological inhibition of de novo sphingolipid synthases prevented diabetes in animal studies. OBJECTIVES: We sought to evaluate prospective associations of serum sphingolipids with incident diabetes in a population-based cohort. METHODS: We included 2010 participants of the Hispanic Community Health Study/Study of Latinos (HCHS/SOL) aged 18-74 y who were free of diabetes and other major chronic diseases at baseline (2008-2011). Metabolomic profiling of fasting serum was performed using a global, untargeted approach. A total of 43 sphingolipids were quantified and, considering subclasses and chemical structures of individual species, 6 sphingolipid scores were constructed. Diabetes status was assessed using standard procedures including blood tests. Multivariable survey Poisson regressions were applied to estimate RR and 95% CI of incident diabetes associated with individual sphingolipids or sphingolipid scores. RESULTS: There were 224 incident cases of diabetes identified during, on average, 6 y of follow-up. After adjustment for socioeconomic and lifestyle factors, a ceramide score (RR Q4 versus Q1 = 2.40; 95% CI: 1.24, 4.65; P-trend = 0.003) and a score of sphingomyelins with fully saturated sphingoid-fatty acid pairs (RR Q4 versus Q1 = 3.15; 95% CI: 1.75, 5.67; P-trend <0.001) both were positively associated with risk of diabetes, whereas scores of glycosylceramides, lactosylceramides, or other unsaturated sphingomyelins (even if having an SFA base) were not associated with risk of diabetes. After additional adjustment for numerous traditional risk factors (especially triglycerides), both associations were attenuated and only the saturated-sphingomyelin score remained associated with risk of diabetes (RR Q4 versus Q1 = 1.98; 95% CI: 1.09, 3.59; P-trend = 0.031). CONCLUSIONS: Our findings suggest that a cluster of saturated sphingomyelins may be associated with elevated risk of diabetes beyond traditional risk factors, which needs to be verified in other population studies. This study was registered at clinicaltrials.gov as NCT02060344.
Keywords: Adolescent; Adult; Aged; Diabetes Mellitus; Female; Hispanic or Latino; Humans; Male; Middle Aged; Prospective Studies; Risk Factors; Sphingolipids; United States; Young Adult

Variants, N-Acetylated Amino Acids, and Progression of CKD. - Luo, Shengyuan; Surapaneni, Aditya; Zheng, Zihe; Rhee, Eugene P; Coresh, Josef; Hung, Adriana M; Nadkarni, Girish N; Yu, Bing; Eric Boerwinkle; Tin, Adrienne; Arking, Dan E; Steinbrenner, Inga; et al. (Clin J Am Soc Nephrol, 2020)
BACKGROUND AND OBJECTIVES: Genetic variants in , a liver- and kidney-specific acetyltransferase encoding gene, have been associated with eGFR and CKD in European populations. Higher circulating levels of two -associated metabolites, N--acetylornithine and N-acetyl-1-methylhistidine, have been linked to lower eGFR and higher risk of incident CKD in the Black population. We aimed to expand upon prior studies to investigate associations between rs13538, a missense variant in , N-acetylated amino acids, and kidney failure in multiple, well-characterized cohorts. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: We conducted analyses among participants with genetic and/or serum metabolomic data in the African American Study of Kidney Disease and Hypertension (AASK; =962), the Atherosclerosis Risk in Communities (ARIC) study (=1050), and Bio, an electronic health record-linked biorepository (=680). Separately, we evaluated associations between rs13538, urinary N-acetylated amino acids, and kidney failure in participants in the German CKD (GCKD) study (=1624). RESULTS: Of 31 N-acetylated amino acids evaluated, the circulating and urinary levels of 14 were associated with rs13538 (<0.05/31). Higher circulating levels of five of these N-acetylated amino acids, namely, N--acetylornithine, N-acetyl-1-methylhistidine, N-acetyl-3-methylhistidine, N-acetylhistidine, and N2,N5-diacetylornithine, were associated with kidney failure, after adjustment for confounders and combining results in meta-analysis (combined hazard ratios per two-fold higher amino acid levels: 1.48, 1.44, 1.21, 1.65, and 1.41, respectively; 95% confidence intervals: 1.21 to 1.81, 1.22 to 1.70, 1.08 to 1.37, 1.29 to 2.10, and 1.17 to 1.71, respectively; all values <0.05/14). None of the urinary levels of these N-acetylated amino acids were associated with kidney failure in the GCKD study. CONCLUSIONS: We demonstrate significant associations between an gene variant and 14 N-acetylated amino acids, five of which had circulation levels that were associated with kidney failure.
Keywords: Acetylation; Acetyltransferases; Adult; Aged; Aged, 80 and over; Amino Acids; Black People; Disease Progression; Female; Follow-Up Studies; Glomerular Filtration Rate; Histidine; Humans; Kidney Failure, Chronic; Male; Metabolomics; Methylhistidines; Middle Aged; Ornithine; Polymorphism, Single Nucleotide; Prospective Studies; Randomized Controlled Trials as Topic; White People

Whole exome sequencing study identifies novel rare and common Alzheimer's-Associated variants involved in immune response and transcriptional regulation. - Bis, Joshua C; Jian, Xueqiu; Kunkle, Brian W; Chen, Yuning; Hamilton-Nelson, Kara L; Bush, William S; Salerno, William J; Lancour, Daniel; Ma, Yiyi; Renton, Alan E; Marcora, Edoardo; Farrell, John J; et al. (Mol Psychiatry, 2020)
The Alzheimer's Disease Sequencing Project (ADSP) undertook whole exome sequencing in 5,740 late-onset Alzheimer disease (AD) cases and 5,096 cognitively normal controls primarily of European ancestry (EA), among whom 218 cases and 177 controls were Caribbean Hispanic (CH). An age-, sex- and APOE based risk score and family history were used to select cases most likely to harbor novel AD risk variants and controls least likely to develop AD by age 85 years. We tested ~1.5 million single nucleotide variants (SNVs) and 50,000 insertion-deletion polymorphisms (indels) for association to AD, using multiple models considering individual variants as well as gene-based tests aggregating rare, predicted functional, and loss of function variants. Sixteen single variants and 19 genes that met criteria for significant or suggestive associations after multiple-testing correction were evaluated for replication in four independent samples; three with whole exome sequencing (2,778 cases, 7,262 controls) and one with genome-wide genotyping imputed to the Haplotype Reference Consortium panel (9,343 cases, 11,527 controls). The top findings in the discovery sample were also followed-up in the ADSP whole-genome sequenced family-based dataset (197 members of 42 EA families and 501 members of 157 CH families). We identified novel and predicted functional genetic variants in genes previously associated with AD. We also detected associations in three novel genes: IGHG3 (p = 9.8 × 10), an immunoglobulin gene whose antibodies interact with β-amyloid, a long non-coding RNA AC099552.4 (p = 1.2 × 10), and a zinc-finger protein ZNF655 (gene-based p = 5.0 × 10). The latter two suggest an important role for transcriptional regulation in AD pathogenesis.
Keywords: Aged; Aged, 80 and over; Alzheimer Disease; Amyloid beta-Peptides; Apolipoproteins E; Exome Sequencing; Female; Gene Expression Regulation; Haplotypes; Humans; Immunity; Immunoglobulin G; Kruppel-Like Transcription Factors; Male; Polymorphism, Genetic; RNA, Long Noncoding; Transcription, Genetic

Wolff-Parkinson-White syndrome: De novo variants and evidence for mutational burden in genes associated with atrial fibrillation. - Coban-Akdemir, Zeynep H; Charng, Wu-Lin; Azamian, Mahshid; Paine, Ingrid S; Punetha, Jaya; Grochowski, Christopher M; Gambin, Tomasz; Valdes, Santiago O; Cannon, Bryan; Zapata, Gladys; Hernandez, Patricia P; Jhangiani, Shalini; et al. (Am J Med Genet A, 2020)
BACKGROUND: Wolff-Parkinson-White (WPW) syndrome is a relatively common arrhythmia affecting ~1-3/1,000 individuals. Mutations in PRKAG2 have been described in rare patients in association with cardiomyopathy. However, the genetic basis of WPW in individuals with a structurally normal heart remains poorly understood. Sudden death due to atrial fibrillation (AF) can also occur in these individuals. Several studies have indicated that despite ablation of an accessory pathway, the risk of AF remains high in patients compared to general population. METHODS: We applied exome sequencing in 305 subjects, including 65 trios, 80 singletons, and 6 multiple affected families. We used de novo analysis, candidate gene approach, and burden testing to explore the genetic contributions to WPW. RESULTS: A heterozygous deleterious variant in PRKAG2 was identified in one subject, accounting for 0.6% (1/151) of the genetic basis of WPW in this study. Another individual with WPW and left ventricular hypertrophy carried a known pathogenic variant in MYH7. We found rare de novo variants in genes associated with arrhythmia and cardiomyopathy (ANK2, NEBL, PITX2, and PRDM16) in this cohort. There was an increased burden of rare deleterious variants (MAF ≤ 0.005) with CADD score ≥ 25 in genes linked to AF in cases compared to controls (P = .0023). CONCLUSIONS: Our findings show an increased burden of rare deleterious variants in genes linked to AF in WPW syndrome, suggesting that genetic factors that determine the development of accessory pathways may be linked to an increased susceptibility of atrial muscle to AF in a subset of patients.
Keywords: Adolescent; Adult; AMP-Activated Protein Kinases; Ankyrins; Atrial Fibrillation; Carrier Proteins; Child; Cohort Studies; Cytoskeletal Proteins; DNA-Binding Proteins; Exome Sequencing; Female; Genetic Association Studies; Genetic Predisposition to Disease; Heart Atria; Homeodomain Proteins; Humans; LIM Domain Proteins; Male; Mutation; Transcription Factors; Wolff-Parkinson-White Syndrome; Young Adult

ACAT: A Fast and Powerful p Value Combination Method for Rare-Variant Analysis in Sequencing Studies. - Liu, Yaowu; Chen, Sixing; Li, Zilin; Morrison, Alanna C; Eric Boerwinkle; Lin, Xihong (Am J Hum Genet, 2019)
Set-based analysis that jointly tests the association of variants in a group has emerged as a popular tool for analyzing rare and low-frequency variants in sequencing studies. The existing set-based tests can suffer significant power loss when only a small proportion of variants are causal, and their powers can be sensitive to the number, effect sizes, and effect directions of the causal variants and the choices of weights. Here we propose an aggregated Cauchy association test (ACAT), a general, powerful, and computationally efficient p value combination method for boosting power in sequencing studies. First, by combining variant-level p values, we use ACAT to construct a set-based test (ACAT-V) that is particularly powerful in the presence of only a small number of causal variants in a variant set. Second, by combining different variant-set-level p values, we use ACAT to construct an omnibus test (ACAT-O) that combines the strength of multiple complimentary set-based tests, including the burden test, sequence kernel association test (SKAT), and ACAT-V. Through analysis of extensively simulated data and the whole-genome sequencing data from the Atherosclerosis Risk in Communities (ARIC) study, we demonstrate that ACAT-V complements the SKAT and the burden test, and that ACAT-O has a substantially more robust and higher power than those of the alternative tests.
Keywords: Algorithms; Computer Simulation; Data Interpretation, Statistical; Disease; Genetic Association Studies; Genetic Variation; Genome, Human; Humans; Models, Genetic; Sequence Analysis, DNA

Association of sickle cell trait with measures of cognitive function and dementia in African Americans. - Chen, Nemin; Caruso, Christina; Alonso, Alvaro; Derebail, Vimal K; Kshirsagar, Abhijit V; Sharrett, A Richey; Key, Nigel S; Gottesman, Rebecca F; Grove, Megan L; Bressler, Jan; Eric Boerwinkle; Windham, B Gwen; et al. (eNeurologicalSci, 2019)
OBJECTIVE: The incidence and prevalence of cognitive decline and dementia are significantly higher among African Americans compared with non-Hispanic Whites. The aim of this study was to determine whether inheritance of the sickle cell trait (SCT) i.e. heterozygosity for the sickle cell mutation increases the risk of cognitive decline or dementia Among African Americans. METHODS: We studied African American participants enrolled in the Atherosclerosis Risk in Communities study. SCT genotype at baseline and outcome data from cognitive assessments at visits 2, 4 and 5, and an MRI performed at visit 5 were analyzed for the association between SCT and risk of cognitive impairment and/or dementia. RESULTS: There was no significant difference in risk factors profile between participants with SCT ( = 176) and those without SCT ( = 2532). SCT was not independently associated with a higher prevalence of global or domain-specific cognitive impairment at baseline or with more rapid cognitive decline. Participants with SCT had slightly lower incidence of dementia (HR = 0.63 [0.38, 1.05]). On the other hand, SCT seems to interact with the apolipoprotein E ε4 risk allele resulting in poor performance on digit symbol substitution test at baseline (z-score = -0.08, P = 0.05) and over time (z-score = -0.12, P = 0.04); and with diabetes mellitus leading to a moderately increased risk of dementia (HR = 2.06 [0.89, 4.78], P = 0.01). CONCLUSIONS: SCT was not an independent risk factor for prevalence or incidence of cognitive decline or dementia, although it may interact with and modify other putative risk factors for cognitive decline and dementia.

Atlas-CNV: a validated approach to call single-exon CNVs in the eMERGESeq gene panel. - Chiang, Theodore; Liu, Xiuping; Wu, Tsung-Jung; Jianhong Hu; Fritz J Sedlazeck; White, Simon; Schaid, Daniel; Andrade, Mariza de; Jarvik, Gail P; Crosslin, David; Stanaway, Ian; Carrell, David S; et al. (Genet Med, 2019)
PURPOSE: To provide a validated method to confidently identify exon-containing copy-number variants (CNVs), with a low false discovery rate (FDR), in targeted sequencing data from a clinical laboratory with particular focus on single-exon CNVs. METHODS: DNA sequence coverage data are normalized within each sample and subsequently exonic CNVs are identified in a batch of samples, when the target log ratio of the sample to the batch median exceeds defined thresholds. The quality of exonic CNV calls is assessed by C-scores (Z-like scores) using thresholds derived from gold standard samples and simulation studies. We integrate an ExonQC threshold to lower FDR and compare performance with alternate software (VisCap). RESULTS: Thirteen CNVs were used as a truth set to validate Atlas-CNV and compared with VisCap. We demonstrated FDR reduction in validation, simulation, and 10,926 eMERGESeq samples without sensitivity loss. Sixty-four multiexon and 29 single-exon CNVs with high C-scores were assessed by Multiplex Ligation-dependent Probe Amplification (MLPA). CONCLUSION: Atlas-CNV is validated as a method to identify exonic CNVs in targeted sequencing data generated in the clinical laboratory. The ExonQC and C-score assignment can reduce FDR (identification of targets with high variance) and improve calling accuracy of single-exon CNVs respectively. We propose guidelines and criteria to identify high confidence single-exon CNVs.
Keywords: DNA Copy Number Variations; Exons; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Sequence Analysis, DNA; Software

Author Correction: Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Author Correction: Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2019)
Christina M. Lill, who contributed to analysis of data, was inadvertently omitted from the author list in the originally published version of this article. This has now been corrected in both the PDF and HTML versions of the article.

Blood Leukocyte DNA Methylation Predicts Risk of Future Myocardial Infarction and Coronary Heart Disease. - Agha, Golareh; Mendelson, Michael M; Ward-Caviness, Cavin K; Joehanes, Roby; Huan, Tianxiao; Gondalia, Rahul; Salfati, Elias; Brody, Jennifer A; Fiorito, Giovanni; Bressler, Jan; Chen, Brian H; Ligthart, Symen; et al. (Circulation, 2019)
BACKGROUND: DNA methylation is implicated in coronary heart disease (CHD), but current evidence is based on small, cross-sectional studies. We examined blood DNA methylation in relation to incident CHD across multiple prospective cohorts. METHODS: Nine population-based cohorts from the United States and Europe profiled epigenome-wide blood leukocyte DNA methylation using the Illumina Infinium 450k microarray, and prospectively ascertained CHD events including coronary insufficiency/unstable angina, recognized myocardial infarction, coronary revascularization, and coronary death. Cohorts conducted race-specific analyses adjusted for age, sex, smoking, education, body mass index, blood cell type proportions, and technical variables. We conducted fixed-effect meta-analyses across cohorts. RESULTS: Among 11 461 individuals (mean age 64 years, 67% women, 35% African American) free of CHD at baseline, 1895 developed CHD during a mean follow-up of 11.2 years. Methylation levels at 52 CpG (cytosine-phosphate-guanine) sites were associated with incident CHD or myocardial infarction (false discovery rate<0.05). These CpGs map to genes with key roles in calcium regulation (ATP2B2, CASR, GUCA1B, HPCAL1), and genes identified in genome- and epigenome-wide studies of serum calcium (CASR), serum calcium-related risk of CHD (CASR), coronary artery calcified plaque (PTPRN2), and kidney function (CDH23, HPCAL1), among others. Mendelian randomization analyses supported a causal effect of DNA methylation on incident CHD; these CpGs map to active regulatory regions proximal to long non-coding RNA transcripts. CONCLUSION: Methylation of blood-derived DNA is associated with risk of future CHD across diverse populations and may serve as an informative tool for gaining further insight on the development of CHD.
Keywords: Adult; Aged; Cohort Studies; Coronary Disease; CpG Islands; DNA Methylation; Europe; Female; Genome-Wide Association Study; Humans; Incidence; Leukocytes; Male; Middle Aged; Myocardial Infarction; Population Groups; Prognosis; Prospective Studies; Risk; United States

The Consortium of Metabolomics Studies (COMETS): Metabolomics in 47 Prospective Cohort Studies. - Yu, Bing; Zanetti, Krista A; Temprosa, Marinella; Albanes, Demetrius; Appel, Nathan; Barrera, Clara Barrios; Ben-Shlomo, Yoav; Eric Boerwinkle; Casas, Juan P; Clish, Clary; Dale, Caroline; Dehghan, Abbas; et al. (Am J Epidemiol, 2019)
The Consortium of Metabolomics Studies (COMETS) was established in 2014 to facilitate large-scale collaborative research on the human metabolome and its relationship with disease etiology, diagnosis, and prognosis. COMETS comprises 47 cohorts from Asia, Europe, North America, and South America that together include more than 136,000 participants with blood metabolomics data on samples collected from 1985 to 2017. Metabolomics data were provided by 17 different platforms, with the most frequently used labs being Metabolon, Inc. (14 cohorts), the Broad Institute (15 cohorts), and Nightingale Health (11 cohorts). Participants have been followed for a median of 23 years for health outcomes including death, cancer, cardiovascular disease, diabetes, and others; many of the studies are ongoing. Available exposure-related data include common clinical measurements and behavioral factors, as well as genome-wide genotype data. Two feasibility studies were conducted to evaluate the comparability of metabolomics platforms used by COMETS cohorts. The first study showed that the overlap between any 2 different laboratories ranged from 6 to 121 metabolites at 5 leading laboratories. The second study showed that the median Spearman correlation comparing 111 overlapping metabolites captured by Metabolon and the Broad Institute was 0.79 (interquartile range, 0.56-0.89).
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Biomarkers; Body Mass Index; Child; Epidemiologic Methods; Epidemiology; Female; Global Health; Health Behavior; Hematologic Tests; Humans; Longitudinal Studies; Male; Metabolomics; Middle Aged; Prospective Studies; Socioeconomic Factors; Young Adult

Dynamic Scan Procedure for Detecting Rare-Variant Association Regions in Whole-Genome Sequencing Studies. - Li, Zilin; Li, Xihao; Liu, Yaowu; Shen, Jincheng; Chen, Han; Zhou, Hufeng; Morrison, Alanna C; Eric Boerwinkle; Lin, Xihong (Am J Hum Genet, 2019)
Whole-genome sequencing (WGS) studies are being widely conducted in order to identify rare variants associated with human diseases and disease-related traits. Classical single-marker association analyses for rare variants have limited power, and variant-set-based analyses are commonly used by researchers for analyzing rare variants. However, existing variant-set-based approaches need to pre-specify genetic regions for analysis; hence, they are not directly applicable to WGS data because of the large number of intergenic and intron regions that consist of a massive number of non-coding variants. The commonly used sliding-window method requires the pre-specification of fixed window sizes, which are often unknown as a priori, are difficult to specify in practice, and are subject to limitations given that the sizes of genetic-association regions are likely to vary across the genome and phenotypes. We propose a computationally efficient and dynamic scan-statistic method (Scan the Genome [SCANG]) for analyzing WGS data; this method flexibly detects the sizes and the locations of rare-variant association regions without the need to specify a prior, fixed window size. The proposed method controls for the genome-wise type I error rate and accounts for the linkage disequilibrium among genetic variants. It allows the detected sizes of rare-variant association regions to vary across the genome. Through extensive simulated studies that consider a wide variety of scenarios, we show that SCANG substantially outperforms several alternative methods for detecting rare-variant-associations while controlling for the genome-wise type I error rates. We illustrate SCANG by analyzing the WGS lipids data from the Atherosclerosis Risk in Communities (ARIC) study.
Keywords: Algorithms; Computational Biology; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Models, Genetic; Whole Genome Sequencing

Efficient Variant Set Mixed Model Association Tests for Continuous and Binary Traits in Large-Scale Whole-Genome Sequencing Studies. - Chen, Han; Huffman, Jennifer E; Brody, Jennifer A; Wang, Chaolong; Lee, Seunggeun; Li, Zilin; Gogarten, Stephanie M; Sofer, Tamar; Bielak, Lawrence F; Bis, Joshua C; Blangero, John; Bowler, Russell P; et al. (Am J Hum Genet, 2019)
With advances in whole-genome sequencing (WGS) technology, more advanced statistical methods for testing genetic association with rare variants are being developed. Methods in which variants are grouped for analysis are also known as variant-set, gene-based, and aggregate unit tests. The burden test and sequence kernel association test (SKAT) are two widely used variant-set tests, which were originally developed for samples of unrelated individuals and later have been extended to family data with known pedigree structures. However, computationally efficient and powerful variant-set tests are needed to make analyses tractable in large-scale WGS studies with complex study samples. In this paper, we propose the variant-set mixed model association tests (SMMAT) for continuous and binary traits using the generalized linear mixed model framework. These tests can be applied to large-scale WGS studies involving samples with population structure and relatedness, such as in the National Heart, Lung, and Blood Institute's Trans-Omics for Precision Medicine (TOPMed) program. SMMATs share the same null model for different variant sets, and a virtue of this null model, which includes covariates only, is that it needs to be fit only once for all tests in each genome-wide analysis. Simulation studies show that all the proposed SMMATs correctly control type I error rates for both continuous and binary traits in the presence of population structure and relatedness. We also illustrate our tests in a real data example of analysis of plasma fibrinogen levels in the TOPMed program (n = 23,763), using the Analysis Commons, a cloud-based computing platform.
Keywords: Chromosomes, Human, Pair 4; Cloud Computing; Female; Fibrinogen; Genetic Association Studies; Genetics, Population; Humans; Male; Models, Genetic; National Heart, Lung, and Blood Institute (U.S.); Precision Medicine; Research Design; Time Factors; United States; Whole Genome Sequencing

Exome sequencing of 20,791 cases of type 2 diabetes and 24,440 controls. - Flannick, Jason; Mercader, Josep M; Fuchsberger, Christian; Udler, Miriam S; Mahajan, Anubha; Wessel, Jennifer; Teslovich, Tanya M; Caulkins, Lizz; Koesterer, Ryan; Barajas-Olmos, Francisco; Blackwell, Thomas W; Eric Boerwinkle; et al. (Nature, 2019)
Protein-coding genetic variants that strongly affect disease risk can yield relevant clues to disease pathogenesis. Here we report exome-sequencing analyses of 20,791 individuals with type 2 diabetes (T2D) and 24,440 non-diabetic control participants from 5 ancestries. We identify gene-level associations of rare variants (with minor allele frequencies of less than 0.5%) in 4 genes at exome-wide significance, including a series of more than 30 SLC30A8 alleles that conveys protection against T2D, and in 12 gene sets, including those corresponding to T2D drug targets (P = 6.1 × 10) and candidate genes from knockout mice (P = 5.2 × 10). Within our study, the strongest T2D gene-level signals for rare variants explain at most 25% of the heritability of the strongest common single-variant signals, and the gene-level effect sizes of the rare variants that we observed in established T2D drug targets will require 75,000-185,000 sequenced cases to achieve exome-wide significance. We propose a method to interpret these modest rare-variant associations and to incorporate these associations into future target or gene prioritization efforts.
Keywords: Animals; Case-Control Studies; Decision Support Techniques; Diabetes Mellitus, Type 2; Exome; Exome Sequencing; Female; Gene Frequency; Genome-Wide Association Study; Humans; Male; Mice; Mice, Knockout

Functionally oriented analysis of cardiometabolic traits in a trans-ethnic sample. - Petty, Lauren E; Highland, Heather M; Gamazon, Eric R; Hu, Hao; Karhade, Mandar; Chen, Hung-Hsin; de Vries, Paul S; Grove, Megan L; Aguilar, David; Bell, Graeme I; Huff, Chad D; Hanis, Craig L; et al. (Hum Mol Genet, 2019)
Interpretation of genetic association results is difficult because signals often lack biological context. To generate hypotheses of the functional genetic etiology of complex cardiometabolic traits, we estimated the genetically determined component of gene expression from common variants using PrediXcan (1) and determined genes with differential predicted expression by trait. PrediXcan imputes tissue-specific expression levels from genetic variation using variant-level effect on gene expression in transcriptome data. To explore the value of imputed genetically regulated gene expression (GReX) models across different ancestral populations, we evaluated imputed expression levels for predictive accuracy genome-wide in RNA sequence data in samples drawn from European-ancestry and African-ancestry populations and identified substantial predictive power using European-derived models in a non-European target population. We then tested the association of GReX on 15 cardiometabolic traits including blood lipid levels, body mass index, height, blood pressure, fasting glucose and insulin, RR interval, fibrinogen level, factor VII level and white blood cell and platelet counts in 15 755 individuals across three ancestry groups, resulting in 20 novel gene-phenotype associations reaching experiment-wide significance across ancestries. In addition, we identified 18 significant novel gene-phenotype associations in our ancestry-specific analyses. Top associations were assessed for additional support via query of S-PrediXcan (2) results derived from publicly available genome-wide association studies summary data. Collectively, these findings illustrate the utility of transcriptome-based imputation models for discovery of cardiometabolic effect genes in a diverse dataset.
Keywords: Adult; Aged; Blood Pressure; Body Mass Index; Chromosome Mapping; Ethnicity; Female; Forecasting; Genetic Association Studies; Genome-Wide Association Study; Humans; Male; Metabolome; Middle Aged; Multifactorial Inheritance; Phenotype; Polymorphism, Single Nucleotide; Transcriptome; White People

Genetic architecture of laterality defects revealed by whole exome sequencing. - Li, Alexander H; Hanchard, Neil A; Azamian, Mahshid; D'Alessandro, Lisa C A; Coban-Akdemir, Zeynep; Lopez, Keila N; Hall, Nancy J; Dickerson, Heather; Nicosia, Annarita; Fernbach, Susan; Boone, Philip M; Gambin, Tomaz; et al. (Eur J Hum Genet, 2019)
Aberrant left-right patterning in the developing human embryo can lead to a broad spectrum of congenital malformations. The causes of most laterality defects are not known, with variants in established genes accounting for <20% of cases. We sought to characterize the genetic spectrum of these conditions by performing whole-exome sequencing of 323 unrelated laterality cases. We investigated the role of rare, predicted-damaging variation in 1726 putative laterality candidate genes derived from model organisms, pathway analyses, and human phenotypes. We also evaluated the contribution of homo/hemizygous exon deletions and gene-based burden of rare variation. A total of 28 candidate variants (26 rare predicted-damaging variants and 2 hemizygous deletions) were identified, including variants in genes known to cause heterotaxy and primary ciliary dyskinesia (ACVR2B, NODAL, ZIC3, DNAI1, DNAH5, HYDIN, MMP21), and genes without a human phenotype association, but with prior evidence for a role in embryonic laterality or cardiac development. Sanger validation of the latter variants in probands and their parents revealed no de novo variants, but apparent transmitted heterozygous (ROCK2, ISL1, SMAD2), and hemizygous (RAI2, RIPPLY1) variant patterns. Collectively, these variants account for 7.1% of our study subjects. We also observe evidence for an excess burden of rare, predicted loss-of-function variation in PXDNL and BMS1- two genes relevant to the broader laterality phenotype. These findings highlight potential new genes in the development of laterality defects, and suggest extensive locus heterogeneity and complex genetic models in this class of birth defects.
Keywords: Animals; Body Patterning; Embryonic Development; Exome Sequencing; Female; Genetic Association Studies; Genome, Human; Genomics; GTP Phosphohydrolases; Heart Defects, Congenital; Heterotaxy Syndrome; Humans; Male; Peroxidases; Zebrafish; Zebrafish Proteins

Genetic meta-analysis of diagnosed Alzheimer's disease identifies new risk loci and implicates Aβ, tau, immunity and lipid processing. - Kunkle, Brian W; Grenier-Boley, Benjamin; Sims, Rebecca; Bis, Joshua C; Damotte, Vincent; Naj, Adam C; Boland, Anne; Vronskaya, Maria; van der Lee, Sven J; Amlie-Wolf, Alexandre; Bellenguez, Céline; Frizatti, Aura; et al. (Nat Genet, 2019)
Risk for late-onset Alzheimer's disease (LOAD), the most prevalent dementia, is partially driven by genetics. To identify LOAD risk loci, we performed a large genome-wide association meta-analysis of clinically diagnosed LOAD (94,437 individuals). We confirm 20 previous LOAD risk loci and identify five new genome-wide loci (IQCK, ACE, ADAM10, ADAMTS1, and WWOX), two of which (ADAM10, ACE) were identified in a recent genome-wide association (GWAS)-by-familial-proxy of Alzheimer's or dementia. Fine-mapping of the human leukocyte antigen (HLA) region confirms the neurological and immune-mediated disease haplotype HLA-DR15 as a risk factor for LOAD. Pathway analysis implicates immunity, lipid metabolism, tau binding proteins, and amyloid precursor protein (APP) metabolism, showing that genetic variants affecting APP and Aβ processing are associated not only with early-onset autosomal dominant Alzheimer's disease but also with LOAD. Analyses of risk genes and pathways show enrichment for rare variants (P = 1.32 × 10), indicating that additional rare variants remain to be identified. We also identify important genetic correlations between LOAD and traits such as family history of dementia and education.
Keywords: Aged; Alzheimer Disease; Amyloid beta-Peptides; Case-Control Studies; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Testing; Genome-Wide Association Study; Haplotypes; Humans; Immunity; Lipid Metabolism; Lipids; Male; tau Proteins

A Genocentric Approach to Discovery of Mendelian Disorders. - Hansen, Adam W; Mullai Murugan; Li, He; Khayat, Michael M; Wang, Liwen; Rosenfeld, Jill; B. Kim Andrews; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Fritz J Sedlazeck; Ashley-Koch, Allison E; Liu, Pengfei; et al. (Am J Hum Genet, 2019)
The advent of inexpensive, clinical exome sequencing (ES) has led to the accumulation of genetic data from thousands of samples from individuals affected with a wide range of diseases, but for whom the underlying genetic and molecular etiology of their clinical phenotype remains unknown. In many cases, detailed phenotypes are unavailable or poorly recorded and there is little family history to guide study. To accelerate discovery, we integrated ES data from 18,696 individuals referred for suspected Mendelian disease, together with relatives, in an Apache Hadoop data lake (Hadoop Architecture Lake of Exomes [HARLEE]) and implemented a genocentric analysis that rapidly identified 154 genes harboring variants suspected to cause Mendelian disorders. The approach did not rely on case-specific phenotypic classifications but was driven by optimization of gene- and variant-level filter parameters utilizing historical Mendelian disease-gene association discovery data. Variants in 19 of the 154 candidate genes were subsequently reported as causative of a Mendelian trait and additional data support the association of all other candidate genes with disease endpoints.
Keywords: Databases, Genetic; Exome; Exome Sequencing; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Variation; Genomics; Humans; Pedigree; Phenotype

A genome-wide association study identifies new loci for factor VII and implicates factor VII in ischemic stroke etiology. - de Vries, Paul S; Sabater-Lleal, Maria; Huffman, Jennifer E; Marten, Jonathan; Song, Ci; Pankratz, Nathan; Bartz, Traci M; de Haan, Hugoline G; Delgado, Graciela E; Eicher, John D; Martinez-Perez, Angel; Ward-Caviness, Cavin K; et al. (Blood, 2019)
Factor VII (FVII) is an important component of the coagulation cascade. Few genetic loci regulating FVII activity and/or levels have been discovered to date. We conducted a meta-analysis of 9 genome-wide association studies of plasma FVII levels (7 FVII activity and 2 FVII antigen) among 27 495 participants of European and African ancestry. Each study performed ancestry-specific association analyses. Inverse variance weighted meta-analysis was performed within each ancestry group and then combined for a -ancestry meta-analysis. Our primary analysis included the 7 studies that measured FVII activity, and a secondary analysis included all 9 studies. We provided functional genomic validation for newly identified significant loci by silencing candidate genes in a human liver cell line (HuH7) using small-interfering RNA and then measuring messenger RNA and FVII protein expression. Lastly, we used meta-analysis results to perform Mendelian randomization analysis to estimate the causal effect of FVII activity on coronary artery disease, ischemic stroke (IS), and venous thromboembolism. We identified 2 novel ( and ) and 6 known loci associated with FVII activity, explaining 19.0% of the phenotypic variance. Adding FVII antigen data to the meta-analysis did not result in the discovery of further loci. Silencing in HuH7 cells upregulated FVII, whereas silencing downregulated FVII. Mendelian randomization analyses suggest that FVII activity has a positive causal effect on the risk of IS. Variants at and contribute to FVII activity by regulating expression levels. FVII activity appears to contribute to the etiology of IS in the general population.
Keywords: Brain Ischemia; Co-Repressor Proteins; Cohort Studies; Coronary Artery Disease; DNA-Binding Proteins; Factor VII; Female; Follow-Up Studies; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Membrane Transport Proteins; Mendelian Randomization Analysis; Middle Aged; Neoplasm Proteins; Phenotype; Polymorphism, Single Nucleotide; Prognosis; Stroke; Venous Thromboembolism

Genome-Wide Association Transethnic Meta-Analyses Identifies Novel Associations Regulating Coagulation Factor VIII and von Willebrand Factor Plasma Levels. - Sabater-Lleal, Maria; Huffman, Jennifer E; de Vries, Paul S; Marten, Jonathan; Mastrangelo, Michael A; Song, Ci; Pankratz, Nathan; Ward-Caviness, Cavin K; Yanek, Lisa R; Trompet, Stella; Delgado, Graciela E; Guo, Xiuqing; et al. (Circulation, 2019)
BACKGROUND: Factor VIII (FVIII) and its carrier protein von Willebrand factor (VWF) are associated with risk of arterial and venous thrombosis and with hemorrhagic disorders. We aimed to identify and functionally test novel genetic associations regulating plasma FVIII and VWF. METHODS: We meta-analyzed genome-wide association results from 46 354 individuals of European, African, East Asian, and Hispanic ancestry. All studies performed linear regression analysis using an additive genetic model and associated ≈35 million imputed variants with natural log-transformed phenotype levels. In vitro gene silencing in cultured endothelial cells was performed for candidate genes to provide additional evidence on association and function. Two-sample Mendelian randomization analyses were applied to test the causal role of FVIII and VWF plasma levels on the risk of arterial and venous thrombotic events. RESULTS: We identified 13 novel genome-wide significant ( P≤2.5×10) associations, 7 with FVIII levels ( FCHO2/TMEM171/TNPO1, HLA, SOX17/RP1, LINC00583/NFIB, RAB5C-KAT2A, RPL3/TAB1/SYNGR1, and ARSA) and 11 with VWF levels ( PDHB/PXK/KCTD6, SLC39A8, FCHO2/TMEM171/TNPO1, HLA, GIMAP7/GIMAP4, OR13C5/NIPSNAP, DAB2IP, C2CD4B, RAB5C-KAT2A, TAB1/SYNGR1, and ARSA), beyond 10 previously reported associations with these phenotypes. Functional validation provided further evidence of association for all loci on VWF except ARSA and DAB2IP. Mendelian randomization suggested causal effects of plasma FVIII activity levels on venous thrombosis and coronary artery disease risk and plasma VWF levels on ischemic stroke risk. CONCLUSIONS: The meta-analysis identified 13 novel genetic loci regulating FVIII and VWF plasma levels, 10 of which we validated functionally. We provide some evidence for a causal role of these proteins in thrombotic events.
Keywords: Arterial Occlusive Diseases; Biomarkers; Blood Coagulation; Blood Coagulation Disorders, Inherited; Factor VIII; Genetic Loci; Genetic Markers; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Phenotype; Ribosomal Protein L3; Risk Factors; Venous Thrombosis; von Willebrand Factor

The Genomics of Arthrogryposis, a Complex Trait: Candidate Genes and Further Evidence for Oligogenic Inheritance. - Pehlivan, Davut; Bayram, Yavuz; Gunes, Nilay; Coban Akdemir, Zeynep; Shukla, Anju; Bierhals, Tatjana; Tabakci, Burcu; Sahin, Yavuz; Gezdirici, Alper; Fatih, Jawid M; Gulec, Elif Yilmaz; Yesil, Gozde; et al. (Am J Hum Genet, 2019)
Arthrogryposis is a clinical finding that is present either as a feature of a neuromuscular condition or as part of a systemic disease in over 400 Mendelian conditions. The underlying molecular etiology remains largely unknown because of genetic and phenotypic heterogeneity. We applied exome sequencing (ES) in a cohort of 89 families with the clinical sign of arthrogryposis. Additional molecular techniques including array comparative genomic hybridization (aCGH) and Droplet Digital PCR (ddPCR) were performed on individuals who were found to have pathogenic copy number variants (CNVs) and mosaicism, respectively. A molecular diagnosis was established in 65.2% (58/89) of families. Eleven out of 58 families (19.0%) showed evidence for potential involvement of pathogenic variation at more than one locus, probably driven by absence of heterozygosity (AOH) burden due to identity-by-descent (IBD). RYR3, MYOM2, ERGIC1, SPTBN4, and ABCA7 represent genes, identified in two or more families, for which mutations are probably causative for arthrogryposis. We also provide evidence for the involvement of CNVs in the etiology of arthrogryposis and for the idea that both mono-allelic and bi-allelic variants in the same gene cause either similar or distinct syndromes. We were able to identify the molecular etiology in nine out of 20 families who underwent reanalysis. In summary, our data from family-based ES further delineate the molecular etiology of arthrogryposis, yielded several candidate disease-associated genes, and provide evidence for mutational burden in a biological pathway or network. Our study also highlights the importance of reanalysis of individuals with unsolved diagnoses in conjunction with sequencing extended family members.
Keywords: Adolescent; Adult; Arthrogryposis; Child; Child, Preschool; Cohort Studies; Connectin; DNA Copy Number Variations; Exome Sequencing; Female; Genetic Markers; Genomics; Gestational Age; Humans; Infant; Infant, Newborn; Male; Mosaicism; Multifactorial Inheritance; Mutation; Pedigree; Ryanodine Receptor Calcium Release Channel; Vesicular Transport Proteins; Young Adult

HFE H63D Polymorphism and the Risk for Systemic Hypertension, Myocardial Remodeling, and Adverse Cardiovascular Events in the ARIC Study. - Selvaraj, Senthil; Seidelmann, Sara; Silvestre, Odilson M; Claggett, Brian; Ndumele, Chiadi E; Cheng, Susan; Yu, Bing; Fernandes-Silva, Miguel M; Grove, Megan L; Eric Boerwinkle; Shah, Amil M; Solomon, Scott D (Hypertension, 2019)
H63D has been identified as a novel locus associated with the development of hypertension. The quantitative risks for hypertension, cardiac remodeling, and adverse events are not well studied. We analyzed white participants from the ARIC study (Atherosclerosis Risk in Communities) with H63D genotyping (N=10 902). We related genotype status to prevalence of hypertension at each of 5 study visits and risk for adverse cardiovascular events. Among visit 5 participants (N=4507), we related genotype status to echocardiographic features. Frequencies of wild type (WT)/WT, H63D/WT, and H63D/H63D were 73%, 24.6%, and 2.4%. The average age at baseline was 54.9±5.7 years and 47% were men. Participants carrying the H63D variant had higher systolic blood pressure ( P=0.004), diastolic blood pressure (0.012), and more frequently had hypertension ( P<0.001). Compared with WT/WT, H63D/WT and H63D/H63D participants had a 2% to 4% and 4% to 7% absolute increase in hypertension risk at each visit, respectively. The population attributable risk of H63D for hypertension among individuals aged 45 to 64 was 3.2% (95% CI, 1.3-5.1%) and 1.3% (95% CI, 0.0-2.4%) among individuals >65 years. After 25 years of follow-up, there was no relationship between genotype status and any outcome ( P>0.05). H63D/WT and H63D/H63D genotypes were associated with small differences in cardiac remodeling. In conclusion, the HFE H63D variant confers an increased risk for hypertension per allele and, given its frequency, accounts for a significant number of cases of hypertension. However, there was no increased risk for adverse cardiovascular events or substantial left ventricular remodeling.
Keywords: Cardiovascular Diseases; Echocardiography; Female; Genetic Predisposition to Disease; Hemochromatosis Protein; Humans; Hypertension; Male; Middle Aged; Mutation; Polymorphism, Genetic; Risk Assessment; United States; Ventricular Remodeling

Hypertensive APOL1 risk allele carriers demonstrate greater blood pressure reduction with angiotensin receptor blockade compared to low risk carriers. - Cunningham, Patrick N; Wang, Zhiying; Grove, Megan L; Cooper-Dehoff, Rhonda M; Beitelshees, Amber L; Gong, Yan; Gums, John G; Johnson, Julie A; Turner, Stephen T; Eric Boerwinkle; Chapman, Arlene B (PLoS One, 2019)
BACKGROUND: Hypertension (HTN) disproportionately affects African Americans (AAs), who respond better to thiazide diuretics than other antihypertensives. Variants of the APOL1 gene found in AAs are associated with a higher rate of kidney disease and play a complex role in cardiovascular disease. METHODS: AA subjects from four HTN trials (n = 961) (GERA1, GERA2, PEAR1, and PEAR2) were evaluated for blood pressure (BP) response based on APOL1 genotype after 4-9 weeks of monotherapy with thiazides, beta blockers, or candesartan. APOL1 G1 and G2 variants were determined by direct sequencing or imputation. RESULTS: Baseline systolic BP (SBP) and diastolic BP (DBP) levels did not differ based on APOL1 genotype. Subjects with 1-2 APOL1 risk alleles had a greater SBP response to candesartan (-12.2 +/- 1.2 vs -7.5 +/- 1.8 mmHg, p = 0.03; GERA2), and a greater decline in albuminuria with candesartan (-8.3 +/- 3.1 vs +3.7 +/- 4.3 mg/day, p = 0.02). APOL1 genotype did not associate with BP response to thiazides or beta blockers. GWAS was performed to determine associations with BP response to candesartan depending on APOL1 genotype. While no SNPs reached genome wide significance, SNP rs10113352, intronic in CSMD1, predicted greater office SBP response to candesartan (p = 3.7 x 10-7) in those with 1-2 risk alleles, while SNP rs286856, intronic in DPP6, predicted greater office SBP response (p = 3.2 x 10-7) in those with 0 risk alleles. CONCLUSIONS: Hypertensive AAs without overt kidney disease who carry 1 or more APOL1 risk variants have a greater BP and albuminuria reduction in response to candesartan therapy. BP response to thiazides or beta blockers did not differ by APOL1 genotype. Future studies confirming this initial finding in an independent cohort are required.
Keywords: Adult; Angiotensin II Type 1 Receptor Blockers; Apolipoprotein L1; Benzimidazoles; Biphenyl Compounds; Black or African American; Female; Genome-Wide Association Study; Genotype; Humans; Hypertension; Male; Middle Aged; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Tetrazoles; Treatment Outcome

Impact of Rare and Common Genetic Variants on Diabetes Diagnosis by Hemoglobin A1c in Multi-Ancestry Cohorts: The Trans-Omics for Precision Medicine Program. - Sarnowski, Chloe; Leong, Aaron; Raffield, Laura M; Wu, Peitao; de Vries, Paul S; DiCorpo, Daniel; Guo, Xiuqing; Xu, Huichun; Liu, Yongmei; Zheng, Xiuwen; Hu, Yao; Brody, Jennifer A; et al. (Am J Hum Genet, 2019)
Hemoglobin A1c (HbA1c) is widely used to diagnose diabetes and assess glycemic control in individuals with diabetes. However, nonglycemic determinants, including genetic variation, may influence how accurately HbA1c reflects underlying glycemia. Analyzing the NHLBI Trans-Omics for Precision Medicine (TOPMed) sequence data in 10,338 individuals from five studies and four ancestries (6,158 Europeans, 3,123 African-Americans, 650 Hispanics, and 407 East Asians), we confirmed five regions associated with HbA1c (GCK in Europeans and African-Americans, HK1 in Europeans and Hispanics, FN3K and/or FN3KRP in Europeans, and G6PD in African-Americans and Hispanics) and we identified an African-ancestry-specific low-frequency variant (rs1039215 in HBG2 and HBE1, minor allele frequency (MAF) = 0.03). The most associated G6PD variant (rs1050828-T, p.Val98Met, MAF = 12% in African-Americans, MAF = 2% in Hispanics) lowered HbA1c (-0.88% in hemizygous males, -0.34% in heterozygous females) and explained 23% of HbA1c variance in African-Americans and 4% in Hispanics. Additionally, we identified a rare distinct G6PD coding variant (rs76723693, p.Leu353Pro, MAF = 0.5%; -0.98% in hemizygous males, -0.46% in heterozygous females) and detected significant association with HbA1c when aggregating rare missense variants in G6PD. We observed similar magnitude and direction of effects for rs1039215 (HBG2) and rs76723693 (G6PD) in the two largest TOPMed African American cohorts, and we replicated the rs76723693 association in the UK Biobank African-ancestry participants. These variants in G6PD and HBG2 were monomorphic in the European and Asian samples. African or Hispanic ancestry individuals carrying G6PD variants may be underdiagnosed for diabetes when screened with HbA1c. Thus, assessment of these variants should be considered for incorporation into precision medicine approaches for diabetes diagnosis.
Keywords: Cohort Studies; Diabetes Mellitus; Female; Genetic Variation; Glycated Hemoglobin; Humans; Male; Polymorphism, Single Nucleotide; Population Groups; Precision Medicine

Importance of Participant-Centricity and Trust for a Sustainable Medical Information Commons. - McGuire, Amy L; Majumder, Mary A; Villanueva, Angela G; Bardill, Jessica; Bollinger, Juli M; Eric Boerwinkle; Bubela, Tania; Deverka, Patricia A; Evans, Barbara J; Garrison, Nanibaa' A; Glazer, David; Goldstein, Melissa M; et al. (J Law Med Ethics, 2019)
Drawing on a landscape analysis of existing data-sharing initiatives, in-depth interviews with expert stakeholders, and public deliberations with community advisory panels across the U.S., we describe features of the evolving medical information commons (MIC). We identify participant-centricity and trustworthiness as the most important features of an MIC and discuss the implications for those seeking to create a sustainable, useful, and widely available collection of linked resources for research and other purposes.
Keywords: Community Participation; Humans; Information Dissemination; Medical Informatics; Stakeholder Participation; Trust

Insights into genetics, human biology and disease gleaned from family based genomic studies. - Posey, Jennifer E; O'Donnell-Luria, Anne H; Chong, Jessica X; Harel, Tamar; Jhangiani, Shalini N; Coban Akdemir, Zeynep H; Buyske, Steven; Pehlivan, Davut; Carvalho, Claudia M B; Baxter, Samantha; Sobreira, Nara; Liu, Pengfei; et al. (Genet Med, 2019)
Identifying genes and variants contributing to rare disease phenotypes and Mendelian conditions informs biology and medicine, yet potential phenotypic consequences for variation of >75% of the ~20,000 annotated genes in the human genome are lacking. Technical advances to assess rare variation genome-wide, particularly exome sequencing (ES), enabled establishment in the United States of the National Institutes of Health (NIH)-supported Centers for Mendelian Genomics (CMGs) and have facilitated collaborative studies resulting in novel "disease gene" discoveries. Pedigree-based genomic studies and rare variant analyses in families with suspected Mendelian conditions have led to the elucidation of hundreds of novel disease genes and highlighted the impact of de novo mutational events, somatic variation underlying nononcologic traits, incompletely penetrant alleles, phenotypes with high locus heterogeneity, and multilocus pathogenic variation. Herein, we highlight CMG collaborative discoveries that have contributed to understanding both rare and common diseases and discuss opportunities for future discovery in single-locus Mendelian disorder genomics. Phenotypic annotation of all human genes; development of bioinformatic tools and analytic methods; exploration of non-Mendelian modes of inheritance including reduced penetrance, multilocus variation, and oligogenic inheritance; construction of allelic series at a locus; enhanced data sharing worldwide; and integration with clinical genomics are explored. Realizing the full contribution of rare disease research to functional annotation of the human genome, and further illuminating human biology and health, will lay the foundation for the Precision Medicine Initiative.
Keywords: Databases, Genetic; Exome Sequencing; Genetic Diseases, Inborn; Genetic Heterogeneity; Genetic Predisposition to Disease; Genome, Human; Genomics; Humans; National Institutes of Health (U.S.); Pedigree; United States

Leveraging linkage evidence to identify low-frequency and rare variants on 16p13 associated with blood pressure using TOPMed whole genome sequencing data. - He, Karen Y; Li, Xiaoyin; Kelly, Tanika N; Liang, Jingjing; Cade, Brian E; Assimes, Themistocles L; Becker, Lewis C; Beitelshees, Amber L; Bress, Adam P; Chang, Yen-Pei Christy; Chen, Yii-Der Ida; de Vries, Paul S; et al. (Hum Genet, 2019)
In this study, we investigated low-frequency and rare variants associated with blood pressure (BP) by focusing on a linkage region on chromosome 16p13. We used whole genome sequencing (WGS) data obtained through the NHLBI Trans-Omics for Precision Medicine (TOPMed) program on 395 Cleveland Family Study (CFS) European Americans (CFS-EA). By analyzing functional coding variants and non-coding rare variants with CADD score > 10 residing within the chromosomal region in families with linkage evidence, we observed 25 genes with nominal statistical evidence (burden or SKAT p < 0.05). One of the genes is RBFOX1, an evolutionarily conserved RNA-binding protein that regulates tissue-specific alternative splicing that we previously reported to be associated with BP using exome array data in CFS. After follow-up analysis of the 25 genes in ten independent TOPMed studies with individuals of European, African, and East Asian ancestry, and Hispanics (N = 29,988), we identified variants in SLX4 (p = 2.19 × 10) to be significantly associated with BP traits when accounting for multiple testing. We also replicated the associations previously reported for RBFOX1 (p = 0.007). Follow-up analysis with GTEx eQTL data shows SLX4 variants are associated with gene expression in coronary artery, multiple brain tissues, and right atrial appendage of the heart. Our study demonstrates that linkage analysis of family data can provide an efficient approach for detecting rare variants associated with complex traits in WGS data.
Keywords: Alternative Splicing; Blood Pressure; Chromosomes, Human, Pair 16; Exome; Female; Follow-Up Studies; Genetic Linkage; Genetic Variation; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Male; Recombinases; RNA Splicing Factors

Mendelian randomization evaluation of causal effects of fibrinogen on incident coronary heart disease. - Ward-Caviness, Cavin K; de Vries, Paul S; Wiggins, Kerri L; Huffman, Jennifer E; Yanek, Lisa R; Bielak, Lawrence F; Giulianini, Franco; Guo, Xiuqing; Kleber, Marcus E; Kacprowski, Tim; Groß, Stefan; Petersman, Astrid; et al. (PLoS One, 2019)
BACKGROUND: Fibrinogen is an essential hemostatic factor and cardiovascular disease risk factor. Early attempts at evaluating the causal effect of fibrinogen on coronary heart disease (CHD) and myocardial infraction (MI) using Mendelian randomization (MR) used single variant approaches, and did not take advantage of recent genome-wide association studies (GWAS) or multi-variant, pleiotropy robust MR methodologies. METHODS AND FINDINGS: We evaluated evidence for a causal effect of fibrinogen on both CHD and MI using MR. We used both an allele score approach and pleiotropy robust MR models. The allele score was composed of 38 fibrinogen-associated variants from recent GWAS. Initial analyses using the allele score used a meta-analysis of 11 European-ancestry prospective cohorts, free of CHD and MI at baseline, to examine incidence CHD and MI. We also applied 2 sample MR methods with data from a prevalent CHD and MI GWAS. Results are given in terms of the hazard ratio (HR) or odds ratio (OR), depending on the study design, and associated 95% confidence interval (CI). In single variant analyses no causal effect of fibrinogen on CHD or MI was observed. In multi-variant analyses using incidence CHD cases and the allele score approach, the estimated causal effect (HR) of a 1 g/L higher fibrinogen concentration was 1.62 (CI = 1.12, 2.36) when using incident cases and the allele score approach. In 2 sample MR analyses that accounted for pleiotropy, the causal estimate (OR) was reduced to 1.18 (CI = 0.98, 1.42) and 1.09 (CI = 0.89, 1.33) in the 2 most precise (smallest CI) models, out of 4 models evaluated. In the 2 sample MR analyses for MI, there was only very weak evidence of a causal effect in only 1 out of 4 models. CONCLUSIONS: A small causal effect of fibrinogen on CHD is observed using multi-variant MR approaches which account for pleiotropy, but not single variant MR approaches. Taken together, results indicate that even with large sample sizes and multi-variant approaches MR analyses still cannot exclude the null when estimating the causal effect of fibrinogen on CHD, but that any potential causal effect is likely to be much smaller than observed in epidemiological studies.
Keywords: Alleles; Coronary Disease; Fibrinogen; Genetic Pleiotropy; Genetic Variation; Genome-Wide Association Study; Humans; Incidence; Mendelian Randomization Analysis; Models, Genetic; Multivariate Analysis; Myocardial Infarction; Odds Ratio

Metabolomic Pattern Predicts Incident Coronary Heart Disease. - Wang, Zhe; Zhu, Cong; Nambi, Vijay; Morrison, Alanna C; Folsom, Aaron R; Ballantyne, Christie M; Eric Boerwinkle; Yu, Bing (Arterioscler Thromb Vasc Biol, 2019)
Objective- Alterations in the serum metabolome may be detectable in at-risk individuals before the onset of coronary heart disease (CHD). Identifying metabolomic signatures associated with CHD may provide insight into disease pathophysiology and prevention. Approach and Results- Metabolomic profiling (chromatography-mass spectrometry) was performed in 2232 African Americans and 1366 European Americans from the ARIC study (Atherosclerosis Risk in Communities). We applied Cox regression with least absolute shrinkage and selection operator to select metabolites associated with incident CHD. A metabolite risk score was constructed to evaluate whether the metabolite risk score predicted CHD risk beyond traditional risk factors. After 30 years of follow-up, we observed 633 incident CHD cases. Thirty-two metabolites were selected by least absolute shrinkage and selection operator to be associated with CHD, and 19 of the 32 showed significant individual associations with CHD, including a sugar substitute, erythritol. Theophylline (hazard ratio [95% CI] =1.16 [1.09-1.25]) and gamma-linolenic acid (hazard ratio [95% CI] =0.89 [0.81-0.97]) showed the greatest positive and negative associations with CHD, respectively. A 1 SD greater standardized metabolite risk score was associated with a 1.37-fold higher risk of CHD (hazard ratio [95% CI] =1.37 [1.27-1.47]). Adding the metabolite risk score to the traditional risk factors significantly improved model predictive performance (30-year risk prediction: Δ C statistics [95% CI] =0.016 [0.008-0.024], continuous net reclassification index [95% CI] =0.522 [0.480-0.556], integrated discrimination index [95% CI] =0.038 [0.019-0.065]). Conclusions- We identified 19 metabolites from known and novel metabolic pathways that collectively improved CHD risk prediction. Visual Overview- An online visual overview is available for this article.
Keywords: Atherosclerosis; Coronary Disease; Female; Humans; Male; Metabolomics; Middle Aged; Proportional Hazards Models; Prospective Studies; Risk Factors

Metabolomics Identifies Novel Blood Biomarkers of Pulmonary Function and COPD in the General Population. - Yu, Bing; Flexeder, Claudia; McGarrah, Robert W; Wyss, Annah; Morrison, Alanna C; North, Kari E; Eric Boerwinkle; Kastenmüller, Gabi; Gieger, Christian; Suhre, Karsten; Karrasch, Stefan; Peters, Annette; et al. (Metabolites, 2019)
Determination of metabolomic signatures of pulmonary function and chronic obstructive pulmonary disease (COPD) in the general population could aid in identification and understanding of early disease processes. Metabolome measurements were performed on serum from 4742 individuals (2354 African-Americans and 1529 European-Americans from the Atherosclerosis Risk in Communities study and 859 Europeans from the Cooperative Health Research in the Region of Augsburg study). We examined 368 metabolites in relation to cross-sectional measures of forced expiratory volume in 1 s (FEV1), forced vital capacity (FVC), their ratio (FEV1/FVC) and COPD using multivariable regression followed by meta-analysis. At a false discovery rate of 0.05, 95 metabolites were associated with FEV1 and 100 with FVC (73 overlapping), including inverse associations with branched-chain amino acids and positive associations with glutamine. Ten metabolites were associated with FEV1/FVC and seventeen with COPD (393 cases). Enriched pathways of amino acid metabolism were identified. Associations with FEV1 and FVC were not driven by individuals with COPD. We identified novel metabolic signatures of pulmonary function and COPD in African and European ancestry populations. These may allow development of biomarkers in the general population of early disease pathogenesis, before pulmonary function has decreased to levels diagnostic for COPD.

Multiancestry Genome-Wide Association Study of Lipid Levels Incorporating Gene-Alcohol Interactions. - de Vries, Paul S; Brown, Michael R; Bentley, Amy R; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Schwander, Karen; Kraja, Aldi T; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; et al. (Am J Epidemiol, 2019)
A person's lipid profile is influenced by genetic variants and alcohol consumption, but the contribution of interactions between these exposures has not been studied. We therefore incorporated gene-alcohol interactions into a multiancestry genome-wide association study of levels of high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. We included 45 studies in stage 1 (genome-wide discovery) and 66 studies in stage 2 (focused follow-up), for a total of 394,584 individuals from 5 ancestry groups. Analyses covered the period July 2014-November 2017. Genetic main effects and interaction effects were jointly assessed by means of a 2-degrees-of-freedom (df) test, and a 1-df test was used to assess the interaction effects alone. Variants at 495 loci were at least suggestively associated (P < 1 × 10-6) with lipid levels in stage 1 and were evaluated in stage 2, followed by combined analyses of stage 1 and stage 2. In the combined analysis of stages 1 and 2, a total of 147 independent loci were associated with lipid levels at P < 5 × 10-8 using 2-df tests, of which 18 were novel. No genome-wide-significant associations were found testing the interaction effect alone. The novel loci included several genes (proprotein convertase subtilisin/kexin type 5 (PCSK5), vascular endothelial growth factor B (VEGFB), and apolipoprotein B mRNA editing enzyme, catalytic polypeptide 1 (APOBEC1) complementation factor (A1CF)) that have a putative role in lipid metabolism on the basis of existing evidence from cellular and experimental models.
Keywords: Adolescent; Adult; Aged; Alcohol Drinking; Cholesterol, HDL; Cholesterol, LDL; Female; Genome-Wide Association Study; Genotype; Humans; Life Style; Lipids; Male; Middle Aged; Phenotype; Racial Groups; Triglycerides; Vascular Endothelial Growth Factor B; Young Adult

Multi-ancestry genome-wide gene-smoking interaction study of 387,272 individuals identifies new loci associated with serum lipids. - Bentley, Amy R; Sung, Yun J; Brown, Michael R; Winkler, Thomas W; Kraja, Aldi T; Ntalla, Ioanna; Schwander, Karen; Chasman, Daniel I; Lim, Elise; Deng, Xuan; Guo, Xiuqing; Liu, Jingmin; et al. (Nat Genet, 2019)
The concentrations of high- and low-density-lipoprotein cholesterol and triglycerides are influenced by smoking, but it is unknown whether genetic associations with lipids may be modified by smoking. We conducted a multi-ancestry genome-wide gene-smoking interaction study in 133,805 individuals with follow-up in an additional 253,467 individuals. Combined meta-analyses identified 13 new loci associated with lipids, some of which were detected only because association differed by smoking status. Additionally, we demonstrate the importance of including diverse populations, particularly in studies of interactions with lifestyle factors, where genomic and lifestyle differences by ancestry may contribute to novel findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Female; Genome-Wide Association Study; Genotype; Humans; Life Style; Linkage Disequilibrium; Lipids; Male; Middle Aged; Smoking; Young Adult

A multi-ancestry genome-wide study incorporating gene-smoking interactions identifies multiple new loci for pulse pressure and mean arterial pressure. - Sung, Yun Ju; de Las Fuentes, Lisa; Winkler, Thomas W; Chasman, Daniel I; Bentley, Amy R; Kraja, Aldi T; Ntalla, Ioanna; Warren, Helen R; Guo, Xiuqing; Schwander, Karen; Manning, Alisa K; Brown, Michael R; et al. (Hum Mol Genet, 2019)
Elevated blood pressure (BP), a leading cause of global morbidity and mortality, is influenced by both genetic and lifestyle factors. Cigarette smoking is one such lifestyle factor. Across five ancestries, we performed a genome-wide gene-smoking interaction study of mean arterial pressure (MAP) and pulse pressure (PP) in 129 913 individuals in stage 1 and follow-up analysis in 480 178 additional individuals in stage 2. We report here 136 loci significantly associated with MAP and/or PP. Of these, 61 were previously published through main-effect analysis of BP traits, 37 were recently reported by us for systolic BP and/or diastolic BP through gene-smoking interaction analysis and 38 were newly identified (P < 5 × 10-8, false discovery rate < 0.05). We also identified nine new signals near known loci. Of the 136 loci, 8 showed significant interaction with smoking status. They include CSMD1 previously reported for insulin resistance and BP in the spontaneously hypertensive rats. Many of the 38 new loci show biologic plausibility for a role in BP regulation. SLC26A7 encodes a chloride/bicarbonate exchanger expressed in the renal outer medullary collecting duct. AVPR1A is widely expressed, including in vascular smooth muscle cells, kidney, myocardium and brain. FHAD1 is a long non-coding RNA overexpressed in heart failure. TMEM51 was associated with contractile function in cardiomyocytes. CASP9 plays a central role in cardiomyocyte apoptosis. Identified only in African ancestry were 30 novel loci. Our findings highlight the value of multi-ancestry investigations, particularly in studies of interaction with lifestyle factors, where genomic and lifestyle differences may contribute to novel findings.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Antiporters; Arterial Pressure; Blood Pressure; Caspase 9; Ethnicity; Female; Gene-Environment Interaction; Genome-Wide Association Study; Humans; Hypertension; Male; Membrane Proteins; Middle Aged; Polymorphism, Genetic; Racial Groups; Receptors, Vasopressin; Smoking; Sulfate Transporters; Tumor Suppressor Proteins; Young Adult

Multi-ancestry sleep-by-SNP interaction analysis in 126,926 individuals reveals lipid loci stratified by sleep duration. - Noordam, Raymond; Bos, Maxime M; Wang, Heming; Winkler, Thomas W; Bentley, Amy R; Kilpeläinen, Tuomas O; de Vries, Paul S; Sung, Yun Ju; Schwander, Karen; Cade, Brian E; Manning, Alisa; Aschard, Hugues; et al. (Nat Commun, 2019)
Both short and long sleep are associated with an adverse lipid profile, likely through different biological pathways. To elucidate the biology of sleep-associated adverse lipid profile, we conduct multi-ancestry genome-wide sleep-SNP interaction analyses on three lipid traits (HDL-c, LDL-c and triglycerides). In the total study sample (discovery + replication) of 126,926 individuals from 5 different ancestry groups, when considering either long or short total sleep time interactions in joint analyses, we identify 49 previously unreported lipid loci, and 10 additional previously unreported lipid loci in a restricted sample of European-ancestry cohorts. In addition, we identify new gene-sleep interactions for known lipid loci such as LPL and PCSK9. The previously unreported lipid loci have a modest explained variance in lipid levels: most notable, gene-short-sleep interactions explain 4.25% of the variance in triglyceride level. Collectively, these findings contribute to our understanding of the biological mechanisms involved in sleep-associated adverse lipid profiles.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Chromosome Mapping; Female; Genetic Loci; Humans; Lipids; Male; Middle Aged; Phylogeny; Polymorphism, Single Nucleotide; Sleep; Young Adult

Multi-ancestry study of blood lipid levels identifies four loci interacting with physical activity. - Kilpeläinen, Tuomas O; Bentley, Amy R; Noordam, Raymond; Sung, Yun Ju; Schwander, Karen; Winkler, Thomas W; Jakupović, Hermina; Chasman, Daniel I; Manning, Alisa; Ntalla, Ioanna; Aschard, Hugues; Brown, Michael R; et al. (Nat Commun, 2019)
Many genetic loci affect circulating lipid levels, but it remains unknown whether lifestyle factors, such as physical activity, modify these genetic effects. To identify lipid loci interacting with physical activity, we performed genome-wide analyses of circulating HDL cholesterol, LDL cholesterol, and triglyceride levels in up to 120,979 individuals of European, African, Asian, Hispanic, and Brazilian ancestry, with follow-up of suggestive associations in an additional 131,012 individuals. We find four loci, in/near CLASP1, LHX1, SNTA1, and CNTNAP2, that are associated with circulating lipid levels through interaction with physical activity; higher levels of physical activity enhance the HDL cholesterol-increasing effects of the CLASP1, LHX1, and SNTA1 loci and attenuate the LDL cholesterol-increasing effect of the CNTNAP2 locus. The CLASP1, LHX1, and SNTA1 regions harbor genes linked to muscle function and lipid metabolism. Our results elucidate the role of physical activity interactions in the genetic contribution to blood lipid levels.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Asian People; Black People; Brazil; Calcium-Binding Proteins; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Exercise; Female; Genetic Loci; Genome-Wide Association Study; Genotype; Hispanic or Latino; Humans; LIM-Homeodomain Proteins; Lipid Metabolism; Lipids; Male; Membrane Proteins; Microtubule-Associated Proteins; Middle Aged; Muscle Proteins; Nerve Tissue Proteins; Transcription Factors; Triglycerides; White People; Young Adult

Pharmacogenomics of statin-related myopathy: Meta-analysis of rare variants from whole-exome sequencing. - Floyd, James S; Bloch, Katarzyna M; Brody, Jennifer A; Maroteau, Cyrielle; Siddiqui, Moneeza K; Gregory, Richard; Carr, Daniel F; Molokhia, Mariam; Liu, Xiaoming; Bis, Joshua C; Ahmed, Ammar; Liu, Xuan; et al. (PLoS One, 2019)
AIMS: Statin-related myopathy (SRM), which includes rhabdomyolysis, is an uncommon but important adverse drug reaction because the number of people prescribed statins world-wide is large. Previous association studies of common genetic variants have had limited success in identifying a genetic basis for this adverse drug reaction. We conducted a multi-site whole-exome sequencing study to investigate whether rare coding variants confer an increased risk of SRM. METHODS AND RESULTS: SRM 3-5 cases (N = 505) and statin treatment-tolerant controls (N = 2047) were recruited from multiple sites in North America and Europe. SRM 3-5 was defined as symptoms consistent with muscle injury and an elevated creatine phosphokinase level >4 times upper limit of normal without another likely cause of muscle injury. Whole-exome sequencing and variant calling was coordinated from two analysis centres, and results of single-variant and gene-based burden tests were meta-analysed. No genome-wide significant associations were identified. Given the large number of cases, we had 80% power to identify a variant with minor allele frequency of 0.01 that increases the risk of SRM 6-fold at genome-wide significance. CONCLUSIONS: In this large whole-exome sequencing study of severe statin-related muscle injury conducted to date, we did not find evidence that rare coding variants are responsible for this adverse drug reaction. Larger sample sizes would be required to identify rare variants with small effects, but it is unclear whether such findings would be clinically actionable.
Keywords: Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Muscle, Skeletal; Rhabdomyolysis; Whole Genome Sequencing

Protein-coding variants implicate novel genes related to lipid homeostasis contributing to body-fat distribution. - Justice, Anne E; Karaderi, Tugce; Highland, Heather M; Young, Kristin L; Graff, Mariaelisa; Lu, Yingchang; Turcot, Valérie; Auer, Paul L; Fine, Rebecca S; Guo, Xiuqing; Schurmann, Claudia; Lempradl, Adelheid; et al. (Nat Genet, 2019)
Body-fat distribution is a risk factor for adverse cardiovascular health consequences. We analyzed the association of body-fat distribution, assessed by waist-to-hip ratio adjusted for body mass index, with 228,985 predicted coding and splice site variants available on exome arrays in up to 344,369 individuals from five major ancestries (discovery) and 132,177 European-ancestry individuals (validation). We identified 15 common (minor allele frequency, MAF ≥5%) and nine low-frequency or rare (MAF <5%) coding novel variants. Pathway/gene set enrichment analyses identified lipid particle, adiponectin, abnormal white adipose tissue physiology and bone development and morphology as important contributors to fat distribution, while cross-trait associations highlight cardiometabolic traits. In functional follow-up analyses, specifically in Drosophila RNAi-knockdowns, we observed a significant increase in the total body triglyceride levels for two genes (DNAH10 and PLXND1). We implicate novel genes in fat distribution, stressing the importance of interrogating low-frequency and protein-coding variants.
Keywords: Animals; Body Fat Distribution; Body Mass Index; Case-Control Studies; Drosophila; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeostasis; Humans; Lipids; Male; Proteins; Risk Factors; Waist-Hip Ratio

Publisher Correction: Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2019)
An amendment to this paper has been published and can be accessed via a link at the top of the paper.

Quality control and integration of genotypes from two calling pipelines for whole genome sequence data in the Alzheimer's disease sequencing project. - Naj, Adam C; Lin, Honghuang; Vardarajan, Badri N; White, Simon; Lancour, Daniel; Ma, Yiyi; Schmidt, Michael; Sun, Fangui; Butkiewicz, Mariusz; Bush, William S; Kunkle, Brian W; Malamon, John; et al. (Genomics, 2019)
The Alzheimer's Disease Sequencing Project (ADSP) performed whole genome sequencing (WGS) of 584 subjects from 111 multiplex families at three sequencing centers. Genotype calling of single nucleotide variants (SNVs) and insertion-deletion variants (indels) was performed centrally using GATK-HaplotypeCaller and Atlas V2. The ADSP Quality Control (QC) Working Group applied QC protocols to project-level variant call format files (VCFs) from each pipeline, and developed and implemented a novel protocol, termed "consensus calling," to combine genotype calls from both pipelines into a single high-quality set. QC was applied to autosomal bi-allelic SNVs and indels, and included pipeline-recommended QC filters, variant-level QC, and sample-level QC. Low-quality variants or genotypes were excluded, and sample outliers were noted. Quality was assessed by examining Mendelian inconsistencies (MIs) among 67 parent-offspring pairs, and MIs were used to establish additional genotype-specific filters for GATK calls. After QC, 578 subjects remained. Pipeline-specific QC excluded ~12.0% of GATK and 14.5% of Atlas SNVs. Between pipelines, ~91% of SNV genotypes across all QCed variants were concordant; 4.23% and 4.56% of genotypes were exclusive to Atlas or GATK, respectively; the remaining ~0.01% of discordant genotypes were excluded. For indels, variant-level QC excluded ~36.8% of GATK and 35.3% of Atlas indels. Between pipelines, ~55.6% of indel genotypes were concordant; while 10.3% and 28.3% were exclusive to Atlas or GATK, respectively; and ~0.29% of discordant genotypes were. The final WGS consensus dataset contains 27,896,774 SNVs and 3,133,926 indels and is publicly available.
Keywords: Algorithms; Alzheimer Disease; Female; Genome-Wide Association Study; Genotype; Genotyping Techniques; Humans; Male; Polymorphism, Genetic; Quality Control; Whole Genome Sequencing

Rare variants in SLC5A10 are associated with serum 1,5-anhydroglucitol (1,5-AG) in the Atherosclerosis Risk in Communities (ARIC) Study. - Loomis, Stephanie J; Köttgen, Anna; Li, Man; Tin, Adrienne; Coresh, Josef; Eric Boerwinkle; Richard A Gibbs; Donna M Muzny; Pankow, James; Selvin, Elizabeth; Duggal, Priya (Sci Rep, 2019)
Serum 1,5-anhydroglucitol (1,5-AG) is an emerging biomarker used to monitor glycemic control in persons with diabetes. We performed whole-exome sequencing, examining the association between rare, coding genetic variants and 1,5-AG among European ancestry (N = 6,589) and African ancestry (N = 2,309) participants without diagnosed diabetes in the Atherosclerosis Risk in Communities (ARIC) Study. Five variants representing 3 independent signals on chromosome 17 in SLC5A10, a glucose transporter not previously known to transport 1,5-AG, were associated with 1,5-AG levels up to 10.38 µg/mL lower per allele (1,5-AG range 3.4-32.8 µg/mL) in the European ancestry sample and validated in the African ancestry sample. Together these variants explained 6% of the variance in 1,5-AG. Two of these variants (rs61741107, p = 8.85E-56; rs148178887, p = 1.13E-36) were rare, nonsynonymous, and predicted to be damaging or deleterious by multiple algorithms. Gene-based SKAT-O analysis supported these results (SLC5A10 p = 5.13E-64 in European ancestry, validated in African ancestry, p = 0.006). Interestingly, these novel variants are not associated with other biomarkers of hyperglycemia or diabetes (p > 0.2). The large effect sizes and protein-altering, multiple independent signals suggest SLC5A10 may code for an important transporter of 1,5-AG in the kidney, with a potential nonglucose-related effect on 1,5-AG, impacting its clinical utility as a diabetes biomarker in this subpopulation.
Keywords: Atherosclerosis; Deoxyglucose; Exome Sequencing; Female; Humans; Longitudinal Studies; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Sodium-Glucose Transport Proteins

Reproducibility and Variability of Protein Analytes Measured Using a Multiplexed Modified Aptamer Assay. - Tin, Adrienne; Yu, Bing; Ma, Jianzhong; Masushita, Kunihiro; Daya, Natalie; Hoogeveen, Ron C; Ballantyne, Christie M; Couper, David; Rebholz, Casey M; Grams, Morgan E; Alonso, Alvaro; Mosley, Thomas; et al. (J Appl Lab Med, 2019)
BACKGROUND: There is growing interest in the use of multiplexed aptamer-based assays for large-scale proteomic studies. However, the analytic, short- and long-term variation of the measured proteins is largely uncharacterized. METHODS: We quantified 4001 plasma protein analytes from 42 participants in the Atherosclerosis Risk in Communities (ARIC) Study in split samples and at multiple visits using a multiplexed modified aptamer assay. We calculated the CV, Spearman correlation, and intraclass correlation (ICC) between split samples and evaluated the short-term (4-9 weeks) and long-term (approximately 20 years) variability using paired -tests with log-transformed protein concentrations and Bonferroni-corrected significance thresholds. We performed principal component (PC) analysis of protein analyte concentrations and evaluated their associations with age, sex, race, and estimated glomerular filtration rate (eGFR). RESULTS: The mean baseline age was 57 years at the first visit, 43% of participants were male and 57% were white. Among 3693 protein analytes that passed quality control, half (n = 1846) had CVs < 5.0%, Spearman correlations > 0.89, and ICCs > 0.96 among the split samples. Over the short term, only 1 analyte had a statistically significant difference between the 2 time points, whereas, over approximately 20 years, 866 analytes (23.4%) had statistically significant differences ( < 1.4 × 10, 681 increased, 185 decreased). PC1 had high correlations with age (-0.73) and eGFR (0.60). PC2 had moderate correlation with male sex (0.18) and white race (0.31). CONCLUSIONS: Multiplexed modified aptamer technology can assay thousands of proteins with excellent precision. Our results support the potential for large-scale studies of the plasma proteome over the lifespan.
Keywords: Aged; Atherosclerosis; Blood Proteins; Equipment Design; Female; Glomerular Filtration Rate; Humans; Male; Middle Aged; Prospective Studies; Proteomics; Reproducibility of Results

Sequencing Analysis at 8p23 Identifies Multiple Rare Variants in DLC1 Associated with Sleep-Related Oxyhemoglobin Saturation Level. - Liang, Jingjing; Cade, Brian E; He, Karen Y; Wang, Heming; Lee, Jiwon; Sofer, Tamar; Williams, Stephanie; Li, Ruitong; Chen, Han; Gottlieb, Daniel J; Evans, Daniel S; Guo, Xiuqing; et al. (Am J Hum Genet, 2019)
Average arterial oxyhemoglobin saturation during sleep (AvSpOS) is a clinically relevant measure of physiological stress associated with sleep-disordered breathing, and this measure predicts incident cardiovascular disease and mortality. Using high-depth whole-genome sequencing data from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) project and focusing on genes with linkage evidence on chromosome 8p23, we observed that six coding and 51 noncoding variants in a gene that encodes the GTPase-activating protein (DLC1) are significantly associated with AvSpOS and replicated in independent subjects. The combined DLC1 association evidence of discovery and replication cohorts reaches genome-wide significance in European Americans (p = 7.9 × 10). A risk score for these variants, built on an independent dataset, explains 0.97% of the AvSpOS variation and contributes to the linkage evidence. The 51 noncoding variants are enriched in regulatory features in a human lung fibroblast cell line and contribute to DLC1 expression variation. Mendelian randomization analysis using these variants indicates a significant causal effect of DLC1 expression in fibroblasts on AvSpOS. Multiple sources of information, including genetic variants, gene expression, and methylation, consistently suggest that DLC1 is a gene associated with AvSpOS.
Keywords: Chromosomes, Human, Pair 8; Genetic Linkage; Genome-Wide Association Study; GTPase-Activating Proteins; Humans; Oxyhemoglobins; Sleep; Tumor Suppressor Proteins; Whole Genome Sequencing

Unraveling the functional role of the orphan solute carrier, SLC22A24 in the transport of steroid conjugates through metabolomic and genome-wide association studies. - Yee, Sook Wah; Stecula, Adrian; Chien, Huan-Chieh; Zou, Ling; Feofanova, Elena V; van Borselen, Marjolein; Cheung, Kit Wun Kathy; Yousri, Noha A; Suhre, Karsten; Kinchen, Jason M; Eric Boerwinkle; Irannejad, Roshanak; et al. (PLoS Genet, 2019)
Variation in steroid hormone levels has wide implications for health and disease. The genes encoding the proteins involved in steroid disposition represent key determinants of interindividual variation in steroid levels and ultimately, their effects. Beginning with metabolomic data from genome-wide association studies (GWAS), we observed that genetic variants in the orphan transporter, SLC22A24 were significantly associated with levels of androsterone glucuronide and etiocholanolone glucuronide (sentinel SNPs p-value <1x10-30). In cells over-expressing human or various mammalian orthologs of SLC22A24, we showed that steroid conjugates and bile acids were substrates of the transporter. Phylogenetic, genomic, and transcriptomic analyses suggested that SLC22A24 has a specialized role in the kidney and appears to function in the reabsorption of organic anions, and in particular, anionic steroids. Phenome-wide analysis showed that functional variants of SLC22A24 are associated with human disease such as cardiovascular diseases and acne, which have been linked to dysregulated steroid metabolism. Collectively, these functional genomic studies reveal a previously uncharacterized protein involved in steroid homeostasis, opening up new possibilities for SLC22A24 as a pharmacological target for regulating steroid levels.
Keywords: Androsterone; Animals; Biological Transport; Genome-Wide Association Study; HEK293 Cells; Humans; Metabolomics; Models, Molecular; Organic Cation Transport Proteins; Phylogeny; Polymorphism, Single Nucleotide; Steroids; Symporters

Use of >100,000 NHLBI Trans-Omics for Precision Medicine (TOPMed) Consortium whole genome sequences improves imputation quality and detection of rare variant associations in admixed African and Hispanic/Latino populations. - Kowalski, Madeline H; Qian, Huijun; Hou, Ziyi; Rosen, Jonathan D; Tapia, Amanda L; Shan, Yue; Jain, Deepti; Argos, Maria; Arnett, Donna K; Avery, Christy; Barnes, Kathleen C; Becker, Lewis C; et al. (PLoS Genet, 2019)
Most genome-wide association and fine-mapping studies to date have been conducted in individuals of European descent, and genetic studies of populations of Hispanic/Latino and African ancestry are limited. In addition, these populations have more complex linkage disequilibrium structure. In order to better define the genetic architecture of these understudied populations, we leveraged >100,000 phased sequences available from deep-coverage whole genome sequencing through the multi-ethnic NHLBI Trans-Omics for Precision Medicine (TOPMed) program to impute genotypes into admixed African and Hispanic/Latino samples with genome-wide genotyping array data. We demonstrated that using TOPMed sequencing data as the imputation reference panel improves genotype imputation quality in these populations, which subsequently enhanced gene-mapping power for complex traits. For rare variants with minor allele frequency (MAF) < 0.5%, we observed a 2.3- to 6.1-fold increase in the number of well-imputed variants, with 11-34% improvement in average imputation quality, compared to the state-of-the-art 1000 Genomes Project Phase 3 and Haplotype Reference Consortium reference panels. Impressively, even for extremely rare variants with minor allele count <10 (including singletons) in the imputation target samples, average information content rescued was >86%. Subsequent association analyses of TOPMed reference panel-imputed genotype data with hematological traits (hemoglobin (HGB), hematocrit (HCT), and white blood cell count (WBC)) in ~21,600 African-ancestry and ~21,700 Hispanic/Latino individuals identified associations with two rare variants in the HBB gene (rs33930165 with higher WBC [p = 8.8x10-15] in African populations, rs11549407 with lower HGB [p = 1.5x10-12] and HCT [p = 8.8x10-10] in Hispanics/Latinos). By comparison, neither variant would have been genome-wide significant if either 1000 Genomes Project Phase 3 or Haplotype Reference Consortium reference panels had been used for imputation. Our findings highlight the utility of the TOPMed imputation reference panel for identification of novel rare variant associations not previously detected in similarly sized genome-wide studies of under-represented African and Hispanic/Latino populations.
Keywords: Adult; Aged; Aged, 80 and over; beta-Globins; Black or African American; Computational Biology; Databases, Genetic; Female; Gene Frequency; Genetic Predisposition to Disease; Genetics, Population; Genome-Wide Association Study; Genotyping Techniques; Hispanic or Latino; Humans; Linkage Disequilibrium; Male; Middle Aged; Precision Medicine; United States; Whole Genome Sequencing

A biallelic ANTXR1 variant expands the anthrax toxin receptor associated phenotype to tooth agenesis. - Dinckan, Nuriye; Du, Renqian; Akdemir, Zeynep C; Bayram, Yavuz; Jhangiani, Shalini N; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Eric Boerwinkle; et al. (Am J Med Genet A, 2018)
Tooth development is regulated by multiple genetic pathways, which ultimately drive the complex interactions between the oral epithelium and mesenchyme. Disruptions at any time point during this process may lead to failure of tooth development, also known as tooth agenesis (TA). TA is a common craniofacial abnormality in humans and represents the failure to develop one or more permanent teeth. Many genes and potentially subtle variants in these genes contribute to the TA phenotype. We report the clinical and genetic impact of a rare homozygous ANTXR1 variant (c.1312C>T), identified by whole exome sequencing (WES), in a consanguineous Turkish family with TA. Mutations in ANTXR1 have been associated with GAPO (growth retardation, alopecia, pseudoanodontia, and optic atrophy) syndrome and infantile hemangioma, however no clinical characteristics associated with these conditions were observed in our study family. We detected the expression of Antxr1 in oral and dental tissues of developing mouse embryos, further supporting a role for this gene in tooth development. Our findings implicate ANTXR1 as a candidate gene for isolated TA, suggest the involvement of specific hypomorphic alleles, and expand the previously known ANTXR1-associated phenotypes.
Keywords: Alleles; Amino Acid Substitution; Animals; Anodontia; Child; Consanguinity; Exome Sequencing; Facies; Genetic Association Studies; Genotype; Humans; Male; Mice; Microfilament Proteins; Mutation; Neoplasm Proteins; Pedigree; Phenotype; Radiography; Receptors, Cell Surface

Blood pressure signature genes and blood pressure response to thiazide diuretics: results from the PEAR and PEAR-2 studies. - Sá, Ana Caroline C; Webb, Amy; Gong, Yan; McDonough, Caitrin W; Shahin, Mohamed H; Datta, Somnath; Langaee, Taimour Y; Turner, Stephen T; Beitelshees, Amber L; Chapman, Arlene B; Eric Boerwinkle; Gums, John G; et al. (BMC Med Genomics, 2018)
BACKGROUND: Recently, 34 genes had been associated with differential expression relative to blood pressure (BP)/ hypertension (HTN). We hypothesize that some of the genes associated with BP/HTN are also associated with BP response to antihypertensive treatment with thiazide diuretics. METHODS: We assessed these 34 genes for association with differential expression to BP response to thiazide diuretics with RNA sequencing in whole blood samples from 150 hypertensive participants from the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) and PEAR-2 studies. PEAR white and PEAR-2 white and black participants (n = 50 for each group) were selected based on the upper and lower quartile of BP response to hydrochlorothiazide (HCTZ) and to chlorthalidone. RESULTS: FOS, DUSP1 and PPP1R15A were differentially expressed across all cohorts (meta-analysis p-value < 2.0 × 10), and responders to HCTZ or chlorthalidone presented up-regulated transcripts. Rs11065987 in chromosome 12, a trans-eQTL for expression of FOS, PPP1R15A and other genes, is also associated with BP response to HCTZ in PEAR whites (SBP: β = - 2.1; p = 1.7 × 10; DBP: β = - 1.4; p = 2.9 × 10). CONCLUSIONS: These findings suggest FOS, DUSP1 and PPP1R15A as potential molecular determinants of antihypertensive response to thiazide diuretics. TRIAL REGISTRATION: NCT00246519 , NCT01203852 www.clinicaltrials.gov.
Keywords: Antihypertensive Agents; Blood Pressure; Female; Gene Expression Profiling; Humans; Hypertension; Male; Middle Aged; Pharmacogenomic Testing; Sodium Chloride Symporter Inhibitors

CD163+ macrophages promote angiogenesis and vascular permeability accompanied by inflammation in atherosclerosis. - Guo, Liang; Akahori, Hirokuni; Harari, Emanuel; Smith, Samantha L; Polavarapu, Rohini; Karmali, Vinit; Otsuka, Fumiyuki; Gannon, Rachel L; Braumann, Ryan E; Dickinson, Megan H; Gupta, Anuj; Jenkins, Audrey L; et al. (J Clin Invest, 2018)
Intake of hemoglobin by the hemoglobin-haptoglobin receptor CD163 leads to a distinct alternative non-foam cell antiinflammatory macrophage phenotype that was previously considered atheroprotective. Here, we reveal an unexpected but important pathogenic role for these macrophages in atherosclerosis. Using human atherosclerotic samples, cultured cells, and a mouse model of advanced atherosclerosis, we investigated the role of intraplaque hemorrhage on macrophage function with respect to angiogenesis, vascular permeability, inflammation, and plaque progression. In human atherosclerotic lesions, CD163+ macrophages were associated with plaque progression, microvascularity, and a high level of HIF1α and VEGF-A expression. We observed irregular vascular endothelial cadherin in intraplaque microvessels surrounded by CD163+ macrophages. Within these cells, activation of HIF1α via inhibition of prolyl hydroxylases promoted VEGF-mediated increases in intraplaque angiogenesis, vascular permeability, and inflammatory cell recruitment. CD163+ macrophages increased intraplaque endothelial VCAM expression and plaque inflammation. Subjects with homozygous minor alleles of the SNP rs7136716 had elevated microvessel density, increased expression of CD163 in ruptured coronary plaques, and a higher risk of myocardial infarction and coronary heart disease in population cohorts. Thus, our findings highlight a nonlipid-driven mechanism by which alternative macrophages promote plaque angiogenesis, leakiness, inflammation, and progression via the CD163/HIF1α/VEGF-A pathway.
Keywords: Adult; Animals; Antigens, CD; Antigens, Differentiation, Myelomonocytic; Atherosclerosis; Coronary Disease; Coronary Vessels; Disease Progression; Female; Hemoglobins; Humans; Inflammation; Macrophages; Male; Mice; Mice, Inbred C57BL; Middle Aged; Myocardial Infarction; Neovascularization, Pathologic; Oxidative Stress; Permeability; Phenotype; Polymorphism, Single Nucleotide; Receptors, Cell Surface; Signal Transduction

Common Coding Variants in Are Associated With the Nav1.8 Late Current and Cardiac Conduction. - Macri, Vincenzo; Brody, Jennifer A; Arking, Dan E; Hucker, William J; Yin, Xiaoyan; Lin, Honghuang; Mills, Robert W; Sinner, Moritz F; Lubitz, Steven A; Liu, Ching-Ti; Morrison, Alanna C; Alonso, Alvaro; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Genetic variants at the / locus are strongly associated with electrocardiographic PR and QRS intervals. While is the canonical cardiac sodium channel gene, the role of in cardiac conduction is less well characterized. METHODS: We sequenced the locus in 3699 European-ancestry individuals to identify variants associated with cardiac conduction, and replicated our findings in 21,000 individuals of European ancestry. We examined association with expression in human atrial tissue. We explored the biophysical effect of variation on channel function using cellular electrophysiology. RESULTS: We identified 2 intronic single nucleotide polymorphisms in high linkage disequilibrium (  =0.86) with each other to be the strongest signals for PR (rs10428132, β=-4.74, =1.52×10) and QRS intervals (rs6599251, QRS β=-0.73; =1.2×10), respectively. Although these variants were not associated with or expression in human atrial tissue (n=490), they were in high linkage disequilibrium (  ≥0.72) with a common missense variant, rs6795970 (V1073A). In total, we identified 7 missense variants, 4 of which (I962V, P1045T, V1073A, and L1092P) were associated with cardiac conduction. These 4 missense variants cluster in the cytoplasmic linker of the second and third domains of the SCN10A protein and together form 6 common haplotypes. Using cellular electrophysiology, we found that haplotypes associated with shorter PR intervals had a significantly larger percentage of late current compared with wild-type (I962V+V1073A+L1092P, 20.2±3.3%, =0.03, and I962V+V1073A, 22.4±0.8%, =0.0004 versus wild-type 11.7±1.6%), and the haplotype associated with the longest PR interval had a significantly smaller late current percentage (P1045T, 6.4±1.2%, =0.03). CONCLUSIONS: Our findings suggest an association between genetic variation in , the late sodium current, and alterations in cardiac conduction.
Keywords: Biophysical Phenomena; Electrocardiography; Genetic Association Studies; Haplotypes; Heart Conduction System; Humans; Ion Channel Gating; Mutation, Missense; NAV1.8 Voltage-Gated Sodium Channel; Polymorphism, Single Nucleotide; Quantitative Trait Loci

Comprehensive genomic analysis of patients with disorders of cerebral cortical development. - Wiszniewski, Wojciech; Gawlinski, Pawel; Gambin, Tomasz; Bekiesinska-Figatowska, Monika; Obersztyn, Ewa; Antczak-Marach, Dorota; Akdemir, Zeynep Hande Coban; Harel, Tamar; Karaca, Ender; Jurek, Marta; Sobecka, Katarzyna; Nowakowska, Beata; et al. (Eur J Hum Genet, 2018)
Malformations of cortical development (MCDs) manifest with structural brain anomalies that lead to neurologic sequelae, including epilepsy, cerebral palsy, developmental delay, and intellectual disability. To investigate the underlying genetic architecture of patients with disorders of cerebral cortical development, a cohort of 54 patients demonstrating neuroradiologic signs of MCDs was investigated. Individual genomes were interrogated for single-nucleotide variants (SNV) and copy number variants (CNV) with whole-exome sequencing and chromosomal microarray studies. Variation affecting known MCDs-associated genes was found in 16/54 cases, including 11 patients with SNV, 2 patients with CNV, and 3 patients with both CNV and SNV, at distinct loci. Diagnostic pathogenic SNV and potentially damaging variants of unknown significance (VUS) were identified in two groups of seven individuals each. We demonstrated that de novo variants are important among patients with MCDs as they were identified in 10/16 individuals with a molecular diagnosis. Three patients showed changes in known MCDs genes  and a clinical phenotype beyond the usual characteristics observed, i.e., phenotypic expansion, for a particular known disease gene clinical entity. We also discovered 2 likely candidate genes, CDH4, and ASTN1, with human and animal studies supporting their roles in brain development, and 5 potential candidate genes. Our findings emphasize genetic heterogeneity of MCDs disorders and postulate potential novel candidate genes involved in cerebral cortical development.
Keywords: Cadherins; DNA Copy Number Variations; Exome; Female; Genetic Heterogeneity; Humans; Male; Malformations of Cortical Development; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Receptors, Cell Surface

Contributions of rare coding variants in hypotension syndrome genes to population blood pressure variation. - Nandakumar, Priyanka; Morrison, Alanna C; Grove, Megan L; Eric Boerwinkle; Chakravarti, Aravinda (Medicine (Baltimore), 2018)
Rare variants, in particular renal salt handling genes, contribute to monogenic forms of hypertension and hypotension syndromes with electrolyte abnormalities. A study by Ji et al (2008) demonstrated this effect for rare loss-of-function coding variants in SLC12A3 (NCCT), SLC12A1 (NKCC2), and KCNJ1 (ROMK) that led to reduction of ∼6 mm Hg for SBP and ∼3 mm Hg for DBP among carriers in 2492 European ancestry Framingham Heart Study (FHS) subjects. These findings support a potentially large role for these variants in interindividual variation in systolic and diastolic blood pressure (SBP, DBP) in the population. The present study focuses on replicating the analyses completed by Ji et al to identify effects of rare variants in the population-based Atherosclerosis Risk in Communities (ARIC) study.We attempted to replicate the findings by Ji et al by applying their criteria to identify putative loss-of-function variants with allele frequency <0.001 and complete conservation across a set of orthologs, to exome sequencing data from 7444 European ancestry participants of the ARIC study.Although we failed to replicate the previous findings when applying their methods to the ARIC study data, we observed a similar effect when we restricted analyses to the subset of variants they observed.These results simultaneously support the utility of exome sequencing data for studying extremely rare coding variants in hypertension and underscore the need for improved filtering methods for identifying functional variants in human sequences.
Keywords: Black People; Blood Pressure; Exome Sequencing; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Hypertension; Hypotension; Male; Middle Aged; Phenotype; Potassium Channels, Inwardly Rectifying; Prospective Studies; Reproducibility of Results; Risk Factors; Solute Carrier Family 12, Member 1; Solute Carrier Family 12, Member 3; White People

DNA methylation age is associated with an altered hemostatic profile in a multiethnic meta-analysis. - Ward-Caviness, Cavin K; Huffman, Jennifer E; Everett, Karl; Germain, Marine; van Dongen, Jenny; Hill, W David; Jhun, Min A; Brody, Jennifer A; Ghanbari, Mohsen; Du, Lei; Roetker, Nicholas S; de Vries, Paul S; et al. (Blood, 2018)
Many hemostatic factors are associated with age and age-related diseases; however, much remains unknown about the biological mechanisms linking aging and hemostatic factors. DNA methylation is a novel means by which to assess epigenetic aging, which is a measure of age and the aging processes as determined by altered epigenetic states. We used a meta-analysis approach to examine the association between measures of epigenetic aging and hemostatic factors, as well as a clotting time measure. For fibrinogen, we performed European and African ancestry-specific meta-analyses which were then combined via a random effects meta-analysis. For all other measures we could not estimate ancestry-specific effects and used a single fixed effects meta-analysis. We found that 1-year higher extrinsic epigenetic age as compared with chronological age was associated with higher fibrinogen (0.004 g/L/y; 95% confidence interval, 0.001-0.007; = .01) and plasminogen activator inhibitor 1 (PAI-1; 0.13 U/mL/y; 95% confidence interval, 0.07-0.20; = 6.6 10) concentrations, as well as lower activated partial thromboplastin time, a measure of clotting time. We replicated PAI-1 associations using an independent cohort. To further elucidate potential functional mechanisms, we associated epigenetic aging with expression levels of the PAI-1 protein encoding gene () and the 3 fibrinogen subunit-encoding genes (, , and ) in both peripheral blood and aorta intima-media samples. We observed associations between accelerated epigenetic aging and transcription of in both tissues. Collectively, our results indicate that accelerated epigenetic aging is associated with a procoagulation hemostatic profile, and that epigenetic aging may regulate hemostasis in part via gene transcription.
Keywords: Aging; DNA Methylation; Epigenesis, Genetic; Hemostasis; Humans

Effects of Gender-Specific Differences, Inflammatory Response, and Genetic Variation on the Associations Among Depressive Symptoms and the Risk of Major Adverse Coronary Events in Patients With Acute Coronary Syndrome. - Sanner, Jennifer; Grove, Megan L; Yu, Erica; Moeller, F Gerard; Cron, Stanley G; Eric Boerwinkle; Morrison, Alanna C; Frazier, Lorraine (Biol Res Nurs, 2018)
Depressive symptoms independently contribute to major adverse coronary events (MACEs), with the biological immune response to depression being a likely mediator of this relationship. To determine whether genetic- and/or gender-specific phenotypic differences contribute to associations among depressive symptoms, inflammatory response, and risk of MACE in patients with acute coronary syndrome (ACS), we conducted a prospective study of 1,117 ACS patients to test a gender-specific model in which depressive symptoms (Beck Depression Inventory-II [BDI-II]) are associated with risk of MACE. Cox proportional hazards models were used to model time to incident MACE and determine whether single-nucleotide polymorphisms (SNPs) in specific inflammatory protein-coding genes and depressive symptoms interact to influence levels of inflammatory proteins or risk of MACE. Females had significantly higher high-sensitivity C-reactive protein and monocyte chemoattractant protein-1 levels. Depression status differed by gender (29.9% of females and 21.1% of males had BDI-II scores indicative of depression [ p = .0014]). Depressive symptoms were associated with MACE; however, the interaction between these symptoms and gender was not significant. SNPs and depressive symptoms did not interact to influence inflammation or MACE. More females than males had BDI-II scores indicative of depression, yet the association between positive depressive symptom status and MACE did not vary by gender. Nor did the SNPs interact with depressive symptoms to influence inflammation or MACE. It remains of interest to identify a high-risk subgroup of ACS patients with genetic polymorphisms that result in immunoinflammatory dysregulation in the presence of depressive symptoms.
Keywords: Acute Coronary Syndrome; Aged; Depression; Female; Genetic Variation; Humans; Inflammation; Male; Middle Aged; Prospective Studies; Risk Assessment; Sex Factors

Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
High blood pressure is a highly heritable and modifiable risk factor for cardiovascular disease. We report the largest genetic association study of blood pressure traits (systolic, diastolic and pulse pressure) to date in over 1 million people of European ancestry. We identify 535 novel blood pressure loci that not only offer new biological insights into blood pressure regulation but also highlight shared genetic architecture between blood pressure and lifestyle exposures. Our findings identify new biological pathways for blood pressure regulation with potential for improved cardiovascular disease prevention in the future.
Keywords: Adult; Aged; Aged, 80 and over; Blood Pressure; Cardiovascular Diseases; Cells, Cultured; Female; Genetic Loci; Genetic Predisposition to Disease; Genetic Testing; Genetics, Population; Genome-Wide Association Study; Human Umbilical Vein Endothelial Cells; Humans; Hypertension; Life Style; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Genetic variants in microRNA genes and targets associated with cardiovascular disease risk factors in the African-American population. - Li, Chang; Grove, Megan L; Yu, Bing; Jones, Barbara C; Morrison, Alanna; Eric Boerwinkle; Liu, Xiaoming (Hum Genet, 2018)
The purpose of this study is to identify microRNA (miRNA) related polymorphism, including single nucleotide variants (SNVs) in mature miRNA-encoding sequences or in miRNA-target sites, and their association with cardiovascular disease (CVD) risk factors in African-American population. To achieve our objective, we examined 1900 African-Americans from the Atherosclerosis Risk in Communities study using SNVs identified from whole-genome sequencing data. A total of 971 SNVs found in 726 different mature miRNA-encoding sequences and 16,057 SNVs found in the three prime untranslated region (3'UTR) of 3647 protein-coding genes were identified and interrogated their associations with 17 CVD risk factors. Using single-variant-based approach, we found 5 SNVs in miRNA-encoding sequences to be associated with serum Lipoprotein(a) [Lp(a)], high-density lipoprotein (HDL) or triglycerides, and 2 SNVs in miRNA-target sites to be associated with Lp(a) and HDL, all with false discovery rates of 5%. Using a gene-based approach, we identified 3 pairs of associations between gene NSD1 and platelet count, gene HSPA4L and cardiac troponin T, and gene AHSA2 and magnesium. We successfully validated the association between a variant specific to African-American population, NR_039880.1:n.18A>C, in mature hsa-miR-4727-5p encoding sequence and serum HDL level in an independent sample of 2135 African-Americans. Our study provided candidate miRNAs and their targets for further investigation of their potential contribution to ethnic disparities in CVD risk factors.
Keywords: 3' Untranslated Regions; Adult; Black or African American; Cardiovascular Diseases; Female; Genetic Predisposition to Disease; Genotyping Techniques; Humans; Male; MicroRNAs; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; Whole Genome Sequencing

Genetic Variants in SGLT1, Glucose Tolerance, and Cardiometabolic Risk. - Seidelmann, Sara B; Feofanova, Elena; Yu, Bing; Franceschini, Nora; Claggett, Brian; Kuokkanen, Mikko; Puolijoki, Hannu; Ebeling, Tapani; Perola, Markus; Salomaa, Veikko; Shah, Amil; Coresh, Josef; et al. (J Am Coll Cardiol, 2018)
BACKGROUND: Loss-of-function mutations in the SGLT1 (sodium/glucose co-transporter-1) gene result in a rare glucose/galactose malabsorption disorder and neonatal death if untreated. In the general population, variants related to intestinal glucose absorption remain uncharacterized. OBJECTIVES: The goal of this study was to identify functional SGLT1 gene variants and characterize their clinical consequences. METHODS: Whole exome sequencing was performed in the ARIC (Atherosclerosis Risk in Communities) study participants enrolled from 4 U.S. communities. The association of functional, nonsynonymous substitutions in SGLT1 with 2-h oral glucose tolerance test results was determined. Variants related to impaired glucose tolerance were studied, and Mendelian randomization analysis of cardiometabolic outcomes was performed. RESULTS: Among 5,687 European-American subjects (mean age 54 ± 6 years; 47% male), those who carried a haplotype of 3 missense mutations (frequency of 6.7%)-Asn51Ser, Ala411Thr, and His615Gln-had lower 2-h glucose and odds of impaired glucose tolerance than noncarriers (β-coefficient: -8.0; 95% confidence interval [CI]: -12.7 to -3.3; OR: 0.71; 95% CI: 0.59 to 0.86, respectively). The association of the haplotype with oral glucose tolerance test results was consistent in a replication sample of 2,791 African-American subjects (β = -16.3; 95% CI: -36.6 to 4.1; OR: 0.39; 95% CI: 0.17 to 0.91) and an external European-Finnish population sample of 6,784 subjects (β = -3.2; 95% CI: -6.4 to -0.02; OR: 0.81; 95% CI: 0.68 to 0.98). Using a Mendelian randomization approach in the index cohort, the estimated 25-year effect of a reduction of 20 mg/dl in 2-h glucose via SGLT1 inhibition would be reduced prevalent obesity (OR: 0.43; 95% CI: 0.23 to 0.63), incident diabetes (hazard ratio [HR]: 0.58; 95% CI: 0.35 to 0.81), heart failure (HR: 0.53; 95% CI: 0.24 to 0.83), and death (HR: 0.66; 95% CI: 0.42 to 0.90). CONCLUSIONS: Functionally damaging missense variants in SGLT1 protect from diet-induced hyperglycemia in multiple populations. Reduced intestinal glucose uptake may protect from long-term cardiometabolic outcomes, providing support for therapies that target SGLT1 function to prevent and treat metabolic conditions.
Keywords: Cardiovascular Diseases; Exome Sequencing; Female; Genetic Variation; Glucose; Glucose Tolerance Test; Humans; Hyperglycemia; Intestinal Absorption; Loss of Function Mutation; Male; Mendelian Randomization Analysis; Middle Aged; Outcome Assessment, Health Care; Protective Factors; Risk Assessment; Sodium-Glucose Transporter 1; United States; White People

Genetic Variants Influencing Plasma Renin Activity in Hypertensive Patients From the PEAR Study (Pharmacogenomic Evaluation of Antihypertensive Responses). - McDonough, Caitrin W; Magvanjav, Oyunbileg; Sá, Ana C C; El Rouby, Nihal M; Dave, Chintan; Deitchman, Amelia N; Kawaguchi-Suzuki, Marina; Mei, Wenbin; Shen, Yong; Singh, Ravi Shankar Prasad; Solayman, Mohamed; Bailey, Kent R; et al. (Circ Genom Precis Med, 2018)
BACKGROUND: Plasma renin is an important regulator of blood pressure (BP). Plasma renin activity (PRA) has been shown to correlate with variability in BP response to antihypertensive agents. We conducted a genome-wide association study to identify single-nucleotide polymorphisms (SNPs) associated with baseline PRA using data from the PEAR study (Pharmacogenomic Evaluation of Antihypertensive Responses). METHODS: Multiple linear regression analysis was performed in 461 whites and 297 blacks using an additive model, adjusting for age, sex, and ancestry-specific principal components. Top SNPs were prioritized by testing the expected direction of association for BP response to atenolol and hydrochlorothiazide. Top regions from the BP response prioritization were tested for functional evidence through differences in gene expression by genotype using RNA sequencing data. Regions with functional evidence were assessed for replication with baseline PRA in an independent study (PEAR-2). RESULTS: Our top SNP rs3784921 was in the gene region. The G allele of rs3784921 was associated with higher baseline PRA (β=0.47; =2.09×10) and smaller systolic BP reduction in response to hydrochlorothiazide (β=2.97; 1-sided =0.006). In addition, expression differed by rs3784921 genotype (=0.007), and rs1802409, a proxy SNP for rs3784921 (=0.98-1.00), replicated in PEAR-2 (β=0.15; 1-sided =0.038). Additional SNPs associated with baseline PRA that passed BP response prioritization were in/near the genes and CONCLUSIONS: We identified multiple regions associated with baseline PRA that were prioritized through BP response signals to 2 mechanistically different antihypertensive drugs. CLINICAL TRIAL REGISTRATION: URL: https://www.clinicaltrials.gov. Unique identifier: NCT00246519.
Keywords: Adolescent; Adult; Aged; Antihypertensive Agents; Atenolol; Blood Pressure; Genome-Wide Association Study; Humans; Hydrochlorothiazide; Hypertension; Male; Middle Aged; Pharmacogenomic Variants; Polymorphism, Single Nucleotide; Prospective Studies; Renin; Treatment Outcome; United States; Young Adult

Genome Analyses of >200,000 Individuals Identify 58 Loci for Chronic Inflammation and Highlight Pathways that Link Inflammation and Complex Disorders. - Ligthart, Symen; Vaez, Ahmad; Võsa, Urmo; Stathopoulou, Maria G; de Vries, Paul S; Prins, Bram P; van der Most, Peter J; Tanaka, Toshiko; Naderi, Elnaz; Rose, Lynda M; Wu, Ying; Karlsson, Robert; et al. (Am J Hum Genet, 2018)
C-reactive protein (CRP) is a sensitive biomarker of chronic low-grade inflammation and is associated with multiple complex diseases. The genetic determinants of chronic inflammation remain largely unknown, and the causal role of CRP in several clinical outcomes is debated. We performed two genome-wide association studies (GWASs), on HapMap and 1000 Genomes imputed data, of circulating amounts of CRP by using data from 88 studies comprising 204,402 European individuals. Additionally, we performed in silico functional analyses and Mendelian randomization analyses with several clinical outcomes. The GWAS meta-analyses of CRP revealed 58 distinct genetic loci (p < 5 × 10). After adjustment for body mass index in the regression analysis, the associations at all except three loci remained. The lead variants at the distinct loci explained up to 7.0% of the variance in circulating amounts of CRP. We identified 66 gene sets that were organized in two substantially correlated clusters, one mainly composed of immune pathways and the other characterized by metabolic pathways in the liver. Mendelian randomization analyses revealed a causal protective effect of CRP on schizophrenia and a risk-increasing effect on bipolar disorder. Our findings provide further insights into the biology of inflammation and could lead to interventions for treating inflammation and its clinical consequences.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Biomarkers; Bipolar Disorder; Body Mass Index; C-Reactive Protein; Child; Female; Genetic Loci; Genome-Wide Association Study; Humans; Inflammation; Liver; Male; Mendelian Randomization Analysis; Metabolic Networks and Pathways; Middle Aged; Schizophrenia; Young Adult

GWAS and colocalization analyses implicate carotid intima-media thickness and carotid plaque loci in cardiovascular outcomes. - Franceschini, Nora; Giambartolomei, Claudia; de Vries, Paul S; Finan, Chris; Bis, Joshua C; Huntley, Rachael P; Lovering, Ruth C; Tajuddin, Salman M; Winkler, Thomas W; Graff, Misa; Kavousi, Maryam; Dale, Caroline; et al. (Nat Commun, 2018)
Carotid artery intima media thickness (cIMT) and carotid plaque are measures of subclinical atherosclerosis associated with ischemic stroke and coronary heart disease (CHD). Here, we undertake meta-analyses of genome-wide association studies (GWAS) in 71,128 individuals for cIMT, and 48,434 individuals for carotid plaque traits. We identify eight novel susceptibility loci for cIMT, one independent association at the previously-identified PINX1 locus, and one novel locus for carotid plaque. Colocalization analysis with nearby vascular expression quantitative loci (cis-eQTLs) derived from arterial wall and metabolic tissues obtained from patients with CHD identifies candidate genes at two potentially additional loci, ADAMTS9 and LOXL4. LD score regression reveals significant genetic correlations between cIMT and plaque traits, and both cIMT and plaque with CHD, any stroke subtype and ischemic stroke. Our study provides insights into genes and tissue-specific regulatory mechanisms linking atherosclerosis both to its functional genomic origins and its clinical consequences in humans.
Keywords: ADAMTS9 Protein; Amino Acid Oxidoreductases; Carotid Intima-Media Thickness; Coronary Disease; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Lod Score; Plaque, Atherosclerotic; Polymorphism, Single Nucleotide; Protein-Lysine 6-Oxidase; Quantitative Trait Loci; Risk Factors

Identification of likely pathogenic and known variants in TSPEAR, LAMB3, BCOR, and WNT10A in four Turkish families with tooth agenesis. - Du, Renqian; Dinckan, Nuriye; Song, Xiaofei; Coban-Akdemir, Zeynep; Jhangiani, Shalini N; Guven, Yeliz; Aktoren, Oya; Kayserili, Hulya; Petty, Lauren E; Donna M Muzny; Below, Jennifer E; Eric Boerwinkle; et al. (Hum Genet, 2018)
Tooth agenesis (TA), the failure of development of one or more permanent teeth, is a common craniofacial abnormality observed in different world populations. The genetic etiology of TA is heterogeneous; more than a dozen genes have been associated with isolated or nonsyndromic TA, and more than 80 genes with syndromic forms. In this study, we applied whole exome sequencing (WES) to identify candidate genes contributing to TA in four Turkish families. Likely pathogenic variants with a low allele frequency in the general population were identified in four disease-associated genes, including two distinct variants in TSPEAR, associated with syndromic and isolated TA in one family each; a variant in LAMB3 associated with syndromic TA in one family; and a variant in BCOR plus a disease-associated WNT10A variant in one family with syndromic TA. With the notable exception of WNT10A (Tooth agenesis, selective, 4, MIM #150400), the genotype-phenotype relationships described in the present cohort represent an expansion of the clinical spectrum associated with these genes: TSPEAR (Deafness, autosomal recessive 98, MIM #614861), LAMB3 (Amelogenesis imperfecta, type IA, MIM #104530; Epidermolysis bullosa, junctional, MIMs #226700 and #226650), and BCOR (Microphthalmia, syndromic 2, MIM #300166). We provide evidence supporting the candidacy of these genes with TA, and propose TSPEAR as a novel nonsyndromic TA gene. Our data also suggest potential multilocus genomic variation, or mutational burden, in a single family, involving the BCOR and WNT10A loci, underscoring the complexity of the genotype-phenotype relationship in the common complex trait of TA.
Keywords: Anodontia; Cell Adhesion Molecules; Child; Child, Preschool; Female; Genetic Markers; Humans; Kalinin; Male; Mutation; Pedigree; Phenotype; Proteins; Proto-Oncogene Proteins; Repressor Proteins; Turkey; Wnt Proteins

Identifying Genes Whose Mutant Transcripts Cause Dominant Disease Traits by Potential Gain-of-Function Alleles. - Coban-Akdemir, Zeynep; White, Janson J; Song, Xiaofei; Jhangiani, Shalini N; Fatih, Jawid M; Gambin, Tomasz; Bayram, Yavuz; Chinn, Ivan K; Karaca, Ender; Punetha, Jaya; Poli, Cecilia; Eric Boerwinkle; et al. (Am J Hum Genet, 2018)
Premature termination codon (PTC)-bearing transcripts are often degraded by nonsense-mediated decay (NMD) resulting in loss-of-function (LoF) alleles. However, not all PTCs result in LoF mutations, i.e., some such transcripts escape NMD and are translated to truncated peptide products that result in disease due to gain-of-function (GoF) effects. Since the location of the PTC is a major factor determining transcript fate, we hypothesized that depletion of protein-truncating variants (PTVs) within the gene region predicted to escape NMD in control databases could provide a rank for genic susceptibility for disease through GoF versus LoF. We developed an NMD escape intolerance score to rank genes based on the depletion of PTVs that would render them able to escape NMD using the Atherosclerosis Risk in Communities Study (ARIC) and the Exome Aggregation Consortium (ExAC) control databases, which was further used to screen the Baylor-Center for Mendelian Genomics disease database. This analysis revealed 1,996 genes significantly depleted for PTVs that are predicted to escape from NMD, i.e., PTVesc; further studies provided evidence that revealed a subset as candidate genes underlying Mendelian phenotypes. Importantly, these genes have characteristically low pLI scores, which can cause them to be overlooked as candidates for dominant diseases. Collectively, we demonstrate that this NMD escape intolerance score is an effective and efficient tool for gene discovery in Mendelian diseases due to production of truncated or altered proteins. More importantly, we provide a complementary analytical tool to aid identification of genes associated with dominant traits through a mechanism distinct from LoF.
Keywords: Alleles; Codon, Nonsense; Databases, Genetic; Exome; Gain of Function Mutation; Humans; Mutation; Nonsense Mediated mRNA Decay; Phenotype

Interaction between manganese and in relation to autism spectrum disorder while controlling for exposure to mixture of lead, mercury, arsenic, and cadmium. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Lee, MinJae; Christian, MacKinsey A; Bressler, Jan; Hessabi, Manouchehr; Grove, Megan L; Shakespeare-Pellington, Sydonnie; Desai, Charlene Coore; Reece, Jody-Ann; Loveland, Katherine A; Beecher, Compton; et al. (Res Autism Spectr Disord, 2018)
BACKGROUND: We previously reported a significant interactive association between polymorphisms of and blood manganese concentrations (BMC) with autism spectrum disorder (ASD) in Jamaican children. In this paper, we investigate the same interactive association with ASD while adjusting for the mixture of four metals (lead, mercury, cadmium, and arsenic). METHOD: We used data from 163 case-control pairs of children 2-8 years of age from our autism project in Jamaica, in which we collected blood for heavy metals analysis at enrollment. To minimize potential multicollinearity between concentrations of the four metals, we generated a mixture index using generalized weighted quantile sum regression, which was used in conditional logistic regression models to control for the four metals while assessing the interactive association between and BMC with ASD. RESULTS: Similar to the findings we reported previously, we found that in co-dominant and dominant models for among children with the Ile/Ile genotype, those with BMC > 12μg/L had 4.6 and 4.27 times higher odds of ASD compared to those with BMC < 12μg/L (adjusted Matched Odds Ratio (MOR) = 4.6, 95% CI: 1.21 - 17.42 and adjusted MOR = 4.27, 95% CI: 1.15 - 15.85, respectively). In the co-dominant model, for children with the Ile/Val and Val/Val genotypes, the adjusted MORs were 1.26 (95% CI: 0.32, 5.01) and 0.26 (95% CI: 0.05, 1.42), respectively. CONCLUSIONS: After adjusting for the mixture of four metals, the interactive association of BMC and with ASD remained significant with similar magnitude of associations. Results should be interpreted cautiously.

Maternal Exposures Associated with Autism Spectrum Disorder in Jamaican Children. - Christian, MacKinsey A; Samms-Vaughan, Maureen; Lee, MinJae; Bressler, Jan; Hessabi, Manouchehr; Grove, Megan L; Shakespeare-Pellington, Sydonnie; Coore Desai, Charlene; Reece, Jody-Ann; Loveland, Katherine A; Eric Boerwinkle; Rahbar, Mohammad H (J Autism Dev Disord, 2018)
Autism spectrum disorder (ASD) is a complex neurodevelopmental disorder with poorly understood etiology. Many maternal exposures during pregnancy and breastfeeding potentially interfere with neurodevelopment. Using data from two age- and sex-matched case-control studies in Jamaica (n = 298 pairs), results of conditional logistic regression analyses suggest that maternal exposures to fever or infection (matched odds ratio (MOR) = 3.12, 95% CI 1.74-5.60), physical trauma (MOR 2.02, 95% CI 1.01-4.05), and oil-based paints (MOR 1.99, 95% CI 1.14-3.46) may be associated with ASD. Additionally, maternal exposure to oil-based paints may modify the relationship between maternal exposure to pesticides and ASD, which deepens our understanding of the association between pesticides and ASD.
Keywords: Adult; Autism Spectrum Disorder; Child; Communicable Diseases; Female; Humans; Jamaica; Male; Maternal Exposure; Pesticides; Pregnancy; Volatile Organic Compounds

Multi-ethnic genome-wide association study for atrial fibrillation. - Roselli, Carolina; Chaffin, Mark D; Weng, Lu-Chen; Aeschbacher, Stefanie; Ahlberg, Gustav; Albert, Christine M; Almgren, Peter; Alonso, Alvaro; Anderson, Christopher D; Aragam, Krishna G; Arking, Dan E; Barnard, John; et al. (Nat Genet, 2018)
Atrial fibrillation (AF) affects more than 33 million individuals worldwide and has a complex heritability. We conducted the largest meta-analysis of genome-wide association studies (GWAS) for AF to date, consisting of more than half a million individuals, including 65,446 with AF. In total, we identified 97 loci significantly associated with AF, including 67 that were novel in a combined-ancestry analysis, and 3 that were novel in a European-specific analysis. We sought to identify AF-associated genes at the GWAS loci by performing RNA-sequencing and expression quantitative trait locus analyses in 101 left atrial samples, the most relevant tissue for AF. We also performed transcriptome-wide analyses that identified 57 AF-associated genes, 42 of which overlap with GWAS loci. The identified loci implicate genes enriched within cardiac developmental, electrophysiological, contractile and structural pathways. These results extend our understanding of the biological pathways underlying AF and may facilitate the development of therapeutics for AF.
Keywords: Atrial Fibrillation; Case-Control Studies; Ethnicity; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Quantitative Trait Loci; Transcriptome

Novel genetic associations for blood pressure identified via gene-alcohol interaction in up to 570K individuals across multiple ancestries. - Feitosa, Mary F; Kraja, Aldi T; Chasman, Daniel I; Sung, Yun J; Winkler, Thomas W; Ntalla, Ioanna; Guo, Xiuqing; Franceschini, Nora; Cheng, Ching-Yu; Sim, Xueling; Vojinovic, Dina; Marten, Jonathan; et al. (PLoS One, 2018)
Heavy alcohol consumption is an established risk factor for hypertension; the mechanism by which alcohol consumption impact blood pressure (BP) regulation remains unknown. We hypothesized that a genome-wide association study accounting for gene-alcohol consumption interaction for BP might identify additional BP loci and contribute to the understanding of alcohol-related BP regulation. We conducted a large two-stage investigation incorporating joint testing of main genetic effects and single nucleotide variant (SNV)-alcohol consumption interactions. In Stage 1, genome-wide discovery meta-analyses in ≈131K individuals across several ancestry groups yielded 3,514 SNVs (245 loci) with suggestive evidence of association (P < 1.0 x 10-5). In Stage 2, these SNVs were tested for independent external replication in ≈440K individuals across multiple ancestries. We identified and replicated (at Bonferroni correction threshold) five novel BP loci (380 SNVs in 21 genes) and 49 previously reported BP loci (2,159 SNVs in 109 genes) in European ancestry, and in multi-ancestry meta-analyses (P < 5.0 x 10-8). For African ancestry samples, we detected 18 potentially novel BP loci (P < 5.0 x 10-8) in Stage 1 that warrant further replication. Additionally, correlated meta-analysis identified eight novel BP loci (11 genes). Several genes in these loci (e.g., PINX1, GATA4, BLK, FTO and GABBR2) have been previously reported to be associated with alcohol consumption. These findings provide insights into the role of alcohol consumption in the genetic architecture of hypertension.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Alcohol Drinking; Blood Pressure; Cohort Studies; Female; Gene-Environment Interaction; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Hypertension; Male; Middle Aged; Pedigree; Polymorphism, Single Nucleotide; Racial Groups; Young Adult

Prospective Study of Epigenetic Age Acceleration and Incidence of Cardiovascular Disease Outcomes in the ARIC Study (Atherosclerosis Risk in Communities). - Roetker, Nicholas S; Pankow, James S; Bressler, Jan; Morrison, Alanna C; Eric Boerwinkle (Circ Genom Precis Med, 2018)
BACKGROUND: DNA methylation-based patterns of biological aging, known as epigenetic age acceleration, are predictive of all-cause mortality, but little is known about their association with cardiovascular disease (CVD). METHODS: We estimated 2 versions of epigenetic age acceleration (Horvath and Hannum) using whole-blood samples from 2543 blacks. Linear and Cox proportional hazards regression, respectively, were used to assess the association of age acceleration with carotid intima-media thickness (cross-sectionally) and incident cardiovascular events, including CVD mortality, myocardial infarction, fatal coronary heart disease, peripheral arterial disease, and heart failure, during a median 21-year follow-up. All models were adjusted for chronological age and traditional CVD risk factors. RESULTS: In comparison to chronological age, the 2 measures of epigenetic age acceleration were weaker, but independent, potential risk markers for subclinical atherosclerosis and most incident cardiovascular outcomes, including fatal coronary heart disease, peripheral arterial disease, and heart failure. For example, each 5-year increment of epigenetic age acceleration was associated with an average of 0.01 mm greater carotid intima-media thickness (each ≤0.01), and the hazard ratios (95% confidence intervals) of fatal coronary heart disease per 5-year increment in Horvath and Hannum age acceleration were 1.17 (1.02-1.33) and 1.22 (1.04-1.44), respectively. CONCLUSIONS: In this sample of blacks, increased epigenetic age acceleration in whole blood was a potential risk marker for incident fatal coronary heart disease, peripheral arterial disease, and heart failure independently of chronological age and traditional CVD risk factors. DNA methylation-based measures of biological aging may help to identify new pathophysiological mechanisms contributing to the development of CVD.
Keywords: Age Factors; Black or African American; Cardiovascular Diseases; Carotid Intima-Media Thickness; DNA Methylation; Female; Humans; Male; Middle Aged; Prevalence; Proportional Hazards Models; Prospective Studies; Risk Factors

Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
Genome-wide association studies (GWAS) have identified >250 loci for body mass index (BMI), implicating pathways related to neuronal biology. Most GWAS loci represent clusters of common, noncoding variants from which pinpointing causal genes remains challenging. Here we combined data from 718,734 individuals to discover rare and low-frequency (minor allele frequency (MAF) < 5%) coding variants associated with BMI. We identified 14 coding variants in 13 genes, of which 8 variants were in genes (ZBTB7B, ACHE, RAPGEF3, RAB21, ZFHX3, ENTPD6, ZFR2 and ZNF169) newly implicated in human obesity, 2 variants were in genes (MC4R and KSR2) previously observed to be mutated in extreme obesity and 2 variants were in GIPR. The effect sizes of rare variants are ~10 times larger than those of common variants, with the largest effect observed in carriers of an MC4R mutation introducing a stop codon (p.Tyr35Ter, MAF = 0.01%), who weighed ~7 kg more than non-carriers. Pathway analyses based on the variants associated with BMI confirm enrichment of neuronal genes and provide new evidence for adipocyte and energy expenditure biology, widening the potential of genetically supported therapeutic targets in obesity.
Keywords: Adult; Animals; Body Mass Index; Drosophila; Energy Intake; Energy Metabolism; Female; Gene Frequency; Genetic Variation; Humans; Male; Obesity; Proteins; Syndrome

Publisher Correction: Genetic analysis of over 1 million people identifies 535 new loci associated with blood pressure traits. - Evangelou, Evangelos; Warren, Helen R; Mosen-Ansorena, David; Mifsud, Borbala; Pazoki, Raha; Gao, He; Ntritsos, Georgios; Dimou, Niki; Cabrera, Claudia P; Karaman, Ibrahim; Ng, Fu Liang; Evangelou, Marina; et al. (Nat Genet, 2018)
In the version of this article originally published, the name of author Martin H. de Borst was coded incorrectly in the XML. The error has now been corrected in the HTML version of the paper.

Publisher Correction: Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
In the version of this article originally published, one of the two authors with the name Wei Zhao was omitted from the author list and the affiliations for both authors were assigned to the single Wei Zhao in the author list. In addition, the ORCID for Wei Zhao (Department of Biostatistics and Epidemiology, Perelman School of Medicine, University of Pennsylvania, Philadelphia, PA, USA) was incorrectly assigned to author Wei Zhou. The errors have been corrected in the HTML and PDF versions of the article.

Publisher Correction: Protein-altering variants associated with body mass index implicate pathways that control energy intake and expenditure in obesity. - Turcot, Valérie; Lu, Yingchang; Highland, Heather M; Schurmann, Claudia; Justice, Anne E; Fine, Rebecca S; Bradfield, Jonathan P; Esko, Tõnu; Giri, Ayush; Graff, Mariaelisa; Guo, Xiuqing; Hendricks, Audrey E; et al. (Nat Genet, 2018)
In the published version of this paper, the name of author Emanuele Di Angelantonio was misspelled. This error has now been corrected in the HTML and PDF versions of the article.

Refining the accuracy of validated target identification through coding variant fine-mapping in type 2 diabetes. - Mahajan, Anubha; Wessel, Jennifer; Willems, Sara M; Zhao, Wei; Robertson, Neil R; Chu, Audrey Y; Gan, Wei; Kitajima, Hidetoshi; Taliun, Daniel; Rayner, N William; Guo, Xiuqing; Lu, Yingchang; et al. (Nat Genet, 2018)
We aggregated coding variant data for 81,412 type 2 diabetes cases and 370,832 controls of diverse ancestry, identifying 40 coding variant association signals (P < 2.2 × 10); of these, 16 map outside known risk-associated loci. We make two important observations. First, only five of these signals are driven by low-frequency variants: even for these, effect sizes are modest (odds ratio ≤1.29). Second, when we used large-scale genome-wide association data to fine-map the associated variants in their regional context, accounting for the global enrichment of complex trait associations in coding sequence, compelling evidence for coding variant causality was obtained for only 16 signals. At 13 others, the associated coding variants clearly represent 'false leads' with potential to generate erroneous mechanistic inference. Coding variant associations offer a direct route to biological insight for complex diseases and identification of validated therapeutic targets; however, appropriate mechanistic inference requires careful specification of their causal contribution to disease predisposition.
Keywords: Alleles; Chromosome Mapping; Diabetes Mellitus, Type 2; Exome Sequencing; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Male; White People

The role of FREM2 and FRAS1 in the development of congenital diaphragmatic hernia. - Jordan, Valerie K; Beck, Tyler F; Hernandez-Garcia, Andres; Kundert, Peter N; Kim, Bum-Jun; Jhangiani, Shalini N; Gambin, Tomasz; Starkovich, Molly; Punetha, Jaya; Paine, Ingrid S; Posey, Jennifer E; Li, Alexander H; et al. (Hum Mol Genet, 2018)
Congenital diaphragmatic hernia (CDH) has been reported twice in individuals with a clinical diagnosis of Fraser syndrome, a genetic disorder that can be caused by recessive mutations affecting FREM2 and FRAS1. In the extracellular matrix, FREM2 and FRAS1 form a self-stabilizing complex with FREM1, a protein whose deficiency causes sac CDH in humans and mice. By sequencing FREM2 and FRAS1 in a CDH cohort, and searching online databases, we identified five individuals who carried recessive or double heterozygous, putatively deleterious variants in these genes which may represent susceptibility alleles. Three of these alleles were significantly enriched in our CDH cohort compared with ethnically matched controls. We subsequently demonstrated that 8% of Frem2ne/ne and 1% of Fras1Q1263*/Q1263* mice develop the same type of anterior sac CDH seen in FREM1-deficient mice. We went on to show that development of sac hernias in FREM1-deficient mice is preceded by failure of anterior mesothelial fold progression resulting in the persistence of an amuscular, poorly vascularized anterior diaphragm that is abnormally adherent to the underlying liver. Herniation occurs in the perinatal period when the expanding liver protrudes through this amuscular region of the anterior diaphragm that is juxtaposed to areas of muscular diaphragm. Based on these data, we conclude that deficiency of FREM2, and possibly FRAS1, are associated with an increased risk of developing CDH and that loss of the FREM1/FREM2/FRAS1 complex, or its function, leads to anterior sac CDH development through its effects on mesothelial fold progression.
Keywords: Animals; Child; Child, Preschool; Epithelium; Extracellular Matrix Proteins; Female; Hernias, Diaphragmatic, Congenital; Humans; Infant; Infant, Newborn; Male; Mice; Mice, Knockout; Mutation; Pregnancy; Receptors, Interleukin

Sequence-Based Analysis of Lipid-Related Metabolites in a Multiethnic Study. - Feofanova, Elena V; Yu, Bing; Ginger A Metcalf; Liu, Xiaoming; Donna M Muzny; Below, Jennifer E; Wagenknecht, Lynne E; Richard A Gibbs; Morrison, Alanna C; Eric Boerwinkle (Genetics, 2018)
Small molecule lipid-related metabolites are important components of fatty acid and steroid metabolism-two important contributors to human health. This study investigated the extent to which rare and common genetic variants spanning the human genome influence the lipid-related metabolome. Sequence data from 1552 European-Americans (EA) and 1872 African-Americans (AA) were analyzed to examine the impact of common and rare variants on the levels of 102 circulating lipid-related metabolites measured by a combination of chromatography and mass spectroscopy. We conducted single variant tests [minor allele frequency (MAF) > 5%, statistical significance -value ≤ 2.45 × 10] and tests aggregating rare variants (MAF ≤ 5%) across multiple genomic motifs, such as coding regions and regulatory domains, and sliding windows. Multiethnic meta-analyses detected 53 lipid-related metabolites-locus pairs, which were inspected for evidence of consistent signal between the two ethnic groups. Thirty-eight lipid-related metabolite-genomic region associations were consistent across ethnicities, among which seven were novel. The regions contain genes that are related to metabolite transport () and metabolism (, , , and ). Six of the seven novel findings lie in expression quantitative trait loci affecting the expression levels of 14 surrounding genes in multiple tissues. Imputed expression levels of 10 of the affected genes were associated with four corresponding lipid-related traits in at least one tissue. Our findings offer valuable insight into circulating lipid-related metabolite regulation in a multiethnic population.
Keywords: Black or African American; Female; Humans; Lipid Metabolism; Male; Metabolome; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; White People

Study of 300,486 individuals identifies 148 independent genetic loci influencing general cognitive function. - Davies, Gail; Lam, Max; Harris, Sarah E; Trampush, Joey W; Luciano, Michelle; Hill, W David; Hagenaars, Saskia P; Ritchie, Stuart J; Marioni, Riccardo E; Fawns-Ritchie, Chloe; Liewald, David C M; Okely, Judith A; et al. (Nat Commun, 2018)
General cognitive function is a prominent and relatively stable human trait that is associated with many important life outcomes. We combine cognitive and genetic data from the CHARGE and COGENT consortia, and UK Biobank (total N = 300,486; age 16-102) and find 148 genome-wide significant independent loci (P < 5 × 10) associated with general cognitive function. Within the novel genetic loci are variants associated with neurodegenerative and neurodevelopmental disorders, physical and psychiatric illnesses, and brain structure. Gene-based analyses find 709 genes associated with general cognitive function. Expression levels across the cortex are associated with general cognitive function. Using polygenic scores, up to 4.3% of variance in general cognitive function is predicted in independent samples. We detect significant genetic overlap between general cognitive function, reaction time, and many health variables including eyesight, hypertension, and longevity. In conclusion we identify novel genetic loci and pathways contributing to the heritability of general cognitive function.
Keywords: Adolescent; Adult; Aged; Aged, 80 and over; Cognition; Genetic Loci; Genetic Predisposition to Disease; Humans; Mental Disorders; Middle Aged; Multifactorial Inheritance; Neurodegenerative Diseases; Neurodevelopmental Disorders; Polymorphism, Single Nucleotide; Reaction Time; Young Adult

Targeted sequencing identifies a missense variant in the BEST3 gene associated with antihypertensive response to hydrochlorothiazide. - Singh, Sonal; Wang, Zhiying; Shahin, Mohamed H; Langaee, Taimour Y; Gong, Yan; Turner, Stephen T; Chapman, Arlene B; Gums, John G; McDonough, Caitrin W; Bailey, Kent R; Beitelshees, Amber L; Cooper-Dehoff, Rhonda M; et al. (Pharmacogenet Genomics, 2018)
Chromosome 12q15 was identified in Genetic Epidemiology of Response Assessment (GERA) and replicated in Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) for its association with blood pressure (BP) response to hydrochlorothiazide (HCTZ). However, the functional variant is unknown and we aimed to identify the likely functional variants through targeted sequencing. The chromosome 12q15 region was sequenced in 397 best and worst responders to HCTZ in PEAR (N=199) and GERA (N=198) hypertensive study participants. Logistic regression was used for the association analysis adjusting for age, sex, race, and principal components 1 and 2. For validation, the significant single nucleotide polymorphism was tested for association with the change in systolic (ΔSBP) and diastolic BP (ΔDBP) post-treatment in the entire PEAR (N=370) and GERA (N=570) cohorts. A novel missense polymorphism (G>A, Pro383Leu) in BEST3, rs61747221, was significantly associated with better HCTZ response (P=0.0021, odds ratio=2.05). It was validated in the entire cohort of PEAR (ΔSBP: P=0.021, β=-1.60, ΔDBP: P=0.023, β=-1.08) and GERA (ΔSBP: P=0.028, β=-1.95, ΔDBP: P=0.032, β=-1.28). BEST3 encodes the calcium sensitive chloride channel in the vascular smooth muscle implicated in the regulation of BP, especially in response to vasoconstrictors like angiotensin II. These results suggest that BEST3 is involved in the chronic BP lowering mechanism of thiazides and highlight its importance as a genetic predictor of the BP response to thiazide diuretics.
Keywords: Adult; Angiotensin II; Antihypertensive Agents; Atenolol; Bestrophins; Blood Pressure; Female; Genetic Association Studies; Humans; Hypertension; Male; Middle Aged; Muscle Proteins; Polymorphism, Single Nucleotide; Sodium Chloride Symporter Inhibitors

Whole-Exome Sequencing Identifies Novel Variants for Tooth Agenesis. - Dinckan, N; Du, R; Petty, L E; Coban-Akdemir, Z; Jhangiani, S N; Paine, I; Baugh, E H; Erdem, A P; Kayserili, H; Harshavardhan Doddapaneni; Jianhong Hu; Donna M Muzny; et al. (J Dent Res, 2018)
Tooth agenesis is a common craniofacial abnormality in humans and represents failure to develop 1 or more permanent teeth. Tooth agenesis is complex, and variations in about a dozen genes have been reported as contributing to the etiology. Here, we combined whole-exome sequencing, array-based genotyping, and linkage analysis to identify putative pathogenic variants in candidate disease genes for tooth agenesis in 10 multiplex Turkish families. Novel homozygous and heterozygous variants in LRP6, DKK1, LAMA3, and COL17A1 genes, as well as known variants in WNT10A, were identified as likely pathogenic in isolated tooth agenesis. Novel variants in KREMEN1 were identified as likely pathogenic in 2 families with suspected syndromic tooth agenesis. Variants in more than 1 gene were identified segregating with tooth agenesis in 2 families, suggesting oligogenic inheritance. Structural modeling of missense variants suggests deleterious effects to the encoded proteins. Functional analysis of an indel variant (c.3607+3_6del) in LRP6 suggested that the predicted resulting mRNA is subject to nonsense-mediated decay. Our results support a major role for WNT pathways genes in the etiology of tooth agenesis while revealing new candidate genes. Moreover, oligogenic cosegregation was suggestive for complex inheritance and potentially complex gene product interactions during development, contributing to improved understanding of the genetic etiology of familial tooth agenesis.
Keywords: Anodontia; Exome Sequencing; Female; Genetic Linkage; Genetic Variation; Humans; Intercellular Signaling Peptides and Proteins; Laminin; Low Density Lipoprotein Receptor-Related Protein-6; Male; Membrane Proteins; Mutation, Missense; Pedigree; Real-Time Polymerase Chain Reaction; Turkey; Wnt Proteins

The Alzheimer's Disease Sequencing Project: Study design and sample selection. - Beecham, Gary W; Bis, J C; Martin, E R; Choi, S-H; DeStefano, A L; van Duijn, C M; Fornage, M; Gabriel, S B; Koboldt, D C; Larson, D E; Naj, A C; Psaty, B M; et al. (Neurol Genet, 2017)

Analysis commons, a team approach to discovery in a big-data environment for genetic epidemiology. - Brody, Jennifer A; Morrison, Alanna C; Bis, Joshua C; O'Connell, Jeffrey R; Brown, Michael R; Huffman, Jennifer E; Ames, Darren C; Carroll, Andrew; Conomos, Matthew P; Gabriel, Stacey; Richard A Gibbs; Gogarten, Stephanie M; et al. (Nat Genet, 2017)
The exploding volume of whole-genome sequence (WGS) and multi-omics data requires new approaches for analysis. As one solution, we have created a cloud-based Analysis Commons, which brings together genotype and phenotype data from multiple studies in a setting that is accessible by multiple investigators. This framework addresses many of the challenges of multi-center WGS analyses, including data sharing mechanisms, phenotype harmonization, integrated multi-omics analyses, annotation, and computational flexibility. In this setting, the computational pipeline facilitates a sequence-to-discovery analysis workflow illustrated here by an analysis of plasma fibrinogen levels in 3996 individuals from the National Heart, Lung, and Blood Institute (NHLBI) Trans-Omics for Precision Medicine (TOPMed) WGS program. The Analysis Commons represents a novel model for transforming WGS resources from a massive quantity of phenotypic and genomic data into knowledge of the determinants of health and disease risk in diverse human populations.
Keywords: big data; Fibrinogen; Genetics, Population; Genome; Humans; Information Dissemination; Mobile Applications; Molecular Epidemiology; Regression Analysis; Software; Workflow

ANGPTL3 Deficiency and Protection Against Coronary Artery Disease. - Stitziel, Nathan O; Khera, Amit V; Wang, Xiao; Bierhals, Andrew J; Vourakis, A Christina; Sperry, Alexandra E; Natarajan, Pradeep; Klarin, Derek; Emdin, Connor A; Zekavat, Seyedeh M; Nomura, Akihiro; Erdmann, Jeanette; et al. (J Am Coll Cardiol, 2017)
BACKGROUND: Familial combined hypolipidemia, a Mendelian condition characterized by substantial reductions in all 3 major lipid fractions, is caused by mutations that inactivate the gene angiopoietin-like 3 (ANGPTL3). Whether ANGPTL3 deficiency reduces risk of coronary artery disease (CAD) is unknown. OBJECTIVES: The study goal was to leverage 3 distinct lines of evidence-a family that included individuals with complete (compound heterozygote) ANGPTL3 deficiency, a population based-study of humans with partial (heterozygote) ANGPTL3 deficiency, and biomarker levels in patients with myocardial infarction (MI)-to test whether ANGPTL3 deficiency is associated with lower risk for CAD. METHODS: We assessed coronary atherosclerotic burden in 3 individuals with complete ANGPTL3 deficiency and 3 wild-type first-degree relatives using computed tomography angiography. In the population, ANGPTL3 loss-of-function (LOF) mutations were ascertained in up to 21,980 people with CAD and 158,200 control subjects. LOF mutations were defined as nonsense, frameshift, and splice-site variants, along with missense variants resulting in <25% of wild-type ANGPTL3 activity in a mouse model. In a biomarker study, circulating ANGPTL3 concentration was measured in 1,493 people who presented with MI and 3,232 control subjects. RESULTS: The 3 individuals with complete ANGPTL3 deficiency showed no evidence of coronary atherosclerotic plaque. ANGPTL3 gene sequencing demonstrated that approximately 1 in 309 people was a heterozygous carrier for an LOF mutation. Compared with those without mutation, heterozygous carriers of ANGPTL3 LOF mutations demonstrated a 17% reduction in circulating triglycerides and a 12% reduction in low-density lipoprotein cholesterol. Carrier status was associated with a 34% reduction in odds of CAD (odds ratio: 0.66; 95% confidence interval: 0.44 to 0.98; p = 0.04). Individuals in the lowest tertile of circulating ANGPTL3 concentrations, compared with the highest, had reduced odds of MI (adjusted odds ratio: 0.65; 95% confidence interval: 0.55 to 0.77; p < 0.001). CONCLUSIONS: ANGPTL3 deficiency is associated with protection from CAD.
Keywords: Adult; Angiopoietin-Like Protein 3; Angiopoietin-like Proteins; Angiopoietins; Animals; Atherosclerosis; Case-Control Studies; Coronary Artery Disease; Female; Humans; Lipids; Male; Mice, Inbred C57BL; Mice, Knockout; Middle Aged; Mutation, Missense; Myocardial Infarction; Risk Factors

Association between mitochondrial DNA copy number and sudden cardiac death: findings from the Atherosclerosis Risk in Communities study (ARIC). - Zhang, Yiyi; Guallar, Eliseo; Ashar, Foram N; Longchamps, Ryan J; Castellani, Christina A; Lane, John; Grove, Megan L; Coresh, Josef; Sotoodehnia, Nona; Ilkhanoff, Leonard; Eric Boerwinkle; Pankratz, Nathan; et al. (Eur Heart J, 2017)
AIMS: Sudden cardiac death (SCD) is a major public health burden. Mitochondrial dysfunction has been implicated in a wide range of cardiovascular diseases including cardiomyopathy, heart failure, and arrhythmias, but it is unknown if it also contributes to SCD risk. We sought to examine the prospective association between mtDNA copy number (mtDNA-CN), a surrogate marker of mitochondrial function, and SCD risk. METHODS AND RESULTS: We measured baseline mtDNA-CN in 11 093 participants from the Atherosclerosis Risk in Communities (ARIC) study. mtDNA copy number was calculated from probe intensities of mitochondrial single nucleotide polymorphisms (SNP) on the Affymetrix Genome-Wide Human SNP Array 6.0. Sudden cardiac death was defined as a sudden pulseless condition presumed due to a ventricular tachyarrhythmia in a previously stable individual without evidence of a non-cardiac cause of cardiac arrest. Sudden cardiac death cases were reviewed and adjudicated by an expert committee. During a median follow-up of 20.4 years, we observed 361 SCD cases. After adjusting for age, race, sex, and centre, the hazard ratio for SCD comparing the 1st to the 5th quintiles of mtDNA-CN was 2.24 (95% confidence interval 1.58-3.19; P-trend <0.001). When further adjusting for traditional cardiovascular disease risk factors, prevalent coronary heart disease, heart rate, QT interval, and QRS duration, the association remained statistically significant. Spline regression models showed that the association was approximately linear over the range of mtDNA-CN values. No apparent interaction by race or by sex was detected. CONCLUSION: In this community-based prospective study, mtDNA-CN in peripheral blood was inversely associated with the risk of SCD.
Keywords: Coronary Artery Disease; Death, Sudden, Cardiac; DNA Copy Number Variations; DNA, Mitochondrial; Female; Humans; Male; Middle Aged; Prospective Studies; Risk Factors

Association of Body Mass Index with DNA Methylation and Gene Expression in Blood Cells and Relations to Cardiometabolic Disease: A Mendelian Randomization Approach. - Mendelson, Michael M; Marioni, Riccardo E; Joehanes, Roby; Liu, Chunyu; Hedman, Åsa K; Aslibekyan, Stella; Demerath, Ellen W; Guan, Weihua; Zhi, Degui; Yao, Chen; Huan, Tianxiao; Willinger, Christine; et al. (PLoS Med, 2017)
BACKGROUND: The link between DNA methylation, obesity, and adiposity-related diseases in the general population remains uncertain. METHODS AND FINDINGS: We conducted an association study of body mass index (BMI) and differential methylation for over 400,000 CpGs assayed by microarray in whole-blood-derived DNA from 3,743 participants in the Framingham Heart Study and the Lothian Birth Cohorts, with independent replication in three external cohorts of 4,055 participants. We examined variations in whole blood gene expression and conducted Mendelian randomization analyses to investigate the functional and clinical relevance of the findings. We identified novel and previously reported BMI-related differential methylation at 83 CpGs that replicated across cohorts; BMI-related differential methylation was associated with concurrent changes in the expression of genes in lipid metabolism pathways. Genetic instrumental variable analysis of alterations in methylation at one of the 83 replicated CpGs, cg11024682 (intronic to sterol regulatory element binding transcription factor 1 [SREBF1]), demonstrated links to BMI, adiposity-related traits, and coronary artery disease. Independent genetic instruments for expression of SREBF1 supported the findings linking methylation to adiposity and cardiometabolic disease. Methylation at a substantial proportion (16 of 83) of the identified loci was found to be secondary to differences in BMI. However, the cross-sectional nature of the data limits definitive causal determination. CONCLUSIONS: We present robust associations of BMI with differential DNA methylation at numerous loci in blood cells. BMI-related DNA methylation and gene expression provide mechanistic insights into the relationship between DNA methylation, obesity, and adiposity-related diseases.
Keywords: Aged; Body Mass Index; Coronary Artery Disease; DNA Methylation; Epigenesis, Genetic; Female; Gene Expression Regulation; Genome-Wide Association Study; Humans; Leukocytes; Lipid Metabolism; Male; Mendelian Randomization Analysis; Obesity; Oligonucleotide Array Sequence Analysis

The association of lipoprotein(a) with incident heart failure hospitalization: Atherosclerosis Risk in Communities study. - Agarwala, Anandita; Pokharel, Yashashwi; Saeed, Anum; Sun, Wensheng; Virani, Salim S; Nambi, Vijay; Ndumele, Chiadi; Shahar, Eyal; Heiss, Gerardo; Eric Boerwinkle; Konety, Suma; Hoogeveen, Ron C; et al. (Atherosclerosis, 2017)
BACKGROUND AND AIMS: Lipoprotein(a) [Lp(a)] is a proatherogenic lipoprotein associated with coronary heart disease, ischemic stroke, and more recently aortic stenosis and heart failure (HF). We examined the association of Lp(a) levels with incident HF hospitalization in the Atherosclerosis Risk in Communities (ARIC) study. We also assessed the relationship between Lp(a) levels and arterial stiffness as a potential mechanism for development of HF. METHODS: Lp(a) was measured in 14,154 ARIC participants without prevalent HF at ARIC visit 1 (1987-1989). The association of Lp(a) quintiles with incident HF hospitalization was assessed using Cox proportional-hazards models. Arterial stiffness parameters were stratified based on Lp(a) quintiles, and p-trend was calculated across ordered groups. RESULTS: At a median follow-up of 23.4 years, there were 2605 incident HF hospitalizations. Lp(a) levels were directly associated with incident HF hospitalization in models adjusted for age, race, gender, systolic blood pressure, history of hypertension, diabetes, smoking status, body mass index, heart rate, and high-density lipoprotein cholesterol (quintile 5 vs. quintile 1: hazard ratio [HR] 1.24, 95% confidence interval [CI] 1.09-1.41; p-trend across increasing quintiles <0.01), but not after excluding prevalent and incident myocardial infarction cases (HR 1.07, 95% CI 0.91-1.27; p-trend = 0.70). When adjusted for age, gender, and race, Lp(a) quintiles were not significantly associated with arterial stiffness parameters. CONCLUSIONS: Increased Lp(a) levels were associated with increased risk of incident HF hospitalization. After excluding prevalent and incident myocardial infarction, the association was no longer significant. Lp(a) levels were not associated with arterial stiffness parameters.
Keywords: Biomarkers; Chi-Square Distribution; Comorbidity; Female; Heart Failure; Hospitalization; Humans; Incidence; Linear Models; Lipoprotein(a); Male; Middle Aged; Multivariate Analysis; Myocardial Infarction; Prevalence; Prognosis; Proportional Hazards Models; Prospective Studies; Risk Factors; Time Factors; United States; Up-Regulation; Vascular Stiffness

Creating a data resource: what will it take to build a medical information commons? - Deverka, Patricia A; Majumder, Mary A; Villanueva, Angela G; Anderson, Margaret; Bakker, Annette C; Bardill, Jessica; Eric Boerwinkle; Bubela, Tania; Evans, Barbara J; Garrison, Nanibaa' A; Richard A Gibbs; Gentleman, Robert; et al. (Genome Med, 2017)
National and international public-private partnerships, consortia, and government initiatives are underway to collect and share genomic, personal, and healthcare data on a massive scale. Ideally, these efforts will contribute to the creation of a medical information commons (MIC), a comprehensive data resource that is widely available for both research and clinical uses. Stakeholder participation is essential in clarifying goals, deepening understanding of areas of complexity, and addressing long-standing policy concerns such as privacy and security and data ownership. This article describes eight core principles proposed by a diverse group of expert stakeholders to guide the formation of a successful, sustainable MIC. These principles promote formation of an ethically sound, inclusive, participant-centric MIC and provide a framework for advancing the policy response to data-sharing opportunities and challenges.
Keywords: Humans; Information Dissemination; Information Services; Medical Informatics

DNA Methylation Analysis Identifies Loci for Blood Pressure Regulation. - Richard, Melissa A; Huan, Tianxiao; Ligthart, Symen; Gondalia, Rahul; Jhun, Min A; Brody, Jennifer A; Irvin, Marguerite R; Marioni, Riccardo; Shen, Jincheng; Tsai, Pei-Chien; Montasser, May E; Jia, Yucheng; et al. (Am J Hum Genet, 2017)
Genome-wide association studies have identified hundreds of genetic variants associated with blood pressure (BP), but sequence variation accounts for a small fraction of the phenotypic variance. Epigenetic changes may alter the expression of genes involved in BP regulation and explain part of the missing heritability. We therefore conducted a two-stage meta-analysis of the cross-sectional associations of systolic and diastolic BP with blood-derived genome-wide DNA methylation measured on the Infinium HumanMethylation450 BeadChip in 17,010 individuals of European, African American, and Hispanic ancestry. Of 31 discovery-stage cytosine-phosphate-guanine (CpG) dinucleotides, 13 replicated after Bonferroni correction (discovery: N = 9,828, p < 1.0 × 10; replication: N = 7,182, p < 1.6 × 10). The replicated methylation sites are heritable (h > 30%) and independent of known BP genetic variants, explaining an additional 1.4% and 2.0% of the interindividual variation in systolic and diastolic BP, respectively. Bidirectional Mendelian randomization among up to 4,513 individuals of European ancestry from 4 cohorts suggested that methylation at cg08035323 (TAF1B-YWHAQ) influences BP, while BP influences methylation at cg00533891 (ZMIZ1), cg00574958 (CPT1A), and cg02711608 (SLC1A5). Gene expression analyses further identified six genes (TSPAN2, SLC7A11, UNC93B1, CPT1A, PTMS, and LPCAT3) with evidence of triangular associations between methylation, gene expression, and BP. Additional integrative Mendelian randomization analyses of gene expression and DNA methylation suggested that the expression of TSPAN2 is a putative mediator of association between DNA methylation at cg23999170 and BP. These findings suggest that heritable DNA methylation plays a role in regulating BP independently of previously known genetic variants.
Keywords: Aged; Blood Pressure; CpG Islands; Cross-Sectional Studies; DNA Methylation; Epigenesis, Genetic; Genetic Variation; Genome-Wide Association Study; Humans; Mendelian Randomization Analysis; Middle Aged; Nerve Tissue Proteins; Quantitative Trait Loci; Tetraspanins

Exome-wide association study of plasma lipids in >300,000 individuals. - Liu, Dajiang J; Peloso, Gina M; Yu, Haojie; Butterworth, Adam S; Wang, Xiao; Mahajan, Anubha; Saleheen, Danish; Emdin, Connor; Alam, Dewan; Alves, Alexessander Couto; Amouyel, Philippe; Di Angelantonio, Emanuele; et al. (Nat Genet, 2017)
We screened variants on an exome-focused genotyping array in >300,000 participants (replication in >280,000 participants) and identified 444 independent variants in 250 loci significantly associated with total cholesterol (TC), high-density-lipoprotein cholesterol (HDL-C), low-density-lipoprotein cholesterol (LDL-C), and/or triglycerides (TG). At two loci (JAK2 and A1CF), experimental analysis in mice showed lipid changes consistent with the human data. We also found that: (i) beta-thalassemia trait carriers displayed lower TC and were protected from coronary artery disease (CAD); (ii) excluding the CETP locus, there was not a predictable relationship between plasma HDL-C and risk for age-related macular degeneration; (iii) only some mechanisms of lowering LDL-C appeared to increase risk for type 2 diabetes (T2D); and (iv) TG-lowering alleles involved in hepatic production of TG-rich lipoproteins (TM6SF2 and PNPLA3) tracked with higher liver fat, higher risk for T2D, and lower risk for CAD, whereas TG-lowering alleles involved in peripheral lipolysis (LPL and ANGPTL4) had no effect on liver fat but decreased risks for both T2D and CAD.
Keywords: Coronary Artery Disease; Diabetes Mellitus, Type 2; Exome; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipids; Macular Degeneration; Phenotype; Risk Factors

An Expanded Genome-Wide Association Study of Type 2 Diabetes in Europeans. - Scott, Robert A; Scott, Laura J; Mägi, Reedik; Marullo, Letizia; Gaulton, Kyle J; Kaakinen, Marika; Pervjakova, Natalia; Pers, Tune H; Johnson, Andrew D; Eicher, John D; Jackson, Anne U; Ferreira, Teresa; et al. (Diabetes, 2017)
To characterize type 2 diabetes (T2D)-associated variation across the allele frequency spectrum, we conducted a meta-analysis of genome-wide association data from 26,676 T2D case and 132,532 control subjects of European ancestry after imputation using the 1000 Genomes multiethnic reference panel. Promising association signals were followed up in additional data sets (of 14,545 or 7,397 T2D case and 38,994 or 71,604 control subjects). We identified 13 novel T2D-associated loci ( < 5 × 10), including variants near the , , and genes. Our analysis brought the total number of independent T2D associations to 128 distinct signals at 113 loci. Despite substantially increased sample size and more complete coverage of low-frequency variation, all novel associations were driven by common single nucleotide variants. Credible sets of potentially causal variants were generally larger than those based on imputation with earlier reference panels, consistent with resolution of causal signals to common risk haplotypes. Stratification of T2D-associated loci based on T2D-related quantitative trait associations revealed tissue-specific enrichment of regulatory annotations in pancreatic islet enhancers for loci influencing insulin secretion and in adipocytes, monocytes, and hepatocytes for insulin action-associated loci. These findings highlight the predominant role played by common variants of modest effect and the diversity of biological mechanisms influencing T2D pathophysiology.
Keywords: Diabetes Mellitus, Type 2; Gene Expression Regulation; Genetic Variation; Genome-Wide Association Study; Humans; White People

Fifteen new risk loci for coronary artery disease highlight arterial-wall-specific mechanisms. - Howson, Joanna M M; Zhao, Wei; Barnes, Daniel R; Ho, Weang-Kee; Young, Robin; Paul, Dirk S; Waite, Lindsay L; Freitag, Daniel F; Fauman, Eric B; Salfati, Elias L; Sun, Benjamin B; Eicher, John D; et al. (Nat Genet, 2017)
Coronary artery disease (CAD) is a leading cause of morbidity and mortality worldwide. Although 58 genomic regions have been associated with CAD thus far, most of the heritability is unexplained, indicating that additional susceptibility loci await identification. An efficient discovery strategy may be larger-scale evaluation of promising associations suggested by genome-wide association studies (GWAS). Hence, we genotyped 56,309 participants using a targeted gene array derived from earlier GWAS results and performed meta-analysis of results with 194,427 participants previously genotyped, totaling 88,192 CAD cases and 162,544 controls. We identified 25 new SNP-CAD associations (P < 5 × 10, in fixed-effects meta-analysis) from 15 genomic regions, including SNPs in or near genes involved in cellular adhesion, leukocyte migration and atherosclerosis (PECAM1, rs1867624), coagulation and inflammation (PROCR, rs867186 (p.Ser219Gly)) and vascular smooth muscle cell differentiation (LMOD1, rs2820315). Correlation of these regions with cell-type-specific gene expression and plasma protein levels sheds light on potential disease mechanisms.
Keywords: Arteries; Atherosclerosis; Cell Adhesion; Chemotaxis, Leukocyte; Coronary Artery Disease; Energy Metabolism; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Histone Code; Humans; Male; Muscle, Smooth, Vascular; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Risk Factors

Genetic variants associated with risk of Alzheimer's disease contribute to cognitive change in midlife: The Atherosclerosis Risk in Communities Study. - Bressler, Jan; Mosley, Thomas H; Penman, Alan; Gottesman, Rebecca F; Windham, Beverly Gwen; Knopman, David S; Wruck, Lisa M; Eric Boerwinkle (Am J Med Genet B Neuropsychiatr Genet, 2017)
Alzheimer's disease (AD) is the most common form of dementia and is characterized by impairment in memory, behavioral changes, and gradual loss of autonomy. Since there is a long latent period prior to diagnosis, the aim of this study was to determine whether twenty single nucleotide polymorphisms identified in genome-wide association analyses of AD are associated with cognitive change in 8,320 white and 2,039 African-American middle-aged adults enrolled in the prospective Atherosclerosis Risk in Communities (ARIC) study. Cognition was evaluated using the Delayed Word Recall Test (DWRT; verbal memory), Digit Symbol Substitution Test (DSST; processing speed), and Word Fluency Test (WFT; executive function). General linear models were used to assess mean differences in 6-year change in test scores among individuals categorized by genotype after adjusting for age, gender, and years of education. Addition of the minor allele for rs670139 (MS4A4E), rs9331896 (CLU), and rs12155159 (NME8) was nominally associated with change on the DWRT, DSST, and WFT, respectively, in whites. The ZCWPW1 (rs1476679) and CDS33 (rs3865444) variants were nominally associated with change on the DWRT and WFT in African-Americans. For rs670139 and rs9331896 the association was only significant in individuals bearing at least one APOE ϵ4 allele in stratified analyses. An unweighted genetic risk score aggregating the risk alleles for 15 polymorphisms was not associated with change in cognitive function. Although the AD-associated genetic variants appear to have small effects on early cognitive change, replication will be required to establish whether there is a discernible influence on cognitive status in midlife. © 2016 Wiley Periodicals, Inc.
Keywords: Alleles; Alzheimer Disease; Atherosclerosis; Black or African American; Black People; Clusterin; Cognition; Cognition Disorders; Dementia; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Membrane Proteins; Memory; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Thioredoxins; White People

Genome-wide association study of 1,5-anhydroglucitol identifies novel genetic loci linked to glucose metabolism. - Li, Man; Maruthur, Nisa M; Loomis, Stephanie J; Pietzner, Maik; North, Kari E; Mei, Hao; Morrison, Alanna C; Friedrich, Nele; Pankow, James S; Nauck, Matthias; Eric Boerwinkle; Teumer, Alexander; et al. (Sci Rep, 2017)
1,5-anhydroglucitol (1,5-AG) is a biomarker of hyperglycemic excursions associated with diabetic complications. Because of its structural similarity to glucose, genetic studies of 1,5-AG can deliver complementary insights into glucose metabolism. We conducted genome-wide association studies of serum 1,5-AG concentrations in 7,550 European ancestry (EA) and 2,030 African American participants (AA) free of diagnosed diabetes from the ARIC Study. Seven loci in/near EFNA1/SLC50A1, MCM6/LCT, SI, MGAM, MGAM2, SLC5A10, and SLC5A1 showed genome-wide significant associations (P < 5 × 10) among EA participants, five of which were novel. Six of the seven loci were successfully replicated in 8,790 independent EA individuals, and MCM6/LCT and SLC5A10 were also associated among AA. Most of 1,5-AG-associated index SNPs were not associated with the clinical glycemic markers fasting glucose or the  HbA1c, and vice versa. Only the index variant in SLC5A1 showed a significant association with fasting glucose in the expected opposing direction. Products of genes in all 1,5-AG-associated loci have known roles in carbohydrate digestion and enteral or renal glucose transport, suggesting that genetic variants associated with 1,5-AG influence its concentration via effects on glucose metabolism and handling.
Keywords: Aged; Black or African American; Deoxyglucose; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose; Glycated Hemoglobin; Humans; Hyperglycemia; Insulin; Male; Middle Aged; Minichromosome Maintenance Complex Component 6; Sodium-Glucose Transporter 1; White People

Homozygous and hemizygous CNV detection from exome sequencing data in a Mendelian disease cohort. - Gambin, Tomasz; Akdemir, Zeynep C; Bo Yuan; Gu, Shen; Chiang, Theodore; Carvalho, Claudia M B; Shaw, Chad; Jhangiani, Shalini; Boone, Philip M; Eldomery, Mohammad K; Karaca, Ender; Bayram, Yavuz; et al. (Nucleic Acids Res, 2017)
We developed an algorithm, HMZDelFinder, that uses whole exome sequencing (WES) data to identify rare and intragenic homozygous and hemizygous (HMZ) deletions that may represent complete loss-of-function of the indicated gene. HMZDelFinder was applied to 4866 samples in the Baylor-Hopkins Center for Mendelian Genomics (BHCMG) cohort and detected 773 HMZ deletion calls (567 homozygous or 206 hemizygous) with an estimated sensitivity of 86.5% (82% for single-exonic and 88% for multi-exonic calls) and precision of 78% (53% single-exonic and 96% for multi-exonic calls). Out of 773 HMZDelFinder-detected deletion calls, 82 were subjected to array comparative genomic hybridization (aCGH) and/or breakpoint PCR and 64 were confirmed. These include 18 single-exon deletions out of which 8 were exclusively detected by HMZDelFinder and not by any of seven other CNV detection tools examined. Further investigation of the 64 validated deletion calls revealed at least 15 pathogenic HMZ deletions. Of those, 7 accounted for 17-50% of pathogenic CNVs in different disease cohorts where 7.1-11% of the molecular diagnosis solved rate was attributed to CNVs. In summary, we present an algorithm to detect rare, intragenic, single-exon deletion CNVs using WES data; this tool can be useful for disease gene discovery efforts and clinical WES analyses.
Keywords: Algorithms; Alternative Splicing; Cohort Studies; Computational Biology; Consanguinity; Datasets as Topic; DNA Copy Number Variations; Exome; Genetic Diseases, Inborn; Hemizygote; High-Throughput Nucleotide Sequencing; Homozygote; Humans; Inheritance Patterns; Models, Genetic; Pedigree; Reproducibility of Results; Sequence Deletion; Workflow

Incident Heart Failure and Cognitive Decline: The Atherosclerosis Risk in Communities Study. - Bressler, Jan; Knopman, David S; Sharrett, A Richey; Gottesman, Rebecca F; Penman, Alan; Chang, Patricia P; Rosamond, Wayne D; Eric Boerwinkle; Mosley, Thomas H (J Card Fail, 2017)
BACKGROUND: Cognitive impairment is found in a significant proportion of patients with heart failure (HF). Although cognitive impairment may be a consequence of HF, early signs of cognitive impairment may also indicate subclinical vascular disease, and thus a risk factor for future cardiovascular events. METHODS AND RESULTS: The Atherosclerosis Risk in Communities Study is a prospective cohort study of the development of atherosclerosis. Cox proportional hazards regression was used to examine the association between mean 6-year change in cognitive function and incident HF in 7962 white and 1933 African-American men and women aged 46 to 70 years and free of clinical stroke. Scores were obtained for the Delayed Word Recall Test, the Digit Symbol Substitution Test (DSST), and the Word Fluency Test. There was a significantly increased risk of developing HF during the mean 12.6-year follow-up period after adjustment for age, gender, race, and education for those in the quartile with the greatest decline in DSST scores (hazard ratio [HR] = 1.17, P = .009), and in the quartile with the lowest baseline DSST scores (HR = 1.43, P < .001). CONCLUSIONS: The results suggest that relatively low performance on a test of information processing speed may serve as an indicator of HF risk in middle age.
Keywords: Adult; Aged; Atherosclerosis; Cognition; Cognitive Dysfunction; Female; Follow-Up Studies; Heart Failure; Humans; Incidence; Male; Middle Aged; Neuropsychological Tests; Prospective Studies; Residence Characteristics; Risk Assessment; Risk Factors; Time Factors; United States

Large-scale analyses of common and rare variants identify 12 new loci associated with atrial fibrillation. - Christophersen, Ingrid E; Rienstra, Michiel; Roselli, Carolina; Yin, Xiaoyan; Geelhoed, Bastiaan; Barnard, John; Lin, Honghuang; Arking, Dan E; Smith, Albert V; Albert, Christine M; Chaffin, Mark; Tucker, Nathan R; et al. (Nat Genet, 2017)
Atrial fibrillation affects more than 33 million people worldwide and increases the risk of stroke, heart failure, and death. Fourteen genetic loci have been associated with atrial fibrillation in European and Asian ancestry groups. To further define the genetic basis of atrial fibrillation, we performed large-scale, trans-ancestry meta-analyses of common and rare variant association studies. The genome-wide association studies (GWAS) included 17,931 individuals with atrial fibrillation and 115,142 referents; the exome-wide association studies (ExWAS) and rare variant association studies (RVAS) involved 22,346 cases and 132,086 referents. We identified 12 new genetic loci that exceeded genome-wide significance, implicating genes involved in cardiac electrical and structural remodeling. Our results nearly double the number of known genetic loci for atrial fibrillation, provide insights into the molecular basis of atrial fibrillation, and may facilitate the identification of new potential targets for drug discovery.
Keywords: Atrial Fibrillation; Black or African American; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Quantitative Trait Loci; White People

Lessons learned from additional research analyses of unsolved clinical exome cases. - Eldomery, Mohammad K; Coban-Akdemir, Zeynep; Harel, Tamar; Rosenfeld, Jill A; Gambin, Tomasz; Stray-Pedersen, Asbjørg; Küry, Sébastien; Mercier, Sandra; Lessel, Davor; Denecke, Jonas; Wiszniewski, Wojciech; Penney, Samantha; et al. (Genome Med, 2017)
BACKGROUND: Given the rarity of most single-gene Mendelian disorders, concerted efforts of data exchange between clinical and scientific communities are critical to optimize molecular diagnosis and novel disease gene discovery. METHODS: We designed and implemented protocols for the study of cases for which a plausible molecular diagnosis was not achieved in a clinical genomics diagnostic laboratory (i.e. unsolved clinical exomes). Such cases were recruited to a research laboratory for further analyses, in order to potentially: (1) accelerate novel disease gene discovery; (2) increase the molecular diagnostic yield of whole exome sequencing (WES); and (3) gain insight into the genetic mechanisms of disease. Pilot project data included 74 families, consisting mostly of parent-offspring trios. Analyses performed on a research basis employed both WES from additional family members and complementary bioinformatics approaches and protocols. RESULTS: Analysis of all possible modes of Mendelian inheritance, focusing on both single nucleotide variants (SNV) and copy number variant (CNV) alleles, yielded a likely contributory variant in 36% (27/74) of cases. If one includes candidate genes with variants identified within a single family, a potential contributory variant was identified in a total of ~51% (38/74) of cases enrolled in this pilot study. The molecular diagnosis was achieved in 30/63 trios (47.6%). Besides this, the analysis workflow yielded evidence for pathogenic variants in disease-associated genes in 4/6 singleton cases (66.6%), 1/1 multiplex family involving three affected siblings, and 3/4 (75%) quartet families. Both the analytical pipeline and the collaborative efforts between the diagnostic and research laboratories provided insights that allowed recent disease gene discoveries (PURA, TANGO2, EMC1, GNB5, ATAD3A, and MIPEP) and increased the number of novel genes, defined in this study as genes identified in more than one family (DHX30 and EBF3). CONCLUSION: An efficient genomics pipeline in which clinical sequencing in a diagnostic laboratory is followed by the detailed reanalysis of unsolved cases in a research environment, supplemented with WES data from additional family members, and subject to adjuvant bioinformatics analyses including relaxed variant filtering parameters in informatics pipelines, can enhance the molecular diagnostic yield and provide mechanistic insights into Mendelian disorders. Implementing these approaches requires collaborative clinical molecular diagnostic and research efforts.
Keywords: Adenosine Triphosphatases; ATPases Associated with Diverse Cellular Activities; Computational Biology; DNA Copy Number Variations; DNA-Binding Proteins; Exome; Female; Genetic Diseases, Inborn; Genomics; GTP-Binding Protein beta Subunits; Humans; Male; Membrane Proteins; Metalloendopeptidases; Mitochondrial Proteins; Pilot Projects; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Transcription Factors

Metabolomics and cognition in African American adults in midlife: the atherosclerosis risk in communities study. - Bressler, J; Yu, B; Mosley, T H; Knopman, D S; Gottesman, R F; Alonso, A; Sharrett, A R; Wruck, L M; Eric Boerwinkle (Transl Psychiatry, 2017)
Clinical studies have shown alterations in metabolic profiles when patients with mild cognitive impairment and Alzheimer's disease dementia were compared to cognitively normal subjects. Associations between 204 serum metabolites measured at baseline (1987-1989) and cognitive change were investigated in 1035 middle-aged community-dwelling African American participants in the biracial Atherosclerosis Risk in Communities (ARIC) Study. Cognition was evaluated using the Delayed Word Recall Test (DWRT; verbal memory), the Digit Symbol Substitution Test (DSST; processing speed) and the Word Fluency Test (WFT; verbal fluency) at visits 2 (1990-1992) and 4 (1996-1998). In addition, Cox regression was used to analyze the metabolites as predictors of incident hospitalized dementia between baseline and 2011. There were 141 cases among 1534 participants over a median 17.1-year follow-up period. After adjustment for established risk factors, one standard deviation increase in N-acetyl-1-methylhistidine was significantly associated with greater 6-year change in DWRT scores (β=-0.66 words; P=3.65 × 10). Two metabolites (one unnamed and a long-chain omega-6 polyunsaturated fatty acid found in vegetable oils (docosapentaenoate (DPA, 22:5 n-6)) were significantly associated with less decline on the DSST (DPA: β=1.25 digit-symbol pairs, P=9.47 × 10). Two unnamed compounds and three sex steroid hormones were associated with an increased risk of dementia (all P<3.9 × 10). The association of 4-androstene-3beta, 17beta-diol disulfate 1 with dementia was replicated in European Americans. These results demonstrate that screening the metabolome in midlife can detect biologically plausible biomarkers that may improve risk stratification for cognitive impairment at older ages.
Keywords: Atherosclerosis; Black or African American; Black People; Cognition; Female; Humans; Longitudinal Studies; Male; Metabolomics; Middle Aged; Neuropsychological Tests; Prospective Studies; Risk Factors; White People

MicroRNAs in the miR-17 and miR-15 families are downregulated in chronic kidney disease with hypertension. - Nandakumar, Priyanka; Tin, Adrienne; Grove, Megan L; Ma, Jianzhong; Eric Boerwinkle; Coresh, Josef; Chakravarti, Aravinda (PLoS One, 2017)
BACKGROUND: In older adults (aged 70-74 years), African-Americans have 4-fold higher risk of developing hypertension-attributed end-stage renal disease (ESRD) than European-Americans. A hypothesized mechanism linking hypertension and progressive chronic kidney disease (CKD) is the innate immune response and inflammation. Persons with CKD are also more susceptible to infection. Gene expression in peripheral blood can provide a view of the innate immune activation profile. We aimed to identify differentially expressed genes, microRNAs, and pathways in peripheral blood between cases with CKD and high blood pressure under hypertension treatment versus controls without CKD and with controlled blood pressure in African Americans. METHODS: Case and control pairs (N = 15x2) were selected from those without diabetes and were matched for age, sex, body mass index, APOL1 risk allele count, and hypertension medication use. High blood pressure under hypertension treatment was defined as hypertension medication use and systolic blood pressure (SBP) ≥ 145 mmHg. CKD was defined as estimated glomerular filtration rate (eGFR) < 60 mL/min/1.73m2. Cases were selected from those with CKD and high blood pressure under hypertension treatment, and controls were selected from those without CKD (eGFR: 75-120 mL/min/1.73m2 and urine albumin-to-creatinine ratio < 30mg/g) and with blood pressure controlled by hypertension medication use (SBP < 135 mmHg and D(diastolic)BP < 90 mm Hg). We perform RNA sequencing of mRNA and microRNA and conducted differential expression and co-expression network analysis. RESULTS: Of 347 miRNAs included in the analysis, 14 were significantly associated with case status (Benjamini-Hochberg adjusted p-value [BH p] < 0.05). Of these, ten were downregulated in cases: three of each belong to the miR-17 and miR-15 families. In co-expression network analysis of miRNA, one module, which included 13 of the 14 significant miRNAs, had significant association with case status. Of the 14,488 genes and 41,739 transcripts included in the analysis, none had significant association with case status. Gene co-expression network analyses did not yield any significant associations for mRNA. CONCLUSION: We have identified 14 differentially expressed miRNAs in the peripheral blood of CKD cases with high blood pressure under hypertension treatment as compared to appropriate controls. Most of the significant miRNAs were downregulated and have critical roles in immune cell functions. Future studies are needed to replicate our findings and determine whether the downregulation of these miRNAs in immune cells may influence CKD progression or complications.
Keywords: Down-Regulation; Female; Gene Expression Profiling; Gene Ontology; Gene Regulatory Networks; Humans; Hypertension; Male; MicroRNAs; Middle Aged; Renal Insufficiency, Chronic; RNA, Messenger; Sequence Analysis, RNA

The performance of deleteriousness prediction scores for rare non-protein-changing single nucleotide variants in human genes. - Liu, Xiaoming; Li, Chang; Eric Boerwinkle (J Med Genet, 2017)
Keywords: Databases, Genetic; Genes; Genetic Predisposition to Disease; Genome, Human; Genome-Wide Association Study; Humans; Polymorphism, Single Nucleotide; Reproducibility of Results; ROC Curve

Practical Approaches for Whole-Genome Sequence Analysis of Heart- and Blood-Related Traits. - Morrison, Alanna C; Huang, Zhuoyi; Yu, Bing; Ginger A Metcalf; Liu, Xiaoming; Ballantyne, Christie; Coresh, Josef; Fuli Yu; Donna M Muzny; Feofanova, Elena; Rustagi, Navin; Richard A Gibbs; et al. (Am J Hum Genet, 2017)
Whole-genome sequencing (WGS) allows for a comprehensive view of the sequence of the human genome. We present and apply integrated methodologic steps for interrogating WGS data to characterize the genetic architecture of 10 heart- and blood-related traits in a sample of 1,860 African Americans. In order to evaluate the contribution of regulatory and non-protein coding regions of the genome, we conducted aggregate tests of rare variation across the entire genomic landscape using a sliding window, complemented by an annotation-based assessment of the genome using predefined regulatory elements and within the first intron of all genes. These tests were performed treating all variants equally as well as with individual variants weighted by a measure of predicted functional consequence. Significant findings were assessed in 1,705 individuals of European ancestry. After these steps, we identified and replicated components of the genomic landscape significantly associated with heart- and blood-related traits. For two traits, lipoprotein(a) levels and neutrophil count, aggregate tests of low-frequency and rare variation were significantly associated across multiple motifs. For a third trait, cardiac troponin T, investigation of regulatory domains identified a locus on chromosome 9. These practical approaches for WGS analysis led to the identification of informative genomic regions and also showed that defined non-coding regions, such as first introns of genes and regulatory domains, are associated with important risk factor phenotypes. This study illustrates the tractable nature of WGS data and outlines an approach for characterizing the genetic architecture of complex traits.
Keywords: Black or African American; C-Reactive Protein; Cholesterol, HDL; Cholesterol, LDL; Chromosomes, Human, Pair 9; Gene Frequency; Genome, Human; Genome-Wide Association Study; Genomics; Hemoglobins; Humans; Introns; Leukocyte Count; Lipoprotein(a); Magnesium; Natriuretic Peptide, Brain; Neutrophils; Peptide Fragments; Phosphorus; Platelet Count; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Troponin T; White People

Primary immunodeficiency diseases: Genomic approaches delineate heterogeneous Mendelian disorders. - Stray-Pedersen, Asbjørg; Sorte, Hanne Sørmo; Samarakoon, Pubudu; Gambin, Tomasz; Chinn, Ivan K; Coban Akdemir, Zeynep H; Erichsen, Hans Christian; Forbes, Lisa R; Gu, Shen; Bo Yuan; Jhangiani, Shalini N; Donna M Muzny; et al. (J Allergy Clin Immunol, 2017)
BACKGROUND: Primary immunodeficiency diseases (PIDDs) are clinically and genetically heterogeneous disorders thus far associated with mutations in more than 300 genes. The clinical phenotypes derived from distinct genotypes can overlap. Genetic etiology can be a prognostic indicator of disease severity and can influence treatment decisions. OBJECTIVE: We sought to investigate the ability of whole-exome screening methods to detect disease-causing variants in patients with PIDDs. METHODS: Patients with PIDDs from 278 families from 22 countries were investigated by using whole-exome sequencing. Computational copy number variant (CNV) prediction pipelines and an exome-tiling chromosomal microarray were also applied to identify intragenic CNVs. Analytic approaches initially focused on 475 known or candidate PIDD genes but were nonexclusive and further tailored based on clinical data, family history, and immunophenotyping. RESULTS: A likely molecular diagnosis was achieved in 110 (40%) unrelated probands. Clinical diagnosis was revised in about half (60/110) and management was directly altered in nearly a quarter (26/110) of families based on molecular findings. Twelve PIDD-causing CNVs were detected, including 7 smaller than 30 Kb that would not have been detected with conventional diagnostic CNV arrays. CONCLUSION: This high-throughput genomic approach enabled detection of disease-related variants in unexpected genes; permitted detection of low-grade constitutional, somatic, and revertant mosaicism; and provided evidence of a mutational burden in mixed PIDD immunophenotypes.
Keywords: Adolescent; Adult; Aged; Child; Child, Preschool; DNA Copy Number Variations; Female; Genomics; High-Throughput Nucleotide Sequencing; Humans; Immunologic Deficiency Syndromes; Infant; Male; Middle Aged; Young Adult

An Promoter Polymorphism Associated With Elevated N-Terminal pro-B-Type Natriuretic Peptide and Lower Blood Pressure, Hypertension, and Mortality. - Seidelmann, Sara B; Vardeny, Orly; Claggett, Brian; Yu, Bing; Shah, Amil M; Ballantyne, Christie M; Selvin, Elizabeth; MacRae, Calum A; Eric Boerwinkle; Solomon, Scott D (J Am Heart Assoc, 2017)
BACKGROUND: Elevated B-type natriuretic peptide (BNP) levels are associated with heart failure and increased mortality in the general population. We investigated rs198389, a functional variant in the promoter region of the BNP gene (), in patients from the Atherosclerosis Risk in Communities Study to investigate associations with N-terminal pro-BNP (NT-proBNP) levels and outcomes. METHODS AND RESULTS: A total of 11 361 black and white patients with rs198389 genotyping attended visit 1 (aged 45-64 years; 1987-1989), with follow-up visits occurring every 3 years (visit 2-visit 4, 1990-1999), followed by visit 5 (2011-2013). NT-proBNP levels were measured at visits 2, 4, and 5. At visit 2, the GG genotype (frequency 18%) was associated with a 41% higher mean plasma level of NT-proBNP compared with the AA genotype (frequency 34%), with intermediate values observed in AGs (=4.2×10). The GG genotype was associated with reduced systolic blood pressure (-1.6 mm Hg, =0.006), diastolic blood pressure (-1 mm Hg, =0.003), antihypertension medication use (odds ratio, 0.85; 95% CI, 0.74-0.97 [=0.02]), and hypertension (odds ratio, 0.81; 95% CI, 0.72-0.92 [=0.002]) compared with the AA genotype with intermediate values in AGs. These relationships persisted throughout subsequent visits. After a median follow-up of 23 years, there were 4031 deaths. With and without covariate adjustment, the GG genotype was associated with modestly lower mortality (hazard ratio, 0.86; 95% CI, 0.78-0.95), primarily reflective of cardiovascular death (hazard ratio, 0.75; 95% CI, 0.61-0.92), and increased residual lifespan of 8 months from 50 years of age (=0.02) versus AAs. CONCLUSIONS: The rs198389 G allele in the promoter is associated with elevated levels of NT-proBNP throughout adult life, reduced blood pressure, hypertension and cardiovascular mortality, and increased lifespan.
Keywords: Black or African American; Blood Pressure; Chi-Square Distribution; Female; Genetic Predisposition to Disease; Humans; Hypertension; Kaplan-Meier Estimate; Linear Models; Longevity; Male; Middle Aged; Natriuretic Peptide, Brain; Odds Ratio; Peptide Fragments; Phenotype; Polymorphism, Single Nucleotide; Predictive Value of Tests; Promoter Regions, Genetic; Prospective Studies; Risk Assessment; Risk Factors; Time Factors; United States; Up-Regulation; White People

Rare and low-frequency coding variants alter human adult height. - Marouli, Eirini; Graff, Mariaelisa; Medina-Gomez, Carolina; Lo, Ken Sin; Wood, Andrew R; Kjaer, Troels R; Fine, Rebecca S; Lu, Yingchang; Schurmann, Claudia; Highland, Heather M; Rüeger, Sina; Thorleifsson, Gudmar; et al. (Nature, 2017)
Height is a highly heritable, classic polygenic trait with approximately 700 common associated variants identified through genome-wide association studies so far. Here, we report 83 height-associated coding variants with lower minor-allele frequencies (in the range of 0.1-4.8%) and effects of up to 2 centimetres per allele (such as those in IHH, STC2, AR and CRISPLD2), greater than ten times the average effect of common variants. In functional follow-up studies, rare height-increasing alleles of STC2 (giving an increase of 1-2 centimetres per allele) compromised proteolytic inhibition of PAPP-A and increased cleavage of IGFBP-4 in vitro, resulting in higher bioavailability of insulin-like growth factors. These 83 height-associated variants overlap genes that are mutated in monogenic growth disorders and highlight new biological candidates (such as ADAMTS3, IL11RA and NOX4) and pathways (such as proteoglycan and glycosaminoglycan synthesis) involved in growth. Our results demonstrate that sufficiently large sample sizes can uncover rare and low-frequency variants of moderate-to-large effect associated with polygenic human phenotypes, and that these variants implicate relevant genes and pathways.
Keywords: ADAMTS Proteins; Adult; Alleles; Body Height; Cell Adhesion Molecules; Female; Gene Frequency; Genetic Variation; Genome, Human; Glycoproteins; Glycosaminoglycans; Hedgehog Proteins; Humans; Intercellular Signaling Peptides and Proteins; Interferon Regulatory Factors; Interleukin-11 Receptor alpha Subunit; Male; Multifactorial Inheritance; NADPH Oxidase 4; NADPH Oxidases; Phenotype; Pregnancy-Associated Plasma Protein-A; Procollagen N-Endopeptidase; Proteoglycans; Proteolysis; Receptors, Androgen; Somatomedins

Rare coding variants in PLCG2, ABI3, and TREM2 implicate microglial-mediated innate immunity in Alzheimer's disease. - Sims, Rebecca; van der Lee, Sven J; Naj, Adam C; Bellenguez, Céline; Badarinarayan, Nandini; Jakobsdottir, Johanna; Kunkle, Brian W; Boland, Anne; Raybould, Rachel; Bis, Joshua C; Martin, Eden R; Grenier-Boley, Benjamin; et al. (Nat Genet, 2017)
We identified rare coding variants associated with Alzheimer's disease in a three-stage case-control study of 85,133 subjects. In stage 1, we genotyped 34,174 samples using a whole-exome microarray. In stage 2, we tested associated variants (P < 1 × 10) in 35,962 independent samples using de novo genotyping and imputed genotypes. In stage 3, we used an additional 14,997 samples to test the most significant stage 2 associations (P < 5 × 10) using imputed genotypes. We observed three new genome-wide significant nonsynonymous variants associated with Alzheimer's disease: a protective variant in PLCG2 (rs72824905: p.Pro522Arg, P = 5.38 × 10, odds ratio (OR) = 0.68, minor allele frequency (MAF) = 0.0059, MAF = 0.0093), a risk variant in ABI3 (rs616338: p.Ser209Phe, P = 4.56 × 10, OR = 1.43, MAF = 0.011, MAF = 0.008), and a new genome-wide significant variant in TREM2 (rs143332484: p.Arg62His, P = 1.55 × 10, OR = 1.67, MAF = 0.0143, MAF = 0.0089), a known susceptibility gene for Alzheimer's disease. These protein-altering changes are in genes highly expressed in microglia and highlight an immune-related protein-protein interaction network enriched for previously identified risk genes in Alzheimer's disease. These genetic findings provide additional evidence that the microglia-mediated innate immune response contributes directly to the development of Alzheimer's disease.
Keywords: Adaptor Proteins, Signal Transducing; Alzheimer Disease; Amino Acid Sequence; Case-Control Studies; Exome; Gene Expression Profiling; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Immunity, Innate; Linkage Disequilibrium; Membrane Glycoproteins; Microglia; Odds Ratio; Phospholipase C gamma; Polymorphism, Single Nucleotide; Protein Interaction Maps; Receptors, Immunologic; Sequence Homology, Amino Acid

Resolution of Disease Phenotypes Resulting from Multilocus Genomic Variation. - Posey, Jennifer E; Harel, Tamar; Liu, Pengfei; Rosenfeld, Jill A; James, Regis A; Coban Akdemir, Zeynep H; Walkiewicz, Magdalena; Bi, Weimin; Xiao, Rui; Ding, Yan; Xia, Fan; Beaudet, Arthur L; et al. (N Engl J Med, 2017)
BACKGROUND: Whole-exome sequencing can provide insight into the relationship between observed clinical phenotypes and underlying genotypes. METHODS: We conducted a retrospective analysis of data from a series of 7374 consecutive unrelated patients who had been referred to a clinical diagnostic laboratory for whole-exome sequencing; our goal was to determine the frequency and clinical characteristics of patients for whom more than one molecular diagnosis was reported. The phenotypic similarity between molecularly diagnosed pairs of diseases was calculated with the use of terms from the Human Phenotype Ontology. RESULTS: A molecular diagnosis was rendered for 2076 of 7374 patients (28.2%); among these patients, 101 (4.9%) had diagnoses that involved two or more disease loci. We also analyzed parental samples, when available, and found that de novo variants accounted for 67.8% (61 of 90) of pathogenic variants in autosomal dominant disease genes and 51.7% (15 of 29) of pathogenic variants in X-linked disease genes; both variants were de novo in 44.7% (17 of 38) of patients with two monoallelic variants. Causal copy-number variants were found in 12 patients (11.9%) with multiple diagnoses. Phenotypic similarity scores were significantly lower among patients in whom the phenotype resulted from two distinct mendelian disorders that affected different organ systems (50 patients) than among patients with disorders that had overlapping phenotypic features (30 patients) (median score, 0.21 vs. 0.36; P=1.77×10). CONCLUSIONS: In our study, we found multiple molecular diagnoses in 4.9% of cases in which whole-exome sequencing was informative. Our results show that structured clinical ontologies can be used to determine the degree of overlap between two mendelian diseases in the same patient; the diseases can be distinct or overlapping. Distinct disease phenotypes affect different organ systems, whereas overlapping disease phenotypes are more likely to be caused by two genes encoding proteins that interact within the same pathway. (Funded by the National Institutes of Health and the Ting Tsung and Wei Fong Chao Foundation.).
Keywords: Exome; Genetic Diseases, Inborn; Genetic Variation; Genotyping Techniques; High-Throughput Nucleotide Sequencing; Humans; Phenotype; Retrospective Studies; Sequence Analysis, DNA

Whole exome sequence-based association analyses of plasma amyloid-β in African and European Americans; the Atherosclerosis Risk in Communities-Neurocognitive Study. - Simino, Jeannette; Wang, Zhiying; Bressler, Jan; Chouraki, Vincent; Yang, Qiong; Younkin, Steven G; Seshadri, Sudha; Fornage, Myriam; Eric Boerwinkle; Mosley, Thomas H (PLoS One, 2017)
OBJECTIVE: We performed single-variant and gene-based association analyses of plasma amyloid-β (aβ) concentrations using whole exome sequence from 1,414 African and European Americans. Our goal was to identify genes that influence plasma aβ42 concentrations and aβ42:aβ40 ratios in late middle age (mean = 59 years), old age (mean = 77 years), or change over time (mean = 18 years). METHODS: Plasma aβ measures were linearly regressed onto age, gender, APOE ε4 carrier status, and time elapsed between visits (fold-changes only) separately by race. Following inverse normal transformation of the residuals, seqMeta was used to conduct race-specific single-variant and gene-based association tests while adjusting for population structure. Linear regression models were fit on autosomal variants with minor allele frequencies (MAF)≥1%. T5 burden and Sequence Kernel Association (SKAT) gene-based tests assessed functional variants with MAF≤5%. Cross-race fixed effects meta-analyses were Bonferroni-corrected for the number of variants or genes tested. RESULTS: Seven genes were associated with aβ in late middle age or change over time; no associations were identified in old age. Single variants in KLKB1 (rs3733402; p = 4.33x10-10) and F12 (rs1801020; p = 3.89x10-8) were significantly associated with midlife aβ42 levels through cross-race meta-analysis; the KLKB1 variant replicated internally using 1,014 additional participants with exome chip. ITPRIP, PLIN2, and TSPAN18 were associated with the midlife aβ42:aβ40 ratio via the T5 test; TSPAN18 was significant via the cross-race meta-analysis, whereas ITPRIP and PLIN2 were European American-specific. NCOA1 and NT5C3B were associated with the midlife aβ42:aβ40 ratio and the fold-change in aβ42, respectively, via SKAT in African Americans. No associations replicated externally (N = 725). CONCLUSION: We discovered age-dependent genetic effects, established associations between vascular-related genes (KLKB1, F12, PLIN2) and midlife plasma aβ levels, and identified a plausible Alzheimer's Disease candidate gene (ITPRIP) influencing cell death. Plasma aβ concentrations may have dynamic biological determinants across the lifespan; plasma aβ study designs or analyses must consider age.
Keywords: Aged; Amyloid beta-Peptides; Black or African American; Exome; Female; Gene Regulatory Networks; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; United States; White People

Whole exome sequencing in 342 congenital cardiac left sided lesion cases reveals extensive genetic heterogeneity and complex inheritance patterns. - Li, Alexander H; Hanchard, Neil A; Furthner, Dieter; Fernbach, Susan; Azamian, Mahshid; Nicosia, Annarita; Rosenfeld, Jill; Donna M Muzny; D'Alessandro, Lisa C A; Morris, Shaine; Jhangiani, Shalini; Parekh, Dhaval R; et al. (Genome Med, 2017)
BACKGROUND: Left-sided lesions (LSLs) account for an important fraction of severe congenital cardiovascular malformations (CVMs). The genetic contributions to LSLs are complex, and the mutations that cause these malformations span several diverse biological signaling pathways: TGFB, NOTCH, SHH, and more. Here, we use whole exome sequence data generated in 342 LSL cases to identify likely damaging variants in putative candidate CVM genes. METHODS: Using a series of bioinformatics filters, we focused on genes harboring population-rare, putative loss-of-function (LOF), and predicted damaging variants in 1760 CVM candidate genes constructed a priori from the literature and model organism databases. Gene variants that were not observed in a comparably sequenced control dataset of 5492 samples without severe CVM were then subjected to targeted validation in cases and parents. Whole exome sequencing data from 4593 individuals referred for clinical sequencing were used to bolster evidence for the role of candidate genes in CVMs and LSLs. RESULTS: Our analyses revealed 28 candidate variants in 27 genes, including 17 genes not previously associated with a human CVM disorder, and revealed diverse patterns of inheritance among LOF carriers, including 9 confirmed de novo variants in both novel and newly described human CVM candidate genes (ACVR1, JARID2, NR2F2, PLRG1, SMURF1) as well as established syndromic CVM genes (KMT2D, NF1, TBX20, ZEB2). We also identified two genes (DNAH5, OFD1) with evidence of recessive and hemizygous inheritance patterns, respectively. Within our clinical cohort, we also observed heterozygous LOF variants in JARID2 and SMAD1 in individuals with cardiac phenotypes, and collectively, carriers of LOF variants in our candidate genes had a four times higher odds of having CVM (odds ratio = 4.0, 95% confidence interval 2.5-6.5). CONCLUSIONS: Our analytical strategy highlights the utility of bioinformatic resources, including human disease records and model organism phenotyping, in novel gene discovery for rare human disease. The results underscore the extensive genetic heterogeneity underlying non-syndromic LSLs, and posit potential novel candidate genes and complex modes of inheritance in this important group of birth defects.
Keywords: Exome Sequencing; Female; Genetic Heterogeneity; Heart Defects, Congenital; Humans; Inheritance Patterns; Male

Whole Transcriptome Sequencing Analyses Reveal Molecular Markers of Blood Pressure Response to Thiazide Diuretics. - Sá, Ana Caroline C; Webb, Amy; Gong, Yan; McDonough, Caitrin W; Datta, Somnath; Langaee, Taimour Y; Turner, Stephen T; Beitelshees, Amber L; Chapman, Arlene B; Eric Boerwinkle; Gums, John G; Scherer, Steven E; et al. (Sci Rep, 2017)
Thiazide diuretics (TD) are commonly prescribed anti-hypertensives worldwide. However, <40% of patients treated with thiazide monotherapy achieve BP control. This study uses whole transcriptome sequencing to identify novel molecular markers associated with BP response to TD. We assessed global RNA expression levels in whole blood samples from 150 participants, representing patients in the upper and lower quartile of BP response to TD from the Pharmacogenomic Evaluation of Antihypertensive Responses (PEAR) (50 whites) and from PEAR-2 (50 whites and 50 blacks). In each study cohort, we performed poly-A RNA-sequencing in baseline samples from 25 responders and 25 non-responders to hydrochlorothiazide (HCTZ) or chlorthalidone. At FDR adjusted p-value < 0.05, 29 genes were differentially expressed in relation to HCTZ or chlorthalidone BP response in whites. For each differentially expressed gene, replication was attempted in the alternate white group and PEAR-2 blacks. CEBPD (meta-analysis p = 1.8 × 10) and TSC22D3 (p = 1.9 × 10) were differentially expressed in all 3 cohorts, and explain, in aggregate, 21.9% of response variability to TD. This is the first report of the use of transcriptome-wide sequencing data to identify molecular markers of antihypertensive drug response. These findings support CEBPD and TSC22D3 as potential biomarkers of BP response to TD.
Keywords: Alleles; Biomarkers; Blood Pressure; CCAAT-Enhancer-Binding Protein-delta; Chlorthalidone; Diuretics; Female; Gene Expression Profiling; Gene Expression Regulation; Humans; Hydrochlorothiazide; Logistic Models; Male; Middle Aged; Potassium; Reproducibility of Results; RNA, Messenger; ROC Curve; Transcription Factors; Uric Acid

Whole-genome sequencing study of serum peptide levels: the Atherosclerosis Risk in Communities study. - de Vries, Paul S; Yu, Bing; Feofanova, Elena V; Ginger A Metcalf; Brown, Michael R; Zeighami, Atefeh L; Liu, Xiaoming; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; Morrison, Alanna C (Hum Mol Genet, 2017)
Oligopeptides are important markers of protein metabolism, as they are cleaved from larger polypeptides and proteins. Genetic association studies may help elucidate their origin and function. In 1,552 European Americans and 1,872 African Americans of the Atherosclerosis Risk in Communities study, we performed whole-genome and whole-exome sequencing and measured serum levels of 25 peptides. Common variants (minor allele frequency > 5%) were analysed individually. We grouped low-frequency variants (minor allele frequency ≤ 5%) by a genome-wide sliding window using region-based aggregate tests. Furthermore, low-frequency regulatory variants were grouped by gene, as were functional coding variants. All analyses were performed separately in each ancestry group and then meta-analysed. We identified 22 common variant associations with peptide levels (P-value < 4.2 × 10-10), including 16 novel gene-peptide pairs. Notably, variants in kinin-kallikrein genes KNG1, F12, KLKB1, and ACE were associated with several different peptides. Variants in KLKB1 and ACE were associated with a fragment of complement component 3f. Both common variants and low-frequency coding variants in CPN1 were associated with a fibrinogen cleavage peptide. Four sliding windows were significantly associated with peptide levels (P-value < 4.2 × 10-10). Our results highlight the importance of the kinin-kallikrein system in the regulation of serum peptide levels, strengthen the evidence for a broad link between the kinin-kallikrein and complement systems, and suggest a role of CPN1 in the conversion of fibrinogen to fibrin.
Keywords: Alleles; Atherosclerosis; Black or African American; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Kallikreins; Male; Middle Aged; Peptides; Polymorphism, Single Nucleotide; Proteins; Risk Factors; White People; Whole Genome Sequencing

Association of MTOR Mutations With Developmental Brain Disorders, Including Megalencephaly, Focal Cortical Dysplasia, and Pigmentary Mosaicism. - Mirzaa, Ghayda M; Campbell, Catarina D; Solovieff, Nadia; Goold, Carleton; Jansen, Laura A; Menon, Suchithra; Timms, Andrew E; Conti, Valerio; Biag, Jonathan D; Adams, Carissa; Boyle, Evan August; Collins, Sarah; et al. (JAMA Neurol, 2016)
IMPORTANCE: Focal cortical dysplasia (FCD), hemimegalencephaly, and megalencephaly constitute a spectrum of malformations of cortical development with shared neuropathologic features. These disorders are associated with significant childhood morbidity and mortality. OBJECTIVE: To identify the underlying molecular cause of FCD, hemimegalencephaly, and diffuse megalencephaly. DESIGN, SETTING, AND PARTICIPANTS: Patients with FCD, hemimegalencephaly, or megalencephaly (mean age, 11.7 years; range, 2-32 years) were recruited from Pediatric Hospital A. Meyer, the University of Hong Kong, and Seattle Children's Research Institute from June 2012 to June 2014. Whole-exome sequencing (WES) was performed on 8 children with FCD or hemimegalencephaly using standard-depth (50-60X) sequencing in peripheral samples (blood, saliva, or skin) from the affected child and their parents and deep (150-180X) sequencing in affected brain tissue. Targeted sequencing and WES were used to screen 93 children with molecularly unexplained diffuse or focal brain overgrowth. Histopathologic and functional assays of phosphatidylinositol 3-kinase-AKT (serine/threonine kinase)-mammalian target of rapamycin (mTOR) pathway activity in resected brain tissue and cultured neurons were performed to validate mutations. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing and targeted sequencing identified variants associated with this spectrum of developmental brain disorders. RESULTS: Low-level mosaic mutations of MTOR were identified in brain tissue in 4 children with FCD type 2a with alternative allele fractions ranging from 0.012 to 0.086. Intermediate-level mosaic mutation of MTOR (p.Thr1977Ile) was also identified in 3 unrelated children with diffuse megalencephaly and pigmentary mosaicism in skin. Finally, a constitutional de novo mutation of MTOR (p.Glu1799Lys) was identified in 3 unrelated children with diffuse megalencephaly and intellectual disability. Molecular and functional analysis in 2 children with FCD2a from whom multiple affected brain tissue samples were available revealed a mutation gradient with an epicenter in the most epileptogenic area. When expressed in cultured neurons, all MTOR mutations identified here drive constitutive activation of mTOR complex 1 and enlarged neuronal size. CONCLUSIONS AND RELEVANCE: In this study, mutations of MTOR were associated with a spectrum of brain overgrowth phenotypes extending from FCD type 2a to diffuse megalencephaly, distinguished by different mutations and levels of mosaicism. These mutations may be sufficient to cause cellular hypertrophy in cultured neurons and may provide a demonstration of the pattern of mosaicism in brain and substantiate the link between mosaic mutations of MTOR and pigmentary mosaicism in skin.
Keywords: Adolescent; Adult; Amino Acids; Animals; Cells, Cultured; Cerebral Cortex; Child; Child, Preschool; Developmental Disabilities; Embryo, Mammalian; Female; Gene Expression Regulation; Genetic Association Studies; Humans; Intercellular Signaling Peptides and Proteins; Male; Malformations of Cortical Development; Mechanistic Target of Rapamycin Complex 1; Megalencephaly; Mosaicism; Multiprotein Complexes; Mutation; Nerve Tissue Proteins; Neurons; Rats; Retrospective Studies; TOR Serine-Threonine Kinases; Young Adult

Association of the IGF1 gene with fasting insulin levels. - Willems, Sara M; Cornes, Belinda K; Brody, Jennifer A; Morrison, Alanna C; Lipovich, Leonard; Dauriz, Marco; Chen, Yuning; Liu, Ching-Ti; Rybin, Denis V; Richard A Gibbs; Donna M Muzny; Pankow, James S; et al. (Eur J Hum Genet, 2016)
Insulin-like growth factor 1 (IGF-I) has been associated with insulin resistance. Genome-wide association studies (GWASs) of fasting insulin (FI) identified single-nucleotide variants (SNVs) near the IGF1 gene, raising two hypotheses: (1) these associations are mediated by IGF-I levels and (2) these noncoding variants either tag other functional variants in the region or are directly functional. In our study, analyses including 5141 individuals from population-based cohorts suggest that FI associations near IGF1 are not mediated by IGF-I. Analyses of targeted sequencing data in 3539 individuals reveal a large number of novel rare variants at the IGF1 locus and show a FI association with a subset of rare nonsynonymous variants (PSKAT=5.7 × 10(-4)). Conditional analyses suggest that this association is partly explained by the GWAS signal and the presence of a residual independent rare variant effect (Pconditional=0.019). Annotation using ENCODE data suggests that the GWAS variants may have a direct functional role in insulin biology. In conclusion, our study provides insight into variation present at the IGF1 locus and into the genetic architecture underlying FI levels, suggesting that FI associations of SNVs near IGF1 are not mediated by IGF-I and suggesting a role for both rare nonsynonymous and common functional variants in insulin biology.
Keywords: Adult; Aged; Fasting; Female; Humans; Insulin; Insulin-Like Growth Factor I; Male; Middle Aged; Polymorphism, Single Nucleotide

Causal Role of Alcohol Consumption in an Improved Lipid Profile: The Atherosclerosis Risk in Communities (ARIC) Study. - Vu, Khanh N; Ballantyne, Christie M; Hoogeveen, Ron C; Nambi, Vijay; Volcik, Kelly A; Eric Boerwinkle; Morrison, Alanna C (PLoS One, 2016)
INTRODUCTION: Health benefits of low-to-moderate alcohol consumption may operate through an improved lipid profile. A Mendelian randomization (MR) approach was used to examine whether alcohol consumption causally affects lipid levels. METHODS: This analysis involved 10,893 European Americans (EA) from the Atherosclerosis Risk in Communities (ARIC) study. Common and rare variants in alcohol dehydrogenase and acetaldehyde dehydrogenase genes were evaluated for MR assumptions. Five variants, residing in the ADH1B, ADH1C, and ADH4 genes, were selected as genetic instruments and were combined into an unweighted genetic score. Triglycerides (TG), total cholesterol, high-density lipoprotein cholesterol (HDL-c) and its subfractions (HDL2-c and HDL3-c), low-density lipoprotein cholesterol (LDL-c), small dense LDL-c (sdLDL-c), apolipoprotein B (apoB), and lipoprotein (a) (Lp(a)) levels were analyzed. RESULTS: Alcohol consumption significantly increased HDL2-c and reduced TG, total cholesterol, LDL-c, sdLDL-c, and apoB levels. For each of these lipids a non-linear trend was observed. Compared to the first quartile of alcohol consumption, the third quartile had a 12.3% lower level of TG (p < 0.001), a 7.71 mg/dL lower level of total cholesterol (p = 0.007), a 10.3% higher level of HDL2-c (p = 0.007), a 6.87 mg/dL lower level of LDL-c (p = 0.012), a 7.4% lower level of sdLDL-c (p = 0.037), and a 3.5% lower level of apoB (p = 0.058, poverall = 0.022). CONCLUSIONS: This study supports the causal role of regular low-to-moderate alcohol consumption in increasing HDL2-c, reducing TG, total cholesterol, and LDL-c, and provides evidence for the novel finding that low-to-moderate consumption of alcohol reduces apoB and sdLDL-c levels among EA. However, given the nonlinearity of the effect of alcohol consumption, even within the range of low-to-moderate drinking, increased consumption does not always result in a larger benefit.
Keywords: Alcohol Dehydrogenase; Alcohol Drinking; Atherosclerosis; Female; Humans; Lipids; Male; Middle Aged

dbNSFP v3.0: A One-Stop Database of Functional Predictions and Annotations for Human Nonsynonymous and Splice-Site SNVs. - Liu, Xiaoming; Wu, Chunlei; Li, Chang; Eric Boerwinkle (Hum Mutat, 2016)
The purpose of the dbNSFP is to provide a one-stop resource for functional predictions and annotations for human nonsynonymous single-nucleotide variants (nsSNVs) and splice-site variants (ssSNVs), and to facilitate the steps of filtering and prioritizing SNVs from a large list of SNVs discovered in an exome-sequencing study. A list of all potential nsSNVs and ssSNVs based on the human reference sequence were created and functional predictions and annotations were curated and compiled for each SNV. Here, we report a recent major update of the database to version 3.0. The SNV list has been rebuilt based on GENCODE 22 and currently the database includes 82,832,027 nsSNVs and ssSNVs. An attached database dbscSNV, which compiled all potential human SNVs within splicing consensus regions and their deleteriousness predictions, add another 15,030,459 potentially functional SNVs. Eleven prediction scores (MetaSVM, MetaLR, CADD, VEST3, PROVEAN, 4× fitCons, fathmm-MKL, and DANN) and allele frequencies from the UK10K cohorts and the Exome Aggregation Consortium (ExAC), among others, have been added. The original seven prediction scores in v2.0 (SIFT, 2× Polyphen2, LRT, MutationTaster, MutationAssessor, and FATHMM) as well as many SNV and gene functional annotations have been updated. dbNSFP v3.0 is freely available at http://sites.google.com/site/jpopgen/dbNSFP.
Keywords: Computational Biology; Exome; Gene Frequency; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; RNA Splicing

Discovery of Genetic Variation on Chromosome 5q22 Associated with Mortality in Heart Failure. - Smith, J Gustav; Felix, Janine F; Morrison, Alanna C; Kalogeropoulos, Andreas; Trompet, Stella; Wilk, Jemma B; Gidlöf, Olof; Wang, Xinchen; Morley, Michael; Mendelson, Michael; Joehanes, Roby; Ligthart, Symen; et al. (PLoS Genet, 2016)
Failure of the human heart to maintain sufficient output of blood for the demands of the body, heart failure, is a common condition with high mortality even with modern therapeutic alternatives. To identify molecular determinants of mortality in patients with new-onset heart failure, we performed a meta-analysis of genome-wide association studies and follow-up genotyping in independent populations. We identified and replicated an association for a genetic variant on chromosome 5q22 with 36% increased risk of death in subjects with heart failure (rs9885413, P = 2.7x10-9). We provide evidence from reporter gene assays, computational predictions and epigenomic marks that this polymorphism increases activity of an enhancer region active in multiple human tissues. The polymorphism was further reproducibly associated with a DNA methylation signature in whole blood (P = 4.5x10-40) that also associated with allergic sensitization and expression in blood of the cytokine TSLP (P = 1.1x10-4). Knockdown of the transcription factor predicted to bind the enhancer region (NHLH1) in a human cell line (HEK293) expressing NHLH1 resulted in lower TSLP expression. In addition, we observed evidence of recent positive selection acting on the risk allele in populations of African descent. Our findings provide novel genetic leads to factors that influence mortality in patients with heart failure.
Keywords: Alleles; Basic Helix-Loop-Helix Transcription Factors; Black or African American; Chromosomes, Human, Pair 5; DNA Methylation; Female; Gene Expression Regulation; Gene Knockdown Techniques; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genotype; Heart Failure; HEK293 Cells; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Cytokine

An Empirical Comparison of Joint and Stratified Frameworks for Studying G × E Interactions: Systolic Blood Pressure and Smoking in the CHARGE Gene-Lifestyle Interactions Working Group. - Sung, Yun Ju; Winkler, Thomas W; Manning, Alisa K; Aschard, Hugues; Gudnason, Vilmundur; Harris, Tamara B; Smith, Albert V; Eric Boerwinkle; Brown, Michael R; Morrison, Alanna C; Fornage, Myriam; Lin, Li-An; et al. (Genet Epidemiol, 2016)
Studying gene-environment (G × E) interactions is important, as they extend our knowledge of the genetic architecture of complex traits and may help to identify novel variants not detected via analysis of main effects alone. The main statistical framework for studying G × E interactions uses a single regression model that includes both the genetic main and G × E interaction effects (the "joint" framework). The alternative "stratified" framework combines results from genetic main-effect analyses carried out separately within the exposed and unexposed groups. Although there have been several investigations using theory and simulation, an empirical comparison of the two frameworks is lacking. Here, we compare the two frameworks using results from genome-wide association studies of systolic blood pressure for 3.2 million low frequency and 6.5 million common variants across 20 cohorts of European ancestry, comprising 79,731 individuals. Our cohorts have sample sizes ranging from 456 to 22,983 and include both family-based and population-based samples. In cohort-specific analyses, the two frameworks provided similar inference for population-based cohorts. The agreement was reduced for family-based cohorts. In meta-analyses, agreement between the two frameworks was less than that observed in cohort-specific analyses, despite the increased sample size. In meta-analyses, agreement depended on (1) the minor allele frequency, (2) inclusion of family-based cohorts in meta-analysis, and (3) filtering scheme. The stratified framework appears to approximate the joint framework well only for common variants in population-based cohorts. We conclude that the joint framework is the preferred approach and should be used to control false positives when dealing with low-frequency variants and/or family-based cohorts.
Keywords: Blood Pressure; Cohort Studies; Databases, Factual; Family; Gene Frequency; Gene-Environment Interaction; Genome-Wide Association Study; Genotype; Humans; Phenotype; Smoking

An exome array study of the plasma metabolome. - Rhee, Eugene P; Yang, Qiong; Yu, Bing; Liu, Xuan; Cheng, Susan; Deik, Amy; Pierce, Kerry A; Bullock, Kevin; Ho, Jennifer E; Levy, Daniel; Florez, Jose C; Kathiresan, Sek; et al. (Nat Commun, 2016)
The study of rare variants may enhance our understanding of the genetic determinants of the metabolome. Here, we analyze the association between 217 plasma metabolites and exome variants on the Illumina HumanExome Beadchip in 2,076 participants in the Framingham Heart Study, with replication in 1,528 participants of the Atherosclerosis Risk in Communities Study. We identify an association between GMPS and xanthosine using single variant analysis and associations between HAL and histidine, PAH and phenylalanine, and UPB1 and ureidopropionate using gene-based tests (P<5 × 10(-8) in meta-analysis), highlighting novel coding variants that may underlie inborn errors of metabolism. Further, we show how an examination of variants across the spectrum of allele frequency highlights independent association signals at select loci and generates a more integrated view of metabolite heritability. These studies build on prior metabolomics genome wide association studies to provide a more complete picture of the genetic architecture of the plasma metabolome.
Keywords: Exome; Female; Gene Frequency; Genome-Wide Association Study; Humans; Male; Metabolome; Middle Aged; Plasma; Polymorphism, Single Nucleotide; Ribonucleosides; Xanthines

Exome Genotyping Identifies Pleiotropic Variants Associated with Red Blood Cell Traits. - Chami, Nathalie; Chen, Ming-Huei; Slater, Andrew J; Eicher, John D; Evangelou, Evangelos; Tajuddin, Salman M; Love-Gregory, Latisha; Kacprowski, Tim; Schick, Ursula M; Nomura, Akihiro; Giri, Ayush; Lessard, Samuel; et al. (Am J Hum Genet, 2016)
Red blood cell (RBC) traits are important heritable clinical biomarkers and modifiers of disease severity. To identify coding genetic variants associated with these traits, we conducted meta-analyses of seven RBC phenotypes in 130,273 multi-ethnic individuals from studies genotyped on an exome array. After conditional analyses and replication in 27,480 independent individuals, we identified 16 new RBC variants. We found low-frequency missense variants in MAP1A (rs55707100, minor allele frequency [MAF] = 3.3%, p = 2 × 10(-10) for hemoglobin [HGB]) and HNF4A (rs1800961, MAF = 2.4%, p < 3 × 10(-8) for hematocrit [HCT] and HGB). In African Americans, we identified a nonsense variant in CD36 associated with higher RBC distribution width (rs3211938, MAF = 8.7%, p = 7 × 10(-11)) and showed that it is associated with lower CD36 expression and strong allelic imbalance in ex vivo differentiated human erythroblasts. We also identified a rare missense variant in ALAS2 (rs201062903, MAF = 0.2%) associated with lower mean corpuscular volume and mean corpuscular hemoglobin (p < 8 × 10(-9)). Mendelian mutations in ALAS2 are a cause of sideroblastic anemia and erythropoietic protoporphyria. Gene-based testing highlighted three rare missense variants in PKLR, a gene mutated in Mendelian non-spherocytic hemolytic anemia, associated with HGB and HCT (SKAT p < 8 × 10(-7)). These rare, low-frequency, and common RBC variants showed pleiotropy, being also associated with platelet, white blood cell, and lipid traits. Our association results and functional annotation suggest the involvement of new genes in human erythropoiesis. We also confirm that rare and low-frequency variants play a role in the architecture of complex human traits, although their phenotypic effect is generally smaller than originally anticipated.
Keywords: Allelic Imbalance; Black or African American; Erythrocyte Indices; Erythrocytes; Erythropoiesis; Exome; Gene Frequency; Genetic Pleiotropy; Genetic Variation; Genotype; Hematocrit; Hemoglobins; Humans; Quantitative Trait Loci

Exome sequencing in mostly consanguineous Arab families with neurologic disease provides a high potential molecular diagnosis rate. - Charng, Wu-Lin; Karaca, Ender; Coban Akdemir, Zeynep; Gambin, Tomasz; Atik, Mehmed M; Gu, Shen; Posey, Jennifer E; Jhangiani, Shalini N; Donna M Muzny; Harshavardhan Doddapaneni; Jianhong Hu; Eric Boerwinkle; et al. (BMC Med Genomics, 2016)
BACKGROUND: Neurodevelopment is orchestrated by a wide range of genes, and the genetic causes of neurodevelopmental disorders are thus heterogeneous. We applied whole exome sequencing (WES) for molecular diagnosis and in silico analysis to identify novel disease gene candidates in a cohort from Saudi Arabia with primarily Mendelian neurologic diseases. METHODS: We performed WES in 31 mostly consanguineous Arab families and analyzed both single nucleotide and copy number variants (CNVs) from WES data. Interaction/expression network and pathway analyses, as well as paralog studies were utilized to investigate potential pathogenicity and disease association of novel candidate genes. Additional cases for candidate genes were identified through the clinical WES database at Baylor Miraca Genetics Laboratories and GeneMatcher. RESULTS: We found known pathogenic or novel variants in known disease genes with phenotypic expansion in 6 families, disease-associated CNVs in 2 families, and 12 novel disease gene candidates in 11 families, including KIF5B, GRM7, FOXP4, MLLT1, and KDM2B. Overall, a potential molecular diagnosis was provided by variants in known disease genes in 17 families (54.8 %) and by novel candidate disease genes in an additional 11 families, making the potential molecular diagnostic rate ~90 %. CONCLUSIONS: Molecular diagnostic rate from WES is improved by exome-predicted CNVs. Novel candidate disease gene discovery is facilitated by paralog studies and through the use of informatics tools and available databases to identify additional evidence for pathogenicity. TRIAL REGISTRATION: Not applicable.
Keywords: Arabs; Cohort Studies; Consanguinity; Data Mining; Databases, Genetic; DNA Copy Number Variations; Exome; Female; High-Throughput Nucleotide Sequencing; Humans; Male; Molecular Diagnostic Techniques; Nervous System Diseases; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

FLAGS: A Flexible and Adaptive Association Test for Gene Sets Using Summary Statistics. - Huang, Jianfei; Wang, Kai; Wei, Peng; Liu, Xiangtao; Liu, Xiaoming; Tan, Kai; Eric Boerwinkle; Potash, James B; Han, Shizhong (Genetics, 2016)
Genome-wide association studies (GWAS) have been widely used for identifying common variants associated with complex diseases. Despite remarkable success in uncovering many risk variants and providing novel insights into disease biology, genetic variants identified to date fail to explain the vast majority of the heritability for most complex diseases. One explanation is that there are still a large number of common variants that remain to be discovered, but their effect sizes are generally too small to be detected individually. Accordingly, gene set analysis of GWAS, which examines a group of functionally related genes, has been proposed as a complementary approach to single-marker analysis. Here, we propose a FL: exible and A: daptive test for G: ene S: ets (FLAGS), using summary statistics. Extensive simulations showed that this method has an appropriate type I error rate and outperforms existing methods with increased power. As a proof of principle, through real data analyses of Crohn's disease GWAS data and bipolar disorder GWAS meta-analysis results, we demonstrated the superior performance of FLAGS over several state-of-the-art association tests for gene sets. Our method allows for the more powerful application of gene set analysis to complex diseases, which will have broad use given that GWAS summary results are increasingly publicly available.
Keywords: Computer Simulation; Crohn Disease; Genome-Wide Association Study; Genotype; Humans; Models, Genetic; Models, Statistical; Phenotype; Polymorphism, Single Nucleotide

Genetic Variants in LRP1 and ULK4 Are Associated with Acute Aortic Dissections. - Guo, Dong-chuan; Grove, Megan L; Prakash, Siddharth K; Eriksson, Per; Hostetler, Ellen M; LeMaire, Scott A; Body, Simon C; Shalhub, Sherene; Estrera, Anthony L; Safi, Hazim J; Regalado, Ellen S; Zhou, Wei; et al. (Am J Hum Genet, 2016)
Acute aortic dissections are a preventable cause of sudden death if individuals at risk are identified and surgically repaired in a non-emergency setting. Although mutations in single genes can be used to identify at-risk individuals, the majority of dissection case subjects do not have evidence of a single gene disorder, but rather have the other major risk factor for dissections, hypertension. Initial genome-wide association studies (GWASs) identified SNPs at the FBN1 locus associated with both thoracic aortic aneurysms and dissections. Here, we used the Illumina HumanExome array to genotype 753 individuals of European descent presenting specifically with non-familial, sporadic thoracic aortic dissection (STAD) and compared them to the genotypes of 2,259 control subjects from the Atherosclerosis Risk in Communities (ARIC) study matched for age, gender, and, for the majority of cases, hypertension. SNPs in FBN1, LRP1, and ULK4 were identified to be significantly associated with STAD, and these results were replicated in two independent cohorts. Combining the data from all cohorts confirmed an inverse association between LRP1 rs11172113 and STAD (p = 2.74 × 10(-8); OR = 0.82, 95% CI = 0.76-0.89) and a direct association between ULK4 rs2272007 and STAD (p = 1.15 × 10(-9); OR = 1.35, 95% CI = 1.23-1.49). Genomic copy-number variation analysis independently confirmed that ULK4 deletions were significantly associated with development of thoracic aortic disease. These results indicate that genetic variations in LRP1 and ULK4 contribute to risk for presenting with an acute aortic dissection.
Keywords: Aged; Aortic Aneurysm, Thoracic; Aortic Dissection; Atherosclerosis; Case-Control Studies; Cohort Studies; DNA Copy Number Variations; Europe; Exome; Female; Fibrillin-1; Gene Deletion; Genetic Association Studies; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Hypertension; Linkage Disequilibrium; Low Density Lipoprotein Receptor-Related Protein-1; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases; Risk Factors

A genomic approach to therapeutic target validation identifies a glucose-lowering GLP1R variant protective for coronary heart disease. - Scott, Robert A; Freitag, Daniel F; Li, Li; Chu, Audrey Y; Surendran, Praveen; Young, Robin; Grarup, Niels; Stančáková, Alena; Chen, Yuning; Varga, Tibor V; Yaghootkar, Hanieh; Luan, Jian'an; et al. (Sci Transl Med, 2016)
Regulatory authorities have indicated that new drugs to treat type 2 diabetes (T2D) should not be associated with an unacceptable increase in cardiovascular risk. Human genetics may be able to guide development of antidiabetic therapies by predicting cardiovascular and other health endpoints. We therefore investigated the association of variants in six genes that encode drug targets for obesity or T2D with a range of metabolic traits in up to 11,806 individuals by targeted exome sequencing and follow-up in 39,979 individuals by targeted genotyping, with additional in silico follow-up in consortia. We used these data to first compare associations of variants in genes encoding drug targets with the effects of pharmacological manipulation of those targets in clinical trials. We then tested the association of those variants with disease outcomes, including coronary heart disease, to predict cardiovascular safety of these agents. A low-frequency missense variant (Ala316Thr; rs10305492) in the gene encoding glucagon-like peptide-1 receptor (GLP1R), the target of GLP1R agonists, was associated with lower fasting glucose and T2D risk, consistent with GLP1R agonist therapies. The minor allele was also associated with protection against heart disease, thus providing evidence that GLP1R agonists are not likely to be associated with an unacceptable increase in cardiovascular risk. Our results provide an encouraging signal that these agents may be associated with benefit, a question currently being addressed in randomized controlled trials. Genetic variants associated with metabolic traits and multiple disease outcomes can be used to validate therapeutic targets at an early stage in the drug development process.
Keywords: Alleles; Coronary Disease; Diabetes Mellitus, Type 2; Dipeptidyl Peptidase 4; Genotype; Glucagon-Like Peptide-1 Receptor; Humans; Obesity; Receptor, Cannabinoid, CB2; Receptor, Serotonin, 5-HT2C; Receptors, Somatostatin; Sodium-Glucose Transporter 1

A hybrid computational strategy to address WGS variant analysis in >5000 samples. - Huang, Zhuoyi; Rustagi, Navin; Veeraraghavan, Narayanan; Carroll, Andrew; Richard A Gibbs; Eric Boerwinkle; Venkata, Manjunath Gorentla; Fuli Yu (BMC Bioinformatics, 2016)
BACKGROUND: The decreasing costs of sequencing are driving the need for cost effective and real time variant calling of whole genome sequencing data. The scale of these projects are far beyond the capacity of typical computing resources available with most research labs. Other infrastructures like the cloud AWS environment and supercomputers also have limitations due to which large scale joint variant calling becomes infeasible, and infrastructure specific variant calling strategies either fail to scale up to large datasets or abandon joint calling strategies. RESULTS: We present a high throughput framework including multiple variant callers for single nucleotide variant (SNV) calling, which leverages hybrid computing infrastructure consisting of cloud AWS, supercomputers and local high performance computing infrastructures. We present a novel binning approach for large scale joint variant calling and imputation which can scale up to over 10,000 samples while producing SNV callsets with high sensitivity and specificity. As a proof of principle, we present results of analysis on Cohorts for Heart And Aging Research in Genomic Epidemiology (CHARGE) WGS freeze 3 dataset in which joint calling, imputation and phasing of over 5300 whole genome samples was produced in under 6 weeks using four state-of-the-art callers. The callers used were SNPTools, GATK-HaplotypeCaller, GATK-UnifiedGenotyper and GotCloud. We used Amazon AWS, a 4000-core in-house cluster at Baylor College of Medicine, IBM power PC Blue BioU at Rice and Rhea at Oak Ridge National Laboratory (ORNL) for the computation. AWS was used for joint calling of 180 TB of BAM files, and ORNL and Rice supercomputers were used for the imputation and phasing step. All other steps were carried out on the local compute cluster. The entire operation used 5.2 million core hours and only transferred a total of 6 TB of data across the platforms. CONCLUSIONS: Even with increasing sizes of whole genome datasets, ensemble joint calling of SNVs for low coverage data can be accomplished in a scalable, cost effective and fast manner by using heterogeneous computing platforms without compromising on the quality of variants.
Keywords: Databases, Genetic; Genome, Human; Genomics; High-Throughput Nucleotide Sequencing; Humans

Identification of Rare Variants in Metabolites of the Carnitine Pathway by Whole Genome Sequencing Analysis. - Yazdani, Akram; Yazdani, Azam; Liu, Xiaoming; Eric Boerwinkle (Genet Epidemiol, 2016)
We use whole genome sequence data and rare variant analysis methods to investigate a subset of the human serum metabolome, including 16 carnitine-related metabolites that are important components of mammalian energy metabolism. Medium pass sequence data consisting of 12,820,347 rare variants and serum metabolomics data were available on 1,456 individuals. By applying a penalization method, we identified two genes FGF8 and MDGA2 with significant effects on lysine and cis-4-decenoylcarnitine, respectively, using Δ-AIC and likelihood ratio test statistics. Single variant analyses in these regions did not identify a single low-frequency variant (minor allele count > 3) responsible for the underlying signal. The results demonstrate the utility of whole genome sequence and innovative analyses for identifying candidate regions influencing complex phenotypes.
Keywords: Biomarkers; Carnitine; Female; Fibroblast Growth Factor 8; Genetic Variation; GPI-Linked Proteins; High-Throughput Nucleotide Sequencing; Humans; Linkage Disequilibrium; Lysine; Male; Metabolomics; Middle Aged; Neural Cell Adhesion Molecules; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

The impact of multiple single day blood pressure readings on cardiovascular risk estimation: The Atherosclerosis Risk in Communities study. - Ogunwale, Abayomi N; Morrison, Alanna C; Sun, Wensheng; Dodge, Rhiannon C; Virani, Salim S; Taylor, Addison; Gottesman, Rebecca F; Yang, Eric; Wei, Peng; McEvoy, John W; Heiss, Gerardo; Eric Boerwinkle; et al. (Eur J Prev Cardiol, 2016)
AIMS: The aim of this study was to determine the magnitude of change in estimated cardiovascular disease risk when multiple same day blood pressure measurements are used in estimating coronary heart disease, heart failure and stroke risks. METHODS AND RESULTS: Black and White participants, N = 11,129, enrolled in the Atherosclerosis Risk in Communities study (mean age 53.9 ± 5.7 (SD) years) were included. Each participant had three sitting, five supine, and six standing blood pressure measures during one day. Main outcome measures were changes in estimated coronary heart disease, heart failure and stroke risk when using the different blood pressure measures. Mean sitting, standing and supine systolic blood pressure values of the study population were 120.8 ± 18.6, 124.9 ± 20 and 124.7 ± 19.6 mmHg, respectively. The substitution of the second sitting systolic blood pressure with the third sitting systolic blood pressure (taken ∼5 min later) in two separate coronary heart disease risk models reclassified 3.3% to 5.1% of study participants. Similar substitutions for heart failure and stroke risk prediction models led to reclassification of 1.9% and 2.7% of participants respectively. When mean sitting systolic blood pressure was replaced with mean standing systolic blood pressure 5.4% to 11.6% of the participants were reclassified. Maximum upward and downward change in an individual's estimated risk was 31% and 26% respectively. CONCLUSIONS: Estimated risks of coronary heart disease, heart failure, and stroke for an individual can change significantly within a day due to changes in systolic blood pressure. Given recommendations to use estimated risk for therapeutic decisions, our study has implications for the use of a single systolic blood pressure in cardiovascular risk estimation.
Keywords: Atherosclerosis; Blood Pressure; Blood Pressure Determination; Cardiovascular Diseases; Female; Humans; Incidence; Male; Middle Aged; Risk Assessment; Risk Factors; United States

Large-Scale Exome-wide Association Analysis Identifies Loci for White Blood Cell Traits and Pleiotropy with Immune-Mediated Diseases. - Tajuddin, Salman M; Schick, Ursula M; Eicher, John D; Chami, Nathalie; Giri, Ayush; Brody, Jennifer A; Hill, W David; Kacprowski, Tim; Li, Jin; Lyytikäinen, Leo-Pekka; Manichaikul, Ani; Mihailov, Evelin; et al. (Am J Hum Genet, 2016)
White blood cells play diverse roles in innate and adaptive immunity. Genetic association analyses of phenotypic variation in circulating white blood cell (WBC) counts from large samples of otherwise healthy individuals can provide insights into genes and biologic pathways involved in production, differentiation, or clearance of particular WBC lineages (myeloid, lymphoid) and also potentially inform the genetic basis of autoimmune, allergic, and blood diseases. We performed an exome array-based meta-analysis of total WBC and subtype counts (neutrophils, monocytes, lymphocytes, basophils, and eosinophils) in a multi-ancestry discovery and replication sample of ∼157,622 individuals from 25 studies. We identified 16 common variants (8 of which were coding variants) associated with one or more WBC traits, the majority of which are pleiotropically associated with autoimmune diseases. Based on functional annotation, these loci included genes encoding surface markers of myeloid, lymphoid, or hematopoietic stem cell differentiation (CD69, CD33, CD87), transcription factors regulating lineage specification during hematopoiesis (ASXL1, IRF8, IKZF1, JMJD1C, ETS2-PSMG1), and molecules involved in neutrophil clearance/apoptosis (C10orf54, LTA), adhesion (TNXB), or centrosome and microtubule structure/function (KIF9, TUBD1). Together with recent reports of somatic ASXL1 mutations among individuals with idiopathic cytopenias or clonal hematopoiesis of undetermined significance, the identification of a common regulatory 3' UTR variant of ASXL1 suggests that both germline and somatic ASXL1 mutations contribute to lower blood counts in otherwise asymptomatic individuals. These association results shed light on genetic mechanisms that regulate circulating WBC counts and suggest a prominent shared genetic architecture with inflammatory and autoimmune diseases.
Keywords: Blood Cell Count; Exome; Genetic Loci; Genetic Pleiotropy; Genome-Wide Association Study; Humans; Immune System Diseases; Leukocytes; Quality Control

Loss-of-function variants influence the human serum metabolome. - Yu, Bing; Li, Alexander H; Ginger A Metcalf; Donna M Muzny; Morrison, Alanna C; White, Simon; Mosley, Thomas H; Richard A Gibbs; Eric Boerwinkle (Sci Adv, 2016)
The metabolome is a collection of small molecules resulting from multiple cellular and biological processes that can act as biomarkers of disease, and African-Americans exhibit high levels of genetic diversity. Exome sequencing of a sample of deeply phenotyped African-Americans allowed us to analyze the effects of annotated loss-of-function (LoF) mutations on 308 serum metabolites measured by untargeted liquid and gas chromatography coupled with mass spectrometry. In an independent sample, we identified and replicated four genes harboring six LoF mutations that significantly affected five metabolites. These sites were related to a 19 to 45% difference in geometric mean metabolite levels, with an average effect size of 25%. We show that some of the affected metabolites are risk predictors or diagnostic biomarkers of disease and, using the principle of Mendelian randomization, are in the causal pathway of disease. For example, LoF mutations in SLCO1B1 elevate the levels of hexadecanedioate, a fatty acid significantly associated with increased blood pressure levels and risk of incident heart failure in both African-Americans and an independent sample of European-Americans. We show that SLCO1B1 LoF mutations significantly increase the risk of incident heart failure, thus implicating the metabolite in the causal pathway of disease. These results reveal new avenues into gene function and the understanding of disease etiology by integrating -omic technologies into a deeply phenotyped population study.
Keywords: Aged; Biomarkers; Black or African American; Exome; Female; Genetic Variation; Heart Failure; High-Throughput Nucleotide Sequencing; Humans; Hypertension; Liver-Specific Organic Anion Transporter 1; Male; Metabolome; Middle Aged; Mutation; Risk Factors; White People

Meta-analysis of 49 549 individuals imputed with the 1000 Genomes Project reveals an exonic damaging variant in ANGPTL4 determining fasting TG levels. - van Leeuwen, Elisabeth M; Aniko Sabo; Bis, Joshua C; Huffman, Jennifer E; Manichaikul, Ani; Smith, Albert V; Feitosa, Mary F; Demissie, Serkalem; Joshi, Peter K; Duan, Qing; Marten, Jonathan; van Klinken, Jan B; et al. (J Med Genet, 2016)
BACKGROUND: So far, more than 170 loci have been associated with circulating lipid levels through genome-wide association studies (GWAS). These associations are largely driven by common variants, their function is often not known, and many are likely to be markers for the causal variants. In this study we aimed to identify more new rare and low-frequency functional variants associated with circulating lipid levels. METHODS: We used the 1000 Genomes Project as a reference panel for the imputations of GWAS data from ∼60 000 individuals in the discovery stage and ∼90 000 samples in the replication stage. RESULTS: Our study resulted in the identification of five new associations with circulating lipid levels at four loci. All four loci are within genes that can be linked biologically to lipid metabolism. One of the variants, rs116843064, is a damaging missense variant within the ANGPTL4 gene. CONCLUSIONS: This study illustrates that GWAS with high-scale imputation may still help us unravel the biological mechanism behind circulating lipid levels.
Keywords: Angiopoietin-Like Protein 4; Angiopoietins; Exons; Fasting; Female; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide

MIPEP recessive variants cause a syndrome of left ventricular non-compaction, hypotonia, and infantile death. - Eldomery, Mohammad K; Akdemir, Zeynep C; Vögtle, F-Nora; Charng, Wu-Lin; Mulica, Patrycja; Rosenfeld, Jill A; Gambin, Tomasz; Gu, Shen; Burrage, Lindsay C; Al Shamsi, Aisha; Penney, Samantha; Jhangiani, Shalini N; et al. (Genome Med, 2016)
BACKGROUND: Mitochondrial presequence proteases perform fundamental functions as they process about 70 % of all mitochondrial preproteins that are encoded in the nucleus and imported posttranslationally. The mitochondrial intermediate presequence protease MIP/Oct1, which carries out precursor processing, has not yet been established to have a role in human disease. METHODS: Whole exome sequencing was performed on four unrelated probands with left ventricular non-compaction (LVNC), developmental delay (DD), seizures, and severe hypotonia. Proposed pathogenic variants were confirmed by Sanger sequencing or array comparative genomic hybridization. Functional analysis of the identified MIP variants was performed using the model organism Saccharomyces cerevisiae as the protein and its functions are highly conserved from yeast to human. RESULTS: Biallelic single nucleotide variants (SNVs) or copy number variants (CNVs) in MIPEP, which encodes MIP, were present in all four probands, three of whom had infantile/childhood death. Two patients had compound heterozygous SNVs (p.L582R/p.L71Q and p.E602*/p.L306F) and one patient from a consanguineous family had a homozygous SNV (p.K343E). The fourth patient, identified through the GeneMatcher tool, a part of the Matchmaker Exchange Project, was found to have inherited a paternal SNV (p.H512D) and a maternal CNV (1.4-Mb deletion of 13q12.12) that includes MIPEP. All amino acids affected in the patients' missense variants are highly conserved from yeast to human and therefore S. cerevisiae was employed for functional analysis (for p.L71Q, p.L306F, and p.K343E). The mutations p.L339F (human p.L306F) and p.K376E (human p.K343E) resulted in a severe decrease of Oct1 protease activity and accumulation of non-processed Oct1 substrates and consequently impaired viability under respiratory growth conditions. The p.L83Q (human p.L71Q) failed to localize to the mitochondria. CONCLUSIONS: Our findings reveal for the first time the role of the mitochondrial intermediate peptidase in human disease. Loss of MIP function results in a syndrome which consists of LVNC, DD, seizures, hypotonia, and cataracts. Our approach highlights the power of data exchange and the importance of an interrelationship between clinical and research efforts for disease gene discovery.
Keywords: Adult; Amino Acid Sequence; Female; Genes, Recessive; Heart Defects, Congenital; Humans; Infant; Infant, Newborn; Male; Metalloendopeptidases; Muscle Hypotonia; Pedigree; Phenotype; Sequence Homology, Amino Acid; Sudden Infant Death; Syndrome

Molecular diagnostic experience of whole-exome sequencing in adult patients. - Posey, Jennifer E; Rosenfeld, Jill A; James, Regis A; Bainbridge, Matthew; Niu, Zhiyv; Wang, Xia; Dhar, Shweta; Wiszniewski, Wojciech; Akdemir, Zeynep H C; Gambin, Tomasz; Xia, Fan; Person, Richard E; et al. (Genet Med, 2016)
PURPOSE: Whole-exome sequencing (WES) is increasingly used as a diagnostic tool in medicine, but prior reports focus on predominantly pediatric cohorts with neurologic or developmental disorders. We describe the diagnostic yield and characteristics of WES in adults. METHODS: We performed a retrospective analysis of consecutive WES reports for adults from a diagnostic laboratory. Phenotype composition was determined using Human Phenotype Ontology terms. RESULTS: Molecular diagnoses were reported for 17.5% (85/486) of adults, which is lower than that for a primarily pediatric population (25.2%; P = 0.0003); the diagnostic rate was higher (23.9%) for those 18-30 years of age compared to patients older than 30 years (10.4%; P = 0.0001). Dual Mendelian diagnoses contributed to 7% of diagnoses, revealing blended phenotypes. Diagnoses were more frequent among individuals with abnormalities of the nervous system, skeletal system, head/neck, and growth. Diagnostic rate was independent of family history information, and de novo mutations contributed to 61.4% of autosomal dominant diagnoses. CONCLUSION: Early WES experience in adults demonstrates molecular diagnoses in a substantial proportion of patients, informing clinical management, recurrence risk, and recommendations for relatives. A positive family history was not predictive, consistent with molecular diagnoses often revealed by de novo events, informing the Mendelian basis of genetic disease in adults.Genet Med 18 7, 678-685.
Keywords: Adult; Exome; Female; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Male; Pathology, Molecular

Monoallelic and Biallelic Variants in EMC1 Identified in Individuals with Global Developmental Delay, Hypotonia, Scoliosis, and Cerebellar Atrophy. - Harel, Tamar; Yesil, Gozde; Bayram, Yavuz; Coban-Akdemir, Zeynep; Charng, Wu-Lin; Karaca, Ender; Al Asmari, Ali; Eldomery, Mohammad K; Hunter, Jill V; Jhangiani, Shalini N; Rosenfeld, Jill A; Pehlivan, Davut; et al. (Am J Hum Genet, 2016)
The paradigm of a single gene associated with one specific phenotype and mode of inheritance has been repeatedly challenged. Genotype-phenotype correlations can often be traced to different mutation types, localization of the variants in distinct protein domains, or the trigger of or escape from nonsense-mediated decay. Using whole-exome sequencing, we identified homozygous variants in EMC1 that segregated with a phenotype of developmental delay, hypotonia, scoliosis, and cerebellar atrophy in three families. In addition, a de novo heterozygous EMC1 variant was seen in an individual with a similar clinical and MRI imaging phenotype. EMC1 encodes a member of the endoplasmic reticulum (ER)-membrane protein complex (EMC), an evolutionarily conserved complex that has been proposed to have multiple roles in ER-associated degradation, ER-mitochondria tethering, and proper assembly of multi-pass transmembrane proteins. Perturbations of protein folding and organelle crosstalk have been implicated in neurodegenerative processes including cerebellar atrophy. We propose EMC1 as a gene in which either biallelic or monoallelic variants might lead to a syndrome including intellectual disability and preferential degeneration of the cerebellum.
Keywords: Adolescent; Alleles; Amino Acid Sequence; Atrophy; Cerebellum; Child; Child, Preschool; Developmental Disabilities; Endoplasmic Reticulum-Associated Degradation; Female; Genetic Association Studies; Genetic Variation; Heterozygote; Humans; Magnetic Resonance Imaging; Male; Membrane Proteins; Molecular Sequence Data; Muscle Hypotonia; Mutation; Pedigree; Protein Folding; Proteins; Scoliosis

Multiallelic Positions in the Human Genome: Challenges for Genetic Analyses. - Campbell, Ian M; Gambin, Tomasz; Jhangiani, Shalini; Grove, Megan L; Veeraraghavan, Narayanan; Donna M Muzny; Shaw, Chad A; Richard A Gibbs; Eric Boerwinkle; Fuli Yu; Lupski, James R (Hum Mutat, 2016)
As the amount of human genomic sequence available from personal genomes and exomes has increased, so too has the observation of genomic positions having two or more alternative alleles, so-called multiallelic sites. For portions of the haploid genome that are present in more than one copy, including segmental duplications, variation at such multisite variant positions becomes even more complex. Despite the frequency of multiallelic variants, a number of commonly used resources and tools in genomic research and diagnostics do not support these multiallelic variants all together or require special modifications. Here, we explore the frequency of multiallelic sites in large samples with whole exome sequencing and discuss potential outcomes of failing to account for multiple variant alleles. We also briefly discuss some commonly utilized resources that fully support multiallelic sites.
Keywords: Alleles; Exome; Genome, Human; Humans

Mutations in the nuclear bile acid receptor FXR cause progressive familial intrahepatic cholestasis. - Gomez-Ospina, Natalia; Potter, Carol J; Xiao, Rui; Manickam, Kandamurugu; Kim, Mi-Sun; Kim, Kang Ho; Shneider, Benjamin L; Picarsic, Jennifer L; Jacobson, Theodora A; Zhang, Jing; He, Weimin; Liu, Pengfei; et al. (Nat Commun, 2016)
Neonatal cholestasis is a potentially life-threatening condition requiring prompt diagnosis. Mutations in several different genes can cause progressive familial intrahepatic cholestasis, but known genes cannot account for all familial cases. Here we report four individuals from two unrelated families with neonatal cholestasis and mutations in NR1H4, which encodes the farnesoid X receptor (FXR), a bile acid-activated nuclear hormone receptor that regulates bile acid metabolism. Clinical features of severe, persistent NR1H4-related cholestasis include neonatal onset with rapid progression to end-stage liver disease, vitamin K-independent coagulopathy, low-to-normal serum gamma-glutamyl transferase activity, elevated serum alpha-fetoprotein and undetectable liver bile salt export pump (ABCB11) expression. Our findings demonstrate a pivotal function for FXR in bile acid homeostasis and liver protection.
Keywords: ATP Binding Cassette Transporter, Subfamily B, Member 11; ATP-Binding Cassette Transporters; Bile Acids and Salts; Cholestasis, Intrahepatic; Female; Humans; Male; Mutation; Receptors, Cytoplasmic and Nuclear; Young Adult

PEHO Syndrome May Represent Phenotypic Expansion at the Severe End of the Early-Onset Encephalopathies. - Gawlinski, Pawel; Posmyk, Renata; Gambin, Tomasz; Sielicka, Danuta; Chorazy, Monika; Nowakowska, Beata; Jhangiani, Shalini N; Donna M Muzny; Bekiesinska-Figatowska, Monika; Bal, Jerzy; Eric Boerwinkle; Richard A Gibbs; et al. (Pediatr Neurol, 2016)
BACKGROUND: Progressive encephalopathy with edema, hypsarrhythmia and optic atrophy (PEHO) syndrome is a distinct neurodevelopmental disorder. Patients without optic nerve atrophy and brain imaging abnormalities but fulfilling other PEHO criteria are often described as a PEHO-like syndrome. The molecular bases of both clinically defined conditions remain unknown in spite of the widespread application of genome analyses in both clinic and research. METHODS: We enrolled two patients with a prior diagnosis of PEHO and two individuals with PEHO-like syndrome. All four individuals subsequently underwent whole-exome sequencing and comprehensive genomic analysis. RESULTS: We identified disease-causing mutations in known genes associated with neurodevelopmental disorders including GNAO1 and CDKL5 in two of four individuals. One patient with PEHO syndrome and a de novoGNAO1 mutation was found to have an additional de novo mutation in HESX1 that is associated with optic atrophy. CONCLUSIONS: We hypothesize that PEHO and PEHO-like syndrome may represent a severe end of the spectrum of the early-onset encephalopathies and, in some instances, its complex phenotype may result from an aggregated effect of mutations at two loci.
Keywords: Brain Edema; Child; Child, Preschool; Female; GTP-Binding Protein alpha Subunits, Gi-Go; Humans; Infant; Male; Mutation; Neurodegenerative Diseases; Optic Atrophy; Phenotype; Protein Serine-Threonine Kinases; Spasms, Infantile

Platelet-Related Variants Identified by Exomechip Meta-analysis in 157,293 Individuals. - Eicher, John D; Chami, Nathalie; Kacprowski, Tim; Nomura, Akihiro; Chen, Ming-Huei; Yanek, Lisa R; Tajuddin, Salman M; Schick, Ursula M; Slater, Andrew J; Pankratz, Nathan; Polfus, Linda; Schurmann, Claudia; et al. (Am J Hum Genet, 2016)
Platelet production, maintenance, and clearance are tightly controlled processes indicative of platelets' important roles in hemostasis and thrombosis. Platelets are common targets for primary and secondary prevention of several conditions. They are monitored clinically by complete blood counts, specifically with measurements of platelet count (PLT) and mean platelet volume (MPV). Identifying genetic effects on PLT and MPV can provide mechanistic insights into platelet biology and their role in disease. Therefore, we formed the Blood Cell Consortium (BCX) to perform a large-scale meta-analysis of Exomechip association results for PLT and MPV in 157,293 and 57,617 individuals, respectively. Using the low-frequency/rare coding variant-enriched Exomechip genotyping array, we sought to identify genetic variants associated with PLT and MPV. In addition to confirming 47 known PLT and 20 known MPV associations, we identified 32 PLT and 18 MPV associations not previously observed in the literature across the allele frequency spectrum, including rare large effect (FCER1A), low-frequency (IQGAP2, MAP1A, LY75), and common (ZMIZ2, SMG6, PEAR1, ARFGAP3/PACSIN2) variants. Several variants associated with PLT/MPV (PEAR1, MRVI1, PTGES3) were also associated with platelet reactivity. In concurrent BCX analyses, there was overlap of platelet-associated variants with red (MAP1A, TMPRSS6, ZMIZ2) and white (PEAR1, ZMIZ2, LY75) blood cell traits, suggesting common regulatory pathways with shared genetic architecture among these hematopoietic lineages. Our large-scale Exomechip analyses identified previously undocumented associations with platelet traits and further indicate that several complex quantitative hematological, lipid, and cardiovascular traits share genetic factors.
Keywords: Blood Platelets; Exome; Female; Genetic Variation; Genome-Wide Association Study; Humans; Male; Mean Platelet Volume; Platelet Count

POGZ truncating alleles cause syndromic intellectual disability. - White, Janson; Beck, Christine R; Harel, Tamar; Posey, Jennifer E; Jhangiani, Shalini N; Tang, Sha; Farwell, Kelly D; Powis, Zöe; Mendelsohn, Nancy J; Baker, Janice A; Pollack, Lynda; Mason, Kati J; et al. (Genome Med, 2016)
BACKGROUND: Large-scale cohort-based whole exome sequencing of individuals with neurodevelopmental disorders (NDDs) has identified numerous novel candidate disease genes; however, detailed phenotypic information is often lacking in such studies. De novo mutations in pogo transposable element with zinc finger domain (POGZ) have been identified in six independent and diverse cohorts of individuals with NDDs ranging from autism spectrum disorder to developmental delay. METHODS: Whole exome sequencing was performed on five unrelated individuals. Sanger sequencing was used to validate variants and segregate mutations with the phenotype in available family members. RESULTS: We identified heterozygous truncating mutations in POGZ in five unrelated individuals, which were confirmed to be de novo or not present in available parental samples. Careful review of the phenotypes revealed shared features that included developmental delay, intellectual disability, hypotonia, behavioral abnormalities, and similar facial characteristics. Variable features included short stature, microcephaly, strabismus and hearing loss. CONCLUSIONS: While POGZ has been associated with neurodevelopmental disorders in large cohort studies, our data suggest that loss of function variants in POGZ lead to an identifiable syndrome of NDD with specific phenotypic traits. This study exemplifies the era of human reverse clinical genomics ushered in by large disease-directed cohort studies; first defining a new syndrome molecularly and, only subsequently, phenotypically.
Keywords: Adolescent; Adult; Alleles; Child, Preschool; Exome; Female; Heterozygote; Humans; Infant; Intellectual Disability; Male; Mutation; Sequence Analysis, DNA; Transposases

Rare Exome Sequence Variants in CLCN6 Reduce Blood Pressure Levels and Hypertension Risk. - Yu, Bing; Pulit, Sara L; Hwang, Shih-Jen; Brody, Jennifer A; Amin, Najaf; Auer, Paul L; Bis, Joshua C; Eric Boerwinkle; Burke, Gregory L; Chakravarti, Aravinda; Correa, Adolfo; Dreisbach, Albert W; et al. (Circ Cardiovasc Genet, 2016)
BACKGROUND: Rare genetic variants influence blood pressure (BP). METHODS AND RESULTS: Whole-exome sequencing was performed on DNA samples from 17 956 individuals of European ancestry and African ancestry (14 497, first-stage discovery and 3459, second-stage discovery) to examine the effect of rare variants on hypertension and 4 BP traits: systolic BP, diastolic BP, pulse pressure, and mean arterial pressure. Tests of ≈170 000 common variants (minor allele frequency, ≥1%; statistical significance, P≤2.9×10(-7)) and gene-based tests of rare variants (minor allele frequency, <1%; ≈17 000 genes; statistical significance, P≤1.5×10(-6)) were evaluated for each trait and ancestry, followed by multiethnic meta-analyses. In the first-stage discovery, rare coding variants (splicing, stop-gain, stop-loss, nonsynonymous variants, or indels) in CLCN6 were associated with lower diastolic BP (cumulative minor allele frequency, 1.3%; β=-3.20; P=4.1×10(-6)) and were independent of a nearby common variant (rs17367504) previously associated with BP. CLCN6 rare variants were also associated with lower systolic BP (β=-4.11; P=2.8×10(-4)), mean arterial pressure (β=-3.50; P=8.9×10(-6)), and reduced hypertension risk (odds ratio, 0.72; P=0.017). Meta-analysis of the 2-stage discovery samples showed that CLCN6 was associated with lower diastolic BP at exome-wide significance (cumulative minor allele frequency, 1.1%; β=-3.30; P=5.0×10(-7)). CONCLUSIONS: These findings implicate the effect of rare coding variants in CLCN6 in BP variation and offer new insights into BP regulation.
Keywords: Alleles; Black People; Blood Pressure; Chloride Channels; Exome; Female; Gene Frequency; Humans; Hypertension; Male; Risk Factors; White People

Rare Functional Variant in TM2D3 is Associated with Late-Onset Alzheimer's Disease. - Jakobsdottir, Johanna; van der Lee, Sven J; Bis, Joshua C; Chouraki, Vincent; Li-Kroeger, David; Yamamoto, Shinya; Grove, Megan L; Naj, Adam; Vronskaya, Maria; Salazar, Jose L; DeStefano, Anita L; Brody, Jennifer A; et al. (PLoS Genet, 2016)
We performed an exome-wide association analysis in 1393 late-onset Alzheimer's disease (LOAD) cases and 8141 controls from the CHARGE consortium. We found that a rare variant (P155L) in TM2D3 was enriched in Icelanders (~0.5% versus <0.05% in other European populations). In 433 LOAD cases and 3903 controls from the Icelandic AGES sub-study, P155L was associated with increased risk and earlier onset of LOAD [odds ratio (95% CI) = 7.5 (3.5-15.9), p = 6.6x10-9]. Mutation in the Drosophila TM2D3 homolog, almondex, causes a phenotype similar to loss of Notch/Presenilin signaling. Human TM2D3 is capable of rescuing these phenotypes, but this activity is abolished by P155L, establishing it as a functionally damaging allele. Our results establish a rare TM2D3 variant in association with LOAD susceptibility, and together with prior work suggests possible links to the β-amyloid cascade.
Keywords: Age of Onset; Aged; Alleles; Alzheimer Disease; Amyloid beta-Protein Precursor; Animals; Apolipoproteins E; Drosophila melanogaster; Drosophila Proteins; Exome; Female; Genome-Wide Association Study; Genomics; Humans; Iceland; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Mutation; Phenotype; Receptors, Notch; Tropomyosin; White People

Recurrent De Novo and Biallelic Variation of ATAD3A, Encoding a Mitochondrial Membrane Protein, Results in Distinct Neurological Syndromes. - Harel, Tamar; Yoon, Wan Hee; Garone, Caterina; Gu, Shen; Coban-Akdemir, Zeynep; Eldomery, Mohammad K; Posey, Jennifer E; Jhangiani, Shalini N; Rosenfeld, Jill A; Cho, Megan T; Fox, Stephanie; Withers, Marjorie; et al. (Am J Hum Genet, 2016)
ATPase family AAA-domain containing protein 3A (ATAD3A) is a nuclear-encoded mitochondrial membrane protein implicated in mitochondrial dynamics, nucleoid organization, protein translation, cell growth, and cholesterol metabolism. We identified a recurrent de novo ATAD3A c.1582C>T (p.Arg528Trp) variant by whole-exome sequencing (WES) in five unrelated individuals with a core phenotype of global developmental delay, hypotonia, optic atrophy, axonal neuropathy, and hypertrophic cardiomyopathy. We also describe two families with biallelic variants in ATAD3A, including a homozygous variant in two siblings, and biallelic ATAD3A deletions mediated by nonallelic homologous recombination (NAHR) between ATAD3A and gene family members ATAD3B and ATAD3C. Tissue-specific overexpression of bor, the Drosophila mutation homologous to the human c.1582C>T (p.Arg528Trp) variant, resulted in a dramatic decrease in mitochondrial content, aberrant mitochondrial morphology, and increased autophagy. Homozygous null bor larvae showed a significant decrease of mitochondria, while overexpression of bor resulted in larger, elongated mitochondria. Finally, fibroblasts of an affected individual exhibited increased mitophagy. We conclude that the p.Arg528Trp variant functions through a dominant-negative mechanism that results in small mitochondria that trigger mitophagy, resulting in a reduction in mitochondrial content. ATAD3A variation represents an additional link between mitochondrial dynamics and recognizable neurological syndromes, as seen with MFN2, OPA1, DNM1L, and STAT2 mutations.
Keywords: Adenosine Triphosphatases; Adult; Alleles; Animals; ATPases Associated with Diverse Cellular Activities; Axons; Cardiomyopathies; Child; Child, Preschool; Developmental Disabilities; DNA Copy Number Variations; Drosophila melanogaster; Female; Fibroblasts; Homozygote; Humans; Infant; Infant, Newborn; Male; Membrane Proteins; Mitochondria; Mitochondrial Proteins; Muscle Hypotonia; Muscles; Mutation; Nervous System Diseases; Neurons; Optic Atrophy; Phenotype; Polymorphism, Single Nucleotide; Syndrome; Young Adult

Recurrent Muscle Weakness with Rhabdomyolysis, Metabolic Crises, and Cardiac Arrhythmia Due to Bi-allelic TANGO2 Mutations. - Lalani, Seema R; Liu, Pengfei; Rosenfeld, Jill A; Watkin, Levi B; Chiang, Theodore; Leduc, Magalie S; Zhu, Wenmiao; Ding, Yan; Pan, Shujuan; Vetrini, Francesco; Miyake, Christina Y; Shinawi, Marwan; et al. (Am J Hum Genet, 2016)
The underlying genetic etiology of rhabdomyolysis remains elusive in a significant fraction of individuals presenting with recurrent metabolic crises and muscle weakness. Using exome sequencing, we identified bi-allelic mutations in TANGO2 encoding transport and Golgi organization 2 homolog (Drosophila) in 12 subjects with episodic rhabdomyolysis, hypoglycemia, hyperammonemia, and susceptibility to life-threatening cardiac tachyarrhythmias. A recurrent homozygous c.460G>A (p.Gly154Arg) mutation was found in four unrelated individuals of Hispanic/Latino origin, and a homozygous ∼34 kb deletion affecting exons 3-9 was observed in two families of European ancestry. One individual of mixed Hispanic/European descent was found to be compound heterozygous for c.460G>A (p.Gly154Arg) and the deletion of exons 3-9. Additionally, a homozygous exons 4-6 deletion was identified in a consanguineous Middle Eastern Arab family. No homozygotes have been reported for these changes in control databases. Fibroblasts derived from a subject with the recurrent c.460G>A (p.Gly154Arg) mutation showed evidence of increased endoplasmic reticulum stress and a reduction in Golgi volume density in comparison to control. Our results show that the c.460G>A (p.Gly154Arg) mutation and the exons 3-9 heterozygous deletion in TANGO2 are recurrent pathogenic alleles present in the Latino/Hispanic and European populations, respectively, causing considerable morbidity in the homozygotes in these populations.
Keywords: Alleles; Arabs; Arrhythmias, Cardiac; Base Sequence; Child; Child, Preschool; Endoplasmic Reticulum Stress; Exome; Exons; Female; Gene Deletion; Golgi Apparatus; Hispanic or Latino; Homozygote; Humans; Infant; Male; Molecular Sequence Data; Muscle Weakness; Pedigree; Rhabdomyolysis; White People

On Robust Association Testing for Quantitative Traits and Rare Variants. - Wei, Peng; Cao, Ying; Zhang, Yiwei; Xu, Zhiyuan; Kwak, Il-Youp; Eric Boerwinkle; Pan, Wei (G3 (Bethesda), 2016)
With the advance of sequencing technologies, it has become a routine practice to test for association between a quantitative trait and a set of rare variants (RVs). While a number of RV association tests have been proposed, there is a dearth of studies on the robustness of RV association testing for nonnormal distributed traits, e.g., due to skewness, which is ubiquitous in cohort studies. By extensive simulations, we demonstrate that commonly used RV tests, including sequence kernel association test (SKAT) and optimal unified SKAT (SKAT-O), are not robust to heavy-tailed or right-skewed trait distributions with inflated type I error rates; in contrast, the adaptive sum of powered score (aSPU) test is much more robust. Here we further propose a robust version of the aSPU test, called aSPUr. We conduct extensive simulations to evaluate the power of the tests, finding that for a larger number of RVs, aSPU is often more powerful than SKAT and SKAT-O, owing to its high data-adaptivity. We also compare different tests by conducting association analysis of triglyceride levels using the NHLBI ESP whole-exome sequencing data. The QQ plots for SKAT and SKAT-O were severely inflated (λ = 1.89 and 1.78, respectively), while those for aSPU and aSPUr behaved normally. Due to its relatively high robustness to outliers and high power of the aSPU test, we recommend its use complementary to SKAT and SKAT-O. If there is evidence of inflated type I error rate from the aSPU test, we would recommend the use of the more robust, but less powerful, aSPUr test.
Keywords: Algorithms; Computer Simulation; Exome; Genetic Association Studies; Genetic Variation; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Models, Genetic; Phenotype; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable

WGSA: an annotation pipeline for human genome sequencing studies. - Liu, Xiaoming; White, Simon; Peng, Bo; Johnson, Andrew D; Brody, Jennifer A; Li, Alexander H; Huang, Zhuoyi; Carroll, Andrew; Wei, Peng; Richard A Gibbs; Klein, Robert J; Eric Boerwinkle (J Med Genet, 2016)
Keywords: Cloud Computing; Genome, Human; Humans; Molecular Sequence Annotation; Sequence Analysis, DNA; Software

Whole Exome Sequencing in Atrial Fibrillation. - Lubitz, Steven A; Brody, Jennifer A; Bihlmeyer, Nathan A; Roselli, Carolina; Weng, Lu-Chen; Christophersen, Ingrid E; Alonso, Alvaro; Eric Boerwinkle; Richard A Gibbs; Bis, Joshua C; Cupples, L Adrienne; Mohler, Peter J; et al. (PLoS Genet, 2016)
Atrial fibrillation (AF) is a morbid and heritable arrhythmia. Over 35 genes have been reported to underlie AF, most of which were described in small candidate gene association studies. Replication remains lacking for most, and therefore the contribution of coding variation to AF susceptibility remains poorly understood. We examined whole exome sequencing data in a large community-based sample of 1,734 individuals with and 9,423 without AF from the Framingham Heart Study, Cardiovascular Health Study, Atherosclerosis Risk in Communities Study, and NHLBI-GO Exome Sequencing Project and meta-analyzed the results. We also examined whether genetic variation was enriched in suspected AF genes (N = 37) in AF cases versus controls. The mean age ranged from 59 to 73 years; 8,656 (78%) were of European ancestry. None of the 99,404 common variants evaluated was significantly associated after adjusting for multiple testing. Among the most significantly associated variants was a common (allele frequency = 86%) missense variant in SYNPO2L (rs3812629, p.Pro707Leu, [odds ratio 1.27, 95% confidence interval 1.13-1.43, P = 6.6x10-5]) which lies at a known AF susceptibility locus and is in linkage disequilibrium with a top marker from prior analyses at the locus. We did not observe significant associations between rare variants and AF in gene-based tests. Individuals with AF did not display any statistically significant enrichment for common or rare coding variation in previously implicated AF genes. In conclusion, we did not observe associations between coding genetic variants and AF, suggesting that large-effect coding variation is not the predominant mechanism underlying AF. A coding variant in SYNPO2L requires further evaluation to determine whether it is causally related to AF. Efforts to identify biologically meaningful coding variation underlying AF may require large sample sizes or populations enriched for large genetic effects.
Keywords: Aged; Atrial Fibrillation; Exome; Female; Gene Frequency; Genetic Association Studies; Genetic Predisposition to Disease; High-Throughput Nucleotide Sequencing; Humans; Male; Microfilament Proteins; Middle Aged; Polymorphism, Single Nucleotide

Whole genome sequence analysis of serum amino acid levels. - Yu, Bing; de Vries, Paul S; Ginger A Metcalf; Wang, Zhe; Feofanova, Elena V; Liu, Xiaoming; Donna M Muzny; Wagenknecht, Lynne E; Richard A Gibbs; Morrison, Alanna C; Eric Boerwinkle (Genome Biol, 2016)
BACKGROUND: Blood levels of amino acids are important biomarkers of disease and are influenced by synthesis, protein degradation, and gene-environment interactions. Whole genome sequence analysis of amino acid levels may establish a paradigm for analyzing quantitative risk factors. RESULTS: In a discovery cohort of 1872 African Americans and a replication cohort of 1552 European Americans we sequenced exons and whole genomes and measured serum levels of 70 amino acids. Rare and low-frequency variants (minor allele frequency ≤5%) were analyzed by three types of aggregating motifs defined by gene exons, regulatory regions, or genome-wide sliding windows. Common variants (minor allele frequency >5%) were analyzed individually. Over all four analysis strategies, 14 gene-amino acid associations were identified and replicated. The 14 loci accounted for an average of 1.8% of the variance in amino acid levels, which ranged from 0.4 to 9.7%. Among the identified locus-amino acid pairs, four are novel and six have been reported to underlie known Mendelian conditions. These results suggest that there may be substantial genetic effects on amino acid levels in the general population that may underlie inborn errors of metabolism. We also identify a predicted promoter variant in AGA (the gene that encodes aspartylglucosaminidase) that is significantly associated with asparagine levels, with an effect that is independent of any observed coding variants. CONCLUSIONS: These data provide insights into genetic influences on circulating amino acid levels by integrating -omic technologies in a multi-ethnic population. The results also help establish a paradigm for whole genome sequence analysis of quantitative traits.
Keywords: Adult; Aged; Amino Acids; Biomarkers; Exons; Female; Genome, Human; Genome-Wide Association Study; High-Throughput Nucleotide Sequencing; Humans; Male; Middle Aged; Nucleotide Motifs; Polymorphism, Single Nucleotide; Population Surveillance; Regulatory Sequences, Nucleic Acid

Whole-Exome Sequencing Identifies Loci Associated with Blood Cell Traits and Reveals a Role for Alternative GFI1B Splice Variants in Human Hematopoiesis. - Polfus, Linda M; Khajuria, Rajiv K; Schick, Ursula M; Pankratz, Nathan; Pazoki, Raha; Brody, Jennifer A; Chen, Ming-Huei; Auer, Paul L; Floyd, James S; Huang, Jie; Lange, Leslie; van Rooij, Frank J A; et al. (Am J Hum Genet, 2016)
Circulating blood cell counts and indices are important indicators of hematopoietic function and a number of clinical parameters, such as blood oxygen-carrying capacity, inflammation, and hemostasis. By performing whole-exome sequence association analyses of hematologic quantitative traits in 15,459 community-dwelling individuals, followed by in silico replication in up to 52,024 independent samples, we identified two previously undescribed coding variants associated with lower platelet count: a common missense variant in CPS1 (rs1047891, MAF = 0.33, discovery + replication p = 6.38 × 10(-10)) and a rare synonymous variant in GFI1B (rs150813342, MAF = 0.009, discovery + replication p = 1.79 × 10(-27)). By performing CRISPR/Cas9 genome editing in hematopoietic cell lines and follow-up targeted knockdown experiments in primary human hematopoietic stem and progenitor cells, we demonstrate an alternative splicing mechanism by which the GFI1B rs150813342 variant suppresses formation of a GFI1B isoform that preferentially promotes megakaryocyte differentiation and platelet production. These results demonstrate how unbiased studies of natural variation in blood cell traits can provide insight into the regulation of human hematopoiesis.
Keywords: Alternative Splicing; Blood Platelets; CRISPR-Cas Systems; DNA Mutational Analysis; Exome; Gene Editing; Genetic Loci; Hematopoiesis; Hematopoietic Stem Cells; Humans; Megakaryocytes; Platelet Count; Proto-Oncogene Proteins; Repressor Proteins

Whole-Exome Sequencing in Familial Parkinson Disease. - Farlow, Janice L; Robak, Laurie A; Hetrick, Kurt; Bowling, Kevin; Eric Boerwinkle; Coban-Akdemir, Zeynep H; Gambin, Tomasz; Richard A Gibbs; Gu, Shen; Jain, Preti; Jankovic, Joseph; Jhangiani, Shalini; et al. (JAMA Neurol, 2016)
IMPORTANCE: Parkinson disease (PD) is a progressive neurodegenerative disease for which susceptibility is linked to genetic and environmental risk factors. OBJECTIVE: To identify genetic variants contributing to disease risk in familial PD. DESIGN, SETTING, AND PARTICIPANTS: A 2-stage study design that included a discovery cohort of families with PD and a replication cohort of familial probands was used. In the discovery cohort, rare exonic variants that segregated in multiple affected individuals in a family and were predicted to be conserved or damaging were retained. Genes with retained variants were prioritized if expressed in the brain and located within PD-relevant pathways. Genes in which prioritized variants were observed in at least 4 families were selected as candidate genes for replication in the replication cohort. The setting was among individuals with familial PD enrolled from academic movement disorder specialty clinics across the United States. All participants had a family history of PD. MAIN OUTCOMES AND MEASURES: Identification of genes containing rare, likely deleterious, genetic variants in individuals with familial PD using a 2-stage exome sequencing study design. RESULTS: The 93 individuals from 32 families in the discovery cohort (49.5% [46 of 93] female) had a mean (SD) age at onset of 61.8 (10.0) years. The 49 individuals with familial PD in the replication cohort (32.6% [16 of 49] female) had a mean (SD) age at onset of 50.1 (15.7) years. Discovery cohort recruitment dates were 1999 to 2009, and replication cohort recruitment dates were 2003 to 2014. Data analysis dates were 2011 to 2015. Three genes containing a total of 13 rare and potentially damaging variants were prioritized in the discovery cohort. Two of these genes (TNK2 and TNR) also had rare variants that were predicted to be damaging in the replication cohort. All 9 variants identified in the 2 replicated genes in 12 families across the discovery and replication cohorts were confirmed via Sanger sequencing. CONCLUSIONS AND RELEVANCE: TNK2 and TNR harbored rare, likely deleterious, variants in individuals having familial PD, with similar findings in an independent cohort. To our knowledge, these genes have not been previously associated with PD, although they have been linked to critical neuronal functions. Further studies are required to confirm a potential role for these genes in the pathogenesis of PD.
Keywords: Adult; Aged; Cohort Studies; Exome; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Middle Aged; Parkinsonian Disorders; Protein-Tyrosine Kinases; Sequence Analysis, DNA; Tenascin

Whole-exome sequencing reveals an inherited R566X mutation of the epithelial sodium channel β-subunit in a case of early-onset phenotype of Liddle syndrome. - Polfus, Linda M; Eric Boerwinkle; Richard A Gibbs; Ginger A Metcalf; Donna M Muzny; Veeraraghavan, Narayanan; Grove, Megan; Shete, Sanjay; Wallace, Stephanie; Milewicz, Dianna; Hanchard, Neil; Lupski, James R; et al. (Cold Spring Harb Mol Case Stud, 2016)
To comprehensively evaluate a European-American child with severe hypertension, whole-exome sequencing (WES) was performed on the child and parents, which identified causal variation of the proband's early-onset disease. The proband's hypertension was resistant to treatment, requiring a multiple drug regimen including amiloride, spironolactone, and hydrochlorothiazide. We suspected a monogenic form of hypertension because of the persistent hypokalemia with low plasma levels of renin and aldosterone. To address this, we focused on rare functional variants and indels, and performed gene-based tests incorporating linkage scores and allele frequency and filtered on deleterious functional mutations. Drawing upon clinical presentation, 27 genes were selected evidenced to cause monogenic hypertension and matched to the gene-based results. This resulted in the identification of a stop-gain mutation in an epithelial sodium channel (ENaC), , an established Liddle syndrome gene, shared by the child and her father. Interestingly, the father also harbored a missense mutation (p.Trp552Arg) in the α-subunit of the ENaC trimer, , possibly pointing to pseudohypoaldosteronism type I. This case is unique in that we present the early-onset disease and treatment response caused by a canonical stop-gain mutation (p.Arg566*) as well as ENaC digenic hits in the father, emphasizing the utility of WES informing precision medicine.
Keywords: Adult; Aldosterone; Alleles; Amiloride; Child, Preschool; Epithelial Sodium Channels; Exome; Exome Sequencing; Female; Gene Frequency; Germ-Line Mutation; Humans; Hydrochlorothiazide; Hypertension; Hypokalemia; Liddle Syndrome; Male; Mutation; Mutation, Missense; Renin

The amyloidogenic V122I transthyretin variant in elderly black Americans. - Quarta, C Cristina; Buxbaum, Joel N; Shah, Amil M; Falk, Rodney H; Claggett, Brian; Kitzman, Dalane W; Mosley, Thomas H; Butler, Kenneth R; Eric Boerwinkle; Solomon, Scott D (N Engl J Med, 2015)
BACKGROUND: Approximately 4% of black Americans carry a valine-to-isoleucine substitution (V122I) in the transthyretin protein, which has been associated with late-onset restrictive amyloid cardiomyopathy and increased risks of death and heart failure. METHODS: We determined genotype status for the transthyretin gene (TTR) in 3856 black participants in the Atherosclerosis Risk in Communities study and assessed clinical profiles, mortality, and the risk of incident heart failure in V122I TTR variant carriers (124 participants [3%]) versus noncarriers (3732 participants). Cardiac structure and function and features suggestive of cardiac amyloidosis were assessed in participants who underwent echocardiography during visit 5 (2011 to 2013), when they were older than 65 years of age. RESULTS: After 21.5 years of follow-up, we did not detect a significant difference in mortality between carriers (41 deaths, 33%) and noncarriers (1382 deaths, 37%; age- and sex-stratified hazard ratio among carriers, 0.99; 95% confidence interval [CI], 0.73 to 1.36; P=0.97). The TTR variant was associated with an increased risk of incident heart failure (age- and sex-stratified hazard ratio, 1.47; 95% CI, 1.03 to 2.10; P=0.04). On echocardiography at visit 5, carriers (46 participants) had worse systolic and diastolic function, as well as a higher level of N-terminal pro-brain natriuretic peptide, than noncarriers (1194 participants), although carriers had a low prevalence (7%) of overt manifestations of amyloid cardiomyopathy. CONCLUSIONS: We did not detect a significant difference in mortality between V122I TTR allele carriers and noncarriers, a finding that contrasts with prior observations; however, the risk of heart failure was increased among carriers. The prevalence of overt cardiac abnormalities among V122I TTR carriers was low. (Funded by the National Heart, Lung, and Blood Institute and others.).
Keywords: Aged; Amyloidosis; Black or African American; Cardiomyopathy, Restrictive; Cohort Studies; Echocardiography; Female; Follow-Up Studies; Genotype; Heart Failure; Heterozygote; Humans; Kaplan-Meier Estimate; Male; Middle Aged; Natriuretic Peptide, Brain; Peptide Fragments; Prealbumin

Analysis of loss-of-function variants and 20 risk factor phenotypes in 8,554 individuals identifies loci influencing chronic disease. - Li, Alexander H; Morrison, Alanna C; Kovar, Christie; Cupples, L Adrienne; Brody, Jennifer A; Polfus, Linda M; Yu, Bing; Ginger A Metcalf; Donna M Muzny; Veeraraghavan, Narayanan; Liu, Xiaoming; Lumley, Thomas; et al. (Nat Genet, 2015)
A typical human exome harbors dozens of loss-of-function (LOF) variants, which can lower disease risk factor levels and affect drug efficacy. We hypothesized that LOF variants are enriched in genes influencing risk factor levels and the onset of common chronic diseases, such as cardiovascular disease and diabetes. To test this hypothesis, we sequenced the exomes of 8,554 individuals and analyzed the effects of predicted LOF variants on 20 chronic disease risk factor phenotypes. Analysis of this sample as discovery and replication strata of equal size verified two relationships in well-studied genes (PCSK9 and APOC3) and identified eight new loci. Previously unknown relationships included elevated fasting glucose in carriers of heterozygous LOF variation in TXNDC5, which encodes a biomarker for type 1 diabetes progression, and apparent recessive effects of C1QTNF8 on serum magnesium levels. These data demonstrate the utility of functional-variant annotation within a large sample of deeply phenotyped individuals for gene discovery.
Keywords: Atherosclerosis; Chronic Disease; Exome; Gene Frequency; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genome, Human; Humans; Molecular Sequence Annotation; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Assessing structural variation in a personal genome-towards a human reference diploid genome. - English, Adam C; Salerno, William J; Hampton, Oliver A; Gonzaga-Jauregui, Claudia; Ambreth, Shruthi; Ritter, Deborah I; Beck, Christine R; Davis, Caleb F; Dahdouli, Mahmoud; Ma, Singer; Carroll, Andrew; Veeraraghavan, Narayanan; et al. (BMC Genomics, 2015)
BACKGROUND: Characterizing large genomic variants is essential to expanding the research and clinical applications of genome sequencing. While multiple data types and methods are available to detect these structural variants (SVs), they remain less characterized than smaller variants because of SV diversity, complexity, and size. These challenges are exacerbated by the experimental and computational demands of SV analysis. Here, we characterize the SV content of a personal genome with Parliament, a publicly available consensus SV-calling infrastructure that merges multiple data types and SV detection methods. RESULTS: We demonstrate Parliament's efficacy via integrated analyses of data from whole-genome array comparative genomic hybridization, short-read next-generation sequencing, long-read (Pacific BioSciences RSII), long-insert (Illumina Nextera), and whole-genome architecture (BioNano Irys) data from the personal genome of a single subject (HS1011). From this genome, Parliament identified 31,007 genomic loci between 100 bp and 1 Mbp that are inconsistent with the hg19 reference assembly. Of these loci, 9,777 are supported as putative SVs by hybrid local assembly, long-read PacBio data, or multi-source heuristics. These SVs span 59 Mbp of the reference genome (1.8%) and include 3,801 events identified only with long-read data. The HS1011 data and complete Parliament infrastructure, including a BAM-to-SV workflow, are available on the cloud-based service DNAnexus. CONCLUSIONS: HS1011 SV analysis reveals the limits and advantages of multiple sequencing technologies, specifically the impact of long-read SV discovery. With the full Parliament infrastructure, the HS1011 data constitute a public resource for novel SV discovery, software calibration, and personal genome structural variation analysis.
Keywords: Computational Biology; Databases, Genetic; Diploidy; Genome, Human; Genomic Structural Variation; Humans; Sequence Analysis, DNA; Software

Association of exome sequences with plasma C-reactive protein levels in >9000 participants. - Schick, Ursula M; Auer, Paul L; Bis, Joshua C; Lin, Honghuang; Wei, Peng; Pankratz, Nathan; Lange, Leslie A; Brody, Jennifer; Stitziel, Nathan O; Kim, Daniel S; Carlson, Christopher S; Fornage, Myriam; et al. (Hum Mol Genet, 2015)
C-reactive protein (CRP) concentration is a heritable systemic marker of inflammation that is associated with cardiovascular disease risk. Genome-wide association studies have identified CRP-associated common variants associated in ∼25 genes. Our aims were to apply exome sequencing to (1) assess whether the candidate loci contain rare coding variants associated with CRP levels and (2) perform an exome-wide search for rare variants in novel genes associated with CRP levels. We exome-sequenced 6050 European-Americans (EAs) and 3109 African-Americans (AAs) from the NHLBI-ESP and the CHARGE consortia, and performed association tests of sequence data with measured CRP levels. In single-variant tests across candidate loci, a novel rare (minor allele frequency = 0.16%) CRP-coding variant (rs77832441-A; p.Thr59Met) was associated with 53% lower mean CRP levels (P = 2.9 × 10(-6)). We replicated the association of rs77832441 in an exome array analysis of 11 414 EAs (P = 3.0 × 10(-15)). Despite a strong effect on CRP levels, rs77832441 was not associated with inflammation-related phenotypes including coronary heart disease. We also found evidence for an AA-specific association of APOE-ε2 rs7214 with higher CRP levels. At the exome-wide significance level (P < 5.0 × 10(-8)), we confirmed associations for reported common variants of HNF1A, CRP, IL6R and TOMM40-APOE. In gene-based tests, a burden of rare/lower frequency variation in CRP in EAs (P ≤ 6.8 × 10(-4)) and in retinoic acid receptor-related orphan receptor α (RORA) in AAs (P = 1.7 × 10(-3)) were associated with CRP levels at the candidate gene level (P < 2.0 × 10(-3)). This inquiry did not elucidate novel genes, but instead demonstrated that variants distributed across the allele frequency spectrum within candidate genes contribute to CRP levels.
Keywords: Adult; Black or African American; C-Reactive Protein; Cardiovascular Diseases; Cohort Studies; Exome; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Hepatocyte Nuclear Factor 1-alpha; Humans; Male; Plasma; Polymorphism, Single Nucleotide; Receptors, Interleukin-6; Risk Factors; White People

Association of Rare Loss-Of-Function Alleles in HAL, Serum Histidine: Levels and Incident Coronary Heart Disease. - Yu, Bing; Li, Alexander H; Donna M Muzny; Veeraraghavan, Narayanan; de Vries, Paul S; Bis, Joshua C; Musani, Solomon K; Alexander, Danny; Morrison, Alanna C; Franco, Oscar H; Uitterlinden, Andre; Hofman, Albert; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Histidine is a semiessential amino acid with antioxidant and anti-inflammatory properties. Few data are available on the associations between genetic variants, histidine levels, and incident coronary heart disease (CHD) in a population-based sample. METHODS AND RESULTS: By conducting whole exome sequencing on 1152 African Americans in the Atherosclerosis Risk in Communities (ARIC) study and focusing on loss-of-function (LoF) variants, we identified 3 novel rare LoF variants in HAL, a gene that encodes histidine ammonia-lyase in the first step of histidine catabolism. These LoF variants had large effects on blood histidine levels (β=0.26; P=1.2×10(-13)). The positive association with histidine levels was replicated by genotyping an independent sample of 718 ARIC African Americans (minor allele frequency=1%; P=1.2×10(-4)). In addition, high blood histidine levels were associated with reduced risk of developing incident CHD with an average of 21.5 years of follow-up among African Americans (hazard ratio=0.18; P=1.9×10(-4)). This finding was validated in an independent sample of European Americans from the Framingham Heart Study (FHS) Offspring Cohort. However, LoF variants in HAL were not directly significantly associated with incident CHD after meta-analyzing results from the CHARGE Consortium. CONCLUSIONS: Three LoF mutations in HAL were associated with increased histidine levels, which in turn were shown to be inversely related to the risk of CHD among both African Americans and European Americans. Future investigations on the association between HAL gene variation and CHD are warranted.
Keywords: Adult; Alleles; Black or African American; Coronary Disease; Female; Histidine; Histidine Ammonia-Lyase; Humans; Male; Mutation; White People

Comparison and integration of deleteriousness prediction methods for nonsynonymous SNVs in whole exome sequencing studies. - Dong, Chengliang; Wei, Peng; Jian, Xueqiu; Richard A Gibbs; Eric Boerwinkle; Wang, Kai; Liu, Xiaoming (Hum Mol Genet, 2015)
Accurate deleteriousness prediction for nonsynonymous variants is crucial for distinguishing pathogenic mutations from background polymorphisms in whole exome sequencing (WES) studies. Although many deleteriousness prediction methods have been developed, their prediction results are sometimes inconsistent with each other and their relative merits are still unclear in practical applications. To address these issues, we comprehensively evaluated the predictive performance of 18 current deleteriousness-scoring methods, including 11 function prediction scores (PolyPhen-2, SIFT, MutationTaster, Mutation Assessor, FATHMM, LRT, PANTHER, PhD-SNP, SNAP, SNPs&GO and MutPred), 3 conservation scores (GERP++, SiPhy and PhyloP) and 4 ensemble scores (CADD, PON-P, KGGSeq and CONDEL). We found that FATHMM and KGGSeq had the highest discriminative power among independent scores and ensemble scores, respectively. Moreover, to ensure unbiased performance evaluation of these prediction scores, we manually collected three distinct testing datasets, on which no current prediction scores were tuned. In addition, we developed two new ensemble scores that integrate nine independent scores and allele frequency. Our scores achieved the highest discriminative power compared with all the deleteriousness prediction scores tested and showed low false-positive prediction rate for benign yet rare nonsynonymous variants, which demonstrated the value of combining information from multiple orthologous approaches. Finally, to facilitate variant prioritization in WES studies, we have pre-computed our ensemble scores for 87 347 044 possible variants in the whole-exome and made them publicly available through the ANNOVAR software and the dbNSFP database.
Keywords: Computational Biology; Exome; Genome, Human; Humans; Polymorphism, Single Nucleotide; Software

A comprehensive 1,000 Genomes-based genome-wide association meta-analysis of coronary artery disease. - Nikpay, Majid; Goel, Anuj; Won, Hong-Hee; Hall, Leanne M; Willenborg, Christina; Kanoni, Stavroula; Saleheen, Danish; Kyriakou, Theodosios; Nelson, Christopher P; Hopewell, Jemma C; Webb, Thomas R; Zeng, Lingyao; et al. (Nat Genet, 2015)
Existing knowledge of genetic variants affecting risk of coronary artery disease (CAD) is largely based on genome-wide association study (GWAS) analysis of common SNPs. Leveraging phased haplotypes from the 1000 Genomes Project, we report a GWAS meta-analysis of ∼185,000 CAD cases and controls, interrogating 6.7 million common (minor allele frequency (MAF) > 0.05) and 2.7 million low-frequency (0.005 < MAF < 0.05) variants. In addition to confirming most known CAD-associated loci, we identified ten new loci (eight additive and two recessive) that contain candidate causal genes newly implicating biological processes in vessel walls. We observed intralocus allelic heterogeneity but little evidence of low-frequency variants with larger effects and no evidence of synthetic association. Our analysis provides a comprehensive survey of the fine genetic architecture of CAD, showing that genetic susceptibility to this common disease is largely determined by common SNPs of small effect size.
Keywords: Coronary Artery Disease; Genome, Human; Genome-Wide Association Study; Humans; Phenotype

COPA mutations impair ER-Golgi transport and cause hereditary autoimmune-mediated lung disease and arthritis. - Watkin, Levi B; Jessen, Birthe; Wiszniewski, Wojciech; Vece, Timothy J; Jan, Max; Sha, Youbao; Thamsen, Maike; Santos-Cortez, Regie L P; Lee, Kwanghyuk; Gambin, Tomasz; Forbes, Lisa R; Law, Christopher S; et al. (Nat Genet, 2015)
Unbiased genetic studies have uncovered surprising molecular mechanisms in human cellular immunity and autoimmunity. We performed whole-exome sequencing and targeted sequencing in five families with an apparent mendelian syndrome of autoimmunity characterized by high-titer autoantibodies, inflammatory arthritis and interstitial lung disease. We identified four unique deleterious variants in the COPA gene (encoding coatomer subunit α) affecting the same functional domain. Hypothesizing that mutant COPA leads to defective intracellular transport via coat protein complex I (COPI), we show that COPA variants impair binding to proteins targeted for retrograde Golgi-to-ER transport. Additionally, expression of mutant COPA results in ER stress and the upregulation of cytokines priming for a T helper type 17 (TH17) response. Patient-derived CD4(+) T cells also demonstrate significant skewing toward a TH17 phenotype that is implicated in autoimmunity. Our findings uncover an unexpected molecular link between a vesicular transport protein and a syndrome of autoimmunity manifested by lung and joint disease.
Keywords: Amino Acid Sequence; Arthritis; Autoimmune Diseases; Child, Preschool; Coatomer Protein; Endoplasmic Reticulum; Endoplasmic Reticulum Stress; Female; Genetic Association Studies; Genetic Predisposition to Disease; Golgi Apparatus; HEK293 Cells; Humans; Infant; Lod Score; Lung Diseases, Interstitial; Male; Molecular Sequence Data; Pedigree; Protein Transport

Coronary heart disease and genetic variants with low phospholipase A2 activity. - Polfus, Linda M; Richard A Gibbs; Eric Boerwinkle (N Engl J Med, 2015)
Keywords: Aged; Black or African American; Coronary Disease; Exome; Female; Genetic Variation; Heterozygote; Humans; Male; Middle Aged; Mutation; Phospholipases A2; Risk Factors; White People

Epigenome-wide association study (EWAS) of BMI, BMI change and waist circumference in African American adults identifies multiple replicated loci. - Demerath, Ellen W; Guan, Weihua; Grove, Megan L; Aslibekyan, Stella; Mendelson, Michael; Zhou, Yi-Hui; Hedman, Åsa K; Sandling, Johanna K; Li, Li-An; Irvin, Marguerite R; Zhi, Degui; Deloukas, Panos; et al. (Hum Mol Genet, 2015)
Obesity is an important component of the pathophysiology of chronic diseases. Identifying epigenetic modifications associated with elevated adiposity, including DNA methylation variation, may point to genomic pathways that are dysregulated in numerous conditions. The Illumina 450K Bead Chip array was used to assay DNA methylation in leukocyte DNA obtained from 2097 African American adults in the Atherosclerosis Risk in Communities (ARIC) study. Mixed-effects regression models were used to test the association of methylation beta value with concurrent body mass index (BMI) and waist circumference (WC), and BMI change, adjusting for batch effects and potential confounders. Replication using whole-blood DNA from 2377 White adults in the Framingham Heart Study and CD4+ T cell DNA from 991 Whites in the Genetics of Lipid Lowering Drugs and Diet Network Study was followed by testing using adipose tissue DNA from 648 women in the Multiple Tissue Human Expression Resource cohort. Seventy-six BMI-related probes, 164 WC-related probes and 8 BMI change-related probes passed the threshold for significance in ARIC (P < 1 × 10(-7); Bonferroni), including probes in the recently reported HIF3A, CPT1A and ABCG1 regions. Replication using blood DNA was achieved for 37 BMI probes and 1 additional WC probe. Sixteen of these also replicated in adipose tissue, including 15 novel methylation findings near genes involved in lipid metabolism, immune response/cytokine signaling and other diverse pathways, including LGALS3BP, KDM2B, PBX1 and BBS2, among others. Adiposity traits are associated with DNA methylation at numerous CpG sites that replicate across studies despite variation in tissue type, ethnicity and analytic approaches.
Keywords: Aged; Atherosclerosis; Black or African American; Body Mass Index; DNA Methylation; Epigenesis, Genetic; Female; Genome-Wide Association Study; Humans; Lipid Metabolism; Male; Metabolic Networks and Pathways; Middle Aged; Obesity; Waist Circumference; White People

Exome Sequence Analysis Suggests that Genetic Burden Contributes to Phenotypic Variability and Complex Neuropathy. - Gonzaga-Jauregui, Claudia; Harel, Tamar; Gambin, Tomasz; Kousi, Maria; Griffin, Laurie B; Francescatto, Ludmila; Ozes, Burcak; Karaca, Ender; Jhangiani, Shalini N; Bainbridge, Matthew N; Lawson, Kim S; Pehlivan, Davut; et al. (Cell Rep, 2015)
Charcot-Marie-Tooth (CMT) disease is a clinically and genetically heterogeneous distal symmetric polyneuropathy. Whole-exome sequencing (WES) of 40 individuals from 37 unrelated families with CMT-like peripheral neuropathy refractory to molecular diagnosis identified apparent causal mutations in ∼ 45% (17/37) of families. Three candidate disease genes are proposed, supported by a combination of genetic and in vivo studies. Aggregate analysis of mutation data revealed a significantly increased number of rare variants across 58 neuropathy-associated genes in subjects versus controls, confirmed in a second ethnically discrete neuropathy cohort, suggesting that mutation burden potentially contributes to phenotypic variability. Neuropathy genes shown to have highly penetrant Mendelizing variants (HPMVs) and implicated by burden in families were shown to interact genetically in a zebrafish assay exacerbating the phenotype established by the suppression of single genes. Our findings suggest that the combinatorial effect of rare variants contributes to disease burden and variable expressivity.
Keywords: Animals; Charcot-Marie-Tooth Disease; Exome; Female; Genetic Load; Genetic Variation; HSP40 Heat-Shock Proteins; Humans; Male; Mutation; Myelin P2 Protein; Pedigree; Penetrance; Peripheral Nervous System Diseases; Phenotype; Serine C-Palmitoyltransferase; Suppression, Genetic; Zebrafish

Exome sequencing identifies rare LDLR and APOA5 alleles conferring risk for myocardial infarction. - Do, Ron; Stitziel, Nathan O; Won, Hong-Hee; Jørgensen, Anders Berg; Duga, Stefano; Angelica Merlini, Pier; Kiezun, Adam; Farrall, Martin; Goel, Anuj; Zuk, Or; Guella, Illaria; Asselta, Rosanna; et al. (Nature, 2015)
Myocardial infarction (MI), a leading cause of death around the world, displays a complex pattern of inheritance. When MI occurs early in life, genetic inheritance is a major component to risk. Previously, rare mutations in low-density lipoprotein (LDL) genes have been shown to contribute to MI risk in individual families, whereas common variants at more than 45 loci have been associated with MI risk in the population. Here we evaluate how rare mutations contribute to early-onset MI risk in the population. We sequenced the protein-coding regions of 9,793 genomes from patients with MI at an early age (≤50 years in males and ≤60 years in females) along with MI-free controls. We identified two genes in which rare coding-sequence mutations were more frequent in MI cases versus controls at exome-wide significance. At low-density lipoprotein receptor (LDLR), carriers of rare non-synonymous mutations were at 4.2-fold increased risk for MI; carriers of null alleles at LDLR were at even higher risk (13-fold difference). Approximately 2% of early MI cases harbour a rare, damaging mutation in LDLR; this estimate is similar to one made more than 40 years ago using an analysis of total cholesterol. Among controls, about 1 in 217 carried an LDLR coding-sequence mutation and had plasma LDL cholesterol > 190 mg dl(-1). At apolipoprotein A-V (APOA5), carriers of rare non-synonymous mutations were at 2.2-fold increased risk for MI. When compared with non-carriers, LDLR mutation carriers had higher plasma LDL cholesterol, whereas APOA5 mutation carriers had higher plasma triglycerides. Recent evidence has connected MI risk with coding-sequence mutations at two genes functionally related to APOA5, namely lipoprotein lipase and apolipoprotein C-III (refs 18, 19). Combined, these observations suggest that, as well as LDL cholesterol, disordered metabolism of triglyceride-rich lipoproteins contributes to MI risk.
Keywords: Age Factors; Age of Onset; Alleles; Apolipoprotein A-V; Apolipoproteins A; Case-Control Studies; Cholesterol, LDL; Coronary Artery Disease; Exome; Female; Genetic Predisposition to Disease; Genetics, Population; Heterozygote; Humans; Male; Middle Aged; Mutation; Myocardial Infarction; National Heart, Lung, and Blood Institute (U.S.); Receptors, LDL; Triglycerides; United States

Factors associated with blood lead concentrations of children in Jamaica. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Dickerson, Aisha S; Loveland, Katherine A; Ardjomand-Hessabi, Manouchehr; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Eric Boerwinkle (J Environ Sci Health A Tox Hazard Subst Environ Eng, 2015)
Lead is a heavy metal known to be detrimental to neurologic, physiologic, and behavioral health of children. Previous studies from Jamaica reported that mean lead levels in soil are four times that of lead levels in some other parts of the world. Other studies detected lead levels in fruits and root vegetables, which were grown in areas with lead contaminated soil. In this study, we investigate environmental factors associated with blood lead concentrations in Jamaican children. The participants in this study comprised 125 typically developing (TD) children (ages 2-8 years) who served as controls in an age- and sex-matched case-control study that enrolled children from 2009-2012 in Jamaica. We administered a questionnaire to assess demographic and socioeconomic information as well as potential exposures to lead through food. Using General Linear Models (GLMs), we identified factors associated with blood lead concentrations in Jamaican children. The geometric mean blood lead concentration (GMBLC) in the sample of children in this study was 2.80 μg dL(-1). In univariable GLM analyses, GMBLC was higher for children whose parents did not have education beyond high school compared to those whose parents had attained this level (3.00 μg dL(-1) vs. 2.31 μg dL(-1); P = 0.05), children living near a high traffic road compared to those who did not (3.43 μg dL(-1) vs. 2.52 μg dL(-1); P < 0.01), and children who reported eating ackee compared to those who did not eat this fruit (2.89 μg dL(-1) vs. 1.65 μg dL(-1); P < 0.05). In multivariable analysis, living near a high traffic road was identified as an independent risk factor for higher adjusted GMBLC (3.05 μg dL(-1) vs. 2.19 μg dL(-1); P = 0.01). While our findings indicate that GMBLC in Jamaican children has dropped by at least 62% during the past two decades, children living in Jamaica still have GMBLC that is twice that of children in more developed countries. In addition, we have identified significant risk factors for higher blood lead concentrations in Jamaican children. We believe increasing awareness among parents regarding these risk factors could potentially lead to a lower level of lead exposure in Jamaican children.
Keywords: Case-Control Studies; Child; Child, Preschool; Environmental Exposure; Environmental Pollutants; Female; Humans; Jamaica; Lead; Lead Poisoning; Male; Risk Factors; Socioeconomic Factors

FBN1 contributing to familial congenital diaphragmatic hernia. - Beck, Tyler F; Campeau, Philippe M; Jhangiani, Shalini N; Gambin, Tomasz; Li, Alexander H; Abo-Zahrah, Reem; Jordan, Valerie K; Hernandez-Garcia, Andres; Wiszniewski, Wojciech K; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; et al. (Am J Med Genet A, 2015)
Congenital diaphragmatic hernia (CDH) is a relatively common, life--threatening birth defect. We present a family with recurrent CDH--paraesophageal and central--for whom exome sequencing (ES) revealed a frameshift mutation (c.4969_4970insA, p.Ile1657Asnfs*30) in the fibrillin 1 gene (FBN1) that causes Marfan syndrome. A diagnosis of Marfan syndrome had not been considered previously in this family. However, a review of the literature demonstrated that FBN1 mutations have an unusual pattern of CDH in which paraesophageal hernias are particularly common. Subsequent clinical evaluations revealed evidence for ectopia lentis in affected family members supporting a clinical diagnosis of Marfan syndrome. Since only two other cases of familial CDH have been described in association with FBN1 mutations, we investigated an oligogenic hypothesis by examining ES data for deleterious sequence changes in other CDH-related genes. This search revealed putatively deleterious sequence changes in four other genes that have been shown to cause diaphragm defects in humans and/or mice--FREM1, DES, PAX3 and MET. It is unclear whether these changes, alone or in aggregate, are contributing to the development of CDH in this family. However, their individual contribution is likely to be small compared to that of the frameshift mutation in FBN1. We conclude that ES can be used to identify both major and minor genetic factors that may contribute to CDH. These results also suggest that ES should be considered in the diagnostic evaluation of individuals and families with CDH, particularly when other diagnostic modalities have failed to reveal a molecular etiology.
Keywords: Adult; Child, Preschool; DNA Mutational Analysis; Exome; Female; Fibrillin-1; Fibrillins; Frameshift Mutation; Genetic Association Studies; Hernias, Diaphragmatic, Congenital; Humans; Male; Marfan Syndrome; Microfilament Proteins; Pedigree

Fine mapping the region reveals a common intronic insertion associated to HDL-C. - van Leeuwen, Elisabeth M; Huffman, Jennifer E; Bis, Joshua C; Isaacs, Aaron; Mulder, Monique; Aniko Sabo; Smith, Albert V; Demissie, Serkalem; Manichaikul, Ani; Brody, Jennifer A; Feitosa, Mary F; Duan, Qing; et al. (NPJ Aging Mech Dis, 2015)
BACKGROUND: Individuals with exceptional longevity and their offspring have significantly larger high-density lipoprotein concentrations (HDL-C) particle sizes due to the increased homozygosity for the I405V variant in the cholesteryl ester transfer protein ( gene. In this study, we investigate the association of and HDL-C further to identify novel, independent variants associated with HDL-C in humans. METHODS: We performed a meta-analysis of HDL-C within the region using 59,432 individuals imputed with 1000 Genomes data. We performed replication in an independent sample of 47,866 individuals and validation was done by Sanger sequencing. RESULTS: The meta-analysis of HDL-C within the region identified five independent variants, including an exonic variant and a common intronic insertion. We replicated these 5 variants significantly in an independent sample of 47,866 individuals. Sanger sequencing of the insertion within a single family confirmed segregation of this variant. The strongest reported association between HDL-C and variants, was rs3764261; however, after conditioning on the five novel variants we identified the support for rs3764261 was highly reduced (=3.179 mg/dl ( value=5.25×10), =0.859 mg/dl ( value=9.51×10)), and this finding suggests that these five novel variants may partly explain the association of with HDL-C. Indeed, three of the five novel variants (rs34065661, rs5817082, rs7499892) are independent of rs3764261. CONCLUSIONS: The causal variants in that account for the association with HDL-C remain unknown. We used studies imputed to the 1000 Genomes reference panel for fine mapping of the region. We identified and validated five variants within this region that may partly account for the association of the known variant (rs3764261), as well as other sources of genetic contribution to HDL-C.

Genes that Affect Brain Structure and Function Identified by Rare Variant Analyses of Mendelian Neurologic Disease. - Karaca, Ender; Harel, Tamar; Pehlivan, Davut; Jhangiani, Shalini N; Gambin, Tomasz; Coban Akdemir, Zeynep; Gonzaga-Jauregui, Claudia; Erdin, Serkan; Bayram, Yavuz; Campbell, Ian M; Hunter, Jill V; Atik, Mehmed M; et al. (Neuron, 2015)
Development of the human nervous system involves complex interactions among fundamental cellular processes and requires a multitude of genes, many of which remain to be associated with human disease. We applied whole exome sequencing to 128 mostly consanguineous families with neurogenetic disorders that often included brain malformations. Rare variant analyses for both single nucleotide variant (SNV) and copy number variant (CNV) alleles allowed for identification of 45 novel variants in 43 known disease genes, 41 candidate genes, and CNVs in 10 families, with an overall potential molecular cause identified in >85% of families studied. Among the candidate genes identified, we found PRUNE, VARS, and DHX37 in multiple families and homozygous loss-of-function variants in AGBL2, SLC18A2, SMARCA1, UBQLN1, and CPLX1. Neuroimaging and in silico analysis of functional and expression proximity between candidate and known disease genes allowed for further understanding of genetic networks underlying specific types of brain malformations.
Keywords: Brain; Cohort Studies; Databases, Genetic; Female; Gene Regulatory Networks; Genetic Association Studies; Genetic Variation; Humans; Male; Mendelian Randomization Analysis; Nervous System Diseases; Pedigree

A genetic association study of activated partial thromboplastin time in European Americans and African Americans: the ARIC Study. - Weng, Lu-Chen; Cushman, Mary; Pankow, James S; Basu, Saonli; Eric Boerwinkle; Folsom, Aaron R; Tang, Weihong (Hum Mol Genet, 2015)
Reduced activated partial thromboplastin time (aPTT) is a risk marker for incident and recurrent venous thromboembolism (VTE). Genetic factors influencing aPTT are not well understood, especially in populations of non-European ancestry. The present study aimed to identify aPTT-related gene variants in both European Americans (EAs) and African Americans (AAs). We conducted a genetic association study for aPTT in 9719 EAs and 2799 AAs from the Atherosclerosis Risk in Communities (ARIC) study. Using the Candidate Gene Association Resource (CARe) consortium candidate gene array, the analyses were based on ∼50 000 SNPs in ∼2000 candidate genes. In EAs, the analyses identified a new independent association for aPTT in F5 (rs2239852, P-value = 1.9 × 10(-8)), which clusters with a coding variant rs6030 (P-value = 7.8 × 10(-7)). The remaining significant signals were located on F5, HRG, KNG1, F11, F12 and ABO and have been previously reported in EA populations. In AAs, significant signals were identified in KNG1, HRG, F12, ABO and VWF, with the leading variants in KNG1, HRG and F12 being the same as in the EAs; the significant variant in VWF (rs2229446, P-value = 1.2 × 10(-6)) was specific to the AA sample (minor allele frequency = 19% in AAs and 0.2% in EAs) and has not been previously reported. This is the first study to report aPTT-related genetic variants in AAs. Our findings in AAs demonstrate transferability of previously reported associations with KNG1, HRG and F12 in EAs. We also identified new associations at F5 in EAs and VWF in AAs that have not been previously reported for aPTT.
Keywords: Aged; Atherosclerosis; Black or African American; Female; Genetic Association Studies; Genome-Wide Association Study; Humans; Kininogens; Male; Middle Aged; Neural Cell Adhesion Molecule L1; Partial Thromboplastin Time; Polymorphism, Single Nucleotide; Prospective Studies; Proteins; White People

The Genetic Basis of Mendelian Phenotypes: Discoveries, Challenges, and Opportunities. - Chong, Jessica X; Buckingham, Kati J; Jhangiani, Shalini N; Boehm, Corinne; Sobreira, Nara; Smith, Joshua D; Harrell, Tanya M; McMillin, Margaret J; Wiszniewski, Wojciech; Gambin, Tomasz; Coban Akdemir, Zeynep H; Doheny, Kimberly; et al. (Am J Hum Genet, 2015)
Discovering the genetic basis of a Mendelian phenotype establishes a causal link between genotype and phenotype, making possible carrier and population screening and direct diagnosis. Such discoveries also contribute to our knowledge of gene function, gene regulation, development, and biological mechanisms that can be used for developing new therapeutics. As of February 2015, 2,937 genes underlying 4,163 Mendelian phenotypes have been discovered, but the genes underlying ∼50% (i.e., 3,152) of all known Mendelian phenotypes are still unknown, and many more Mendelian conditions have yet to be recognized. This is a formidable gap in biomedical knowledge. Accordingly, in December 2011, the NIH established the Centers for Mendelian Genomics (CMGs) to provide the collaborative framework and infrastructure necessary for undertaking large-scale whole-exome sequencing and discovery of the genetic variants responsible for Mendelian phenotypes. In partnership with 529 investigators from 261 institutions in 36 countries, the CMGs assessed 18,863 samples from 8,838 families representing 579 known and 470 novel Mendelian phenotypes as of January 2015. This collaborative effort has identified 956 genes, including 375 not previously associated with human health, that underlie a Mendelian phenotype. These results provide insight into study design and analytical strategies, identify novel mechanisms of disease, and reveal the extensive clinical variability of Mendelian phenotypes. Discovering the gene underlying every Mendelian phenotype will require tackling challenges such as worldwide ascertainment and phenotypic characterization of families affected by Mendelian conditions, improvement in sequencing and analytical techniques, and pervasive sharing of phenotypic and genomic data among researchers, clinicians, and families.
Keywords: Genetic Diseases, Inborn; Genetics, Medical; Humans; Phenotype; Proteins

Genetic contributions to variation in general cognitive function: a meta-analysis of genome-wide association studies in the CHARGE consortium (N=53949). - Davies, G; Armstrong, N; Bis, J C; Bressler, J; Chouraki, V; Giddaluru, S; Hofer, E; Ibrahim-Verbaas, C A; Kirin, M; Lahti, J; van der Lee, S J; Le Hellard, S; et al. (Mol Psychiatry, 2015)
General cognitive function is substantially heritable across the human life course from adolescence to old age. We investigated the genetic contribution to variation in this important, health- and well-being-related trait in middle-aged and older adults. We conducted a meta-analysis of genome-wide association studies of 31 cohorts (N=53,949) in which the participants had undertaken multiple, diverse cognitive tests. A general cognitive function phenotype was tested for, and created in each cohort by principal component analysis. We report 13 genome-wide significant single-nucleotide polymorphism (SNP) associations in three genomic regions, 6q16.1, 14q12 and 19q13.32 (best SNP and closest gene, respectively: rs10457441, P=3.93 × 10(-9), MIR2113; rs17522122, P=2.55 × 10(-8), AKAP6; rs10119, P=5.67 × 10(-9), APOE/TOMM40). We report one gene-based significant association with the HMGN1 gene located on chromosome 21 (P=1 × 10(-6)). These genes have previously been associated with neuropsychiatric phenotypes. Meta-analysis results are consistent with a polygenic model of inheritance. To estimate SNP-based heritability, the genome-wide complex trait analysis procedure was applied to two large cohorts, the Atherosclerosis Risk in Communities Study (N=6617) and the Health and Retirement Study (N=5976). The proportion of phenotypic variation accounted for by all genotyped common SNPs was 29% (s.e.=5%) and 28% (s.e.=7%), respectively. Using polygenic prediction analysis, ~1.2% of the variance in general cognitive function was predicted in the Generation Scotland cohort (N=5487; P=1.5 × 10(-17)). In hypothesis-driven tests, there was significant association between general cognitive function and four genes previously associated with Alzheimer's disease: TOMM40, APOE, ABCG1 and MEF2C.
Keywords: Aged; Aged, 80 and over; Atherosclerosis; Cognition; Cognition Disorders; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; HMGN1 Protein; Humans; Male; Middle Aged; Neuropsychological Tests; Phenotype; Polymorphism, Single Nucleotide; Scotland

Genetic fine mapping and genomic annotation defines causal mechanisms at type 2 diabetes susceptibility loci. - Gaulton, Kyle J; Ferreira, Teresa; Lee, Yeji; Raimondo, Anne; Mägi, Reedik; Reschen, Michael E; Mahajan, Anubha; Locke, Adam; Rayner, N William; Robertson, Neil; Scott, Robert A; Prokopenko, Inga; et al. (Nat Genet, 2015)
We performed fine mapping of 39 established type 2 diabetes (T2D) loci in 27,206 cases and 57,574 controls of European ancestry. We identified 49 distinct association signals at these loci, including five mapping in or near KCNQ1. 'Credible sets' of the variants most likely to drive each distinct signal mapped predominantly to noncoding sequence, implying that association with T2D is mediated through gene regulation. Credible set variants were enriched for overlap with FOXA2 chromatin immunoprecipitation binding sites in human islet and liver cells, including at MTNR1B, where fine mapping implicated rs10830963 as driving T2D association. We confirmed that the T2D risk allele for this SNP increases FOXA2-bound enhancer activity in islet- and liver-derived cells. We observed allele-specific differences in NEUROD1 binding in islet-derived cells, consistent with evidence that the T2D risk allele increases islet MTNR1B expression. Our study demonstrates how integration of genetic and genomic information can define molecular mechanisms through which variants underlying association signals exert their effects on disease.
Keywords: Binding Sites; Case-Control Studies; Chromatin Immunoprecipitation; Chromosome Mapping; Diabetes Mellitus, Type 2; Gene Expression Regulation; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Genomics; Hepatocyte Nuclear Factor 3-beta; Humans; Islets of Langerhans; Liver; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Receptor, Melatonin, MT2

Genetic overlap between diagnostic subtypes of ischemic stroke. - Holliday, Elizabeth G; Traylor, Matthew; Malik, Rainer; Bevan, Steve; Falcone, Guido; Hopewell, Jemma C; Cheng, Yu-Ching; Cotlarciuc, Ioana; Bis, Joshua C; Eric Boerwinkle; Boncoraglio, Giorgio B; Clarke, Robert; et al. (Stroke, 2015)
BACKGROUND AND PURPOSE: Despite moderate heritability, the phenotypic heterogeneity of ischemic stroke has hampered gene discovery, motivating analyses of diagnostic subtypes with reduced sample sizes. We assessed evidence for a shared genetic basis among the 3 major subtypes: large artery atherosclerosis (LAA), cardioembolism, and small vessel disease (SVD), to inform potential cross-subtype analyses. METHODS: Analyses used genome-wide summary data for 12 389 ischemic stroke cases (including 2167 LAA, 2405 cardioembolism, and 1854 SVD) and 62 004 controls from the Metastroke consortium. For 4561 cases and 7094 controls, individual-level genotype data were also available. Genetic correlations between subtypes were estimated using linear mixed models and polygenic profile scores. Meta-analysis of a combined LAA-SVD phenotype (4021 cases and 51 976 controls) was performed to identify shared risk alleles. RESULTS: High genetic correlation was identified between LAA and SVD using linear mixed models (rg=0.96, SE=0.47, P=9×10(-4)) and profile scores (rg=0.72; 95% confidence interval, 0.52-0.93). Between LAA and cardioembolism and SVD and cardioembolism, correlation was moderate using linear mixed models but not significantly different from zero for profile scoring. Joint meta-analysis of LAA and SVD identified strong association (P=1×10(-7)) for single nucleotide polymorphisms near the opioid receptor μ1 (OPRM1) gene. CONCLUSIONS: Our results suggest that LAA and SVD, which have been hitherto treated as genetically distinct, may share a substantial genetic component. Combined analyses of LAA and SVD may increase power to identify small-effect alleles influencing shared pathophysiological processes.
Keywords: Alleles; Atherosclerosis; Cerebral Small Vessel Diseases; Cohort Studies; Data Interpretation, Statistical; Embolism; Genome-Wide Association Study; Genotype; Humans; Ischemia; Linear Models; Meta-Analysis as Topic; Phenotype; Polymorphism, Single Nucleotide; Stroke

Global transcriptional disturbances underlie Cornelia de Lange syndrome and related phenotypes. - Bo Yuan; Pehlivan, Davut; Karaca, Ender; Patel, Nisha; Charng, Wu-Lin; Gambin, Tomasz; Gonzaga-Jauregui, Claudia; Sutton, V Reid; Yesil, Gozde; Bozdogan, Sevcan Tug; Tos, Tulay; Koparir, Asuman; et al. (J Clin Invest, 2015)
Cornelia de Lange syndrome (CdLS) is a genetically heterogeneous disorder that presents with extensive phenotypic variability, including facial dysmorphism, developmental delay/intellectual disability (DD/ID), abnormal extremities, and hirsutism. About 65% of patients harbor mutations in genes that encode subunits or regulators of the cohesin complex, including NIPBL, SMC1A, SMC3, RAD21, and HDAC8. Wiedemann-Steiner syndrome (WDSTS), which shares CdLS phenotypic features, is caused by mutations in lysine-specific methyltransferase 2A (KMT2A). Here, we performed whole-exome sequencing (WES) of 2 male siblings clinically diagnosed with WDSTS; this revealed a hemizygous, missense mutation in SMC1A that was predicted to be deleterious. Extensive clinical evaluation and WES of 32 Turkish patients clinically diagnosed with CdLS revealed the presence of a de novo heterozygous nonsense KMT2A mutation in 1 patient without characteristic WDSTS features. We also identified de novo heterozygous mutations in SMC3 or SMC1A that affected RNA splicing in 2 independent patients with combined CdLS and WDSTS features. Furthermore, in families from 2 separate world populations segregating an autosomal-recessive disorder with CdLS-like features, we identified homozygous mutations in TAF6, which encodes a core transcriptional regulatory pathway component. Together, our data, along with recent transcriptome studies, suggest that CdLS and related phenotypes may be "transcriptomopathies" rather than cohesinopathies.
Keywords: Adolescent; Adult; Cell Cycle Proteins; Child; Child, Preschool; Chondroitin Sulfate Proteoglycans; Chromosomal Proteins, Non-Histone; Codon, Nonsense; De Lange Syndrome; Exome; Exonucleases; Gene Expression Profiling; Gene Expression Regulation; Genome-Wide Association Study; Heterozygote; Histone Deacetylases; Histone-Lysine N-Methyltransferase; Humans; Infant; Male; Myeloid-Lymphoid Leukemia Protein; Phenotype; Proteins; Repressor Proteins; Transcriptome

Homozygous loss-of-function mutations in SOHLH1 in patients with nonsyndromic hypergonadotropic hypogonadism. - Bayram, Yavuz; Gulsuner, Suleyman; Guran, Tulay; Abaci, Ayhan; Yesil, Gozde; Gulsuner, Hilal Unal; Atay, Zeynep; Pierce, Sarah B; Gambin, Tomasz; Lee, Ming; Turan, Serap; Bober, Ece; et al. (J Clin Endocrinol Metab, 2015)
CONTEXT: Hypergonadotropic hypogonadism presents in females with delayed or arrested puberty, primary or secondary amenorrhea due to gonadal dysfunction, and is further characterized by elevated gonadotropins and low sex steroids. Chromosomal aberrations and various specific gene defects can lead to hypergonadotropic hypogonadism. Responsible genes include those with roles in gonadal development or maintenance, sex steroid synthesis, or end-organ resistance to gonadotropins. Identification of novel causative genes in this disorder will contribute to our understanding of the regulation of human reproductive function. OBJECTIVES: The aim of this study was to identify and report the gene responsible for autosomal-recessive hypergonadotropic hypogonadism in two unrelated families. DESIGN AND PARTICIPANTS: Clinical evaluation and whole-exome sequencing were performed in two pairs of sisters with nonsyndromic hypergonadotropic hypogonadism from two unrelated families. RESULTS: Exome sequencing analysis revealed two different truncating mutations in the same gene: SOHLH1 c.705delT (p.Pro235fs*4) and SOHLH1 c.27C>G (p.Tyr9stop). Both mutations were unique to the families and segregation was consistent with Mendelian expectations for an autosomal-recessive mode of inheritance. CONCLUSIONS: Sohlh1 was known from previous mouse studies to be a transcriptional regulator that functions in the maintenance and survival of primordial ovarian follicles, but loss-of-function mutations in human females have not been reported. Our results provide evidence that homozygous-truncating mutations in SOHLH1 cause female nonsyndromic hypergonadotropic hypogonadism.
Keywords: Adolescent; Basic Helix-Loop-Helix Transcription Factors; Child; Exome; Female; Homozygote; Humans; Hypogonadism; Mutation

Interaction between and allele variants as a risk modulating-factor for autism spectrum disorders. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Ma, Jianzhong; Bressler, Jan; Loveland, Katherine A; Hessabi, Manouchehr; Dickerson, Aisha S; Grove, Megan L; Shakespeare-Pellington, Sydonnie; Beecher, Compton; McLaughlin, Wayne; Eric Boerwinkle (Res Autism Spectr Disord, 2015)
We investigated the role of glutathione S-transferase () genes in Autism Spectrum Disorder (ASD). We used data from 111 pairs of age- and sex-matched ASD cases and typically developing (TD) controls between 2-8 years of age from Jamaica to investigate the role of pi 1 (), theta 1 (), and mu 1 () polymorphisms in susceptibility to ASD. In univariable conditional logistic regression models we did not observe significant associations between ASD status and , , or genotype (all > 0.15). However, in multivariable conditional logistic regression models, we identified a significant interaction between and in relation to ASD. Specifically, in children heterozygous for the Ile105Val polymorphism, the odds of ASD was significantly higher in those with the null genotype than those with the other genotypes [Matched Odds Ratio (MOR) = 2.97, 95% CI (1.09, 8.01), = 0.03]. Replication in other populations is warranted.

Large-scale genomic analyses link reproductive aging to hypothalamic signaling, breast cancer susceptibility and BRCA1-mediated DNA repair. - Day, Felix R; Ruth, Katherine S; Thompson, Deborah J; Lunetta, Kathryn L; Pervjakova, Natalia; Chasman, Daniel I; Stolk, Lisette; Finucane, Hilary K; Sulem, Patrick; Bulik-Sullivan, Brendan; Esko, Tõnu; Johnson, Andrew D; et al. (Nat Genet, 2015)
Menopause timing has a substantial impact on infertility and risk of disease, including breast cancer, but the underlying mechanisms are poorly understood. We report a dual strategy in ∼70,000 women to identify common and low-frequency protein-coding variation associated with age at natural menopause (ANM). We identified 44 regions with common variants, including two regions harboring additional rare missense alleles of large effect. We found enrichment of signals in or near genes involved in delayed puberty, highlighting the first molecular links between the onset and end of reproductive lifespan. Pathway analyses identified major association with DNA damage response (DDR) genes, including the first common coding variant in BRCA1 associated with any complex trait. Mendelian randomization analyses supported a causal effect of later ANM on breast cancer risk (∼6% increase in risk per year; P = 3 × 10(-14)), likely mediated by prolonged sex hormone exposure rather than DDR mechanisms.
Keywords: Adult; Age Factors; Aging; BRCA1 Protein; Breast Neoplasms; DNA Repair; Female; Gene Regulatory Networks; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Genomics; Genotype; Humans; Hypothalamus; Menopause; Middle Aged; Models, Genetic; Phenotype; Reproduction; Signal Transduction

Lipoprotein associated phospholipase A2 activity, apolipoprotein C3 loss-of-function variants and cardiovascular disease: The Atherosclerosis Risk In Communities Study. - Pokharel, Yashashwi; Sun, Wensheng; Polfus, Linda M; Folsom, Aaron R; Heiss, Gerardo; Sharrett, A Richey; Eric Boerwinkle; Ballantyne, Christie M; Hoogeveen, Ron C (Atherosclerosis, 2015)
OBJECTIVE: Lipoprotein-associated phospholipase A2 (LpPLA2) activity was associated with higher CHD risk in a meta-analysis, which was partly dependent on circulating lipid levels. Apolipoprotein C3 loss-of-function (ApoC3 LOF) mutations were related with reduced postprandial lipemia and CHD risk. However, the association of LpPLA2 activity with ApoC3 LOF is not known. METHODS: We examined the association of LpPLA2 activity and ApoC3 LOF mutations and incident cardiovascular disease (CVD) (defined as coronary heart disease [CHD] plus ischemic stroke) and all-cause mortality in the biracial longitudinal Atherosclerosis Risk In Communities (ARIC) study. RESULTS: The mean LpPLA2 activity was 229.3 nmol/min/mL and was higher in men and whites. LpPLA2 activity correlated positively with atherogenic dyslipidemia. ApoC3 LOF carriers had lower LpPLA2 activity levels compared to non-carriers, and there was inverse association between LpPLA2 activity and ApoC3 LOF mutations in whites. In a fully adjusted model, greater LpPLA2 activity was independently associated with incident CVD (HR 1.35, 1.09-1.68 for highest vs. lowest quintile), which was mainly explained by its association with CHD, and was also associated with all-cause mortality (HR 1.65, 1.38-1.98). CONCLUSIONS: Greater LpPLA2 activity was associated with increased CHD and all-cause mortality in both whites and African-Americans in the ARIC study. The inverse relation between LpPLA2 activity and ApoC3 LOF mutations suggests that delayed lipoprotein clearance may at least in part explain the observed association of LpPLA2 activity with increased CVD risk.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Aged; Alleles; Apolipoprotein C-III; Atherosclerosis; Cardiovascular Diseases; Dyslipidemias; Female; Humans; Lipoprotein Lipase; Male; Middle Aged; Mutation; Postprandial Period; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke; United States

Loss of Function Mutations in NNT Are Associated With Left Ventricular Noncompaction. - Bainbridge, Matthew N; Davis, Erica E; Choi, Wen-Yee; Dickson, Amy; Martinez, Hugo R; Wang, Min; Dinh, Huyen; Donna M Muzny; Pignatelli, Ricardo; Katsanis, Nicholas; Eric Boerwinkle; Richard A Gibbs; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Left ventricular noncompaction (LVNC) is an autosomal-dominant, genetically heterogeneous cardiomyopathy with variable severity, which may co-occur with cardiac hypertrophy. METHODS AND RESULTS: Here, we generated whole exome sequence data from multiple members from 5 families with LVNC. In 4 of 5 families, the candidate causative mutation segregates with disease in known LVNC genes MYH7 and TPM1. Subsequent sequencing of MYH7 in a larger LVNC cohort identified 7 novel likely disease causing variants. In the fifth family, we identified a frameshift mutation in NNT, a nuclear-encoded mitochondrial protein, not implicated previously in human cardiomyopathies. Resequencing of NNT in additional LVNC families identified a second likely pathogenic missense allele. Suppression of nnt in zebrafish caused early ventricular malformation and contractility defects, probably driven by altered cardiomyocyte proliferation. In vivo complementation studies showed that mutant human NNT failed to rescue nnt morpholino-induced heart dysfunction, indicating a probable haploinsufficiency mechanism. CONCLUSIONS: Together, our data expand the genetic spectrum of LVNC and demonstrate how the intersection of whole exome sequence with in vivo functional studies can accelerate the identification of genes that drive human genetic disorders.
Keywords: Animals; Animals, Genetically Modified; Embryo, Nonmammalian; Exome; Family Health; Female; Frameshift Mutation; Genetic Complementation Test; Genetic Predisposition to Disease; Humans; Isolated Noncompaction of the Ventricular Myocardium; Luminescent Proteins; Male; Microscopy, Confocal; Mitochondrial Proteins; NADP Transhydrogenase, AB-Specific; Pedigree; Sequence Analysis, DNA; Zebrafish

Low-frequency and rare exome chip variants associate with fasting glucose and type 2 diabetes susceptibility. - Wessel, Jennifer; Chu, Audrey Y; Willems, Sara M; Wang, Shuai; Yaghootkar, Hanieh; Brody, Jennifer A; Dauriz, Marco; Hivert, Marie-France; Raghavan, Sridharan; Lipovich, Leonard; Hidalgo, Bertha; Fox, Keolu; et al. (Nat Commun, 2015)
Fasting glucose and insulin are intermediate traits for type 2 diabetes. Here we explore the role of coding variation on these traits by analysis of variants on the HumanExome BeadChip in 60,564 non-diabetic individuals and in 16,491 T2D cases and 81,877 controls. We identify a novel association of a low-frequency nonsynonymous SNV in GLP1R (A316T; rs10305492; MAF=1.4%) with lower FG (β=-0.09±0.01 mmol l(-1), P=3.4 × 10(-12)), T2D risk (OR[95%CI]=0.86[0.76-0.96], P=0.010), early insulin secretion (β=-0.07±0.035 pmolinsulin mmolglucose(-1), P=0.048), but higher 2-h glucose (β=0.16±0.05 mmol l(-1), P=4.3 × 10(-4)). We identify a gene-based association with FG at G6PC2 (pSKAT=6.8 × 10(-6)) driven by four rare protein-coding SNVs (H177Y, Y207S, R283X and S324P). We identify rs651007 (MAF=20%) in the first intron of ABO at the putative promoter of an antisense lncRNA, associating with higher FG (β=0.02±0.004 mmol l(-1), P=1.3 × 10(-8)). Our approach identifies novel coding variant associations and extends the allelic spectrum of variation underlying diabetes-related quantitative traits and T2D susceptibility.
Keywords: Black People; Blood Glucose; Diabetes Mellitus, Type 2; Exome; Fasting; Genetic Association Studies; Genetic Loci; Genetic Predisposition to Disease; Genetic Variation; Glucagon-Like Peptide-1 Receptor; Glucose-6-Phosphatase; Humans; Insulin; Mutation Rate; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; White People

Metabolomics and Incidence of Atrial Fibrillation in African Americans: The Atherosclerosis Risk in Communities (ARIC) Study. - Alonso, Alvaro; Yu, Bing; Qureshi, Waqas T; Grams, Morgan E; Selvin, Elizabeth; Soliman, Elsayed Z; Loehr, Laura R; Chen, Lin Y; Agarwal, Sunil K; Alexander, Danny; Eric Boerwinkle (PLoS One, 2015)
BACKGROUND: Atrial fibrillation (AF) is a common arrhythmia. Application of metabolomic approaches, which may identify novel pathways and biomarkers of disease risk, to a longitudinal epidemiologic study of AF has been limited. METHODS: We determined the prospective association of 118 serum metabolites identified through untargeted metabolomics profiling with the incidence of newly-diagnosed AF in 1919 African-American men and women from the Atherosclerosis Risk in Communities study without AF at baseline (1987-1989). Incident AF cases through 2011 were ascertained from study electrocardiograms, hospital discharge codes, and death certificates. RESULTS: During a median follow-up of 22 years, we identified 183 incident AF cases. In Cox proportional hazards models adjusted for age, sex, smoking, body mass index, systolic blood pressure, use of antihypertensive medication, diabetes, prevalent heart failure, prevalent coronary heart disease, and kidney function, two conjugated bile acids (glycolithocholate sulfate and glycocholenate sulfate) were significantly associated with AF risk after correcting for multiple comparisons (p<0.0004). Multivariable-adjusted hazard ratios (95% confidence intervals) of AF were 1.22 (1.12-1.32) for glycolithocholate sulfate and 1.22 (1.10-1.35) for glycocholenate sulfate per 1-standard deviation higher levels. Associations were not appreciably different after additional adjustment for alcohol consumption or concentrations of circulating albumin and liver enzymes. CONCLUSION: We found an association of higher levels of two bile acids with an increased risk of AF, pointing to a potential novel pathway in AF pathogenesis. Replication of results in independent studies is warranted.
Keywords: Atherosclerosis; Atrial Fibrillation; Black or African American; Female; Humans; Incidence; Male; Metabolomics; Middle Aged; Residence Characteristics

Multiethnic genome-wide association study of cerebral white matter hyperintensities on MRI. - Verhaaren, Benjamin F J; Debette, Stephanie; Bis, Joshua C; Smith, Jennifer A; Ikram, M Kamran; Adams, Hieab H; Beecham, Ashley H; Rajan, Kumar B; Lopez, Lorna M; Barral, Sandra; van Buchem, Mark A; van der Grond, Jeroen; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: The burden of cerebral white matter hyperintensities (WMH) is associated with an increased risk of stroke, dementia, and death. WMH are highly heritable, but their genetic underpinnings are incompletely characterized. To identify novel genetic variants influencing WMH burden, we conducted a meta-analysis of multiethnic genome-wide association studies. METHODS AND RESULTS: We included 21 079 middle-aged to elderly individuals from 29 population-based cohorts, who were free of dementia and stroke and were of European (n=17 936), African (n=1943), Hispanic (n=795), and Asian (n=405) descent. WMH burden was quantified on MRI either by a validated automated segmentation method or a validated visual grading scale. Genotype data in each study were imputed to the 1000 Genomes reference. Within each ethnic group, we investigated the relationship between each single-nucleotide polymorphism and WMH burden using a linear regression model adjusted for age, sex, intracranial volume, and principal components of ancestry. A meta-analysis was conducted for each ethnicity separately and for the combined sample. In the European descent samples, we confirmed a previously known locus on chr17q25 (P=2.7×10(-19)) and identified novel loci on chr10q24 (P=1.6×10(-9)) and chr2p21 (P=4.4×10(-8)). In the multiethnic meta-analysis, we identified 2 additional loci, on chr1q22 (P=2.0×10(-8)) and chr2p16 (P=1.5×10(-8)). The novel loci contained genes that have been implicated in Alzheimer disease (chr2p21 and chr10q24), intracerebral hemorrhage (chr1q22), neuroinflammatory diseases (chr2p21), and glioma (chr10q24 and chr2p16). CONCLUSIONS: We identified 4 novel genetic loci that implicate inflammatory and glial proliferative pathways in the development of WMH in addition to previously proposed ischemic mechanisms.
Keywords: Aged; Aged, 80 and over; Chromosomes, Human; Female; Genetic Loci; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Models, Genetic; Racial Groups; Stroke; White Matter

New mutations in the RAB28 gene in 2 Spanish families with cone-rod dystrophy. - Riveiro-Álvarez, Rosa; Xie, Yajing Angela; López-Martínez, Miguel-Ángel; Gambin, Tomasz; Pérez-Carro, Raquel; Ávila-Fernández, Almudena; López-Molina, María-Isabel; Zernant, Jana; Jhangiani, Shalini; Donna M Muzny; Bo Yuan; Eric Boerwinkle; et al. (JAMA Ophthalmol, 2015)
IMPORTANCE: The families evaluated in this study represent the second report of cone-rod dystrophy (CRD) cases caused by mutations in RAB28, a recently discovered gene associated with CRD. OBJECTIVE: To determine the disease-causing gene in 2 families of Spanish descent presenting with CRD who do not have ABCA4 mutations. DESIGN, SETTING, AND PARTICIPANTS: Molecular genetics and observational case studies of 2 families, each with 1 affected proband with CRD and 3 or 5 unaffected family members. The affected individual from each family received a complete ophthalmic examination including assessment of refractive errors and best-corrected visual acuity, biomicroscopy, color fundus photography, electroretinography analysis, and visual-evoked potential analysis. After complete sequencing of the ABCA4 gene with negative results, the screening for disease-causing mutations was performed by whole-exome sequencing. Possible disease-associated variants were determined by filtering based on minor allele frequency, predicted pathogenicity, and segregation analysis in all family members. MAIN OUTCOMES AND MEASURES: The appearance of the macula was evaluated by clinical examination, fundus photography, and fundus autofluorescence imaging, and visual function was assessed by electroretinography. Disease-causing mutations were assessed by sequence analyses. RESULTS: Ophthalmologic findings included markedly reduced visual acuity, bull's eye maculopathy, foveal hyperpigmentation, peripapillary atrophy, dyschromatopsia, extinguished photopic responses, and reduced scotopic responses observed on electroretinography consistent with the CRD phenotype often associated with ABCA4 mutations. Although no ABCA4 mutations were detected in either patient, whole-exome sequencing analysis identified 2 new homozygous mutations in the recently described RAB28 gene, the c.172 + 1G>C splice site variant in IVS2 and the missense c.T651G:p.C217W substitution. Both variants were determined as deleterious by predictive programs and were segregated with the disease in both families. Sequencing of 107 additional patients of Spanish descent with CRD did not reveal other cases with RAB28 mutations. CONCLUSIONS AND RELEVANCE: Deleterious mutations in RAB28 result in a classic CRD phenotype and are an infrequent cause of CRD in the Spanish population.
Keywords: Adolescent; Adult; Child; Diagnosis, Differential; DNA Mutational Analysis; Female; Follow-Up Studies; Genetic Predisposition to Disease; Hispanic or Latino; Humans; Male; Microscopy, Acoustic; Mutation; Pedigree; Phenotype; rab GTP-Binding Proteins; Retinitis Pigmentosa; Retrospective Studies; Young Adult

PacBio-LITS: a large-insert targeted sequencing method for characterization of human disease-associated chromosomal structural variations. - Wang, Min; Beck, Christine R; English, Adam C; Meng, Qingchang; Buhay, Christian; Yi Han; Harshavardhan Doddapaneni; Fuli Yu; Eric Boerwinkle; Lupski, James R; Donna M Muzny; Richard A Gibbs (BMC Genomics, 2015)
BACKGROUND: Generation of long (>5 Kb) DNA sequencing reads provides an approach for interrogation of complex regions in the human genome. Currently, large-insert whole genome sequencing (WGS) technologies from Pacific Biosciences (PacBio) enable analysis of chromosomal structural variations (SVs), but the cost to achieve the required sequence coverage across the entire human genome is high. RESULTS: We developed a method (termed PacBio-LITS) that combines oligonucleotide-based DNA target-capture enrichment technologies with PacBio large-insert library preparation to facilitate SV studies at specific chromosomal regions. PacBio-LITS provides deep sequence coverage at the specified sites at substantially reduced cost compared with PacBio WGS. The efficacy of PacBio-LITS is illustrated by delineating the breakpoint junctions of low copy repeat (LCR)-associated complex structural rearrangements on chr17p11.2 in patients diagnosed with Potocki-Lupski syndrome (PTLS; MIM#610883). We successfully identified previously determined breakpoint junctions in three PTLS cases, and also were able to discover novel junctions in repetitive sequences, including LCR-mediated breakpoints. The new information has enabled us to propose mechanisms for formation of these structural variants. CONCLUSIONS: The new method leverages the cost efficiency of targeted capture-sequencing as well as the mappability and scaffolding capabilities of long sequencing reads generated by the PacBio platform. It is therefore suitable for studying complex SVs, especially those involving LCRs, inversions, and the generation of chimeric Alu elements at the breakpoints. Other genomic research applications, such as haplotype phasing and small insertion and deletion validation could also benefit from this technology.
Keywords: Chromosome Aberrations; Gene Library; Gene Rearrangement; Genetic Association Studies; Genomics; High-Throughput Nucleotide Sequencing; Humans; Workflow

PLD3 variants in population studies. - van der Lee, Sven J; Holstege, Henne; Wong, Tsz Hang; Jakobsdottir, Johanna; Bis, Joshua C; Chouraki, Vincent; van Rooij, Jeroen G J; Grove, Megan L; Smith, Albert V; Amin, Najaf; Choi, Seung-Hoan; Beiser, Alexa S; et al. (Nature, 2015)
Keywords: Alzheimer Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Humans; Male; Phospholipase D

Population genomic analysis of 962 whole genome sequences of humans reveals natural selection in non-coding regions. - Fuli Yu; Lu, Jian; Liu, Xiaoming; Gazave, Elodie; Chang, Diana; Raj, Srilakshmi; Hunter-Zinck, Haley; Blekhman, Ran; Arbiza, Leonardo; Van Hout, Cris; Morrison, Alanna; Johnson, Andrew D; et al. (PLoS One, 2015)
Whole genome analysis in large samples from a single population is needed to provide adequate power to assess relative strengths of natural selection across different functional components of the genome. In this study, we analyzed next-generation sequencing data from 962 European Americans, and found that as expected approximately 60% of the top 1% of positive selection signals lie in intergenic regions, 33% in intronic regions, and slightly over 1% in coding regions. Several detailed functional annotation categories in intergenic regions showed statistically significant enrichment in positively selected loci when compared to the null distribution of the genomic span of ENCODE categories. There was a significant enrichment of purifying selection signals detected in enhancers, transcription factor binding sites, microRNAs and target sites, but not on lincRNA or piRNAs, suggesting different evolutionary constraints for these domains. Loci in "repressed or low activity regions" and loci near or overlapping the transcription start site were the most significantly over-represented annotations among the top 1% of signals for positive selection.
Keywords: DNA, Intergenic; Genetic Loci; Humans; Metagenomics; Open Reading Frames; Polymorphism, Single Nucleotide

Rare and low-frequency variants and their association with plasma levels of fibrinogen, FVII, FVIII, and vWF. - Huffman, Jennifer E; de Vries, Paul S; Morrison, Alanna C; Sabater-Lleal, Maria; Kacprowski, Tim; Auer, Paul L; Brody, Jennifer A; Chasman, Daniel I; Chen, Ming-Huei; Guo, Xiuqing; Lin, Li-An; Marioni, Riccardo E; et al. (Blood, 2015)
Fibrinogen, coagulation factor VII (FVII), and factor VIII (FVIII) and its carrier von Willebrand factor (vWF) play key roles in hemostasis. Previously identified common variants explain only a small fraction of the trait heritabilities, and additional variations may be explained by associations with rarer variants with larger effects. The aim of this study was to identify low-frequency (minor allele frequency [MAF] ≥0.01 and <0.05) and rare (MAF <0.01) variants that influence plasma concentrations of these 4 hemostatic factors by meta-analyzing exome chip data from up to 76,000 participants of 4 ancestries. We identified 12 novel associations of low-frequency (n = 2) and rare (n = 10) variants across the fibrinogen, FVII, FVIII, and vWF traits that were independent of previously identified associations. Novel loci were found within previously reported genes and had effect sizes much larger than and independent of previously identified common variants. In addition, associations at KCNT1, HID1, and KATNB1 identified new candidate genes related to hemostasis for follow-up replication and functional genomic analysis. Newly identified low-frequency and rare-variant associations accounted for modest amounts of trait variance and therefore are unlikely to increase predicted trait heritability but provide new information for understanding individual variation in hemostasis pathways.
Keywords: Cohort Studies; Factor VII; Factor VIII; Fibrinogen; Gene Frequency; Genetic Association Studies; Genetic Variation; Humans; Nerve Tissue Proteins; Polymorphism, Single Nucleotide; Potassium Channels; Potassium Channels, Sodium-Activated; von Willebrand Factor

Rare variants analysis using penalization methods for whole genome sequence data. - Yazdani, Akram; Yazdani, Azam; Eric Boerwinkle (BMC Bioinformatics, 2015)
BACKGROUND: Availability of affordable and accessible whole genome sequencing for biomedical applications poses a number of statistical challenges and opportunities, particularly related to the analysis of rare variants and sparseness of the data. Although efforts have been devoted to address these challenges, the performance of statistical methods for rare variants analysis still needs further consideration. RESULT: We introduce a new approach that applies restricted principal component analysis with convex penalization and then selects the best predictors of a phenotype by a concave penalized regression model, while estimating the impact of each genomic region on the phenotype. Using simulated data, we show that the proposed method maintains good power for association testing while keeping the false discovery rate low under a verity of genetic architectures. Illustrative data analyses reveal encouraging result of this method in comparison with other commonly applied methods for rare variants analysis. CONCLUSION: By taking into account linkage disequilibrium and sparseness of the data, the proposed method improves power and controls the false discovery rate compared to other commonly applied methods for rare variant analyses.
Keywords: Algorithms; Atherosclerosis; Genetic Association Studies; Genetic Variation; Genome, Human; High-Throughput Nucleotide Sequencing; Humans; Linkage Disequilibrium; Phenotype; Principal Component Analysis

Roger et al. respond to "future of population studies". - Roger, Véronique L; Eric Boerwinkle; Crapo, James D; Douglas, Pamela S; Epstein, Jonathan A; Granger, Christopher B; Greenland, Philip; Kohane, Isaac; Psaty, Bruce M (Am J Epidemiol, 2015)
Keywords: Data Collection; Epidemiologic Research Design; Epidemiologic Studies; Humans; Research

Secondary findings and carrier test frequencies in a large multiethnic sample. - Gambin, Tomasz; Jhangiani, Shalini N; Below, Jennifer E; Campbell, Ian M; Wiszniewski, Wojciech; Donna M Muzny; Staples, Jeffrey; Morrison, Alanna C; Bainbridge, Matthew N; Penney, Samantha; McGuire, Amy L; Richard A Gibbs; et al. (Genome Med, 2015)
BACKGROUND: Besides its growing importance in clinical diagnostics and understanding the genetic basis of Mendelian and complex diseases, whole exome sequencing (WES) is a rich source of additional information of potential clinical utility for physicians, patients and their families. We analyzed the frequency and nature of single nucleotide variants (SNVs) considered secondary findings and recessive disease allele carrier status in the exomes of 8554 individuals from a large, randomly sampled cohort study and 2514 patients from a study of presumed Mendelian disease having undergone WES. METHODS: We used the same sequencing platform and data processing pipeline to analyze all samples and characterized the distributions of reported pathogenic (ClinVar, Human Gene Mutation Database (HGMD)) and predicted deleterious variants in the pre-specified American College of Medical Genetics and Genomics (ACMG) secondary findings and recessive disease genes in different ethnic groups. RESULTS: In the 56 ACMG secondary findings genes, the average number of predicted deleterious variants per individual was 0.74, and the mean number of ClinVar reported pathogenic variants was 0.06. We observed an average of 10 deleterious and 0.78 ClinVar reported pathogenic variants per individual in 1423 autosomal recessive disease genes. By repeatedly sampling pairs of exomes, 0.5 % of the randomly generated couples were at 25 % risk of having an affected offspring for an autosomal recessive disorder based on the ClinVar variants. CONCLUSIONS: By investigating reported pathogenic and novel, predicted deleterious variants we estimated the lower and upper limits of the population fraction for which exome sequencing may reveal additional medically relevant information. We suggest that the observed wide range for the lower and upper limits of these frequency numbers will be gradually reduced due to improvement in classification databases and prediction algorithms.

Sequence variation in telomerase reverse transcriptase (TERT) as a determinant of risk of cardiovascular disease: the Atherosclerosis Risk in Communities (ARIC) study. - Bressler, Jan; Franceschini, Nora; Demerath, Ellen W; Mosley, Thomas H; Folsom, Aaron R; Eric Boerwinkle (BMC Med Genet, 2015)
BACKGROUND: Telomerase reverse transcriptase (TERT) maintains telomere ends during DNA replication by catalyzing the addition of short telomere repeats. The expression of telomerase is normally repressed in somatic cells leading to a gradual shortening of telomeres and cellular senescence with aging. Interindividual variation in leukocyte telomere length has been previously associated with susceptibility to cardiovascular disease. The aim of the present study was to determine whether six variants in the TERT gene are associated with risk of incident coronary heart disease, incident ischemic stroke, and mortality in participants in the biracial population-based Atherosclerosis Risk in Communities (ARIC) study, including rs2736100 that was found to influence mean telomere length in a genome-wide analysis. METHODS: ARIC is a prospective study of the etiology and natural history of atherosclerosis in 15,792 individuals aged 45 to 64 years at baseline in 1987-1989. Haplotype tagging SNPs in TERT were genotyped using a custom array containing nearly 49,000 SNPs in 2,100 genes associated with cardiovascular and metabolic phenotypes. Cox proportional hazards models were used to assess the association between the TERT polymorphisms and incident cardiovascular disease and mortality over a 20-year follow-up period in 8,907 whites and 3,022 African-Americans with no history of disease at the baseline examination, while individuals with prevalent cardiovascular disease were not excluded from the analyses of mortality. RESULTS: After adjustment for age and gender, and assuming an additive genetic model, rs2736122 and rs2853668 were nominally associated with incident coronary heart disease (hazards rate ratio = 1.20, p = 0.02, 95 % confidence interval = 1.03- 1.40) and stroke (hazards rate ratio = 1.17, p = 0.05, 95 % confidence interval = 1.00 - 1.38), respectively, in African-Americans. None of the variants was significantly associated with cardiovascular disease in white study participants or with mortality in either racial group. CONCLUSIONS: Replication in additional population-based samples combined with genotyping of polymorphisms in other genes involved in maintenance of telomere length may help to determine whether genetic variants associated with telomere homeostasis influence the risk of cardiovascular disease in middle-aged adults.
Keywords: Atherosclerosis; Black or African American; Cellular Senescence; Coronary Disease; Female; Gene Frequency; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk; Stroke; Telomerase; Telomere Homeostasis; White People

Strategic transformation of population studies: recommendations of the working group on epidemiology and population sciences from the National Heart, Lung, and Blood Advisory Council and Board of External Experts. - Roger, Véronique L; Eric Boerwinkle; Crapo, James D; Douglas, Pamela S; Epstein, Jonathan A; Granger, Christopher B; Greenland, Philip; Kohane, Isaac; Psaty, Bruce M (Am J Epidemiol, 2015)
In 2013, the National Heart, Lung, and Blood Institute assembled a working group on epidemiology and population sciences from its Advisory Council and Board of External Experts. The working group was charged with making recommendations to the National Heart, Lung, and Blood Advisory Council about how the National Heart, Lung, and Blood Institute could take advantage of new scientific opportunities and delineate future directions for the epidemiology of heart, lung, blood, and sleep diseases. Seven actionable recommendations were proposed for consideration. The themes included 1) defining the compelling scientific questions and challenges in population sciences and epidemiology of heart, lung, blood, and sleep diseases; 2) developing methods and training mechanisms to integrate "big data" science into the practice of epidemiology; 3) creating a cohort consortium and inventory of major studies to optimize the efficient use of data and specimens; and 4) fostering a more open, competitive approach to evaluating large-scale longitudinal epidemiology and population studies. By building on the track record of success of the heart, lung, blood, and sleep cohorts to leverage new data science opportunities and encourage broad research and training partnerships, these recommendations lay a strong foundation for the transformation of heart, lung, blood, and sleep epidemiology.
Keywords: Epidemiologic Studies; Health Planning Councils; Health Planning Guidelines; Heart Diseases; Hematologic Diseases; Humans; Longitudinal Studies; Lung Diseases; National Heart, Lung, and Blood Institute (U.S.); Sleep Wake Disorders; United States

TET2 and CSMD1 genes affect SBP response to hydrochlorothiazide in never-treated essential hypertensives. - Chittani, Martina; Zaninello, Roberta; Lanzani, Chiara; Frau, Francesca; Ortu, Maria F; Salvi, Erika; Fresu, Giovanni; Citterio, Lorena; Braga, Daniele; Piras, Daniela A; Carpini, Simona Delli; Velayutham, Dinesh; et al. (J Hypertens, 2015)
BACKGROUND: Thiazide diuretics have been recommended as a first-line antihypertensive treatment, although the choice of 'the right drug in the individual essential hypertensive patient' remains still empirical. Essential hypertension is a complex, polygenic disease derived from the interaction of patient's genetic background with the environment. Pharmacogenomics could be a useful tool to pinpoint gene variants involved in antihypertensive drug response, thus optimizing therapeutic advantages and minimizing side effects. METHODS AND RESULTS: We looked for variants associated with blood pressure response to hydrochlorothiazide over an 8-week follow-up by means of a genome-wide association analysis in two Italian cohorts of never-treated essential hypertensive patients: 343 samples from Sardinia and 142 from Milan. TET2 and CSMD1 as plausible candidate genes to affect SBP response to hydrochlorothiazide were identified. The specificity of our findings for hydrochlorothiazide was confirmed in an independent cohort of essential hypertensive patients treated with losartan. Our best findings were also tested for replication in four independent hypertensive samples of European Ancestry, such as GENetics of drug RESponsiveness in essential hypertension, Genetic Epidemiology of Responses to Antihypertensives, NORdic DILtiazem intervention, Pharmacogenomics Evaluation of Antihypertensive Responses, and Campania Salute Network-StayOnDiur. We validated a polymorphism in CSMD1 and UGGT2. CONCLUSION: This exploratory study reports two plausible loci associated with SBP response to hydrochlorothiazide: TET2, an aldosterone-responsive mediator of αENaC gene transcription; and CSMD1, previously described as associated with hypertension in a case-control study.
Keywords: Adult; Aged; Aldosterone; Antihypertensive Agents; Blood Pressure; Case-Control Studies; Dioxygenases; DNA-Binding Proteins; Essential Hypertension; Genome-Wide Association Study; Humans; Hydrochlorothiazide; Hypertension; Italy; Losartan; Male; Membrane Proteins; Middle Aged; Pharmacogenetics; Proto-Oncogene Proteins; Sodium Chloride Symporter Inhibitors; Systole; Tumor Suppressor Proteins; White People

Transethnic meta-analysis suggests genetic variation in the HEME pathway influences potassium response in patients treated with hydrochlorothiazide. - Del-Aguila, J L; Cooper-Dehoff, R M; Chapman, A B; Gums, J G; Beitelshees, A L; Bailey, K; Turner, S T; Johnson, J A; Eric Boerwinkle (Pharmacogenomics J, 2015)
Hypokalemia is a recognized adverse effect of thiazide diuretic treatment. This phenomenon, which may impair insulin secretion, has been suggested to be a reason for the adverse effects on glucose metabolism associated with thiazide diuretic treatment of hypertension. However, the mechanisms underlying thiazide diuretic-induced hypokalemia are not well understood. In an effort to identify genes or genomic regions associated with potassium response to hydrochlorothiazide, without a priori knowledge of biologic effects, we performed a genome-wide association study and a multiethnic meta-analysis in 718 European- and African-American hypertensive participants from two different pharmacogenetic studies. Single-nucleotide polymorphisms rs10845697 (Bayes factor=5.560) on chromosome 12, near to the HEME binding protein 1 gene, and rs11135740 (Bayes factor=5.258) on chromosome 8, near to the Mitoferrin-1 gene, reached genome-wide association study significance (Bayes factor >5). These results, if replicated, suggest a novel mechanism involving effects of genes in the HEME pathway influencing hydrochlorothiazide-induced renal potassium loss.
Keywords: Antihypertensive Agents; Bayes Theorem; Black or African American; Carrier Proteins; Cation Transport Proteins; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 8; Female; Genome-Wide Association Study; Heme; Heme-Binding Proteins; Hemeproteins; Humans; Hydrochlorothiazide; Hypertension; Hypokalemia; Male; Middle Aged; Mitochondrial Proteins; Polymorphism, Single Nucleotide; Potassium; White People

Variants for HDL-C, LDL-C, and triglycerides identified from admixture mapping and fine-mapping analysis in African American families. - Shetty, Priya B; Tang, Hua; Feng, Tao; Tayo, Bamidele; Morrison, Alanna C; Kardia, Sharon L R; Hanis, Craig L; Arnett, Donna K; Hunt, Steven C; Eric Boerwinkle; Rao, Dabeeru C; Cooper, Richard S; et al. (Circ Cardiovasc Genet, 2015)
BACKGROUND: Admixture mapping of lipids was followed-up by family-based association analysis to identify variants for cardiovascular disease in African Americans. METHODS AND RESULTS: The present study conducted admixture mapping analysis for total cholesterol, high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides. The analysis was performed in 1905 unrelated African American subjects from the National Heart, Lung and Blood Institute's Family Blood Pressure Program (FBPP). Regions showing admixture evidence were followed-up with family-based association analysis in 3556 African American subjects from the FBPP. The admixture mapping and family-based association analyses were adjusted for age, age(2), sex, body mass index, and genome-wide mean ancestry to minimize the confounding caused by population stratification. Regions that were suggestive of local ancestry association evidence were found on chromosomes 7 (low-density lipoprotein cholesterol), 8 (high-density lipoprotein cholesterol), 14 (triglycerides), and 19 (total cholesterol and triglycerides). In the fine-mapping analysis, 52 939 single-nucleotide polymorphisms (SNPs) were tested and 11 SNPs (8 independent SNPs) showed nominal significant association with high-density lipoprotein cholesterol (2 SNPs), low-density lipoprotein cholesterol (4 SNPs), and triglycerides (5 SNPs). The family data were used in the fine-mapping to identify SNPs that showed novel associations with lipids and regions, including genes with known associations for cardiovascular disease. CONCLUSIONS: This study identified regions on chromosomes 7, 8, 14, and 19 and 11 SNPs from the fine-mapping analysis that were associated with high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides for further studies of cardiovascular disease in African Americans.
Keywords: Adult; Aged; Aged, 80 and over; Black or African American; Cardiovascular Diseases; Cholesterol, HDL; Cholesterol, LDL; Chromosome Mapping; Chromosomes, Human; Family; Female; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Triglycerides

Association of levels of fasting glucose and insulin with rare variants at the chromosome 11p11.2-MADD locus: Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Cornes, Belinda K; Brody, Jennifer A; Nikpoor, Naghmeh; Morrison, Alanna C; Chu, Huan; Ahn, Byung Soo; Wang, Shuai; Dauriz, Marco; Barzilay, Joshua I; Dupuis, Josée; Florez, Jose C; Coresh, Josef; et al. (Circ Cardiovasc Genet, 2014)
BACKGROUND: Common variation at the 11p11.2 locus, encompassing MADD, ACP2, NR1H3, MYBPC3, and SPI1, has been associated in genome-wide association studies with fasting glucose and insulin (FI). In the Cohorts for Heart and Aging Research in Genomic Epidemiology Targeted Sequencing Study, we sequenced 5 gene regions at 11p11.2 to identify rare, potentially functional variants influencing fasting glucose or FI levels. METHODS AND RESULTS: Sequencing (mean depth, 38×) across 16.1 kb in 3566 individuals without diabetes mellitus identified 653 variants, 79.9% of which were rare (minor allele frequency <1%) and novel. We analyzed rare variants in 5 gene regions with FI or fasting glucose using the sequence kernel association test. At NR1H3, 53 rare variants were jointly associated with FI (P=2.73×10(-3)); of these, 7 were predicted to have regulatory function and showed association with FI (P=1.28×10(-3)). Conditioning on 2 previously associated variants at MADD (rs7944584, rs10838687) did not attenuate this association, suggesting that there are >2 independent signals at 11p11.2. One predicted regulatory variant, chr11:47227430 (hg18; minor allele frequency=0.00068), contributed 20.6% to the overall sequence kernel association test score at NR1H3, lies in intron 2 of NR1H3, and is a predicted binding site for forkhead box A1 (FOXA1), a transcription factor associated with insulin regulation. In human HepG2 hepatoma cells, the rare chr11:47227430 A allele disrupted FOXA1 binding and reduced FOXA1-dependent transcriptional activity. CONCLUSIONS: Sequencing at 11p11.2-NR1H3 identified rare variation associated with FI. One variant, chr11:47227430, seems to be functional, with the rare A allele reducing transcription factor FOXA1 binding and FOXA1-dependent transcriptional activity.
Keywords: Aged; Aged, 80 and over; Aging; Blood Glucose; Chromosomes, Human, Pair 11; Cohort Studies; Death Domain Receptor Signaling Adaptor Proteins; Diabetes Mellitus, Type 2; Fasting; Female; Gene Frequency; Genetic Variation; Genome-Wide Association Study; Genomics; Guanine Nucleotide Exchange Factors; Heart Diseases; Humans; Insulin; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Association of low-frequency and rare coding-sequence variants with blood lipids and coronary heart disease in 56,000 whites and blacks. - Peloso, Gina M; Auer, Paul L; Bis, Joshua C; Voorman, Arend; Morrison, Alanna C; Stitziel, Nathan O; Brody, Jennifer A; Khetarpal, Sumeet A; Crosby, Jacy R; Fornage, Myriam; Isaacs, Aaron; Jakobsdottir, Johanna; et al. (Am J Hum Genet, 2014)
Low-frequency coding DNA sequence variants in the proprotein convertase subtilisin/kexin type 9 gene (PCSK9) lower plasma low-density lipoprotein cholesterol (LDL-C), protect against risk of coronary heart disease (CHD), and have prompted the development of a new class of therapeutics. It is uncertain whether the PCSK9 example represents a paradigm or an isolated exception. We used the "Exome Array" to genotype >200,000 low-frequency and rare coding sequence variants across the genome in 56,538 individuals (42,208 European ancestry [EA] and 14,330 African ancestry [AA]) and tested these variants for association with LDL-C, high-density lipoprotein cholesterol (HDL-C), and triglycerides. Although we did not identify new genes associated with LDL-C, we did identify four low-frequency (frequencies between 0.1% and 2%) variants (ANGPTL8 rs145464906 [c.361C>T; p.Gln121*], PAFAH1B2 rs186808413 [c.482C>T; p.Ser161Leu], COL18A1 rs114139997 [c.331G>A; p.Gly111Arg], and PCSK7 rs142953140 [c.1511G>A; p.Arg504His]) with large effects on HDL-C and/or triglycerides. None of these four variants was associated with risk for CHD, suggesting that examples of low-frequency coding variants with robust effects on both lipids and CHD will be limited.
Keywords: 1-Alkyl-2-acetylglycerophosphocholine Esterase; Adult; Aged; Alleles; Animals; Black People; Cholesterol, HDL; Cholesterol, LDL; Cohort Studies; Coronary Disease; Female; Gene Frequency; Genetic Association Studies; Genetic Code; Genetic Variation; Humans; Linear Models; Male; Mice; Mice, Inbred C57BL; Microtubule-Associated Proteins; Middle Aged; Phenotype; Sequence Analysis, DNA; Subtilisins; Triglycerides; White People

Associations of NINJ2 sequence variants with incident ischemic stroke in the Cohorts for Heart and Aging in Genomic Epidemiology (CHARGE) consortium. - Bis, Joshua C; DeStefano, Anita; Liu, Xiaoming; Brody, Jennifer A; Choi, Seung Hoan; Verhaaren, Benjamin F J; Debette, Stephanie; Ikram, M Arfan; Shahar, Eyal; Butler, Kenneth R; Gottesman, Rebecca F; Donna M Muzny; et al. (PLoS One, 2014)
BACKGROUND: Stroke, the leading neurologic cause of death and disability, has a substantial genetic component. We previously conducted a genome-wide association study (GWAS) in four prospective studies from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) consortium and demonstrated that sequence variants near the NINJ2 gene are associated with incident ischemic stroke. Here, we sought to fine-map functional variants in the region and evaluate the contribution of rare variants to ischemic stroke risk. METHODS AND RESULTS: We sequenced 196 kb around NINJ2 on chromosome 12p13 among 3,986 European ancestry participants, including 475 ischemic stroke cases, from the Atherosclerosis Risk in Communities Study, Cardiovascular Health Study, and Framingham Heart Study. Meta-analyses of single-variant tests for 425 common variants (minor allele frequency [MAF] ≥ 1%) confirmed the original GWAS results and identified an independent intronic variant, rs34166160 (MAF = 0.012), most significantly associated with incident ischemic stroke (HR = 1.80, p = 0.0003). Aggregating 278 putatively-functional variants with MAF≤ 1% using count statistics, we observed a nominally statistically significant association, with the burden of rare NINJ2 variants contributing to decreased ischemic stroke incidence (HR = 0.81; p = 0.026). CONCLUSION: Common and rare variants in the NINJ2 region were nominally associated with incident ischemic stroke among a subset of CHARGE participants. Allelic heterogeneity at this locus, caused by multiple rare, low frequency, and common variants with disparate effects on risk, may explain the difficulties in replicating the original GWAS results. Additional studies that take into account the complex allelic architecture at this locus are needed to confirm these findings.
Keywords: Cell Adhesion Molecules, Neuronal; Female; Genetic Association Studies; Genetic Heterogeneity; Humans; Introns; Ischemia; Male; Myocardial Infarction; Polymorphism, Single Nucleotide; Prospective Studies; Sequence Analysis, DNA; White People

Blood lead concentrations in Jamaican children with and without autism spectrum disorder. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Dickerson, Aisha S; Loveland, Katherine A; Ardjomand-Hessabi, Manouchehr; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Pearson, Deborah A; Eric Boerwinkle (Int J Environ Res Public Health, 2014)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder manifesting by early childhood. Lead is a toxic metal shown to cause neurodevelopmental disorders in children. Several studies have investigated the possible association between exposure to lead and ASD, but their findings are conflicting. Using data from 100 ASD cases (2-8 years of age) and their age- and sex-matched typically developing controls, we investigated the association between blood lead concentrations (BLC) and ASD in Jamaican children. We administered a questionnaire to assess demographic and socioeconomic information as well as exposure to potential lead sources. We used General Linear Models (GLM) to assess the association of BLC with ASD status as well as with sources of exposure to lead. In univariable GLM, we found a significant difference between geometric mean blood lead concentrations of ASD cases and controls (2.25 μg/dL cases vs. 2.73 μg/dL controls, p < 0.05). However, after controlling for potential confounders, there were no significant differences between adjusted geometric mean blood lead concentrations of ASD cases and controls (2.55 μg/dL vs. 2.72 μg/dL, p = 0.64). Our results do not support an association between BLC and ASD in Jamaican children. We have identified significant confounders when assessing an association between ASD and BLC.
Keywords: Case-Control Studies; Child; Child Development Disorders, Pervasive; Child, Preschool; Diet; Environmental Pollutants; Female; Humans; Jamaica; Lead; Male; Socioeconomic Factors; Surveys and Questionnaires

De novo truncating mutations in AHDC1 in individuals with syndromic expressive language delay, hypotonia, and sleep apnea. - Xia, Fan; Bainbridge, Matthew N; Tan, Tiong Yang; Wangler, Michael F; Scheuerle, Angela E; Zackai, Elaine H; Harr, Margaret H; Sutton, V Reid; Nalam, Roopa L; Zhu, Wenmiao; Nash, Margot; Ryan, Monique M; et al. (Am J Hum Genet, 2014)
Clinical whole-exome sequencing (WES) for identification of mutations leading to Mendelian disease has been offered to the medical community since 2011. Clinically undiagnosed neurological disorders are the most frequent basis for test referral, and currently, approximately 25% of such cases are diagnosed at the molecular level. To date, there are approximately 4,000 "known" disease-associated loci, and many are associated with striking dysmorphic features, making genotype-phenotype correlations relatively straightforward. A significant fraction of cases, however, lack characteristic dysmorphism or clinical pathognomonic traits and are dependent upon molecular tests for definitive diagnoses. Further, many molecular diagnoses are guided by recent gene-disease association discoveries. Hence, there is a critical interplay between clinical testing and research leading to gene-disease association discovery. Here, we describe four probands, all of whom presented with hypotonia, intellectual disability, global developmental delay, and mildly dysmorphic facial features. Three of the four also had sleep apnea. Each was a simplex case without a remarkable family history. Using WES, we identified AHDC1 de novo truncating mutations that most likely cause this genetic syndrome.
Keywords: Child; Child, Preschool; DNA-Binding Proteins; Exome; Female; Humans; Infant; Intellectual Disability; Language Development Disorders; Male; Muscle Hypotonia; Mutation; Sleep Apnea Syndromes; Syndrome

A drosophila genetic resource of mutants to study mechanisms underlying human genetic diseases. - Yamamoto, Shinya; Jaiswal, Manish; Charng, Wu-Lin; Gambin, Tomasz; Karaca, Ender; Mirzaa, Ghayda; Wiszniewski, Wojciech; Sandoval, Hector; Haelterman, Nele A; Xiong, Bo; Zhang, Ke; Bayat, Vafa; et al. (Cell, 2014)
Invertebrate model systems are powerful tools for studying human disease owing to their genetic tractability and ease of screening. We conducted a mosaic genetic screen of lethal mutations on the Drosophila X chromosome to identify genes required for the development, function, and maintenance of the nervous system. We identified 165 genes, most of whose function has not been studied in vivo. In parallel, we investigated rare variant alleles in 1,929 human exomes from families with unsolved Mendelian disease. Genes that are essential in flies and have multiple human homologs were found to be likely to be associated with human diseases. Merging the human data sets with the fly genes allowed us to identify disease-associated mutations in six families and to provide insights into microcephaly associated with brain dysgenesis. This bidirectional synergism between fly genetics and human genomics facilitates the functional annotation of evolutionarily conserved genes involved in human health.
Keywords: Animals; Disease; Disease Models, Animal; Drosophila melanogaster; Genetic Testing; Humans; Inheritance Patterns; RNA Interference; X Chromosome

Epistasis analysis for quantitative traits by functional regression model. - Zhang, Futao; Eric Boerwinkle; Xiong, Momiao (Genome Res, 2014)
The critical barrier in interaction analysis for rare variants is that most traditional statistical methods for testing interactions were originally designed for testing the interaction between common variants and are difficult to apply to rare variants because of their prohibitive computational time and poor ability. The great challenges for successful detection of interactions with next-generation sequencing (NGS) data are (1) lack of methods for interaction analysis with rare variants, (2) severe multiple testing, and (3) time-consuming computations. To meet these challenges, we shift the paradigm of interaction analysis between two loci to interaction analysis between two sets of loci or genomic regions and collectively test interactions between all possible pairs of SNPs within two genomic regions. In other words, we take a genome region as a basic unit of interaction analysis and use high-dimensional data reduction and functional data analysis techniques to develop a novel functional regression model to collectively test interactions between all possible pairs of single nucleotide polymorphisms (SNPs) within two genome regions. By intensive simulations, we demonstrate that the functional regression models for interaction analysis of the quantitative trait have the correct type 1 error rates and a much better ability to detect interactions than the current pairwise interaction analysis. The proposed method was applied to exome sequence data from the NHLBI's Exome Sequencing Project (ESP) and CHARGE-S study. We discovered 27 pairs of genes showing significant interactions after applying the Bonferroni correction (P-values < 4.58 × 10(-10)) in the ESP, and 11 were replicated in the CHARGE-S study.
Keywords: Epistasis, Genetic; Genome, Human; Humans; Models, Genetic; Polymorphism, Single Nucleotide; Quantitative Trait, Heritable; Regression Analysis

Following-up genome-wide association study signals: lessons learned from Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium Targeted Sequencing Study. - Eric Boerwinkle; Heckbert, Susan R (Circ Cardiovasc Genet, 2014)
Keywords: Adult; Aged; Aged, 80 and over; Aging; Cohort Studies; Female; Genome-Wide Association Study; Genomics; Heart Diseases; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

A framework for the interpretation of de novo mutation in human disease. - Samocha, Kaitlin E; Robinson, Elise B; Sanders, Stephan J; Stevens, Christine; Aniko Sabo; McGrath, Lauren M; Kosmicki, Jack A; Rehnström, Karola; Mallick, Swapan; Kirby, Andrew; Wall, Dennis P; MacArthur, Daniel G; et al. (Nat Genet, 2014)
Spontaneously arising (de novo) mutations have an important role in medical genetics. For diseases with extensive locus heterogeneity, such as autism spectrum disorders (ASDs), the signal from de novo mutations is distributed across many genes, making it difficult to distinguish disease-relevant mutations from background variation. Here we provide a statistical framework for the analysis of excesses in de novo mutation per gene and gene set by calibrating a model of de novo mutation. We applied this framework to de novo mutations collected from 1,078 ASD family trios, and, whereas we affirmed a significant role for loss-of-function mutations, we found no excess of de novo loss-of-function mutations in cases with IQ above 100, suggesting that the role of de novo mutations in ASDs might reside in fundamental neurodevelopmental processes. We also used our model to identify ∼1,000 genes that are significantly lacking in functional coding variation in non-ASD samples and are enriched for de novo loss-of-function mutations identified in ASD cases.
Keywords: Child Development Disorders, Pervasive; Exome; Female; Genetic Code; Genetic Predisposition to Disease; Genetics, Medical; Humans; Male; Mutation

Gene-specific function prediction for non-synonymous mutations in monogenic diabetes genes. - Li, Quan; Liu, Xiaoming; Richard A Gibbs; Eric Boerwinkle; Polychronakos, Constantin; Qu, Hui-Qi (PLoS One, 2014)
The rapid progress of genomic technologies has been providing new opportunities to address the need of maturity-onset diabetes of the young (MODY) molecular diagnosis. However, whether a new mutation causes MODY can be questionable. A number of in silico methods have been developed to predict functional effects of rare human mutations. The purpose of this study is to compare the performance of different bioinformatics methods in the functional prediction of nonsynonymous mutations in each MODY gene, and provides reference matrices to assist the molecular diagnosis of MODY. Our study showed that the prediction scores by different methods of the diabetes mutations were highly correlated, but were more complimentary than replacement to each other. The available in silico methods for the prediction of diabetes mutations had varied performances across different genes. Applying gene-specific thresholds defined by this study may be able to increase the performance of in silico prediction of disease-causing mutations.
Keywords: Adolescent; Apoptosis Regulatory Proteins; Basic Helix-Loop-Helix Transcription Factors; Cell Cycle Proteins; Child; Computational Biology; Diabetes Mellitus, Type 2; Hepatocyte Nuclear Factor 1-alpha; Hepatocyte Nuclear Factor 1-beta; Hepatocyte Nuclear Factor 4; Homeodomain Proteins; Humans; Lipase; Mutation, Missense; Paired Box Transcription Factors; Potassium Channels, Inwardly Rectifying; Repressor Proteins; src-Family Kinases; Sulfonylurea Receptors; Trans-Activators; Young Adult

Genetic determinants influencing human serum metabolome among African Americans. - Yu, Bing; Zheng, Yan; Alexander, Danny; Morrison, Alanna C; Coresh, Josef; Eric Boerwinkle (PLoS Genet, 2014)
Phenotypes proximal to gene action generally reflect larger genetic effect sizes than those that are distant. The human metabolome, a result of multiple cellular and biological processes, are functional intermediate phenotypes proximal to gene action. Here, we present a genome-wide association study of 308 untargeted metabolite levels among African Americans from the Atherosclerosis Risk in Communities (ARIC) Study. Nineteen significant common variant-metabolite associations were identified, including 13 novel loci (p<1.6 × 10(-10)). These loci were associated with 7-50% of the difference in metabolite levels per allele, and the variance explained ranged from 4% to 20%. Fourteen genes were identified within the nineteen loci, and four of them contained non-synonymous substitutions in four enzyme-encoding genes (KLKB1, SIAE, CPS1, and NAT8); the other significant loci consist of eight other enzyme-encoding genes (ACE, GATM, ACY3, ACSM2B, THEM4, ADH4, UGT1A, TREH), a transporter gene (SLC6A13) and a polycystin protein gene (PKD2L1). In addition, four potential disease-associated paths were identified, including two direct longitudinal predictive relationships: NAT8 with N-acetylornithine, N-acetyl-1-methylhistidine and incident chronic kidney disease, and TREH with trehalose and incident diabetes. These results highlight the value of using endophenotypes proximal to gene function to discover new insights into biology and disease pathology.
Keywords: Acetyltransferases; Alleles; Atherosclerosis; Black or African American; Diabetes Mellitus; Genome-Wide Association Study; Humans; Metabolome; Phenotype; Polymorphism, Single Nucleotide; Trehalose

Genetic markers associated with plasma protein C level in African Americans: the atherosclerosis risk in communities (ARIC) study. - Munir, M Shahzeb; Weng, Lu-Chen; Tang, Weihong; Basu, Saonli; Pankow, James S; Matijevic, Nena; Cushman, Mary; Eric Boerwinkle; Folsom, Aaron R (Genet Epidemiol, 2014)
Protein C is an endogenous anticoagulant protein with anti-inflammatory properties. Single-nucleotide polymorphisms (SNPs) affect the levels of circulating protein C in European Americans. We performed a genome-wide association (GWA) scan of plasma protein C concentration with approximately 2.5 million SNPs in 2,701 African Americans in the Atherosclerosis Risk in Communities Study. Seventy-nine SNPs from the 20q11 and 2q14 regions reached the genome-wide significance threshold of 5 × 10(-8) . A missense variant rs867186 in the PROCR gene at 20q11 is known to affect protein C levels in individuals of European descent and showed the strongest signal (P = 9.84 × 10(-65) ) in African Americans. The minor allele of this SNP was associated with higher protein C levels (β = 0.49 μg/ml; 10% variance explained). In the 2q14 region, the top SNPs were near or within the PROC gene: rs7580658 (β = 0.15 μg/ml; 2% variance explained, P = 1.7 × 10(-12) ) and rs1799808 (β = 0.15 μg/ml; 2% variance explained, P = 2.03 × 10(-12) ). These two SNPs were in strong linkage disequilibrium (LD) with another SNP rs1158867 that resides in a biochemically functional site and in weak to strong LD with the top PROC variants previously reported in individuals of European descent. In addition, two variants outside the PROC region were significantly and independently associated with protein C levels: rs4321325 in CYP27C1 and rs13419716 in MYO7B. In summary, this first GWA study for plasma protein C levels in African Americans confirms the associations of SNPs in the PROC and PROCR regions with circulating levels of protein C across ethnic populations and identifies new candidates for protein C regulation.
Keywords: Atherosclerosis; Black or African American; Female; Genetic Markers; Genome-Wide Association Study; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Protein C; Risk

Gene-wide analysis detects two new susceptibility genes for Alzheimer's disease. - Escott-Price, Valentina; Bellenguez, Céline; Wang, Li-San; Choi, Seung-Hoan; Harold, Denise; Jones, Lesley; Holmans, Peter; Gerrish, Amy; Vedernikov, Alexey; Richards, Alexander; DeStefano, Anita L; Lambert, Jean-Charles; et al. (PLoS One, 2014)
BACKGROUND: Alzheimer's disease is a common debilitating dementia with known heritability, for which 20 late onset susceptibility loci have been identified, but more remain to be discovered. This study sought to identify new susceptibility genes, using an alternative gene-wide analytical approach which tests for patterns of association within genes, in the powerful genome-wide association dataset of the International Genomics of Alzheimer's Project Consortium, comprising over 7 m genotypes from 25,580 Alzheimer's cases and 48,466 controls. PRINCIPAL FINDINGS: In addition to earlier reported genes, we detected genome-wide significant loci on chromosomes 8 (TP53INP1, p = 1.4×10-6) and 14 (IGHV1-67 p = 7.9×10-8) which indexed novel susceptibility loci. SIGNIFICANCE: The additional genes identified in this study, have an array of functions previously implicated in Alzheimer's disease, including aspects of energy metabolism, protein degradation and the immune system and add further weight to these pathways as potential therapeutic targets in Alzheimer's disease.
Keywords: Alzheimer Disease; Carrier Proteins; Case-Control Studies; Genome-Wide Association Study; Heat-Shock Proteins; Humans; Polymorphism, Single Nucleotide; Receptors, Antigen, B-Cell

Genome-wide association analyses suggest NELL1 influences adverse metabolic response to HCTZ in African Americans. - Del-Aguila, J L; Beitelshees, A L; Cooper-Dehoff, R M; Chapman, A B; Gums, J G; Bailey, K; Gong, Y; Turner, S T; Johnson, J A; Eric Boerwinkle (Pharmacogenomics J, 2014)
Hydrochlorothiazide (HCTZ) is one of the most widely prescribed antihypertensive medications. Although it is well known that HCTZ is associated with hyperglycemia and hypertriglyceridemia, the mechanisms underlying these adverse effects are not well understood. We performed a genome-wide association study and meta-analysis of the change in fasting plasma glucose and triglycerides in response to HCTZ from two different clinical trials: the Pharmacogenomic Evaluation of Antihypertensive Responses and the Genetic Epidemiology of Responses to Antihypertensive studies. Two single-nucleotide polymorphisms (rs12279250 and rs4319515 (r(2)=0.73)), located at 11p15.1 in the NELL1 gene, achieved genome-wide significance for association with change in fasting plasma triglycerides in African Americans, whereby each variant allele was associated with a 28 mg dl(-1) increase in the change in triglycerides. NELL1 encodes a cytoplasmic protein that contains epidermal growth factor-like repeats and has been shown to represses adipogenic differentiation. These findings may represent a novel mechanism underlying HCTZ-induced adverse metabolic effects.
Keywords: Adipogenesis; Antihypertensive Agents; Black or African American; Blood Glucose; Calcium-Binding Proteins; Genome-Wide Association Study; Humans; Hydrochlorothiazide; Hypertension; Lipid Metabolism; Nerve Tissue Proteins; Triglycerides

Human CLP1 mutations alter tRNA biogenesis, affecting both peripheral and central nervous system function. - Karaca, Ender; Weitzer, Stefan; Pehlivan, Davut; Shiraishi, Hiroshi; Gogakos, Tasos; Hanada, Toshikatsu; Jhangiani, Shalini N; Wiszniewski, Wojciech; Withers, Marjorie; Campbell, Ian M; Erdin, Serkan; Isikay, Sedat; et al. (Cell, 2014)
CLP1 is a RNA kinase involved in tRNA splicing. Recently, CLP1 kinase-dead mice were shown to display a neuromuscular disorder with loss of motor neurons and muscle paralysis. Human genome analyses now identified a CLP1 homozygous missense mutation (p.R140H) in five unrelated families, leading to a loss of CLP1 interaction with the tRNA splicing endonuclease (TSEN) complex, largely reduced pre-tRNA cleavage activity, and accumulation of linear tRNA introns. The affected individuals develop severe motor-sensory defects, cortical dysgenesis, and microcephaly. Mice carrying kinase-dead CLP1 also displayed microcephaly and reduced cortical brain volume due to the enhanced cell death of neuronal progenitors that is associated with reduced numbers of cortical neurons. Our data elucidate a neurological syndrome defined by CLP1 mutations that impair tRNA splicing. Reduction of a founder mutation to homozygosity illustrates the importance of rare variations in disease and supports the clan genomics hypothesis.
Keywords: Abnormalities, Multiple; Animals; Central Nervous System Diseases; Cerebrum; Child, Preschool; Endoribonucleases; Female; Fibroblasts; Humans; Infant; Male; Mice; Mice, Inbred CBA; Microcephaly; Mutation, Missense; Nuclear Proteins; Peripheral Nervous System Diseases; Phosphotransferases; RNA, Transfer; RNA-Binding Proteins; Transcription Factors

Human metabolome associates with dietary intake habits among African Americans in the atherosclerosis risk in communities study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Steffen, Lyn M; Eric Boerwinkle (Am J Epidemiol, 2014)
The human metabolome is a measurable outcome of interactions among an individual's inherited genome, microbiome, and dietary intake. We explored the relationship between dietary intake and serum untargeted metabolomic profiles in a subsample of 1,977 African Americans from the Atherosclerosis Risk in Communities (ARIC) Study in 1987-1989. For each metabolite, we conducted linear regression to estimate its relationships with each food group and food category. Potential confounding factors included age, sex, body mass index (weight (kg)/height (m)(2)), energy intake, kidney function, and food groups. We used a modified Bonferroni correction to determine statistical significance. In total, 48 pairs of diet-metabolite associations were identified, including multiple novel associations. The food group "sugar-rich foods and beverages" was inversely associated with 5 metabolites in the 2-hydroxybutyrate-related subpathway and positively associated with 5 γ-glutamyl dipeptides. The hypothesized mechanism of these associations may be through oxidative stress. "Sugar-rich foods and beverages" were also inversely associated with 7 unsaturated long-chain fatty acids. These findings suggest that the contribution of a sugar-rich dietary pattern to increased cardiovascular disease risk may be partially attributed to oxidative stress and disordered lipid profiles. Metabolomics may reveal novel metabolic biomarkers of dietary intake and provide insight into biochemical pathways underlying nutritional effects on disease development.
Keywords: Atherosclerosis; Biomarkers; Black or African American; Diet; Feeding Behavior; Female; Humans; Male; Metabolome; Middle Aged; Overweight; Risk Factors

In silico tools for splicing defect prediction: a survey from the viewpoint of end users. - Jian, Xueqiu; Eric Boerwinkle; Liu, Xiaoming (Genet Med, 2014)
RNA splicing is the process during which introns are excised and exons are spliced. The precise recognition of splicing signals is critical to this process, and mutations affecting splicing comprise a considerable proportion of genetic disease etiology. Analysis of RNA samples from the patient is the most straightforward and reliable method to detect splicing defects. However, currently, the technical limitation prohibits its use in routine clinical practice. In silico tools that predict potential consequences of splicing mutations may be useful in daily diagnostic activities. In this review, we provide medical geneticists with some basic insights into some of the most popular in silico tools for splicing defect prediction, from the viewpoint of end users. Bioinformaticians in relevant areas who are working on huge data sets may also benefit from this review. Specifically, we focus on those tools whose primary goal is to predict the impact of mutations within the 5' and 3' splicing consensus regions: the algorithms used by different tools as well as their major advantages and disadvantages are briefly introduced; the formats of their input and output are summarized; and the interpretation, evaluation, and prospection are also discussed.
Keywords: Computational Biology; Computer Simulation; Genetic Variation; Humans; RNA Precursors; RNA Splicing; Software

Launching genomics into the cloud: deployment of Mercury, a next generation sequence analysis pipeline. - Reid, Jeffrey G; Carroll, Andrew; Veeraraghavan, Narayanan; Dahdouli, Mahmoud; Sundquist, Andreas; English, Adam; Bainbridge, Matthew; White, Simon; Salerno, William; Buhay, Christian; Fuli Yu; Donna M Muzny; et al. (BMC Bioinformatics, 2014)
BACKGROUND: Massively parallel DNA sequencing generates staggering amounts of data. Decreasing cost, increasing throughput, and improved annotation have expanded the diversity of genomics applications in research and clinical practice. This expanding scale creates analytical challenges: accommodating peak compute demand, coordinating secure access for multiple analysts, and sharing validated tools and results. RESULTS: To address these challenges, we have developed the Mercury analysis pipeline and deployed it in local hardware and the Amazon Web Services cloud via the DNAnexus platform. Mercury is an automated, flexible, and extensible analysis workflow that provides accurate and reproducible genomic results at scales ranging from individuals to large cohorts. CONCLUSIONS: By taking advantage of cloud computing and with Mercury implemented on the DNAnexus platform, we have demonstrated a powerful combination of a robust and fully validated software pipeline and a scalable computational resource that, to date, we have applied to more than 10,000 whole genome and whole exome samples.
Keywords: Genome; Genomics; High-Throughput Nucleotide Sequencing; Humans; Internet; Software

Linkage analysis incorporating gene-age interactions identifies seven novel lipid loci: the Family Blood Pressure Program. - Simino, Jeannette; Kume, Rezart; Kraja, Aldi T; Turner, Stephen T; Hanis, Craig L; Sheu, Wayne; Chen, Ida; Jaquish, Cashell; Cooper, Richard S; Chakravarti, Aravinda; Quertermous, Thomas; Eric Boerwinkle; et al. (Atherosclerosis, 2014)
OBJECTIVE: To detect novel loci with age-dependent effects on fasting (≥ 8 h) levels of total cholesterol, high-density lipoprotein, low-density lipoprotein, and triglycerides using 3600 African Americans, 1283 Asians, 3218 European Americans, and 2026 Mexican Americans from the Family Blood Pressure Program (FBPP). METHODS: Within each subgroup (defined by network, race, and sex), we employed stepwise linear regression (retention p ≤ 0.05) to adjust lipid levels for age, age-squared, age-cubed, body-mass-index, current smoking status, current drinking status, field center, estrogen therapy (females only), as well as antidiabetic, antihypertensive, and antilipidemic medication use. For each trait, we pooled the standardized male and female residuals within each network and race and fit a generalized variance components model that incorporated gene-age interactions. We conducted FBPP-wide and race-specific meta-analyses by combining the p-values of each linkage marker across subgroups using a modified Fisher's method. RESULTS: We identified seven novel loci with age-dependent effects; four total cholesterol loci from the meta-analysis of Mexican Americans (on chromosomes 2q24.1, 4q21.21, 8q22.2, and 12p11.23) and three high-density lipoprotein loci from the meta-analysis of all FBPP subgroups (on chromosomes 1p12, 14q11.2, and 21q21.1). These loci lacked significant genome-wide linkage or association evidence in the literature and had logarithm of odds (LOD) score ≥ 3 in the meta-analysis with LOD ≥ 1 in at least two network and race subgroups (exclusively of non-European descent). CONCLUSION: Incorporating gene-age interactions into the analysis of lipids using multi-ethnic cohorts can enhance gene discovery. These interaction loci can guide the selection of families for sequencing studies of lipid-associated variants.
Keywords: Adult; Age Factors; Asian; Asian People; Black or African American; Black People; Blood Pressure; Cholesterol; Cholesterol, HDL; Cholesterol, LDL; Coronary Disease; Ethnicity; Family Health; Female; Genetic Linkage; Genetic Markers; Genetic Variation; Genome-Wide Association Study; Genotype; Humans; Lipids; Male; Mexican Americans; Middle Aged; Phenotype; Quantitative Trait Loci; White People

Metabolomic patterns and alcohol consumption in African Americans in the Atherosclerosis Risk in Communities Study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Steffen, Lyn M; Nettleton, Jennifer A; Eric Boerwinkle (Am J Clin Nutr, 2014)
BACKGROUND: Effects of alcohol consumption on health and disease are complex and involve a number of cellular and metabolic processes. OBJECTIVE: We examined the association between alcohol consumption habits and metabolomic profiles. DESIGN: We conducted a cross-sectional study to explore the association of alcohol consumption habits measured by using a questionnaire with serum metabolites measured by using untargeted mass spectrometry in 1977 African Americans from the Jackson field center in the Atherosclerosis Risk in Communities Study. The whole sample was split into a discovery set (n = 1500) and a replication set (n = 477). Alcohol consumption habits were treated as an ordinal variable, with nondrinkers as the reference group and quartiles of current drinkers as ordinal groups with higher values. For each metabolite, a linear regression was conducted to estimate its relation with alcohol consumption habits separately in both sets. A modified Bonferroni procedure was used in the discovery set to adjust the significance threshold (P < 1.9 × 10⁻⁴). RESULTS: In 356 named metabolites, 39 metabolites were significantly associated with alcohol consumption habits in both discovery and replication sets. In general, alcohol consumption was associated with higher levels of most metabolites such as those in amino acid and lipid pathways and with lower levels of γ-glutamyl dipeptides. Three pathways, 2-hydroxybutyrate-related metabolites, γ-glutamyl dipeptides, and lysophosphatidylcholines, which are considered to be involved in inflammation and oxidation, were associated with incident cardiovascular diseases. CONCLUSIONS: To our knowledge, this is the largest metabolomic study thus far conducted in nonwhites. Metabolomic biomarkers of alcohol consumption were identified and replicated. The results lend new insight into potential mediating effects between alcohol consumption and future health and disease.
Keywords: Alcohol Drinking; Atherosclerosis; Biomarkers; Black or African American; Cohort Studies; Cross-Sectional Studies; Female; Humans; Incidence; Linear Models; Longitudinal Studies; Male; Metabolome; Middle Aged; Prevalence; Prospective Studies; Reproducibility of Results; Risk Factors; United States; Up-Regulation

Molecular findings among patients referred for clinical whole-exome sequencing. - Yang, Yaping; Donna M Muzny; Xia, Fan; Niu, Zhiyv; Person, Richard; Ding, Yan; Ward, Patricia; Braxton, Alicia; Wang, Min; Buhay, Christian; Veeraraghavan, Narayanan; Hawes, Alicia; et al. (JAMA, 2014)
IMPORTANCE: Clinical whole-exome sequencing is increasingly used for diagnostic evaluation of patients with suspected genetic disorders. OBJECTIVE: To perform clinical whole-exome sequencing and report (1) the rate of molecular diagnosis among phenotypic groups, (2) the spectrum of genetic alterations contributing to disease, and (3) the prevalence of medically actionable incidental findings such as FBN1 mutations causing Marfan syndrome. DESIGN, SETTING, AND PATIENTS: Observational study of 2000 consecutive patients with clinical whole-exome sequencing analyzed between June 2012 and August 2014. Whole-exome sequencing tests were performed at a clinical genetics laboratory in the United States. Results were reported by clinical molecular geneticists certified by the American Board of Medical Genetics and Genomics. Tests were ordered by the patient's physician. The patients were primarily pediatric (1756 [88%]; mean age, 6 years; 888 females [44%], 1101 males [55%], and 11 fetuses [1% gender unknown]), demonstrating diverse clinical manifestations most often including nervous system dysfunction such as developmental delay. MAIN OUTCOMES AND MEASURES: Whole-exome sequencing diagnosis rate overall and by phenotypic category, mode of inheritance, spectrum of genetic events, and reporting of incidental findings. RESULTS: A molecular diagnosis was reported for 504 patients (25.2%) with 58% of the diagnostic mutations not previously reported. Molecular diagnosis rates for each phenotypic category were 143/526 (27.2%; 95% CI, 23.5%-31.2%) for the neurological group, 282/1147 (24.6%; 95% CI, 22.1%-27.2%) for the neurological plus other organ systems group, 30/83 (36.1%; 95% CI, 26.1%-47.5%) for the specific neurological group, and 49/244 (20.1%; 95% CI, 15.6%-25.8%) for the nonneurological group. The Mendelian disease patterns of the 527 molecular diagnoses included 280 (53.1%) autosomal dominant, 181 (34.3%) autosomal recessive (including 5 with uniparental disomy), 65 (12.3%) X-linked, and 1 (0.2%) mitochondrial. Of 504 patients with a molecular diagnosis, 23 (4.6%) had blended phenotypes resulting from 2 single gene defects. About 30% of the positive cases harbored mutations in disease genes reported since 2011. There were 95 medically actionable incidental findings in genes unrelated to the phenotype but with immediate implications for management in 92 patients (4.6%), including 59 patients (3%) with mutations in genes recommended for reporting by the American College of Medical Genetics and Genomics. CONCLUSIONS AND RELEVANCE: Whole-exome sequencing provided a potential molecular diagnosis for 25% of a large cohort of patients referred for evaluation of suspected genetic conditions, including detection of rare genetic events and new mutations contributing to disease. The yield of whole-exome sequencing may offer advantages over traditional molecular diagnostic approaches in certain patients.
Keywords: Adolescent; Adult; Child; Child, Preschool; Exome; Female; Fetus; Genetic Diseases, Inborn; Genetic Testing; Genomics; Humans; Incidental Findings; Infant; Infant, Newborn; Male; Molecular Diagnostic Techniques; Mutation; Phenotype; Referral and Consultation; Sequence Analysis, DNA

Mutations in PURA cause profound neonatal hypotonia, seizures, and encephalopathy in 5q31.3 microdeletion syndrome. - Lalani, Seema R; Zhang, Jing; Schaaf, Christian P; Brown, Chester W; Magoulas, Pilar; Tsai, Anne Chun-Hui; El-Gharbawy, Areeg; Wierenga, Klaas J; Bartholomew, Dennis; Fong, Chin-To; Barbaro-Dieber, Tina; Kukolich, Mary K; et al. (Am J Hum Genet, 2014)
5q31.3 microdeletion syndrome is characterized by neonatal hypotonia, encephalopathy with or without epilepsy, and severe developmental delay, and the minimal critical deletion interval harbors three genes. We describe 11 individuals with clinical features of 5q31.3 microdeletion syndrome and de novo mutations in PURA, encoding transcriptional activator protein Pur-α, within the critical region. These data implicate causative PURA mutations responsible for the severe neurological phenotypes observed in this syndrome.
Keywords: Abnormalities, Multiple; Amino Acid Sequence; Animals; Base Sequence; Caenorhabditis elegans; Chromosome Deletion; Chromosome Mapping; Chromosomes, Human, Pair 5; DNA-Binding Proteins; Humans; Molecular Sequence Data; Muscle Hypotonia; Mutation; Seizures; Sequence Analysis, DNA; Syndrome; Transcription Factors

New syndrome with retinitis pigmentosa is caused by nonsense mutations in retinol dehydrogenase RDH11. - Xie, Yajing Angela; Lee, Winston; Cai, Carolyn; Gambin, Tomasz; Nõupuu, Kalev; Sujirakul, Tharikarn; Ayuso, Carmen; Jhangiani, Shalini; Donna M Muzny; Eric Boerwinkle; Richard A Gibbs; Greenstein, Vivienne C; et al. (Hum Mol Genet, 2014)
Retinitis pigmentosa (RP), a genetically heterogeneous group of retinopathies that occur in both non-syndromic and syndromic forms, is caused by mutations in ∼100 genes. Although recent advances in next-generation sequencing have aided in the discovery of novel RP genes, a number of the underlying contributing genes and loci remain to be identified. We investigated three siblings, born to asymptomatic parents of Italian-American descent, who each presented with atypical RP with systemic features, including facial dysmorphologies, psychomotor developmental delays recognized since early childhood, learning disabilities and short stature. RP-associated ophthalmological findings included salt-and-pepper retinopathy, attenuation of the arterioles and generalized rod-cone dysfunction as determined by almost extinguished electroretinogram in 2 of 3 siblings. Atypical for RP features included mottled macula at an early age and peripapillary sparing of the retinal pigment epithelium. Whole-exome sequencing data, queried under a recessive model of inheritance, identified compound heterozygous stop mutations, c.C199T:p.R67* and c.C322T:p.R108*, in the retinol dehydrogenase 11 (RDH11) gene, resulting in a non-functional protein, in all affected children. In summary, deleterious mutations in RDH11, an important enzyme for vision-related and systemic retinoic acid metabolism, cause a new syndrome with RP.
Keywords: Adolescent; Child; Codon, Nonsense; Female; Humans; Male; Oxidoreductases; Pedigree; Phenotype; Retinitis Pigmentosa; Syndrome; Vision Tests; Visual Acuity; Young Adult

No evidence for genome-wide interactions on plasma fibrinogen by smoking, alcohol consumption and body mass index: results from meta-analyses of 80,607 subjects. - Baumert, Jens; Huang, Jie; McKnight, Barbara; Sabater-Lleal, Maria; Steri, Maristella; Chu, Audrey Y; Trompet, Stella; Lopez, Lorna M; Fornage, Myriam; Teumer, Alexander; Tang, Weihong; Rudnicka, Alicja R; et al. (PLoS One, 2014)
Plasma fibrinogen is an acute phase protein playing an important role in the blood coagulation cascade having strong associations with smoking, alcohol consumption and body mass index (BMI). Genome-wide association studies (GWAS) have identified a variety of gene regions associated with elevated plasma fibrinogen concentrations. However, little is yet known about how associations between environmental factors and fibrinogen might be modified by genetic variation. Therefore, we conducted large-scale meta-analyses of genome-wide interaction studies to identify possible interactions of genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentration. The present study included 80,607 subjects of European ancestry from 22 studies. Genome-wide interaction analyses were performed separately in each study for about 2.6 million single nucleotide polymorphisms (SNPs) across the 22 autosomal chromosomes. For each SNP and risk factor, we performed a linear regression under an additive genetic model including an interaction term between SNP and risk factor. Interaction estimates were meta-analysed using a fixed-effects model. No genome-wide significant interaction with smoking status, alcohol consumption or BMI was observed in the meta-analyses. The most suggestive interaction was found for smoking and rs10519203, located in the LOC123688 region on chromosome 15, with a p value of 6.2 × 10(-8). This large genome-wide interaction study including 80,607 participants found no strong evidence of interaction between genetic variants and smoking status, alcohol consumption or BMI on fibrinogen concentrations. Further studies are needed to yield deeper insight in the interplay between environmental factors and gene variants on the regulation of fibrinogen concentrations.
Keywords: Alcohol Drinking; Body Mass Index; Fibrinogen; Gene-Environment Interaction; Genomics; Humans; Smoking

PGM3 mutations cause a congenital disorder of glycosylation with severe immunodeficiency and skeletal dysplasia. - Stray-Pedersen, Asbjørg; Backe, Paul H; Sorte, Hanne S; Mørkrid, Lars; Chokshi, Niti Y; Erichsen, Hans Christian; Gambin, Tomasz; Elgstøen, Katja B P; Bjørås, Magnar; Wlodarski, Marcin W; Krüger, Marcus; Jhangiani, Shalini N; et al. (Am J Hum Genet, 2014)
Human phosphoglucomutase 3 (PGM3) catalyzes the conversion of N-acetyl-glucosamine (GlcNAc)-6-phosphate into GlcNAc-1-phosphate during the synthesis of uridine diphosphate (UDP)-GlcNAc, a sugar nucleotide critical to multiple glycosylation pathways. We identified three unrelated children with recurrent infections, congenital leukopenia including neutropenia, B and T cell lymphopenia, and progression to bone marrow failure. Whole-exome sequencing demonstrated deleterious mutations in PGM3 in all three subjects, delineating their disease to be due to an unsuspected congenital disorder of glycosylation (CDG). Functional studies of the disease-associated PGM3 variants in E. coli cells demonstrated reduced PGM3 activity for all mutants tested. Two of the three children had skeletal anomalies resembling Desbuquois dysplasia: short stature, brachydactyly, dysmorphic facial features, and intellectual disability. However, these additional features were absent in the third child, showing the clinical variability of the disease. Two children received hematopoietic stem cell transplantation of cord blood and bone marrow from matched related donors; both had successful engraftment and correction of neutropenia and lymphopenia. We define PGM3-CDG as a treatable immunodeficiency, document the power of whole-exome sequencing in gene discoveries for rare disorders, and illustrate the utility of genomic analyses in studying combined and variable phenotypes.
Keywords: Bone Diseases, Developmental; Congenital Disorders of Glycosylation; Female; Humans; Immunologic Deficiency Syndromes; Male; Mutation; Pedigree; Phosphoglucomutase

Possible race and gender divergence in association of genetic variations with plasma von Willebrand factor: a study of ARIC and 1000 genome cohorts. - Zhou, Zhou; Fuli Yu; Buchanan, Ashley; Fu, Yuanyuan; Campos, Marco; Wu, Kenneth K; Chambless, Lloyd E; Folsom, Aaron R; Eric Boerwinkle; Dong, Jing-fei (PLoS One, 2014)
The synthesis, secretion and clearance of von Willebrand factor (VWF) are regulated by genetic variations in coding and promoter regions of the VWF gene. We have previously identified 19 single nucleotide polymorphisms (SNPs), primarily in introns that are associated with VWF antigen levels in subjects of European descent. In this study, we conducted race by gender analyses to compare the association of VWF SNPs with VWF antigen among 10,434 healthy Americans of European (EA) or African (AA) descent from the Atherosclerosis Risk in Communities (ARIC) study. Among 75 SNPs analyzed, 13 and 10 SNPs were associated with VWF antigen levels in EA male and EA female subjects, respectively. However, only one SNP (RS1063857) was significantly associated with VWF antigen in AA females and none was in AA males. Haplotype analysis of the ARIC samples and studying racial diversities in the VWF gene from the 1000 genomes database suggest a greater degree of variations in the VWF gene in AA subjects as compared to EA subjects. Together, these data suggest potential race and gender divergence in regulating VWF expression by genetic variations.
Keywords: Atherosclerosis; Black People; Cohort Studies; Demography; Female; Gene Frequency; Genetic Variation; Genome, Human; Haplotypes; Humans; Male; Polymorphism, Single Nucleotide; Sex Characteristics; von Willebrand Factor; White People

Prospective associations of coronary heart disease loci in African Americans using the MetaboChip: the PAGE study. - Franceschini, Nora; Hu, Yijuan; Reiner, Alex P; Buyske, Steven; Nalls, Mike; Yanek, Lisa R; Li, Yun; Hindorff, Lucia A; Cole, Shelley A; Howard, Barbara V; Stafford, Jeanette M; Carty, Cara L; et al. (PLoS One, 2014)
BACKGROUND: Coronary heart disease (CHD) is a leading cause of morbidity and mortality in African Americans. However, there is a paucity of studies assessing genetic determinants of CHD in African Americans. We examined the association of published variants in CHD loci with incident CHD, attempted to fine map these loci, and characterize novel variants influencing CHD risk in African Americans. METHODS AND RESULTS: Up to 8,201 African Americans (including 546 first CHD events) were genotyped using the MetaboChip array in the Atherosclerosis Risk in Communities (ARIC) study and Women's Health Initiative (WHI). We tested associations using Cox proportional hazard models in sex- and study-stratified analyses and combined results using meta-analysis. Among 44 validated CHD loci available in the array, we replicated and fine-mapped the SORT1 locus, and showed same direction of effects as reported in studies of individuals of European ancestry for SNPs in 22 additional published loci. We also identified a SNP achieving array wide significance (MYC: rs2070583, allele frequency 0.02, P = 8.1 × 10(-8)), but the association did not replicate in an additional 8,059 African Americans (577 events) from the WHI, HealthABC and GeneSTAR studies, and in a meta-analysis of 5 cohort studies of European ancestry (24,024 individuals including 1,570 cases of MI and 2,406 cases of CHD) from the CHARGE Consortium. CONCLUSIONS: Our findings suggest that some CHD loci previously identified in individuals of European ancestry may be relevant to incident CHD in African Americans.
Keywords: Adaptor Proteins, Vesicular Transport; Black or African American; Coronary Disease; Female; Genetic Association Studies; Genetic Predisposition to Disease; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Prospective Studies; Proto-Oncogene Proteins c-myc

Sequence analysis of six blood pressure candidate regions in 4,178 individuals: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) targeted sequencing study. - Morrison, Alanna C; Bis, Joshua C; Hwang, Shih-Jen; Ehret, Georg B; Lumley, Thomas; Rice, Kenneth; Donna M Muzny; Richard A Gibbs; Eric Boerwinkle; Psaty, Bruce M; Chakravarti, Aravinda; Levy, Daniel (PLoS One, 2014)
BACKGROUND: Genome-wide association studies (GWAS) identified multiple loci for blood pressure (BP) and hypertension. Six genes--ATP2B1, CACNB2, CYP17A1, JAG1, PLEKHA7, and SH2B3--were evaluated for sequence variation with large effects on systolic blood pressure (SBP), diastolic blood pressure (DBP), pulse pressure (PP), and mean arterial pressure (MAP). METHODS AND RESULTS: Targeted genomic sequence was determined in 4,178 European ancestry participants from the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium. Common variants (≥50 minor allele copies) were evaluated individually and rare variants (minor allele frequency, MAF≤1%) were aggregated by locus. 464 common variants were identified across the 6 genes. An upstream CYP17A1 variant, rs11191416 (MAF = 0.09), was the most significant association for SBP (P = 0.0005); however the association was attenuated (P = 0.0469) after conditioning on the GWAS index single nucleotide polymorphism (SNP). A PLEKHA7 intronic variant was the strongest DBP association (rs12806040, MAF = 0.007, P = 0.0006) and was not in LD (r² = 0.01) with the GWAS SNP. A CACNB2 intronic SNP, rs1571787, was the most significant association with PP (MAF = 0.27, P = 0.0003), but was not independent from the GWAS SNP (r² = 0.34). Three variants (rs6163 and rs743572 in the CYP17A1 region and rs112467382 in PLEKHA7) were associated with BP traits (P<0.001). Rare variation, aggregately assessed in the 6 regions, was not significantly associated with BP measures. CONCLUSION: Six targeted gene regions, previously identified by GWAS, did not harbor novel variation with large effects on BP in this sample.
Keywords: Aging; Blood Pressure; Cohort Studies; Heart; Humans; Sequence Analysis

Serum metabolomic profiling and incident CKD among African Americans. - Yu, Bing; Zheng, Yan; Nettleton, Jennifer A; Alexander, Danny; Coresh, Josef; Eric Boerwinkle (Clin J Am Soc Nephrol, 2014)
BACKGROUND AND OBJECTIVES: Novel biomarkers that more accurately reflect kidney function and predict future CKD are needed. The human metabolome is the product of multiple physiologic or pathophysiologic processes and may provide novel insight into disease etiology and progression. This study investigated whether estimated kidney function would be associated with multiple metabolites and whether selected metabolomic factors would be independent risk factors for incident CKD. DESIGN, SETTING, PARTICIPANTS, & MEASUREMENTS: In total, 1921 African Americans free of CKD with a median of 19.6 years follow-up among the Atherosclerosis Risk in Communities Study were included. A total of 204 serum metabolites quantified by untargeted gas chromatography-mass spectrometry and liquid chromatography-mass spectrometry was analyzed by both linear regression for the cross-sectional associations with eGFR (specified by the Chronic Kidney Disease Epidemiology Collaboration equation) and Cox proportional hazards model for the longitudinal associations with incident CKD. RESULTS: Forty named and 34 unnamed metabolites were found to be associated with eGFR specified by the Chronic Kidney Disease Epidemiology Collaboration equation with creatine and 3-indoxyl sulfate showing the strongest positive (2.8 ml/min per 1.73 m(2) per +1 SD; 95% confidence interval, 2.1 to 3.5) and negative association (-14.2 ml/min per 1.73 m(2) per +1 SD; 95% confidence interval, -17.0 to -11.3), respectively. Two hundred four incident CKD events with a median follow-up time of 19.6 years were included in the survival analyses. Higher levels of 5-oxoproline (hazard ratio, 0.70; 95% confidence interval, 0.60 to 0.82) and 1,5-anhydroglucitol (hazard ratio, 0.68; 95% confidence interval, 0.58 to 0.80) were significantly related to lower risk of incident CKD, and the associations did not appreciably change when mutually adjusted. CONCLUSIONS: These data identify a large number of metabolites associated with kidney function as well as two metabolites that are candidate risk factors for CKD and may provide new insights into CKD biomarker identification.
Keywords: Biomarkers; Black or African American; Chromatography, Liquid; Creatine; Cross-Sectional Studies; Deoxyglucose; Female; Gas Chromatography-Mass Spectrometry; Humans; Incidence; Indican; Kidney; Linear Models; Longitudinal Studies; Male; Metabolomics; Middle Aged; Proportional Hazards Models; Pyrrolidonecarboxylic Acid; Renal Insufficiency, Chronic; Risk Factors; Time Factors; United States

Targeted sequencing in candidate genes for atrial fibrillation: the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study. - Lin, Honghuang; Sinner, Moritz F; Brody, Jennifer A; Arking, Dan E; Lunetta, Kathryn L; Rienstra, Michiel; Lubitz, Steven A; Magnani, Jared W; Sotoodehnia, Nona; McKnight, Barbara; McManus, David D; Eric Boerwinkle; et al. (Heart Rhythm, 2014)
BACKGROUND: Genome-wide association studies (GWAS) have identified common genetic variants that predispose to atrial fibrillation (AF). It is unclear whether rare and low-frequency variants in genes implicated by such GWAS confer additional risk of AF. OBJECTIVE: To study the association of genetic variants with AF at GWAS top loci. METHODS: In the Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Targeted Sequencing Study, we selected and sequenced 77 target gene regions from GWAS loci of complex diseases or traits, including 4 genes hypothesized to be related to AF (PRRX1, CAV1, CAV2, and ZFHX3). Sequencing was performed in participants with (n = 948) and without (n = 3330) AF from the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Massachusetts General Hospital. RESULTS: One common variant (rs11265611; P = 1.70 × 10(-6)) intronic to IL6R (interleukin-6 receptor gene) was significantly associated with AF after Bonferroni correction (odds ratio 0.70; 95% confidence interval 0.58-0.85). The variant was not genotyped or imputed by prior GWAS, but it is in linkage disequilibrium (r(2) = .69) with the single-nucleotide polymorphism, with the strongest association with AF so far at this locus (rs4845625). In the rare variant joint analysis, damaging variants within the PRRX1 region showed significant association with AF after Bonferroni correction (P = .01). CONCLUSIONS: We identified 1 common single-nucleotide polymorphism and 1 gene region that were significantly associated with AF. Future sequencing efforts with larger sample sizes and more comprehensive genome coverage are anticipated to identify additional AF-related variants.
Keywords: Aged; Atrial Fibrillation; Female; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Homeodomain Proteins; Humans; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide; Receptors, Interleukin-6

Whole exome sequencing identifies novel genes for fetal hemoglobin response to hydroxyurea in children with sickle cell anemia. - Sheehan, Vivien A; Crosby, Jacy R; Aniko Sabo; Mortier, Nicole A; Howard, Thad A; Donna M Muzny; Dugan-Perez, Shannon; Aygun, Banu; Nottage, Kerri A; Eric Boerwinkle; Richard A Gibbs; Ware, Russell E; et al. (PLoS One, 2014)
Hydroxyurea has proven efficacy in children and adults with sickle cell anemia (SCA), but with considerable inter-individual variability in the amount of fetal hemoglobin (HbF) produced. Sibling and twin studies indicate that some of that drug response variation is heritable. To test the hypothesis that genetic modifiers influence pharmacological induction of HbF, we investigated phenotype-genotype associations using whole exome sequencing of children with SCA treated prospectively with hydroxyurea to maximum tolerated dose (MTD). We analyzed 171 unrelated patients enrolled in two prospective clinical trials, all treated with dose escalation to MTD. We examined two MTD drug response phenotypes: HbF (final %HbF minus baseline %HbF), and final %HbF. Analyzing individual genetic variants, we identified multiple low frequency and common variants associated with HbF induction by hydroxyurea. A validation cohort of 130 pediatric sickle cell patients treated to MTD with hydroxyurea was genotyped for 13 non-synonymous variants with the strongest association with HbF response to hydroxyurea in the discovery cohort. A coding variant in Spalt-like transcription factor, or SALL2, was associated with higher final HbF in this second independent replication sample and SALL2 represents an outstanding novel candidate gene for further investigation. These findings may help focus future functional studies and provide new insights into the pharmacological HbF upregulation by hydroxyurea in patients with SCA.
Keywords: Anemia, Sickle Cell; Child; Cohort Studies; DNA-Binding Proteins; Dose-Response Relationship, Drug; Exome; Fetal Hemoglobin; Genomics; Humans; Hydroxyurea; Maximum Tolerated Dose; Open Reading Frames; Phenotype; Prospective Studies; Sequence Analysis, DNA; Transcription Factors; Treatment Outcome

Whole exome sequencing identifies three novel mutations in ANTXR1 in families with GAPO syndrome. - Bayram, Yavuz; Pehlivan, Davut; Karaca, Ender; Gambin, Tomasz; Jhangiani, Shalini N; Erdin, Serkan; Gonzaga-Jauregui, Claudia; Wiszniewski, Wojciech; Donna M Muzny; Elcioglu, Nursel H; Yildirim, M Selman; Bozkurt, Banu; et al. (Am J Med Genet A, 2014)
GAPO syndrome (OMIM#230740) is the acronym for growth retardation, alopecia, pseudoanodontia, and optic atrophy. About 35 cases have been reported, making it among one of the rarest recessive conditions. Distinctive craniofacial features including alopecia, rarefaction of eyebrows and eyelashes, frontal bossing, high forehead, mid-facial hypoplasia, hypertelorism, and thickened eyelids and lips make GAPO syndrome a clinically recognizable phenotype. While this genomic study was in progress mutations in ANTXR1 were reported to cause GAPO syndrome. In our study we performed whole exome sequencing (WES) for five affected individuals from three Turkish kindreds segregating the GAPO trait. Exome sequencing analysis identified three novel homozygous mutations including; one frame-shift (c.1220_1221insT; p.Ala408Cysfs*2), one splice site (c.411A>G; p.Gln137Gln), and one non-synonymous (c.1150G>A; p.Gly384Ser) mutation in the ANTXR1 gene. Our studies expand the allelic spectrum in this rare condition and potentially provide insight into the role of ANTXR1 in the regulation of the extracellular matrix.
Keywords: Adolescent; Adult; Alopecia; Anodontia; Base Sequence; Child; Chromosome Segregation; DNA Mutational Analysis; Exome; Facies; Family; Female; Growth Disorders; Humans; Male; Microfilament Proteins; Molecular Sequence Data; Mutation; Neoplasm Proteins; Optic Atrophies, Hereditary; Pedigree; Protein Structure, Tertiary; Receptors, Cell Surface

Analysis of rare, exonic variation amongst subjects with autism spectrum disorders and population controls. - Liu, Li; Aniko Sabo; Neale, Benjamin M; Nagaswamy, Uma; Stevens, Christine; Lim, Elaine; Bodea, Corneliu A; Donna M Muzny; Reid, Jeffrey G; Banks, Eric; Coon, Hillary; DePristo, Mark; et al. (PLoS Genet, 2013)
We report on results from whole-exome sequencing (WES) of 1,039 subjects diagnosed with autism spectrum disorders (ASD) and 870 controls selected from the NIMH repository to be of similar ancestry to cases. The WES data came from two centers using different methods to produce sequence and to call variants from it. Therefore, an initial goal was to ensure the distribution of rare variation was similar for data from different centers. This proved straightforward by filtering called variants by fraction of missing data, read depth, and balance of alternative to reference reads. Results were evaluated using seven samples sequenced at both centers and by results from the association study. Next we addressed how the data and/or results from the centers should be combined. Gene-based analyses of association was an obvious choice, but should statistics for association be combined across centers (meta-analysis) or should data be combined and then analyzed (mega-analysis)? Because of the nature of many gene-based tests, we showed by theory and simulations that mega-analysis has better power than meta-analysis. Finally, before analyzing the data for association, we explored the impact of population structure on rare variant analysis in these data. Like other recent studies, we found evidence that population structure can confound case-control studies by the clustering of rare variants in ancestry space; yet, unlike some recent studies, for these data we found that principal component-based analyses were sufficient to control for ancestry and produce test statistics with appropriate distributions. After using a variety of gene-based tests and both meta- and mega-analysis, we found no new risk genes for ASD in this sample. Our results suggest that standard gene-based tests will require much larger samples of cases and controls before being effective for gene discovery, even for a disorder like ASD.
Keywords: Case-Control Studies; Child; Child Development Disorders, Pervasive; Exome; Genetic Predisposition to Disease; Genetic Variation; Genome-Wide Association Study; Humans; Population Control; Sequence Analysis, DNA; Software

APOE modulates the correlation between triglycerides, cholesterol, and CHD through pleiotropy, and gene-by-gene interactions. - Maxwell, Taylor J; Ballantyne, Christie M; Cheverud, James M; Guild, Cameron S; Ndumele, Chiadi E; Eric Boerwinkle (Genetics, 2013)
Relationship loci (rQTL) exist when the correlation between multiple traits varies by genotype. rQTL often occur due to gene-by-gene (G × G) or gene-by-environmental interactions, making them a powerful tool for detecting G × G. Here we present an empirical analysis of apolipoprotein E (APOE) with respect to lipid traits and incident CHD leading to the discovery of loci that interact with APOE to affect these traits. We found that the relationship between total cholesterol (TC) and triglycerides (ln TG) varies by APOE isoform genotype in African-American (AA) and European-American (EA) populations. The e2 allele is associated with strong correlation between ln TG and TC while the e4 allele leads to little or no correlation. This led to a priori hypotheses that APOE genotypes affect the relationship of TC and/or ln TG with incident CHD. We found that APOE*TC was significant (P = 0.016) for AA but not EA while APOE*ln TG was significant for EA (P = 0.027) but not AA. In both cases, e2e2 and e2e3 had strong relationships between TC and ln TG with CHD while e2e4 and e4e4 results in little or no relationship between TC and ln TG with CHD. Using ARIC GWAS data, scans for loci that significantly interact with APOE produced four loci for African Americans (one CHD, one TC, and two HDL). These interactions contribute to the rQTL pattern. rQTL are a powerful tool to identify loci that modify the relationship between risk factors and disease and substantially increase statistical power for detecting G × G.
Keywords: Alleles; Apolipoproteins E; Black or African American; Cholesterol; Coronary Disease; Epistasis, Genetic; Female; Genetic Pleiotropy; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Triglycerides; White People

Association of genome-wide variation with highly sensitive cardiac troponin-T levels in European Americans and Blacks: a meta-analysis from atherosclerosis risk in communities and cardiovascular health studies. - Yu, Bing; Barbalic, Maja; Brautbar, Ariel; Nambi, Vijay; Hoogeveen, Ron C; Tang, Weihong; Mosley, Thomas H; Rotter, Jerome I; deFilippi, Christopher R; O'Donnell, Christopher J; Kathiresan, Sekar; Rice, Ken; et al. (Circ Cardiovasc Genet, 2013)
BACKGROUND: High levels of cardiac troponin T, measured by a highly sensitive assay (hs-cTnT), are strongly associated with incident coronary heart disease and heart failure. To date, no large-scale genome-wide association study of hs-cTnT has been reported. We sought to identify novel genetic variants that are associated with hs-cTnT levels. METHODS AND RESULTS: We performed a genome-wide association in 9491 European Americans and 2053 blacks free of coronary heart disease and heart failure from 2 prospective cohorts: the Atherosclerosis Risk in Communities Study and the Cardiovascular Health Study. Genome-wide association studies were conducted in each study and race stratum. Fixed-effect meta-analyses combined the results of linear regression from 2 cohorts within each race stratum and then across race strata to produce overall estimates and probability values. The meta-analysis identified a significant association at chromosome 8q13 (rs10091374; P=9.06×10(-9)) near the nuclear receptor coactivator 2 (NCOA2) gene. Overexpression of NCOA2 can be detected in myoblasts. An additional analysis using logistic regression and the clinically motivated 99th percentile cut point detected a significant association at 1q32 (rs12564445; P=4.73×10(-8)) in the gene TNNT2, which encodes the cardiac troponin T protein itself. The hs-cTnT-associated single-nucleotide polymorphisms were not associated with coronary heart disease in a large case-control study, but rs12564445 was significantly associated with incident heart failure in Atherosclerosis Risk in Communities Study European Americans (hazard ratio=1.16; P=0.004). CONCLUSIONS: We identified 2 loci, near NCOA2 and in the TNNT2 gene, at which variation was significantly associated with hs-cTnT levels. Further use of the new assay should enable replication of these results.
Keywords: Atherosclerosis; Black People; Female; Genome-Wide Association Study; Humans; Male; Middle Aged; Nuclear Receptor Coactivator 2; Polymorphism, Single Nucleotide; Prospective Studies; Residence Characteristics; Risk Factors; Troponin T; White People

Associations between metabolomic compounds and incident heart failure among African Americans: the ARIC Study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Manolio, Teri A; Aguilar, David; Coresh, Josef; Heiss, Gerardo; Eric Boerwinkle; Nettleton, Jennifer A (Am J Epidemiol, 2013)
Heart failure is more prevalent among African Americans than in the general population. Metabolomic studies among African Americans may efficiently identify novel biomarkers of heart failure. We used untargeted methods to measure 204 stable serum metabolites and evaluated their associations with incident heart failure hospitalization (n = 276) after a median follow-up of 20 years (1987-2008) by using Cox regression in data from 1,744 African Americans aged 45-64 years without heart failure at baseline from the Jackson, Mississippi, field center of the Atherosclerosis Risk in Communities (ARIC) Study. After adjustment for established risk factors, we found that 16 metabolites (6 named with known structural identities and 10 unnamed with unknown structural identities, the latter denoted by using the format X-12345) were associated with incident heart failure (P < 0.0004 based on a modified Bonferroni procedure). Of the 6 named metabolites, 4 are involved in amino acid metabolism, 1 (prolylhydroxyproline) is a dipeptide, and 1 (erythritol) is a sugar alcohol. After additional adjustment for kidney function, 2 metabolites remained associated with incident heart failure (for metabolite X-11308, hazard ratio = 0.75, 95% confidence interval: 0.65, 0.86; for metabolite X-11787, hazard ratio = 1.23, 95% confidence interval: 1.10, 1.37). Further structural analysis revealed X-11308 to be a dihydroxy docosatrienoic acid and X-11787 to be an isoform of either hydroxyleucine or hydroxyisoleucine. Our metabolomic analysis revealed novel biomarkers associated with incident heart failure independent of traditional risk factors.
Keywords: Age Distribution; Atherosclerosis; Biomarkers; Black or African American; Comorbidity; Diabetes Mellitus; Female; Follow-Up Studies; Heart Failure; Humans; Hypertension; Kidney Diseases; Male; Metabolomics; Middle Aged; Mississippi; Obesity; Proportional Hazards Models; Sedentary Behavior

Best practices and joint calling of the HumanExome BeadChip: the CHARGE Consortium. - Grove, Megan L; Yu, Bing; Cochran, Barbara J; Haritunians, Talin; Bis, Joshua C; Taylor, Kent D; Hansen, Mark; Borecki, Ingrid B; Cupples, L Adrienne; Fornage, Myriam; Gudnason, Vilmundur; Harris, Tamara B; et al. (PLoS One, 2013)
Genotyping arrays are a cost effective approach when typing previously-identified genetic polymorphisms in large numbers of samples. One limitation of genotyping arrays with rare variants (e.g., minor allele frequency [MAF] <0.01) is the difficulty that automated clustering algorithms have to accurately detect and assign genotype calls. Combining intensity data from large numbers of samples may increase the ability to accurately call the genotypes of rare variants. Approximately 62,000 ethnically diverse samples from eleven Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium cohorts were genotyped with the Illumina HumanExome BeadChip across seven genotyping centers. The raw data files for the samples were assembled into a single project for joint calling. To assess the quality of the joint calling, concordance of genotypes in a subset of individuals having both exome chip and exome sequence data was analyzed. After exclusion of low performing SNPs on the exome chip and non-overlap of SNPs derived from sequence data, genotypes of 185,119 variants (11,356 were monomorphic) were compared in 530 individuals that had whole exome sequence data. A total of 98,113,070 pairs of genotypes were tested and 99.77% were concordant, 0.14% had missing data, and 0.09% were discordant. We report that joint calling allows the ability to accurately genotype rare variation using array technology when large sample sizes are available and best practices are followed. The cluster file from this experiment is available at www.chargeconsortium.com/main/exomechip.
Keywords: Aging; Alleles; Cluster Analysis; Cohort Studies; Exome; Female; Gene Frequency; Genomics; Genotype; Heart; Humans; Male; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; Racial Groups; Sample Size; Self Report; Sequence Analysis, DNA

Characterizing polymorphisms and allelic diversity of von Willebrand factor gene in the 1000 Genomes. - Wang, Q Y; Song, J; Richard A Gibbs; Eric Boerwinkle; Dong, J F; Yu, F L (J Thromb Haemost, 2013)
BACKGROUND: The von Willebrand factor (VWF) gene is highly polymorphic, with variants correlated with VWF antigen levels, adhesion activity, clearance and factor VIII binding. VWF mutations are detected in patients with von Willebrand disease (VWD), whereas polymorphic variants could be associated with thrombosis. However, information on the ethnic diversity of VWF variants and their association with diseases is limited. OBJECTIVES: To characterize novel VWF variants from different ethnicities in the general population. PATIENTS/METHODS: We analyzed samples from 1092 subjects of 14 ethnicities available in the 1000 Genomes database for VWF variants and their potential functional impacts. RESULTS: We identified 2728 SNPs and 91 insertions and deletions that had a high level of ethnic diversity, with Africans having the highest number of variants. The highest level of diversity was found in the D' and D2 domains. Among 94 non-synonymous variants, 31 were predicted to be deleterious, including 19 that were previously associated with VWD. Most of these 'VWD variants' had allele frequencies consistent with disease incidence in European subjects, but some had a significantly higher frequency in other ethnicities. The mutations R2185Q, H817Q and M740I associated with type 1 and type 2N VWD were present in more than 13% of African subjects. CONCLUSIONS: These results highlight the complexity of VWF variations in different ethnic groups and emphasize the importance of interrogating variations on multiple ethnic backgrounds for associations with bleeding and thrombosis.
Keywords: Asian People; Black or African American; Black People; Databases, Genetic; DNA Mutational Analysis; Ethnicity; Gene Frequency; Genetic Predisposition to Disease; Hemostasis; Human Genome Project; Humans; Incidence; Mutation; Phenotype; Polymorphism, Single Nucleotide; von Willebrand Diseases; von Willebrand Factor; White People

dbNSFP v2.0: a database of human non-synonymous SNVs and their functional predictions and annotations. - Liu, Xiaoming; Jian, Xueqiu; Eric Boerwinkle (Hum Mutat, 2013)
dbNSFP is a database developed for functional prediction and annotation of all potential non-synonymous single-nucleotide variants (nsSNVs) in the human genome. This database significantly facilitates the process of querying predictions and annotations from different databases/web-servers for large amounts of nsSNVs discovered in exome-sequencing studies. Here we report a recent major update of the database to version 2.0. We have rebuilt the SNV collection based on GENCODE 9 and currently the database includes 87,347,043 nsSNVs and 2,270,742 essential splice site SNVs (an 18% increase compared to dbNSFP v1.0). For each nsSNV dbNSFP v2.0 has added two prediction scores (MutationAssessor and FATHMM) and two conservation scores (GERP++ and SiPhy). The original five prediction and conservation scores in v1.0 (SIFT, Polyphen2, LRT, MutationTaster and PhyloP) have been updated. Rich functional annotations for SNVs and genes have also been added into the new version, including allele frequencies observed in the 1000 Genomes Project phase 1 data and the NHLBI Exome Sequencing Project, various gene IDs from different databases, functional descriptions of genes, gene expression and gene interaction information, among others. dbNSFP v2.0 is freely available for download at http://sites.google.com/site/jpopgen/dbNSFP.
Keywords: Computational Biology; Databases, Nucleic Acid; Exome; Gene Frequency; Genome, Human; Humans; Molecular Sequence Annotation; Polymorphism, Single Nucleotide; Software

Exon sequencing of PAX3 and T (brachyury) in cases with spina bifida. - Agopian, A J; Bhalla, Angela D; Eric Boerwinkle; Finnell, Richard H; Grove, Megan L; Hixson, James E; Shimmin, Lawrence C; Sewda, Anshuman; Stuart, Colin; Zhong, Yu; Zhu, Huiping; Mitchell, Laura E (Birth Defects Res A Clin Mol Teratol, 2013)
BACKGROUND: Based on studies in animals and humans, PAX3 and T (brachyury) are candidate genes for spina bifida. However, neither gene has been definitively identified as a risk factor for this condition. METHODS: Sanger sequencing was used to identify variants in all PAX3 and T exons and promoter regions in 114 spina bifida cases. For known variants, allele frequencies in cases were compared with those from public databases using unadjusted odds ratios. Novel variants were genotyped in parents and assessed for predicted functional impact. RESULTS: We identified common variants in PAX3 (n = 2) and T (n = 3) for which the allele frequencies in cases were significantly different from those reported in at least one public database. We also identified novel variants in both PAX3 (n = 11) and T (n = 1) in spina bifida cases. Several of the novel PAX3 variants are predicted to be highly conserved and/or impact gene function or expression. CONCLUSION: These studies provide some evidence that common variants of PAX3 and T are associated with spina bifida. Rare and novel variants in these genes were also identified in affected individuals. However, additional studies will be required to determine whether these variants influence the risk of spina bifida.
Keywords: Base Sequence; Exons; Fetal Proteins; Gene Frequency; Genetic Association Studies; Genetic Variation; Genotype; Humans; Molecular Sequence Data; Odds Ratio; Paired Box Transcription Factors; PAX3 Transcription Factor; Promoter Regions, Genetic; Sequence Analysis, DNA; Spinal Dysraphism; T-Box Domain Proteins; United States

Fat mass and obesity gene and cognitive decline: the Atherosclerosis Risk in Communities Study. - Bressler, Jan; Fornage, Myriam; Demerath, Ellen W; Knopman, David S; Monda, Keri L; North, Kari E; Penman, Alan; Mosley, Thomas H; Eric Boerwinkle (Neurology, 2013)
OBJECTIVE: To determine whether 4 genetic variants in the fat mass and obesity associated gene (FTO) identified in genome-wide association studies of diabetes and obesity are associated with cognitive change in midlife in the Atherosclerosis Risk in Communities (ARIC) Study. METHODS: ARIC is a prospective cohort study of the development of atherosclerosis in 15,792 individuals aged 45 to 64 years at baseline from 1986 to 1989. FTO is highly expressed in human fetal and adult brain, and a single nucleotide polymorphism in FTO has previously been associated with reduced brain volume in cognitively normal subjects. Since a relationship between brain atrophy and diminished cognitive function has been demonstrated in ARIC participants, general linear models were used to evaluate the association between 6-year change in scores on 3 neuropsychological tests and FTO genotype. RESULTS: In a sample of 8,364 white and 2,083 African American men and women with no clinical history of stroke, significantly greater mean change in performance on the Delayed Word Recall Test was associated with 2 of 4 FTO single nucleotide polymorphisms examined (rs9939609, rs805136, rs17817449, and rs1421085) in whites but not in African Americans (p ≤ 0.002). The association of the FTO polymorphisms with cognitive change was independent of potential confounding clinical and demographic variables including age, gender, education, diabetes, hypertension, and body mass index. CONCLUSIONS: Further studies will be needed to clarify the biological mechanisms and genetic pathways through which variants in FTO can increase susceptibility to decline in verbal memory detectable in middle-aged, community-dwelling adults.
Keywords: Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Black or African American; Body Mass Index; Cognition Disorders; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Male; Middle Aged; Neuropsychological Tests; Polymorphism, Single Nucleotide; Prospective Studies; Proteins; White People

A genome-wide association study for venous thromboembolism: the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) consortium. - Tang, Weihong; Teichert, Martina; Chasman, Daniel I; Heit, John A; Morange, Pierre-Emmanuel; Li, Guo; Pankratz, Nathan; Leebeek, Frank W; Paré, Guillaume; de Andrade, Mariza; Tzourio, Christophe; Psaty, Bruce M; et al. (Genet Epidemiol, 2013)
Venous thromboembolism (VTE) is a common, heritable disease resulting in high rates of hospitalization and mortality. Yet few associations between VTE and genetic variants, all in the coagulation pathway, have been established. To identify additional genetic determinants of VTE, we conducted a two-stage genome-wide association study (GWAS) among individuals of European ancestry in the extended cohorts for heart and aging research in genomic epidemiology (CHARGE) VTE consortium. The discovery GWAS comprised 1,618 incident VTE cases out of 44,499 participants from six community-based studies. Genotypes for genome-wide single-nucleotide polymorphisms (SNPs) were imputed to approximately 2.5 million SNPs in HapMap and association with VTE assessed using study-design appropriate regression methods. Meta-analysis of these results identified two known loci, in F5 and ABO. Top 1,047 tag SNPs (P ≤ 0.0016) from the discovery GWAS were tested for association in an additional 3,231 cases and 3,536 controls from three case-control studies. In the combined data from these two stages, additional genome-wide significant associations were observed on 4q35 at F11 (top SNP rs4253399, intronic to F11) and on 4q28 at FGG (rs6536024, 9.7 kb from FGG; P < 5.0 × 10(-13) for both). The associations at the FGG locus were not completely explained by previously reported variants. Loci at or near SUSD1 and OTUD7A showed borderline yet novel associations (P < 5.0 × 10(-6) ) and constitute new candidate genes. In conclusion, this large GWAS replicated key genetic associations in F5 and ABO, and confirmed the importance of F11 and FGG loci for VTE. Future studies are warranted to better characterize the associations with F11 and FGG and to replicate the new candidate associations.
Keywords: Aged; Aging; Case-Control Studies; Cohort Studies; Female; Genome-Wide Association Study; Humans; Male; Meta-Analysis as Topic; Middle Aged; Polymorphism, Single Nucleotide; Regression Analysis; Risk Factors; Venous Thromboembolism

Genome-wide association study of a heart failure related metabolomic profile among African Americans in the Atherosclerosis Risk in Communities (ARIC) study. - Yu, Bing; Zheng, Yan; Alexander, Danny; Manolio, Teri A; Alonso, Alvaro; Nettleton, Jennifer A; Eric Boerwinkle (Genet Epidemiol, 2013)
Both the prevalence and incidence of heart failure (HF) are increasing, especially among African Americans, but no large-scale, genome-wide association study (GWAS) of HF-related metabolites has been reported. We sought to identify novel genetic variants that are associated with metabolites previously reported to relate to HF incidence. GWASs of three metabolites identified previously as risk factors for incident HF (pyroglutamine, dihydroxy docosatrienoic acid, and X-11787, being either hydroxy-leucine or hydroxy-isoleucine) were performed in 1,260 African Americans free of HF at the baseline examination of the Atherosclerosis Risk in Communities (ARIC) study. A significant association on chromosome 5q33 (rs10463316, MAF = 0.358, P-value = 1.92 × 10(-10) ) was identified for pyroglutamine. One region on chromosome 2p13 contained a nonsynonymous substitution in N-acetyltransferase 8 (NAT8) was associated with X-11787 (rs13538, MAF = 0.481, P-value = 1.71 × 10(-23) ). The smallest P-value for dihydroxy docosatrienoic acid was rs4006531 on chromosome 8q24 (MAF = 0.400, P-value = 6.98 × 10(-7) ). None of the above SNPs were individually associated with incident HF, but a genetic risk score (GRS) created by summing the most significant risk alleles from each metabolite detected 11% greater risk of HF per allele. In summary, we identified three loci associated with previously reported HF-related metabolites. Further use of metabolomics technology will facilitate replication of these findings in independent samples.
Keywords: Acetyltransferases; Alleles; Atherosclerosis; Black or African American; Chromosomes, Human, Pair 2; Chromosomes, Human, Pair 5; Cohort Studies; Fatty Acids, Unsaturated; Female; Genetic Loci; Genetic Predisposition to Disease; Genome-Wide Association Study; Heart Failure; Humans; Incidence; Isoleucine; Leucine; Male; Metabolome; Metabolomics; Middle Aged; Polymorphism, Single Nucleotide; Pyrrolidonecarboxylic Acid; Risk Factors

Metabolomics and incident hypertension among blacks: the atherosclerosis risk in communities study. - Zheng, Yan; Yu, Bing; Alexander, Danny; Mosley, Thomas H; Heiss, Gerardo; Nettleton, Jennifer A; Eric Boerwinkle (Hypertension, 2013)
Development of hypertension is influenced by genes, environmental effects, and their interactions, and the human metabolome is a measurable manifestation of gene-environment interaction. We explored the metabolomic antecedents of developing incident hypertension in a sample of blacks, a population with a high prevalence of hypertension and its comorbidities. We examined 896 black normotensives (565 women; aged, 45-64 years) from the Atherosclerosis Risk in Communities study, whose metabolome was measured in serum collected at the baseline examination and analyzed by high-throughput methods. The analyses presented here focus on 204 stably measured metabolites during a period of 4 to 6 weeks. Weibull parametric models considering interval censored data were used to assess the hazard ratio for incident hypertension. We used a modified Bonferroni correction accounting for the correlations among metabolites to define a threshold for statistical significance (P<3.9 × 10(-4)). During 10 years of follow-up, 38% of baseline normotensives developed hypertension (n=344). With adjustment for traditional risk factors and estimated glomerular filtration rate, each +1SD difference in baseline 4-hydroxyhippurate, a product of gut microbial fermentation, was associated with 17% higher risk of hypertension (P=2.5 × 10(-4)), which remained significant after adjusting for both baseline systolic and diastolic blood pressure (P=3.8 × 10(-4)). After principal component analyses, a sex steroids pattern was significantly associated with risk of incident hypertension (highest versus lowest quintile hazard ratio, 1.72; 95% confidence interval, 1.05-2.82; P for trend, 0.03), and stratified analyses suggested that this association was consistent in both sexes. Metabolomic analyses identify novel pathways in the pathogenesis of hypertension.
Keywords: Atherosclerosis; Black People; Female; High-Throughput Screening Assays; Humans; Hypertension; Male; Metabolomics; Middle Aged; Principal Component Analysis; Risk Factors

Mutations in VRK1 associated with complex motor and sensory axonal neuropathy plus microcephaly. - Gonzaga-Jauregui, Claudia; Lotze, Timothy; Jamal, Leila; Penney, Samantha; Campbell, Ian M; Pehlivan, Davut; Hunter, Jill V; Woodbury, Suzanne L; Raymond, Gerald; Adesina, Adekunle M; Jhangiani, Shalini N; Reid, Jeffrey G; et al. (JAMA Neurol, 2013)
IMPORTANCE: Patients with rare diseases and complex clinical presentations represent a challenge for clinical diagnostics. Genomic approaches are allowing the identification of novel variants in genes for very rare disorders, enabling a molecular diagnosis. Genomics is also revealing a phenotypic expansion whereby the full spectrum of clinical expression conveyed by mutant alleles at a locus can be better appreciated. OBJECTIVE: To elucidate the molecular cause of a complex neuropathy phenotype in 3 patients by applying genomic sequencing strategies. DESIGN, SETTING, AND PARTICIPANTS: Three affected individuals from 2 unrelated families presented with a complex neuropathy phenotype characterized by axonal sensorimotor neuropathy and microcephaly. They were recruited into the Centers for Mendelian Genomics research program to identify the molecular cause of their phenotype. Whole-genome, targeted whole-exome sequencing, and high-resolution single-nucleotide polymorphism arrays were performed in genetics clinics of tertiary care pediatric hospitals and biomedical research institutions. MAIN OUTCOMES AND MEASURES: Whole-genome and whole-exome sequencing identified the variants responsible for the patients' clinical phenotype. RESULTS: We identified compound heterozygous alleles in 2 affected siblings from 1 family and a homozygous nonsense variant in the third unrelated patient in the vaccinia-related kinase 1 gene (VRK1). In the latter subject, we found a common haplotype on which the nonsense mutation occurred and that segregates in the Ashkenazi Jewish population. CONCLUSIONS AND RELEVANCE: We report the identification of disease-causing alleles in 3 children from 2 unrelated families with a previously uncharacterized complex axonal motor and sensory neuropathy accompanied by severe nonprogressive microcephaly and cerebral dysgenesis. Our data raise the question of whether VRK1 mutations disturb cell cycle progression and may result in apoptosis of cells in the nervous system. The application of unbiased genomic approaches allows the identification of potentially pathogenic mutations in unsuspected genes in highly genetically heterogeneous and uncharacterized neurological diseases.
Keywords: Child; Child, Preschool; DNA Mutational Analysis; Female; Genotype; Hereditary Sensory and Motor Neuropathy; Humans; Infant; Intracellular Signaling Peptides and Proteins; Magnetic Resonance Imaging; Male; Microcephaly; Mutation; Neural Conduction; Polymorphism, Single Nucleotide; Protein Serine-Threonine Kinases

Rare complete knockouts in humans: population distribution and significant role in autism spectrum disorders. - Lim, Elaine T; Raychaudhuri, Soumya; Sanders, Stephan J; Stevens, Christine; Aniko Sabo; MacArthur, Daniel G; Neale, Benjamin M; Kirby, Andrew; Ruderfer, Douglas M; Fromer, Menachem; Lek, Monkol; Liu, Li; et al. (Neuron, 2013)
To characterize the role of rare complete human knockouts in autism spectrum disorders (ASDs), we identify genes with homozygous or compound heterozygous loss-of-function (LoF) variants (defined as nonsense and essential splice sites) from exome sequencing of 933 cases and 869 controls. We identify a 2-fold increase in complete knockouts of autosomal genes with low rates of LoF variation (≤ 5% frequency) in cases and estimate a 3% contribution to ASD risk by these events, confirming this observation in an independent set of 563 probands and 4,605 controls. Outside the pseudoautosomal regions on the X chromosome, we similarly observe a significant 1.5-fold increase in rare hemizygous knockouts in males, contributing to another 2% of ASDs in males. Taken together, these results provide compelling evidence that rare autosomal and X chromosome complete gene knockouts are important inherited risk factors for ASD.
Keywords: Case-Control Studies; Child Development Disorders, Pervasive; Child, Preschool; Chromosomes, Human, X; Demography; Female; Gene Deletion; Genetic Variation; Homozygote; Humans; Linkage Disequilibrium; Loss of Heterozygosity; Male; Risk Factors

Seafood consumption and blood mercury concentrations in Jamaican children with and without autism spectrum disorders. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Loveland, Katherine A; Ardjomand-Hessabi, Manouchehr; Chen, Zhongxue; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Bloom, Kari; Pearson, Deborah A; Lalor, Gerald C; Eric Boerwinkle (Neurotox Res, 2013)
Mercury is a toxic metal shown to have harmful effects on human health. Several studies have reported high blood mercury concentrations as a risk factor for autism spectrum disorders (ASDs), while other studies have reported no such association. The goal of this study was to investigate the association between blood mercury concentrations in children and ASDs. Moreover, we investigated the role of seafood consumption in relation to blood mercury concentrations in Jamaican children. Based on data for 65 sex- and age-matched pairs (2-8 years), we used a General Linear Model to test whether there is an association between blood mercury concentrations and ASDs. After controlling for the child's frequency of seafood consumption, maternal age, and parental education, we did not find a significant difference (P = 0.61) between blood mercury concentrations and ASDs. However, in both cases and control groups, children who ate certain types of seafood (i.e., salt water fish, sardine, or mackerel fish) had significantly higher (all P < 0.05) geometric means blood mercury concentration which were about 3.5 times that of children living in the US or Canada. Our findings also indicate that Jamaican children with parents who both had education up to high school are at a higher risk of exposure to mercury compared to children with at least one parent who had education beyond high school. Based on our findings, we recommend additional education to Jamaican parents regarding potential hazards of elevated blood mercury concentrations, and its association with seafood consumption and type of seafood.
Keywords: Adult; Age Factors; Animals; Biomarkers; Case-Control Studies; Child; Child Development Disorders, Pervasive; Child, Preschool; Female; Humans; Jamaica; Male; Mercury; Seafood; Socioeconomic Factors; Surveys and Questionnaires

Whole-genome sequence-based analysis of high-density lipoprotein cholesterol. - Morrison, Alanna C; Voorman, Arend; Johnson, Andrew D; Liu, Xiaoming; Yu, Jin; Li, Alexander; Donna M Muzny; Fuli Yu; Rice, Kenneth; Zhu, Chengsong; Bis, Joshua; Heiss, Gerardo; et al. (Nat Genet, 2013)
We describe initial steps for interrogating whole-genome sequence data to characterize the genetic architecture of a complex trait, levels of high-density lipoprotein cholesterol (HDL-C). We report whole-genome sequencing and analysis of 962 individuals from the Cohorts for Heart and Aging Research in Genetic Epidemiology (CHARGE) studies. From this analysis, we estimate that common variation contributes more to heritability of HDL-C levels than rare variation, and screening for mendelian variants for dyslipidemia identified individuals with extreme HDL-C levels. Whole-genome sequencing analyses highlight the value of regulatory and non-protein-coding regions of the genome in addition to protein-coding regions.
Keywords: Cholesterol, HDL; Computational Biology; Databases, Genetic; Genetic Variation; Genome, Human; Genome-Wide Association Study; Genomics; Heterozygote; Humans; Open Reading Frames

Atypical angiopoietin-like protein that regulates ANGPTL3. - Quagliarini, Fabiana; Wang, Yan; Kozlitina, Julia; Grishin, Nick V; Hyde, Rhonda; Eric Boerwinkle; Valenzuela, David M; Murphy, Andrew J; Cohen, Jonathan C; Hobbs, Helen H (Proc Natl Acad Sci U S A, 2012)
Angiopoietin-like proteins (ANGPTLs) play major roles in the trafficking and metabolism of lipids. Inactivation of ANGPTL3, a gene located in an intron of DOCK7, results in very low levels of LDL-cholesterol (C), HDL-C and triglyceride (TAG). We identified another ANGPTL family member, ANGPTL8, which is located in the corresponding intron of DOCK6. A variant in this family member (rs2278426, R59W) was associated with lower plasma LDL-C and HDL-C levels in three populations. ANGPTL8 is expressed in liver and adipose tissue, and circulates in plasma of humans. Expression of ANGPTL8 was reduced by fasting and increased by refeeding in both mice and humans. To examine the functional relationship between the two ANGPTL family members, we expressed ANGPTL3 at physiological levels alone or together with ANGPTL8 in livers of mice. Plasma TAG level did not change in mice expressing ANGPTL3 alone, whereas coexpression with ANGPTL8 resulted in hypertriglyceridemia, despite a reduction in circulating ANGPTL3. ANGPTL8 coimmunoprecipitated with the N-terminal domain of ANGPTL3 in plasma of these mice. In cultured hepatocytes, ANGPTL8 expression increased the appearance of N-terminal ANGPTL3 in the medium, suggesting ANGPTL8 may activate ANGPTL3. Consistent with this scenario, expression of ANGPTL8 in Angptl3(-/-) mice failed to promote hypertriglyceridemia. Thus, ANGPTL8, a paralog of ANGPTL3 that arose through duplication of an ancestral DOCK gene, regulates postprandial TAG and fatty acid metabolism by controlling activation of its progenitor, and perhaps other ANGPTLs. Inhibition of ANGPTL8 provides a new therapeutic strategy for reducing plasma lipoprotein levels.
Keywords: Amino Acid Sequence; Angiopoietin-Like Protein 3; Angiopoietin-like Proteins; Angiopoietins; Animals; Cholesterol, HDL; Cholesterol, LDL; GTPase-Activating Proteins; Guanine Nucleotide Exchange Factors; Hypertriglyceridemia; Introns; Liver; Mice; Molecular Sequence Data; Sequence Homology, Amino Acid; Triglycerides

The Centers for Mendelian Genomics: a new large-scale initiative to identify the genes underlying rare Mendelian conditions. - Bamshad, Michael J; Shendure, Jay A; Valle, David; Hamosh, Ada; Lupski, James R; Richard A Gibbs; Eric Boerwinkle; Lifton, Richard P; Gerstein, Mark; Gunel, Murat; Mane, Shrikant; Nickerson, Deborah A (Am J Med Genet A, 2012)
Next generation exome sequencing (ES) and whole genome sequencing (WGS) are new powerful tools for discovering the gene(s) that underlie Mendelian disorders. To accelerate these discoveries, the National Institutes of Health has established three Centers for Mendelian Genomics (CMGs): the Center for Mendelian Genomics at the University of Washington; the Center for Mendelian Genomics at Yale University; and the Baylor-Johns Hopkins Center for Mendelian Genomics at Baylor College of Medicine and Johns Hopkins University. The CMGs will provide ES/WGS and extensive analysis expertise at no cost to collaborating investigators where the causal gene(s) for a Mendelian phenotype has yet to be uncovered. Over the next few years and in collaboration with the global human genetics community, the CMGs hope to facilitate the identification of the genes underlying a very large fraction of all Mendelian disorders; see http://mendelian.org.
Keywords: Academies and Institutes; Genetic Diseases, Inborn; Genetics, Medical; Genome, Human; Genome-Wide Association Study; Genomics; High-Throughput Nucleotide Sequencing; Humans

Maternal and paternal age are jointly associated with childhood autism in Jamaica. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Loveland, Katherine A; Pearson, Deborah A; Bressler, Jan; Chen, Zhongxue; Ardjomand-Hessabi, Manouchehr; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Beecher, Compton; Bloom, Kari; Eric Boerwinkle (J Autism Dev Disord, 2012)
Several studies have reported maternal and paternal age as risk factors for having a child with Autism Spectrum Disorder (ASD), yet the results remain inconsistent. We used data for 68 age- and sex-matched case-control pairs collected from Jamaica. Using Multivariate General Linear Models (MGLM) and controlling for parity, gestational age, and parental education, we found a significant (p < 0.0001) joint effect of parental ages on having children with ASD indicating an adjusted mean paternal age difference between cases and controls of [5.9 years; 95% CI (2.6, 9.1)] and a difference for maternal age of [6.5 years; 95% CI (4.0, 8.9)]. To avoid multicollinearity in logistic regression, we recommend joint modeling of parental ages as a vector of outcome variables using MGLM.
Keywords: Autistic Disorder; Child; Child, Preschool; Female; Humans; Infant; Jamaica; Male; Maternal Age; Paternal Age; Registries; Risk Factors

Patterns and rates of exonic de novo mutations in autism spectrum disorders. - Neale, Benjamin M; Kou, Yan; Liu, Li; Ma'ayan, Avi; Samocha, Kaitlin E; Aniko Sabo; Lin, Chiao-Feng; Stevens, Christine; Wang, Li-San; Makarov, Vladimir; Polak, Paz; Yoon, Seungtai; et al. (Nature, 2012)
Autism spectrum disorders (ASD) are believed to have genetic and environmental origins, yet in only a modest fraction of individuals can specific causes be identified. To identify further genetic risk factors, here we assess the role of de novo mutations in ASD by sequencing the exomes of ASD cases and their parents (n = 175 trios). Fewer than half of the cases (46.3%) carry a missense or nonsense de novo variant, and the overall rate of mutation is only modestly higher than the expected rate. In contrast, the proteins encoded by genes that harboured de novo missense or nonsense mutations showed a higher degree of connectivity among themselves and to previous ASD genes as indexed by protein-protein interaction screens. The small increase in the rate of de novo events, when taken together with the protein interaction results, are consistent with an important but limited role for de novo point mutations in ASD, similar to that documented for de novo copy number variants. Genetic models incorporating these data indicate that most of the observed de novo events are unconnected to ASD; those that do confer risk are distributed across many genes and are incompletely penetrant (that is, not necessarily sufficient for disease). Our results support polygenic models in which spontaneous coding mutations in any of a large number of genes increases risk by 5- to 20-fold. Despite the challenge posed by such models, results from de novo events and a large parallel case-control study provide strong evidence in favour of CHD8 and KATNAL2 as genuine autism risk factors.
Keywords: Autistic Disorder; Case-Control Studies; DNA-Binding Proteins; Exome; Exons; Family Health; Genetic Predisposition to Disease; Humans; Models, Genetic; Multifactorial Inheritance; Mutation; Phenotype; Poisson Distribution; Protein Interaction Maps; Transcription Factors

PNPLA3 polymorphisms and liver aminotransferase levels in a Mexican American population. - Li, Quan; Qu, Hui-Qi; Rentfro, Anne R; Grove, Megan L; Mirza, Shaper; Lu, Yang; Hanis, Craig L; Fallon, Michael B; Eric Boerwinkle; Fisher-Hoch, Susan P; McCormick, Joseph B (Clin Invest Med, 2012)
PURPOSE: This study examined genetic associations of patatin-like phospholipase domain containing 3 gene (PNPLA3) polymorphisms and liver aminotransferases in an extensively documented, randomly recruited Mexican American population at high risk of liver disease. METHODS: Two single nucleotide polymorphisms (SNP) in the PNPLA3 gene (i.e., rs738409 and rs2281135) were genotyped in 1532 individuals. Population stratification was corrected by the genotyping of 103 ancestry informative markers (AIMs) for Mexican Americans. RESULTS: Both PNPLA3 SNPs showed highly significant association with alanine aminotransferase (ALT) levels, but was also, in males, associated with aspartate aminotransferase (AST) levels. Haplotypic association test of the two SNPs suggested stronger genetic association with rs738409 than rs2281135. Obvious sex effects were observed: rs738409-sex interaction in ALT levels P = 8.37 x 10(-4); rs738409-sex interaction in AST levels P = 5.03 x 10(-3). CONCLUSIONS: This population study highlights a sex-specific association of PNPLA3 polymorphisms and elevated liver enzymes in a population-based study, independent of common pathological factors of the metabolic syndrome. The strong genetic association found in women ≤ 50 years old, but not in women > 50 years old, suggests that sex hormones may mediate the sex effect.
Keywords: Adult; Age Factors; Alanine Transaminase; Aspartate Aminotransferases; Female; Genotype; Humans; Lipase; Liver; Liver Diseases; Male; Membrane Proteins; Metabolic Syndrome; Mexican Americans; Middle Aged; Polymorphism, Single Nucleotide; Sex Characteristics

Population-based risk factors for elevated alanine aminotransferase in a South Texas Mexican-American population. - Qu, Hui-Qi; Li, Quan; Grove, Megan L; Lu, Yang; Pan, Jen-Jung; Rentfro, Anne R; Bickel, Perry E; Fallon, Michael B; Hanis, Craig L; Eric Boerwinkle; McCormick, Joseph B; Fisher-Hoch, Susan P (Arch Med Res, 2012)
BACKGROUND AND AIMS: Elevated alanine aminotransferase (ALT >40 IU/mL) is a marker of liver injury but provides little insight into etiology. We aimed to identify and stratify risk factors associated with elevated ALT in a randomly selected population with a high prevalence of elevated ALT (39%), obesity (49%) and diabetes (30%). METHODS: Two machine learning methods, the support vector machine (SVM) and Bayesian logistic regression (BLR), were used to capture risk factors in a community cohort of 1532 adults from the Cameron County Hispanic Cohort (CCHC). A total of 28 predictor variables were used in the prediction models. The recently identified genetic marker rs738409 on the PNPLA3 gene was genotyped using the Sequenom iPLEX assay. RESULTS: The four major risk factors for elevated ALT were fasting plasma insulin level and insulin resistance, increased BMI and total body weight, plasma triglycerides and non-HDL cholesterol, and diastolic hypertension. In spite of the highly significant association of rs738409 in females, the role of rs738409 in the prediction model is minimal, compared to other epidemiological risk factors. Age and drug and alcohol consumption were not independent determinants of elevated ALT in this analysis. CONCLUSIONS: The risk factors most strongly associated with elevated ALT in this population are components of the metabolic syndrome and point to nonalcoholic fatty liver disease (NAFLD). This population-based model identifies the likely cause of liver disease without the requirement of individual pathological diagnosis of liver diseases. Use of such a model can greatly contribute to a population-based approach to prevention of liver disease.
Keywords: Alanine Transaminase; Female; Humans; Male; Mexican Americans; Risk Factors; Support Vector Machine; Texas

The role of drinking water sources, consumption of vegetables and seafood in relation to blood arsenic concentrations of Jamaican children with and without Autism Spectrum Disorders. - Rahbar, Mohammad H; Samms-Vaughan, Maureen; Ardjomand-Hessabi, Manouchehr; Loveland, Katherine A; Dickerson, Aisha S; Chen, Zhongxue; Bressler, Jan; Shakespeare-Pellington, Sydonnie; Grove, Megan L; Bloom, Kari; Wirth, Julie; Pearson, Deborah A; et al. (Sci Total Environ, 2012)
Arsenic is a toxic metal with harmful effects on human health, particularly on cognitive function. Autism Spectrum Disorders (ASDs) are lifelong neurodevelopmental and behavioral disorders manifesting in infancy or early childhood. We used data from 130 children between 2 and 8 years (65 pairs of ASD cases with age- and sex-matched control), to compare the mean total blood arsenic concentrations in children with and without ASDs in Kingston, Jamaica. Based on univariable analysis, we observed a significant difference between ASD cases and controls (4.03 μg/L for cases vs. 4.48 μg/L for controls, P<0.01). In the final multivariable General Linear Model (GLM), after controlling for car ownership, maternal age, parental education levels, source of drinking water, consumption of "yam, sweet potato, or dasheen", "carrot or pumpkin", "callaloo, broccoli, or pak choi", cabbage, avocado, and the frequency of seafood consumption per week, we did not find a significant association between blood arsenic concentrations and ASD status (4.36 μg/L for cases vs. 4.65 μg/L for controls, P=0.23). Likewise, in a separate final multivariable GLM, we found that source of drinking water, eating avocado, and eating "callaloo, broccoli, or pak choi" was significantly associated with higher blood arsenic concentrations (all three P<0.05). Based on our findings, we recommend assessment of arsenic levels in water, fruits, and vegetables, as well as increased awareness among the Jamaican population regarding potential risks for various exposures to arsenic.
Keywords: Arsenic; Case-Control Studies; Child; Child Development Disorders, Pervasive; Drinking Water; Humans; Jamaica; Seafood; Vegetables

Association studies for next-generation sequencing. - Luo, Li; Eric Boerwinkle; Xiong, Momiao (Genome Res, 2011)
Genome-wide association studies (GWAS) have become the primary approach for identifying genes with common variants influencing complex diseases. Despite considerable progress, the common variations identified by GWAS account for only a small fraction of disease heritability and are unlikely to explain the majority of phenotypic variations of common diseases. A potential source of the missing heritability is the contribution of rare variants. Next-generation sequencing technologies will detect millions of novel rare variants, but these technologies have three defining features: identification of a large number of rare variants, a high proportion of sequence errors, and a large proportion of missing data. These features raise challenges for testing the association of rare variants with phenotypes of interest. In this study, we use a genome continuum model and functional principal components as a general principle for developing novel and powerful association analysis methods designed for resequencing data. We use simulations to calculate the type I error rates and the power of nine alternative statistics: two functional principal component analysis (FPCA)-based statistics, the multivariate principal component analysis (MPCA)-based statistic, the weighted sum (WSS), the variable-threshold (VT) method, the generalized T(2), the collapsing method, the CMC method, and individual tests. We also examined the impact of sequence errors on their type I error rates. Finally, we apply the nine statistics to the published resequencing data set from ANGPTL4 in the Dallas Heart Study. We report that FPCA-based statistics have a higher power to detect association of rare variants and a stronger ability to filter sequence errors than the other seven methods.
Keywords: Angiopoietin-Like Protein 4; Angiopoietins; Computational Biology; Computer Simulation; Databases, Genetic; Genetic Variation; Genetics, Population; Genome, Human; Genome-Wide Association Study; Genotype; Humans; Models, Biological; Models, Statistical; Multivariate Analysis; Phenotype; Sequence Analysis, DNA

Clan genomics and the complex architecture of human disease. - Lupski, James R; Belmont, John W; Eric Boerwinkle; Richard A Gibbs (Cell, 2011)
Human diseases are caused by alleles that encompass the full range of variant types, from single-nucleotide changes to copy-number variants, and these variations span a broad frequency spectrum, from the very rare to the common. The picture emerging from analysis of whole-genome sequences, the 1000 Genomes Project pilot studies, and targeted genomic sequencing derived from very large sample sizes reveals an abundance of rare and private variants. One implication of this realization is that recent mutation may have a greater influence on disease susceptibility or protection than is conferred by variations that arose in distant ancestors.
Keywords: Genetic Predisposition to Disease; Genetic Variation; Genetics, Population; Genome, Human; Genomics; Humans; Pedigree; Pilot Projects; Precision Medicine

dbNSFP: a lightweight database of human nonsynonymous SNPs and their functional predictions. - Liu, Xiaoming; Jian, Xueqiu; Eric Boerwinkle (Hum Mutat, 2011)
With the advance of sequencing technologies, whole exome sequencing has increasingly been used to identify mutations that cause human diseases, especially rare Mendelian diseases. Among the analysis steps, functional prediction (of being deleterious) plays an important role in filtering or prioritizing nonsynonymous SNP (NS) for further analysis. Unfortunately, different prediction algorithms use different information and each has its own strength and weakness. It has been suggested that investigators should use predictions from multiple algorithms instead of relying on a single one. However, querying predictions from different databases/Web-servers for different algorithms is both tedious and time consuming, especially when dealing with a huge number of NSs identified by exome sequencing. To facilitate the process, we developed dbNSFP (database for nonsynonymous SNPs' functional predictions). It compiles prediction scores from four new and popular algorithms (SIFT, Polyphen2, LRT, and MutationTaster), along with a conservation score (PhyloP) and other related information, for every potential NS in the human genome (a total of 75,931,005). It is the first integrated database of functional predictions from multiple algorithms for the comprehensive collection of human NSs. dbNSFP is freely available for download at http://sites.google.com/site/jpopgen/dbNSFP.
Keywords: Algorithms; Computational Biology; Databases, Nucleic Acid; Genetic Association Studies; Humans; Internet; Polymorphism, Single Nucleotide; Software

Dissociation between APOC3 variants, hepatic triglyceride content and insulin resistance. - Kozlitina, Julia; Eric Boerwinkle; Cohen, Jonathan C; Hobbs, Helen H (Hepatology, 2011)
UNLABELLED: Nonalcoholic fatty liver disease (NAFLD) is an escalating health problem that is frequently associated with obesity and insulin resistance. The mechanistic relationship between NAFLD, obesity, and insulin resistance is not well understood. A nonsynonymous variant in patatin-like phospholipase domain containing 3 (rs738409, I148M) has been reproducibly associated with increased hepatic triglyceride content (HTGC) but has not been associated with either the body mass index (BMI) or indices of insulin resistance. Conversely, two sequence variants in apolipoprotein C3 (APOC3) that have been linked to hypertriglyceridemia (rs2854117 C > T and rs2854116 T > C) have recently been reported to be associated with both hepatic fat content and insulin resistance. Here we genotyped two APOC3 variants in 1228 African Americans, 843 European Americans and 426 Hispanics from a multiethnic population based study, the Dallas Heart Study and test for association with HTGC and homeostatic model of insulin resistance (HOMA-IR). We also examined the relationship between these two variants and HOMA-IR in the Atherosclerosis Risk in Communities (ARIC) study. No significant difference in hepatic fat content was found between carriers and noncarriers in the Dallas Heart Study. Neither APOC3 variant was associated with HOMA-IR in the Dallas Heart Study; this lack of association was confirmed in the ARIC study, even after the analysis was restricted to lean (BMI < 25 kg/m(2) ) individuals (n = 4399). CONCLUSION: Our data do not support a causal relationship between these two variants in APOC3 and either HTGC or insulin resistance in middle-aged men and women.
Keywords: Adult; Apolipoprotein C-III; Black or African American; Body Mass Index; Female; Gene Frequency; Genetic Variation; Genotype; Heterozygote; Hispanic or Latino; Humans; Insulin Resistance; Liver; Male; Middle Aged; Triglycerides; White People

Genome-wide association analysis of incident coronary heart disease (CHD) in African Americans: a short report. - Barbalic, Maja; Reiner, Alex P; Wu, Chunyuan; Hixson, James E; Franceschini, Nora; Eaton, Charles B; Heiss, Gerardo; Couper, David; Mosley, Thomas; Eric Boerwinkle (PLoS Genet, 2011)
African Americans have the highest rate of mortality due to coronary heart disease (CHD). Although multiple loci have been identified influencing CHD risk in European-Americans using a genome-wide association (GWAS) approach, no GWAS of incident CHD has been reported for African Americans. We performed a GWAS for incident CHD events collected during 19 years of follow-up in 2,905 African Americans from the Atherosclerosis Risk in Communities (ARIC) study. We identified a genome-wide significant SNP (rs1859023, MAF = 31%) located at 7q21 near the PFTK1 gene (HR = 0.57, 95% CI 0.46 to 0.69, p = 1.86×10(-08)), which replicated in an independent sample of over 8,000 African American women from the Women's Health Initiative (WHI) (HR = 0.81, 95% CI 0.70 to 0.93, p = 0.005). PFTK1 encodes a serine/threonine-protein kinase, PFTAIRE-1, that acts as a cyclin-dependent kinase regulating cell cycle progression and cell proliferation. This is the first finding of incident CHD locus identified by GWAS in African Americans.
Keywords: Aged; Black or African American; Coronary Disease; Female; Gene Expression Regulation; Genetic Loci; Genome-Wide Association Study; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors

Genome-wide association studies of cerebral white matter lesion burden: the CHARGE consortium. - Fornage, Myriam; Debette, Stephanie; Bis, Joshua C; Schmidt, Helena; Ikram, M Arfan; Dufouil, Carole; Sigurdsson, Sigurdur; Lumley, Thomas; DeStefano, Anita L; Fazekas, Franz; Vrooman, Henri A; Shibata, Dean K; et al. (Ann Neurol, 2011)
OBJECTIVE: White matter hyperintensities (WMHs) detectable by magnetic resonance imaging are part of the spectrum of vascular injury associated with aging of the brain and are thought to reflect ischemic damage to the small deep cerebral vessels. WMHs are associated with an increased risk of cognitive and motor dysfunction, dementia, depression, and stroke. Despite a significant heritability, few genetic loci influencing WMH burden have been identified. METHODS: We performed a meta-analysis of genome-wide association studies (GWASs) for WMH burden in 9,361 stroke-free individuals of European descent from 7 community-based cohorts. Significant findings were tested for replication in 3,024 individuals from 2 additional cohorts. RESULTS: We identified 6 novel risk-associated single nucleotide polymorphisms (SNPs) in 1 locus on chromosome 17q25 encompassing 6 known genes including WBP2, TRIM65, TRIM47, MRPL38, FBF1, and ACOX1. The most significant association was for rs3744028 (p(discovery) = 4.0 × 10(-9) ; p(replication) = 1.3 × 10(-7) ; p(combined) = 4.0 × 10(-15) ). Other SNPs in this region also reaching genome-wide significance were rs9894383 (p = 5.3 × 10(-9) ), rs11869977 (p = 5.7 × 10(-9) ), rs936393 (p = 6.8 × 10(-9) ), rs3744017 (p = 7.3 × 10(-9) ), and rs1055129 (p = 4.1 × 10(-8) ). Variant alleles at these loci conferred a small increase in WMH burden (4-8% of the overall mean WMH burden in the sample). INTERPRETATION: This large GWAS of WMH burden in community-based cohorts of individuals of European descent identifies a novel locus on chromosome 17. Further characterization of this locus may provide novel insights into the pathogenesis of cerebral WMH.
Keywords: Aged; Aged, 80 and over; Cerebral Cortex; Chromosomes, Human, Pair 17; Cognition Disorders; Cohort Studies; Female; Gene Frequency; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Humans; Leukoencephalopathies; Magnetic Resonance Imaging; Male; Middle Aged; Movement Disorders; Nerve Fibers, Myelinated; Polymorphism, Single Nucleotide; Residence Characteristics; RNA, Messenger; White People

Global DNA methylation and risk of subclinical atherosclerosis in young adults: the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study. - Bressler, Jan; Shimmin, Lawrence C; Eric Boerwinkle; Hixson, James E (Atherosclerosis, 2011)
OBJECTIVE: The association between hepatic global DNA methylation measured using pyrosequencing technology and the risk of subclinical atherosclerosis was examined in the Pathobiological Determinants of Atherosclerosis in Youth (PDAY) study. PDAY is a bi-racial investigation of the natural history of atherosclerosis and its risk factors involving 3013 individuals aged 15-34 years who underwent autopsy after dying of unrelated causes in 1987-1994. METHODS: Raised atherosclerotic lesions were defined as the sum of the percentages of intimal surface area detected in the right coronary artery and left half of the abdominal and thoracic aorta harboring fibrous plaques, complicated lesions, and calcified lesions during a postmortem pathological examination. To conduct the case-control study, 300 cases selected with the highest raised lesion scores were paired with 300 controls without raised lesions after matching for age, race, and gender. RESULTS: Global DNA methylation was not associated with disease risk in the study population considered as a whole using conditional logistic regression models to analyze matched pairs. Since the estimation of the risk of atherosclerosis associated with inter-individual variation in DNA methylation was similar if unconditional logistic regression was used, subgroup analyses were carried out after adjusting for matching variables. A modest association with methylation levels below the median value was found in white but not in African-American study participants (odds ratio = 1.59, 95% confidence interval = 1.02-2.49, p = 0.04). CONCLUSIONS: Hepatic global DNA methylation does not appear to be a definitive determinant of atherosclerosis burden in a postmortem sample of young adults.
Keywords: Adolescent; Adult; Age Factors; Aorta, Abdominal; Aorta, Thoracic; Aortic Diseases; Asymptomatic Diseases; Atherosclerosis; Autopsy; Black or African American; Case-Control Studies; Coronary Artery Disease; Coronary Vessels; DNA; DNA Methylation; Female; Humans; Liver; Logistic Models; Male; Matched-Pair Analysis; Odds Ratio; Plaque, Atherosclerotic; Risk Assessment; Risk Factors; Texas; White People; Young Adult

High-resolution identity by descent mapping uncovers the genetic basis for blood pressure differences between spontaneously hypertensive rat lines. - Bell, Rebecca; Herring, Stacy M; Gokul, Nisha; Monita, Monique; Grove, Megan L; Eric Boerwinkle; Doris, Peter A (Circ Cardiovasc Genet, 2011)
BACKGROUND: The recent development of a large panel of genome-wide single nucleotide polymorphisms (SNPs) provides the opportunity to examine genetic relationships between distinct SHR lines that share hypertension but differ in their susceptibility to hypertensive end-organ disease. METHODS AND RESULTS: We compared genotypes at nearly 10,000 SNPs obtained for the hypertension end-organ injury-susceptible spontaneously hypertensive rat (SHR)-A3 (SHRSP, SHR-stroke prone) line and the injury-resistant SHR-B2 line. This revealed that that the 2 lines were genetically identical by descent (IBD) across 86.6% of the genome. Areas of the genome that were not IBD were distributed across 19 of the 20 autosomes and the X chromosome. A block structure of non-IBD comprising a total of 121 haplotype blocks was formed by clustering of SNPs inherited from different ancestors. To test the null hypothesis that distinct SHR lines share a common set of hypertension susceptibility alleles, we compared blood pressure in adult SHR animals from both lines and their F1 and F2 progeny using telemetry. In 16- to 18-week-old animals fed a normal diet, systolic blood pressure (SBP, mm Hg) in SHR-A3 was 205.7 ± 3.86 (mean ± SEM, n = 26), whereas in similar SHR-B2 animals, SBP was 186.7 ± 2.53 (n = 20). In F1 and F2 animals, SBP was 188.2 ± 4.23 (n = 19) and 185.6 ± 1.1 (n = 211), respectively (P<10(-6), ANOVA). To identify non-IBD haplotype blocks contributing to blood pressure differences between these SHR lines, we developed a high-throughput SNP genotyping system to genotype SNPs marking non-IBD blocks. We mapped a single non-IBD block on chromosome 17 extending over <10 Mb, at which SHR-A3 alleles significantly elevate blood pressure compared with SHR-B2. CONCLUSIONS: Thus hypertension in SHR-A3 and -B2 appears to arise from an overlapping set of susceptibility alleles, with SHR-A3 possessing an additional hypertension locus that contributes to further increase blood pressure.
Keywords: Animals; Blood Pressure; Chromosome Mapping; Female; Gene Expression; Genetic Predisposition to Disease; Genotype; Haplotypes; Lod Score; Male; Molecular Sequence Data; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR

Immunoglobulin locus associates with serum IgG levels and albuminuria. - Herring, Stacy M; Gokul, Nisha; Monita, Monique; Bell, Rebecca; Eric Boerwinkle; Wenderfer, Scott E; Braun, Michael C; Doris, Peter A (J Am Soc Nephrol, 2011)
The interaction between IgG and Fc-γ receptors in glomeruli contributes to the development of several types of proteinuric glomerular disease, but the involvement of immunological mechanisms in hypertensive renal injury is incompletely understood. Here, we investigated serum IgG levels in SHR-A3 rats, which develop hypertensive injury, and compared them with the injury-resistant SHR-B2 line. At 18 weeks old, SHR-A3 rats had serum total IgG levels nearly twice those of SHR-B2 rats, although subclass IgG2b was undetectable in SHR-A3 rats compared with mean levels (± SEM) of 80.7 ± 12.8 mg/dl (18 weeks) and 116.6 ± 19.0 mg/dl (30 weeks) in SHR-B2 rats. In addition, these two strains had significantly different serum levels of IgG1, IgG2a, and IgG2c; differences persisted at 30 weeks for all subclasses except IgG2a. Genetic mapping revealed that a locus on chromosome 6 linked to IgG subclass levels that affected IgG1, IgG2b, and IgG2c but not IgG2a. The mapped haplotype block contains IgH, suggesting regulation of three of four serum IgG subclass levels in cis. Resequencing revealed variation in the sequence of the Fc portion of the IgG heavy chain, which predicts important functional changes. To examine whether there is any relationship between this haplotype block and susceptibility to renal injury, we examined the effect of SHR-A3 and SHR-B2 alleles at this block on albumin excretion in an F2 intercross. Albuminuria doubled with inheritance of SHR-A3 alleles. In summary, allelic variation in IgH or nearby genes may modulate the susceptibility to hypertensive renal injury in SHR-A3 rats.
Keywords: Albuminuria; Animals; Chromosome Mapping; Female; Haplotypes; Hypertension; Immunoglobulin G; Immunoglobulin Heavy Chains; Male; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Rats; Rats, Inbred SHR

Interaction of folate intake and the paraoxonase Q192R polymorphism with risk of incident coronary heart disease and ischemic stroke: the atherosclerosis risk in communities study. - Luu, Hung N; Kingah, Pascal L; North, Kari; Eric Boerwinkle; Volcik, Kelly A (Ann Epidemiol, 2011)
PURPOSE: To investigate the potential interaction between folate intake and the paraoxonase 1 (PON1) Q192R polymorphism with the risk of incident coronary heart disease (CHD) and ischemic stroke in the Atherosclerosis Risk in Communities study, a population-based prospective cohort of cardiovascular disease in 15,792 white and African-American subject. METHODS: Race-stratified Cox proportional hazards models were performed to examine the interaction between folate intake and the PON1 Q192R polymorphism. RESULTS: A significant inverse association between folate intake and risk of incident CHD among white subjects was found (hazard rate ratio, 1.30; 95% confidence interval, 1.09-1.56; P = .004; folate intake ≤155 μg vs ≥279 μg, reference group). An interaction effect was observed between the dominant genetic model and folate intake with regards to incident ischemic stroke in white subjects (hazard rate ratio, 0.68; 95% confidence interval, 0.91-0.99; and 1.24 from 1st-4th quartile, respectively; P-trend = .05). CONCLUSIONS: There was an interaction between folate intake and PON1 Q192 polymorphism with regard to the risk of ischemic stroke in white subjects. Future studies should investigate the interaction between additional polymorphisms within the PON1 gene and genetic variants in other folate metabolizing genes with folate intake on the risk of incident CHD and stroke.
Keywords: Adult; Aryldialkylphosphatase; Atherosclerosis; Black or African American; Cohort Studies; Coronary Disease; Female; Folic Acid; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Prospective Studies; Stroke; United States; White People

Is low-grade serous ovarian cancer part of the tumor spectrum of hereditary breast and ovarian cancer? - Vineyard, Marisa A; Daniels, Molly S; Urbauer, Diana L; Deavers, Michael T; Sun, Charlotte C; Eric Boerwinkle; Bodurka, Diane C; Gershenson, David M; Crawford, Jessica; Lu, Karen H (Gynecol Oncol, 2011)
OBJECTIVE: To determine whether women with low-grade serous ovarian cancer (LGSOC) have personal and family histories of breast and ovarian cancer that are less suggestive of Hereditary Breast and Ovarian Cancer (HBOC), as compared to women with high-grade serous ovarian cancer (HGSOC). METHODS: A single institution, case-control retrospective review of medical records was conducted. Personal demographics, personal cancer history, and family history of breast and ovarian cancer of women with LGSOC were collected and compared to controls with HGSOC, which is known to be associated with HBOC. RESULTS: 195 cases of LGSOC and 386 controls with HGSOC were included in the analysis. Women with LGSOC were significantly less likely to have a first- or second-degree relative with breast or ovarian cancer (p=0.0016). Additionally, when the personal and family histories were quantified using the AMyriad BRC mutation prevalence tables, women with LGSOC had lower scores indicative of a less suggestive family history for HBOC (p=0.027). CONCLUSIONS: In this study, women with LGSOC had family histories that were less suggestive of HBOC compared to women with HGSOC, especially when the degree of relatedness of affected relatives was taken into account. By beginning to determine if LGSOC is part of the tumor spectrum seen in HBOC, this study is an important step towards refining hereditary cancer risk assessment for women with ovarian cancer.
Keywords: Breast Neoplasms; Case-Control Studies; Cystadenocarcinoma, Serous; Female; Genes, BRCA1; Genes, BRCA2; Genetic Predisposition to Disease; Humans; Middle Aged; Ovarian Neoplasms; Retrospective Studies

Oligogenic heterozygosity in individuals with high-functioning autism spectrum disorders. - Schaaf, Christian P; Aniko Sabo; Sakai, Yasunari; Crosby, Jacy; Donna M Muzny; Hawes, Alicia; Lewis, Lora; Akbar, Humeira; Varghese, Robin; Eric Boerwinkle; Richard A Gibbs; Zoghbi, Huda Y (Hum Mol Genet, 2011)
Autism spectrum disorders (ASDs) are a heterogeneous group of neuro-developmental disorders. While significant progress has been made in the identification of genes and copy number variants associated with syndromic autism, little is known to date about the etiology of idiopathic non-syndromic autism. Sanger sequencing of 21 known autism susceptibility genes in 339 individuals with high-functioning, idiopathic ASD revealed de novo mutations in at least one of these genes in 6 of 339 probands (1.8%). Additionally, multiple events of oligogenic heterozygosity were seen, affecting 23 of 339 probands (6.8%). Screening of a control population for novel coding variants in CACNA1C, CDKL5, HOXA1, SHANK3, TSC1, TSC2 and UBE3A by the same sequencing technology revealed that controls were carriers of oligogenic heterozygous events at significantly (P < 0.01) lower rate, suggesting oligogenic heterozygosity as a new potential mechanism in the pathogenesis of ASDs.
Keywords: Adolescent; Child; Child Development Disorders, Pervasive; Child, Preschool; Genetic Predisposition to Disease; Heterozygote; Humans; Male; Mutation

Systems biology data analysis methodology in pharmacogenomics. - Rodin, Andrei S; Gogoshin, Grigoriy; Eric Boerwinkle (Pharmacogenomics, 2011)
Pharmacogenetics aims to elucidate the genetic factors underlying the individual's response to pharmacotherapy. Coupled with the recent (and ongoing) progress in high-throughput genotyping, sequencing and other genomic technologies, pharmacogenetics is rapidly transforming into pharmacogenomics, while pursuing the primary goals of identifying and studying the genetic contribution to drug therapy response and adverse effects, and existing drug characterization and new drug discovery. Accomplishment of both of these goals hinges on gaining a better understanding of the underlying biological systems; however, reverse-engineering biological system models from the massive datasets generated by the large-scale genetic epidemiology studies presents a formidable data analysis challenge. In this article, we review the recent progress made in developing such data analysis methodology within the paradigm of systems biology research that broadly aims to gain a 'holistic', or 'mechanistic' understanding of biological systems by attempting to capture the entirety of interactions between the components (genetic and otherwise) of the system.
Keywords: Artificial Intelligence; Drug Discovery; Drug-Related Side Effects and Adverse Reactions; Epistasis, Genetic; Genotype; Humans; Molecular Epidemiology; Pharmacogenetics; Research Design; Statistics as Topic; Systems Biology

Association of glycemic index and glycemic load with risk of incident coronary heart disease among Whites and African Americans with and without type 2 diabetes: the Atherosclerosis Risk in Communities study. - Hardy, Dale S; Hoelscher, Deanna M; Aragaki, Corinne; Stevens, June; Steffen, Lyn M; Pankow, James S; Eric Boerwinkle (Ann Epidemiol, 2010)
PURPOSE: In this study we examined whether high glycemic index (GI) and glycemic load (GL) diets are associated with increased risk of developing coronary heart disease (CHD) in Whites and African Americans with and without type 2 diabetes. METHODS: Data on 13,051 patients ages 45 to 64 years from the Atherosclerosis Risk in Communities study were analyzed. The ARIC food frequency questionnaire baseline data provided GI and GL indices. A propensity score was created to estimate the effect of a patient's covariates on energy-adjusted GI or GL. During a maximum of 17 years of follow-up, 1683 cases of CHD (371 with diabetes and 1312 without diabetes) were recorded. RESULTS: For every 5-units increase in GI, there was a 1.16-fold (95% confidence interval [95% CI], 1.01-1.33) increased risk of incident CHD in African Americans. For every 30-units increase in GL, there was a 1.11-fold (95% CI, 1.01-1.21) increased risk of incident CHD in Whites. High GL was an especially important CHD risk factor for Whites without diabetes (per 30-units increase; hazard ratio, 1.14; 95% CI, 1.02-1.26). However, these relationships were not seen in individuals with diabetes. CONCLUSIONS: Nutritional advice to reduce the GI and GL in diets of African Americans and Whites subjects (without diabetes) may play a role in reducing CHD risk.
Keywords: Black or African American; Coronary Disease; Diabetes Mellitus, Type 2; Diet; Female; Follow-Up Studies; Glycemic Index; Humans; Male; Middle Aged; Risk Assessment; Surveys and Questionnaires; White People

Associations between dietary patterns and flow cytometry-measured biomarkers of inflammation and cellular activation in the Atherosclerosis Risk in Communities (ARIC) Carotid Artery MRI Study. - Nettleton, Jennifer A; Matijevic, Nena; Follis, Jack L; Folsom, Aaron R; Eric Boerwinkle (Atherosclerosis, 2010)
BACKGROUND: Specific foods and overall dietary patterns are associated with soluble biomarkers of systemic inflammation and endothelial activation. However, no large epidemiological studies have evaluated relationships between such dietary factors and cell-specific markers of activation and inflammation as measured by flow cytometry. METHODS: Cell aggregates and multiple platelet and leukocyte markers were quantified by flow cytometry in fresh whole blood from 1101 white adults participating in the Carotid Artery MRI Study, a subset of the larger Atherosclerosis Risk in Communities (ARIC) Study. Two dietary patterns ("Healthy" and "Western") were empirically derived via principal components analysis using data collected by food frequency questionnaire. Cross-sectional associations between dietary patterns and flow cytometry-measured biomarkers were evaluated, adjusting for demographics and lifestyle factors, including medications use. RESULTS: After multivariable adjustment, monocyte lipopolysaccharide receptor (CD14), monocyte toll-like receptor-2, and platelet glycoprotein IIb (CD41) showed inverse associations with the Healthy dietary pattern (p=0.01, 0.04, and 0.01, respectively). In contrast, the Western dietary pattern was positively associated with CD41 and platelet-granulocyte aggregates (p=0.01 and 0.04, respectively). Independent of other dietary factors, alcohol consumption was inversely associated with levels of pan-leukocyte marker (CD45), P-selectin (CD62P) on PLA1 and on PLA2 platelets, and platelet-monocyte, platelet-granulocyte, and platelet-lymphocyte aggregates. CONCLUSION: Dietary patterns and alcohol intake were each cross-sectionally associated with select markers of cellular activation and inflammation measured by flow cytometry. These data are consistent with the hypothesis that holistic measures of dietary intake are associated with inflammation.
Keywords: Aged; Alcohol Drinking; Biomarkers; Carotid Arteries; Carotid Artery Diseases; Cross-Sectional Studies; Diet Records; Feeding Behavior; Female; Flow Cytometry; Humans; Inflammation; Inflammation Mediators; Leukocyte Common Antigens; Life Style; Linear Models; Lipopolysaccharide Receptors; Magnetic Resonance Angiography; Male; P-Selectin; Platelet Membrane Glycoprotein IIb; Principal Component Analysis; Risk Assessment; Risk Factors; Surveys and Questionnaires; Toll-Like Receptor 2; United States

Common INSIG2 polymorphisms are associated with age-related changes in body size and high-density lipoprotein cholesterol from young adulthood to middle age. - Fornage, Myriam; Papanicolaou, George; Lewis, Cora E; Eric Boerwinkle; Siscovick, David S (Metabolism, 2010)
Insulin-induced gene 2 (INSIG2) plays an important role in the regulation of cholesterol and fatty acids synthesis. A polymorphism, rs7566605, located 10 kilobases upstream of the INSIG2 gene, was identified in a genomewide association study of obesity. We conducted an association study of 12 INSIG2 tag-single nucleotide polymorphisms with longitudinal measures of body size (body mass index and waist circumference) and lipid metabolism (plasma high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides levels). We investigated their interaction with age in 4304 Coronary Artery Risk Development in Young Adults participants (49.5% blacks, 50.5% whites) followed prospectively for 20 years. rs7566605 was not associated with variation in body size or lipid metabolism at any age in either racial group. However, rs1352083 and rs10185316 were associated with age-related decline in high-density lipoprotein cholesterol in whites (P = .0005 and .04, respectively). A similar trend was observed in blacks who consistently maintained a body mass index less than 25 kg/m(2) over the study period. These data support a role of INSIG2 sequence variation in the regulation of cholesterol metabolism.
Keywords: Adolescent; Adult; Age Factors; Body Mass Index; Body Size; Cholesterol, HDL; Cross-Sectional Studies; Female; Humans; Intracellular Signaling Peptides and Proteins; Male; Membrane Proteins; Polymorphism, Single Nucleotide; Young Adult

Deep resequencing reveals excess rare recent variants consistent with explosive population growth. - Coventry, Alex; Bull-Otterson, Lara M; Liu, Xiaoming; Clark, Andrew G; Maxwell, Taylor J; Crosby, Jacy; Hixson, James E; Rea, Thomas J; Donna M Muzny; Lewis, Lora R; David A Wheeler; Aniko Sabo; et al. (Nat Commun, 2010)
Accurately determining the distribution of rare variants is an important goal of human genetics, but resequencing of a sample large enough for this purpose has been unfeasible until now. Here, we applied Sanger sequencing of genomic PCR amplicons to resequence the diabetes-associated genes KCNJ11 and HHEX in 13,715 people (10,422 European Americans and 3,293 African Americans) and validated amplicons potentially harbouring rare variants using 454 pyrosequencing. We observed far more variation (expected variant-site count ∼578) than would have been predicted on the basis of earlier surveys, which could only capture the distribution of common variants. By comparison with earlier estimates based on common variants, our model shows a clear genetic signal of accelerating population growth, suggesting that humanity harbours a myriad of rare, deleterious variants, and that disease risk and the burden of disease in contemporary populations may be heavily influenced by the distribution of rare variants.

Diabetes genes and prostate cancer in the Atherosclerosis Risk in Communities study. - Meyer, Tamra E; Eric Boerwinkle; Morrison, Alanna C; Volcik, Kelly A; Sanderson, Maureen; Coker, Ann L; Pankow, James S; Folsom, Aaron R (Cancer Epidemiol Biomarkers Prev, 2010)
There is a known inverse association between type 2 diabetes (T2D) and prostate cancer (PrCa) that is poorly understood. Genetic studies of the T2D-PrCa association may provide insight into the underlying mechanisms of this association. We evaluated associations in the Atherosclerosis Risk in Communities study between PrCa and nine T2D single nucleotide polymorphisms from genome-wide association studies of T2D (in CDKAL1, CDKN2A/B, FTO, HHEX, IGF2BP2, KCNJ11, PPARG, SLC30A8, and TCF7L2) and four T2D single nucleotide polymorphisms from pre-genome-wide association studies (in ADRB2, CAPN10, SLC2A2, and UCP2). From 1987 to 2000, there were 397 incident PrCa cases among 6,642 men ages 45 to 64 years at baseline. We used race-adjusted Cox proportional hazards models to estimate associations between PrCa and increasing number of T2D risk-raising alleles. PrCa was positively associated with the CAPN10 rs3792267 G allele [hazard ratio (HR) 1.20; 95% confidence interval (CI), 1.00-1.44] and inversely associated with the SLC2A2 rs5400 Thr110 allele (HR, 0.85; 95% CI, 0.72, 1.00), the UCP2 rs660339 Val55 allele (HR, 0.84; 95% CI, 0.73, 0.97) and the IGF2BP2 rs4402960 T allele (HR, 0.79; 95% CI, 0.61-1.02; blacks only). The TCF7L2 rs7903146 T allele was inversely associated with PrCa using a dominant genetic model (HR, 0.79; 95% CI, 0.65-0.97). Further knowledge of T2D gene-PrCa mechanisms may improve understanding of PrCa etiology.
Keywords: Atherosclerosis; Calpain; Cohort Studies; Diabetes Mellitus, Type 2; Genetic Predisposition to Disease; Genome-Wide Association Study; Glucose Transporter Type 2; Humans; Ion Channels; Male; Middle Aged; Mitochondrial Proteins; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prostatic Neoplasms; RNA-Binding Proteins; TCF Transcription Factors; Transcription Factor 7-Like 2 Protein; Uncoupling Protein 2

Estimating population genetic parameters and comparing model goodness-of-fit using DNA sequences with error. - Liu, Xiaoming; Fu, Yun-Xin; Maxwell, Taylor J; Eric Boerwinkle (Genome Res, 2010)
It is known that sequencing error can bias estimation of evolutionary or population genetic parameters. This problem is more prominent in deep resequencing studies because of their large sample size n, and a higher probability of error at each nucleotide site. We propose a new method based on the composite likelihood of the observed SNP configurations to infer population mutation rate theta = 4N(e)micro, population exponential growth rate R, and error rate epsilon, simultaneously. Using simulation, we show the combined effects of the parameters, theta, n, epsilon, and R on the accuracy of parameter estimation. We compared our maximum composite likelihood estimator (MCLE) of theta with other theta estimators that take into account the error. The results show the MCLE performs well when the sample size is large or the error rate is high. Using parametric bootstrap, composite likelihood can also be used as a statistic for testing the model goodness-of-fit of the observed DNA sequences. The MCLE method is applied to sequence data on the ANGPTL4 gene in 1832 African American and 1045 European American individuals.
Keywords: Angiopoietin-Like Protein 4; Angiopoietins; Base Sequence; Black or African American; Black People; Computational Biology; Computer Simulation; Genetics, Population; Humans; Likelihood Functions; Models, Genetic; Mutation; Polymorphism, Single Nucleotide; White People

Genetic variants identified in a European genome-wide association study that were found to predict incident coronary heart disease in the atherosclerosis risk in communities study. - Bressler, Jan; Folsom, Aaron R; Couper, David J; Volcik, Kelly A; Eric Boerwinkle (Am J Epidemiol, 2010)
In 2007, the Wellcome Trust Case Control Consortium (WTCCC) performed a genome-wide association study in 2,000 British coronary heart disease (CHD) cases and 3,000 controls after genotyping 469,557 single nucleotide polymorphisms (SNPs). Seven variants associated with CHD were initially identified, and 5 SNPs were later found in replication studies. In the current study, the authors aimed to determine whether the 12 SNPs reported by the WTCCC predicted incident CHD through 2004 in a biracial, prospective cohort study (Atherosclerosis Risk in Communities) comprising 15,792 persons aged 45-64 years who had been selected by probability sampling from 4 different US communities in 1987-1989. Cox proportional hazards models with adjustment for age and gender were used to estimate CHD hazard rate ratios (HRRs) over a 17-year period (1,362 cases in whites and 397 cases in African Americans) under an additive genetic model. The results showed that 3 SNPs in whites (rs599839, rs1333049, and rs501120; HRRs were 1.10 (P = 0.044), 1.14 (P < 0.001), and 1.14 (P = 0.030), respectively) and 1 SNP in African Americans (rs7250581; HRR = 1.60, P = 0.05) were significantly associated with incident CHD. This study demonstrates that genetic variants revealed in a case-control genome-wide association study enriched for early disease onset may play a role in the genetic etiology of CHD in the general population.
Keywords: Black or African American; Case-Control Studies; Coronary Artery Disease; Female; Genetic Variation; Genome, Human; Genome-Wide Association Study; Humans; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Residence Characteristics; Risk; Risk Assessment; Risk Factors; United Kingdom; United States; White People

Genome-wide association studies of serum magnesium, potassium, and sodium concentrations identify six Loci influencing serum magnesium levels. - Meyer, Tamra E; Verwoert, Germaine C; Hwang, Shih-Jen; Glazer, Nicole L; Smith, Albert V; van Rooij, Frank J A; Ehret, Georg B; Eric Boerwinkle; Felix, Janine F; Leak, Tennille S; Harris, Tamara B; Yang, Qiong; et al. (PLoS Genet, 2010)
Magnesium, potassium, and sodium, cations commonly measured in serum, are involved in many physiological processes including energy metabolism, nerve and muscle function, signal transduction, and fluid and blood pressure regulation. To evaluate the contribution of common genetic variation to normal physiologic variation in serum concentrations of these cations, we conducted genome-wide association studies of serum magnesium, potassium, and sodium concentrations using approximately 2.5 million genotyped and imputed common single nucleotide polymorphisms (SNPs) in 15,366 participants of European descent from the international CHARGE Consortium. Study-specific results were combined using fixed-effects inverse-variance weighted meta-analysis. SNPs demonstrating genome-wide significant (p<5 x 10(-8)) or suggestive associations (p<4 x 10(-7)) were evaluated for replication in an additional 8,463 subjects of European descent. The association of common variants at six genomic regions (in or near MUC1, ATP2B1, DCDC5, TRPM6, SHROOM3, and MDS1) with serum magnesium levels was genome-wide significant when meta-analyzed with the replication dataset. All initially significant SNPs from the CHARGE Consortium showed nominal association with clinically defined hypomagnesemia, two showed association with kidney function, two with bone mineral density, and one of these also associated with fasting glucose levels. Common variants in CNNM2, a magnesium transporter studied only in model systems to date, as well as in CNNM3 and CNNM4, were also associated with magnesium concentrations in this study. We observed no associations with serum sodium or potassium levels exceeding p<4 x 10(-7). Follow-up studies of newly implicated genomic loci may provide additional insights into the regulation and homeostasis of human serum magnesium levels.
Keywords: Adult; Aged; Female; Genome-Wide Association Study; Humans; Magnesium; Male; Middle Aged; Polymorphism, Single Nucleotide; Potassium; Sodium; White People

Genomic variation associated with mortality among adults of European and African ancestry with heart failure: the cohorts for heart and aging research in genomic epidemiology consortium. - Morrison, Alanna C; Felix, Janine F; Cupples, L Adrienne; Glazer, Nicole L; Loehr, Laura R; Dehghan, Abbas; Demissie, Serkalem; Bis, Joshua C; Rosamond, Wayne D; Aulchenko, Yurii S; Wang, Ying A; Haritunians, Talin; et al. (Circ Cardiovasc Genet, 2010)
BACKGROUND: Prognosis and survival are significant concerns for individuals with heart failure (HF). To better understand the pathophysiology of HF prognosis, the association between 2,366,858 single-nucleotide polymorphisms (SNPs) and all-cause mortality was evaluated among individuals with incident HF from 4 community-based prospective cohorts: the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. METHODS AND RESULTS: Participants were 2526 individuals of European ancestry and 466 individuals of African ancestry who experienced an incident HF event during follow-up in the respective cohorts. Within each study, the association between genetic variants and time to mortality among individuals with HF was assessed by Cox proportional hazards models that included adjustment for sex and age at the time of the HF event. Prospective fixed-effect meta-analyses were conducted for the 4 study populations of European ancestry (N=1645 deaths) and for the 2 populations of African ancestry (N=281 deaths). Genome-wide significance was set at P=5.0x10(-7). Meta-analytic findings among individuals of European ancestry revealed 1 genome-wide significant locus on chromosome 3p22 in an intron of CKLF-like MARVEL transmembrane domain containing 7 (CMTM7, P=3.2x10(-7)). Eight additional loci in individuals of European ancestry and 4 loci in individuals of African ancestry were identified by high-signal SNPs (P<1.0x10(-5)) but did not meet genome-wide significance. CONCLUSIONS: This study identified a novel locus associated with all-cause mortality among individuals of European ancestry with HF. This finding warrants additional investigation, including replication, in other studies of HF.
Keywords: Aged; Aged, 80 and over; Black or African American; Chemokines; Cohort Studies; Female; Genome-Wide Association Study; Genotype; Heart Failure; Humans; Introns; Male; MARVEL Domain-Containing Proteins; Membrane Proteins; Middle Aged; Polymorphism, Single Nucleotide; Risk Factors; White People

Large-scale genomic studies reveal central role of ABO in sP-selectin and sICAM-1 levels. - Barbalic, Maja; Dupuis, Josée; Dehghan, Abbas; Bis, Joshua C; Hoogeveen, Ron C; Schnabel, Renate B; Nambi, Vijay; Bretler, Monique; Smith, Nicholas L; Peters, Annette; Lu, Chen; Tracy, Russell P; et al. (Hum Mol Genet, 2010)
P-selectin and intercellular adhesion molecule-1 (ICAM-1) participate in inflammatory processes by promoting adhesion of leukocytes to vascular wall endothelium. Their soluble levels have been associated with adverse cardiovascular events. To identify loci affecting soluble levels of P-selectin (sP-selectin) and ICAM-1 (sICAM-1), we performed a genome-wide association study in a sample of 4115 (sP-selectin) and 9813 (sICAM-1) individuals of European ancestry as a part of The Cohorts for Heart and Aging Research in Genome Epidemiology consortium. The most significant SNP association for sP-selectin was within the SELP gene (rs6136, P = 4.05 x 10(-61)) and for sICAM-1 levels within the ICAM-1 gene (rs3093030, P = 3.53 x 10(-23)). Both sP-selectin and sICAM-1 were associated with ABO gene variants (rs579459, P = 1.86 x 10(-41) and rs649129, P = 1.22 x 10(-15), respectively) and in both cases the observed associations could be accounted for by the A1 allele of the ABO blood group. The absence of an association between ABO blood group and platelet-bound P-selectin levels in an independent subsample (N = 1088) from the ARIC study, suggests that the ABO blood group may influence cleavage of the P-selectin protein from the cell surface or clearance from the circulation, rather than its production and cellular presentation. These results provide new insights into adhesion molecule biology.
Keywords: ABO Blood-Group System; Blood Platelets; Enzyme-Linked Immunosorbent Assay; Fluorescence; Genome-Wide Association Study; Humans; Intercellular Adhesion Molecule-1; P-Selectin; White People

MMP2 genetic variation is associated with measures of fibrous cap thickness: The Atherosclerosis Risk in Communities Carotid MRI Study. - Volcik, Kelly A; Campbell, Stephen; Chambless, Lloyd E; Coresh, Josef; Folsom, Aaron R; Mosley, Thomas H; Ni, Hanyu; Wagenknecht, Lynne E; Wasserman, Bruce A; Eric Boerwinkle (Atherosclerosis, 2010)
OBJECTIVE: Genetic variation in matrix metalloproteinase (MMP) promoter regions alter the transcriptional activity of MMPs and has been consistently associated with CHD, presumably through plaque degradation and remodeling. We examined the association of MMP promoter variation with multiple plaque characteristics measured by gadolinium-enhanced MRI among 1700 participants in the Atherosclerosis Risk in Communities (ARIC) Carotid MRI Study. METHODS: For the analyses presented here, 1700 participants of the biracial ARIC Carotid MRI Study ( approximately 1000 participants with thick carotid artery walls and approximately 700 randomly sampled participants) were evaluated for associations of MMP genetic variation with multiple plaque characteristics, including carotid artery wall thickness, lipid core and fibrous cap measures. MRI studies were performed on a 1.5T scanner equipped with a bilateral 4-element phased array carotid coil. RESULTS: Fifty-one percent of the participants were female, 77% white, 23% African American, and the mean age was 70 years. MMP2 C-1306T variant genotypes (CT+TT) were significantly associated with higher cap thickness measures, but not with wall thickness or lipid core measures. Individuals with the CC genotype had approximately 0.1mm thinner cap thickness compared to those carrying a T allele (P=0.02). CONCLUSION: Genetic variation within the MMP2 promoter region was associated with cap thickness and therefore may influence the role of MMP2 in plaque vulnerability.
Keywords: Aged; Atherosclerosis; Carotid Arteries; Female; Genetic Variation; Genotype; Humans; Magnetic Resonance Imaging; Male; Matrix Metalloproteinase 2; Middle Aged; Promoter Regions, Genetic; Prospective Studies; Transcription, Genetic

Risk of type 2 diabetes and obesity is differentially associated with variation in FTO in whites and African-Americans in the ARIC study. - Bressler, Jan; Kao, W H Linda; Pankow, James S; Eric Boerwinkle (PLoS One, 2010)
Single nucleotide polymorphisms (SNPs) in the fat mass and obesity associated (FTO) gene are associated with body mass index (BMI) in populations of European descent. The FTO rs9939609 variant, first detected in a genome-wide association study of diabetes, conferred an increased disease risk that was abolished after adjustment for BMI, suggesting that the association may be due to variation in adiposity. The relationship between diabetes, four previously identified FTO polymorphisms that span a 19.6-kb genomic region, and obesity was therefore evaluated in the biracial population-based Atherosclerosis Risk in Communities Study with the goal of further refining the association by comparing results between the two ethnic groups. The prevalence of diabetes and obesity (BMI > or = 30 kg/m(2)) was established at baseline, and diabetes was determined by either self-report, a fasting glucose level > or = 126 mg/dL, or non-fasting glucose > or = 200 mg/dL. There were 1,004 diabetes cases and 10,038 non-cases in whites, and 670 cases and 2,780 non-cases in African-Americans. Differences in mean BMI were assessed by a general linear model, and multivariable logistic regression was used to predict the risk of diabetes and obesity. For white participants, the FTO rs9939609 A allele was associated with an increased risk of diabetes (odds ratio (OR) = 1.19, p<0.001) and obesity (OR = 1.22, p<0.001) under an additive genetic model that was similar for all of the SNPs analyzed. In African-Americans, only the rs1421085 C allele was a determinant of obesity risk (OR = 1.17, p = 0.05), but was found to be protective against diabetes (OR = 0.79, p = 0.03). Adjustment for BMI did not eliminate any of the observed associations with diabetes. Significant statistical interaction between race and the FTO variants suggests that the effect on diabetes susceptibility may be context dependent.
Keywords: Alleles; Alpha-Ketoglutarate-Dependent Dioxygenase FTO; Atherosclerosis; Black or African American; Body Mass Index; Diabetes Mellitus, Type 2; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Obesity; Polymorphism, Single Nucleotide; Proteins; Quantitative Trait, Heritable; White People

A weighted false discovery rate control procedure reveals alleles at FOXA2 that influence fasting glucose levels. - Xing, Chao; Cohen, Jonathan C; Eric Boerwinkle (Am J Hum Genet, 2010)
Association signals in GWAS are usually prioritized solely by p values. Here, we attempt to improve the power of GWAS by using a weighted false discovery rate control procedure to detect associations of low-frequency variants with effect sizes similar to or even larger than those of common variants. We used the Affymetrix Genome-Wide Human SNP Array 6.0 to test for association with fasting glucose levels in the Atherosclerosis Risk in Communities Study (ARIC) population. In addition to finding several previously identified sequence variations, we identified a low-frequency variant (rs1209523; minor allele frequency = 0.043) near FOXA2 that was associated with fasting glucose levels in European Americans (EAs) (n = 7428, p value = 1.3 x 10(-5)). The association between rs1209523 and glucose levels was also significant in African Americans (AAs) (n = 2029, p value = 6.7 x 10(-3)) of the ARIC and was confirmed by replication in both EAs and AAs of the Dallas Heart Study (n = 963 and 1571, respectively; p values = 5.3 x 10(-3) and 5.8 x 10(-4), respectively) and in EAs of the Cooper Center Longitudinal Study (n = 2862; p value = 1.6 x 10(-2)). A meta-analysis of these five populations yielded an estimated effect size of -1.31 mg/dl per minor allele (p value = 2.2 x 10(-11)). This study reveals that there is a cache of less-frequent variants in GWAS arrays that can be identified via analytical approaches accounting for allele frequencies.
Keywords: Alleles; Biostatistics; Black or African American; Blood Glucose; Fasting; Gene Frequency; Genome-Wide Association Study; Hepatocyte Nuclear Factor 3-beta; Humans; Linkage Disequilibrium; Oligonucleotide Array Sequence Analysis; Polymorphism, Single Nucleotide; White People

Carbohydrate intake modifies associations between ANGPTL4[E40K] genotype and HDL-cholesterol concentrations in White men from the Atherosclerosis Risk in Communities (ARIC) study. - Nettleton, Jennifer A; Volcik, Kelly A; Hoogeveen, Ron C; Eric Boerwinkle (Atherosclerosis, 2009)
BACKGROUND: Common allelic variation in the angiopoietin-like 4 gene (ANGPTL4[E40K]) has been associated with low triglyceride (TG) and high HDL-C. OBJECTIVE: We examined whether dietary macronutrient intake modified associations between ANGPTL4[E40K] variation and TG and HDL-C in White men and women from the Atherosclerosis Risk in Communities study. DESIGN: Diet was assessed by food frequency questionnaire. Intake of fat (total fat [TF], saturated fat [SF], monounsaturated fat [MUFA], polyunsaturated fat [PUFA], and n-3 PUFA) and carbohydrate were expressed as percentage of total energy intake. ANGPTL4 A allele carriers (n=148 in men, 200 in women) were compared to non-carriers (n=3667 in men, 4496 in women). Interactions were tested separately in men and women, adjusting for study center, age, smoking, physical activity, BMI, and alcohol intake. RESULTS: ANGPTL4 A allele carriers had significantly greater HDL-C and lower TG than non-carriers (p<or=0.001). In all participants, carbohydrate intake was inversely associated with HDL-C and positively associated with TG, whereas TF, SF, and MUFA showed opposite associations with TG and HDL-C (p<0.001). These relations were uniform between sex-specific genotype groups, with one exception. In men, but not women, the inverse association between carbohydrate and HDL-C was stronger in A allele carriers (beta+/-S.E. -1.80+/-0.54) than non-carriers (beta+/-S.E. -0.54+/-0.11, p(interaction)=0.04 in men and 0.69 in women; p 3-way interaction=0.14). CONCLUSIONS: These data suggest that ANGPTL4 variation and relative contributions of dietary fat and carbohydrate influence TG and HDL-C concentrations. In men, ANGPTL4 variation and dietary carbohydrate may interactively influence HDL-C.
Keywords: Alleles; Angiopoietin-Like Protein 4; Angiopoietins; Atherosclerosis; Cholesterol; Cholesterol, HDL; Community Health Services; Diet; Female; Genetic Variation; Genotype; Humans; Male; Middle Aged; Nutritional Sciences; Risk; Sex Factors; Triglycerides; White People

Cohorts for Heart and Aging Research in Genomic Epidemiology (CHARGE) Consortium: Design of prospective meta-analyses of genome-wide association studies from 5 cohorts. - Psaty, Bruce M; O'Donnell, Christopher J; Gudnason, Vilmundur; Lunetta, Kathryn L; Folsom, Aaron R; Rotter, Jerome I; Uitterlinden, André G; Harris, Tamara B; Witteman, Jacqueline C M; Eric Boerwinkle (Circ Cardiovasc Genet, 2009)
BACKGROUND: The primary aim of genome-wide association studies is to identify novel genetic loci associated with interindividual variation in the levels of risk factors, the degree of subclinical disease, or the risk of clinical disease. The requirement for large sample sizes and the importance of replication have served as powerful incentives for scientific collaboration. Methods- The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium was formed to facilitate genome-wide association studies meta-analyses and replication opportunities among multiple large population-based cohort studies, which collect data in a standardized fashion and represent the preferred method for estimating disease incidence. The design of the Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium includes 5 prospective cohort studies from the United States and Europe: the Age, Gene/Environment Susceptibility-Reykjavik Study, the Atherosclerosis Risk in Communities Study, the Cardiovascular Health Study, the Framingham Heart Study, and the Rotterdam Study. With genome-wide data on a total of about 38 000 individuals, these cohort studies have a large number of health-related phenotypes measured in similar ways. For each harmonized trait, within-cohort genome-wide association study analyses are combined by meta-analysis. A prospective meta-analysis of data from all 5 cohorts, with a properly selected level of genome-wide statistical significance, is a powerful approach to finding genuine phenotypic associations with novel genetic loci. CONCLUSIONS: The Cohorts for Heart and Aging Research in Genomic Epidemiology Consortium and collaborating non-member studies or consortia provide an excellent framework for the identification of the genetic determinants of risk factors, subclinical-disease measures, and clinical events.
Keywords: Adult; Aged; Aging; Cohort Studies; Female; Genetic Predisposition to Disease; Genome-Wide Association Study; Genotype; Heart Diseases; Humans; Male; Meta-Analysis as Topic; Middle Aged; Phenotype; Research Design; Risk Factors

Gene by smoking interaction in hypertension: identification of a major quantitative trait locus on chromosome 15q for systolic blood pressure in Mexican-Americans. - Montasser, May E; Shimmin, Lawrence C; Hanis, Craig L; Eric Boerwinkle; Hixson, James E (J Hypertens, 2009)
OBJECTIVE: Our objective was to investigate the influence of gene by smoking (GxS) interaction on hypertension and blood pressure (BP) using genome-wide linkage analysis in Mexican-Americans, followed by single nucleotide polymorphism (SNP) fine mapping of candidate genes in the linked chromosomal region. METHODS: We used nonparametric methods to test for linkage of microsatellites with hypertension and BP measures in smokers, nonsmokers, and the combined group. To begin fine mapping of a major quantitative trait locus (QTL) for systolic blood pressure (SBP) on chromosome 15q that showed strong evidence for GxS interaction, we genotyped 55 SNPs in nine candidate genes for association studies using two population-based statistical methods. RESULTS: The strongest evidence for GxS interaction (P = 0.0004) was found for SBP on chromosome 15q, where a major QTL (LOD = 3.36) was identified only in nonsmokers. Follow-up studies identified three SNPs in three genes (ANPEP, IGF1R, and SLCO3A1) that showed associations with SBP only in nonsmokers, cumulatively accounting for a 7 mmHg increase in SBP. However, conditional linkage analyses that accounted for phenotypic effects of these SNPs only slightly reduced the original LOD score. CONCLUSION: The detection of a major QTL on chromosome 15q for SBP in nonsmokers indicates the presence of loci that influence BP via GxS interactions. However, identification of the genes that underlie such QTL effects remains a challenge. Although we found three candidate genes that showed significant associations with SBP in nonsmokers, further studies are required to identify the gene(s) that underlie the chromosome 15q QTL that influences SBP via GxS interactions.
Keywords: Aged; Blood Pressure; Chromosomes, Human, Pair 15; Female; Genetic Linkage; Humans; Hypertension; Lod Score; Male; Mexican Americans; Microsatellite Repeats; Middle Aged; Physical Chromosome Mapping; Polymorphism, Single Nucleotide; Quantitative Trait Loci; Smoking; Statistics, Nonparametric; Texas

Genome-wide identification of allelic expression in hypertensive rats. - Dmitrieva, Renata I; Hinojos, Cruz A; Grove, Megan L; Bell, Rebecca J; Eric Boerwinkle; Fornage, Myriam; Doris, Peter A (Circ Cardiovasc Genet, 2009)
BACKGROUND: Identification of genes involved in complex cardiovascular disease traits has proven challenging. Inbred animal models can facilitate genetic studies of disease traits. The spontaneously hypertensive rat (SHR) is an inbred model of hypertension that exists in several closely related but genetically distinct lines. METHODS AND RESULTS: We used renal gene-expression profiling across 3 distinct SHR lines to identify genes that show different expression in SHR than in the genetically related normotensive control strain, Wistar-Kyoto. To ensure robust discovery of genes showing SHR-specific expression differences, we considered only those genes in which differential expression is replicated in multiple animals of each of multiple hypertensive rat lines at multiple time points during the ontogeny of hypertension. Mutation analysis was performed on the identified genes to uncover allelic variation. We identified those genes in which all SHR lines share a single allele of the gene when normotensive controls (Wistar-Kyoto) have fixed the alternative allele. We then identified which of the differentially expressed genes show expression that is controlled by the alleleic variation present in and around the gene. Allelic expression was demonstrated by observing the effect on gene expression of alleles inherited in the freely segregating F(2) progeny of a cross between SHR and Wistar-Kyoto animals. CONCLUSIONS: The result of these studies is the identification of several genes (Ptprj, Ela1, Dapk-2, and Gstt2) in which each of 4 SHR lines examined have fixed the same allele and in which each of 2 Wistar-Kyoto lines have a contrasting allele for which the inherited allele influences the level of gene expression. We further show that alleles of these genes lie in extensive haplotype blocks that have been inherited identical by descent in the hypertensive lines.
Keywords: Alleles; Animals; Blood Pressure; Disease Models, Animal; Female; Gene Expression Profiling; Genome-Wide Association Study; Humans; Hypertension; Kidney; Male; Pedigree; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Inbred WKY

Glucocorticoid receptor gene variant in the 3' untranslated region is associated with multiple measures of blood pressure. - Chung, Charles C; Shimmin, Lawrence; Natarajan, Sivamani; Hanis, Craig L; Eric Boerwinkle; Hixson, James E (J Clin Endocrinol Metab, 2009)
CONTEXT: The glucocorticoid receptor (GR) is a key hormone in the hypothalamus-pituitary-adrenal axis that regulates many pathways including blood pressure homeostasis. Thus, GR gene variation may influence interindividual differences in blood pressure in human populations. OBJECTIVE: We resequenced individual GR alleles for comprehensive discovery of GR variants and their chromosomal phase in three major American ethnic groups. We examined the influence of GR variants on blood pressure in large numbers of families using family-based association methods. DESIGN AND PARTICIPANTS: For association studies, we genotyped GR variants in family members from the Genetic Epidemiology Network of Arteriopathy (GENOA) study that were measured for multiple blood pressure traits. The GENOA families consisted of African-Americans, Mexican-Americans, and European-Americans. MAIN MEASUREMENTS: The blood pressure measurements for association studies included systolic blood pressure, diastolic blood pressure, mean arterial pressure, and pulse pressure. RESULTS: Single-nucleotide polymorphisms (SNPs) identified by resequencing were tested for associations with blood pressure measures in GENOA families. Analysis of individual SNPs identified significant associations of rs6198 A/G in exon 9beta with multiple blood pressure measures in European-Americans. Analysis of GR haplotypes found significant associations of a haplotype that is distinguished by rs6198 A/G. CONCLUSIONS: Significant associations of blood pressure with rs6198 A/G likely reflect allelic effects on GR signaling. This SNP disrupts a 3' untranslated region sequence element in exon 9beta that destabilizes mRNA, resulting in increased production of the inactive GRbeta isoform. Excess heterodimerization with the active GRalpha isoform may reduce GR signaling with subsequent physiological effects on blood pressure regulation.
Keywords: 3' Untranslated Regions; Blood Pressure; Cell Line; Haplotypes; Humans; Polymorphism, Single Nucleotide; Protein Isoforms; Receptors, Glucocorticoid

GOSR2 Lys67Arg is associated with hypertension in whites. - Meyer, Tamra E; Shiffman, Dov; Morrison, Alanna C; Rowland, Charles M; Louie, Judy Z; Bare, Lance A; Ross, David A; Arellano, Andre R; Chasman, Daniel I; Ridker, Paul M; Pankow, James S; Coresh, Josef; et al. (Am J Hypertens, 2009)
BACKGROUND: Hypertension is a risk factor for coronary heart disease (CHD), but the causes of hypertension remain largely unknown. Genetic variation is thought to contribute to the etiology of hypertension. We tested a single-nucleotide polymorphism (SNP) (Lys67Arg, rs197922) in the Golgi SNAP Receptor Complex Member 2 (GOSR2) gene for association with hypertension and blood pressure (BP). We chose this SNP because it was nominally associated with CHD in earlier studies. Further, GOSR2 is located in a linkage region for hypertension and BP in human and animal studies. METHODS: We used logistic and linear regression to test associations of the GOSR2 SNP with hypertension and BP among 3,528 blacks and 9,861 whites from the Atherosclerosis Risk in Communities (ARIC) study. Race-specific regression models of hypertension were adjusted for age and gender. Regression models of BP were further adjusted for antihypertensive medication use. RESULTS: The GOSR2 Lys67 allele was associated with hypertension in whites (odds ratio (OR) = 1.09, P = 0.01) but not blacks (OR = 0.96, P = 0.47). The Lys67 allele was associated with increased systolic BP (SBP) in both races (0.87 mm Hg, P < 0.001 among whites and 1.05 mm Hg, P = 0.05 among blacks). A similar association in whites was observed for the GOSR2 SNP and SBP in the Women's Genome Health Study (WGHS) (OR = 1.03, P = 0.04). The OR remained unchanged after adjustment for antihypertensive medication use (OR = 1.03, P = 0.11), though it was no longer statistically significant. CONCLUSIONS: We found evidence that a SNP in GOSR2 is modestly associated with hypertension in whites from the ARIC study and the WGHS.
Keywords: Black People; Humans; Hypertension; Longitudinal Studies; Odds Ratio; Polymorphism, Single Nucleotide; Qb-SNARE Proteins; White People

Inferring population mutation rate and sequencing error rate using the SNP frequency spectrum in a sample of DNA sequences. - Liu, Xiaoming; Maxwell, Taylor J; Eric Boerwinkle; Fu, Yun-Xin (Mol Biol Evol, 2009)
One challenge of analyzing samples of DNA sequences is to account for the nonnegligible polymorphisms produced by error when the sequencing error rate is high or the sample size is large. Specifically, those artificial sequence variations will bias the observed single nucleotide polymorphism (SNP) frequency spectrum, which in turn may further bias the estimators of the population mutation rate theta =4N mu for diploids. In this paper, we propose a new approach based on the generalized least squares (GLS) method to estimate theta, given a SNP frequency spectrum in a random sample of DNA sequences from a population. With this approach, error rate epsilon can be either known or unknown. In the latter case, epsilon can be estimated given an estimation of theta. Using coalescent simulation, we compared our estimators with other estimators of theta. The results showed that the GLS estimators are more efficient than other theta estimators with error, and the estimation of epsilon is usable in practice when the theta per bp is small. We demonstrate the application of the estimators with 10-kb noncoding region sequence sampled from a human population and provide suggestions for choosing theta estimators with error.
Keywords: Base Sequence; Computer Simulation; Humans; Mutation; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

The INSIG2 rs7566605 genetic variant does not play a major role in obesity in a sample of 24,722 individuals from four cohorts. - Bressler, Jan; Fornage, Myriam; Hanis, Craig L; Kao, Wen Hong Linda; Lewis, Cora E; McPherson, Ruth; Dent, Robert; Mosley, Thomas H; Pennacchio, Len A; Eric Boerwinkle (BMC Med Genet, 2009)
BACKGROUND: In a genome-wide association study performed in the Framingham Offspring Cohort, individuals homozygous for the rs7566605 C allele located upstream of insulin-induced gene 2 (INSIG2) were reported to incur an increased risk of obesity. This finding was later replicated in four out of five populations examined. The goal of the study reported here was to assess the role of the INSIG2 single nucleotide polymorphism (SNP) in susceptibility to obesity in the prospective longitudinal Atherosclerosis Risk in Communities (ARIC) study (n = 14,566) and in three other cohorts: the Coronary Artery Risk Development in Young Adults (CARDIA) study (n = 3,888), the Genetic Epidemiology Network of Arteriopathy (GENOA) study (n = 4,766), and extremely obese and lean individuals ascertained at the University of Ottawa (n = 1,502). The combined study sample is comprised of 24,722 white, African-American, and Mexican-American participants. METHODS: Differences in mean body mass index (BMI) and other anthropometric measures including weight, waist circumference, and waist-to-hip ratio were assessed by a general linear model in individuals categorized by INSIG2 rs7566605 genotype. Multivariable logistic regression was used to predict the risk of obesity (BMI >or= 30 kg/m2). RESULTS: There was no discernable variation in the frequencies of the three INSIG2 SNP genotypes observed between white, Hispanic, and African-American obese individuals and non-obese study subjects. When the relationship between rs7566605 and BMI considered either as a categorical variable or a continuous variable was examined, no significant association with obesity was found for participants in any of the four study populations or in a combined analysis (p = 0.38) under a recessive genetic model. There was also no association between the INSIG2 polymorphism and the obesity-related quantitative traits except for a reduced waist-to-hip ratio in white ARIC study participants homozygous for the C allele, and an increased waist-to-hip ratio in African-Americans in the ARIC cohort with the same genotype (p = 0.04 and p = 0.01, respectively). An association with waist-to-hip ratio was not seen when the combined study sample was analyzed (p = 0.74). CONCLUSION: These results suggest that the INSIG2 rs7566605 variant does not play a major role in determining obesity risk in a racially and ethnically diverse sample of 24,722 individuals from four cohorts.
Keywords: Alleles; Atherosclerosis; Black or African American; Body Mass Index; Case-Control Studies; Cohort Studies; Coronary Artery Disease; Genome-Wide Association Study; Genotype; Humans; Intracellular Signaling Peptides and Proteins; Logistic Models; Membrane Proteins; Mexican Americans; Obesity; Polymorphism, Single Nucleotide; Risk Factors; United States; White People; Young Adult

Kininogen gene (KNG) variation has a consistent effect on aldosterone response to antihypertensive drug therapy: the GERA study. - Barbalic, Maja; Schwartz, Gary L; Chapman, Arlene B; Turner, Stephen T; Eric Boerwinkle (Physiol Genomics, 2009)
Recent experimental and clinical studies suggested that apart from playing an essential role in blood pressure homeostasis, aldosterone is involved in the pathophysiology of cardiovascular and renal diseases by inducing structural changes in the heart, kidney, and vessel wall. The interindividual variation of aldosterone response to antihypertensive treatment is considerable, and is at least partially explained by genetic variation. In this study, we investigated aldosterone response to two antihypertensive drugs-a thiazide diuretic and an angiotensin receptor blocker (ARB). Genetic variations in 50 candidate genes were tested for association with aldosterone response in four independent samples: African American (AA) responders to a diuretic (n = 289), AA responders to an ARB (n = 252), European American (EA) responders to a diuretic (n = 295) and EA responders to an ARB (n = 300). Linear regression was used to test the association with inclusion of age, sex, and body mass index as covariates. The results indicated the existence of one or more variants in the kininogen gene (KNG) that influence interindividual variation in aldosterone response. The significant association was replicated in three of four studied groups. The single nucleotide polymorphism rs4686799 was associated in AA and EA responders to the diuretic (P = 0.04 and P = 0.07, respectively), and rs5030062 and rs698078 were significantly associated in EA responders to the diuretic (P = 0.05 and P = 0.01) and EA responders to the ARB (P = 0.04 and P = 0.02). Although the clinical implication of KNG gene variation to antihypertensive drug response is yet to be determined, this novel candidate locus provides important new insights into drug response physiology.
Keywords: Adult; Aldosterone; Antihypertensive Agents; Female; Genetic Variation; Genotype; Humans; Kininogens; Linkage Disequilibrium; Male; Middle Aged; Polymorphism, Single Nucleotide

Mutations in smooth muscle alpha-actin (ACTA2) cause coronary artery disease, stroke, and Moyamoya disease, along with thoracic aortic disease. - Guo, Dong-chuan; Papke, Christina L; Tran-Fadulu, Van; Regalado, Ellen S; Avidan, Nili; Johnson, Ralph Jay; Kim, Dong H; Pannu, Hariyadarshi; Willing, Marcia C; Sparks, Elizabeth; Pyeritz, Reed E; Singh, Michael N; et al. (Am J Hum Genet, 2009)
The vascular smooth muscle cell (SMC)-specific isoform of alpha-actin (ACTA2) is a major component of the contractile apparatus in SMCs located throughout the arterial system. Heterozygous ACTA2 mutations cause familial thoracic aortic aneurysms and dissections (TAAD), but only half of mutation carriers have aortic disease. Linkage analysis and association studies of individuals in 20 families with ACTA2 mutations indicate that mutation carriers can have a diversity of vascular diseases, including premature onset of coronary artery disease (CAD) and premature ischemic strokes (including Moyamoya disease [MMD]), as well as previously defined TAAD. Sequencing of DNA from patients with nonfamilial TAAD and from premature-onset CAD patients independently identified ACTA2 mutations in these patients and premature onset strokes in family members with ACTA2 mutations. Vascular pathology and analysis of explanted SMCs and myofibroblasts from patients harboring ACTA2 suggested that increased proliferation of SMCs contributed to occlusive diseases. These results indicate that heterozygous ACTA2 mutations predispose patients to a variety of diffuse and diverse vascular diseases, including TAAD, premature CAD, ischemic strokes, and MMD. These data demonstrate that diffuse vascular diseases resulting from either occluded or enlarged arteries can be caused by mutations in a single gene and have direct implications for clinical management and research on familial vascular diseases.
Keywords: Actins; Adolescent; Adult; Aortic Aneurysm, Thoracic; Aortic Dissection; Cell Proliferation; Cells, Cultured; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Humans; Male; Middle Aged; Models, Molecular; Moyamoya Disease; Mutation; Myocytes, Smooth Muscle; Protein Isoforms; Stroke; Young Adult

Rare loss-of-function mutations in ANGPTL family members contribute to plasma triglyceride levels in humans. - Romeo, Stefano; Yin, Wu; Kozlitina, Julia; Pennacchio, Len A; Eric Boerwinkle; Hobbs, Helen H; Cohen, Jonathan C (J Clin Invest, 2009)
The relative activity of lipoprotein lipase (LPL) in different tissues controls the partitioning of lipoprotein-derived fatty acids between sites of fat storage (adipose tissue) and oxidation (heart and skeletal muscle). Here we used a reverse genetic strategy to test the hypothesis that 4 angiopoietin-like proteins (ANGPTL3, -4, -5, and -6) play key roles in triglyceride (TG) metabolism in humans. We re-sequenced the coding regions of the genes encoding these proteins and identified multiple rare nonsynonymous (NS) sequence variations that were associated with low plasma TG levels but not with other metabolic phenotypes. Functional studies revealed that all mutant alleles of ANGPTL3 and ANGPTL4 that were associated with low plasma TG levels interfered either with the synthesis or secretion of the protein or with the ability of the ANGPTL protein to inhibit LPL. A total of 1% of the Dallas Heart Study population and 4% of those participants with a plasma TG in the lowest quartile had a rare loss-of-function mutation in ANGPTL3, ANGPTL4, or ANGPTL5. Thus, ANGPTL3, ANGPTL4, and ANGPTL5, but not ANGPTL6, play nonredundant roles in TG metabolism, and multiple alleles at these loci cumulatively contribute to variability in plasma TG levels in humans.
Keywords: Alleles; Amino Acid Sequence; Angiopoietin-Like Protein 1; Angiopoietin-like Proteins; Angiopoietins; Animals; Cell Line; Ethnicity; Genetic Variation; Humans; Mice; Mutation; Protein Isoforms; Tissue Distribution; Triglycerides

SELP and SELPLG genetic variation is associated with cell surface measures of SELP and SELPLG: the Atherosclerosis Risk in Communities Carotid MRI Study. - Volcik, Kelly A; Catellier, Diane; Folsom, Aaron R; Matijevic, Nena; Wasserman, Bruce; Eric Boerwinkle (Clin Chem, 2009)
BACKGROUND: P-selectin (SELP) and its ligand, P-selectin glycoprotein ligand 1 (SELPLG), play key roles in both the inflammatory response and the atherosclerotic process. Previous studies have shown genetic variation in the SELP gene [selectin P (granule membrane protein 140 kDa, antigen CD62)] to be associated with plasma SELP concentrations; however, the major biological function of SELP (and SELPLG) is at the cell surface. We therefore investigated the association of SELP polymorphisms with platelet SELP measures and polymorphisms in the SELPLG gene (selectin P ligand) with lymphocyte, granulocyte, and monocyte SELPLG measures among 1870 participants in the Atherosclerosis Risk in Communities (ARIC) Carotid MRI Study. METHODS: Whole-blood flow cytometry was used to analyze leukocyte and platelet markers in the ARIC Carotid MRI Study. The allele frequencies for the SELP and SELPLG polymorphisms of whites and African Americans were markedly different; therefore, all analyses were race specific. RESULTS: SELP T715P was significantly associated with lower values for platelet SELP measures in whites (P = 0.0001), whereas SELP N562D was significantly associated with higher values for SELP measures in African Americans (P = 0.02). SELPLG M62I was significantly associated with lower granulocyte and monocyte SELPLG measures in African Americans (P = 0.003 and P = 0.0002, respectively) and with lower lymphocyte SELPLG measures in whites (P = 0.01). CONCLUSIONS: Specific SELP and SELPLG polymorphisms were associated with cell surface measures of SELP and SELPLG in both whites and African Americans in the ARIC Carotid MRI Study. To our knowledge, this study is the first to examine the association of SELP and SELPLG genetic variation with measures of cell surface SELP and SELPLG.
Keywords: Atherosclerosis; Black People; Carotid Arteries; Flow Cytometry; Humans; Magnetic Resonance Imaging; Membrane Glycoproteins; Middle Aged; Polymorphism, Genetic; Risk Factors; Selenoprotein P; White People

Use of wrapper algorithms coupled with a random forests classifier for variable selection in large-scale genomic association studies. - Rodin, Andrei S; Litvinenko, Anatoliy; Klos, Kathy; Morrison, Alanna C; Woodage, Trevor; Coresh, Josef; Eric Boerwinkle (J Comput Biol, 2009)
Modern large-scale genetic association studies generate increasingly high-dimensional datasets. Therefore, some variable selection procedure should be performed before the application of traditional data analysis methods, for reasons of both computational efficiency and problems related to overfitting. We describe here a "wrapper" strategy (SIZEFIT) for variable selection that uses a Random Forests classifier, coupled with various local search/optimization algorithms. We apply it to a large dataset consisting of 2,425 African-American and non-Hispanic white individuals genotyped for 4,869 single-nucleotide polymorphisms (SNPs) in a coronary heart disease (CHD) case-cohort association study (Atherosclerosis Risk in Communities), using incident CHD and plasma low-density lipoprotein (LDL) cholesterol levels as the dependent variables. We show that most SNPs can be safely removed from the dataset without compromising the predictive (classification) accuracy, with only a small number of SNPs (sometimes less than 100) containing any predictive signal. A statistical (SUMSTAT) approach is also applied to the dataset for comparison purposes. We describe a novel method for refining the subset of signal-containing SNPs (FIXFIT), based on an Extremal Optimization algorithm. Finally, we compare the top SNP rankings obtained by different methods and devise practical guidelines for researchers trying to generate a compact subset of predictive SNPs from genome-wide association datasets. Interestingly, there is a significant amount of overlap between seemingly very heterogeneous rankings. We conclude by constructing compact optimal predictive SNP subsets for CHD (less than 150 SNPs) and LDL (less than 300 SNPs) phenotypes, and by comparing various rankings for two well-known positive control SNPs for LDL in the apolipoprotein E gene.
Keywords: Algorithms; Apolipoproteins E; Atherosclerosis; Black or African American; Databases, Genetic; Genetic Predisposition to Disease; Genome-Wide Association Study; Humans; Models, Genetic

APOE/C1/C4/C2 hepatic control region polymorphism influences plasma apoE and LDL cholesterol levels. - Klos, Kathy; Shimmin, Lawrence; Ballantyne, Christie; Eric Boerwinkle; Clark, Andrew; Coresh, Josef; Hanis, Craig; Liu, Kiang; Sayre, Scott; Hixson, James (Hum Mol Genet, 2008)
We characterized 102 kb of chromosome 19 containing the apolipoprotein (APO) E/C1/C4/C2 cluster and two flanking genes for common DNA variants associated with plasma low-density lipoprotein cholesterol (LDL-C) level. DNA variants were identified by comparing sequences of 48 haploid hybrid cell lines. We genotyped participants (1943 Whites and 2046 African-Americans) of the Coronary Artery Risk Development in Young Adults study for 115 variants. After controlling for the effects of the APOE epsilon2/3/4 polymorphism, a single nucleotide polymorphism, rs35136575, in the downstream hepatic control region 2 (HCR-2) was associated with LDL-C in Caucasians (P = 0.0004), accounting for 1% of variation. We genotyped rs35136575 in the Atherosclerosis Risk in Communities (ARIC) cohort (3679 African-Americans and 10 427 Whites) and in the Genetic Epidemiology Network of Arteriopathy (GENOA) sibships (1381 African-Americans in 592 sibships, 1116 Caucasians in 503 sibships and 1378 Mexican-Americans in 416 sibships), finding association with LDL-C level in ARIC Caucasians (P = 0.0064). Lower plasma LDL-C was observed with the rare allele. Plasma apoE level was strongly associated with HCR-2 variant genotype in all three GENOA samples (P </= 0.002), indicating an effect on apoE concentration. Patterns of association for plasma apo A-I, apoB, LDL-C, high-density lipoprotein cholesterol, total cholesterol and triglyceride levels with rs35136575 in the population-based samples evaluated in this study suggest a pleiotropic effect that may be context-dependent.
Keywords: Adult; Aged; Animals; Apolipoproteins; Apolipoproteins E; Black or African American; Cholesterol; Cholesterol, LDL; Chromosomes, Human, Pair 19; Female; Genotype; Humans; Hybrid Cells; Male; Mexican Americans; Mice; Middle Aged; Polymorphism, Single Nucleotide; United States; White People

Association of the complement factor H Y402H polymorphism with cardiovascular disease is dependent upon hypertension status: The ARIC study. - Volcik, Kelly A; Ballantyne, Christie M; Braun, Michael C; Coresh, Josef; Mosley, Thomas H; Eric Boerwinkle (Am J Hypertens, 2008)
BACKGROUND: Complement factor H (CFH) is a plasma protein that is essential in the regulation of the alternative complement pathway and has been implicated as taking part in complement inhibition in atherogenesis. We evaluated the association of the Y402H polymorphism with incident coronary heart disease (CHD), incident ischemic stroke, and carotid artery wall thickness (intima-media thickness (IMT)) in the Atherosclerosis Risk in Communities (ARIC) cohort. METHODS: Incident ischemic stroke and CHD were identified through annual telephone calls and hospital and death certificate surveillance. Carotid IMT was measured by means of high-resolution B-mode ultrasound. Four hundred eighty-three validated ischemic stroke and 1,544 CHD events were identified. Because of allele frequency differences between whites and African Americans, analyses were performed separately according to the racial group. RESULTS: The 402HH homozygous genotype was a significant predictor of incident ischemic stroke in whites (hazard rate ratio (HRR) 1.47, 95% confidence interval (CI) 1.05-2.05). Significant interaction effects between genotype and hypertension were observed for CHD in whites and for cIMT in whites and African Americans. In further analyses of incident CHD, genotypes carrying the 402H allele were a significant predictor of incident CHD in whites who had hypertension (402YH: HRR 1.19, 95% CI 1.01-1.40; 402HH: HRR 1.28, 95% CI 1.04-1.57). The 402H allele was also associated with higher cIMT measures for whites in the overall cohort, and for whites with hypertension. CONCLUSION: The CFH 402H allele was associated with an increased risk for incident CHD and ischemic stroke in whites, with the strength and significance of the association dependent upon hypertension status.
Keywords: Black or African American; Brain Ischemia; Cardiovascular Diseases; Carotid Artery Diseases; Complement Factor H; Coronary Disease; Female; Gene Frequency; Genetic Predisposition to Disease; Homozygote; Humans; Hypertension; Male; Middle Aged; Polymorphism, Genetic; Proportional Hazards Models; Prospective Studies; Risk Assessment; Risk Factors; Stroke; United States; White People

Comprehensive evaluation of apolipoprotein H gene (APOH) variation identifies novel associations with measures of lipid metabolism in GENOA. - Leduc, Magalie S; Shimmin, Lawrence C; Klos, Kathy L E; Hanis, Craig; Eric Boerwinkle; Hixson, James E (J Lipid Res, 2008)
Apolipoprotein H (apoH, also named beta-2 glycoprotein I) is found on several classes of lipoproteins, and is involved in the activation of lipoprotein lipase in lipid metabolism. We have comprehensively investigated the association of variation in the apoH gene (APOH) with lipid traits in hepatic cholesterol transport, dietary cholesterol transport (DCT), and reverse cholesterol transport (RCT). Our study population consisted of families from the Genetic Epidemiology Network of Arteriopathy multicenter study that include African Americans, Mexican Americans, and European Americans. We individually tested 36 single-nucleotide polymorphisms (SNPs) that span the APOH locus, including nonsynonymous variants that result in known apoH charge isoforms. In addition, we constructed haplotypes from SNPs in the 5' promoter region that comprise cis-acting regulatory elements, as well as haplotypes for multiple amino acid substitutions. We found point-wise significant associations of APOH variants with various lipid measures in the three racial groups. The strongest associations were found for DCT traits (triglyceride and apoE levels) in Mexican Americans with a nonsynonymous variant (SNP 14917, Cys306Gly) that may alter apoH protein folding in a region involved in phospholipid binding. In conclusion, family-based analyses of APOH variants have identified associations with measures of lipid metabolism in three American racial groups.
Keywords: beta 2-Glycoprotein I; Black People; Genetic Variation; Genotype; Haplotypes; Humans; Lipid Metabolism; Multicenter Studies as Topic; Polymorphism, Single Nucleotide; White People

ESR1 polymorphism is associated with plasma lipid and apolipoprotein levels in Caucasians of the Rochester Family Heart Study. - Klos, Kathy L E; Eric Boerwinkle; Ferrell, Robert E; Turner, Stephen T; Morrison, Alanna C (J Lipid Res, 2008)
We evaluated six estrogen receptor 1 (ESR1) polymorphisms for association with ten plasma lipid and apolipoprotein traits in 1,847 individuals (941 females and 906 males) in the multi-generation Rochester Family Heart Study using a generalized estimating equation approach. Apolipoprotein A-I (apoA-I), apoA-II, and HDL-cholesterol (HDL-C) were associated with exon 4 rs1801132 (Pro325Pro) genotype (P = 0.0044, P = 0.0048, and P = 0.0035, respectively). Positive correlation between levels of apoA-I, apoA-II, and HDL-C and the number of G alleles was observed in females (P = 0.0120, P = 0.0032, and P = 0.0030), but not males (P > 0.05). Because few studies have evaluated the effect of ESR1 gene polymorphisms on lipid traits in children, we also stratified our sample at the age of 15 years. There was evidence of association between intron 1 single-nucleotide polymorphisms rs9322331 and rs9340799 and apoC-II, and triglycerides (TGs) in youths 15 years and younger. In youths, evidence of association between rs9322331 and rs9340799 and apoC-II was stronger in males (P = 0.0036 and P = 0.0124) than in females (P > 0.05), whereas evidence of association with TG was stronger in females (P = 0.0030 and P = 0.0024) than in males (P > 0.05). These findings suggest that ESR1 variation plays an age- and sex-dependent role in determining plasma lipid and apolipoprotein levels.
Keywords: Adolescent; Adult; Aged; Apolipoprotein A-I; Apolipoprotein A-II; Apolipoproteins; Cholesterol, HDL; Estrogen Receptor alpha; Female; Humans; Male; Polymorphism, Genetic; Triglycerides; White People

Hepatocyte nuclear factor 1 and hypertensive nephropathy. - Dmitrieva, Renata I; Hinojos, Cruz A; Eric Boerwinkle; Braun, Michael C; Fornage, Myriam; Doris, Peter A (Hypertension, 2008)
Hypertension in spontaneously hypertensive rat (SHR) is associated with renal redox stress, and we hypothesized that nephropathy arises in SHR-A3 from altered capacity to mitigate redox stress compared with nephropathy-resistant SHR lines. We measured renal expression of redox genes in distinct lines of the spontaneously hypertensive rat (SHR-A3, SHR-B2, SHR-C) and the normotensive Wistar-Kyoto (WKY) strain. The SHR lines differ in either resisting (SHR-B2, SHR-C) or experiencing hypertensive nephropathy (SHR-A3). Immediately before the emergence of hypertensive renal injury expression of redox genes in SHR-A3 was profoundly altered compared with the injury-resistant SHR lines and WKY. This change appeared to arise in antioxidant genes where 16 of 28 were expressed at 34.3% of the level in the reference strain (WKY). No such change was observed in the injury-resistant SHR lines. We analyzed occurrence of transcription factor matrices in the promoters of the downregulated antioxidant genes. In these genes, the hepatocyte nuclear factor 1 (HNF1) transcription factor matrix was found to be nearly twice as likely to be present and the overall frequency of HNF1 sites was nearly 5 times higher, compared with HNF1 transcription factor matrices in antioxidant genes that were not downregulated. We identified 35 other (nonredox) renal genes regulated by HNF1. These were also significantly downregulated in SHR-A3, but not in SHR-B2 or SHR-C. Finally, expression of genes that comprise HNF1 (Tcf1, Tcf2, and Dcoh) was also downregulated in SHR-A3. The present experiments uncover a major change in transcriptional control by HNF1 that affects redox and other genes and precedes emergence of hypertensive renal injury.
Keywords: Animal Feed; Animals; Blood Pressure; Gene Expression Profiling; Hepatocyte Nuclear Factor 1; Hypertension, Renal; Kidney; Male; Oxidation-Reduction; Oxidative Stress; Rats; Rats, Inbred SHR; Rats, Inbred WKY; Transcription, Genetic

Longitudinal changes in triglycerides according to ANGPTL4[E40K] genotype and longitudinal body weight change in the atherosclerosis risk in communities study. - Nettleton, Jennifer A; Volcik, Kelly A; Demerath, Ellen W; Eric Boerwinkle; Folsom, Aaron R (Ann Epidemiol, 2008)
PURPOSE: Allelic variation in the adipokine angiopoietin-like 4 gene (ANGPTL4[E40K]) has been cross-sectionally associated with triglycerides, but the effects of genotype, or the interaction between genotype and body weight, on longitudinal triglyceride change have not been studied. METHODS: Body weight, triglycerides, and ANGPTL4[E40K] genotype were determined at baseline (1987-1989) and at 3 follow-up exams (1990-1992, 1993-1995, 1996-1998) in 7,939 white ANGPTL4[E40K] G allele homozygotes and 344 A allele carriers. Changes in body weight and triglycerides were characterized as the difference between exam 4 and baseline measurements. RESULTS: ANGPTL4[E40K] A allele carriers had triglyceride concentrations that were 15 to 18 mg/dL lower than G allele homozygotes at all exams (P<0.0001). Triglycerides increased in both genotype groups over the 9-year period (+19.1+/-0.9 and +16.2+/-4.1 mg/dL in GG and GA/AA, respectively; P difference, 0.48). Weight gain was associated with increased triglycerides to a comparable degree in both genotype groups (+5.5+/-0.3 and +4.3+/-0.9 mg/dL per 2-kg increase in body weight in GG and GA/AA, respectively, p interaction=0.30). CONCLUSIONS: Differences in triglyceride concentrations between ANGPTL4[E40K] A allele carriers and G allele homozygotes are maintained over time, but the degree of increase in triglycerides was similar between groups and was not modified by body weight changes.
Keywords: Aged; Angiopoietin-Like Protein 4; Angiopoietins; Atherosclerosis; Body Mass Index; Female; Humans; Longitudinal Studies; Male; Middle Aged; Risk Factors; Triglycerides; United States; Weight Gain

Peroxisome proliferator-activated receptor [alpha] genetic variation interacts with n-6 and long-chain n-3 fatty acid intake to affect total cholesterol and LDL-cholesterol concentrations in the Atherosclerosis Risk in Communities Study. - Volcik, Kelly A; Nettleton, Jennifer A; Ballantyne, Christie M; Eric Boerwinkle (Am J Clin Nutr, 2008)
BACKGROUND: Peroxisome proliferator-activated receptor-alpha (PPARA) regulates the expression of genes involved in lipid metabolism. The binding of polyunsaturated fatty acids (PUFAs) to PPARA results in rapid changes in the expression of genes involved in lipid oxidation, with long-chain n-3 fatty acids being potent activators of PPARA. OBJECTIVE: We evaluated the potential effect modification of PPARA genetic variation on the association between PUFA intake, specifically n-6 and long-chain n-3 fatty acid intakes, and multiple lipid measures in the large biethnic Atherosclerosis Risk in Communities (ARIC) Study. DESIGN: Study participants (10 134 whites and 3480 African Americans) were selected from the ARIC Study--a prospective investigation of atherosclerosis and its clinical sequelae. Multiple linear regression models were used to assess the relation between PPARA genotypes, as well as dietary fatty acid intake, and baseline lipid measures. PPARA-specific effects of variation were assessed by including genotype-by-fatty acid interaction terms in each statistical model. RESULTS: PPARA genotype frequencies were significantly different between whites and African Americans. No significant associations between lipid measures and PPARA genotype were observed in either whites or African Americans. Significant genotype-by-n-6 fatty acid intake interactions were observed only in whites for the 3'untranslated region (UTR) G-->A single nucleotide polymorphism (SNP) and total cholesterol (P = 0.03) and LDL cholesterol (P = 0.03). Significant genotype-by-long-chain n-3 fatty acid intake interactions were observed only in African Americans for the 3'UTR C-->T SNP and total cholesterol (P = 0.03) and LDL cholesterol (P = 0.02). CONCLUSIONS: Findings from the current study suggest that PPARA 3'UTR SNPs modulate the association between lipid concentrations and dietary n-6 fatty acid intake (in whites) and long-chain n-3 fatty acid intake (in African Americans) such that persons with homozygous variant genotypes have significantly lower total cholesterol and LDL-cholesterol measures when consuming higher quantities of n-6 or long-chain n-3 fatty acids.
Keywords: 3' Untranslated Regions; Atherosclerosis; Black People; Cholesterol; Cholesterol, LDL; Dietary Fats; Fatty Acids, Omega-3; Fatty Acids, Omega-6; Female; Gene Frequency; Genetic Variation; Genotype; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; PPAR alpha; Risk Factors; United States; White People

Regional association-based fine-mapping for sodium-lithium countertransport on chromosome 10. - Morrison, Alanna C; Eric Boerwinkle; Turner, Stephen T; Ferrell, Robert E (Am J Hypertens, 2008)
BACKGROUND: Increased erythrocyte sodium-lithium countertransport (SLC) has been observed in patients with essential hypertension. Consistent evidence of genetic linkage was shown for SLC on chromosome 10, and a region of interest was localized between 26 and 56 Mb. METHODS: This study surveyed single nucleotide polymorphisms (SNPs) in 54 genes that reside in the region of interest, and investigated their association with SLC and blood pressure. These SNPs were genotyped in 1,133 non-Hispanic white individuals from 255 pedigrees comprising the second phase of the Rochester Family Heart Study. The variance-components-based genetics software package SOLAR was used for evaluating whether an SNP contributed to a significant fraction of the trait heritability. RESULTS: Of the 77 SNPs surveyed in this study across the region of interest, four SNPs were associated with SLC (P < 0.04), five SNPs were associated with blood pressure (P < 0.04), and two SNPs in mannose-binding lectin 2 (MBL2) were associated with both phenotypes. In general, the pairwise linkage disequilibrium among the genotyped SNPs was low. CONCLUSIONS: This fine-mapping survey of genetic variation in a linkage region of interest provides overall support for association-mapping for SLC on chromosome 10. Genes significantly associated with systolic blood pressure and/or SLC in these families will be prioritized for future studies.
Keywords: Adolescent; Adult; Aged; Antiporters; Blood Pressure; Child; Chromosome Mapping; Chromosomes, Human, Pair 10; Erythrocytes; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Hypertension; Linkage Disequilibrium; Male; Mannose-Binding Lectin; Middle Aged; Minnesota; Pedigree; Phenotype; Polymorphism, Single Nucleotide; Risk Factors

Relationship of alcohol consumption and type of alcoholic beverage consumed with plasma lipid levels: differences between Whites and African Americans of the ARIC study. - Volcik, Kelly A; Ballantyne, Christie M; Fuchs, Flavio D; Sharrett, A Richey; Eric Boerwinkle (Ann Epidemiol, 2008)
PURPOSE: Alcohol consumption has been shown to contribute to a favorable lipid profile, and most studies have reported a reduction in coronary heart disease risk with low-to-moderate consumption of alcohol that is generally attributed to the beneficial effects of alcohol on lipids. The influence of different types of alcoholic beverages on plasma lipid levels has been investigated to a lesser extent and in limited populations. METHODS: We investigated the effect of overall alcohol consumption, as well as the type of alcoholic beverage consumed, on multiple lipid measures in the large bi-ethnic population of the Atherosclerosis Risk in Communities study. RESULTS: We found both low-to-moderate and heavy alcohol consumption, regardless of the type of alcoholic beverage consumed, to result in significantly greater levels of high-density lipoprotein (HDL) cholesterol, HDL3 cholesterol, and apolipoprotein A-I in both white and African-American males and females. Associations with other lipid measures contrasted between whites and African Americans, with greater levels of alcohol consumption resulting in significantly greater triglyceride levels in African Americans. CONCLUSIONS: Our results confirm previous studies associating alcohol consumption, regardless of beverage type, with greater HDL cholesterol levels, with additional consistent associations detected for the major HDL cholesterol density subfraction, HDL3 cholesterol, and the major HDL cholesterol structural apolipoprotein, apolipoprotein A-I.
Keywords: Alcohol Drinking; Alcoholic Beverages; Black or African American; Humans; Lipoproteins; United States; White People

Single nucleotide polymorphisms associated with coronary heart disease predict incident ischemic stroke in the atherosclerosis risk in communities study. - Morrison, Alanna C; Bare, Lance A; Luke, May M; Pankow, James S; Mosley, Thomas H; Devlin, James J; Willerson, James T; Eric Boerwinkle (Cerebrovasc Dis, 2008)
Ischemic stroke and coronary heart disease (CHD) may share genetic factors contributing to a common etiology. This study investigates whether 51 single nucleotide polymorphisms (SNPs) associated with CHD in multiple antecedent studies are associated with incident ischemic stroke in the Atherosclerosis Risk in Communities (ARIC) study. From the multiethnic ARIC cohort of 14,215 individuals, 495 validated ischemic strokes were identified. Cox proportional hazards models, adjusted for age and gender, identified three SNPs in Whites and two SNPs in Blacks associated with incident stroke (p <or= 0.05). The rs11628722 polymorphism in SERPINA9 was associated with incident stroke in Whites and Blacks, even after taking into account traditional risk factors. The idea that ischemic stroke and CHD may share some common genetic factors, such as variation in SERPINA9, should be investigated in other studies.
Keywords: Black People; Brain Ischemia; Coronary Disease; Female; Genetic Predisposition to Disease; Genotype; Humans; Incidence; Intracranial Arteriosclerosis; Male; Middle Aged; Myocardial Infarction; Neoplasm Proteins; Polymorphism, Single Nucleotide; Predictive Value of Tests; Proportional Hazards Models; Risk Factors; Serpins; Stroke; White People

Absence of an interaction between the angiotensin-converting enzyme insertion-deletion polymorphism and pravastatin on cardiovascular disease in high-risk hypertensive patients: the Genetics of Hypertension-Associated Treatment (GenHAT) study. - Maitland-van der Zee, Anke-Hilse; Eric Boerwinkle; Arnett, Donna K; Davis, Barry R; Leiendecker-Foster, Catherine; Miller, Michael B; Klungel, Olaf H; Ford, Charles E; Eckfeldt, John H (Am Heart J, 2007)
BACKGROUND: The aim of this study was to determine whether the angiotensin-converting enzyme (ACE) insertion-deletion (ID) polymorphism interacts with pravastatin to modify the risk of coronary heart disease (CHD) and other cardiovascular end points in a large clinical trial. METHODS: GenHAT is an ancillary study of the ALLHAT. The ACE ID genotyped population in the lipid-lowering arm of ALLHAT included 9467 participants randomly assigned to pravastatin (n = 4741) or to usual care (n = 4726). The efficacy of pravastatin in reducing the risk of primary outcome (all-cause mortality) and secondary outcomes (fatal CHD and nonfatal myocardial infarction, cardiovascular disease [CVD] mortality, CHD, stroke, other CVD, non-CVD mortality, stroke, and heart failure) was compared between the genotype strata (dominant model ID + II vs DD, additive model II vs ID vs DD), by examining an interaction term in a Cox proportional hazards model. RESULTS: The relative risk of fatal CHD and nonfatal myocardial infarction among subjects randomized to pravastatin compared with subjects randomized to usual care was similar in subjects with the II genotype (hazard ratio [HR] 0.84, 95% CI 0.59-1.18), the ID genotype (HR 0.84, 95% CI 0.68-1.03), and the DD genotype (HR 0.99, 95% CI 0.77-1.27). CONCLUSIONS: We found no evidence that the ACE ID genotype was a major modifier of the efficacy of pravastatin in reducing the risk of cardiovascular events.
Keywords: Aged; Antihypertensive Agents; Coronary Disease; Female; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hypertension; Male; Middle Aged; Myocardial Infarction; Peptidyl-Dipeptidase A; Pharmacogenetics; Polymorphism, Genetic; Pravastatin; Proportional Hazards Models; Randomized Controlled Trials as Topic; Risk Assessment

Corticotropin releasing hormone (CRH) gene variation: comprehensive resequencing for variant and molecular haplotype discovery in monosomic hybrid cell lines. - Shimmin, Lawrence C; Natarajan, Sivamani; Ibarguen, Heladio; Montasser, May; Kim, Do-Kyun; Hanis, Craig L; Eric Boerwinkle; Wadhwa, Pathik D; Hixson, James E (DNA Seq, 2007)
Candidate gene association studies have met with mixed success due to many reasons including incomplete surveys of genetic variation and differences in patterns of genetic variation among study populations. We present the results of comprehensive variant discovery for the corticotropin releasing hormone gene (CRH on chromosome 8) encoding a neuropeptide that is central to many physiologic pathways. Mouse-human hybrid cell lines were constructed that are monosomic for human chromosome 8 for resequencing of separated CRH alleles to identify variants and directly determine their chromosomal phase for three major ethnic groups including African Americans (AA), Mexican Americans (MA) and European Americans (EA). We also resequenced diploid individuals to evaluate single nucleotide polymorphism (SNP) discovery in the limited numbers of monosomic hybrid cell lines. Our results show that CRH variation is very different in AA, yielding larger numbers of variants and haplotypes compared to MA and EA. Analysis of LD structure found three haplotype blocks in AA and two blocks in EA. Comparisons between AA and EA groups yielded extremely high measures of genetic differentiation (Wright's F(ST)>0.6), likely reflecting disruptive selection in CRH evolution. Network analysis showed that AA have retained an ancestral CRH haplotype, while the most common EA haplotype is derived from a single recombination event.
Keywords: Animals; Base Sequence; Cell Line; Corticotropin-Releasing Hormone; Ethnicity; Female; Haplotypes; Humans; Hybrid Cells; Linkage Disequilibrium; Male; Mice; Molecular Sequence Data; Monosomy; Phylogeny; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

An entropy-based genome-wide transmission/disequilibrium test. - Zhao, Jinying; Eric Boerwinkle; Xiong, Momiao (Hum Genet, 2007)
Availability of a large collection of single nucleotide polymorphisms (SNPs) and efficient genotyping methods enable the extension of linkage and association studies for complex diseases from small genomic regions to the whole genome. Establishing global significance for linkage or association requires small P-values of the test. The original TDT statistic compares the difference in linear functions of the number of transmitted and nontransmitted alleles or haplotypes. In this report, we introduce a novel TDT statistic, which uses Shannon entropy as a nonlinear transformation of the frequencies of the transmitted or nontransmitted alleles (or haplotypes), to amplify the difference in the number of transmitted and nontransmitted alleles or haplotypes in order to increase statistical power with large number of marker loci. The null distribution of the entropy-based TDT statistic and the type I error rates in both homogeneous and admixture populations are validated using a series of simulation studies. By analytical methods, we show that the power of the entropy-based TDT statistic is higher than the original TDT, and this difference increases with the number of marker loci. Finally, the new entropy-based TDT statistic is applied to two real data sets to test the association of the RET gene with Hirschsprung disease and the Fcgamma receptor genes with systemic lupus erythematosus. Results show that the entropy-based TDT statistic can reach p-values that are small enough to establish genome-wide linkage or association analyses.
Keywords: Entropy; Gene Frequency; Genetic Techniques; Genome, Human; Haplotypes; Hirschsprung Disease; Humans; Linkage Disequilibrium; Lupus Erythematosus, Systemic; Models, Genetic; Models, Statistical; Proto-Oncogene Proteins c-ret; Receptors, IgG

Family-based association study of matrix metalloproteinase-3 and -9 haplotypes with susceptibility to ischemic white matter injury. - Fornage, Myriam; Mosley, Thomas H; Jack, Clifford R; de Andrade, Mariza; Kardia, Sharon L R; Eric Boerwinkle; Turner, Stephen T (Hum Genet, 2007)
Susceptibility to ischemic damage to the subcortical white matter of the brain has a strong genetic basis. Dysregulation of matrix metalloproteinases (MMPs) contributes to loss of cerebrovascular integrity and white matter injury. We investigated whether sequence variation in the genes encoding MMP3 and MMP9 is associated with variation in leukoaraiosis volume, determined by magnetic resonance imaging, in non-Hispanic whites and African-Americans using family-based association tests. Seven hundred and fifty-six white and 671 African-American individuals from sibships ascertained through two or more siblings with hypertension were genotyped for 7 and 8 haplotype-tagging polymorphisms in the MMP3 and MMP9 genes, respectively. MMP3 sequence variation was significantly associated with variation in leukoaraiosis volume in Whites. Two common haplotypes with opposing relationships to leukoaraiosis volume were identified. MMP9 sequence variation was also significantly associated with variation in leukoaraiosis volume in both African-Americans and Whites. Different haplotypes contributed to these associations in the two racial groups. These findings add to the growing body of evidence from animal models and human clinical studies suggesting a role of MMPs in ischemic white matter injury. They provide the basis for further investigation of the role of these genes in susceptibility and/or progression to clinical disease.
Keywords: Aged; Base Sequence; Black or African American; Brain Ischemia; Family Health; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Haplotypes; Humans; Leukoaraiosis; Linkage Disequilibrium; Male; Matrix Metalloproteinase 3; Matrix Metalloproteinase 9; Middle Aged; Polymorphism, Single Nucleotide; Siblings; White People

A genome-wide linkage scan for diabetic retinopathy susceptibility genes in Mexican Americans with type 2 diabetes from Starr County, Texas. - Hallman, D Michael; Eric Boerwinkle; Gonzalez, Victor H; Klein, Barbara E K; Klein, Ronald; Hanis, Craig L (Diabetes, 2007)
We conducted a genome-wide linkage scan for genes contributing to retinopathy risk using 794 diabetes case subjects from 393 Mexican-American families from Starr County, Texas, having at least two diabetic siblings. The sample included 567 retinopathy case subjects comprising 282 affected sibling pairs. Retinopathy was classified as none, early nonproliferative, moderate-to-severe nonproliferative, or proliferative. Using 360 polymorphic markers (average spacing 9.4 cM), we conducted nonparametric linkage analysis followed by ordered-subset analysis (OSA) ranking families by average age of diabetes diagnosis. For any retinopathy, the highest LOD scores including all families were on chromosomes 3 (2.41 at 117 cM) and 12 (2.47 at 15.5). OSA logarithm of odds (LOD) scores >2 for any retinopathy occurred on chromosomes 12 (4.47 at 13.2 cM), 15 (3.65 at 100.6), and 20 (2.67 at 54.1). Scores >2 for either moderate-to-severe nonproliferative or proliferative retinopathy occurred on chromosomes 5 (2.53 at 11.2 cM), 6 (2.28 at 30.6), and 19 (2.21 at 100.6). Thus, unconditional linkage analysis revealed suggestive evidence of linkage with retinopathy on two chromosomes, whereas OSA revealed strong evidence of linkage on two chromosomes, and suggestive evidence on four. Candidate genes were identified in most implicated regions.
Keywords: Adult; Age of Onset; Body Mass Index; Diabetes Mellitus, Type 2; Diabetic Retinopathy; Family; Female; Genetic Predisposition to Disease; Genome, Human; Humans; Lod Score; Male; Mexican Americans; Middle Aged; Retinal Diseases; Siblings; Texas

Interaction effects of high-density lipoprotein metabolism gene variation and alcohol consumption on coronary heart disease risk: the atherosclerosis risk in communities study. - Volcik, Kelly; Ballantyne, Christie M; Pownall, Henry J; Sharrett, A Richey; Eric Boerwinkle (J Stud Alcohol Drugs, 2007)
OBJECTIVE: Light to moderate alcohol consumption has been widely established to be protective against coronary heart disease (CHD), whereas heavy alcohol consumption has been shown to have a potential detrimental effect. The reduction in risk of CHD associated with light and moderate alcohol intake is generally attributed to the beneficial effects of alcohol on high-density lipoprotein (HDL) cholesterol levels. Previous research in the Atherosclerosis Risk in Communities (ARIC) study showed all levels of alcohol consumption to be protective against CHD in whites but to be associated with an increased risk of CHD in black men. We investigated the ARIC cohort to determine whether risk of incident CHD is influenced by an interaction effect between alcohol intake and genetic variation involved in the regulation of HDL cholesterol. Genes of interest included cholesterol ester transfer protein (CETP), lipoprotein lipase (LPL), hepatic lipase (HL), and paraoxonase-1 (PON1). METHOD: Participants were selected from the ARIC study, a prospective investigation of atherosclerosis and its clinical sequelae, involving 15,792 individuals, ages 45-64 years at recruitment (1987-1989). Incident CHD was identified through annual telephone calls and hospital and death certificate surveillance. Because of ethnic differences in the alcohol-CHD relationship observed in the ARIC cohort and pattern of alcohol consumption differences, statistical analyses were evaluated separately for each race-gender stratum (white men/women, black men/women). RESULTS: Genotype modified the relationship between heavy drinking and CHD risk but did not modify this relationship for light or moderate drinking. Interaction analyses were significant for heavy alcohol intake and PON1 genotype (p=.02) in black men, with a suggested interaction for heavy alcohol intake and CETP genotype (p=.06) in black men. Heavy drinking was associated with an increased risk for CHD in black men with the PON1 QQ and CETP GG genotypes (PON1 hazard rate ratio [HRR]=17.3, 95% confidence interval [CI]: 1.76-170.2; CETP HRR=2.23, 95% CI: 1.01-4.91). CONCLUSIONS: Results from the current study suggest that interaction effects between alcohol consumption and HDL cholesterol metabolism gene variation influence the risk of incident CHD in black men. Additional studies are warranted to confirm these findings.
Keywords: Age Factors; Alcohol Drinking; Aryldialkylphosphatase; Black People; Cholesterol Ester Transfer Proteins; Cholesterol, HDL; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genetic Variation; Genotype; Humans; Lipase; Lipoprotein Lipase; Male; Middle Aged; Prospective Studies; Risk; Sex Factors; White People

Population-based resequencing of ANGPTL4 uncovers variations that reduce triglycerides and increase HDL. - Romeo, Stefano; Pennacchio, Len A; Fu, Yunxin; Eric Boerwinkle; Tybjaerg-Hansen, Anne; Hobbs, Helen H; Cohen, Jonathan C (Nat Genet, 2007)
Resequencing genes provides the opportunity to assess the full spectrum of variants that influence complex traits. Here we report the first application of resequencing to a large population (n = 3,551) to examine the role of the adipokine ANGPTL4 in lipid metabolism. Nonsynonymous variants in ANGPTL4 were more prevalent in individuals with triglyceride levels in the lowest quartile than in individuals with levels in the highest quartile (P = 0.016). One variant (E40K), present in approximately 3% of European Americans, was associated with significantly lower plasma levels of triglyceride and higher levels of high-density lipoprotein cholesterol in European Americans from the Atherosclerosis Risk in Communities Study and in Danes from the Copenhagen City Heart Study. The ratio of nonsynonymous to synonymous variants was higher in European Americans than in African Americans (4:1 versus 1.3:1), suggesting population-specific relaxation of purifying selection. Thus, resequencing of ANGPTL4 in a multiethnic population allowed analysis of the phenotypic effects of both rare and common variants while taking advantage of genetic variation arising from ethnic differences in population history.
Keywords: Adult; Angiopoietin-Like Protein 4; Angiopoietins; Black or African American; Cholesterol, HDL; Cohort Studies; Energy Metabolism; Gene Frequency; Genetic Linkage; Hispanic or Latino; Humans; Intercellular Signaling Peptides and Proteins; Middle Aged; Phenotype; Polymorphism, Single Nucleotide; Sequence Analysis, DNA; Texas; Triglycerides; White People

Prediction of coronary heart disease risk using a genetic risk score: the Atherosclerosis Risk in Communities Study. - Morrison, Alanna C; Bare, Lance A; Chambless, Lloyd E; Ellis, Stephen G; Malloy, Mary; Kane, John P; Pankow, James S; Devlin, James J; Willerson, James T; Eric Boerwinkle (Am J Epidemiol, 2007)
Recent studies have evaluated whether incorporating nontraditional risk factors improves coronary heart disease (CHD) prediction models. This 1986-2001 US study aggregated the contribution of multiple single nucleotide polymorphisms into a genetic risk score (GRS) and assessed whether the GRS plus traditional risk factors predict CHD better than traditional risk factors alone. The Atherosclerosis Risk in Communities (ARIC) cohort was followed for a median of 13 years for CHD events (n = 1,452). Individuals were genotyped for 116 single nucleotide polymorphisms associated with CHD in multiple case-control studies. Single nucleotide polymorphisms nominally predicting incident CHD in the ARIC study were included in the GRS. The GRS was significantly associated with incident CHD in Blacks (hazard rate ratio = 1.20, 95% confidence interval: 1.11, 1.29) and Whites (hazard rate ratio = 1.10, 95% confidence interval: 1.06, 1.14) as well as in each tertile defined by the traditional cardiovascular risk score (p < or = 0.02). When receiver operating characteristic curves based on traditional risk factors were recalculated after the GRS was added, the increase in the area under the receiver operating characteristic curve was statistically significant for Blacks and suggestive of improved CHD prediction for Whites. This study demonstrates the concept of aggregating information from multiple single nucleotide polymorphisms into a risk score and indicates that it can improve prediction of incident CHD in the ARIC study.
Keywords: Atherosclerosis; Black People; Blood Pressure; Cholesterol; Coronary Disease; Female; Follow-Up Studies; Humans; Male; Middle Aged; Polymorphism, Single Nucleotide; Proportional Hazards Models; Prospective Studies; Risk Factors; ROC Curve; United States; White People

Relation of PCSK9 mutations to serum low-density lipoprotein cholesterol in childhood and adulthood (from The Bogalusa Heart Study). - Hallman, D Michael; Srinivasan, Sathanur R; Chen, Wei; Eric Boerwinkle; Berenson, Gerald S (Am J Cardiol, 2007)
Specific mutations in the gene for proprotein convertase, subtilisin-kexin type 9 (PCSK9), that are associated with lower coronary heart disease risk may produce lifelong decreases in low-density lipoprotein (LDL) cholesterol levels, but data on their effects in younger subjects are lacking. We analyzed associations of 1 missense (R46L) and 2 nonsense (Y142X and C679X) PCSK9 mutations with serum LDL cholesterol in 478 African-Americans and 1,086 whites, 4 to 38 years of age, examined 3 to 8 times in the Bogalusa Heart Study. L46 allele frequency in whites was 0.017 +/- 0.003; the combined frequency of X142 or X679 alleles in African-Americans was 0.016 +/- 0.005. In whites, LDL cholesterol was lower in L46 carriers (78.9 +/- 21.8 mg/dl) than in noncarriers (89.7 +/- 24.9 mg/dl, p = 0.027) at their first examination (mean age 9.4 +/- 3.2 years). African-Americans carrying the X142 or X679 allele had lower LDL cholesterol levels than did noncarriers (77.3 +/- 15.1 vs 91.4 +/- 23.9 mg/dl, p = 0.043) at their first examination (mean age 9.0 +/- 3.0 years). Longitudinal LDL cholesterol profiles were significantly lower in whites with the L46 allele and in African-Americans with the X142 or X679 allele. In conclusion, our results show that these PCSK9 variants are associated with significantly lower LDL cholesterol levels starting in childhood.
Keywords: Alleles; Black or African American; Cholesterol, LDL; Codon, Nonsense; Coronary Disease; Female; Humans; Louisiana; Male; Mutation, Missense; Proprotein Convertase 9; Proprotein Convertases; Risk Factors; Serine Endopeptidases; White People

Sequence variation in the soluble epoxide hydrolase gene and subclinical coronary atherosclerosis: interaction with cigarette smoking. - Wei, Qi; Doris, Peter A; Pollizotto, Martin V; Eric Boerwinkle; Jacobs, David R; Siscovick, David S; Fornage, Myriam (Atherosclerosis, 2007)
Soluble epoxide hydrolase (EPHX2) catalyses the degradation of the vasoactive and anti-inflammatory epoxyeicosatrienoic acids and may play a role in the pathophysiology of atherosclerosis. 1337 African-Americans and 1645 Whites from the CARDIA study were genotyped for 22 and 15 EPHX2 single nucleotide polymorphisms (SNPs), respectively, to examine the associations of common EPHX2 haplotypes and genotypes with presence of coronary artery calcified plaque (CAC). The potential influence of cigarette smoking, which increases EPHX2 gene expression, on these associations was also assessed. In African-Americans, a common haplotype uniquely tagged by the R287Q polymorphism was associated with significantly greater risk for CAC (OR=1.7; 95% CI=1.04-3.0). In Whites, a common haplotype uniquely tagged by a polymorphism in Intron 11 of the gene was associated with significantly greater risk for CAC (OR=1.3; 95% CI=1.02-1.6). These haplotype-tagging polymorphisms also showed significant associations with CAC in individual SNP analyses, and these relationships were significantly modified by smoking. This detailed investigation of the association of EPHX2 genetic variation with CAC supports EPHX2's emerging role as a risk factor for atherosclerosis, whose effects are influenced by smoking.
Keywords: Adolescent; Adult; Black or African American; Coronary Artery Disease; Epoxide Hydrolases; Female; Gene Frequency; Haplotypes; Humans; Linkage Disequilibrium; Male; Polymorphism, Single Nucleotide; Prospective Studies; Risk Factors; Smoking; Solubility; White People

Specific P-selectin and P-selectin glycoprotein ligand-1 genotypes/haplotypes are associated with risk of incident CHD and ischemic stroke: the Atherosclerosis Risk in Communities (ARIC) study. - Volcik, Kelly A; Ballantyne, Christie M; Coresh, Josef; Folsom, Aaron R; Eric Boerwinkle (Atherosclerosis, 2007)
OBJECTIVE: P-selectin (PSEL) and its ligand, P-selectin glycoprotein ligand-1 (PSGL-1), play key roles in both the inflammatory response and the atherosclerotic process, but there are conflicting results regarding the affect of PSEL and PSGL-1 gene variation on risk for cardiovascular and cerebrovascular disease. We tested the association of four PSEL and two PSGL-1 polymorphisms with incident coronary heart disease (CHD) and ischemic stroke among 13,875 participants in the prospective Atherosclerosis Risk in Communities (ARIC) study. We also tested common haplotypes in the PSEL and PSGL-1 genes to assess associations with incident CHD and ischemic stroke. METHODS AND RESULTS: Incident ischemic stroke and CHD were identified through annual telephone calls and hospital and death certificate surveillance. Five hundred and twenty-five validated ischemic stroke and 1654 CHD events were identified. Allele frequencies for all PSEL and PSGL-1 polymorphisms were markedly different between whites and African Americans; therefore, all analyses were performed race-specific. Independent analyses showed the PSEL 290NN genotype to be a significant predictor of CHD in whites (HRR 1.30, 95%CI 1.00-1.70, P=0.05). PSGL-1 genotypes carrying the 62I allele were significantly protective for incident CHD (HRR 0.53, 95%CI 0.31-0.92, P=0.02) and ischemic stroke (HRR 0.73, 95%CI 0.55-0.97, P=0.03) in African Americans. Haplotype analyses showed the PSEL NNVP haplotype to be a significant predictor of incident CHD in whites (HRR 2.09, 95%CI 1.23-3.55, P=0.006). No significant haplotype findings were observed in African Americans. CONCLUSIONS: PSEL S290N, in single polymorphism analysis and in the haplotypic background with T715P, was associated with increased risk of incident CHD in whites. The PSGL-1 M62I polymorphism was associated with decreased risk of both incident CHD and stroke in African Americans. These findings illustrate the complex relationship between genetic variation and disease in different racial groups.
Keywords: Aged; Atherosclerosis; Cell Adhesion; Coronary Artery Disease; Genotype; Haplotypes; Humans; Incidence; Ischemia; Membrane Glycoproteins; Middle Aged; P-Selectin; Polymorphism, Genetic; Polymorphism, Single Nucleotide; Risk; Stroke

Apolipoprotein E polymorphisms predict low density lipoprotein cholesterol levels and carotid artery wall thickness but not incident coronary heart disease in 12,491 ARIC study participants. - Volcik, Kelly A; Barkley, Ruth Ann; Hutchinson, Richard G; Mosley, Thomas H; Heiss, Gerardo; Sharrett, A Richey; Ballantyne, Christie M; Eric Boerwinkle (Am J Epidemiol, 2006)
Elevated levels of low density lipoprotein (LDL) cholesterol is a well-established risk factor for cardiovascular disease, and recent advancements have provided evidence that carotid artery intima-media thickness (IMT) is associated with increased occurrence of cardiovascular events. Apolipoprotein E (ApoE) has been widely studied in regard to its role in lipid transport and metabolism, but the role that ApoE genetic variation plays in relation to carotid artery IMT and risk of incident coronary heart disease remains a subject of debate. In 1987-2001, the authors examined the effect of each ApoE allele (epsilon2, epsilon3, epsilon4) on LDL cholesterol and carotid IMT, as well as the association with coronary heart disease risk, in 12,491 participants of the US Atherosclerosis Risk in Communities Study. ApoE epsilon2, epsilon3, and epsilon4 allele frequencies were determined, respectively, in Whites (0.08, 0.77, 0.15) and African Americans (0.11, 0.67, 0.22). These alleles did not predict incident coronary heart disease in either racial group. The ApoE epsilon2 allele was associated with lower LDL cholesterol and the epsilon4 allele with higher LDL cholesterol in both Whites and African Americans. The ApoE epsilon2 and epsilon4 alleles were associated with carotid IMT measures in both racial groups, but, after adjusting for lipid parameters, only the epsilon4 allele was associated with carotid IMT measures in African Americans.
Keywords: Apolipoproteins E; Black People; Carotid Arteries; Cholesterol, LDL; Coronary Disease; Female; Genetic Predisposition to Disease; Humans; Incidence; Male; Middle Aged; Polymorphism, Genetic; Prospective Studies; Tunica Intima; White People

Consistent effects of genes involved in reverse cholesterol transport on plasma lipid and apolipoprotein levels in CARDIA participants. - Klos, Kathy L E; Sing, Charles F; Eric Boerwinkle; Hamon, Sara C; Rea, Thomas J; Clark, Andrew; Fornage, Myriam; Hixson, James E (Arterioscler Thromb Vasc Biol, 2006)
OBJECTIVE: To identify common variations in genes in the reverse cholesterol transport pathway with nongender-specific influence on plasma lipid and apolipoprotein levels. METHODS AND RESULTS: An average of 5 single nucleotide polymorphisms (SNPs) were genotyped within each of 45 genomic regions (54 genes) in blacks (1131 females and 812 males) and whites (1102 females and 954 males) from the Coronary Artery Risk Development in Young Adults (CARDIA) study. SNPs and gene-based 3-SNP haplotypes were evaluated for their ability to predict variation in plasma apolipoproteins (apo) A-I and apoB, total cholesterol (TC), high-density lipoprotein cholesterol, low-density lipoprotein cholesterol, and triglycerides (TG). We identified 14 SNPs in 6 candidate gene regions that explained statistically significant variation in the same trait in both genders of at least one race and with evidence of consistent genotype mean trend across gender within race. Haplotype analyses identified 9 candidate gene regions that explained statistically significant variation in one or both races. CONCLUSIONS: Four gene regions, ABCA1, APOA1/C3/A4/A5, APOE/C1/C4/C2, and CETP, explained plasma lipoprotein variation most consistently across strata. Other gene regions that influence plasma lipid and apolipoprotein levels within race include CYP7A1, LPL, PPARA, SOAT1, and SREBF2.
Keywords: Adult; Apolipoproteins; Apolipoproteins A; Apolipoproteins C; Apolipoproteins E; ATP Binding Cassette Transporter 1; ATP-Binding Cassette Transporters; Biological Transport, Active; Black People; Carrier Proteins; Cholesterol; Cholesterol Ester Transfer Proteins; Coronary Artery Disease; Female; Genetic Predisposition to Disease; Genotype; Glycoproteins; Haplotypes; Humans; Lipids; Male; Polymorphism, Single Nucleotide; White People

Longitudinal analysis of haplotypes and polymorphisms of the APOA5 and APOC3 genes associated with variation in serum triglyceride levels: the Bogalusa Heart Study. - Hallman, D Michael; Srinivasan, Sathanur R; Chen, Wei; Eric Boerwinkle; Berenson, Gerald S (Metabolism, 2006)
Polymorphisms in the APOC3 and APOA5 genes, from the APOA1/APOC3/APOA4/APOA5 gene cluster on chromosome 11q23, have been associated with interindividual variation in plasma triglycerides. APOA5 polymorphisms implicated include 2 in the promoter region (-1131 T/C and -3 A/G) and 1 in exon 2 (+56 C/G). APOC3 polymorphisms implicated include 1 (SstI) in the 3' untranslated region and 1 (-2854 G/T) in the APOC3-APOA4 intergenic region. We analyzed the associations of haplotypes and multilocus genotypes of these polymorphisms on longitudinal serum triglyceride profiles in 360 African American and 823 white subjects from the Bogalusa Heart Study. Subjects were examined from 2 to 8 times (mean +/- SD, 5.4 +/- 1.3) between 1973 and 1996, at ages ranging from 4 to 38 years, with 1978 observations in African Americans and 4465 in whites. Serum triglycerides were significantly higher among whites across all ages. Allele frequencies differed significantly between African Americans and whites at all but the APOA5 +56 C/G locus. Linkage disequilibrium among the loci was higher in whites and haplotype diversity lower: 6 haplotypes had estimated frequencies of more than 1% in African Americans, 5 in whites. Individually, all polymorphisms except APOC3 -2854 G/T showed significant associations with triglyceride levels in the full sample. However, genotype models including all 5 loci showed significant triglyceride associations for only 3 (APOC3 SstI, APOA5 -1131 T/C, and APOA5 +56 C/G); significant interactions among them indicated their effects were not independent. Neither APOC3 -2854 G/T nor APOA5 -3 A/G had significant effects when the other 3 loci were in the models. The EM algorithm was used to estimate haplotype frequencies and assign haplotype probabilities to individuals, which is conditional on their genotypes; individuals' haplotype probability vectors were then used as predictors in multilevel mixed models of longitudinal triglyceride profiles. Of haplotypes comprising, in order, APOC3 SstI and -2854 G/T and APOA5 -1131 T/C, -3 A/G, and +56 C/G, 3 were significantly associated with higher triglycerides, even after adjusting for multiple tests: GGTAG (P = .002), GTTAG (P < .0001), and CGCGC (P = .0002). Each GGTAG haplotype carried would be expected to raise triglyceride levels (relative to those of GTTAC homozygotes) by approximately 19 mg/dL, each GTTAG haplotype by approximately 15 mg/dL, and each CGCGC haplotype by approximately 7 mg/dL. Haplotypes comprising the 3 loci implicated by genotype analyses (SstI, -1131 T/C, and +56 C/G) were also tested: haplotypes C_C_C and G_T_G significantly raised triglycerides, even after adjustment for multiple comparisons (P < .002 for both), with each copy of C_C_C expected to raise triglycerides by approximately 7 mg/dL and each copy of G_T_G by approximately 15 mg/dL. Overall, our findings support those of others in associating specific polymorphisms and haplotypes in the APOA1/C3/A4/A5 gene cluster with higher serum triglyceride levels. However, the degree to which polymorphisms in the APOC3 and APOA5 genes may be independently associated with triglyceride levels remains to be determined.
Keywords: Adolescent; Adult; Apolipoprotein A-V; Apolipoprotein C-III; Apolipoproteins A; Body Mass Index; Child; Child, Preschool; Female; Haplotypes; Humans; Longitudinal Studies; Male; Polymorphism, Genetic; Triglycerides

P-selectin Thr715Pro polymorphism predicts P-selectin levels but not risk of incident coronary heart disease or ischemic stroke in a cohort of 14595 participants: the Atherosclerosis Risk in Communities Study. - Volcik, Kelly A; Ballantyne, Christie M; Coresh, Josef; Folsom, Aaron R; Wu, Kenneth K; Eric Boerwinkle (Atherosclerosis, 2006)
OBJECTIVE: Inflammation, characterized by the recruitment/adhesion of circulating leukocytes by cellular adhesion molecules, plays an important role in the pathogenesis of atherosclerosis. Genetic analyses of P-selectin, a key adhesion molecule in the progression of atherosclerosis, have provided conflicting results regarding the role of variation within the P-selectin gene and risk for heart disease. No studies have examined the association of this polymorphism with stroke. Therefore, we examined the association of the P-selectin Thr715Pro polymorphism with incident coronary heart disease (CHD) and ischemic stroke among 14595 participants in the prospective cohort of the Atherosclerosis Risk in Communities (ARIC) Study. METHODS AND RESULTS: Incidences of ischemic stroke and CHD were determined through annual telephone calls and hospital and death certificate surveillance. Four hundred fifty-six validated ischemic stroke and 1533 CHD events were identified. P-selectin Pro715 allele frequency was determined in whites and African-Americans, respectively, for CHD cases (0.11, 0.02), CHD non-cases (0.11, 0.02), ischemic stroke cases (0.11, 0.02) and stroke non-cases (0.11, 0.02). The P-selectin Pro715 allele was not associated with risk of CHD or stroke in whites or African-Americans. P-selectin levels, however, were associated with the P-selectin Thr715Pro variant in whites, but not in African-Americans. CONCLUSIONS: Genotypes carrying the P-selectin Pro715 variant allele are associated with decreased P-selectin levels compared to the homozygous wild-type genotype in whites. The P-selectin Thr715Pro polymorphism is not associated with incident CHD or ischemic stroke in either whites or African-Americans.
Keywords: Alleles; Biomarkers; Coronary Artery Disease; Disease Progression; Female; Follow-Up Studies; Gene Frequency; Genotype; Humans; Incidence; Male; Middle Aged; P-Selectin; Polymorphism, Genetic; Prospective Studies; Risk Factors; Stroke; United States

Sequence variations in PCSK9, low LDL, and protection against coronary heart disease. - Cohen, Jonathan C; Eric Boerwinkle; Mosley, Thomas H; Hobbs, Helen H (N Engl J Med, 2006)
BACKGROUND: A low plasma level of low-density lipoprotein (LDL) cholesterol is associated with reduced risk of coronary heart disease (CHD), but the effect of lifelong reductions in plasma LDL cholesterol is not known. We examined the effect of DNA-sequence variations that reduce plasma levels of LDL cholesterol on the incidence of coronary events in a large population. METHODS: We compared the incidence of CHD (myocardial infarction, fatal CHD, or coronary revascularization) over a 15-year interval in the Atherosclerosis Risk in Communities study according to the presence or absence of sequence variants in the proprotein convertase subtilisin/kexin type 9 serine protease gene (PCSK9) that are associated with reduced plasma levels of LDL cholesterol. RESULTS: Of the 3363 black subjects examined, 2.6 percent had nonsense mutations in PCSK9; these mutations were associated with a 28 percent reduction in mean LDL cholesterol and an 88 percent reduction in the risk of CHD (P=0.008 for the reduction; hazard ratio, 0.11; 95 percent confidence interval, 0.02 to 0.81; P=0.03). Of the 9524 white subjects examined, 3.2 percent had a sequence variation in PCSK9 that was associated with a 15 percent reduction in LDL cholesterol and a 47 percent reduction in the risk of CHD (hazard ratio, 0.50; 95 percent confidence interval, 0.32 to 0.79; P=0.003). CONCLUSIONS: These data indicate that moderate lifelong reduction in the plasma level of LDL cholesterol is associated with a substantial reduction in the incidence of coronary events, even in populations with a high prevalence of non-lipid-related cardiovascular risk factors.
Keywords: Black People; Carotid Arteries; Cholesterol, LDL; Codon, Nonsense; Cohort Studies; Coronary Disease; Female; Gene Frequency; Genetic Variation; Genotype; Humans; Hypolipoproteinemias; Incidence; Male; Middle Aged; Proportional Hazards Models; Proprotein Convertase 9; Proprotein Convertases; Risk; Serine Endopeptidases; United States; White People

APOA5 polymorphisms influence plasma triglycerides in young, healthy African Americans and whites of the CARDIA Study. - Klos, Kathy L E; Hamon, Sara; Clark, Andrew G; Eric Boerwinkle; Liu, Kiang; Sing, Charles F (J Lipid Res, 2005)
Genetic variation in the apolipoprotein A-V gene (APOA5) has been associated with variation in plasma triglyceride (TG) levels in African American and white females and males older than 40 years and/or at increased risk of coronary artery disease. We have examined whether plasma TG levels are associated with 16 APOA5 polymorphisms in young (18-30 years) African American (1,075 females and 783 males) and white (1,041 females and 932 males) individuals of the Coronary Artery Risk Development in Young Adults (CARDIA) Study selected without regard to health. Plasma TG was significantly (P < 0.01) associated with markers 27376 and 28837 (-3A/G) in both white females and males, with 27709 (-1131T/C) and 29085 in white males, with 29009 (S19W) in African American females and white males, and with 30966 in African American females. No statistically significant associations were observed in African American males. These six single-nucleotide polymorphisms individually accounted for 0-0.78% of lnTG variation among white females, 0-2.46% among white males, and 0-0.69% among African American females. The results of our study suggest a small but replicable context-dependent influence of the APOA5 gene region on plasma TG levels in young, healthy individuals.
Keywords: Adolescent; Adult; Alleles; Apolipoprotein A-V; Apolipoproteins; Apolipoproteins A; Black or African American; Cohort Studies; Coronary Artery Disease; Cross-Sectional Studies; Female; Genetic Variation; Genotype; Humans; Male; Polymorphism, Genetic; Risk Factors; Sex Factors; Triglycerides; United States; White People

Combined genealogical, mapping, and expression approaches to identify spontaneously hypertensive rat hypertension candidate genes. - Hinojos, Cruz A; Eric Boerwinkle; Fornage, Myriam; Doris, Peter A (Hypertension, 2005)
Allelic expression in genes has become recognized as a heritable trait by which phenotypes are generated. We have examined gene expression in the rat kidney using genome-wide microarray technology (Affymetrix). Gene expression was determined across 4 rat strains, 3 hypertensive spontaneously hypertensive rat (SHR) substrains (SHR-A3, SHR-B2, and SHR-C), and a normotensive strain (Wistar-Kyoto [WKY]). Expression measurements were made in multiple animals from all strains at 4 time points (4 weeks, 8 weeks, 12 weeks, and 18 weeks of age), covering the prehypertensive period in SHR (4 weeks), and the period of rapidly rising blood pressure (8 and 12 weeks) and of sustained hypertension (18 weeks). Regression analysis revealed a close relationship across all strains during the first 3 time points, after which SHR-A3 became a substantial outlier. SHR-B2 and SHR-C demonstrated a very close relationship in gene expression at all times but also showed increased differences compared with the other strains at 18 weeks of age. We identified genes that were consistently different in expression, comparing all SHR substrains at each time point with WKY. The resulting list of genes was compared with blood pressure quantitative trait loci reported for SHR to refine a number of genes consistently differentially expressed between SHR substrains and WKY, persistently differentially expressed across multiple time points, and located in SHR blood pressure-determinative regions of the genome. Genealogical relationships and SHR substrain intercrosses suggest that genes responsible for heritable hypertension in SHR are shared across SHR substrains. The present approach identifies a number of genes that may influence blood pressure in SHR by virtue of allelic effects on gene expression.
Keywords: Animals; Blood Pressure; Chromosome Mapping; Expressed Sequence Tags; Gene Expression; Genome; Hypertension; Kidney; Oligonucleotide Array Sequence Analysis; Pedigree; Quantitative Trait Loci; Rats; Rats, Inbred SHR; Rats, Inbred WKY; Regression Analysis; Species Specificity

Demographic, environmental, and genetic predictors of metabolic side effects of hydrochlorothiazide treatment in hypertensive subjects. - Maitland-van der Zee, Anke-Hilse; Turner, Stephen T; Schwartz, Gary L; Chapman, Arlene B; Klungel, Olaf H; Eric Boerwinkle (Am J Hypertens, 2005)
BACKGROUND: Thiazide diuretics are recommended for first-line treatment of hypertension. Although considered safe and effective, their use is associated with dyslipidemia, hyperglycemia, and an increased risk of developing type 2 diabetes. The aim of this study was to characterize interindividual variation in glucose and lipid responses to hydrochlorothiazide and to identify demographic, environmental, and genetic predictors associated with this variation. METHODS: A community-based sample of 585 adults with essential hypertension (291 African Americans [150 women and 141 men] and 294 non-Hispanic whites [126 women and 168 men]) underwent monotherapy with hydrochlorothiazide for 4 weeks. Linear regression was used to construct prediction models for the changes in plasma total cholesterol, triglyceride, and glucose concentrations. RESULTS: The mean changes (+/- standard deviation) in response to hydrochlorothiazide were 6.13 +/- 22.8 mg/dL for total cholesterol, 17.21 +/- 70 mg/dL for triglycerides, and 3.5 +/- 9.5 mg/dL for plasma glucose. Ethnicity and baseline levels of the analytes were the only predictors that were significant for more than one response. Therefore, the mechanism for these metabolic effects are not entirely shared. CONCLUSIONS: Taken together, demographic, environmental, and genetic factors accounted for only 13% of the total variation in total cholesterol response, 17% of the variation in triglyceride response, and 11% of the variation in glucose response to hydrochlorothiazide, and less than half of this predicted variation in response was explained by measured genotypes.
Keywords: Adult; Black or African American; Blood Glucose; Blood Pressure; Cholesterol; Diuretics; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Hydrochlorothiazide; Hypertension; Logistic Models; Male; Middle Aged; Multivariate Analysis; Polymorphism, Genetic; Potassium; Predictive Value of Tests; Treatment Outcome; Triglycerides; White People

An entropy-based statistic for genomewide association studies. - Zhao, Jinying; Eric Boerwinkle; Xiong, Momiao (Am J Hum Genet, 2005)
Efficient genotyping methods and the availability of a large collection of single-nucleotide polymorphisms provide valuable tools for genetic studies of human disease. The standard chi2 statistic for case-control studies, which uses a linear function of allele frequencies, has limited power when the number of marker loci is large. We introduce a novel test statistic for genetic association studies that uses Shannon entropy and a nonlinear function of allele frequencies to amplify the differences in allele and haplotype frequencies to maintain statistical power with large numbers of marker loci. We investigate the relationship between the entropy-based test statistic and the standard chi2 statistic and show that, in most cases, the power of the entropy-based statistic is greater than that of the standard chi2 statistic. The distribution of the entropy-based statistic and the type I error rates are validated using simulation studies. Finally, we apply the new entropy-based test statistic to two real data sets, one for the COMT gene and schizophrenia and one for the MMP-2 gene and esophageal carcinoma, to evaluate the performance of the new method for genetic association studies. The results show that the entropy-based statistic obtained smaller P values than did the standard chi2 statistic.
Keywords: Entropy; Gene Frequency; Genetic Markers; Haplotypes; Humans; Linkage Disequilibrium; Statistics as Topic

Genome-wide linkage study of erythrocyte sodium-lithium countertransport. - Morrison, Alanna C; Eric Boerwinkle; Turner, Stephen T; Ferrell, Robert E (Am J Hypertens, 2005)
BACKGROUND: Increased erythrocyte sodium-lithium countertransport (SLC) has been observed in patients with essential hypertension. An analytic strategy for identification of genetic variation contributing to hypertension is the evaluation of appropriate intermediate phenotypes for hypertension, such as SLC. Thus, in this study, genome-wide linkage scans for SLC were performed in two independent samples of pedigrees from the Rochester Family Heart Study (RFHS). METHODS: Genome-wide linkage scans for SLC were performed in independent samples of 232 and 252 non-Hispanic white families from the RFHS. Multipoint variance-component linkage analysis was performed using MERLIN. RESULTS: Chromosomes 8, 9, 10, 19, and 20 contained evidence for linkage (log of the odds [LOD] > or =2) in at least one sample of RFHS pedigrees. Consistent evidence of linkage for SLC between the two samples was observed on chromosome 10 (LOD = 2.02 at 64 cM in the first sample and LOD = 2.27 at 55 cM in the second sample). CONCLUSIONS: Consistent evidence of linkage (LOD > or =2) for SLC was observed in two independent samples of non-Hispanic white families on chromosome 10. Concordance of linkage evidence between the two samples provides confidence that a region on chromosome 10 contains genetic variation influencing SLC, which may potentially influence susceptibility to hypertension.
Keywords: Antiporters; Erythrocytes; Genetic Linkage; Genome; Humans; Hypertension; Lod Score

Mining genetic epidemiology data with Bayesian networks application to APOE gene variation and plasma lipid levels. - Rodin, Andrei; Mosley, Thomas H; Clark, Andrew G; Sing, Charles F; Eric Boerwinkle (J Comput Biol, 2005)
There is a critical need for data-mining methods that can identify SNPs that predict among individual variation in a phenotype of interest and reverse-engineer the biological network of relationships between SNPs, phenotypes, and other factors. This problem is both challenging and important in light of the large number of SNPs in many genes of interest and across the human genome. A potentially fruitful form of exploratory data analysis is the Bayesian or Belief network. A Bayesian or Belief network provides an analytic approach for identifying robust predictors of among-individual variation in a disease endpoints or risk factor levels. We have applied Belief networks to SNP variation in the human APOE gene and plasma apolipoprotein E levels from two samples: 702 African-Americans from Jackson, MS, and 854 non-Hispanic whites from Rochester, MN. Twenty variable sites in the APOE gene were genotyped in both samples. In Jackson, MS, SNPs 4036 and 4075 were identified to influence plasma apoE levels. In Rochester, MN, SNPs 3937 and 4075 were identified to influence plasma apoE levels. All three SNPs had been previously implicated in affecting measures of lipid and lipoprotein metabolism. Like all data-mining methods, Belief networks are meant to complement traditional hypothesis-driven methods of data analysis. These results document the utility of a Belief network approach for mining large scale genotype-phenotype association data.
Keywords: Apolipoproteins E; Bayes Theorem; Databases, Factual; Genetics, Population; Humans; Linkage Disequilibrium; Lipids; Models, Genetic; Polymorphism, Single Nucleotide

Mining genetic epidemiology data with Bayesian networks I: Bayesian networks and example application (plasma apoE levels). - Rodin, Andrei S; Eric Boerwinkle (Bioinformatics, 2005)
MOTIVATION: The wealth of single nucleotide polymorphism (SNP) data within candidate genes and anticipated across the genome poses enormous analytical problems for studies of genotype-to-phenotype relationships, and modern data mining methods may be particularly well suited to meet the swelling challenges. In this paper, we introduce the method of Belief (Bayesian) networks to the domain of genotype-to-phenotype analyses and provide an example application. RESULTS: A Belief network is a graphical model of a probabilistic nature that represents a joint multivariate probability distribution and reflects conditional independences between variables. Given the data, optimal network topology can be estimated with the assistance of heuristic search algorithms and scoring criteria. Statistical significance of edge strengths can be evaluated using Bayesian methods and bootstrapping. As an example application, the method of Belief networks was applied to 20 SNPs in the apolipoprotein (apo) E gene and plasma apoE levels in a sample of 702 individuals from Jackson, MS. Plasma apoE level was the primary target variable. These analyses indicate that the edge between SNP 4075, coding for the well-known epsilon2 allele, and plasma apoE level was strong. Belief networks can effectively describe complex uncertain processes and can both learn from data and incorporate prior knowledge. AVAILABILITY: Various alternative and supplemental networks (not given in the text) as well as source code extensions, are available from the authors. SUPPLEMENTARY INFORMATION: http://bioinformatics.oxfordjournals.org.
Keywords: Apolipoproteins E; Bayes Theorem; Chromosome Mapping; Computer Simulation; Database Management Systems; Databases, Genetic; DNA Mutational Analysis; Epidemiologic Methods; Genotype; Humans; Information Storage and Retrieval; Models, Genetic; Models, Statistical; Polymorphism, Single Nucleotide

A multilocus approach to the antihypertensive pharmacogenetics of hydrochlorothiazide. - Maitland-van der Zee, Anke-Hilse; Turner, Stephen T; Schwartz, Gary L; Chapman, Arlene B; Klungel, Olaf H; Eric Boerwinkle (Pharmacogenet Genomics, 2005)
OBJECTIVES: To assess the influence of variations in multiple candidate genes on inter-individual variation in diastolic blood pressure (DBP) response to hydrochlorothiazide. METHODS: A community-based sample of 585 adults with essential hypertension underwent monotherapy with hydrochlorothiazide for 4 weeks. In a nested case-control design, 195 individuals in the highest tertile of DBP response (responders) and 195 individuals in the lowest tertile of DBP response (non-responders) were genotyped for 45 polymorphisms in 19 candidate genes. For those polymorphisms where the set association approach found to be significantly associated with DBP response, logistic regression was performed to estimate the odds ratio (OR) for response associated variation in the identified genotype/haplotype. RESULTS: Two polymorphisms in the sodium channel gamma-subunit promotor gene, and a polymorphism in the endothelial nitric oxide synthase gene, were significantly associated with blood pressure response to hydrochlorothiazide. In the final experiment for the set association model P=0.038. In the logistic regression analyses, compared to subjects with the CT/CT haplotype of the SCNN1G gene, those with the GA/GA haplotype had OR 5.21 of being a DBP responder [95% CI 1.65-16.47]. Compared to subjects with the GT genotype of the ENOSA_rs1799983 polymorphism, those with the GG genotype had an OR 2.19 of being a DBP responder [95% CI 1.27-3.77]. CONCLUSIONS: Two polymorphisms in the sodium channel gamma-subunit promotor gene, and a polymorphism in the endothelial nitric oxide synthase gene, were associated with significant differences in odds of DBP response to hydrochlorothiazide. Follow-up studies are needed to define the functional genetic variations and their mechanisms of pharmacogenetic effects.
Keywords: Antihypertensive Agents; Blood Pressure; Cytochrome P-450 CYP11B2; Female; Humans; Hydrochlorothiazide; Male; Middle Aged; Nitric Oxide Synthase; Polymorphism, Genetic; Sodium Channels

Pharmacogenetics of response to statins: where do we stand? - Maitland-van der Zee, Anke-Hilse; Eric Boerwinkle (Curr Atheroscler Rep, 2005)
Cardiovascular disease is one of the leading causes of death, especially in developed countries. Blood cholesterol lowering by way of statin therapy is a common risk-lowering therapy. The risk reduction for coronary artery disease for patients using statins is 27%. These reductions, however, are average effects for all patients included in the trials. There is notable interindividual variation in response to statins, and the origins of this variation are poorly understood. Pharmacogenetics seeks to determine the role of genetic factors in variation of drug response. In patients with primary hypercholesterolemia, 23 studies have examined the effects of genetic polymorphisms at 20 different loci on the lipid response to statin treatment, and 18 studies examined genetic polymorphisms involved in the benefits of statin therapy in the prevention of cardiovascular disease. Even though many studies have been performed, few results have been replicated. It is our contention that larger sample sizes and consideration of multiple genes are needed in the field of pharmacogenetics of statin response.
Keywords: Carrier Proteins; Cholesterol Ester Transfer Proteins; Cholesterol, LDL; Coronary Artery Disease; Glycoproteins; Humans; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Hypercholesterolemia; Pharmacogenetics; Polymorphism, Genetic

The soluble epoxide hydrolase gene harbors sequence variation associated with susceptibility to and protection from incident ischemic stroke. - Fornage, Myriam; Lee, Craig R; Doris, Peter A; Bray, Molly S; Heiss, Gerardo; Zeldin, Darryl C; Eric Boerwinkle (Hum Mol Genet, 2005)
Stroke is the leading cause of severe disability and the third leading cause of death, accounting for one of every 15 deaths in the USA. We investigated the association of polymorphisms in the soluble epoxide hydrolase gene (EPHX2) with incident ischemic stroke in African-Americans and Whites. Twelve single nucleotide polymorphisms (SNPs) spanning EPHX2 were genotyped in a case-cohort sample of 1336 participants from the Atherosclerosis Risk in Communities (ARIC) study. In each racial group, Cox proportional hazard models were constructed to assess the relationship between incident ischemic stroke and EPHX2 polymorphisms. A score test method was used to investigate the association of common haplotypes of the gene with risk of ischemic stroke. In African-Americans, two common EPHX2 haplotypes with significant and opposing relationships to ischemic stroke risk were identified. In Whites, two common haplotypes showed suggestive indication of an association with ischemic stroke risk but, as in African-Americans, these relationships were in opposite direction. These findings suggest that multiple variants exist within or near the EPHX2 gene, with greatly contrasting relationships to ischemic stroke incidence; some associated with a higher incidence and others with a lower incidence.
Keywords: Base Sequence; Black or African American; Brain Ischemia; Epoxide Hydrolases; Female; Genetic Predisposition to Disease; Haplotypes; Humans; Male; Middle Aged; Polymorphism, Genetic; Stroke; White People

The beta(2)-adrenergic receptor Arg16-gly polymorphism and interactions involving beta(2)- and beta(3)-adrenergic receptor polymorphisms are associated with variations in longitudinal serum lipid profiles: the Bogalusa Heart Study. - Hallman, D Michael; Srinivasan, Sathanur R; Chen, Wei; Eric Boerwinkle; Berenson, Gerald S (Metabolism, 2004)
We examined the effects of combined genotypes of the beta(2)-adrenergic receptor (AR) Arg(16)-Gly and beta(3)-AR Trp(64)-Arg polymorphisms on longitudinal serum total (T-C) and low-density lipoprotein cholesterol (LDL-C) profiles in 1,198 subjects examined multiple times (6,488 observations) from 1973 to 1996 in the Bogalusa Heart Study, at ages from 4.5 to 38 years. Within 5-year age groups, T-C was significantly (P <.05) higher in beta(2)-AR Arg(16)/Arg(16) homozygotes than in Gly(16) carriers among those 4 to 8 (171.4 +/- 30.0 v 161.5 +/- 27.7 mg/dL), 9 to 13 (167.7 +/- 28.6 v 162.4 +/- 27.4 mg/dL), and 14 to 18 (158.8 +/- 29.6 v 154.7 +/- 27.5 mg/dL) years of age, but not in those 19 to 23, 24 to 28, 29 to 33, or 34 to 38 years of age. The beta(3)-AR polymorphism was not associated with variation in either T-C or LDL-C. In multilevel polynomial growth curve models, the combination of the beta(2)-AR Arg(16)/Arg(16) genotype with either the beta(3)-AR Arg(64)/Arg(64) or Trp(64)/Arg(64) genotypes, denoted AA/AX, was associated with variation in longitudinal T-C (P <.01) and LDL-C (P <.01) profiles. The association between combined beta(2)/beta(3)-AR genotype and lipid profiles differed among race/sex groups, being most marked in black females, in whom the AA/AX combination was associated with higher T-C and LDL-C profiles across all ages. In White males, the AA/AX combination was most strongly associated with higher lipids in adults. In black males and white females, lipid profiles differed little between genotype groups. Our findings suggest that the beta(2)-AR Arg(16)-Gly genotype influences T-C and LDL-C levels in an age-specific manner, that it may interact with beta(3)-AR Trp(64)-Arg genotypes to influence longitudinal T-C and LDL-C profiles, and that the effect of combined beta(2)/beta(3)-AR genotypes on T-C and LDL-C profiles may differ among race/sex groups.
Keywords: Age Factors; Algorithms; Amino Acid Substitution; Black People; Body Mass Index; Cardiovascular Diseases; Child; Cholesterol, LDL; DNA Primers; Female; Genotype; Humans; Lipids; Longitudinal Studies; Male; Polymorphism, Genetic; Receptors, Adrenergic, beta-2; Receptors, Adrenergic, beta-3; Reverse Transcriptase Polymerase Chain Reaction; Risk Factors; Sex Factors; Triglycerides; White People

Genetic discoveries and nursing implications for complex disease prevention and management. - Frazier, Lorraine; Meininger, Janet; Halsey Lea, Dale; Eric Boerwinkle (J Prof Nurs, 2004)
The purpose of this article is to examine the management of patients with complex diseases, in light of recent genetic discoveries, and to explore how these genetic discoveries will impact nursing practice and nursing research. The nursing science processes discussed are not comprehensive of all nursing practice but, instead, are concentrated in areas where genetics will have the greatest influence. Advances in genetic science will revolutionize our approach to patients and to health care in the prevention, diagnosis, and treatment of disease, raising many issues for nursing research and practice. As the scope of genetics expands to encompass multifactorial disease processes, a continuing reexamination of the knowledge base is required for nursing practice, with incorporation of genetic knowledge into the repertoire of every nurse, and with advanced knowledge for nurses who select specialty roles in the genetics area. This article explores the impact of this revolution on nursing science and practice as well as the opportunities for nursing science and practice to participate fully in this revolution. Because of the high proportion of the population at risk for complex diseases and because nurses are occupied every day in the prevention, assessment, treatment, and therapeutic intervention of patients with such diseases in practice and research, there is great opportunity for nurses to improve health care through the application (nursing practice) and discovery (nursing research) of genetic knowledge.
Keywords: Ecology; Genetic Predisposition to Disease; Genetics, Medical; Humans; Nursing; Nursing Research; Pharmacogenetics; Proteomics

Genome scan for hypertension in nonobese African Americans: the National Heart, Lung, and Blood Institute Family Blood Pressure Program. - Morrison, Alanna C; Cooper, Richard; Hunt, Steven; Lewis, Cora E; Luke, Amy; Mosley, Thomas H; Eric Boerwinkle (Am J Hypertens, 2004)
BACKGROUND: Obesity is an important risk factor for hypertension, but epidemiologic studies provide evidence for the development of hypertension independent of obesity. In addition, the search for hypertension susceptibility genes should prove more informative when applied to a homogeneous subset of patients, such as those that are not obese. For this reason, we sought to identify genomic regions influencing susceptibility to hypertension in a nonobese sample of hypertensive African American families. METHODS: A genome-wide linkage scan was performed in a sample of 275 African American hypertensive families containing two or more nonobese (body mass index, < or = 30 kg/m2) individuals recruited by Networks of the Family Blood Pressure Program (FBPP). RESULTS: The best evidence for linkage of hypertension among the FBPP African American families was found on chromosome 2 (log of the odds [LOD]= 3.59 at 230 cM). All other chromosomes contained LOD scores less than 2. The African American sibships from the GENOA Network appear to largely contribute to the evidence for linkage on chromosome 2 (LOD = 4.07 at 233 cM). CONCLUSIONS: Significant evidence for linkage to hypertension in nonobese African American families was identified on chromosome 2q. These results suggest the presence of genes influencing susceptibility to adiposity-independent hypertension.
Keywords: Black or African American; Body Mass Index; Chromosomes, Human, Pair 2; Genome, Human; Humans; Hypertension; Lod Score; Obesity

Imputing gene-treatment interactions when the genotype distribution is unknown using case-only and putative placebo analyses--a new method for the Genetics of Hypertension Associated Treatment (GenHAT) study. - Davis, Barry R; Ford, Charles E; Eric Boerwinkle; Arnett, Donna; Eckfeldt, John; Black, Henry (Stat Med, 2004)
There is a sizeable literature on methods for detecting gene-environment interaction in the framework of case-control studies, particularly with reference to the assumption of independence of genotype and exposure. In the context of a clinical trial, wherein gene-drug interactions with regard to outcomes are examined, these methods may be readily applied, as gene and drug are independent by randomization. In an active-controlled trial (experimental treatment vs standard) that has collected genotype information, gene-drug interactions can be estimated. In addition, the effect of the experimental treatment vs placebo can be imputed by using data from a historical placebo-controlled trial (standard vs placebo) if either (a) genotype information is available from the historical trial or (b) assumptions are made about the prevalence of genotype and the odds ratios of genotype and disease in the historical trial using information from other studies. Motivation for these procedures is provided by the Genetics of Hypertension Associated Treatment, a large pharmacogenetics, ancillary study of a hypertension clinical trial, and examples from published hypertension trials will be used to illustrate the methods.
Keywords: Controlled Clinical Trials as Topic; Genotype; Humans; Hypertension; Placebos; United States

Parental history of stroke and myocardial infarction predicts coronary artery calcification: The Coronary Artery Risk Development in Young Adults (CARDIA) study. - Fornage, Myriam; Lopez, David S; Roseman, Jeffrey M; Siscovick, David S; Wong, Nathan D; Eric Boerwinkle (Eur J Cardiovasc Prev Rehabil, 2004)
BACKGROUND: Few studies have examined the relationship between parental history of stroke and myocardial infarction (MI) and subclinical atherosclerosis, especially among young, asymptomatic individuals. This study investigates the association between coronary artery calcification (CAC) and parental history of stroke and MI in African-Americans and Caucasians from the CARDIA study. METHODS: Parental history of stroke and MI was determined by self-administered family history questionnaire at baseline and Year 5 examinations. Presence of coronary calcification was determined by computed tomography on 3041 individuals, age 32 to 47, including 1375 African-Americans and 1666 Caucasians. Analyses were restricted to individuals free of clinically manifest coronary heart disease (CHD) and stroke. RESULTS: Parental history of stroke is associated with a two-fold greater risk of CAC in African-Americans, and this relationship is independent from established CHD risk factors (95% CI=1.14-3.43). There is no relationship between parental history of stroke and CAC status in Caucasians. Parental history of MI is associated with a two-fold greater risk of CAC in Caucasians (95% CI=1.38-2.92). The impact of parental history of MI in African-Americans is lower (OR=1.65; 95% CI=1.01-2.69) and no longer statistically significant after adjusting for known CHD risk factors. CONCLUSIONS: The identification of individuals with a parental history of stroke and MI provides important information for clinicians by which to target primary prevention efforts. Further characterization of familial factors, especially genetic factors, contributing to increased risk of CAC will shed light on the basis of the observed associations.
Keywords: Adolescent; Adult; Black or African American; Calcinosis; Coronary Artery Disease; Fathers; Female; Humans; Male; Mothers; Myocardial Infarction; Prospective Studies; Stroke; White People

Polymorphism of the soluble epoxide hydrolase is associated with coronary artery calcification in African-American subjects: The Coronary Artery Risk Development in Young Adults (CARDIA) study. - Fornage, Myriam; Eric Boerwinkle; Doris, Peter A; Jacobs, David; Liu, Kiang; Wong, Nathan D (Circulation, 2004)
BACKGROUND: Modulation of endogenous epoxide levels by soluble epoxide hydrolase (sEH) in the endothelium represents an important mechanism in the regulation of cardiovascular function. We examined the relationship between a common, functional polymorphism of the human sEH gene and coronary artery calcification (CAC) in young, largely asymptomatic African-American and non-Hispanic white subjects. METHODS AND RESULTS: Multiple logistic regression and Tobit regression models were used to assess the relationship between the sEH Arg287Gln polymorphism and presence and quantity of CAC. Models adjusting for race (except in race-specific analyses), age, sex, smoking, body mass index, systolic blood pressure, LDL cholesterol, and HDL cholesterol were estimated. Allele and genotype frequency distributions were not significantly different between the 2 ethnic groups (P=0.22; P=0.17, respectively). The Arg287Gln polymorphism of the sEH gene was a significant predictor of CAC status in African-American participants, either alone or after adjusting for other risk factors. African-American subjects with at least 1 copy of the Gln287 allele had a 2-fold greater risk of having CAC compared with those not carrying this allele (95% CI, 1.1 to 2.9; P=0.02). There was no relationship between Arg287Gln polymorphism and the probability of having CAC in white participants (OR, 0.8; 95% CI, 0.5 to 1.3; P=0.49). Inferences from multivariable Tobit regression were similar to those obtained in the logistic regression models, indicating that the Arg287Gln polymorphism was a significant independent predictor of both presence and quantity of CAC in African-American but not white subjects. CONCLUSIONS: These data suggest an intriguing and possibly novel role for sEH in the pathogenesis of atherosclerosis, which deserves additional investigation.
Keywords: Adolescent; Adult; Black or African American; Calcinosis; Coronary Artery Disease; Coronary Vessels; Epoxide Hydrolases; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Humans; Male; Polymorphism, Genetic; Risk Factors

Relationship between low-density lipoprotein subclasses and asymptomatic atherosclerosis in subjects from the Atherosclerosis Risk in Communities (ARIC) Study. - Hallman, D Michael; Brown, Spencer A; Ballantyne, Christie M; Sharrett, A Richey; Eric Boerwinkle (Biomarkers, 2004)
Low-density lipoprotein (LDL) particle size has been associated with coronary heart disease, but an association between LDL size and preclinical atherosclerosis is less well established. Using gradient gel electrophoresis, large (A), intermediate (I) and small (B) LDL size subclasses were determined in 198 cases with asymptomatic carotid artery atherosclerosis (determined by B-mode ultrasonography) and 318 controls from the Atherosclerosis Risk in Communities (ARIC) Study. In Caucasians, a smaller LDL size was more prevalent in men and associated with a higher body mass index, hypertension prevalence, and plasma total- and LDL-cholesterol and triglycerides, but lower HDL-cholesterol. In African-Americans, a smaller LDL size was associated with higher triglycerides and lower HDL-cholesterol and hypertension prevalence. In Caucasians, Subclass B prevalence was 29.1% among cases and 14.8% among controls. The odds ratio (95% confidence interval) for Subclass B rather than Subclass A in Caucasian cases was 2.94 (1.67-5.17); the association remained significant after controlling for age, body mass index, smoking, and either plasma triglycerides or HDL-cholesterol. In African-Americans, however, there was no significant association between LDL subclass and case status. A predominance of smaller LDL particles is associated with asymptomatic carotid artery atherosclerosis in Caucasians, through mechanisms that remain to be elucidated.
Keywords: Arteriosclerosis; Carotid Arteries; Case-Control Studies; Cholesterol, HDL; Female; Humans; Hypertension; Lipoproteins, LDL; Male; Middle Aged; Odds Ratio; Particle Size; Racial Groups; Triglycerides; Tunica Intima

Comparison of strategies for selecting single nucleotide polymorphisms for case/control association studies. - Huang, Qiqing; Fu, Yun-Xin; Eric Boerwinkle (Hum Genet, 2003)
It is widely believed that a subset of single nucleotide polymorphisms (SNPs) is able to capture the majority of the information for genotype-phenotype association studies that is contained in the complete compliment of genetic variations. The question remains, how does one select that particular subset of SNPs in order to maximize the power of detecting a significant association? In this study, we have used a simulation approach to compare three competing methods of site selection: random selection, selection based on pair-wise linkage disequilibrium, and selection based on maximizing haplotype diversity. The results indicate that site selection based on maximizing haplotype diversity is preferred over random selection and selection based on pair-wise linkage disequilibrium. The results also indicate that it is more prudent to increase the sample size to improve a study's power than to continuously increase the number of SNPs. These results have direct implications for designing gene-based and genome-wide association studies.
Keywords: Case-Control Studies; Haplotypes; Humans; Linkage Disequilibrium; Patient Selection; Phenotype; Polymorphism, Single Nucleotide; Regression Analysis; Sample Size

Evaluating the context-dependent effect of family history of stroke in a genome scan for hypertension. - Morrison, Alanna C; Brown, Andrew; Kardia, Sharon L R; Turner, Stephen T; Eric Boerwinkle (Stroke, 2003)
BACKGROUND AND PURPOSE: Hypertension is an important risk factor for stroke, and the 2 diseases may share susceptibility genes in common. We sought to identify genomic regions influencing susceptibility to both hypertension and stroke. SUBJECTS AND METHODS: Genome-wide linkage scans were performed in samples of 338 white and 265 black hypertensive sibships recruited by the Genetic Epidemiology Network of Arteriopathy Study of the NHLBI Family Blood Pressure Program (FBPP). The hypertensive sibships were stratified by positive (+FH) or negative (-FH) family history of stroke. Genome-wide scans were repeated in each stratum, and the results were compared within each ethnic group by a regression-based analysis of heterogeneity. RESULTS: In whites, the best evidence for linkage was found on chromosome 16 in the unstratified sample of hypertensive sibpairs (logarithm of odds [LOD]=1.85 at 71 cM). In blacks, the best evidence for linkage was found on chromosome 2 in the unstratified sample of hypertensive sibpairs (LOD=1.95 at 230 cM). Additional evidence for linkage (LOD >or=1.5) was observed among white hypertensive sibpairs with a -FH on chromosome 13 and among black hypertensive sibpairs with a +FH of stroke on chromosome 19. CONCLUSIONS: Significant evidence for linkage heterogeneity among hypertensive sibpairs stratified by family history of stroke suggests the presence of genes influencing susceptibility to both hypertension and stroke on chromosomes 13 (whites) and 19 (blacks). Although no significant evidence of heterogeneity was observed on chromosome 16 in whites and chromosome 2 in blacks, these chromosomes do provide evidence of linkage to hypertension.
Keywords: Adult; Aged; Black People; Body Mass Index; Chromosomes, Human, Pair 13; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 2; Ethnicity; Family Health; Female; Genes; Genetic Heterogeneity; Genetic Linkage; Genetic Predisposition to Disease; Genetic Testing; Genome, Human; Humans; Hypercholesterolemia; Hypertension; Male; Middle Aged; Minnesota; Mississippi; Risk Factors; Sample Size; Siblings; Stroke; Texas; White People

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part I. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document focuses on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Acute Disease; Arteriosclerosis; Consensus; Coronary Disease; Death, Sudden, Cardiac; Disease Progression; Humans; Models, Cardiovascular; Risk Assessment; Syndrome; Terminology as Topic

From vulnerable plaque to vulnerable patient: a call for new definitions and risk assessment strategies: Part II. - Naghavi, Morteza; Libby, Peter; Falk, Erling; Casscells, S Ward; Litovsky, Silvio; Rumberger, John; Badimon, Juan Jose; Stefanadis, Christodoulos; Moreno, Pedro; Pasterkamp, Gerard; Fayad, Zahi; Stone, Peter H; et al. (Circulation, 2003)
Atherosclerotic cardiovascular disease results in >19 million deaths annually, and coronary heart disease accounts for the majority of this toll. Despite major advances in treatment of coronary heart disease patients, a large number of victims of the disease who are apparently healthy die suddenly without prior symptoms. Available screening and diagnostic methods are insufficient to identify the victims before the event occurs. The recognition of the role of the vulnerable plaque has opened new avenues of opportunity in the field of cardiovascular medicine. This consensus document concludes the following. (1) Rupture-prone plaques are not the only vulnerable plaques. All types of atherosclerotic plaques with high likelihood of thrombotic complications and rapid progression should be considered as vulnerable plaques. We propose a classification for clinical as well as pathological evaluation of vulnerable plaques. (2) Vulnerable plaques are not the only culprit factors for the development of acute coronary syndromes, myocardial infarction, and sudden cardiac death. Vulnerable blood (prone to thrombosis) and vulnerable myocardium (prone to fatal arrhythmia) play an important role in the outcome. Therefore, the term "vulnerable patient" may be more appropriate and is proposed now for the identification of subjects with high likelihood of developing cardiac events in the near future. (3) A quantitative method for cumulative risk assessment of vulnerable patients needs to be developed that may include variables based on plaque, blood, and myocardial vulnerability. In Part I of this consensus document, we cover the new definition of vulnerable plaque and its relationship with vulnerable patients. Part II of this consensus document will focus on vulnerable blood and vulnerable myocardium and provide an outline of overall risk assessment of vulnerable patients. Parts I and II are meant to provide a general consensus and overviews the new field of vulnerable patient. Recently developed assays (eg, C-reactive protein), imaging techniques (eg, CT and MRI), noninvasive electrophysiological tests (for vulnerable myocardium), and emerging catheters (to localize and characterize vulnerable plaque) in combination with future genomic and proteomic techniques will guide us in the search for vulnerable patients. It will also lead to the development and deployment of new therapies and ultimately to reduce the incidence of acute coronary syndromes and sudden cardiac death. We encourage healthcare policy makers to promote translational research for screening and treatment of vulnerable patients.
Keywords: Animals; Biomarkers; Coronary Artery Disease; Death, Sudden, Cardiac; Disease Susceptibility; Female; Humans; Male; Mass Screening; Myocardial Infarction; Myocardium; Risk Assessment; Severity of Illness Index; Swine; Thrombophilia

Gene expression profiling and functional proteomic analysis reveal perturbed kinase-mediated signaling in genetic stroke susceptibility. - Fornage, Myriam; Swank, Michael W; Eric Boerwinkle; Doris, Peter A (Physiol Genomics, 2003)
The stroke-prone spontaneously hypertensive rat (SHRSP) is a model of heritable hypertension-associated cerebrovascular injury. This study sought to compare SHRSP to the stroke-resistant SHR strain to identify genes and protein pathways whose expression and/or function was significantly altered between the strains prior to the onset of stroke. Cerebral cortex gene expression profiles from male SHRSPs and matched SHRs were examined by Affymetrix microarray analysis. mRNAs encoding the brain-derived neurotrophic factor receptor (TrkB) and multiple kinases of the MAPK/AKT signaling pathways, including JNK2, AKT2, and PI3K, were differentially expressed between SHRSP and SHR. Because these data suggest altered function in pathways involving MAP and AKT kinase activity, we performed Western blot using phosphorylation state-specific antibodies to characterize activity of MAP kinase and PI3K/AKT pathways. Changes in the levels of the phosphorylated forms of these kinases paralleled the changes in transcript levels observed between the strains. Two-dimensional gel electrophoresis and peptide fragment mass fingerprinting were used to identify altered protein substrates of these kinases. Protein profiling of kinase substrates further supported the notion of perturbed kinase-mediated signaling in SHRSP and identified adenylyl cyclase associated protein 2, TOAD-64, propionyl CoA carboxylase, APG-1, and valosin-containing protein as kinase targets whose phosphorylation state is altered between these strains. Altered gene and protein expression patterns in SHRSP are consistent with increased vulnerability of this strain to cerebrovascular injury.
Keywords: Animals; Blotting, Western; Cerebral Cortex; Enzyme Activation; Gene Expression Profiling; Genetic Predisposition to Disease; Male; MAP Kinase Signaling System; Mitogen-Activated Protein Kinases; Oligonucleotide Array Sequence Analysis; Phosphorylation; Protein Kinases; Proteomics; Rats; Rats, Inbred SHR; Receptor, trkB; Stroke

Genetic linkage and imprinting effects on body mass index in children and young adults. - Gorlova, Olga Y; Amos, Christopher I; Wang, Nancy W; Shete, Sanjay; Turner, Stephen T; Eric Boerwinkle (Eur J Hum Genet, 2003)
Body mass index (BMI) is used as a measure of fatness. Here we performed a genome-wide scan for genes related to BMI, while allowing for the possible effects of imprinting. We applied a sib pair linkage analysis to a sample of primarily children and young adults by using the Haseman-Elston method, which we modified to model the separate effects of paternally and maternally derived genetic factors. After stratification of sib pairs according to age, a number of regions showing linkage with BMI were identified. Most linkage and imprinting effects were found in children 5-11 years of age. Strongest evidences for linkage in children were found on chromosome 20 at 20p11.2-pter near the marker D20S851 (LOD(Total)=4.08, P=0.000046) and near the marker D20S482 (LOD(Total) =3.55, P=0.00016), and Chromosome 16 at 16p13 near the marker ATA41E04 (LOD(Total) =3.12, P=0.00025), and those loci did not show significant evidence for imprinting. Six regions showing evidence of imprinting were 3p23-p24 (paternal expression), 4q31.1-q32 (maternal expression), 10p14-q11 (paternal expression), and 12p12-pter (paternal expression) in children, and 4q31-qter (paternal expression) and 8p (paternal expression) in adults.
Keywords: Adolescent; Adult; Age Factors; Body Mass Index; Child; Child, Preschool; Chromosomes, Human, Pair 16; Chromosomes, Human, Pair 20; Genetic Linkage; Genomic Imprinting; Humans; Models, Genetic

Haplotype block linkage disequilibrium mapping. - Xiong, Momiao; Zhao, Jinying; Eric Boerwinkle (Front Biosci, 2003)
Linkage disequilibrium (LD) mapping is emerging as a powerful alternative approach to identifying genes for complex disease. However, the feasibility and success of LD mapping depend largely on the extent and pattern of LD. Erratic pattern of pair-wise LD seriously compromises LD mapping. Recently discovered haplotype block structure dramatically alleviates the irregular pattern of LD and holds the promise for mapping complex disease genes. To facilitate applications of the haplotype block LD mapping, in this report we conduct theoretical analysis for haplotype block LD mapping. We present an overall LD measure of the haplotype to quantify the LD level of the haplotype block, between the haplotype blocks, and between the haplotype block and the marker locus. Most theoretical and empirical studies of the extent of LD and evaluation of the power of LD mapping have focused on pair-wise LD and single marker LD mapping. There is a lack of systematic and integrative analysis for the haplotype block LD mapping. In this report, we develop population genetic models of the haplotype blocks and analytic tools for calculation of noncentrality parameter of the statistic for the haplotype block LD mapping. We evaluate the impact of the population parameters and disease models on the power of the haplotype block LD mapping in the hope to improve its study design. We compare the powers of the single marker LD and haplotype block LD mapping. Haplotype block structure is an important discovery. Our preliminary results of theoretic analysis further demonstrate that the haplotype block LD analysis is a breakthrough in LD mapping and is a promising tool for genome-wide association studies.
Keywords: Chromosome Mapping; Genetic Markers; Genetics, Population; Haplotypes; Humans; Linkage Disequilibrium; Models, Genetic; Models, Statistical

Interaction between soluble thrombomodulin and intercellular adhesion molecule-1 in predicting risk of coronary heart disease. - Wu, Kenneth K; Aleksic, Nena; Ballantyne, Christie M; Ahn, Chul; Juneja, Harinder; Eric Boerwinkle (Circulation, 2003)
BACKGROUND: Results from previous ARIC (Atherosclerosis Risk In Communities) analyses indicate that soluble intercellular adhesive molecule-1 (sICAM) and soluble thrombomodulin (sTM) levels are associated with risk of coronary heart disease (CHD) in an opposite direction. A high sICAM level increases the risk of CHD, whereas a high level of sTM has a lower risk of CHD. It was unclear whether there was an interaction between sTM and sICAM. METHODS AND RESULTS: Using a nested case-cohort design, we measured sTM and sICAM in 317 incident CHD cases and 726 non-cases from the ARIC participants. Consistent with our previous reports, sICAM values in the upper versus the lower tertile increased the risk of CHD event by approximately 2-fold (95% confidence interval [CI], 1.46 to 2.87) whereas sTM values in the lower versus the upper tertile increased CHD risk by approximately 4-fold (95% CI, 2.80 to 5.74). Interaction between these 2 parameters was determined by weighted Cox proportional hazard regression. A significant interaction (P=0.038) was noted. Combinatorial analysis shows a significant increase in CHD risk ratio (RR) (4.66, 95% CI, 1.89 to 11.46) of the lower sTM/upper sICAM group versus the upper sTM/lower sICAM group. Individuals whose sTM values were in the upper tertile had a RR below 1, even when sICAM were in the upper tertile. The RR of lower tertile sTM was increased by sICAM in a tertile-dependent manner. CONCLUSIONS: Weighted Cox proportional hazard analysis shows a significant interaction between sTM and sICAM in predicting risk of CHD event. Combinatorial analysis reveals that an upper tertile sICAM had a significant increase in the risk of a CHD event only when sTM was in the lower tertile.
Keywords: Case-Control Studies; Coronary Disease; Female; Humans; Intercellular Adhesion Molecule-1; Male; Middle Aged; Proportional Hazards Models; Risk Factors; Thrombomodulin

Investigating single nucleotide polymorphism (SNP) density in the human genome and its implications for molecular evolution. - Zhao, Zhongming; Fu, Yun-Xin; Hewett-Emmett, David; Eric Boerwinkle (Gene, 2003)
We investigated the single nucleotide polymorphism (SNP) density across the human genome and in different genic categories using two SNP databases: Celera's CgsSNP, which includes SNPs identified by comparing genomic sequences, and Celera's RefSNP, which includes SNPs from a variety of sources and is biased toward disease-associated genes. Based on CgsSNP, the average numbers of SNPs per 10 kb was 8.33, 8.44, and 8.09 in the human genome, in intergenic regions, and in genic regions, respectively. In genic regions, the SNP density in intronic, exonic and adjoining untranslated regions was 8.21, 5.28, and 7.51 SNPs per 10 kb, respectively. The pattern of SNP density based on RefSNP was different from that based on CgsSNP, emphasizing its utility for genotype-phenotype association studies but not for most population genetic studies. The number of SNPs per chromosome was correlated with chromosome length, but the density of SNPs estimated by CgsSNP was not significantly correlated with the GC content of the chromosome. Based on CgsSNP, the ratio of nonsense to missense mutations (0.027), the ratio of missense to silent mutations (1.15), and the ratio of non-synonymous to synonymous mutations (1.18) was less than half of that expected in a human protein coding sequence under the neutral mutation theory, reflecting a role for natural selection, especially purifying selection.
Keywords: Databases, Nucleic Acid; DNA, Intergenic; Evolution, Molecular; Exons; Gene Frequency; Genome, Human; Humans; Introns; Mutation; Polymorphism, Single Nucleotide

Lack of genetic linkage evidence for a trans-acting factor having a large effect on plasma lipoprotein[a] levels in African Americans. - Barkley, Ruth Ann; Brown, Andrew C; Hanis, Craig L; Kardia, Sharon L; Turner, Stephen T; Eric Boerwinkle (J Lipid Res, 2003)
The distribution of plasma lipoprotein[a] (Lp[a]) concentrations, a risk factor for cardiovascular disease, varies greatly among racial groups, with African Americans having values that are shifted toward higher levels than those of whites. The underlying cause of this heterogeneity is unknown, but a role for "trans-acting" factors has been hypothesized. This study used genetic linkage analysis to localize genetic factors influencing Lp[a] levels in African Americans that were absent in other populations; linkage results were analyzed separately in non-Hispanic whites, Hispanic whites, and African Americans. As expected, all three samples showed highly significant linkage at the approximate location of the lysophosphatidic acid locus. The white populations also independently had regions of significant linkage on chromosome 19 (LOD 3.80) and suggestive linkage on chromosomes 12 (LOD 1.60), 14 (LOD 2.56), and 19 (LOD 2.52). No linkage evidence was found to support the hypothesis of another single gene with large effects specifically segregating in African Americans that may account for their elevated Lp[a] levels.
Keywords: Adult; Aged; Black or African American; Black People; Chromosomes, Human, Pair 12; Chromosomes, Human, Pair 14; Chromosomes, Human, Pair 19; Genetic Linkage; Humans; Lipoprotein(a); Lod Score; Lysophospholipids; Male; Middle Aged; Transcriptional Activation; White People

ADD1 460W allele associated with cardiovascular disease in hypertensive individuals. - Morrison, Alanna C; Bray, Molly S; Folsom, Aaron R; Eric Boerwinkle (Hypertension, 2002)
High blood pressure is a predictor of cardiovascular disease. Hence, genes contributing to essential hypertension may play a role in the etiology of cardiovascular disease. For this reason, we examined the association between the alpha-adducin (ADD1) G460W and G-protein beta3 subunit (GNB3) 825C>T polymorphisms and the prevalence of peripheral arterial disease (PAD) and incidence of coronary heart disease (CHD) in non-Hispanic whites from the Atherosclerosis Risk in Communities (ARIC) Study. PAD prevalence was defined by an ankle-brachial index, ie, the ratio of ankle systolic blood pressure to brachial artery systolic blood pressure, of </=0.90 for men and </=0.85 for women. CHD incidence was determined by following the ARIC cohort for a median of 5.3 years for potential coronary events. Stratified random samples of the ARIC cohort (n=703 and n=684) were used, respectively, as the comparison groups for the PAD (n=144) and incident CHD (n=408) cases. The GNB3 825T allele and the ADD1 460W allele were not significantly associated with prevalence of PAD or incidence of CHD. However, a test of the interaction between hypertension status and the ADD1 G460W polymorphism indicated that further evaluation of the ADD1 polymorphism in only hypertensive individuals was warranted. The ADD1 460W allele was significantly associated with PAD (odds ratio [OR]: 2.61, 95% CI, 1.27-5.37, P=0.01) and CHD (hazard rate ratio [HRR]: 2.30, 95% CI, 1.20-4.42, P=0.01) in hypertensive individuals after adjustment for multiple cardiovascular disease risk factors. An interaction with hypertension in the association between the ADD1 G460W polymorphism and cardiovascular disease merits further testing in additional populations.
Keywords: Alleles; Arterial Occlusive Diseases; Calmodulin-Binding Proteins; Cardiovascular Diseases; Case-Control Studies; Coronary Disease; Female; Gene Frequency; Genetic Predisposition to Disease; Genotype; Heterotrimeric GTP-Binding Proteins; Humans; Hypertension; Incidence; Male; Middle Aged; Polymorphism, Single Nucleotide; Prevalence; White People

Beta 2 adrenergic receptor 5' haplotypes influence promoter activity. - Johnatty, Sharon E; Abdellatif, Maha; Shimmin, Lawrence; Clark, Richard B; Eric Boerwinkle (Br J Pharmacol, 2002)
1. Transcriptional control of the human beta(2) adrenergic receptor gene (ADRB2) predominantly resides within a 549 base pair region immediately 5' to the start of translation. Within this region, four naturally occurring polymorphisms, -468 C-->G, -367 T-->C, -47 T-->C, and -20 T-->C, have been identified. 2. To determine the individual site and haplotype effects of these polymorphisms, we generated 16 luciferase-based mutant constructs which were transiently transfected into HEK293 cells, and measured ADRB2 promoter-driven luciferase activity. 3. Two of the 16 mutant constructs, GCCT (-468G, -367C, -47C, -20T) and CTCT, showed a highly significant 3 fold decrease in luciferase induction relative to the reference CTTT. These haplotype effects could not be accounted for by the separate and additive effects of each site. 4. These findings indicate that promoter polymorphisms interact to significantly alter beta(2) adrenergic receptor expression, and should be examined further for their association with disease-related phenotypes.
Keywords: Cell Line; Haplotypes; Humans; Luciferases; Mutation; Polymorphism, Genetic; Promoter Regions, Genetic; Receptors, Adrenergic, beta-2; Statistics, Nonparametric; Transfection

Factor XIIIA Val34Leu polymorphism does not predict risk of coronary heart disease: The Atherosclerosis Risk in Communities (ARIC) Study. - Aleksic, Nena; Ahn, Chul; Wang, Yao-Wei; Juneja, Harinder; Folsom, Aaron R; Eric Boerwinkle; Wu, Kenneth K (Arterioscler Thromb Vasc Biol, 2002)
Factor XIII catalyzes the cross-linking of fibrin. Cross-sectional studies have suggested that a common polymorphism site at residue 34 of the A subunit of factor XIII (FXIIIA) with a substitution of Leu for Val (FXIIIA Val34Leu) was associated with reduced coronary heart disease (CHD). This association has not been examined in prospective studies. Healthy subjects (n=15 792) were recruited from 4 US communities into the Atherosclerosis Risk in Communities (ARIC) study from 1987 to 1989. They were followed, and incident CHD events were identified and verified. For the present study, we included 423 patients with CHD as cases and 479 noncases. FXIIIA Val34Leu polymorphism was determined by the single-strand conformational polymorphism method. There were no significant differences in the genotype frequencies between cases and noncases. The genotypes showed little association with known CHD risk factors. A weighted proportional hazards regression analysis adjusting for other risk factors confirmed no association of the genotypes with risk of CHD. This prospective study did not provide evidence of a reduced CHD risk for the FXIIIA 34Leu allele.
Keywords: Case-Control Studies; Coronary Artery Disease; Factor XIIIa; Female; Gene Frequency; Genotype; Humans; Incidence; Male; Maryland; Middle Aged; Minnesota; Mississippi; North Carolina; Polymorphism, Single-Stranded Conformational; Risk Factors

Generalized T2 test for genome association studies. - Xiong, Momiao; Zhao, Jinying; Eric Boerwinkle (Am J Hum Genet, 2002)
Recent progress in the development of single-nucleotide polymorphism (SNP) maps within genes and across the genome provides a valuable tool for fine-mapping and has led to the suggestion of genomewide association studies to search for susceptibility loci for complex traits. Test statistics for genome association studies that consider a single marker at a time, ignoring the linkage disequilibrium between markers, are inefficient. In this study, we present a generalized T2 statistic for association studies of complex traits, which can utilize multiple SNP markers simultaneously and considers the effects of multiple disease-susceptibility loci. This generalized T2 statistic is a corollary to that originally developed for multivariate analysis and has a close relationship to discriminant analysis and common measure of genetic distance. We evaluate the power of the generalized T2 statistic and show that power to be greater than or equal to those of the traditional chi2 test of association and a similar haplotype-test statistic. Finally, examples are given to evaluate the performance of the proposed T2 statistic for association studies using simulated and real data.
Keywords: Algorithms; Chi-Square Distribution; Chromosome Mapping; Computer Simulation; Genetic Diseases, Inborn; Genetic Predisposition to Disease; Genome, Human; Haplotypes; Humans; Indians, North American; Models, Genetic; Oklahoma; Penetrance; Polymorphism, Single Nucleotide

LPL polymorphism predicts stroke risk in men. - Morrison, Alanna C; Ballantyne, Christie M; Bray, Molly; Chambless, Lloyd E; Sharrett, A Richey; Eric Boerwinkle (Genet Epidemiol, 2002)
Variation in lipid levels has been associated with atherosclerotic vascular disease, including stroke. Genes contributing to interindividual variation in lipid levels may play a role in the etiology of stroke, either through their effects on lipid synthesis and metabolism or through separate pathways. For this reason, we sought to examine the association between polymorphisms in the lipoprotein lipase (LPL) and apolipoprotein E (APOE) genes and subclinical and clinical stroke in the Atherosclerosis Risk in Communities (ARIC) Study. Subclinical stroke was determined by cerebral magnetic resonance imaging (MRI). Subclinical cerebral infarct cases (n = 197) were compared to a stratified random sample identified from individuals participating in the MRI examination (n = 200). Incidence of clinical ischemic stroke was determined by following the ARIC cohort for an average of 7.5 years for potential cerebrovascular events; 218 validated clinical ischemic strokes were identified. A stratified random sample of the ARIC cohort (CRS, n = 964) was used as the comparison group for clinical cases. The LPL S291-carrying genotypes and APOE epsilon2- and epsilon4-carrying genotypes were not significantly associated with subclinical or clinical stroke. The LPL X447-containing genotypes were significantly associated with subclinical (odds ratio [OR], 4.32; 95% confidence interval [CI], 1.23-15.15; P = 0.020) and clinical stroke (hazard rate ratio [HRR], 2.57; 95% CI, 1.24-5.34; P = 0.01) in men, both by themselves and after adjustment for multiple stroke risk factors. The LPL S447X polymorphism is significantly associated with subclinical cerebral infarction and incident clinical ischemic stroke in men from a middle-aged American population. This association does not appear to be mediated by triglyceride, high-density lipoprotein (HDL)- and low-density lipoprotein (LDL)-cholesterol levels, or additional stroke risk factors.
Keywords: Apolipoproteins E; Genetic Predisposition to Disease; Genotype; Humans; Lipoprotein Lipase; Logistic Models; Magnetic Resonance Imaging; Male; Middle Aged; Polymorphism, Genetic; Predictive Value of Tests; Proportional Hazards Models; Prospective Studies; Risk Factors; Stroke

Neighboring-nucleotide effects on single nucleotide polymorphisms: a study of 2.6 million polymorphisms across the human genome. - Zhao, Zhongming; Eric Boerwinkle (Genome Res, 2002)
We investigated substitution patterns and neighboring-nucleotide effects for 2,576,903 single nucleotide polymorphisms (SNPs) publicly available through the National Center for Biotechnology Information (NCBI). The proportions of substitutions were A/G, 32.77%; C/T, 32.81%; A/C, 8.98%; G/T, 9.06%; A/T, 7.46%; and C/G, 8.92%. The two nucleotides immediately neighboring the variable site showed major deviation from genome-wide and chromosome-specific expectations, although lesser biases extended as far as 200 bp. On the 5' side, the biases for A, C, G, and T were 1.43%, 4.91%, -1.70%, and -4.62%, respectively. These biases were -4.44%, -1.59%, 5.05%, and 0.99%, respectively, on the 3' side. The neighboring-nucleotide patterns for transitions were dominated by the hypermutability effects of CpG dinucleotides. Transitions were more common than transversions, and the probability of a transversion increased with increasing A + T content at the two adjacent sites. Neighboring-nucleotide biases were not consistent among chromosomes, with Chromosomes 19 and 22 standing out as different from the others. These data provide genome-wide information about the effects of neighboring nucleotides on mutational and evolutionary processes giving rise to contemporary patterns of nucleotide occurrence surrounding SNPs.
Keywords: Base Composition; Chromosomes, Human, Pair 19; Chromosomes, Human, Pair 22; Genome, Human; Humans; Nucleotides; Polymorphism, Single Nucleotide; Sequence Analysis, DNA

Polymorphism in soluble epoxide hydrolase and blood pressure in spontaneously hypertensive rats. - Fornage, Myriam; Hinojos, Cruz A; Nurowska, Barbara W; Eric Boerwinkle; Hammock, Bruce D; Morisseau, Christophe H P; Doris, Peter A (Hypertension, 2002)
We measured soluble epoxide hydrolase (sEH) renal gene expression in prehypertensive (4 to 5 weeks old) spontaneously hypertensive rats of the Heidelberg SP substrain (SHR [Heid]) and when blood pressure levels entered the hypertensive plateau (17 to 18 weeks old) and compared expression with matched Wistar-Kyoto (WKY [Heid]) rats. Less expression of the gene encoding sEH (EPHX2) was observed in SHR (Heid) than in WKY (Heid). Analysis of sEH protein abundance showed a similar difference. However, no correlation between sEH abundance and blood pressure was observed in the F(2) progeny of a parental strain cross. Measurement of protein abundance in SHR and WKY obtained from Charles River confirmed a recent report that abundance of sEH was greater in SHR (CRiv) than WKY (CRiv) strains. Polymorphisms were detected in EPHX2. Resequencing revealed that 2 alleles of EPHX2 exist in these 4 rat strains, differing by 4 single nucleotide polymorphisms, of which 3 produce nonsynonymous amino acid substitutions. The ancestral allele was shared by SHR (Heid) and WKY (CRiv), and the variant allele was shared by WKY (Heid) and SHR (CRiv). Activity of sEH was greater in animals carrying the variant allele. However, inheritance of this allele was not correlated with blood pressure in the F(2) progeny of a cross between SHR (Heid) and WKY (Heid). These data indicate that sequence variation determining functional alterations in EPHX2 is not likely to contribute to blood pressure levels in SHR.
Keywords: Animals; Blood Pressure; Epoxide Hydrolases; Hypertension; Kidney; Male; Polymorphism, Single Nucleotide; Rats; Rats, Inbred SHR; Rats, Inbred WKY; RNA, Messenger